Does the Inion OTPSTM absorbable plating system induce higher foreign-body reaction than titanium implants? An experimental randomized comparative study in rabbits - Chalidis, B.; Kitridis, D.; Savvidis, P.; Papalois, A.; Givissis, P. (Biomedical Materials (Bristol), 2020)
Hardware removal after complete fracture healing is a laborious and traumatic procedure that bears the risks of refracture, infection, and soft tissue damage. Absorbable materials for fracture fixation have the advantage of eliminating the need for removal; however, they may stimulate a considerable inflammatory response. For that reason, we compared in a prospective randomized experimental animal model study the incidence of foreign-body reactions between Inion OTPSTM absorbable plate implants, consisting of carbon trimethylene, L-polylactic acid, and D, L-polylactic acid, and conventional titanium plates. Seventy rabbits were equally divided into two groups. Titanium (Group A) or absorbable (Group B) plates and screws were implanted in the femoral shaft of the rabbits. Wound reaction and laboratory tests including white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) values were measured and compared at different time points. Radiographs and histological analysis of tissue samples from all animals were also used to identify potential foreign-body reactions. WBC showed normal values in both groups. In Group A, ESR levels were higher at all time points but CRP values were normalized at 3 weeks postoperatively. In Group B, ESR and CRP levels reached a peak at 3 weeks and were above normal values throughout the whole experiment (p < 0.001). Radiologic examination revealed periosteal thickening and surrounding sclerosis in 23 out of 35 animals of Group B (66%). All Group A animals had normal radiographic findings. Histopathology showed a typical non-specific foreign-body reaction in all animals in Group B (100%) but none in Group A. However, only four of them (11.8%) developed non-infected wound complications and showed significantly elevated CRP and ESR values (p = 0.054). Although Inion OTPSTM Biodegradable Plating System stimulates a foreign-body reaction, only a small but not negligible percentage of almost 12% may lead to wound problems. However, this difference compared to titanium plates was of borderline not statistically significant. Future studies should focus on the development of absorbable implants with improved biocompatibility aiming to further decrease the potential of foreign-body reaction and eliminate the need for additional reoperative procedures.
Keywords: animal experiment; animal model; animal tissue; article; biocompatibility; biodegradable implant; comparative study; controlled study; erythrocyte sedimentation rate; femoral shaft; foreign body reaction; histology; histopathology; human; incidence; laboratory test; Leporidae; leukocyte count; nonhuman; normal value; periosteum; prospective study; protein expression; radiodiagnosis; sclerosis; wound complication; X ray film; C reactive protein; carbon; endogenous compound; polylactic acid; titanium

Clinical Issues-November 2020 - Seeman, K. (AORN journal, 2020)
Using adhesive tape for patient positioning Key words: adhesive tape, surgical tape, patient positioning, pressure injury, contamination. Border sterility of open sterile wrappers Key words: wrapped sterile item, unsterile border, wrapper flap, contaminated, aseptic technique. Cost per minute of OR time Key words: cost comparison, direct costs, cost savings, perioperative efficiency, product evaluation. Packages containing an incorrect number of suture needles Key words: multipack, retained surgical item (RSI), counting, needle, package.
Keywords: adult; article; contamination; cost control; human; injury; patient positioning; surgical tape; suture needle

Abdominal skin inflammation as an initial symptom of a perforating gastric foreign body: A case report - Zhang, L.; Liu, L.; Shao, J.; Sun, F.; Zhao, L. (Medicine, 2020)
RATIONALE: Foreign bodies are frequently ingested, but only approximately 1% of them cause perforation. Perforations in the lesser curvature of the stomach are exceedingly rare. Here, we report a case of gastric perforation in the lesser curvature caused by a foreign body. The patient presented to the clinic complaining of abdominal skin swelling and reddening with upper abdominal discomfort as the initial symptoms. PATIENT CONCERNS: An 83-year-old female presented with a mass in the middle of the epigastrium for 10 days. Physical examination found an apparent local tenderness and inflammatory mass in the upper abdominal wall. Her body temperature was normal (37.5°C) and the white blood cell count was elevated (8.12 × 10/L [reference value 3.5-9.5 × 10/L]). DIAGNOSES: The ultrasound examination of the abdomen revealed a 4 cm strip-like hyperechoic object entangled in the muscles of the abdominal wall. The computed tomography scan revealed a thin strip of bone-like hyperdense shadow. Intraoperative findings showed a sharp fishbone protruding from the lesser curvature of the stomach into the abdominal cavity, part of which remained in the gastric cavity. The postoperative pathological report revealed chronic suppurative inflammation with abscess and sinus canal formation. INTERVENTIONS & OUTCOMES: The patient underwent a gastric foreign body removal with partial gastrectomy. Anti-inflammatory treatment post-surgery rapidly relieved the patient's symptoms of discomfort in the upper abdomen. At the 1-month follow-up, the patient showed no discomfort in the upper abdomen and the inflammatory mass was no longer present. LESSONS: A foreign body had penetrated through the lesser curvature of the stomach, an area with a flat gastric wall, which occurs infrequently. In such cases, computed tomography is the gold standard for diagnosis of foreign bodies in the digestive tract. Ultrasound can also be used as a supplemental diagnostic technique. It is recommended that people who wear dentures should exercise caution while eating, especially when the food contains bones.
Keywords: abdominal wall; aftercare; bone; case report; diagnostic imaging; eating; echography; female; foreign body; human; inflammation; microbiology; pathology; procedures; sea food; skin; spontaneous perforation; stomach; treatment outcome; very elderly; x-ray computed tomography

8. Modifiable polymer promotes a pro-osteogenic, M2-like macrophage phenotype and osteoblastic differentiation of progenitor cells - Bartolacci, J.; Shridhar, A.; Badylak, S.F. (Spine Journal, 2020)
BACKGROUND CONTEXT: Poly-ether-ether-ketone (PEEK) has been the most commonly used biomaterial for spinal fusion for many years, primarily because it meets the necessary mechanical requirements to support the pressures to which the spinal column is subjected. However, the biologic response to PEEK has serious limitations including a persistent foreign body response, very modest osseointegration which can result in micromotion, pain, or worse, delamination requiring surgical reintervention. Recent advances in our understanding of immunobiology show that PEEK elicits a proinflammatory phenotype among cells of the innate immune system, including macrophages. Numerous studies have shown that macrophage phenotype can be predictive of clinical outcome. The host immune response to biomaterials used in spine surgery has been largely ignored in deference to mechanical and biomaterial properties such as peak load bearing, porosity and surface characteristics. Pro-inflammatory (M1-like) macrophages have been shown to release several mediators of cell behavior such as IL-6, IL-1b, and TNF-a, that are osteoclastogenic, while pro-healing (M2-like) macrophages are associated with the release of osteoblastogenic signaling molecules. The emergence of “immunomodulatory biomaterials” is directed toward the biologic consequences associated with permanent implants such as spinal fusion materials. Surface modification of such materials represents one approach for developing more host friendly, biocompatible materials while retaining the required mechanical properties. PURPOSE: The objective of the present study was to characterize and compare the macrophage phenotype elicited by the ZFuze polymer, PEEK, titanium-based alloys, or iterations of modified ZFuze polymer. The ability of these materials to promote differentiation of osteoblast-like cells in vitro was also determined. STUDY DESIGN/SETTING: Macrophage activation study: Primary bone marrow-derived derived macrophages were isolated from C57bl6/j mice and plated on one of the following test articles: ZFuzeTM, PEEK, rough surface titanium alloy, or iterations of modified ZFuze polymer. Gene and protein expression were determined through qPCR and immunolabeling, respectively. Osteoblast differentiation assay: Saos-2 cells were purchased from ATCC. 1*104 cells/cm2 were plated into 6 well tissue culture plates containing test articles composed of: ZFuzeTM, PEEK, rough surface titanium alloy, or iterations of modified ZFuze polymer. Gene and protein expression were determined through qPCR and ELISA, respectively. OUTCOME MEASURES: qPCR, immunolabeling, and ELISA. METHODS: Culture of bone marrow derived macrophages: Bone marrow was isolated from the femurs and tibias of C57bl/6 mice and subsequently cultured in complete growth media, including Dulbecco's modified Eagles medium, 10% fetal bovine serum (FBS), 10% L929 supernatant, 0.1% beta-mercaptoethanol, 100 U/mL penicillin, 100 μg/mL streptomycin, 10 mM nonessential amino acids, and 10 mM HEPES buffer, for 7 days with complete media changes every 48 hours until mature bone marrow-derived macrophages were obtained. Macrophage activation: Mature macrophages were exposed to the following treatments for 24 hours: complete media (M0 control), 20 ng/ml IFN-γ and 100 ng/mL lipopolysaccharide LPS (M1 control), 20 ng/mL interleukin IL-4 (M2 control), PEEK, ZFuze, rough-surface titanium alloy, or ZFuze surface modification iterations. For the cytokine challenge study, cells were exposed for 6 hours to 20 ng/ml IFN-γ and 100 ng/mL LPS, washed and then placed in 10% FBS 1% P/S DMEM for 24 hours. Macrophage immunolabeling: Fixed cells were washed with 1X PBS followed by incubation in a blocking solution composed of PBS, 0.1% Triton-X, 0.1% Tween-20, 4% goat serum, and 2% bovine serum albumin for 1 hour at room temperature. Cells were then incubated in a solution of one of the following primary antibodies: anti-F4/80 at 1:100 dilution as a pan-macrophage marker, anti-inducible nitric oxide synthase (iNOS) at 1:100 dilution as an M1-like marker, and anti-Fizz1 and anti-Arginase1 at 1:200 dilution, each as M2-like markers. Nuclei were counterstained with DAPI. Saos-2 culture: Saos-2 cells were purchased from ATCC. Cells were grown in culture medium comprised of EMEM supplemented with 10% heat-inactivated fetal bovine serum (FBS) and 1% penicillin/streptomycin. Medium was changed every 48 hours. 1*104 cells/cm2 were plated into 6 well tissue culture plates containing test articles composed of either ZFuze, PEEK, rough surface titanium, or iterations of modified ZFuze polymer. Upon reaching confluence, fresh medium was added for 24 hours, and subsequently collected for protein expression determination by ELISA, and then the cells were trypsinized for cell counting and subsequently lysed with TRIzol reagent for RNA isolation. Isolated RNA was then converted to cDNA and gene expression was assessed by qPCR: GAPDH, BMP2, and BMP4. Collected medium was assessed for relative levels of: osteocalcin, BMP2, BMP4, and BMP7. Relative gene and protein expression levels were normalized to cell number and quantified to make relative assessments of differentiation status as a function of test article. RESULTS: Macrophage gene and protein expression: Across three biological replicates, results of qPCR analyses show that ZFuze promoted an M2-like phenotype with expression of Fizz1, and decreased expression of IL-1b and TNF-a compared to PEEK and titanium, which elicited a more “M1-like” macrophage phenotype. Further, zeolite-loaded ZFuze promoted significantly greater expression of Fizz1 by both gene and protein expression than unloaded ZFuze or other test article comparators. Saos-2 osteoblast-like cell gene and protein expression: Aggregated biological replicates show that BMP4 gene expression was upregulated in a statistically significant manner in Saos-2 cells exposed to ZFuze, but not PEEK or rough surface titanium alloy. The expression of BMP2 was also significantly elevated at the translational level in ZFuze, but not PEEK or rough surface titanium, exposed Saos-2 cells. CONCLUSIONS: ZFuze and its iterations elicit a favorable and more biocompatible in vitro immune profile than PEEK or titanium. ZFuze also supports increased expression of osteoblastic differentiation markers’ differentiation of progenitor cells in vitro. FDA DEVICE/DRUG STATUS: ZFuze (Approved for this indication).
Keywords: 4 (2 hydroxyethyl) 1 piperazineethanesulfonic acid; alloy; amino acid; arginase 1; biomaterial; bone morphogenetic protein 2; bone morphogenetic protein 4; bovine serum albumin; cell protein; complementary DNA; endogenous compound; gamma interferon; glyceraldehyde 3 phosphate dehydrogenase; inducible nitric oxide synthase; interleukin 1beta; interleukin 4; interleukin 6; lipopolysaccharide; mercaptoethanol; octoxinol; osteocalcin; osteogenic protein 1; penicillin derivative; polyetheretherketone; polysorbate 20; streptomycin; titanium; tumor necrosis factor; zeolite; animal cell; animal experiment; animal tissue; antibody labeling; bone marrow derived macrophage; C57BL 6 mouse; cell count; cell counting; cell function; clinical outcome; conference abstract; controlled study; culture medium; dilution; eagle; enzyme linked immunosorbent assay; femur; fetal calf serum; goat; heat; human; immune response; implant; macrophage activation; male; mouse; nonhuman; osteoblast; outcome assessment; phenotype; porosity; protein expression level; quantitative analysis; RNA isolation; room temperature; SaOS-2 cell line; signal transduction; spine fusion; stem cell; supernatant; tibia; tissue culture

Clinical Issues-September 2020 - Jones, E.; Wood, A. (AORN journal, 2020)
THIS MONTH: Surgical counts during a partial cystectomy Key words: partial cystectomy, retained surgical item (RSI), counts, bladder, guidewire. Preparing the OR for patients who require both airborne and contact precautions Key words: airborne precautions, contact precautions, contamination, Coronavirus Disease 2019 (COVID-19), negative pressure. Preoperative transport of patients who require both airborne and contact precautions Key words: preoperative patient transport, hand hygiene, personal protective equipment (PPE), N95 respirator, Coronavirus Disease 2019 (COVID-19). Postoperative transport of patients who require both airborne and contact precautions Key words: postoperative patient transport, hand hygiene, personal protective equipment (PPE), N95 respirator, Coronavirus Disease 2019 (COVID-19).
Keywords: adult; article; contamination; coronavirus disease 2019; cystectomy; guide wire; human; hygiene; patient transport; protective equipment; surgery; ventilator

Surgical outcomes of the removal of posterior segment metallic intraocular foreign bodies - Peng, K.-L.; Kung, Y.-H.; Hsu, P.-S.; Wu, T.-T. (BMC ophthalmology, 2020)
BACKGROUND: Posterior segment metallic intraocular foreign bodies (IOFBs) are a leading cause of visual morbidity and blindness, especially among young and middle-aged working populations. Here, we aimed to evaluate the surgical outcomes of the removal of such IOFBs that result from injuries. METHODS: In this retrospective study, 39 patients injured by metallic posterior segment IOFBs and who underwent primary repair procedures, vitrectomies, and IOFBs removal with or without procedures for traumatic cataract removal, scleral buckling and intraoperative tamponade application from January, 2008 to January, 2019. We analyzed the preoperative, intraoperative and postoperative related factors that affect the final visual outcomes. RESULTS: The mean age of the 39 patients was 40.51 ± 12.48 years with the male being predominent (100%).The mean preoperative vision measured 1.50 [Snellen Equivalent (SE), 20/645] ± 1.12 logMAR with the mean final vision measuring 0.93 (SE, 20/172) ± 1.09 logMAR. The related factors that were determined to affect the final visual outcomes included preoperative vision (P = 0.025), IOFB-related macula injuries (P = 0.001) and the development of postoperative complications (P = 0.005) especially retinal detachment (P = 0.002) with the mean final vision measuring 2.12 (SE, counting finger to hand motion) ±1.23 logMAR. Concerning the preoperative signs, the patients with preoperative endophthalmitis also obtained poor mean final vision measuring 1.30 (SE,20/400) ± 1.40 logMAR. CONCLUSION: IOFB-related macula injuries and postoperative retinal detachment were important related factors of poor final visual prognoses in cases involving posterior segment metallic IOFBs. Removing IOFB as early as possible may prevent preoperative endophthalmitis which could lead poor final visions even without significance.
Keywords: adult; article; cataract extraction; clinical article; complication; controlled study; endophthalmitis; finger; human; intraocular foreign body; male; motion; postoperative complication; prevention; prognosis; retina detachment; retina macula lutea; retrospective study; sclera buckling procedure; surgery; traumatic cataract; visual acuity; vitrectomy

Acute inflammatory response after bioresorbable coronary scaffold implantation and impact of trimetazidine - Alsalkhi, H.A.; Rajeeb, A.N.; Ahmed, M.H.; Hadi, N.R.; Amber, K.I.; Muhammad-Baqir, B.M. (International Journal of Pharmaceutical Research, 2020)
Background: Coronary intervention is related to local vascular and systemic inflammation that leads to the stimulation of inflammatory reaction, caused by the rupture of the atherosclerotic plaque and the tunica media fallowing extension of the stent and insertion of a metallic foreign body. Arterial wall damage occurs in addition to the release of inflammatory and chemoattractant factors which stimulate an inflammatory response, leading to leukocyte and platelet activation. Bioresorbable vascular Scaffold (BVS) is considered the fourth revolution in interventional cardiology. It has introduced a novel technology in the treatment of coronary artery disease (CAD). Trimetazidine (TMZ) is an anti-ischemic agent which minimizes the myocardial damage induced by the percutaneous coronary intervention (PCI). Objective: To assess the effect of TMZ on the acute inflammatory response after BVS implantation in patients with CAD. Patients and Methods: A total of 40 diabetic patients with stable coronary artery disease were assigned into two groups: the control group and TMZ treated group. Both groups were admitted to AL-Najaf center for cardiac surgery and Tran’s catheter therapy. Thus, patients under went elective coronary scaffold implantation. Serum blood was collected from peripheral vein before implantation, 12 hrs and 24 hrs after implantation. Collected samples were used to measure IL-8, hs-CRP, cTn-I, MMP-9 and VCAM-1 levels by sand wichELISA method in addition to determine the WBC count. Results. Scaffold implantation produced significant changes in serum levelIL-8, hs-CRP, cTn-I, WBC and VCAM-1(p<0.05).However, no significant change in serum level MMP-9was found (p>0.05).On the other hand, TMZ treatment produced a significant decrease in cTn-I, hs-CRP levels and the WBC count (p<0.05).No significant changes in serum IL-8, MMP-9and VCAM-1were found (p>0.05). Conclusion: Trimetazidine reduced the systemic inflammatory response induced by implantation of Bioresorbable coronary scaffold.
Keywords: adult; article; bioresorbable vascular stent; catheter; clinical article; controlled study; coronary artery disease; diabetic patient; drug therapy; female; gene expression; heart muscle injury; heart surgery; human; human tissue; implantation; inflammation; leukocyte count; male; percutaneous coronary intervention; peripheral vein; protein expression; surgery; C reactive protein; endogenous compound; interleukin 8; trimetazidine; vascular cell adhesion molecule 1

In vitro and in vivo evaluation of the safety and efficacy of a novel liquid fiducial marker for image-guided radiotherapy - Sun, L.-C.; Su, Y.; Ding, X.-C.; Xu, D.-S.; Li, C.-M.; Wang, L.; Li, W.-L.; Sun, X.-D.; Yu, J.-M.; Meng, X. (Oncology Letters, 2020)
The true extent of a tumor is difficult to visualize, during radiotherapy, using current modalities. In the present study, the safety and feasibility of a mixture of N-butyl cyanoacrylate and lipiodol (NBCA/Lip) was evaluated in order to investigate the optimal combination for application as a fiducial marker for radiotherapy. Four combinations of NBCA/Lip injection (1:1-0.1, 1:1-0.15, 1:3-0.1 and 1:3-0.15 ml) were injected into the subcutaneous tissue of BALB/c mice. The changes in gross histopathology, body weight, skin score, marker volume, neutrophil and macrophage counts were observed to analyze the effects of the different mixing ratios and injection volumes, in order to identify the best combination. Evaluation according to the International Organization for Standardization criteria was further conducted in order to test the biocompatibility of the mixture, including an acute systematic assay with mice, cytotoxicity with L929 fibroblasts and delayed-type hypersensitivity tests with guinea pigs and an intradermal test with rabbits. The results revealed that at the seventh week, 42 markers (42/48; 87.5%) were still visible using computed tomography (CT) imaging. No serious adverse effects were observed throughout the study period; however, the combination of 1:1-0.1 ml had the lowest body weight and worst skin score. A review of the histopathological reaction to NBCA/Lip revealed a combination of acute inflammation, chronic inflammation, granulation tissue, foreign-body reaction and fibrous capsule formation. The 1:1 NBCA combination ratio resulted in the most intense tissue repair reaction and a slower degradation rate of markers. In general, the combination of 1:3-0.15 ml had a better fusion with local tissue, maintained a stable imaging nodule on CT images for 7 weeks and the final biocompatibility test demonstrated its safety. Overall, the findings of the present study demonstrated NBCA/Lip as a safe and feasible fiducial marker, when using the 1:3-0.15 ml combination.
Keywords: collagen type 1; cotton seed oil; cyanoacrylate; gelatinase B; interleukin 6; iodinated poppyseed oil; ketamine; animal experiment; animal model; animal tissue; article; ataxic gait; biocompatibility; body weight; cell proliferation; chronic inflammation; computer assisted tomography; controlled study; cytotoxicity; drug efficacy; drug safety; erythema; evaluation study; feasibility study; human; human tissue; hypersensitivity; image analysis; image guided radiotherapy; in vitro study; in vivo study; macrophage; male; mouse; MTT assay; neutrophil; nonhuman; subcutaneous tissue; tissue repair; upregulation

Clinical Analysis of Denture Impaction in the Esophagus of Adults - Wang, F.; Yang, N.; Wang, Z.; Guo, X.; Hui, L. (Dysphagia, 2020)
Denture impacted in the esophagus of adults has been a complex foreign body for otolaryngologists. We reviewed clinical characteristics, diagnosis, and treatment of these patients and evaluated computed tomography (CT) scans to identify a better method of dealing with such tricky situations. Twenty-nine patients who underwent rigid esophagoscopy were included in this retrospective study conducted at the University hospital. The patients underwent preoperative tests and examinations, including complete blood count, blood type and coagulation, electrocardiogram, and CT. The commonest symptoms were retrosternal pain, dysphagia, and odynophagia. Duration of the foreign body impacted within 24 h was 65.5%. CT findings revealed that 4 of 24 cases had complications in the upper esophagus, with 3 of the 4 cases in the mid-esophagus and 1 in the lower esophagus. Complications were related to the duration and location of the obstruction (P < 0.05). The location and complications based on CT findings were coherent with rigid esophagoscopy findings. Denture impaction in the esophagus can be fatal. Early intervention is crucial for prognosis. CT is used for diagnosing and guiding doctors in managing. The commonest location of impacted dentures was the upper esophagus with a lower incidence of complications. The incidence of an impacted denture in the mid-esophagus was low but with a high risk of complications. The incidence of an impacted denture in the lower esophagus was rare. Surgery and proper treatment ensure a good prognosis.
Keywords: computed tomography scanner; nasogastric tube; antibiotic agent; abdominal abscess; adult; aged; article; blood cell count; blood clotting test; blood group typing; clinical article; clinical assessment; clinical feature; computer assisted tomography; denture impaction; diagnostic procedure; disease association; disease duration; dysphagia; dyspnea; electrocardiography; erosion; esophagoscopy; esophagus disease; esophagus perforation; esophagus ulcer; female; foreign body; heart arrest; human; incidence; laceration; male; mediastinitis; odynophagia; patient care; pneumomediastinum; preoperative evaluation; priority journal; prognostic assessment; respiratory arrest; retrospective study; retrosternal pain; risk assessment; thorax surgery; tracheostomy; treatment planning; unconsciousness

976 YOU CAN'T ALWAYS PICK YOUR PATIENTS: EUS-GUIDED TRANSHEPATIC REMOVAL OF AN EMBEDDED TOOTHPICK - James, T.; Baron, T.H. (Gastrointestinal Endoscopy, 2020)
A 75-year-old man with diabetic end-stage renal disease requiring hemodialysis presented with one week of progressive abdominal pain and fevers. Laboratory examination showed an alkaline phosphatase of 140 IU/L and white blood cell count of 15.7 x 109. Non-contrast abdominal computed tomography revealed a 2.9 x 3.3 cm air/fluid collection in the left hepatic lobe with a linear foreign body extending from the collection into the duodenum. An upper endoscopy was performed and was notable for two pustular lesions and edema in the second portion of the duodenum. He was referred to our center for further evaluation and management as an outpatient. On endoscopic ultrasound, a loculated fluid collection within the left hepatic lobe was seen. After transduodenal puncture and contrast injection, a linear foreign body could be seen radiographically within the cavity. A 0.025 inch by 450 cm long guidewire was passed into the cavity and a through-the-scope 6 mm balloon dilator was used to dilated the tract. A 4 cm by 10 mm fully covered self-expandable metal stent was placed into the cavity for abscess drainage and to allow a fistula to form in order to endoscopically retrieve the object. The patient was discharged to home from the procedure suite on oral antibiotics and returned 4 weeks later for repeat endoscopy. The indwelling stents were removed and the tract was dilated with a through-the-scope anastomotic balloon dilator up to 15 mm. The gastroscope was advanced into the cavity. Utilizing a grasping device, a segment of wood was gripped and retrieved. After removal, it was confirmed that the foreign object was a toothpick, but had not been removed intact so a snare was used to grasp the remaining portion of the object for complete retrieval. The patient remained outpatient without the need for hospitalization during our care as there were no procedure-related adverse events. Foreign bodies in the liver are rare and are typically related to surgery or trauma. This patient reported frequently chewing toothpicks, one of which likely was inadvertently ingested and lodged in the duodenum before eventually eroding into the liver. As with all infections, prompt recognition, administration of antibiotics and source control are critical for managing foreign bodies in the liver parenchyma. EUS-guided abscess drainage followed by endoscopic retrieval is a feasible non-surgical option in some cases of intrahepatic foreign bodies.
Keywords: alkaline phosphatase; antibiotic agent; endogenous compound; abdominal pain; abscess drainage; aged; balloon; case report; clinical article; computer assisted tomography; conference abstract; diabetes mellitus; duodenum; edema; end stage renal disease; endoscopic ultrasonography; endoscopy; fever; fistula; foreign body; gastroscope; guide wire; hemodialysis; hospital discharge; hospitalization; human; human tissue; information retrieval; laboratory test; left liver lobe; leukocyte count; liver parenchyma; male; mastication; outpatient; puncture; self expandable metallic stent

Comparison of mechanical characteristics of commonly used vaginal packing materials - Azadi, A.; Pinhasov, K.; Ware, K.; Marchand, G.J.; Ostergard, D.R. (Surgical Technology International, 2020)
Introduction: Clinically, vaginal packing provides the benefit of hemostasis and is designed to prevent the for-mation of postoperative hematomas. Despite the common use of vaginal packing in pelvic surgery, there is lim-ited data to indicate which material has the ideal characteristics for vaginal packing. Materials and Methods: Three packing materials were used: DeRoyal® Fluftex™ (DeRoyal Industries, Inc., Powell, Tennessee), NHP Surgi-Pak™ vaginal packing (NHP Industries, Inc., City of Industry, California), and Curad® Plain Packing Strips (Medline Industries, Inc., Northfield, Illinois). A fluid with similar viscosity to human blood, defibrinated sheep’s blood (Remel Laboratories, Nenexa Kansas) was used to saturate the materials. The primary outcome was the amount of fluid absorbance of each product in both the handpacked and unpacked state. The number of drops used to saturate each material were counted and converted to mL/g. Each product was tested three times and the results were measured by counting the number of drops needed to saturate the material in each experiment. Experiment: Three materials were obtained and conducted into two different experiments to test absorbance. The packed trial consisted of 0.1g of material and was compacted in a 146mm standard Pasteur pipette (Sigma-Aldrich Corp., St. Louis, Missouri). Droplets of sheep’s blood were dispensed until each material had reached its capacity, which was determined by counting the last sequential drop received onto the respective material before the first of the fluid fell from the material into the collecting container. Trials were conducted three times per material and an average of the three trials was calculated. The second experiment tested 1g of each material unpacked and folded into eight layers. Droplets of blood were placed onto the material until each material leaked, which was defined again as the first fluid to fall from the material into the collecting container that it was suspended above. The number of drops needed to produce this effect was recorded. All droplets were counted and converted to mL/g. Standard deviation was calculated for each material in both experiments and an analysis of variance (ANOVA) single factor test was done. Results: Three trials were conducted per material and there was a difference in absorbance between each packing material (p=0.02 packed, p=0.001 unpacked). Additionally, the plain packing strip absorbed the least amount of blood product in the packed and unpacked state compared to DeRoyal® Fluftex™ and NHP Surgi-Pak™ vaginal packing. The average absorbance of the packed materials was 7.7mL/g for DeRoyal® Fluftex™, 9.8mL/g for NHP Surgi-Pak™ vaginal packing, and 7.5mL/g for the Curad® Plain Packing Strips. There was a standard deviation of 2.08 drops for DeRoyal® Fluftex™, 3.51 drops for NHP Surgi-Pak™ vaginal packing, and 1.73 drops for Curad® Plain Packing Strips. Absorbance for DeRoyal® Fluftex™ unpacked was 8.2mL/g, NHP Surgi-Pak™ vaginal packing unpacked was 7.00mL/g, and Curad® Plain Packing Strips was 4.8mL/g. The standard deviation for the unpacked experiment was 29.02 drops for DeRoyal® Fluftex™, 13.61 drops for NHP Surgi-Pak™ vaginal packing, and 15.59 drops for Curad® Plain Packing Strips. A p-value of less than .05 in a confidence interval of 95% was determined. Conclusion: Even though there are studies showing the clinical benefits of vaginal packing after a variety of gynecological surgeries, there is less known about the characteristics of the ideal material. Minimal foreign body reaction, decreased adherence to surgical scars, X-ray visualization, low cost, and easy availability are among the ideal characteristics of the presumed ideal material used for vaginal packing. In this study, we compared the absorbance between three commonly used materials and did not find any statistical differences. Further studies are needed to show the clinical benefits and mechanical characteristics of material used for vaginal packing. Due to the lack of a statistically significant difference in absorbance between the materials, evaluation of mechanical characteristics may be beneficial in determining an ideal vaginal packing product.
Keywords: analysis of variance; article; California; container; controlled study; female; foreign body reaction; gynecologic surgery; human; Illinois; Kansas; Medline; Missouri; nonhuman; outcome assessment; pasteur pipette; scar; sheep; surgery; systematic review; Tennessee; vagina; viscosity; X ray

Investigation of urology intraoperative events leading to root cause analysis at national veterans affairs medical centers - Peard, L.M.; Gunnar, W.; Mills, P.; Harris, A.M. (Journal of Urology, 2020)
INTRODUCTION AND OBJECTIVE: Root Cause Analysis (RCA) is a well-known and effective method of analyzing errors made in the healthcare setting. We aimed to categorize events leading to RCA in urology ORs at VA medical centers in order to increase understanding of when RCA may be appropriate and if where changes may be implemented as a result. METHODS: A dataset of surgery RCAs at VA medical centers that were submitted between the start of fiscal year 2015 to present was created using terms including urology, -gic, -gist, vasectomy; prostatectomy (including TURP, RRP, LRP, PVP), nephrectomy, cystectomy, cystoscopy, lithotripsy, kidney stone, ureteroscopy, ureter, -al, urethral, TURBT, bladder/prostate cancer, and gleason. Cases that did not pertain to an event in a urology OR were excluded. The cases were then categorized based on the type of event. RESULTS: A total of 62 cases were identified. The most common pattern identified was equipment or instrument issue with 23 cases. For example, 'no sterile flexible ureteroscopes available for scheduled ureteroscopy identified after patient asleep'; 'smoking light cord'. There were 12 events categorized as retained foreign bodies (surgical sponge, retained guidewire), 8 pertaining to medical or anesthesia event (incorrect dosing, STEMI during TURP), and 7 pertaining to pathology errors (missing specimen, incorrect diagnosis later revised, mislabeled specimen). There were 6 wrong site surgeries (wrong side ureteral stent placement, prostate biopsy performed in patient scheduled for cystoscopy), 5 cases with incorrect patient information or consent (TURBT performed without consent), and 4 cases identified as major surgical complications (renal artery injury during ureteroscopy, unrecognized bladder perforation during TURP). In 2 cases the wrong case was performed or there was inappropriate work up. One case caused a significant delay in treatment, one case pertained to an incorrect count, and one case identified lack of appropriate credentialing. CONCLUSIONS: RCA is an important tool in improving quality and safety of care. We identified several patterns of events leading to RCA pertaining to urologic operating rooms. By categorizing theses variables, we can better identify targets for efforts on improving quality and safety in our operating rooms. (Figure Presented).
Keywords: accreditation; adult; anesthesia; bladder cancer; bladder perforation; cancer patient; cancer surgery; complication; conference abstract; cystectomy; cystoscopy; flexible ureteroscope; foreign body; guide wire; human; kidney artery; lithotripsy; major clinical study; male; nephrectomy; nephrolithiasis; operating room; patient information; peroperative complication; prostate biopsy; prostate cancer; prostatectomy; root cause analysis; smoking; ST segment elevation myocardial infarction; surgery; surgical sponge; ureter stent; ureteroscopy; urology; vasectomy; veteran

Teamwork in the operating room: How different perceptions of sentinel events may negatively impact patient safety - Weprin, S.; Siev, M.; Li, R.; Maddra, K.; Cho, E.; Nandanan, N.; Klausner, A.; Hampton, L.; Autorino, R. (Journal of Urology, 2020)
INTRODUCTION AND OBJECTIVE: Retained surgical items (RSIs) remain the most frequently encountered sentinel event despite increased vigilance and improved patient safety measures. Recently, a greater emphasis has been placed on improving teamwork and communication in the OR to aid in the prevention of RSI events. Unfortunately, time spent on preventative measures and management of RSIs, especially sharps (i.e. needle, instrument, wire, fragment) is a neglected topic in current literature. This study's objective was to compare how different members of the OR team perceive near-miss and retained surgical sharp events, as this may influence team communication and increase the opportunity for undue patient harm. METHODS: An anonymous survey with 13 questions regarding demographics (6) and perception of near-misses and retained surgical sharps in the last year (7) was distributed electronically to OR staff at three high volume institutions. Responses were ranked in Excel and analyzed by Mann-Whitney U test or Kruskal-Wallis ANOVA test. RESULTS: 30 surgical nurses, 25 surgeons and 12 anesthesiologists responded to the survey. When comparing OR nurses to surgeons, there was no difference in the reported approximate time spent searching for lost sharps (21-30 min, p=0.14), the effectiveness of portable X-ray to help recover RSIs (26-50%, p=0.33) and the amount of time added to the OR due to the use of the X-ray (41-50 min, p=0.8). However, there was significant discordance between surgeons' and nurses' perceptions of the frequency of lost surgical sharps (p=0.025), the frequency of miscounted surgical sharps (p=0.003), and the frequency of lost surgical sharps not recovered (p=0.003). Percentages are listed in Table 1. When performing Kruskal-Wallis ANOVA test to include anesthesiologists, improvement in perception are seen in all categories. CONCLUSIONS: These data provide initial evidence that OR staff may perceive the frequency of near-miss and retained surgical sharps differently. This hints at a lack of communication regarding these sentinel events. Patient safety can be negatively impacted if certain members of the OR team are not aware of lost, miscounted or retained surgical sharps. Further research is needed to evaluate the impact this may have on patient safety, OR culture and the effective reporting of RSI events. (Table Presented).
Keywords: adult; analysis of variance; anesthesiologist; conference abstract; controlled study; demography; drug safety; human; nurse; operating room; patient harm; perception; rank sum test; sentinel event; surgeon; teamwork; X ray

Vaginal retained foreign objects: Applying a human factors perspective - Souders, C.P.; Cohen, T.; Dallas, K.; Cohen, K.; Kanji, F.; Stewart, C.; Anger, J. (Journal of Urology, 2020)
INTRODUCTION AND OBJECTIVE: Retained foreign objects (RFO) after surgery are a serious and preventable issue. Gawande et al (2003) found that the incidence of RFOs in 22 hospitals ranged from 1 in 8,801 to 1 in 18,760 and that retained vaginal sponges accounted for 22% of all retained foreign bodies. Although rare, these events can have severe consequences for both the patients, providers, and hospitals, and can often lead to litigation. We performed a human factors analysis, which is the discipline of studying the interactions of humans and systems, to understand and develop interventions that may help prevent vaginal RFOs. METHODS: We analyzed the safety events reported to our internal tracking system from January 1, 2000 - May 21, 2019 and filtered specifically by potential and actual vaginal RFOs. These events were then categorized into vaginal RFO “Near Misses” (RFO identified before patient leaves the OR) and “Sentinel Events” (RFO not identified before patient leaves the OR). The event reports were then analyzed by three trained human factors researchers. The conditions surrounding each event were analyzed and categorized into the Human Factors Analysis and Classification System (HFACS). RESULTS: 45 events were reported in the 19-year period. The majority of the events analyzed were categorized as “near misses.” The most common items in question (53.33%) were Raytecs, vaginal packing, and vaginal sponges. However, another common instance was breaking of an instrument (20.20%) while operating in the vagina. The majority of cases were laparoscopic hysterectomies or vaginal deliveries. Based on our human factors analysis, the most common contributing factor involved skill-based errors, such as counting errors, followed by issues with communication and shortcomings in the design of tools/technologies (see Table 1). CONCLUSIONS: Fortunately, the occurrence of vaginal RFOs is rare. According to our analysis, the top two contributing factors are skill-based errors and communication, neither of which would have been addressed without the application of a human factors approach. Moreover, both types of errors can be addressed and improved with human factors interventions such as simulation and teamwork training to streamline workflow to reduce the opportunity for errors. (Table Presented).
Keywords: adult; conference abstract; contraceptive sponge; female; human; hysterectomy; plant leaf; sentinel event; simulation; skill; teamwork; vaginal delivery; workflow

A qualitative content analysis of retained surgical items: Learning from root cause analysis investigations - Hibbert, P.D.; Thomas, M.J.W.; Deakin, A.; Runciman, W.B.; Carson-Stevens, A.; Braithwaite, J. (International Journal for Quality in Health Care, 2020)
Objective: To describe incidents of retained surgical items, including their characteristics and the circumstances in which they occur. Design: A qualitative content analysis of root cause analysis investigation reports. Setting: Public health services in Victoria, Australia, 2010-2015. Participants: Incidents of retained surgical items as described by 31 root cause analysis investigation reports. Main Outcome Measure(s): The type of retained surgical item, the length of time between the item being retained and detected and qualitative descriptors of the contributing factors and the circumstances in which the retained surgical items occurred. Results: Surgical packs, drain tubes and vascular devices comprised 68% (21/31) of the retained surgical items. Nearly one-quarter of the retained surgical items were detected either immediately in the post-operative period or on the day of the procedure (7/31). However, about one-sixth (5/31) were only detected after 6 months, with the longest period being 18 months. Contributing factors included complex or multistage surgery; the use of packs not specific to the purpose of the surgery; and design features of the surgical items. Conclusion: Retained drains occurred in the post-operative phase where surgical counts are not applicable and clinician situational awareness may not be as great. Root cause analysis investigation reports can be a valuable means of characterizing infrequently occurring adverse events such as retained surgical items. They may detect incidents that are not detected by other data collections and can inform the design enhancements and development of technologies to reduce the impact of retained surgical items.
Keywords: adult; article; awareness; content analysis; drain; human; learning; outcome assessment; postoperative period; public health service; root cause analysis; Victoria

Patient-reported and objective measures of physical activity are not related 6-months after ACL reconstruction - Kuenze, C.; Lisee, C.; Triplett, A.; Birchmeier, T.; Straus, M.W.; Wilcox, C.L.; Schorfhaar, A.; Joseph, S.; Shingles, M. (Orthopaedic Journal of Sports Medicine, 2020)
Background: When measured objectively, adults with ACL reconstruction (ACLR) are 2.5 times less likely to be physically active than by their healthy counterparts. Currently, it is unclear if patientreported physical activity (PA) is related to objectively-measured PA among high school-aged individuals with ACLR. Purpose: To evaluate the relationship between patient-reported and objectively-measured moderate-to-vigorous PA (MVPA) among high school-aged individuals 6-months after ACLR. Methods: Seventeen participants (age= 15.9±1.3 years, BMI= 24.7±5.1 kg/m2, months since surgery= 6.3±0.7, graft source= 13 hamstring autograft, 3 patellar tendon autograft, and 1 quadriceps tendon autograft, ACL-RSI= 71.3±24.3) with primary unilateral ACLR were enrolled 6±1 months after surgery as part of a prospective cohort study. Participants completed the Tegner Activity and Marx Activity Scales to assess current physical activity level. Participants also completed the International Physical Activity Questionnaire Short Form (IPAQ-SF) to assess patient-reported MVPA (min/day). Objectively-measured MVPA (min/day) and step count (steps/day) were assessed using ActiGraph GTX9-Link accelerometers worn at the hip over a period of no less than 7 days. Wear time (min/day) was validated using recommendations of Choi et al and Evenson's child cutpoints were utilized to categorize PA as light, moderate, vigorous, or very vigorous. Relationships between objectively-measured and patient-reported measures of physical activity were assessed using partial correlations (r) while controlling for total monitor wear-time. We also compared the number of participants who met physical activity guidelines (60 min/day MVPA) via patient-report and objective monitoring using a Fischer's exact test. Results: Participants reported median Tegner activity levels of 5 [range: 5,9] and Marx activity scores of 16 [range: 4,16], and average IPAQ-SF MVPA of 130±80 [range: 0,300] min/day. Objectively, partipants engaged in 26±14 [9,60] min/day of MVPA and took 6140±1691 [range: 3613,9147] steps/day. Current Tegner activity level was moderately correlated to objectivelymeasured MVPA (r = 0.65) but Marx Activity Score (r= 0.14) and IPAQ-SF MVPA (r= 0.01) were not related to objectively-measured MVPA (Figure 1). Individuals who reported meeting MVPA guidelines were no more likely to actually meet objectively-measured MVPA guidelines as compared to participants who reported not meeting guidelines (OR= 1.08, CI= 0.93,1.25, p= 0.99). Conclusion: Objectively, 5.9% of participants were categorized as physically active 6-months following ACLR despite the fact that 82.4% of participants reported meeting PA guidelines. The relationship between objective and patient-reported measures of PA among high school-aged participants months post-ACLR is limited and utilization of patient-reported PA measures in this population should be done with caution.(Table Presented).
Keywords: accelerometer; actigraph; adolescent; anterior cruciate ligament reconstruction; body mass; child; clinical article; cohort analysis; conference abstract; controlled study; female; hamstring muscle; high school; hip; human; international physical activity questionnaire; male; outcome assessment; patellar ligament; practice guideline; prospective study; quadriceps tendon; step count; Tegner activity score; tendon graft

The Impact of Surgical Count Technology on Retained Surgical Items Rates in the Veterans Health Administration - Gunnar, W.; Soncrant, C.; Lynn, M.M.; Neily, J.; Tesema, Y.; Nylander, W. (Journal of patient safety, 2020)
OBJECTIVES: The aim of the study was to compare retained surgical item (RSI) rates for 137 Veterans Health Administration Surgery Programs with and without surgical count technology and the root cause analysis (RCA) for soft good RSI events between October 1, 2009 and December 31, 2016. A 2017 survey identified 46 programs to have independently acquired surgical count technology. METHODS: Retained surgical item rates were calculated by the sum of events (sharp, soft good, instrument) divided by the total procedures performed. The RCAs for RSI events were analyzed using codebooks for procedure type/location and root cause characterization. RESULTS: One hundred twenty-four RSI events occurred in 2,964,472 procedures for an overall RSI rate of 1/23,908 procedures. The RSI rates for 46 programs with surgical count technology were significantly higher in comparison with 91 programs without a surgical count technology system (1/18,221 versus 1/30,593, P = 0.0026). The RSI rates before and after acquiring the surgical count technology were not significantly different (1/17,508 versus 1/18,673, P = 0.8015). Root cause analyses for 42 soft good RSI events identified multiple associated disciplines (general surgery 26, urology 5, cardiac 4, neurosurgery 3, vascular 2, thoracic 1, gynecology 1) and locations (abdomen 26, thorax 7, retroperitoneal 4, paraspinal 2, extremity 1, pelvis 1, and head/neck 1). Human factors (n = 24), failure of policy/procedure (n = 21), and communication (n = 19) accounted for 64 (65%) of the 98 root causes identified. CONCLUSIONS: Acquisition of surgical count technology did not significantly improve RSI rates. Soft good RSI events are associated with multiple disciplines and locations and the following dominant root causes: human factors, failure to follow policy/procedure, and communication.
Keywords: abdomen; article; clinical article; controlled study; general surgery; gynecology; heart; human; limb; neck; neurosurgery; pelvis; root cause analysis; thorax; urology; veterans health

No Surgical Items Left Behind: A Multidisciplinary Approach to the Surgical Count Process - Kertesz, L.; Cordella, C.M.; Nadera, N.M.; Nelson, P.E.; Kahil, M.; Shim, S.-H.; Holtzman, J.S. (Journal of Radiology Nursing, 2020)
The counting process is designed to prevent retained foreign bodies while providing optimal perioperative patient safety. Intraoperative distractions are prevalent and potentially contribute to patient safety risks. Counting is an important preventative measure that is a human process prone to error, especially in this busy environment where multiple things are happening simultaneously. We sought to evaluate the impact of distractions during the count process on patient safety. Trained, nationally certified registered nurses used a validated tool to observe the number of interruptions that occurred during the count process in cardiac surgery. Observation included the key personnel that lead the count process including the scrub person, circulating nurse, attending surgeons, fellows, and residents of all disciplines. Observation included scheduled cases in the cardiac specialty for the adult population including all shifts (24 hours). The predictor in this study was distraction. The primary measure of distraction was the total number of distraction for each case. There are different distraction levels for each distraction. Thus, weighted distraction score for each case was created as the summation of distraction level and it is the secondary measure of distraction. To detect a medium effect size with 80% power at 0.05 level, we needed a minimum sample size of 54. We correlated the relationship between the number of interruptions observed and sequelae. Working together as a cohesive team to minimize interruptions can enhance patient safety and decrease additional workload across departments.
Keywords: surgical equipment; article; effect size; foreign body; heart surgery; human; Medline; multidisciplinary team; observational study; patient care; patient safety; pilot study; priority journal; procedures; prospective study; registered nurse; retained foreign body; sample size; surgical count process; surgical technique; workload

An unusual case of nine cilia embedded in the retina after a perforating ocular injury - Ramos, G.Z.; Goncalves, T.B.; Bordon, A.F. (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To report an extremely rare case involving a 41-year-old man with nine intraocular cilia embedded in the retina after a perforating ocular injury caused by a metal wire. This case is particularly rare because of the number and location of the cilia. Observations: The patient underwent an uneventful corneal suturing and extracapsular extraction of the damaged lens of his right eye. Intraocular foreign bodies were discovered following surgery and were removed at a later date. Following lens extraction and ocular repair, the patient's best-corrected visual acuity (BCVA) was counting fingers. Fundus examination during follow-up revealed several eyelashes embedded in the retina. Thirty-two days after the injury, the patient showed signs of ocular inflammation. Therefore, the patient underwent vitrectomy and intraocular foreign body removal. Nine cilia were embedded in the retina at the posterior perforation site. At the final follow-up visit, his BCVA was 20/25. Conclusion and importance: This report describes an unusual case where intraocular cilia were embedded in the retina after a perforating ocular injury. The eyelashes caused an intraocular inflammatory reaction that subsided after their removal.
Keywords: general device; metal wire; prednisolone acetate; adult; article; best corrected visual acuity; case report; cilium; clinical article; cornea disease; corneal laceration; emergency ward; extracapsular extraction; eye pain; follow up; human; hyperemia; lens capsule rupture; male; perforating eye injury; rare disease; retina; retina detachment; school teacher; slit lamp microscopy; suture technique; traumatic cataract; vitrectomy; vitritis

The perils of penile enlargement-a case of fulminant penile infection - Khor, N.W.M.; Dhar, A.; Cameron-Strange, A. (BJU International, 2020)
Introduction and Objectives: Penile enhancement with injectable agents is a rising trend and yet has received little scientific attention, despite the possibility of serious complications. We report a case of delayed severe infection following penile filler insertion, leading to multi-organ failure and intensive care support. Methods: A 31-year-old man presented two days after unprotected sexual intercourse with progressive pain and swelling of the penile shaft. He had self-administered 50 mg of Prednisone for the swelling. Two months prior, the patient received subcutaneous hyaluronic filler injections at a cosmetic clinic for penile enlargement. Relevant past medical history included tubularised hypospadias repair and genital herpes simplex. The patient had multiple risk factors for deterioration including regular testosterone injections, multiple sexual partners, cocaine use, alcohol consumption of 22 standard drinks a day and a 10 pack-year smoking history. The patient was tachycardic to 127, hypotensive at 90/50 and febrile to 40”. Physical examination revealed gross penile oedema and erythema, with a ventral curvature of his entire shaft stopping at the base of the penis. There was a small abrasion on the ventral aspect 1 cm proximal to glans. Results: Overnight the patient developed septic shock with anuria and hypotension, requiring transfer to the intensive care unit for vasopressor and inotropic support. Repeat examination showed blistering of the penis over filler injection sites. His white cell count was 25, creatinine 391 and lactate 2.3. Antibiotics for necrotising fasciitis was commenced upon infectious disease advice. Penile exploration revealed multiple fluid-filled fillers which appeared pus stained. Fillers were drained and fluid sent for culture. There was no abscess or evidence of necrotising fasciitis intraoperatively and on imaging. Operative wound cultures grew streptococcus pyogenes (penicillin sensitive). He improved with intravenous antibiotics and was stepped down from intensive care after 4 days and discharged on day 8. The patient received 3 weeks of antibiotics, prophylactic valaciclovir and drug and alcohol review. One month post admission there was significant superficial skin loss to both ventral and lateral aspect of the penis, corresponding to the location of blistering, with healthy granulation tissue at the base. He was reviewed by the plastic surgeons for a split skin graft but opted for conservative management with regular dressings. Three months post presentation he reports normal sexual and urinary function. Conclusions: This is the first published case of a penile filler infection causing fulminant infection with multi-organ failure. The severity of the case is due to a combination of behavioural risk factors, presence of foreign material and previous penile surgery. The case highlights the importance of evaluating social risk-factors and need for further research into penile augmentation procedures.
Keywords: alcohol; antihypertensive agent; cocaine; creatinine; filler; hypertensive factor; lactic acid; penicillin derivative; prednisone; testosterone; valaciclovir; abrasion; abscess; adult; alcohol consumption; anuria; bacterium culture; blister; communicable disease; conference abstract; conservative treatment; deterioration; drug combination; drug therapy; edema; erythema; foreign body; genital herpes; granulation tissue; human; human cell; hypospadias; hypotension; in vitro study; injection site; inotropism; intensive care unit; leukocyte count; male; medical history; multiple organ failure; necrotizing fasciitis; nonhuman; pain; penis; physical examination; plastic surgeon; pus; risk factor; septic shock; sexual function; sexual intercourse; skin defect; smoking; split thickness skin graft; Streptococcus pyogenes; tachycardia

Two cases report of retained surgical items - Varela, E.; Iraola Fernández De Casadevante, M.; De Ariño Hervás, I.; Aguirre Allende, I.; García Trancho, A.; Ruiz Montesinos, I.; Enríquez Navascués, J.M. (British Journal of Surgery, 2020)
Objectives: The term 'retained surgical items' refers to any object which, unintentionally, remains inside the patient's body after the surgery, once the skin is closed. This implies a medical error which may lead to medical complications and medical-legal and economic consequences. Our aimas were: (1) to expose two cases of patients treated at our Hospital during 2018 in which retained surgical items from a previous surgery were found (cholecystectomy) after coming to the Emergency Room with abdominal pain, and (2) to study the rate, risk factors, clinical features, diagnosis and treatment of retained surgical items and review updated prevention strategies. Methods: The information from both cases was collected by reviewing the medical history and surgical reports saved in OsabideGlobal, aDUHprogram.We carried out a bibliographic review with the searches: 'surgery iatrogenia foreign body', 'foreign bodies after surgery' and 'retained surgical item' in databases such as UpToDate, Dynamed and Clinical Key Results: The rate at which this occurs can vary. In abdominal cavity surgeries it happens to about 1 out of every 1,000 to 1,500 patients. Among the associated risk factors we can find: emergency surgery, surgery with blood loss >500 ml, erroneous or not performed surgical count, performing more than one procedure in surgery, long surgeries, unexpected changes during the course of surgery and surgery in patients with raised BMI. There are two patterns of clinical presentation of surgical sponge retention: exudative and fibrous pattern. The diagnosis is based on image studies that show the retained object. The trapped object must be removed in symptomatic patients. Observation is accepted in asymptomatic patients when the objects are held for a long time or if they account for a significant amount of comorbidity. There are multiple prevention strategies such as improving the communication among the operating room staff, or the accuracy in counting, among others. Conclusions: Even though there have been many cases of retained surgical items in the past, there are very few publications. Despite the progress made, it is an adverse event that continues to occur. Surgical count plays a main role in the prevention.
Keywords: abdominal cavity; abdominal pain; adult; bleeding; body mass; cholecystectomy; clinical feature; comorbidity; conference abstract; emergency surgery; emergency ward; female; foreign body; human; major clinical study; male; operating room; patient history of surgery; risk factor; surgery; surgical sponge

Implementing a "visualize and verify" process for the surgical sponge count (AORN journal, 2020)
Keywords: classification; human; interview; medical error; prevention and control; procedures; surgical sponge; total quality management

Vaginal retained foreign objects: Applying a human factors perspective - Souders, C.; Cohen, T.; Dallas, K.; Cohen, K.; Kanji, F.; Stewart, C.; Anger, J.T. (Neurourology and Urodynamics, 2020)
Introduction: Retained foreign objects (RFO) after surgery are a serious and preventable issue. Gawande et al (2003) found that the incidence of RFOs in 22 hospitals ranged from 1 in 8,801 to 1 in 18,760 and that retained vaginal sponges accounted for 22% of all retained foreign bodies. Although rare, these events can have severe consequences for both the patients, providers, and hospitals, and can often lead to litigation. We performed a human factors analysis, which is the discipline of studying the interactions of humans and systems, to understand and develop interventions that may help prevent vaginal RFOs. Methods: We analyzed the safety events reported to our internal tracking system from January 1, 2000 - May 21, 2019 and filtered specifically by potential and actual vaginal RFOs. These events were then categorized into vaginal RFO 'Near Misses' (RFO identified before patient leaves the OR) and 'Sentinel Events' (RFO not identified before patient leaves the OR). The event reports were then analyzed by three trained human factors researchers. The conditions surrounding each event were analyzed and categorized into the Human Factors Analysis and Classification System (HFACS). Results: 45 events were reported in the 19-year period. The majority of the events analyzed were categorized as 'near misses.' The most common items in question (53.33%) were Raytecs, vaginal packing, and vaginal sponges. However, another common instance was breaking of an instrument (20.20%) while operating in the vagina. The majority of cases were laparoscopic hysterectomies or vaginal deliveries. Based on our human factors analysis, the most common contributing factor involved skill-based errors, such as counting errors, followed by issues with communication and shortcomings in the design of tools/ technologies (see Table 1). Conclusion: Fortunately, the occurrence of vaginal RFOs is rare. According to our analysis, the top two contributing factors are skill-based errors and communication, neither of which would have been addressed without the application of a human factors approach. Moreover, both types of errors can be addressed and improved with human factors interventions such as simulation and teamwork training to streamline workflow to reduce the opportunity for errors. (Table Presented).
Keywords: adult; conference abstract; contraceptive sponge; female; human; hysterectomy; plant leaf; sentinel event; simulation; skill; teamwork; vaginal delivery; workflow

Impact of staff turnover during cardiac surgical procedures - Bloom, J.P.; Moonsamy, P.; Gartland, R.M.; O'Malley, C.; Tolis, G.; Villavicencio-Theoduloz, M.A.; Burkhardt, C.; Dunn, P.; Sundt, T.M.; D'Alessandro, D.A. (Journal of Thoracic and Cardiovascular Surgery, 2020)
Objective: The impact of staff turnover during cardiac procedures is unknown. Accurate inventory of sharps (needles/blades) requires attention by surgical teams, and sharp count errors result in delays, can lead to retained foreign objects, and may signify communication breakdown. We hypothesized that increased team turnover raises the likelihood of sharp count errors and may negatively affect patient outcomes. Methods: All cardiac operations performed at our institution from May 2011 to March 2016 were reviewed for sharp count errors from a prospectively maintained database. Univariate and multivariable analyses were performed. Results: Among 7264 consecutive cardiac operations, sharp count errors occurred in 723 cases (10%). There were no retained sharps detected by x-ray in our series. Sharp count errors were lower on first start cases (7.7% vs 10.7%, P <.001). Cases with sharp count errors were longer than those without (7 vs 5.7 hours, P <.001). In multivariable analysis, factors associated with an increase in sharp count errors were non–first start cases (odds ratio [OR], 1.3; P =.006), weekend cases (OR, 1.6; P <.004), more than 2 scrub personnel (3 scrubs: OR, 1.3; P =.032; 4 scrubs: OR, 2; P <.001; 5 scrubs: OR, 2.4; P =.004), and more than 1 circulating nurse (2 nurses: OR, 1.9; P <.001; 3 nurses: OR, 2; P <.001; 4 nurses: OR, 2.4; P <.001; 5 nurses: OR, 3.1; P <.001). Sharp count errors were associated with higher rates of in-hospital mortality (OR, 1.9; P =.038). Conclusions: Sharp count errors are more prevalent with increased team turnover and during non–first start cases or weekends. Sharp count errors may be a surrogate marker for other errors and thus increased mortality. Reducing intraoperative team turnover or optimizing hand-offs may reduce sharp count errors.
Keywords: conference paper; controlled study; heart surgery; hospital mortality; human; major clinical study; nurse; operating room; patient safety; prospective study; scrub; turnover rate; X ray

Difluprednate 0.05% versus prednisolone acetate post-phacoemulsification for inflammation and pain: An efficacy and safety clinical trial - Palacio-Pastrana, C.; Mondragón, E.C.; Soto-Gómez, A.; Suárez-Velasco, R.; Montes-Salcedo, M.; de Ortega, L.F.; Nasser-Nasser, L.; Baiza-Durán, L.; Olvera-Montaño, O.; Muñoz-Villegas, P. (Clinical Ophthalmology, 2020)
Background: The purpose of this study was to compare the efficacy and safety of difluprednate 0.05% (PRO-145) versus prednisolone acetate 1% (Prednefrin® SF), for management of postoperative inflammation and pain, after cataract surgery. Methods: This was a Phase III, multicenter, prospective, double-blind, clinical trial. Intentto-treat population included 178 post-phacoemulsification patients that were assigned to receive either PRO-145, or prednisolone. One day after unilateral eye surgery, patients instilled a drop 4 times a day for 14 days (then tapering the dose downward for 14 days). The primary efficacy endpoints were anterior chamber (AC) cell grade and flare. Other parameters measured included: retinal central thickness (measured via OCT), conjunctival hyperemia, edema, pain and photophobia. Tolerability and safety were assessed through burning, itching, foreign body sensation, visual acuity (VA), intraocular pressure (IOP) and incidence of adverse events (AE). Results: A total of 171 subjects were randomized (1:1) and completed the study. Compared to day 1, there was a significant improvement in the AC cell count and flare in both groups by the final visit (80.2% vs 88.4%, p=1.000). Conjunctival hyperemia improved in a similar fashion (81.2% vs 79%, p=0.234) in both PRO-145 and prednisolone groups, without differences between them. This was also observed for edema (82.4% vs 82.5%, p=0.246), pain (15.3% vs 7%, p=0.497) and photophobia (16.4% vs 15.1%, p=0.246), respectively. There was no significant difference between treatments for any tolerability parameter studied. Finally, at the 4-week postoperative visit, there were no significant differences between treatments for VA, IOP and AE results (p-values; 0.095, 0.053 and 0.099, respectively). Conclusion: The results of this study suggest that PRO-145 is as effective and safe as prednisolone acetate in treating postoperative inflammation and pain in patients undergoing phacoemulsification. The study was registered at ClinicalTrials.gov as NCT03693989.
Keywords: NCT03693989; difluprednate; prednefrin; prednisolone acetate; pro 145; adult; aged; anterior eye chamber; article; blurred vision; central retinal thickness; chemosis; conjunctival hyperemia; controlled study; double blind procedure; drug dose reduction; drug efficacy; drug safety; drug tolerability; eye burning; eye pain; female; headache; human; incidence; influenza; intention to treat analysis; intraocular foreign body; intraocular hypertension; intraocular pressure; major clinical study; male; multicenter study; ocular pruritus; optical coherence tomography; phacoemulsification; phase 3 clinical trial; photophobia; postoperative inflammation; postoperative pain; prospective study; randomized controlled trial; retina macula cystoid edema; treatment duration; very elderly; visual acuity; prednefrin; pro 145

Intrathoracic gossypiboma: An overlooked entity - Othman, S.A.; Alsafwani, J.Q.; Alsahwan, A.G.; Aljehani, Y. (American Journal of Case Reports, 2020)
Objective: Rare disease Background: During any surgical procedure, there are several factors that may lead to morbidity and mortality. One of those factors is a retained cotton or gauze surgical sponge inadvertently left in the body during an operation, known as gossypiboma. This clinical oversight may cause serious postoperative complications and increase the risk of mortality, particularly if left undiscovered. Furthermore, this issue adds to the economic burden on healthcare systems by increasing the rate of reoperation and rehospitalization. The length of postoperative gossypiboma diagnosis varies greatly, as patients may either present acutely with symptoms such as a palpable mass, pain, nausea, and vomiting, or remain asymptomatic for several years. Case Report: We report the case of a 48-year-old man who underwent a thoracotomy after a road traffic accident. The resulting empyema led to the intraoperative discovery of an intrathoracic gossypiboma, which was initially interpreted radiologically as a part of the previous surgical staple line. The causative agent was discovered by the team’s nurses during the postsurgical count of instruments and sponges, and who were alerted to a recovered sponge differing in appearance from the sponges used for that procedure. Conclusions: In general, proper counting and adherence to the World Health Organization ‘Surgical Safety Checklist’ can greatly improve the outcome of any surgery. The diagnosis of gossypiboma is often late or missed entirely and leads to additional interventions that can be avoided or detected early when the material contains a radiopaque marker. In cases under suspicion of any mistakenly left object, the use of intraoperative radiology before skin closure is highly recommended to prevent postoperative complications for the patient and organization.
Keywords: accident; adult; article; case report; checklist; clinical article; complication; empyema; Gossypium; health care system; hospital readmission; human; male; middle aged; nausea and vomiting; nonhuman; nurse; pain; postoperative complication; prevention; radiology; reoperation; surgical staple; thoracotomy; traffic; World Health Organization

Clinical characteristics and relevance of coagulase-negative Staphylococci other than S. epidermidis by positive blood culture - Asai, N.; Sakanashi, D.; Suematsu, H.; Kato, H.; Hagihara, M.; Watanabe, H.; Shiota, A.; Koizumi, Y.; Yamagishi, Y.; Mikamo, H. (Journal of Microbiology, Immunology and Infection, 2020)
Introduction: Staphylococci is the most commonly isolated bacteria in blood cultures (BC), and is mostly regarded as contamination. However, the clinical relevance and characteristics of CNS other than Staphylococcus epidermidis (Non-SE-CNS) is still unknown. Methods: For the purpose of clarifying the epidemiology and clinical significance of Non-Se-CNS infections, we retrospectively evaluated BC isolates of Non-Se-CNS at our institute from May 2013 to March 2017. Infections were defined as true bacteremia if (1) two or more positive BCs of the same species were present (or detection of the same species in another clinically relevant sample), (2) the patient had clinical symptoms as outlined in the Centers for Disease Control and Prevention's definition of primary blood stream infection8 and the symptoms or markers of inflammation (e.g., fever, symptoms, white cell counts, C-reactive protein, or procalcitonin) were improved after pathogen-directed therapy (e.g. either antibiotic therapy and/or removal of the foreign body in the case of catheter-related blood stream infections suspected) and (3) without any other infection. Results: During the period, 279 patients with BC positive for Non Se–CNS were identified. 44 patients were excluded, either due to missing data or multiple pathogens in the same BC. Among the remaining 235 patients, 67 (29%) were categorized as true bacteremia (n = 43) or possible infections (n = 24). Resistance rate to methicillin among Non-SE-CNS is about 60%, which is lower than those among S. epidermidis of 78%. Conclusion: About 30% of Non-Se-CNS isolates were clinically relevant in our study. Antibiotic susceptibility of Non-SE-CNS is quite different than those of S. epidermidis.
Keywords: adult; adverse device effect; antibiotic sensitivity; antibiotic therapy; article; bacteremia; blood culture; catheter infection; central nervous system infection; clinical feature; coagulase negative Staphylococcus; contamination; controlled study; disease control; female; fever; foreign body; human; infectious agent; leukocyte count; major clinical study; male; nonhuman; prevention; retrospective study; surgery; C reactive protein; endogenous compound; meticillin; procalcitonin

Rotator cuff repair with biological graft augmentation causes adverse tissue outcomes - Rashid, M.S.; Smith, R.D.J.; Nagra, N.; Wheway, K.; Watkins, B.; Snelling, S.; Dakin, S.G.; Carr, A.J. (Acta Orthopaedica, 2020)
Background and purpose — Biological patches can be used to augment rotator cuff tendon repair in an attempt to improve healing and reduce rates of re-rupture. However, little is known about the in vivo tissue response to these patches. We assessed native rotator cuff tissue response after surgical repair and augmentation with 2 commercially available extracellular matrix (ECM) patches. Patients and methods — Patients underwent a rotator cuff repair augmented with either GraftJacket (Wright Medical), Permacol (Zimmer Biomet), or no patch (Control), applied using an onlay technique. A sample of supraspinatus tendon was collected intraoperatively and 4 weeks post-surgery, using ultrasound-guided biopsy. Histology and immunohistochemistry were performed on all samples. Results — The Permacol group (n = 3) and GraftJacket group (n = 4) demonstrated some changes in native tendon ECM compared with the control group (n = 3). Significant disruption of the extracellular matrix of the repaired native supraspinatus, underlying both patches, was observed. The patches did not generally increase cellularity, foreign body giant cell count, or vascularity compared to the control group. 1 patient in the Permacol group had an adverse tissue immune response characterized by extensive infiltration of IRF5+, CD68+, and CD206+ cells, suggesting involvement of macrophages with a pro-inflammatory phenotype. No significant differences in protein expression of CD4, CD45, CD68, CD206, BMP7, IRF5, TGFβ, and PDPN were observed among the groups. Interpretation — Histological and immunohistochemical analysis of native tendon tissue after patch augmentation in rotator cuff repair raises some concerns about a lack of benefit and potential for harm from these materials.
Keywords: adult; article; case report; cell count; clinical article; extracellular matrix; female; giant cell; histopathology; human; human cell; human tissue; immune response; immunohistochemistry; macrophage; male; phenotype; protein expression; rotator cuff; surgical mesh; tendon; tissue reaction; ultrasound; vascularization; CD4 antigen; CD68 antigen; endogenous compound; mannose receptor; osteogenic protein 1; receptor type tyrosine protein phosphatase C; transforming growth factor beta

Development of a Surgical Sponge Counting System Using Radiographic Images - Kusuda, K.; Yamashita, K.; Tanaka, S.; Tanaka, K.; Ohta, Y. (Surgical Innovation, 2020)
Background. Retention of surgical sponges in patients is a relatively frequent medical malpractice. To prevent it, the surgical sites are scanned using X-ray. However, using radiography in the operation room induces X-ray exposure for both patients and staff. To prevent such issues, a novel sponge counting system was developed. Each surgical sponge used in common hospitals is composed of single radiopaque fibers. Methods. The proposed system scans surgical sponges to estimate their fiber length (EFL) and returns the number of it. In this study, an optimal image acquisition protocol was determined that allows an accurate count of sponges. X-ray doses and multi-angle image procedures were tested. Results. Measurement trials were performed and compared for both dry and blood-soaked sponges. As a result, the X-ray dose of 50 kV and 600 μA and the acquisition of 180 images per sample yielded an accurate EFL. The 180-image protocol achieved good performance in this study and allowed counting of one package of 10 sponges in 226 seconds. For these settings, a significant correlation was found between the actual number of sponges and the estimated fiber lengths. Additionally, the performance of the system was similar for either dry or blood-soaked items. Conclusion. The proposed system could accurately count surgical sponges and is a promising option in preventing the accidental retention of surgical sponges.
Keywords: adult; article; controlled study; human; operating room; radiography; surgical sponge

Laparoscopic treatment of right colic flexure perforation by an ingested wooden toothpick - Casoni Pattacini, G.; Pecchini, F.; Mullineris, B.; De Maria, R.; Trapani, V.; Francescato, A.; Piccoli, M. (International Journal of Surgery Case Reports, 2020)
Introduction: Ingestion of a toothpick, both accidentally and intentionally, is a rare event. Presentation of case: We present the case of a 42-years old man who was admitted to the emergency department at our Institution presenting with a 5-days history of right sided abdominal pain. Laboratory blood count reported leukocytosis and alteration of principal inflammation index; at the abdominal ultrasound no signs of perforation or collection were described. Discussion: Indication to surgery was posed and an explorative laparoscopy was performed. The presence of local peritonitis at the right colonic flexure secondary to a full thickness bowel perforation caused by a toothpick was found. There was also an acute phlegmonous appendicitis. A laparoscopic appendectomy and a full-thickness double running suture of the perforation were performed. Conclusion: Awareness about dangers of ingested toothpicks needs to be taken and the intestinal track/trace of the toothpick is mandatory until its expulsion.
Keywords: abdominal pain; adult; appendectomy; appendicitis; article; awareness; blood cell count; case report; clinical article; colic; colon; emergency ward; foreign body; human; intestine perforation; laparoscopic suture; laparoscopy; leukocytosis; male; peritonitis; running; thickness; ultrasound

Recognising eosinophilic oesophagitis as a cause of food bolus obstruction - Ntuli, Y.; Bough, I.; Wilson, M. (Frontline Gastroenterology, 2020)
Eosinophilic oesophagitis (EoE) is a chronic, inflammatory condition of the oesophagus, characterised by intermittent dysphagia, food bolus obstruction (FBO) and histologically proven, eosinophil-mediated inflammation. EoE is identified in up to 50% of FBO presentations. To evaluate the management of patients presenting with FBO to our centre against current clinical guidelines. Design A retrospective analysis of acute FBO was performed between January 2008 and August 2014. Patients were identified using the ICD 10 code T18.1, foreign body in oesophagus' in their electronic discharge document. Data were collected on admitting specialty, previous FBO, endoscopy findings, biopsy sites and findings, eosinophil count and diagnosis of EoE. Results 310 acute episodes of FBO were included in the final study cohort. 202 (65.2%) flexible oesophagogastroduodenoscopies (OGDs) were performed, with 50 (34.5%) of those occurring in those admitted under ENT (n=145), versus 28 (93.3%) and 124 (91.9%) in general medicine (n=30) and surgery (n=135), respectively. 80 (39.6%) had oesophageal biopsies taken, and 21 novel diagnoses of EoE were made (26.3% biopsy-proven rate). Five (23.8%) of the novel diagnoses had a formal eosinophil count included in the histopathology report, and eight (38.1%) had up to three previous OGDs that had not diagnosed their condition of EoE. Conclusion Our study highlights wide variation in adherence to the guidelines for the management of FBO depending on admitting specialty. We advocate an FBO protocol involving single specialty management, flexible OGD, ≥6 biopsies from the upper and lower oesophagus, and standardisation of oesophageal biopsy reports with a formal eosinophil count.
Keywords: adult; article; cohort analysis; dysphagia; eosinophil count; eosinophilic esophagitis; esophagogastroduodenoscopy; esophagus biopsy; esophagus foreign body; esophagus obstruction; female; follow up; gastrointestinal endoscopy; general practice; histopathology; human; human tissue; major clinical study; male; middle aged; practice guideline; priority journal; retrospective study

Gossypiboma: A Case Series and Literature Review - Alemu, B.N.; Tiruneh, A.G. (Ethiopian journal of health sciences, 2020)
Background: Gossypiboma (retained surgical sponge) is a rare medical event. It could cause a serious complication that can threaten patients' life. Its diagnosis is usually difficult because the clinical symptoms are nonspecific and the imaging findings are often inconclusive. Case Presentations: We present two cases, a 32 years old woman who passed a retained surgical sponge via rectum 5 months after cesarean section and a 30 years old lady presented with an acute abdomen that later found to have localized right lower quadrant abscess with a retained surgical sponge. Conclusion: The most important approach to reduce the incidence of gossypiboma is prevention. At the end of the surgery, a correct count is always the gold standard safeguard against it. Although errors are not to be completely avoided, continuous CPD and strict adherence to rules of the operating room will reduce its incidence to a minimum.
Keywords: case report

Accidental arthrotomy causing aseptic monoarthritis due to agave sap - Ontiveros, S.T.; Minns, A.B. (Journal of Medical Toxicology, 2020)
Background: Agave species has previously been reported to cause both vesicopapular and purpuric dermatitis. Causative agents are believed to be steroidal saponins and calcium oxalate crystals in agave sap. Aseptic inflammatory arthritis has been reported from foreign bodies such as thorns or cactus needles after inadvertent arthrotomy; however, this has not been described from agave plants. Hypothesis: Agave sap irritants may cause an aseptic inflammatory arthritis mimicking a septic arthritis. Methods: This is a single patient chart review. A 27-year-old male presented with malaise, left knee pain, swelling, and inability to range his knee 2 hours after suffering an accidental stab wound to his left lateral knee by an agave plant spine. The patient had no history of intravenous drug use, sexually transmitted infections, or current genitourinary complaints. Workup included complete blood count, basic metabolic panel, ESR, CRP, lactate, blood cultures, gonorrhea/chlamydia testing, synovial fluid studies, and surgical washout. Results: The patient remained afebrile with normal vital signs.WBC was 14 (1000/mm3), ESR was 2 mm/h, CRP was 2.2 mg/dL, and lactate was 2.6 mmol/L. The remainder of his CBC and BMP was within normal limits. Synovial fluid WBC was 92,730 (1000/mm3) with 75% neutrophils and no crystals. Gram stain was negative. After repeating synovial fluid testing, orthopedics took the patient for a washout remarkable for turbid fluid and no foreign bodies. Synovial fluid and blood cultures remained without growth. Antibiotics were stopped on POD 1 and the patient was discharged from the orthopedic service. At 2 weeks follow-up, he is doing well. Conclusion: Agave sap toxicity may contribute to aseptic inflammatory arthritis seen acutely in the emergency department.
Keywords: antibiotic agent; irritant agent; lactic acid; adult; adverse drug reaction; Agave; arthrotomy; bacterial arthritis; bacterium culture; blood cell count; blood culture; case report; Chlamydia; clinical article; conference abstract; drug therapy; emergency ward; follow up; foreign body; gonorrhea; Gram staining; hospital discharge; human; human cell; knee pain; malaise; male; medical record review; monarthritis; neutrophil; nonhuman; orthopedics; plant spine; side effect; stab wound; swelling; synovial fluid; vital sign

Characteristics of open globes secondary to gunshot wounds presenting at a level 1 trauma center - Castro, H.M.; Gross, A.; Chuang, A.; Mankiewicz, K.A.; Richani, K.; Crowell, E.L. (Investigative Ophthalmology and Visual Science, 2020)
Purpose : According to the United States Eye Injury Registry, gunshot wounds (GSW) to the eye account for approximately 6.5% of ocular trauma injuries. While studies have been conducted on gun-related eye injuries, none have concentrated on gunshot-related open globes in a civilian setting. Our aim is to describe the characteristics and outcomes of open globes secondary to GSW. Methods : A retrospective chart review was performed on patients with open globe injuries secondary to GSW at Memorial Hermann Hospital-Texas Medical Center between January 2010 and March 2015. Patient demographics, cause of GSW, gunshot injury characteristics, ocular signs and concurrent injuries, location of injury, evisceration/enucleation performed, and final visual acuity (VA) were recorded. Results : Of 480 open globes, 16 were due to GSW (3.3%). The majority were sustained by males (12 [75%]) and adults (≥18 years; 12 [75%]), with mean age 28.4 years (±17.1, range 1-74). Causes of gun trauma were accidental (6 [38%]), assault (5 [31%]), self-inflicted (4 [25%]), and unknown (1 [6%]). All except 1 were zone 3 injuries. The majority sustained other ocular injuries, including orbital wall fractures (63%), lid lacerations (50%), and hyphema (63%). Four patients (25%) sustained canalicular lacerations. Nine (56%) and 5 (31%) eyes had orbital and intraocular foreign bodies, respectively. Six of the 10 (60%) patients with GSWs who were able to participate in VA testing at initial consultation had no light perception vision. Of the rest, 2 were hand motion, 1 was light perception, and 1 was 20/200. Ten (63%) open globes underwent surgical repair within 24 hours, 3 (19%) in 24 - 48 hours, and 3 (19%) after 48 hours. Eleven (69%) eyes required an enucleation/evisceration. After surgical repair, 12 (79%) eyes had a final VA of NLP, 1 (6%) eye was HM and 3 (19%) eyes had final VA better than counting fingers. These 3 were all shotgun injuries, of which 2 were accidental and 1 from assault. Conclusions : The great majority of open globe injuries secondary to GSW have a poor visual outcome with most suffering unsalvageable damage resulting in evisceration or enucleation. The poor visual prognosis may be explained by the majority sustaining zone 3 injuries, which by nature are typically irreversible. Larger studies are needed to better understand these injuries and prevent their occurrence.
Keywords: adult; assault; case report; clinical article; conference abstract; consultation; demography; emergency health service; evisceration; eye injury; finger; fracture; gunshot injury; human; hyphema; intraocular foreign body; laceration; male; medical record review; motion; prognosis; retrospective study; Texas; vision; visual acuity

Endoscopic removal of foreign body in upper gastrointestinal tract in dogs: Success rate and complications - Poggiani, F.M.; Da Costa Duarte, R.P.; Santana, M.I.S.; Galera, P.D. (Acta Scientiae Veterinariae, 2020)
Background: Dogs and cats with acute signs of choking, retching, cough, vomiting, regurgitation, hypersalivation, dysphagia and odynophagia should have the presence of a gastrointestinal foreign body (FB) as part of their differential diagnosis, where it is a frequent condition in the care of small animals. Most objects lodged in the esophagus, stomach, and proximal duodenum can be removed by upper digestive endoscopy, a curative, little invasive procedure. The objective of our study was to evaluate the physical aspects and location of esophageal and gastric FBs observed in 88 dogs and the age and breed of the affected animals, and to determine the success rate and eventual complications associated with the procedure as well. Materials, Methods & Results: Eighty-eight cases of dogs, males and females of varying ages and breeds, submitted to upper digestive endoscopy were selected because of suspicion of esophageal or gastric FBs. The endoscopic procedure aimed at confirming the diagnosis, whether or not followed by endoscopic removal of these objects. Prior to endoscopy, the animals had laboratory tests (blood count and serum biochemistry) and subsequently to the anesthetic protocols of choice for each case. Data including breed, age, type of constituent material and anatomical location of the FB, endoscopic procedure success rate and complications were recorded and descriptively evaluated. Of the 88 dogs evaluated, 60% (n = 53) were male and 40% (n = 35) female. According to the breed of the animals, 55% (n = 49) were small-breed dogs, 29% (n = 25) large-breed dogs, and 8% (n = 7) medium-breed dogs, and 8% were of mixed breed dogs, which could assume various sizes. Shih tzus accounted for 18% (n = 16) of the animals, Lhasa apso 8% (n = 7) and mixed breed 8% (n = 7), where these were the most frequently affected breeds. Regarding age, animals 1 to 5 years old represented 66% (n = 58) of the patients, and those 6 to 10 years old accounted for 20% (n = 18), while 11% of the dogs were over 10 years old (n = 10). Two animals (3%) had no information about their ages. Pieces of cloth were the most frequently found FBs, representing 20% (n = 20), followed by animal bones (19%) and fruit pits (10%). As for location, 78% (n = 69) of the FBs were located in the stomach and 22% (n = 19) in the esophagus. The success rate of endoscopic FB removal in this study was 83% (n = 73). In 76% (n = 67) of the animals, there were no complications due to the presence of FB in the upper gastrointestinal tract. The most frequent complications were esophageal ulcerations (n = 7) and inability to move the FB (n = 5) and adherences (n = 4). Discussion: The results showed that small-breed dogs, especially Shih tzus and Yorkshires, represented a larger number of cases, probably due to their popularity in Brazil, where the study was conducted. Males were more prevalent than females, and the most affected age was between 1 and 5 years, with emphasis on younger animals. There were more gastric FB cases compared to esophageal FB cases, which was related to the interval between ingestion of the object and veterinary care. Although not the most prevalent FB, the high rate of mango pits can be explained by the vast number of mango trees in the Federal District. There were few complications compared to the success of cases, indicating that endoscopy is the procedure of choice for the diagnosis and removal of FBs from the gastrointestinal tract.
Keywords: animal experiment; animal model; animal tissue; article; biochemistry; blood cell count; bone; Brazil; complication; controlled study; endoscopy; esophagus foreign body; esophagus ulcer; female; human; ingestion; laboratory test; male; mango; mongrel dog; nonhuman; Shih Tzu; stomach; surgery; upper gastrointestinal tract; veterinary medicine

Clinical observation of bronchoscopy alveolar lavage combined with thoracoscopy in the treatment of empyema in children - Yue, F.; Yang, Z.; Yang, F.; Liu, Y.; Zhao, L.; Chen, Z.; Gao, F. (Medicine (United States), 2019)
The objective of this study was to investigate the therapeutic effects of bronchoscopy alveolar lavage (BAL) combined with thoracoscopy in the treatment of empyema in children.Retrospectively analyzed 174 cases of pediatric empyema treated with thoracoscopy combined with BAL from January 2010 to December 2016 in our hospital. All the cases, according to admission order, were randomly divided into 2 groups, the control group (group A), which contained 89 cases, was treated with thoracoscopy; and the experimental group (group B), which contained 85 cases, was treated with BAL combined with thoracoscopy. The results of BAL treatment, the inflammatory indexes including body temperature, total leukocyte count in peripheral blood and CRP, and the therapeutic effect and prognosis including the days of antibiotic use, hospital stay, the incidence of thoracotomy and lobectomy were compared between the 2 groups.1.There was no significant difference in inflammatory indexes between the 2 groups: body temperature (oC), (39.06±0.047 and 39.08±0.050), P>.855; routine leukocyte count (10^9/L), (25.93±1.035 and 24.76±1.019), P>.425); C-reactive protein (mg/L), (128.7±6.653 and 138.6±7.53), P>.328.2.The results of BAL: hyperemia and edema was detected in trachea intima of all cases, including 32 cases of purulent secretion and ulcer, 21 cases of lumen deformation and 5 cases of foreign body.3.There were statistical significances in the curative effects of the control group and the experimental group: the duration of antibiotic use (days), (21.07±0.342 and 17.07±0.288), P<.0001); the average hospital stay (days), (22.91±0.347 and 18.79±0.287), P<.0001; secondary surgery (thoracotomy), 15 cases in the control group, 5 cases in the experimental group, P<.023; lung lobectomy (disability rate), 13 cases in the control group and 3 cases in the experimental group, P<.011.There was statistical difference in all the therapeutic indexes (P<.05).Bronchoscopy alveolar lavage combined with thoracoscopy has a higher success rate in the treatment of pediatric empyema, and is more comprehensive, safe and effective in controlling inflammation.
Keywords: article; bronchoalveolar lavage fluid; bronchoscopy; child; clinical observation; controlled study; edema; female; foreign body; human; hyperemia; intima; length of stay; lung lobectomy; major clinical study; male; pleura empyema; preschool child; priority journal; retrospective study; suppuration; therapeutic index; thoracoscopy; thoracotomy; trachea; ulcer

CONGENITAL BRONCHIAL ATRESIA: A RARE ENTITY - Hussain, M.; Halabiya, M.; Kadri, M.; Al-khateeb, A.; Sharma, H.; Miller, R. (Chest, 2019)
SESSION TITLE: Tuesday Medical Student/Resident Case Report Posters SESSION TYPE: Med Student/Res Case Rep Postr PRESENTED ON: 10/22/2019 01:00 PM - 02:00 PM INTRODUCTION: Congenital Bronchial Atresia (CBA) is a rare developmental anomaly, results from focal interruption of bronchus along with the formation of mucocele (mucus filled bronchus). It often presents in adulthood, as an incidental finding on radiography or recurrent pneumonia. Computed tomography (CT) angiogram of the chest remains the investigation of choice in the diagnosis of CBA while bronchoscopy should be done to rule out other etiologies of hyperinflation. Management of CBA is conservative for asymptomatic individuals while surgery is reserved for individuals who have the recurrent infection and severe symptoms. CASE PRESENTATION: 19-year-old male with no known past medical history presented to the ED for evaluation of dry cough and subjective fever for 5 days. Patient denied any shortness of breath, hemoptysis, chest pain, night sweats, weight loss or change in appetite. Patient was not taking any medication at home. Past surgical and family history was not significant. Patient denied smoking, alcohol use and any illicit drug abuse. On admission, he was afebrile, hemodynamically stable and saturating 99% on room air. In terms of labs, white cell count was elevated initially and then trended down; rest of the labs including molecular flu, pro-calcitonin, legionella antigen, mycoplasma antigen, respiratory syncytial virus PCR and blood culture were negative. Chest x-ray showed hyperlucency and decreased vascularity in the left upper lung zone along with consolidation in the left lower lobe. Patient was started on antibiotics and treated for community-acquired pneumonia. CT angiogram of the chest (1) showed round soft tissue density suggestive of mucoid impaction of the left bronchus likely mucocele along with hyperlucent left upper lobe and hypoplastic vasculature consistent with bronchial atresia (Figure 1 and 2). Bronchoscopy was normal which was done to rule out other etiologies like foreign body, bronchial adenoma, and lung cancer. V/Q scan showed no ventilation and perfusion to the majority of left upper lobe (figure 3). Patient showed signs of clinical improvement and discharged on oral antibiotics with outpatient follow up. DISCUSSION: CBA is a benign and rare entity with characteristic imaging finding resembling other serious underlying disease. Management can range from conservative measure to the surgery of an involved segment of the lung. Therefore, it is imperative to understand the nature of the disease and counsel the patient accordingly. CONCLUSIONS: Although benign entity, CBA should be kept in the differential especially in young patients who present with hyperinflation of one or more segment of lung which might cause compression atelectasis and/or pneumonia of the other adjacent segments as it presented in our case. CTA of the chest is usually the modality to diagnose with bronchoscopy and V/Q scan to guide further management. Reference #1: Psathakis K, Eleftheriou D, Boulas P, Mermigkis C, Tsintiris K. Congenital bronchial atresia presenting as a cavitary lesion on chest radiography: a case report. Cases J. 2009;2(1):17. Published 2009 Jan 7. Reference #2: Mahajan AK, Rahimi R, Vanderlaan P, Folch E, Gangadharan S, et al. (2017) Unique Approach to Diagnosing and Treating Congenital Bronchial Atresia (CBA): A Case Series. J Pulm Respir Med 7:402. DISCLOSURES: No relevant relationships by Anas Al-khateeb, source=Web Response No relevant relationships by mohammed halabiya, source=Web Response No relevant relationships by Muhammad Hussain, source=Web Response No relevant relationships by Muqueet Kadri, source=Web Response No relevant relationships by Richard Miller, source=Web Response No relevant relationships by Hari Sharma, source=Web Response
Keywords: antibiotic agent; antigen; calcitonin; endogenous compound; illicit drug; adult; alcohol consumption; ambient air; appetite; atelectasis; atresia; blood culture; body weight loss; bronchoscopy; cancer patient; cancer surgery; case report; case study; clinical article; community acquired pneumonia; compression; computer assisted tomography; conference abstract; congenital disorder; coughing; diagnosis; drug abuse; drug therapy; duck; dyspnea; family history; fever; follow up; foreign body; hemoptysis; human; Human respiratory syncytial virus; hyperinflation; influenza; Legionella; leukocyte count; lung adenoma; lung cancer; male; mucocele; Mycoplasma; night sweat; nonhuman; outpatient; perfusion; polymerase chain reaction; recurrent infection; smoking; soft tissue; thorax pain; thorax radiography; vascularization; young adult

Crushing the star: Esophageal foreign body extraction using dormia basket - Kilakkathi, S.; Shah, R.; Mulki, R.; Qayed, E. (American Journal of Gastroenterology, 2019)
INTRODUCTION: Sharp objects impacted in the esophagus require prompt endoscopic removal. Removal of sharp foreign bodies can be technically challenging and care should be taken to avoid inducing esophageal trauma during retrieval. CASE DESCRIPTION/METHODS: A 69-year-old female presented with sudden onset dysphagia and sharp chest pain for 1 day. While eating cake one day prior to arrival, she reported sudden, sharp, central chest pain followed by a sensation of food being stuck in her esophagus. Her physical examination was unremarkable with no abdominal tenderness. Her laboratory tests revealed normal complete blood count and chemistry. Chest x-ray revealed no acute abnormality. Upper endoscopy showed a sharp star-shaped foreign body (FB) approximately 2 cm in diameter (Figure 1). The FB was lodged in the distal esophagus, causing mucosal trauma. Due to the large size of the FB, insertion of an overtube was not considered to facilitate removal. An attempt was first made to extract the FB with rat-tooth forceps, but it could not be retrieved through the upper esophageal sphincter. Mucosal trauma was seen in the mid and proximal esophagus following this attempt. The FB was then advanced to the gastric antrum using a Roth net. Attempts to break the FB using argon plasma coagulation (APC) and a snare were unsuccessful due to the rigid nature of the FB. Subsequently, a 2T dual channel therapeutic gastroscope was inserted, and a Dormia stone retrieval basket was used to grasp the foreign body. Using the crushing power of the basket, the FB was successfully crushed and pulled inside the large therapeutic channel of the scope. The scope was withdrawn without additional mucosal trauma. The FB consisted of a star-shaped cake decoration with sharp edges (Figure 2). Following the procedure, the patient reported immediate improvement in her chest pain. DISCUSSION: This is a unique case wherein after the failure of conventional foreign body extraction devices, a Dormia stone retrieval basket was used to crush the object within the stomach allowing for safe retrieval. Gastroenterologists should consider this approach when retrieving irregularly-shaped, sharp, but pliable FBs. For the general public, care should be taken when eating food with non-edible decorations and toppers to avoid inadvertently swallowing or aspirating these objects. (Figure Presented).
Keywords: abdominal tenderness; aged; animal experiment; argon plasma coagulation; blood cell count; conference abstract; dysphagia; eating; endoscopy; esophagus foreign body; female; forceps; gastroenterologist; gastroscope; human; laboratory test; nonhuman; physical examination; rat; sensation; stomach antrum; stone retrieval basket; thorax pain; thorax radiography; tooth; treatment failure; upper esophagus sphincter

Periodontal flora isolated from pyogenic liver abscess in a retired dentist with hepatic metastasis of colon carcinoma - Chokshi, T.; Botti, E.; Arroyo-Mercado, F.; Likhtshteyn, M.; Hossain, N.; Doan Huynh, C.; Tello, D.; McFarlane, I.M. (American Journal of Gastroenterology, 2019)
INTRODUCTION: The association of Streptococcus milleri group with pyogenic liver abscess is well recognized. Streptococcus gordonii, however, is a bacterium not of the milleri group and is included among the colonizers of the periodontal environment as it has a high affinity for molecules in the salivary pellicle on tooth surfaces. Here, we describe a case where Streptococcus gordonii was isolated from a pyogenic liver abscess in a retired dentist with hepatic metastasis of colon carcinoma. The clinical features, work up, management, and significance are described. CASE DESCRIPTION/METHODS: An 85-year-old male with colon carcinoma status post hemicolectomy complicated by metastasis to the liver status post chemotherapy and resection presented to the ED with intermittent abdominal discomfort for 2 weeks. Laboratory values were significant for WBC count of 16,000 with a predominance of granulocytes at 85%. CT of the abdomen and pelvis demonstrated a large, 7.6 cm by 5.3 cm, collection in the liver, likely an abscess. Infectious Diseases was consulted and recommended initiation of Meropenem and Daptomycin, in addition to drainage of the collection. The suspected abscess was drained by IR and Streptococcus gordonii sensitive to Linezolid was isolated on bacterial culture. The patient was transitioned to IV Linezolid and Metronidazole given susceptibilities. The patient's WBC count then began trending upwards. CT of the chest exhibited a 1.2 cm by 0.7 cm loculated pleural effusion on the right side. The pleural fluid collection was drained and a chest tube was placed. Studies of the drainage revealed an exudative process, although gram stain and culture were negative. Repeat CT imaging one week later revealed reduction in the size of the liver abscess. The WBC count normalized to less than 10,000 and the patient was discharged with a two-week course of oral Linezolid and Metronidazole with close outpatient follow-up with Infectious Diseases and Oncology. DISCUSSION: Pyogenic liver abscesses are generally associated with enteric gram-negative bacilli, Streptococcus milleri group, Streptococcus pyogenes, and Staphylococcus aureus. Hepatic abscesses secondary to periodontal flora have not been demonstrated in the literature without direct trauma to the GI tract involving foreign bodies contaminated with these organisms. We propose a possible hematogenous route of infection likely associated with possible risk factors related to the patient's occupation as a dentist and history of dental manipulation.
Keywords: daptomycin; linezolid; meropenem; metronidazole; abdomen; abdominal discomfort; aged; bacterium culture; cancer patient; cancer surgery; case report; chest tube; clinical article; clinical feature; colon carcinoma; communicable disease; complication; conference abstract; dentist; drug combination; drug therapy; flora; follow up; foreign body; gastrointestinal tract; Gram staining; granulocyte; hemicolectomy; hospital discharge; human; human cell; leukocyte count; liver metastasis; male; nonhuman; occupation; outpatient; pelvis; periodontium; pleura effusion; pleura fluid; pyogenic liver abscess; risk factor; Staphylococcus aureus; Streptococcus gordonii; Streptococcus milleri; very elderly

Cerebral palsy-related mortality trends and disparities in the United States, 1968-2016 - Lins, L.; Remington, P.; Durkin, M. (Developmental Medicine and Child Neurology, 2019)
Background and Objective(s): Estimated life expectancy in persons with cerebral palsy (CP) is dependent on several factors, including the severity of gross motor functional limitations and the need for gastrostomy feeding. The objectives of our study were to describe mortality trends and disparities and identify preventable causes of death in persons with CP listed as the underlying cause of mortality. Study Design: Retrospective Cohort Study. Study Participants and Settings: The CDC WONDER Underlying Cause of Death database contains mortality and population counts for all U.S. counties. Data are based on death certificates for U.S. residents. Each death certificate contains a single underlying cause of death (UCOD), up to twenty additional contributing causes, and demographic data. This public health information is de-identified and collected into the CDC WONDER database which can be queried for public health statistical reporting and analysis. Materials and Methods: Using the CDC WONDER database for all US deaths, mortality trends with the UCOD of CP were examined based on age, gender and race for the years 1968-2016. To describe changes over time in the age at death in individuals with CP as the UCOD, the percentage of deaths in each age group (<10, 10-19, 20-34, 35-64, >65y) and rates (per 100 000) was compared over time, overall and stratified by race and gender. The CDC's Multiple Cause of Death database, available for the period 1999-2016, was used to describe the frequency of other contributing causes of death where CP was listed as an UCOD. Results: The predominant age at death in individuals with CP shifted over time from <10 years of age during the period 1968-1995 to the 35-64 year age group during the period 1996-2016. During the period 1999-2015, age-adjusted mortality with CP as an UCOD was higher for males (0.55) than females (0.42) and for black (0.65) relative to white (0.47) individuals. In analyses stratified by age group, the excess mortality with CP as an UCOD for black individuals was present only for the age range of birth through 54 years; for ages 55 years and older, CP-related mortality was higher for white relative to black individuals. Overall, the leading contributing causes of persons with CP as an UCOD, included several preventable causes; namely, pneumonia, pneumonitis due to food and vomit, and foreign body in the respiratory tract. Conclusions or Significance: The shift over time in the age at death with CP as an UCOD, from infancy and childhood to older ages, is consistent with improvements in the care and survival of infants and young children with CP. At the same time, racial disparities persist and many of the leading contributing causes of death in individuals with CP in recent years are preventable, pointing to the need for public health strategies to improve outcomes for individuals with CP. These findings point to potential strategies and public health interventions needed to further improve the life-expectancy and quality of life of all people with CP.
Keywords: adult; cause of death; cerebral palsy; child; child death; cohort analysis; conference abstract; controlled study; death certificate; demography; female; foreign body; gender; human; infancy; infant; life expectancy; male; pneumonia; public health; quality of life; race; resident; respiratory system; retrospective study; United States

Prognostic factors associated with visual outcome of salvageable eyes with posttraumatic endophthalmitis - Lu, X.; Xia, H.; Jin, C.; Chen, W.; Siu-Chun Ng, D.; Yan, H.; Chen, H. (Scientific reports, 2019)
The purpose of this study is to evaluate the prognostic factors associated with visual outcomes in the salvageable eyes with posttraumatic endophthalmitis. We retrospectively reviewed the medical records of all patients diagnosed with posttraumatic endophthalmitis in our hospital between 2008 and 2015. The following information was collected: age, sex, etiology, past medical history, clinical manifestations, wound location, microbiology, blood leukocyte counts, types of interventions, initial visual acuities and final visual acuities. Univariate and multivariate analyses were used to explore the factors associated with final best-corrected visual acuity. In total, 98 eyes of 98 patients were included in our study. Fifty-seven eyes underwent vitrectomy, 27 of them had silicone oil tamponade, 38 eyes received intravitreal ceftazidime only and 3 eyes received intracameral ceftazidime. In univariate analysis, poor initial visual acuity, presence of intraocular foreign body, number of intravitreal injections, retinal detachment and Zone 3 injury were associated with poor visual outcome. In multivariable analysis, poor initial visual acuity, presence of intraocular foreign body and number of intravitreal injections were independently associated with poor visual outcome. The silicone oil group had fewer repeated intravitreal injections than the group without oil tamponade. We concluded that the visual outcome of salvageable eyes with posttraumatic endophthalmitis is associated with initial visual acuity, presence of intraocular foreign body and number of intravitreal antibiotic injections.
Keywords: antiinfective agent; ceftazidime; silicone oil; adolescent; adult; aged; child; drug effect; endophthalmitis; female; human; isolation and purification; male; microbiology; middle aged; pathology; preschool child; prognosis; retina detachment; retrospective study; Staphylococcus epidermidis; visual acuity; vitrectomy; young adult

Electroretinograms before and after extraction of large intraocular iron foreign body - Kumagai, T.; Matsumoto, C.S.; Kimura, I.; Shinoda, K. (American Journal of Ophthalmology Case Reports, 2019)
Purpose: We present our findings in a case with an intraocular foreign body in which the electroretinographic (ERG) findings were useful. Observations: A 37-year-old man was injured by an iron fragment that penetrated into his left eye through the cornea. His visual acuity was counting fingers, and a traumatic cataract prevented an examination of the fundus. B-mode ultrasonography showed a stick-like foreign body of approximately 14 mm in length in the eye. Preoperative ERGs with a contact lens electrode showed reduced responses with many blinking artifacts. Lensectomy and pars plana vitrectomy were performed and a fragment of a wire brush was seen embedded in the superior nasal retina which was removed. The decimal visual acuity improved to 1.2 two weeks later. The postoperative ERG performed with a skin electrode showed reduced responses in the injured eye. Conclusions and importance: We recommend that the physiology of the retina be assessed by recording ERGs with a skin-type electrode as soon as possible after a traumatic injury to the eye.
Keywords: contact lens; electroretinograph; skin electrode; antibiotic agent; iron; adult; article; B scan; best corrected visual acuity; blinking; case report; clinical article; clinical assessment; computer assisted tomography; cornea disease; cornea injury; corneoscleral wound; dark adaptation; electroretinogram; electroretinography; human; intraocular foreign body; intraocular pressure; large intraocular iron foreign body; lensectomy; male; medical history; nasal retina; pars plana vitrectomy; perimetry; traumatic cataract; visual acuity; vitreous hemorrhage; RETeval

The use of alfentanil in a modified rapid sequence induction for general anaesthesia caesarean sections: is this doing any harm? - Farrimond, R.E.; Roberts, F.; Wallis, R.; Brimfield, L. (International Journal of Obstetric Anesthesia, 2019)
Introduction: The National Audit Project 5, whilst demonstrating an overall low risk of accidental awareness under general anaesthesia (AAGA), highlighted an incidence of 1:670 in patients undergoing general anaesthesia (GA) for caesarean section (CS), more than any other surgical category. 1 There is a higher risk of difficult intubation (incidence 1:300) in the obstetric patient, and the recent Every Baby Counts report highlights the importance of induction preparation.2, 3 Our tertiary obstetric centre has recently recommended routine addition of a bolus of intravenous alfentanil as part of a modified rapid-sequence induction (RSI), aiming to reduce these complications. We conducted a multi-speciality service evaluation project to establish whether this modification in anaesthetic technique had any adverse neonatal effects, compared with traditional RSI technique. Methods: Data were collected retrospectively between July 2017 and April 2018. Maternal data were collected using electronic operative records and recorded alfentanil usage. Neonatal data were collected using electronic recording systems. All patients undergoing emergency CS under GA were included. RSI method included thiopental and suxamethonium with the potential addition of alfentanil 0.5-2 mg (mean dose 1 mg). Results: Ten neonates in the alfentanil group were premature as were eight in the non-alfentanil group; none were include in further analysis. Nine term babies required admission to the neonatal unit; five were exposed to alfentanil and four were not. Apgar scores at 1 and 5 min were significantly lower in the alfentanil group (P=0.02). In category 1 caesarean section term neonates, 14/18 (77%) babies exposed to alfentanil required resuscitative input. One neonate required CPR. There were no infant deaths. 16/28 (57%) babies not exposed to alfentanil required resuscitative measures. Discussion: Results suggest alfentanil was associated with lower Apgar scores and an increased requirement for additional brief medical intervention, particularly stimulation and inflation breaths at time of delivery but significantly, that this did not lead to additional unplanned neonatal admissions or harm. Furthermore, babies included in this project were already deemed to be at risk of requiring initial medical assistance, such is the nature of emergency operative delivery, and additional induction opioid does not seem to have increased this risk. We are therefore reassured that the addition of alfentanil is unlikely to worsen neonatal outcomes whilst potentially benefiting the mother.
Keywords: alfentanil; opiate; suxamethonium; thiopental; Apgar score; awareness; breathing; cesarean section; child death; complication; conference abstract; drug therapy; emergency; female; general anesthesia; genetic susceptibility; human; incidence; infant; intubation; major clinical study; medical care; newborn; obstetric patient; retrospective study

An illusion of vesical calculus - David, D.; Jeyasekharan, D. (International Journal of Urology, 2019)
Background and objectives Intra-vesical foreign bodies are rare; it may be a result of iatrogenic injury, sexual abuse, self-insertion or following assault. Their presentation may be late and wide varieties of foreign bodies have been reported. Materials and methods A 30 year old female presented with complaints of dysuria, incontinence and hematuria for 3 years. She gives a history of C-section 3 years back following which she developed these symptoms. She was evaluated and found to have large vesical calculus. Results Patient underwent cystoscopy proceed open cystolithotomy, on retrieval the stone was found to be a calcified surgical sponge; postoperative period was uneventful. She improved symptomatically and she is kept on regular follow-up. Conclusion We report this case for its rarity and would stress on careful gauze/instrument count during any open surgical procedure.
Keywords: adult; bladder stone; case report; clinical article; conference abstract; cystoscopy; dysuria; female; follow up; foreign body; hematuria; human; iatrogenic disease; illusion; incontinence; information retrieval; postoperative period; stress; surgical sponge; surgical technique

Spontaneous pneumothorax in cocaine users - Ciriaco, P.; Rossetti, F.; Carretta, A.; Sant'Angelo, M.; Arrigoni, G.; Negri, G. (QJM : monthly journal of the Association of Physicians, 2019)
BACKGROUND: Pneumothorax is one of the respiratory toxic effects of cocaine inhalation. The literature counts several cases, some associated to other respiratory conditions such as pneumomediastinum, haemoptysis and others not requiring surgical treatment. AIM: We present a series of nonHIV cocaine-inhaler subjects who underwent video-assisted thoracoscopic surgery (VATS) for isolated spontaneous pneumothorax. DESIGN: Nine subjects, with a mean age of 24 ± 4 years, admitting cocaine inhalation, developed spontaneous pneumothorax and underwent 10 surgical treatments by means of VATS, at our Institution. RESULTS: Previous pneumothorax occurred in six cases episodes ranged from 0 to 5 (mean 1.6 ± 1.6). Chest computed tomography (CT) scan showed abnormalities in seven cases. All subjects underwent lung apicectomy, apical pleurectomy and mechanical pleurodesis. Seven subjects had also bullectomy. In all cases the visceral pleura was partially covered by fibrinous exudate. Histology of the lung showed small foreign body granulomatous inflammation in fibrotic and/or emphysematous pulmonary parenchyma. Relapse of pneumothorax occurred in one subject at 60 days and it was surgically treated. Mean follow-up was 150 ± 38 months (range 120-239). All subjects are now well, with no evidence of pneumothorax. CONCLUSIONS: Spontaneous pneumothorax in cocaine-inhaler subjects is a reality of which physicians need to be aware. Chest CT scan might not reveal abnormalities. Macroscopically the lung might presents bullae and/or peculiar visceral pleura. Foreign body granulomas observed in the specimens suggest that the particulate component of inhaled substances can injure the lung. Surgical treatment of the bullous disease and mechanical pleurodesis can provide a long-term follow-up without relapse of pneumothorax.
Keywords: cocaine; adult; cocaine dependence; complication; female; foreign body; human; inhalational drug administration; Italy; male; pathology; pneumothorax; recurrent disease; retrospective study; treatment outcome; video assisted thoracoscopic surgery; x-ray computed tomography; young adult

Modern visual and clinical outcomes of vitrectomy after open globe injury - Marmalidou, A.; Rossin, E.; Kim, L.A.; Wu, D.M.; Miller, J.B. (Investigative Ophthalmology and Visual Science, 2019)
Purpose: To explore the clinical features, visual outcomes, and prognostic factors of visual impairment of eyes that underwent vitrectomy after open globe injuries (OGIs). Methods: A retrospective review was conducted of consecutive cases that underwent pars plana vitrectomy (PPV) after OGIs at Massachusetts Eye and Ear (MEE) over 2 years. Demographic and clinical data including age, gender, type and zone of injury, presenting visual acuity (VA), vitreous hemorrhage (VH), hemorrhagic choroidals (HC), retinal detachment (RD), retinal incarceration (RI), length of follow-up, and final VA were recorded. Results: 37 eyes of 37 patients (27 male) presented with a mean age of 50.6 yo (19-88) and a mean follow-up of 438 days (89-1293). Types of injury included blunt rupture (48.7%), penetrating laceration (29.7%), and intraocular foreign body (21.6%). The injuries requiring vitrectomy were most often in zones II and III, with only 7 (27%) presenting with isolated zone I injuries. The majority of eyes had severe vision loss prior to PPV, with VA better than counting fingers in only 27%. No eyes were deemed inoperable or required subsequent enucleation. Final retinal attachment rate was 82% at last follow-up. Overall, final VA showed significant improvement with 62.2% better than counting fingers and 37.8% better than 20/50. We further stratified eyes into 2 groups based on the presence of RD at the time of initial PPV: group 1 (n=18) had no RD while group 2 (n=19) did have an RD. In group 2 with RD, there was a statistically significant improvement in average VA (logMAR 3.08 at presentation compared to 1.4 at final follow-up, p=0.00025). Those who re-detached had worse final VA (median logMAR 2.7 compared to 1.35, p=0.06), and a strong predictor of re-detachment was the appearance of PVR after the first vitrectomy (p=0.001), while the presence of PVR before the first vitrectomy did not predict ultimate re-detachment (p=1). Presence of retinal incarceration and funnel RD trended toward higher risk of re-detaching and worse final VA, but did not reach statistical significance. Conclusions: OGIs often require retina surgery after the initial open globe repair. Modern pars plana vitrectomy can lead to globe salvage and improvement in vision in even the most severe cases, suggesting that in select cases, vitrectomy after OGR may be warranted.
Keywords: adult; blindness; choroid; clinical article; clinical outcome; conference abstract; controlled study; ear; female; finger; follow up; gender; human; intraocular foreign body; laceration; male; Massachusetts; middle aged; outcome assessment; pars plana vitrectomy; retina detachment; retina surgery; retrospective study; rupture; statistical significance; visual acuity; vitrectomy; vitreous hemorrhage

The Effect of Radiofrequency Technology on Time Spent Searching for Surgical Sponges and Associated Costs - Steelman, V.M.; Schaapveld, A.G.; Storm, H.E.; Perkhounkova, Y.; Shane, D.M. (AORN journal, 2019)
Retained surgical items (eg, sponges, instruments) remain the most frequently reported sentinel events. The primary strategy for preventing retained sponges is the sponge count. Reconciling sponge counts is time consuming and can extend the duration of operative and other invasive procedures. The primary objective of this observational study was to evaluate the effect of a radiofrequency (RF) surgical-sponge detection system on time spent searching for surgical sponges. The study included 27,637 procedures during nine months before and after implementing an RF surgical-sponge detection system. After implementation of the system, time spent searching for sponges was reduced by 79.58%, the percentage of unreconciled counts was reduced by 71.28%, and time spent using radiography to rule out a retained sponge was reduced by 46.31%. This resulted in a reduction of costs. These findings should be used as part of a comprehensive cost analysis of alternative methods when evaluating RF sponge detection technology.
Keywords: diagnostic imaging; foreign body; human; postoperative complication; procedures; radio frequency identification device; sentinel surveillance; surgical sponge

BD-2 and BD-3 increase skin flap survival in a model of ischemia and Pseudomonas aeruginosa infection - Casal, D.; Iria, I.; Ramalho, J.S.; Alves, S.; Mota-Silva, E.; Mascarenhas-Lemos, L.; Pontinha, C.; Guadalupe-Cabral, M.; Ferreira-Silva, J.; Ferraz-Oliveira, M.; Vassilenko, V.; Goyri-O'Neill, J.; et al. (Scientific reports, 2019)
The main aim of this work was to study the usefulness of human β-defensins 2 (BD-2) and 3 (BD-3), which are part of the innate immune system, in the treatment of infected ischemic skin flaps. We investigated the effect of transducing rat ischemic skin flaps with lentiviral vectors encoding human BD-2, BD-3, or both BD-2 and BD-3, to increase flap survival in the context of a P. aeruginosa infection associated with a foreign body. The secondary endpoints assessed were: bacterial counts, and biofilm formation on the surface of the foreign body. A local ischemic environment was created by producing arterialized venous flaps in the left epigastric region of rats. Flaps were intentionally infected by placing underneath them two catheters with 105 CFU of P. aeruginosa before the surgical wounds were hermetically closed. Flap biopsies were performed 3 and 7 days post-operatively, and the specimens submitted to immunohistochemical analysis for BD-2 and BD-3, as well as to bacterial quantification. Subsequently, the catheter segments were analyzed with scanning electron microscopy (SEM). Flaps transduced with BD-2 and BD-3 showed expression of these defensins and presented increased flap survival. Rats transduced with BD-3 presented a net reduction in the number of P. aeruginosa on the surface of the foreign body and lesser biofilm formation.
Keywords: antiinfective agent; beta defensin; DEFB103A protein, human; DEFB4A protein, human; adverse event; animal; complication; disease model; drug effect; drug therapy; gene therapy; gene vector; genetic transduction; genetics; graft survival; human; ischemia; male; metabolism; microbiology; Pseudomonas aeruginosa; Pseudomonas infection; rat; skin transplantation; surgical flaps; Wistar rat

Leaving a foreign object in the body of a patient during abdominal surgery: still a current problem - Szymocha, M.; Pacan, M.; Anufrowicz, M.; Jurek, T.; Rorat, M. (Polski przeglad chirurgiczny, 2019)
INTRODUCTION: Leaving a foreign object (retained surgical item, or RSI) during surgery involving the abdominal cavity and pelvis minor is a relatively frequent, underestimated phenomenon which is dangerous to the health of the patient and the legal security of the medical personnel. These adverse events are easy to avoid through the use of appropriate means of prevention. The aim of the present paper is the collection of epidemiological data and determination of risk factors, symptomatology, health effects, and prevention methods associated with RSIs. MATERIAL AND METHODS: Analysis of global scientific publications in the databases PubMed, ClinicalKey, Google Scholar, ScienceDirect, and Scopus related to the subject of RSIs. RESULTS: The frequency of RSI incidents ranges from 1 to 10 in 10,000 surgeries, which results in at least one case in an average multispeciality hospital on a yearly basis. The items most frequently left behind include soft foreign objects, such as swabs and bandages (90%). Risk factors include emergency surgical procedures, high patient BMI, significant loss of blood during surgery, and neglect in counting the material and surgical tools. The postoperative course, although in many cases asymptomatic, may be complicated by inflammation, bleeding, or perforation, leading to the necessity of a second operation and, in 2 to 4% of cases, even ending in death. Imaging tests are effective diagnostic tools. Effective methods of preventing RSIs are based on checklists and systems for counting and monitoring the location of material and tools. CONCLUSIONS: The globally occurring problem of RSIs requires education of the operating block personnel regarding risk factors and identification with elimination of adverse events of this type. Diagnostics based on imaging should take into account non-specific complaints resulting from a possible oligosymptomatic course. An RSI should not be regarded as a medical error. Changes in the perception of the phenomenon aim aimed at minimising the legal liability of the staff in the event of leaving a foreign object in a patient's body.
Keywords: abdominal cavity; foreign body; human; medical error; patient care; patient safety; prevention and control; risk factor; surgery; surgical equipment

Keep your eye on thrombi in renal cell carcinoma patients - Patel, K.G.; Yin, D.; Schlair, S. (Journal of General Internal Medicine, 2019)
Learning Objective #1: Outline the differential diagnosis of an intracardiac mass in renal cell carcinoma Learning Objective #2: Discuss differentiation and management of bland versus tumor thrombi CASE: A 66 year old man with stage IV renal cell carcinoma (RCC), a non-occlusive IVC tumor thrombus and end-stage renal disease on he-modialysis via a right internal jugular permacath was admitted with a 5-day history of fever and weakness. He had a temperature of 99.3, a WBC count of 17.2 and was found to have Klebsiella bacteremia. Physical exam revealed a new systolic murmur, which prompted echocardiogram, showing a large, mobile, multi-lobed structure in the right atrium likely attached to the permacath, suggestive of thrombus (could not rule out vegetation). Antibiotics and heparin were started. CT showed a chronic IVC tumor thrombus that did not extend into the SVC or right atrium, suggesting the right atrial mass was not tumor thrombus. Permacath was removed and to definitively rule out embolization of the right atrial thrombus, CTPE was performed, revealing a right lower lobe pulmonary embolism and warfarin was initiated. IMPACT/DISCUSSION: RCC is a highly vascular tumor that can invade through the renal vein and into the IVC, with 10-15% of cases resulting in tumor thrombus formation. Less commonly (1%), the tumor may extend into the right cardiac chamber. Accurate differentiation of bland from tumor thrombus is crucial for proper management. While both bland and tumor thrombi present as vessel filling defects, a malignant thrombus has continuity with the primary tumor, enhancement and vessel expansion on CT or MRI. Because a bland thrombus Results from IVC compression by a renal mass, it presents as vessel narrowing on imaging. While nephrectomy and thrombectomy treat tumor thrombi, anticoagulation is used for bland thrombi. Though tumor thrombus dis-lodgement is a known complication of thrombectomy, the development of tumor emboli outside the lung in the absence of such manipulation is unclear. The differential diagnosis of an intracardiac mass in a septic RCC patient can span different etiologies including infectious (vegetation), malignant (primary tumor, metastases, tumor thrombus) and hematologic (bland thrombus). As imaging was strongly suggestive of a thrombus, several key details pointed to bland over tumor thrombus. Risk factors for thrombosis, including a hypercoagulable state due to malignancy as well as foreign body effect from the IVC tumor thrombus and permacath, and attachment of the mass to the permcath raised our suspicion for a bland thrombus. Moreover, lack of IVC thrombus extension into the SVC and right atrium suggested the mass was more likely bland thrombus. Thus, anticoagulation and antibiotics were given empirically. Conclusion: This case demonstrates the importance of reviewing all clinical data when narrowing the differential diagnosis for an intracardiac mass. Moreover, identification of thrombi in RCC patients warrants subsequent differentiation of bland from tumor thrombus for effective management.
Keywords: antibiotic agent; heparin; warfarin; aged; anticoagulation; bacteremia; blood clotting; body weight; cancer patient; cancer staging; cancer surgery; case report; clinical article; complication; compression; conference abstract; dialysis catheter; differential diagnosis; differentiation; drug therapy; echocardiography; end stage renal disease; fever; foreign body; heart right atrium; human; hypercoagulability; kidney vein; Klebsiella; learning; leukocyte count; lung agenesis; lung embolism; male; nephrectomy; nonhuman; nuclear magnetic resonance imaging; physical examination; primary tumor; renal cell carcinoma; risk factor; surgery; systolic heart murmur; thrombectomy; tumor thrombus; vascular tumor; vegetation; weakness

Occult foreign body aspiration presenting as recurrent pneumonia with complicated parapneumonic effusion - Ijaz, S.H.; Hussain, S.; Christian, F.G.; Youness, H. (American Journal of Respiratory and Critical Care Medicine, 2019)
Foreign body aspiration (FBA), if retained and undiagnosed can lead to recurrent post-obstructive pneumonia, atelectasis or bronchiectasis. Aspiration is of concern in children, elderly and adults with neurological deficits. FB aspiration in healthy young adults without neurological or psychiatric disorders is rare. We report a case of recurrent pneumonia with complicated loculated parapneumonic effusion secondary to unknown aspiration event of a plastic foreign body. A 33-year-old male with a history of tobacco use, family history of lung cancer presented with fever, productive cough, dyspnea and right-sided pleuritic chest pain. He reported multiple episodes of pneumonia in the last 3 months. He was afebrile and hemodynamically stable on presentation. Reduced breath sounds were auscultated over the right basal area with dullness to percussion. Complete blood count revealed leukocytosis 30,000/mm3with left shift. Chest X-ray revealed a large right-sided pleural effusion. Computerized tomography (CT) chest demonstrated a large right-sided pleural effusion with evidence of loculation and associated right middle and lobe atelectasis. He was empirically started on vancomycin, piperacillin/tazobactam and levofloxacin. A right-sided pigtail chest tube was placed with pleural fluid (PF) sample consistent with complicated exudate (pH 7.10, LDH 743 units/L). PF cultures remained negative. Dornase alpha and alteplase was used to lyse the septations with total drainage of around 3.5 liters of pleural fluid with partial lung expansion. Flexible bronchoscopy with bronchoalveolar alveolar lavage (BAL) to evaluate persistent lower lobe atelectasis showed concerns of foreign body (FB) with surrounding granulation tissue. BAL fluid cultures and endobronchial biopsies were unrevealing. Rigid bronchoscopy revealed a foreign body covered by reactive tissue partially occluding the right lower lobe bronchus (RB). Pathologic analysis revealed reactive granulation tissue covering 0.8 cm plastic material Patient denied any memory of the event of aspiration. The diagnosis of FBA requires a high degree of clinical suspicion in healthy adults as sign and symptoms can be subtle. Patients may report the aspiration event or recall on history. CXR and CT scan can help visualize the FB if it is radio-opaque. Despite no recall of history or imaging concerns, recurrent pneumonia in the same location and persistent atelectasis raised FBA concerns in our case. Flexible bronchoscopy is the intervention of choice for endobronchial FB removal, with RB reserved for failed attempts or proximal obstruction. Therefore, FBA although uncommon in a healthy individual should be considered in individuals with a chronic cough, recurrent pneumonia or imaging evidence of a mass lesion.
Keywords: alteplase; dornase alfa; levofloxacin; piperacillin plus tazobactam; vancomycin; abnormal respiratory sound; adult; aged; atelectasis; blood cell count; body weight; bronchiectasis; cancer recurrence; case report; chest tube; chronic cough; clinical article; computer assisted tomography; conference abstract; drug combination; dyspnea; family history; fever; fiberoptic bronchoscopy; foreign body aspiration; granulation tissue; human; human tissue; lavage fluid; leukocytosis; lung alveolus; lung cancer; male; memory; mental disease; neurologic disease; obstruction; percussion; pleura effusion; pleura fluid; pneumonia; surgery; thorax pain; thorax radiography; tobacco use

Prepubertal Bleeding as a Presenting Symptom of Von Willebrand Disease: A Case Report - Chambers, C.N.; Adeyemi-Fowode, O. (Journal of Pediatric and Adolescent Gynecology, 2019)
Background: Von Willebrand disease (VWD) affects approximately 1% of the population and is often diagnosed after the presentation of mucocutaneous bleeding. While heavy menstrual bleeding can be the first sign of a bleeding disorder (BD), prepubertal vaginal bleeding (VB) is more commonly caused by precocious puberty, sexual abuse, foreign body, or vaginitis. We present the case of VB in a prepubertal child who was subsequently diagnosed with VWD. Case: A 7-year-old girl with eczema and constipation presented to clinic reporting VB for 2 days. She denied pain, trauma, exogenous hormone exposure, sexual abuse, or placing objects in the vagina. On exam, she was Tanner stage II for breasts and pubic hair. Brown streaks of dried blood were noted in her underwear, but external genital exam was without abrasions, scars, or bruises. Denuded skin was noted within the gluteal cleft. Given her history, a mild steroid cream was prescribed along with a bowel regimen. Plan was for an exam under anesthesia (EUA) if persistent VB occurred. Workup for precocious puberty was negative. Despite resolution of gluteal skin changes, she presented to the emergency center twice in the following month with complaints of VB and new periumbilical pain. Plan was made for an exam under anesthesia (EUA) and vaginoscopy, but she was lost to follow up for 4 months. Upon representation, symptoms persisted and she was taken for surgery as planned. Vaginoscopy was without foreign body or VB, but was notable for increased mucosal vascularity with a friable appearance. Upon removal of the laryngeal mask airway, she was noted to have significant bleeding from her buccal mucosa and gums. This prompted collection of a coagulation panel, a complete blood count, and a VWD panel. Her VWD panel was abnormal with low VWF Antigen and low VWF Activity Ib. Referral to hematology was placed with subsequent diagnosis of type I VWF. Additional testing revealed mild iron deficiency and her Stimate challenge was consistent with a therapeutic response. She was counseled against NSAID use, and instructed to use stimate for any minor bleeding at home and Humate for any future procedures. Comments: VWD is a BD that causes mucous membrane and skin bleeding symptoms, hemorrhage with surgery and other hemostatic challenges. Prompt and accurate diagnosis in the pediatric and adolescent population is important considering the top cause of morbidity and mortality in this age group is accidental trauma. We present a case of prepubertal VB leading to a diagnosis of VWD. To our knowledge, this is the first time that this type of presentation has been described. It is important to keep BD on the differential especially for unexplained prepubertal VB to aid in prompt diagnosis.
Keywords: antigen; desmopressin; endogenous compound; hormone; nonsteroid antiinflammatory agent; steroid; von Willebrand factor; abrasion; adolescent; anesthesia; bleeding disorder; blood cell count; breast; buccal mucosa; case report; child; clinical article; conference abstract; constipation; contusion; diagnosis; drug therapy; eczema; emergency health service; female; follow up; foreign body; girl; hair; hematology; human; intestine; iron deficiency; laryngeal mask; menorrhagia; morbidity; mortality; pain; patient referral; precocious puberty; scar; school child; sexual abuse; skin bleeding; surgery; treatment response; vagina bleeding; vaginitis; vascularization; von Willebrand disease

The sucked surgical sponge: Rare case of Gossypiboma after vaginal hysterectomy - Oehme, F.; Rühle, A.; Stickel, M.; Metzger, J.; Gass, J.-M. (Clinical Case Reports, 2019)
Retained surgical material needs to be a possible differential diagnosis for patients presenting with unspecific abdominal pain after especially cavitary emergency surgery. Even though international standard checklists concerning sponge handling and counting exist, RSM could never be ruled out completely.
Keywords: surgical sponge; C reactive protein; abdominal pain; adult; aged; article; blood pressure; cancer chemotherapy; case report; clinical article; clinical examination; clinical outcome; computer assisted tomography; differential diagnosis; echography; female; follow up; foreign body; gossypiboma; human; intestine sound; leukocytosis; mastectomy; priority journal; temperature; vaginal hysterectomy; very elderly

Twenty years later… A story of intra-thoracic textiloma - Lebas, L.; Dupuis, M.; Solovei, L.; Jaffro, M.; Grunenwald, E.; Pontier-Marchandise, S.; Dahan, M.; Didier, A. (Revue des Maladies Respiratoires, 2019)
Introduction: Intrathoracic textiloma is a rare complication possibly leading to misdiagnosis. It could present as haemoptysis, lung abscess, pseudo-tumour or a chronic cough. Case report: A 65-year-old patient with a history of multiple cardiac problems and needing long-term anticoagulation, complained since 2007 of recurrent haemoptysis of increasing abundance, the etiological investigation of which was negative. A thoracic CT-scan revealed a lesion in the lingula in contact with the pericardial plates of an implanted automatic defibrillator dating from 1989. In 2016, after two failures of arterial embolization, a diagnostic and therapeutic surgical exploration was undertaken on this patient who was a high operative risk. A segmental resection revealed an intra-pulmonary textiloma on pathological examination. Conclusion: The diagnosis of intrathoracic textiloma remains rare and its late presentation is non specific. Radiological imaging with a CT-scan and/or MRI could lead to the diagnosis. Surgery remains the reference treatment for the diagnosis and cure of intrathoracic textiloma with pathological examination, essential for confirmation. A means of prevention has to be developed because swab count is not totally reliable.
Keywords: implantable cardioverter defibrillator; adult; anticoagulant therapy; arterial embolization; article; case report; clinical article; computer assisted tomography; foreign body; hemoptysis; histopathology; human; intrathoracic textiloma; middle aged; thorax disease; thorax surgery

Ingested metallic foreign body impacted in the vermiform appendix presenting as acute appendicitis: Case report - Mohammed, A.A.; Ghazi, D.Y.; Arif, S.H. (International Journal of Surgery Case Reports, 2019)
Introduction: Ingestion of foreign bodies and their impaction at the lumen of the appendix is a very rare finding and only few cases have been reported all over the world. A variety of metallic foreign bodies when ingested may be lodged in the lumen of the appendix such as screws, bird shots, and needles. This is called in most literatures as foreign body appendicitis. Case presentation: A 4-year-old boy with history of an accidental ingestion of a metallic nail presented to the emergency department one week later with right iliac fossa pain and one attack of vomiting. During abdominal examination there was tenderness and rebound tenderness at the right iliac fossa. Plain abdominal X-ray showed the metallic nail in the region of the right iliac fossa. Ultrasound examination was normal apart from tenderness of putting the probe on the right lilac fossa. The white blood cell counts were 14,000 cell per microliter. During surgery the nail was found to be impacted inside the lumen of the vermiform appendix causing inflammation of the appendix. Appendicectomy done and the patient discharged on the third day in a good general condition. Conclusion: Acute appendicitis may be caused by a variety of causes including ingested foreign bodies if impacted in its lumen. When the patient has signs of generalized peritonitis it is important to exclude bowel perforation. The surgery can be done by the open surgery or laparoscopically.
Keywords: abdominal radiography; abdominal tenderness; acute appendicitis; appendectomy; appendix; article; case report; child; clinical article; clinical outcome; foreign body; human; ingestion; leukocyte count; male; preschool child; priority journal; vomiting

Gossypiboma (Textiloma) in the Abdominal Preperitoneal Space Following Cesarean Section: A Case Report with Literature Review - Dhar, H.; Sashidharan, P.; Razek, Y.A. (Journal of SAFOG, 2019)
Retention of surgical items is a preventable complication. The foreign body may be symptomless or migrate in and around the abdomen causing fistula formation, bowel obstruction and perforation. Some major causes responsible for this complication are emergency, prolonged, difficult surgeries associated with obesity, poor communication with an error in sponge and instrument counting. Frequency being 1/1000 to 1/32672 surgeries in the recent review of the literature. Definitive treatment for this condition is surgical removal either by laparotomy or laparoscopically. We report a case whose cesarean section was done in a secondary care hospital for brow presentation and later referred to us after two months with complaints of pain and swelling in the abdomen. Entrapment of a surgical sponge in the preperitoneal space of the abdomen was noted and later removed surgically. This case highlights the need for all health care professionals to be vigilant and cautious intraoperatively as any lapse in mop and instrument counting may be disastrous for both the patient as well as the healthcare team. There is a growing need for patient safety hospital initiation to avoid such errors by surgical teams. The aim of presenting and reporting this case is to increase awareness among healthcare workers to avoid such lapses causing great medical morbidity with medicolegal complications.
Keywords: surgical sponge; abdominal abscess; abdominal pain; abdominal radiography; abdominal viscera; abdominal wall; adenofibroma; anemia; article; case report; cesarean section; cholelithiasis; clinical article; echography; Escherichia coli; female; foreign body; gossypiboma; hepatomegaly; human; inflammation; laparotomy; palpation; patient history of cystectomy; rectus abdominis muscle; retained instrument; secondary care center; surgical wound; x-ray computed tomography

Refinement of estimates of mortality risk using the Radiologic Severity Index in hematologic malignancy patients with respiratory syncytial virus infection - Sheshadri, A.; Karimipour, M.; Vakil, E.; Bashoura, L.; Godoy, M.; Arain, M.H.; Evans, S.E.; Dickey, B.F.; Ost, D.E.; Chemaly, R.F.; Faiz, S.A. (Transplant Infectious Disease, 2019)
Background: Immunocompromised hematologic malignancy (HM) patients experience high mortality after respiratory syncytial virus (RSV) lower respiratory tract infection (LRTI). We measured radiologic severity to determine whether it could improve the performance of 60-day mortality models based only upon immunodeficiency severity. Methods: We studied 155 HM patients, including 84 hematopoietic cell transplant recipients, who developed RSV LRTI from 2001 to 2013. We measured immunodeficiency using lymphopenia (lymphocyte count <200 cells/mm3), Immunodeficiency Severity Index (ISI), and Severe Immunodeficiency (SID) criteria. Radiologic severity was measured by the Radiologic Severity Index (RSI, range 0-72) at time of LRTI (baseline-RSI) and peak severity (peak-RSI). Delta-RSI was defined as the difference between baseline-RSI and peak-RSI. We used logistic regression models to measure the association of immunodeficiency and RSI with 60-day all-cause mortality, and measured model discrimination using areas under the receiver-operating characteristics curves, calibration using Brier scores, and explained variance using pseudo-R2 values. Results: Forty-one patients died within 60 days of RSV LRTI. Severe immunodeficiency was associated with higher mortality. Peak-RSI (odds ratio [OR] 1.06/point, 95% confidence interval [CI] 1.04-1.08), and delta-RSI (OR 1.07/point, 95% CI 1.05-1.10) were associated with 60-day mortality after RSV LRTI, but not baseline-RSI. Addition of peak-RSI or delta-RSI to baseline immunodeficiency improved the discrimination, calibration, and explained variance (P < 0.001) of 60-day mortality models. Conclusions: Although baseline immunodeficiency in HM patients helps predict 60-day mortality after RSV LRTI, mortality risk estimates can be further refined by also measuring LRTI progression using RSI. RSI is well-suited as a marker of LRTI severity in RSV infection.
Keywords: adult; all cause mortality; allogeneic hematopoietic stem cell transplantation; article; assessment of humans; autologous hematopoietic stem cell transplantation; disease severity assessment; female; graft recipient; hematologic malignancy; human; immune deficiency; Immunodeficiency Severity Index; leukemia; lower respiratory tract infection; lymphocyte count; lymphocytopenia; lymphoma; major clinical study; male; medical record review; middle aged; mortality risk; multiple myeloma; priority journal; Radiologic Severity Index; respiratory syncytial virus infection; retrospective study; Severe Immunodeficiency criteria

Biomechanical Analysis of Fixation Devices for Basicervical Femoral Neck Fractures - Johnson, J.; Deren, M.; Chambers, A.; Cassidy, D.; Koruprolu, S.; Born, C. (The Journal of the American Academy of Orthopaedic Surgeons, 2019)
INTRODUCTION: Basicervical femoral neck fractures are challenging fractures in geriatric populations. The goal of this study was to determine whether compression hip screw (CHS) constructs are superior to cephalomedullary constructs for the treatment of basicervical femoral neck fractures. METHODS: Thirty cadaver femurs were osteotomized and received a CHS with derotation screw, a long cephalomedullary nail (long Gamma nail), or a short cephalomedullary nail (short Gamma nail). All constructs were loaded dynamically in compression until dynamic failure. RESULTS: All failed CHS constructs demonstrated superior femoral head cutout. In the long Gamma nail and short Gamma nail groups, constructs failed by nail cutout through the medial wall of the trochanter or rotationally. Normalized fluoroscopic distance was found to increase markedly with an increasing cycle count when considering all treatment groups. CONCLUSIONS: Given our results and those of previous studies, we could not determine superiority of one implant and recommend that surgeons select fixation constructs based on the individual patient's anatomy and the surgeon's comfort with the implant.
Keywords: aged; biomechanics; bone density; bone nail; bone screw; cadaver; compressive strength; device failure analysis; devices; diagnostic imaging; female; femoral neck fracture; fluoroscopy; foreign body; human; intramedullary nailing; procedures; very elderly

Feasible advantage of bioactive/bioresorbable devices made of forged composites of hydroxyapatite particles and poly-L-lactide in alveolar bone augmentation: A preliminary study - Sukegawa, S.; Kawai, H.; Nakano, K.; Kanno, T.; Takabatake, K.; Nagatsuka, H.; Furuki, Y. (International Journal of Medical Sciences, 2019)
Purpose: We aimed to document the clinical usefulness of uncalcined and unsintered hydroxyapatite (u-HA) particles and poly-L-lactide (PLLA) composite materials and their advantageous properties. Methods: Between April 2016 and March 2018, five patients required anterior maxillary alveolar ridge augmentation using fixation with u-HA/PLLA screws for an onlay block bone graft harvested from the mandibular ramus at our institute. Bone biopsies were obtained from the dental implantation site following bone healing for histomorphometric and immunohistochemical (IHC) measurements. Results: Many stromal cells were positive for Osterix, RUNX2, and SOX9 but were negative for CD68. On cell counting, based on IHC staining for Osterix, RUNX2, SOX9 and CD68 from peripheral u-HA/PLLA screw or bone areas, both areas consistently showed no significant difference in terms of Osterix, RUNX2, and SOX9. Hematoxylin-eosin staining revealed direct bone connection to the biomaterials, and no inflammatory cells infiltrated the areas surrounding the bone or artificial material. Area between the bone and u-HA/PLLA screw was seamless with no boundary. Round small cells and immature fibroblasts were noted. The new bone showed the presence of bone lamellae, normal osteocytes, and osteoblasts. Conclusion: The u-HA/PLLA materials showed excellent biodegradability and bioactive osteoconductivity. In addition, this material induced no apparent inflammatory or foreign body reactions following implantation, and it directly bonded to the human bone. Therefore, this u-HA/PLLA material seems ideal and most suitable for use as a substitute for osteosynthesis.
Keywords: bone screw; FIXSORB MX; biomaterial; CD68 antigen; hydroxyapatite; polylactide; transcription factor RUNX2; transcription factor Sox9; adult; aged; alveolar bone grafting; alveolar ridge augmentation; article; biodegradability; bone biopsy; bone structure; cell maturation; cell size; clinical article; composite graft; controlled study; feasibility study; female; fibroblast; human; human cell; human tissue; immunohistochemistry; inflammatory cell; male; mandible; maxilla; morphometry; osteoblast; osteocyte; stroma cell; tooth implantation; FIXSORB MX

Laparascopic extraction of an intraperitoneal gossypiboma following C/S and a retroperitoneal gossypiboma following pyeloplasty - Ozlem, N. (Surgical Endoscopy, 2019)
Gossypibomas are forgatten foreign bodies,iatrogenic.their symptoms are different where they are. they extracted with laparotomy in the past but now we can some article mentioned their extraction was made with laparoscopy. Case 1: 33 Y O female has abdominal pain after c/s for 2.5 years. A gossypiboma was extracted with laparoscopy above umblicus.A superficial surgical site infection existed,drained,subsided. Case 2: 46YO M had a pyleoplasty operation 8 years ago.a gossypiboma was extracted with retroperitonescopy,no postoperative event. Basibuyuk et al reported retroperionescopic extraction of a gossypiboma from single port in first time.Althoug every effort taken the incidence of foreign body detected in the body is about 0.03-0.1%.They are most frequently localized in the intraabdominal cavity followed by tracheobronchial area,pleural cavity,pararenal area,-vagina,spinal chord, neck, femur,breast,bladder,pancreas,and they may cause local irritation,and infection.Tactile sense is absent in laparoscopy. All radiologic examinations(usg ct pet mri etc) be used to detect.we used usg ct.in the end laparoscopy make the diagnosis and remove gossypibomas in our cases with less postoperative pain and cosmosis. Justo et al the computerized tomography (CT) scan is the most useful method for diagnosis; however, sometimes the preoperative diagnosis remains uncertain even after the imaging exam. In that case, laparoscopy arises as a valuable diagnostic tool, as well as a prompt treatment option. Concerning gossypiboma, prevention is preferred rather than treatment. Notwithstanding, there is no highly reliable prevention system. Counting sponges is a method based on staff communication during the surgery with only 77% sensibility. Routine surgical postoperative X-ray (SPOX) constitutes an early detection system, but the need to incorporate a radiopaque marker and to expose the whole surgical field to maximize its efficacy limits its use. More recently, electronic dispositives based on barcode detection and other technological adjuncts for counting sponges are being developed. None of these prevention systems are reliable when used alone. Our education and research clinic was a state hospital before. No surgeon followed above instruction.but now we use all. Multiple procedures and surgical teams, long operations and non-elective operations are the evidenced risk factors.c/s operation was learned full opened of ostium of cervix of the patient.
Keywords: adult; bladder; breast; computer assisted tomography; conference abstract; education; extraction; female; femoral neck; foreign body; human; incidence; laparoscopy; pancreas; pleura cavity; postoperative pain; preoperative evaluation; prevention; pyeloplasty; radiodiagnosis; risk factor; sensibility; surgeon; touch; uterine cervix; vagina

Fish bone penetration through stomach into superior mesenteric vein causing SMV thrombosis formation: Case report - Kang, J.H.; Chen, I.S. (Surgical Endoscopy, 2019)
A 75 year-old female was admitted to the emergency department with complaints of abdominal cramping pain, back pain and diarrhea for one day. She also had fever, ever up to 39°. In these two weeks, she felt occasionally epigastric pain. Her past medical history included hypertension. On physical examination, she was conscious and alert. Abdominal examination revealed diffuse tenderness and knocking pain over right flank. Laboratory tests indicated an degraded white cell count of 2890/cumm with 22% band forms, C-reactive protein of 25 mg/dL and abdominal liver function tests (Alanine Aminotransferase: 149 U/L, alkaline phosphatase: 249 U/L, gammaglutamyl transferase: 175 U/L) without hyperbilirubinemia. Abdominal X-ray showed paralytic ileus. Our presumptive diagnosis was acute peritonitis, based on the patient's symptoms. Empirical antibiotics were administered immediately, and a computed tomography (CT) imaging study was performed. The CT scan showed a stick like foreign body noted between ventral side of pylorus and SMV lumen, about 1.5 cm in length and associated with perifocal infiltration and segmental SMV thrombus formation.(Fig. 1) However, there is no obvious pneumoperitoneum and no evident ascites is associated. An emergency exploratory laparotomy was performed, revealing stomach perforation at posterior wall with a 3 cm fish bone thourgh pancreas into SMV. Localized inflammation and fibrosis were identified without obvious fluid accumulation(Fig. 2-4). Removal of fish bone and simple closure of stomach perforation were performed. Blood cultures revealed Bacteroides thetaiotaomicron. Three weeks later, she received a follow-up CT scan which showed SMV obliteration with chronic pylephlebitis.
Keywords: alanine aminotransferase; alkaline phosphatase; antibiotic agent; C reactive protein; endogenous compound; gamma glutamyltransferase; abdominal radiography; aged; alanine aminotransferase blood level; ascites; backache; Bacteroides thetaiotaomicron; blood clotting; blood culture; bone; case report; clinical article; computer assisted tomography; conference abstract; diarrhea; emergency ward; epigastric pain; female; fever; fibrosis; fish; flank; follow up; foreign body; human; hyperbilirubinemia; hypertension; laboratory test; laparotomy; leukocyte count; liver function test; medical history; muscle cramp; nonhuman; pancreas; paralytic ileus; peritonitis; physical examination; pneumoperitoneum; pylorus; stomach perforation; superior mesenteric vein; thrombosis

Gossypiboma in the abdominal cavity and its clinical implications: An autopsy report - Melo, J.; Ribeiro Pontes, G.; Moita Mota, H.; Nobre Cavalcanti Lucas, G.; Nunes Oliveira, D.; Texeira De Souza, I. (Virchows Archiv, 2019)
Background & Objectives: The oblivion of surgical compresses during abdominal operations can lead to serious complications, such as gossypiboma. To report a case of a patient with gossypiboma. Methods: A 59-year-old woman, previously submitted to appendectomy and videolaparoscopic cholecystectomy. It evolved postoperatively with flank obstruction. She underwent exploratory laparotomy for lysis of the flanges and adhesions. She sought care two days after hospital discharge with distention and severe abdominal pain, nausea and vomiting. Autopsy was made. Results: At the autopsy, a large amount of purulent fluid and a surgical compress adhered to the intestinal loops were seen in the abdominal cavity. Adjacent to this dressing, reddish areas with blackened foci were noted. The body was then referred to the Institute that performs medicallegal autopsies.The oblivion of foreign bodies during abdominal operations represents a serious complication, estimating an incidence of 1 for every 1000-1500 laparotomies and generates inflammatory tissue activity in its environment which can culminate in septic / exudative or aseptic / fibrinous reaction. Most of the time, the diagnosis is only established during the operative procedure for intestinal clearing or during the autopsy. Conclusion: In summary, it was possible to observe that the forgetting of foreign bodies during surgeries leads to significant harm to the patients, often culminating in death. However, there are simple and effective mechanisms to avoid this event, such as adherence to the protocol of safe surgery whose one of the principles is the counting of the surgical material before the patient leaves the operating room.
Keywords: abdominal cavity; abdominal pain; adult; appendectomy; autopsy; case report; cholecystectomy; clinical article; complication; compress; conference abstract; female; foreign body; hospital discharge; human; incidence; intestine loop; laparotomy; middle aged; nausea and vomiting; obstruction; operating room; plant leaf; surgery

Case series: Use of stromal lenticule as patch graft - Song, Y.J.; Kim, S.; Yoon, G.J. (American Journal of Ophthalmology Case Reports, 2018)
Purpose: To introduce cases of the use, as patch grafts, of stromal lenticules obtained by small incision lenticule extraction (SMILE) surgery. Observations: Case 1 was a 79-year-old man who presented with Ahmed-valve-tube exposure in his left eye. His uncorrected visual acuity (UCVA) was 20/40, best-corrected visual acuity (BCVA) 20/32, and intraocular pressure (IOP) 11 mmHg. He was treated with stromal lenticule patch that had been extracted by SMILE surgery. The patch was positioned underneath of the conjunctiva and sutured to it. At postoperative 8 months, the graft site was well maintained without Ahmed valve-tube exposure, the UCVA was 20/32, BCVA 20/20, and IOP 12 mmHg. Case 2 was a 60-year-old man who presented with Ahmed-valve-tube exposure in his right eye. His UCVA was finger-count (FC) 30 cm, his BCVA 20/125, and his IOP 14 mmHg. He was treated with stromal lenticule patch by the same method as employed in case 1. At postoperative 10 days, tube re-exposure and displacement of the Ahmed valve external plate toward the limbus area occurred due to loosening of the anchoring suture. So, we removed the Ahmed valve device, which had been implanted in the supero-temporal area, and performed new Ahmed valve implantation, with a stromal lenticule flap instead of a partial scleral flap, in the supero-nasal area. As of 6 months post-reoperation, the patient was stable, with UCVA 20/200, BCVA 20/40 and IOP 13 mmHg. Case 3 was a 74-year-old man who presented with bullous keratopathy in his right eye, which was blind. Due to severe adhesions, his conjunctiva could not cover the entire cornea. Therefore, we performed a stromal lenticule patch graft with conjunctival advance flap. At postoperative 3 months, the patient's right eye was stable, without displacement or melting of the lenticule graft. Conclusions & importance: It is suggested that the stromal lenticule, with its biocompatibility, sufficient strength, ease of handling and low cost, is a useful patch graft for various therapeutic purposes in the ophthalmic field.
Keywords: Ahmed valve; contact lens; suture; adult; aged; article; best corrected visual acuity; blindness; case report; cataract extraction; clinical article; disease severity; eye pain; eye tissue; foreign body; glaucoma; human; intraocular pressure; keratopathy; male; middle aged; postoperative period; pressure measurement; reoperation; retina detachment; slit lamp microscopy; small incision lenticule extraction; tissue flap; tissue graft; vitrectomy

Recurrent epibulbar dermoid cyst treated with amniotic membrane implant a case report - Villalón, M.L.; Leal, M.L.Á.; Chávez, J.R.; Santillán, E.M.; Lares-Asseff, I.; Loera, V.; Valencia, L.; Camacho, B.; Alvarado, B.; Cervantes, V.; Patrón, L.; Almanza, H. (BMC surgery, 2018)
BACKGROUND: The dermoid cyst considered a cystic teratoma derived from embryonic germinal epithelium is a slow-growing benign tumour. Dermoid cysts may occur in the orbital and periorbital region in paediatric patients and are often recurrent. The surgical approach depends upon the site of the lesion, superficial or deep. To our knowledge, this is the first described case of a patient with resection of dermoid cyst treated with human amniotic membrane implant and topical application of 0.02% mitomycin C. CASE PRESENTATION: We present a case of a 12-year-old male with a tumour in the superotemporal region of the right eye (RE). Symptoms included decreased visual acuity (VA), burning eye, foreign body sensation, and photophobia of the affected eye. A physical examination detected blepharospasm. Ophthalmic examination of his RE, fingers count from a 1-2 m distance, showed no improvement with pinhole. Visual acuity was 20/20 on the left eye (LE). The bio-microscopic examination confirmed the presence of a tumour mass (15 mm × 12 mm) on the surface of the RE, invading the superotemporal sector. The tumour had a lobulated appearance, a shiny and vascularized surface covered by conjunctiva, a pearlescent-pink colour, a medium consistency, was renitent and painless. An ultrasound scan revealed atrophy of the pigmented retinal epithelium with scleral indentation of the RE. A computed tomography (CT) scan revealed a recurrent lesion consistent with an epibulbar dermoid cyst. Surgical excision of the lesion was performed and a human amniotic membrane (HAM) graft and topical 0.02% mitomycin C (MMC) were applied. Histopathological analysis confirmed the diagnosis of recurrent dermoid cyst. CONCLUSION: In this case report, we describe a case of recurrent epibulbar dermoid cyst treated with complete resection; topical MMC and HAM implant with good clinical outcome of the lesion and implant adhesion. Resection of a cyst of the ocular surface is not recommended when a large epibulbar dermoid tissue needs to be resected and no HAM graft is available.
Keywords: amnion; case report; child; echography; human; male; orbit tumor; teratoma; transplantation; x-ray computed tomography

Retained surgical needle and gauze after cesarean section and adnexectomy: A case report and literature review - Lovrec, V.G.; Cokan, A.; Lukman, L.; Arko, D.; Takač, I. (Journal of International Medical Research, 2018)
Although the incidence of retained surgical items (RSIs) is low, it is nevertheless an important preventable cause of patient injury that can ultimately lead to the patient’s death and to subsequent high medical and legal costs. Unintentional RSI is the cause of 70% of re-interventions, with a morbidity of 80% and mortality of 35%. The most common RSIs are sponges or gauze (gossypiboma or textiloma), while retained surgical instruments and needles are rare. Perioperative counting of equipment and materials is the most common method of screening for RSIs, while a diagnosis can later be confirmed by the clinical appearance and by imaging studies. We present a rare case of a 43-year-old patient who was admitted to our hospital because of two retained needles following a cesarean section, despite several subsequent laparotomies. One needle had been removed previously, but in addition to the remaining needle, we also removed a retained gauze. The diagnosis of RSIs is extremely important, and safe surgical practices including the addition of new imaging technologies should be encouraged to detect RSIs.
Keywords: gauze dressing; needle; abdominal hysterectomy; abdominal pain; abdominal radiography; adult; appendectomy; appendicitis; article; case report; cesarean section; chill; clinical article; convalescence; device removal; differential diagnosis; female; fever; hospital admission; hospital discharge; human; iliac vein; laparotomy; nuclear magnetic resonance imaging; omentectomy; patient safety; pelvic inflammatory disease; retained instrument; salpingooophorectomy; vein thrombosis; weakness

Prophylactic ureteral stents incolectomies: Is it really required? - Zainal Adwin, Z.A.; Shukor, S.; Jasman, H.; Zainuddin, Z. (BJU International, 2018)
Introduction: Identification of the ureterduring colectomies is essential to preventiatrogenic injuries to the ureter fromoccurring. The usage of ureteric stents toaid identification has been and still is ahotly debated topic. The prophylacticinsertion of ureteral stents may facilitateidentification of the ureter and allows earlyrecognition of ureteric injuries in colectomies.Materials and Methods: All patients whounderwent colonic resection in UniversitiKebangsaan Malaysia Medical Centerbetween January 2015 and August 2018were analyzed. Demographic data, operative details and post-operative laboratorydata were collected. The primary outcomesof ureteral injury were compared betweenpatients who underwent colonic resectionwith prophylactic insertion of ureteralstent and patients who underwent colonicresection without prophylactic insertionureteral stents. Secondary outcomes ofduration of operation, perioperative whitecell count and perioperative serum creatinine were also compared. Statistical analyses were performed by the Student's ttest as appropriate and statistical significance was indicated by P < 0.05.Results: Between January 2015 andAugust 2018, a total of 526 colectomieswere performed with a larger number ofpatients not submitted to prophylacticureteral stent insertion (490 [93.2%] vs 36[6.8%]). The amount of emergency andelective operations were similar (271[51.5%] vs 255 [48.5]) with more openprocedures were performed as opposed tolaparoscopic resection (357 [67.8%] vs 169[32.1%]). Two ureteral injuries occurredand both these cases did not have prophylactic insertion of ureteral stents (0.4%). We found that there was no significantdifference in mean perioperative serumcreatinine (81.8 [7.5] vs 86.6 [2.3];P = 0.5921). There was a significance indifference in perioperative white cell count(12.54 [0.2] vs 15.39 [1.3]; P = <0.05) andoperating time (in minutes; 329.9 [22.4] vs213 [4.5]; P = <0.05) which may be due toa reaction to foreign body insertion andextra time needed to place stents respectively.Conclusion: In this cohort of 526 patientsundergoing bowel resection, prophylacticureteral stent insertion was associated withincreased operating duration and whitecell count. The rate of ureteral injury wassignificantly low and it occurred in apatient without ureteral stents. Ureteralinjury is a serious complication in colorectal surgery and utility of prophylactic ureteral stents are still controversial.
Keywords: adult; case report; clinical article; colon resection; colorectal surgery; complication; conference abstract; creatinine blood level; demography; emergency; female; foreign body; human; human tissue; leukocyte count; Malaysia; male; outcome assessment; statistical analysis; statistical significance; student; surgery; ureter injury; ureter stent

Retained surgical items: A pictorial and radiographic approach - Gore, A.; Chien, L.C.; Joshi, G.; Graves, J.A. (Emergency Radiology, 2018)
Learning Objectives 1. Identify the names of surgical equipment seen on intraoperative and postoperative imaging. 2. Become familiar with the physical and radiographic appearance of various retained surgical items including sponges, needles, hemostats, and other surgical items. 3. Identify risk factors for retained surgical items. Background Retained surgical items (RSI) can have catastrophic consequences for patients and healthcare providers. The retention of surgical items may cause serious harm resulting in further medical intervention. Surgical teams frequently count needles, sponges, and instruments in order to reduce the risk of retained instruments. Despite this meticulous and regulated process, count discrepancies do occur. Radiologists are routinely consulted to assess for possible retained surgical instruments; however, many radiologists are unfamiliar with the various names and appearance of surgical instruments, sponges, and needles that maybe seen on perioperative radiographs. In radiology reports, surgical devices are rarely or vaguely commented upon. Familiarity with the physical and radiographic appearance of surgical instruments will allow for more effective detection of retained surgical items. Our exhibit will present photographs and radiographs of several retained surgical items and familiarize radiologists with the appearance of these objects as they carry serious patient care and medicolegal implications. Content Photographs with detailed descriptions and names of multiple surgical items will initially be presented and the radiopaque markers will be outlined. This will be complemented by the radiographic appearance of multiple surgical items using both live case examples and chest and body phantoms. Examples of surgical items include: tonsil sponges, FISH viscera retainers, bovie tips, laparotomy sponges, peanut sponges, forceps, towel clamp, trocars, etc. A selection of cases with key teaching points will be also presented. Additionally, risk factors for retained surgical items will also be discussed. Summary Recognition and familiarity with the names and appearance of various retained surgical items will allow more effective detection and prevention of unwanted surgical re-intervention and medicolegal consequences.
Keywords: adult; conference abstract; forceps; human; laparotomy sponge; learning; needle; nomenclature; nonhuman; patient care; peanut; phantom; photography; radiologist; radiology; retained instrument; risk factor; surgery; teaching; thorax; tonsil; towel clip; trocar; viscera; X ray film

Evaluation of factors associated with retained surgical sponges in veterinary patients: a survey of veterinary practitioners - Rodriguez, F.R.; Kirby, B.M.; Ryan, J. (Journal of Small Animal Practice, 2018)
Objectives: To evaluate factors that could be associated with retained surgical sponges in veterinary patients. Materials and Methods: A survey was distributed to 322 veterinarians attending a national veterinary conference in the UK. The survey included questions about the staff, scheduling, type of surgical procedure, surgical sponges, methods to track surgical sponges and details of clinical cases with retained surgical sponges. Results: The response rate was 64 of 322 (19%). Lack of designated scheduled time for surgical procedures was reported by 30% of respondents and was variable for 31%. More than half of respondents (66%) had two people involved in each surgical procedure. The majority of respondents sterilised their own surgical sponges (91%) and used non-radiopaque surgical sponges (56%). Sponges were not counted by 27% of respondents and only occasionally by 20%. Sponge count was not recorded by 70% of respondents. The majority (66%) did not use or have a surgical checklist. Lack of awareness of gossypibomas was reported by 11% of respondents. In all, 27% of respondents were aware of at least one case of retained surgical sponge. Of the 17 cases reported, 14 were small animals. The abdomen was the most common anatomical location for retained surgical sponges and followed elective neutering. Clinical Significance: Despite the low-response rate, our results suggest that methods of surveillance might reduce the incidence of retained surgical sponges. Lack of specifically scheduled time for surgery, few theatre staff and lack of sponge counting and documentation may have contributed to the 17 retained surgical sponge cases reported.
Keywords: operating room; surgical sponge; abdominal pain; abdominal surgery; article; cat; dog; donkey; end to end anastomosis; gossypiboma; health survey; herniorrhaphy; horse; human; hysterectomy; instrument sterilization; intestine resection; medical error; nonhuman; patient safety; postoperative complication; pyometra; radiography; retained surgical sponge; risk factor; surgical technique; veterinarian

Perioperative outcomes in human immunodeficiency virus-infected patients – the PRO HIV study - Shanthamurthy, D.; Manesh, A.; Zacchaeus, N.G.P.; Roy, L.R.; Rupali, P. (International Journal of STD and AIDS, 2018)
It is estimated that a quarter of patients with HIV/AIDS undergo at least one surgical procedure in their life time. Surgical outcomes in these patients from developing countries are poorly characterized and surgeons are often concerned about poor surgical outcomes, especially when their CD4 cell counts are less than 200 cells/µl. This study evaluated the surgical outcomes of HIV-infected patients undergoing various surgical procedures over a six-year period in a large tertiary care hospital from South India. Two hundred and ninety-three patients underwent 374 surgical procedures during the study period. The median duration of HIV prior to surgery was 1.9 years (range 0–18.8 years). Two-thirds (58%) were on highly active antiretroviral therapy (HAART) at the time of surgery with the median duration of this treatment being 38 months (n = 194). About one-third (35%) of surgical procedures were performed as an emergency. Abdomino-pelvic surgeries were the most common (225, 60%). Adverse surgical outcome defined as death or post-operative infection was seen in 25 (6.6%). The post-operative infection rate was 5% (20/374). The most common of these was surgical site infection observed in nine (60%) followed by pneumonia in five patients (33%) and urinary tract infection in one patient. Day 30 mortality was 2% (n = 8) and a quarter of these were reported to be related to post-operative infectious complications. On multivariate analysis, only preoperative haemoglobin of less than 10 g/dl was significantly associated with a poor surgical outcome. HIV-related parameters such as CD4 cell counts, duration of HIV infection and HAART regimen did not seem to contribute towards an adverse surgical outcome.
Keywords: prosthesis; albumin; antifungal agent; efavirenz; hemoglobin; lamivudine; lamivudine plus nevirapine plus zidovudine; tenofovir; abdominal surgery; adolescent; adult; adverse outcome; antifungal therapy; article; blood vessel graft; CD4 lymphocyte count; clinical outcome; combination drug therapy; controlled study; debridement; disease duration; drug use; elective surgery; emergency surgery; female; follow up; foreign body; general anesthesia; highly active antiretroviral therapy; hospital discharge; human; Human immunodeficiency virus infected patient; Human immunodeficiency virus infection; India; infant; major clinical study; male; newborn; open surgery; pelvis surgery; perioperative period; pneumonia; priority journal; retrospective study; side effect; surgical infection; surgical mortality; tertiary care center; treatment duration; urinary tract infection; virus load

Buckshot centered nucleous-matrix ureterolithiasis due to gunshot injury - Sönmez, M.; Kilinç, M.; Atici, A.; Ö ztürk, A.; Göger, Y.E. (Journal of Endourology, 2018)
Introduction & Objective: The foreign bodies within the ureter are extremely rare and they include iatrogenic bodies as fragmented ureteral stents, angio-embolization coils, traumatic sharpnel or bullet and foreign bodies introduced per urethra. In this case, a patient with buckshot centered nucleous-matrix ureterolithiasis due to gunshot injury was presented. Methods: Case Presentation: Fifty-five year old man who referred for left flank pain for 3 months. The patient underwent laparotomy caused by gunshot injury to abdominal area 6 months ago. During this time there was no history of hematuria, febrile urinary tract infection and abdominal pain. The physical examination was unremarkable. Complete blood count was normal and urine culture was negative. Creatinin rate was 1.1 mg/dl. Left side hydroureteronephrosis, upper third ureteric calculi and ureteric foreign body seen on abdominal computed tomography. Results: We decided to perform left ureteroscopy to the patient. A holmium laser lithotripter was used to break the stone during ureteroscopy. It was observed that the bullet inside the stone matrix was the core. After the stone was completely shredded, we removed the buckshot core with endoscopic forceps. Conclusions: Ureteral trauma is uncommon, accounting for less than %1 of all urologic traumas. Penetrating ureteral injuries are more common than blunt uretral injuries in adults Upper third of the ureter is more often injured than the midlle and lower thirds. Complications of ureteric injury are; infected urinomas, ureteric fistulas, ureteric stenosis, and retroperitoneal abscesses. The reason we have presented this case is there is no complication of urinary system due to intra ureteric foreign body within 6 months.
Keywords: creatinine; abdominal pain; adult; blood cell count; case report; clinical article; complication; computer assisted tomography; conference abstract; fistula; flank; forceps; foreign body; gunshot injury; hematuria; holmium laser; human; hydroureter; laparotomy; lithotripter; male; middle aged; physical examination; retroperitoneal abscess; stenosis; ureter injury; ureter stone; ureteroscopy; urinary tract infection; urine culture; urinoma

Mesh induced fibrosis: The role of T regulatory cells - Artsen, A.M.; Rytel, M.; Liang, R.; Moalli, P.A. (Female Pelvic Medicine and Reconstructive Surgery, 2018)
Objective: Of the 350,000 annual Urogynecologic surgeries utilizing mesh, 5% result in mesh removal for complications-most commonly mesh exposure and pain. Regulatory T cells (Tregs), a subset of T helper (Th) cells, promote tolerance to foreign bodies by modifying macrophage differentiation. A profibrotic response characterized by increased type-2 macrophages has been reported in mesh removed for pain but the role of Tregs in mesh complications has not been explored. We sought to determine if decreased Tregs are associated with an increased fibrotic response and if fewer Tregs will be seen in mesh removed for pain as compared to exposure. Methods: Mesh-tissue complexes were removed for pain (N=8) or exposure (N=8). Immunofluorescent labeling of CD4 (Th), and foxp3 (Tregs) was performed (Figure 1A) then stained with Trichrome (Figure 1B). Samples were divided into 0.25 μm2 grids for cell counts. Grids were classified as mild, moderate or high fibrosis by a semi-quantitative assessment of collagen deposition via intensity profiling. High fibrosis was considered pathologic and was compared to mild/moderate fibrosis. Treg concentrations were compared using a mixed effects linear models for high vs mild/moderate fibrosis, Mann-U Whitney tests for pain/exposure groups, and linear regression for duration of implantation. Data is reported as mean±SD for baseline patient data and mean±SE for cell concentrations. Results: Average age was 56.7± 10.0 y, BMI28.9±1.0kg/m2 and median parity 3 (range 1-5). Of pain samples, 4 were midurethral slings (MUS) and 4 were prolapse meshes. Of exposure samples, 3 were MUS and 5 were prolapse meshes. There were no differences in age, BMI, parity, smoking, rate of diabetes, menopausal status, hormone use, or prior hysterectomy based on removal indication or mesh type (p>0.05). Mean time of implantation was 38.1±24.3 months. Tregs were decreased in areas of high fibrosis with 11.3±2.1 Treg/jjm compared to 13.1±1.5 Treg/jjm for mild/moderate areas p<0.001. Th were similarly decreased with 11.5±2.1 Th/(jm vs 13.3±2.1 Th/(jm, p<0.001. On mixed effects linear regression, there were 0.96 fewer Treg/(jm and 1.1 fewer Th/(jm in areas of high fibrosis vs mild/moderate fibrosis (p<0.001). There was no difference in Tregs between pain vs. exposure. Conclusions: Th cells, consisting primarily of Tregs, were present years after mesh implantation challenging the common notion that the adaptive immune response to a foreign body is transient. The inverse relationship between fibrosis and Tregs points to a protective role of these cells. Similar Tregs in patients with pain and exposure suggests these complications exist along the same spectrum. Further research into a potential therapeutic role of Tregs is warranted. [Figure Presented].
Keywords: CD4 antigen; collagen; endogenous compound; hormone; transcription factor FOXP3; adaptive immunity; adult; body mass; cell count; clinical article; complication; conference abstract; controlled study; diabetes mellitus; disease course; female; fibrosis; foreign body; human; human cell; human tissue; immunofluorescence; implantation; linear regression analysis; male; middle aged; mixed cell culture; pain; parity; patient coding; patient history of hysterectomy; prolapse; protein fingerprinting; quantitative analysis; regulatory T lymphocyte; smoking; suburethral sling; Th1 cell

Measured for safety-the apollo quality program - Sibal, D.A.; Sachdeva, P. (International Journal for Quality in Health Care, 2018)
Objectives: The Apollo Quality Program(AQP), is a a unique platform established by Apollo Hospitals, the largest healthcare provider in India, to promulgate patient safety and quality improvement across all of its 64 Hospitals in the country, and create a robust framework for clinical governance through patient safety data measurement systems. Methods: A comprehensive set of safety-solutions, AQP, was developed, for the Group-wide implementation of standardized methodologies for clinical-handovers, international patient safety goals(IPSGs), surgical-care-improvement, medication-safety andstandardization of medical-records.Clinical-handovers were standardized. The six IPSGs as given by the JCI; patient-identifiers, read-back for verbal orders, safety of high-alert medications, sitemarking, time-outs and falls risk-assessment were introduced for all hospitals. Surgical-Care-Improvement-Plan envisages safety during surgeries by preventing wrong-site, wrong-patient, wrong-procedure surgery,surgical-site infections and foreign-body retention during surgery. Medication-Safety included standardizing the medication management plan, ensuring prescription audits of all prescriptions including discharge-summaries and measurement of medicationerrors. Minimum content of all medical-records across Group Hospitals was defined. All parameters together formed a measurable dashboard of 20 parameters with results colour coded as green, orange and red for defined ranges of scores. This dashboard was made online for monthly monitoring wherein each hospital reported compliance data.Intensive training was conducted for all units through video-conferencing.The scores of the AQP were linked to the hospitals' performance scorecard and also to the appraisal of the Medical Heads and the CEOs and helped establish clinical governance. Initiatives were undertaken at each of the unit hospitals to promote the culture of safety. Audits were conducted to validate processes and data. Results: There is a marked increase in the compliance to processes and patient-safety outcomes. The average AQP scores for all Apollo Hospitals improved from 62 in April'11 to 91 in December'17 shows an overall improvement. Various other parameters that show improvement and hence substantiate progress are: Group average percentage compliance to use of nursing-handover form for patient-handover increased from 90.40% to 99%. Compliance to use of two patient-identifiers rose from 95.42% in April'11 to 98.84% in December'17, read-back for verbal-orders from 86.69% to 97.56%, to policy for high alert medications from 87.83% to 97.78%, use of measures to prevent wrong-site, wrongpatient, wrong-procedure surgery from 85.75% to 99.17%, to handwashing from 69.18% to 91.76%, to antimicrobial prophylaxis within one hour before incision from 79.43% to 95.08%. Percentage of patients excluded from SSI calculation due to lack of follow-up for the requisite time frame decreased from 21.25% to 8.67%, compliance to communicating sponge count conveyed to surgeon before skin closure from 82.83% to 100%. Conclusion: AQP is a platform that has empowered the leadership, by providing them with a powerful data driven and evidence based mechanism to look back and introspect each of their units' performance in terms of patient safety and quality more objectively. They are enabled to undertake constructive and tangible measures to improve and drive clinical quality and patient safety processes thereby building in resilience and reliability.
Keywords: antiinfective agent; adult; calculation; clinical article; clinical handover; conference abstract; controlled study; drug safety; female; follow up; foreign body; hand washing; head; human; incision; leadership; male; medical record; medication therapy management; monitoring; outcome assessment; patient safety; prescription; prophylaxis; reliability; risk assessment; skin; surgeon; surgery; surgical infection; videoconferencing

Endophthalmitis as the first presentation following ocular penetrating injury with intraocular foreign body (IOFB) - Basri, M.B.T.H.; Zahidin, A.Z.B.T.M.; Mustapha, M.B.T. (Medical Journal of Malaysia, 2018)
Objective: To report a case of endophthalmitis following ocular penetrating injury with intraocular foreign body, its management and outcome. Method: Case Report. Results: A 34 years old Indonesian male was admitted for sudden painful reduced vision in right eye. He had a history of foreign body hitting his right eye while wielding a hammer two days prior to presentation. Visual acuity was counting finger OD, 6/12 OS and RAPD negative. Examination showed full thickness sclera laceration wound at 9 o'clock with hypopyon and fibrin in anterior chamber. There was severe vitritis. CT scan revealed presence of intraocular foreign body in the right eye. Patient was started on systemic ciprofloxacin and given intravitreal fortum and ceftazidime during right eye sclera laceration wound toilet and suturing with vitreous tapping on the same day. Following primary suturing, patient underwent pars plana vitrectomy, removal of intraocular foreign body and silicone oil insertion. Culture and sensitivity test from vitreous showed Flavobacterium spp and clinically patient responded to topical antibiotics. Postoperatively patient's vision improved to 2/60. Conclusion: Post-traumatic endophthalmitis is an uncommon but severe complication of ocular trauma with its incidence rate of 2.1% of all open globe injury. The incidence increases up to 5% when associated with IOFB. IOFB is most commonly caused by metal hammering metal. The decision whether to remove as a primary procedure or subsequent surgery depends on the IOFB size and material, visual potential, surgeon, and patient preference. Discussion with a vitreoretinal surgeon is crucial in the early management.
Keywords: ceftazidime; ciprofloxacin; fibrin; silicone oil; adult; anterior eye chamber; body size; case report; clinical article; complication; conference abstract; drug combination; drug therapy; endophthalmitis; eye injury; finger; Flavobacterium; human; hypopyon; incidence; Indonesian; intraocular foreign body; laceration; low vision; male; nonhuman; pars plana vitrectomy; patient preference; sclera; surgeon; surgery; topical drug administration; visual acuity; vitreous body; vitritis; wound care; x-ray computed tomography

The effect of ventricular assist device-associated biomaterials on human blood leukocytes - Radley, G.; Pieper, I.L.; Thornton, C.A. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2018)
Ventricular assist devices (VADs) are an effective bridging or destination therapy for patients with advanced stage heart failure. These devices remain susceptible to adverse events including infection, bleeding, and thrombus; events linked to the foreign body response. Therefore, the biocompatibility of all biomaterials used is crucial to the success of medical devices. Biomaterials common in VADs—DLC: diamond-like carbon coated stainless steel; Sap: single-crystal sapphire; SiN: silicon nitride; Ti: titanium alloy; and ZTA: zirconia-toughened alumina—were tested for their biocompatibility through incubation with whole human blood for 2 h with mild agitation. Blood was then removed and used for: complete cell counts; leukocyte activation and death, and the production of key inflammatory cytokines. All were compared to time 0 and an un-exposed 2 h sample. Monocyte numbers were lower after exposure to DLC, SiN, and ZTA and monocytes showed evidence of activation with DLC, Sap, and SiN. Neutrophils and lymphocytes were unaffected. This approach allows comprehensive analysis of the potential blood damaging effects of biomaterials. Monocyte activation by DLC, Sap, ZTA, and SiN warrants further investigation linking effects on this cell type to unfavorable inflammatory/thrombogenic responses to VADs and other blood handling devices. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1730–1738, 2018.
Keywords: ventricular assist device; biomaterial; CD11b antigen; CD14 antigen; CD15 antigen; diamond like carbon coated stainless steel; formyl peptide receptor 1; formylpeptide receptor; interleukin 1beta; interleukin 6; interleukin 8; L selectin; silicon nitride; single crystal sapphire; titanium; tumor necrosis factor; unclassified drug; zirconia toughened alumina; adult; apoptosis; article; biocompatibility; blood; CD3+ T lymphocyte; controlled study; cytokine production; human; human cell; inflammation; leukocyte; leukocyte activation; leukocyte count; lymphocyte; monocyte; monocyte count; neutrophil; normal human; physical parameters; roughness; surface area; thrombocyte aggregation

Filler-induced granulomatous reaction two-years after the treatment - Ebadian, M.; Chapman, A. (British Journal of Dermatology, 2018)
With an increase in aesthetic facial rejuvenation, there has been a higher demand for aesthetic treatment for the hands. Many different types of fillers are available to restore the smooth texture and its volume and elasticity. In majority of cases, fillers are considered to be safe and the complications are rare. The early complications such as bruising, paraesthesia and swelling are usually mild. Delayed or long-term complications are much rarer but of more concern. We report a case of 53-year-old woman with a filler-induced granulomatous reaction as a delayed complication, 2 years after her initial filler treatment. She presented with a 2-month history of worsening skin swelling and hardening, affecting exclusively the dorsa of her hands. She had no significant past medical history apart from breast implants 10 years ago. She reported that Ellanse rejuvenation hand filler was administered, 2 years before the onset of her hand swelling. To our knowledge, there have been no previous reports of granulomatous reactions due to Ellanse treatment. She was presented with woody-hard nodules over the dorsa of her hands that were tender on palpation. Differential diagnosis included sarcoidosis, filler-induced granulation, atypical bacterial infection and deep fungal infection. Blood test showed a normal full blood count, renal function, liver function test and slightly raised angiotensin-converting enzyme 62 (8-52). A deep incisional biopsy was done bilaterally and was reported consistent with a filler-induced granulomatous reaction. Tissue culture showed growth of 'Acinetobacter lwoffii'. Raised ACE was investigated to rule out any underlying systemic sarcoidosis, which may have predisposed her to the filler-induced granulomatous reaction. She was reviewed by respiratory physician, and both CXR and high resolution CT were normal. The slightly raised ACE was thus of no concern. She completed a course of doxycycline and ciprofloxacin. She received intralesional triamcinolone 10 mg/ml injection at week 6 and 16. This resulted in complete resolution of the nodules. Filler-related foreign body granulomas are nonallergic reactions that occur 6- 24 months after filler injections and are a form of chronic inflammatory reaction that is mainly composed of multinucleated giant cells. Foreign body granulomas may occur after the administration of any dermal filler. Treatment options include systemic antibiotics, lesional steroid injection and surgical excision. Although many patients end up having surgical removal, this should not be first line treatment. As our case has demonstrated, medical treatment can be substantial and with no permanent scarring due to surgery.
Keywords: ciprofloxacin; dipeptidyl carboxypeptidase; doxycycline; endogenous compound; filler; triamcinolone; Acinetobacter lwoffii; adult; bacterial infection; biopsy; blood cell count; breast endoprosthesis; case report; clinical article; complication; conference abstract; contusion; differential diagnosis; drug combination; drug toxicity; excision; female; foreign body granuloma; giant cell; high resolution computer tomography; human; human cell; human tissue; injectable implant; injection; kidney function; liver function test; medical history; middle aged; mycosis; nonhuman; palpation; paresthesia; physician; rejuvenation; remission; sarcoidosis; scar formation; skin swelling; surgery; tissue culture

A randomized controlled clinical trial comparing 20 gauge and 23 gauge vitrectomy for patients with macular hole or macular pucker - Scholz, P.; Müther, P.; Schiller, P.; Felsch, M.; Fauser, S. (Investigative Ophthalmology and Visual Science, 2018)
Purpose: To compare the sutureless 23 gauge (G) pars plana vitrectomy (PPV) with the 20G PPV regarding inflammation, visual outcome and patient comfort. Methods: We included 100 patients with symptomatic macular hole or macular pucker, scheduled for vitrectomy in this prospective, randomized, controlled, mono-center clinical trial which followed the tenets of the Declaration of Helsinki. Patients were randomized 1:1 either to 20G PPV (n=51) or 23G PPV (n=49). All eyes underwent standard 20G or 23G PPV with membrane peeling. Primary endpoint was change in aqueous humor flare 3 weeks after surgery compared to baseline. Flare was measured with the FM-500 Laser Flare-Cell Meter (Kowa Company, Ltd, Tokyo, Japan) and expressed as photon counts per millisecond (pc/ms). Secondary outcome measures were postoperative discomfort measured with a visual analog scale, best-corrected visual acuity, postoperative intra ocular pressure (IOP), number of complications and duration of surgery. Results: There was no significant difference in change of aqueous humor flare between the groups (20G:3.5 ±9.5 pc/ms, 23G:2.3 ±13.2 pc/ms, p= 0.452). Only in the per protocol set (31 eyes in each group), a lower increase in aqueous flare was observed after 23G PPV (20G:1.9± 6.7 pc/ms, 23G:-0.1±4.8 pc/ms, p=0.039). Postoperative IOP was lower after 23G PPV (20G:16.9±8.2 mmHg, 23G:12.5±6.2 mmHg, p=0.005), but the rate of postoperative hypo- or hypertension did not differ between the groups (p=0.207). The gain in ETDRS letters 3 weeks after surgery was higher after 23G PPV (20G:4.2±10.4, 23G:6.8±10.4, p=0.034), but showed no significant difference after 6 month (20G:11.0±13.5, 7.3±15.6, p=0.588). The mean duration of surgery was shorter in the 23G group (20G:29 ±6 min, 23 G:20±6 min, p<0.0001) and patients after 23G PPV showed higher comfort (Foreign body sensation 20G:22±24, 23G:9 ±14, p=0.002; itching:20G:12±20, 23G:5±10, p=0.021). The rate of complications did not differ between the groups. Conclusions: The primary endpoint, a significant lower change in flare values in the 23G group three weeks after surgery, could not be reached, but the level of inflammation decreases faster after 23G PPV. Clear advantages of the 23G PPV are a shorter surgery time, faster visual recovery and a higher comfort in the early postoperative phase. These advantages must be seen in relation to the higher cost of the system.
Keywords: adult; aqueous humor; best corrected visual acuity; comfort; complication; conference abstract; controlled study; epiretinal membrane; female; foreign body; gauge; human; hypertension; inflammation; intraocular pressure; Japan; laser flare cell meter; major clinical study; male; operation duration; outcome assessment; pars plana vitrectomy; photon; postoperative period; prospective study; pruritus; randomized controlled trial; retina macula hole; sensation; visual analog scale

Retained surgical sponges: A descriptive study of 319 occurrences and contributing factors from 2012 to 2017 - Steelman, V.M.; Shaw, C.; Shine, L.; Hardy-Fairbanks, A.J. (Patient Safety in Surgery, 2018)
Background: Unintended retention of foreign bodies remain the most frequently reported sentinel events. Surgical sponges account for the majority of these retained items. The purpose of this study was to describe reports of unintentionally retained surgical sponges (RSS): the types of sponges, anatomic locations, accuracy of sponge counts, contributing factors, and harm, in order to make recommendations to improve perioperative safety. Methods: A retrospective review was undertaken of unintentionally RSS voluntarily reported to The Joint Commission Sentinel Event Database by healthcare facilities over a 5-year period (October 1, 2012- September 30, 2017). Event reports involving surgical sponges were reviewed for patients undergoing surgery, invasive procedures, or child birth. Results: A total of 319 events involving RSS were reported. Sponges were most frequently retained in the abdomen or pelvis (50.2%) and the vagina (23.9%). Events occurred in the Operating Room (64.1%), Labor and Delivery (32.7%) and other procedural areas (3.3%). Of the events reported, 318 involved 1 to 12 contributing factors totaling 1430 in 13 different categories, most frequently in human factors and leadership. In 69.6% of reports, the harm was an unexpected additional care or extended stay. Severe temporary harm was associated with 14.7% of the events. One patient died as a result of the retained sponge. Conclusions: Because of the complexity of perioperative patient care, the multitude of contributing factors that are difficult to control, and the potential benefit of radiofrequency sponge detection, we recommend that this technology be considered in areas where surgery is performed and in Labor and Delivery.
Keywords: operating room; surgical sponge; abdominal surgery; article; childbirth; descriptive research; female; human; human factors research; invasive procedure; labor; leadership; observational study; obstetric delivery; patient care; patient safety; pelvis surgery; retained surgical sponge; retrospective study; risk assessment; surgery

Postoperative kinetics of common inflammatory biomarkers after congenital heart defect procedures with extracorporeal circulation in children - Haponiuk, I.; Jaworski, R.; Paczkowski, K.; Chojnicki, M.; Steffens, M.; Szofer-Sendrowska, A.; Gierat-Haponiuk, K.; Kwaśniak, E.; Paśko-Majewska, M.; Leszczyñska, K.; Zieliñski, J.; Szymanowicz, W. (Kardiologia Polska, 2018)
Background: Extracorporeal circulation is associated with systemic inflammatory response syndrome. Therefore, the diagnosis of infection should be differentiated from a typical postoperative course. Aim: The aim of the study was to evaluate the kinetics of inflammatory biomarkers in children in the first days after cardiac surgery with extracorporeal circulation. Methods: Prospective data were collected from 51 consecutive children referred for surgical treatment in Department of Paediatric Cardiac Surgery, St. Adalbertus Hospital in Gdañsk, between February and August 2015. Blood samples were collected on the first, second, and third postoperative days and sent to the institutional laboratory for routine investigations: White blood cell count, serum C-reactive protein (CRP) and procalcitonin concentrations. Results: The highest levels of procalcitonin were on the first postoperative day (median 3.53 ng/mL), although the peak values of CRP concentration and white blood cell count were on the second postoperative day (96 mg/L and 17.3 G/L). In the group of patients with foreign material implantation (Contegra(r) or Gore-Tex(r)), the higher values of procalcitonin concentration and white blood cell count were measured in the subsequent postoperative days. Conclusions: The kinetics of analysed inflammatory biomarkers on the first days after cardiac surgery for congenital heart disease in children have different characteristics. The knowledge about the kinetics of inflammatory biomarkers could be useful in determining the possibility of evolving infections in the early postoperative period.
Keywords: pulmonary valved conduit; politef; immunoassay analyzer; Modular Roche A PB 06-76; politef implant; pulmonary valved conduit; roller pump; Sorin S5; biological marker; C reactive protein; cefazolin; procalcitonin; antibiotic prophylaxis; article; atrioventricular septal defect; blood sampling; calcitonin blood level; child; congenital heart malformation; deep hypothermic circulatory arrest; extracorporeal circulation; Fallot tetralogy; female; Fontan procedure; foreign body; great vessels transposition; heart atrium septum defect; heart surgery; heart ventricle septum defect; human; immunoturbidimetry; infant; leukocyte count; major clinical study; male; maximum plasma concentration; newborn; pediatric surgery; postoperative care; prospective study; protein blood level; surgical infection; systemic inflammatory response syndrome; Contegra; Gore-Tex; Modular Roche A PB 06-76; Sorin S5

Developing Process Maps as a Tool for a Surgical Infection Prevention Quality Improvement Initiative in Resource-Constrained Settings - Forrester, J.A.; Koritsanszky, L.A.; Amenu, D.; Haynes, A.B.; Berry, W.R.; Alemu, S.; Jiru, F.; Weiser, T.G. (Journal of the American College of Surgeons, 2018)
Background: Surgical infections cause substantial morbidity and mortality in low-and middle-income countries (LMICs). To improve adherence to critical perioperative infection prevention standards, we developed Clean Cut, a checklist-based quality improvement program to improve compliance with best practices. We hypothesized that process mapping infection prevention activities can help clinicians identify strategies for improving surgical safety. Study design: We introduced Clean Cut at a tertiary hospital in Ethiopia. Infection prevention standards included skin antisepsis, ensuring a sterile field, instrument decontamination/sterilization, prophylactic antibiotic administration, routine swab/gauze counting, and use of a surgical safety checklist. Processes were mapped by a visiting surgical fellow and local operating theater staff to facilitate the development of contextually relevant solutions; processes were reassessed for improvements. Results: Process mapping helped identify barriers to using alcohol-based hand solution due to skin irritation, inconsistent administration of prophylactic antibiotics due to variable delivery outside of the operating theater, inefficiencies in assuring sterility of surgical instruments through lack of confirmatory measures, and occurrences of retained surgical items through inappropriate guidelines, staffing, and training in proper routine gauze counting. Compliance with most processes improved significantly following organizational changes to align tasks with specific process goals. Conclusions: Enumerating the steps involved in surgical infection prevention using a process mapping technique helped identify opportunities for improving adherence and plotting contextually relevant solutions, resulting in superior compliance with antiseptic standards. Simplifying these process maps into an adaptable tool could be a powerful strategy for improving safe surgery delivery in LMICs.
Keywords: surgical drape; surgical glove; surgical gown; surgical swab; alcohol; ampicillin; ceftriaxone; soap; antibiotic prophylaxis; antisepsis; article; decontamination; hand washing; human; infection prevention; infection risk; instrument sterilization; priority journal; prospective study; skin decontamination; skin irritation; surgical infection; total quality management

1,300 Days and Counting: A Risk Model Approach to Preventing Retained Foreign Objects (RFOs) - Duggan, E.G.; Fernandez, J.; Saulan, M.M.; Mayers, D.L.; Nikolaj, M.; Strah, T.M.; Swift, L.M.; Temple, L. (Joint Commission Journal on Quality and Patient Safety, 2018)
Background: A retained foreign object (RFO) is a devastating surgical complication that typically results in additional surgeries, increased length of stay, and risk of infections and is potentially fatal. Memorial Sloan Kettering Cancer Center (MSKCC) convened a multidisciplinary task force to undertake an improvement initiative to reduce the frequency of RFO incidents. Methods: A needs assessment was undertaken using focus group interviews, review of past RFOs, and operating room (OR) observations, and a comprehensive intervention plan was initiated. Items at risk of retention were reclassified and new tracking sheets were developed. A probabilistic risk model was developed based on aviation industry methodology, an RFO risk projection, and the retention risk classification of surgical items. Training initiatives were launched to shift organizational culture and staff behaviors toward greater awareness of RFO risk and proactive prevention. Results: Since the implementation of our task force's recommendations on March 24, 2014, there have been no RFO incidents at our institution to this day. The last RFO occurred in August 2013—more than 1,300 days ago (as of March 28, 2017). The RFO incident frequency was reduced from 1.69 per year to a risk model estimate of 1 in 22 years. Ongoing training maintains the staff's behavioral changes as well as the improved OR and organizational culture. Conclusion: Implementation of a multidisciplinary approach to preventing RFOs was successful at MSKCC. The use of an RFO risk model enabled the creation of a robust system for RFO prevention. Support from leadership, participation by all stakeholders, education, training, and cooperation from frontline staff are all important contributors to RFO prevention success.
Keywords: operating room; surgical equipment; article; evidence based medicine; foreign body; human; interview; medical education; needs assessment; probabilistic risk model; retained foreign object; risk assessment; statistical model; treatment planning

Systematic review of benefits or harms of routine anaesthetist-inserted throat packs in adults: practice recommendations for inserting and counting throat packs: An evidence-based consensus statement by the Difficult Airway Society (DAS), the British Association of Oral and Maxillofacial Surgery (BAOMS) and the British Association of Otorhinolaryngology, Head and Neck Surgery (ENT-UK) - Athanassoglou, V.; Patel, A.; McGuire, B.; Higgs, A.; Dover, M.S.; Brennan, P.A.; Banerjee, A.; Bingham, B.; Pandit, J.J. (Anaesthesia, 2018)
Throat packs are commonly inserted by anaesthetists after induction of anaesthesia for dental, maxillofacial, nasal or upper airway surgery. However, the evidence supporting this practice as routine is unclear, especially in the light of accidentally retained throat packs which constitute ‘Never Events’ as defined by NHS England. On behalf of three relevant national organisations, we therefore conducted a systematic review and literature search to assess the evidence base for benefit, and also the extent and severity of complications associated with throat pack use. Other than descriptions of how to insert throat packs in many standard texts, we could find no study that sought to assess the benefit of their insertion by anaesthetists. Instead, there were many reports of minor and major complications (the latter including serious postoperative airway obstruction and at least one death), and many descriptions of how to avoid complications. As a result of these findings, the three national organisations no longer recommend the routine insertion of throat packs by anaesthetists but advise caution and careful consideration. Two protocols for pack insertion are presented, should their use be judged necessary.
Keywords: surgical sponge; throat pack; airway obstruction; anesthesist; glossopharyngeal nerve injury; human; infection; patient safety; postoperative nausea and vomiting; review; systematic review; throat culture

Evaluating complication rates and outcomes among infants less than 5 kg undergoing traditional percutaneous endoscopic gastrostomy insertion: A retrospective chart review - Fernandes, A.R.; Elliott, T.; McInnis, C.; Easterbrook, B.; Walton, J.M. (Journal of Pediatric Surgery, 2018)
Purpose: Percutaneous endoscopic gastrostomy (PEG) enables enteral nutrition for patients with inadequate oral intake. Laparoscopic guidance of PEG insertion is used for high-risk populations, including in infants less than 5 kg at insertion. This study aimed to assess complication rates with traditional PEG tube insertion in infants less than 5 kg at a single tertiary care center. Methods: A retrospective review of patients less than 5 kg who underwent PEG insertion was conducted. PEG insertion-related complications, up to four years following insertion, were collected. Outcomes were reported as counts and percentages, or median with minimum and maximum values. Results: 480 pediatric gastrostomy procedures between January 1, 2009 and February 1, 2017, were screened, with 129 included for analysis. Median weight at PEG insertion was 3800 g. Superficial surgical site infection (SSI) occurred in 6 (4.7%) patients, and 1 (0.8%) required readmission for intravenous antibiotics. One (0.8%) required endoscopic management for retained foreign body, 1 (0.8%) required operative management for gastrocolic fistula, and 1 (0.8%) for persistent gastrocutaneous fistula. No deep space SSI, procedure-related hemorrhage requiring readmission or transfusion, buried bumper syndrome, or procedure-related mortality occurred. Conclusion: Traditional PEG tube insertion in infants less than 5 kg results in complication rates comparable to pediatric literature standards. Level of Evidence: Level II, retrospective prognosis study.
Keywords: percutaneous endoscopic gastrostomy tube; antibiotic agent; article; bleeding; colon fistula; endoscopic therapy; female; foreign body; hospital readmission; human; infant; major clinical study; male; medical record review; outcome assessment; percutaneous endoscopic gastrostomy; peroperative complication; priority journal; prognosis; reoperation; retained instrument; retrospective study; stomach fistula; surgical infection; tertiary care center; tube removal

Photorefractive intrastromal corneal crosslinking for treatment of myopic refractive error: Findings from 12-month prospective study using an epithelium-off protocol - Elling, M.; Kersten-Gomez, I.; Dick, H.B. (Journal of Cataract and Refractive Surgery, 2018)
Purpose: To assess the long-term effectiveness and safety of photorefractive intrastromal corneal crosslinking (CXL) in patients with low myopia. Setting: Ruhr University Eye Hospital, Bochum, Germany. Design: Prospective case series. Methods: Healthy eyes with myopia were treated with photorefractive intrastromal CXL using the Mosaic System. Riboflavin 0.1% solution (VibeX Rapid) was topically administered, followed by 365 nm ultraviolet-A (30 mW/cm2) irradiance. Efficacy was assessed by the uncorrected distance visual acuity (UDVA), manifest refraction spherical equivalent (MRSE), and keratometry. Safety was assessed by corrected distance visual acuity (CDVA), slitlamp biomicroscopy, endothelial cell count, and adverse event rates. Results: Fourteen patients (24 eyes) with a mean age of 35.7 years were included. At all follow-ups, a statistically significant improvement in UDVA was observed (all P <.001). The CDVA progressively improved from 1 month postoperatively and a statistically significant improvement was achieved at 12 months (P <.001). The average reduction in manifest sphere was 0.90 diopter (D) ± 0.40 (SD) by 12 months. There were no significant differences in mean manifest sphere and MRSE at 3, 6, or 12 months. Compared with baseline, significant reductions in corneal curvature were also observed at all follow-ups (all P <.05). There were no significant changes in endothelial cell density (P = 1.00) or number of cells (P =.95) at 12 months postoperatively, and no adverse events were reported. Conclusion: Photorefractive intrastromal CXL was a safe and efficacious treatment of refractive error in patients with low myopia.
Keywords: riboflavin; vibex rapid; adult; adverse outcome; article; cell density; clinical article; cornea curvature; cornea surgery; corrected distance visual acuity; dry eye; endothelium cell; follow up; foreign body; Germany; human; keratometry; light irradiance; low myopia; manifest refraction spherical equivalent; myopia; photorefractive intrastromal corneal crosslinking; postoperative complication; priority journal; prospective study; slit lamp microscopy; ultraviolet A radiation; uncorrected distance visual acuity; university hospital; visual acuity; visual system parameters; vibex rapid

Retained surgical sponge: Medicolegal aspects - Gualniera, P.; Serena, S. (Legal Medicine, 2018)
Retained surgical sponge events continue to occur despite the implementation of preventive surgical count policies, procedures, and adjunct technologies to manual counting. Such intraoperative mistakes can cause chronic nonspecific symptoms during the early postoperative period. When discovered years after surgery, they raise thorny medicolegal questions. We describe two cases from our practice that illustrate the need to identify the responsibility of the surgical team, as delineated in ministerial directives and the current legal framework, as well as the difficulty in evaluating clinical actions taken at different times and in different settings, with regard to the permanent health damage incurred by sponge retention. Finally, we discuss prevention actions operating room staff should take to reduce the risk of retained surgical sponges.
Keywords: surgical sponge; adult; appendectomy; article; case report; clinical article; colic; computer assisted tomography; dyspepsia; female; foreign body reaction; gallstone; granulomatous inflammation; human; hypertransaminasemia; hysterectomy; laboratory test; laparoscopic cholecystectomy; medicolegal aspect; middle aged; neurosis; postoperative period; retained instrument; risk factor; surgical patient; vomiting

Evaluation of patient safety checklist in surgical block in CH & ICH Lahore - Naseem, S.; Saleem, M. (Pakistan Paediatric Journal, 2018)
Introduction: Patient safety in Operation theatre is one of the greatest challenges in Health care. Ensuring patient safety in operating room begins as the patient enters the operation theatre and includes attention to all applicable types of preventable medical faults (including, for example medication mistakes), so that surgical errors should be rare to this environment. Steps to avoid wrong-site, wrong-person, wrong-procedure errors, or retained foreign objects unchecked blood transfusions, mismatched organ transplantation and un-noticed allergies have been recommended, it should start with a structured communication between the patient, the surgeon(s), and other health care team members. Prevention of surgical errors requires the watchfulness of all personnel involved in the patient's care. Objective: The aim of this current study is to improve patient safety in operation room. Method: Descriptive study design was used. This study was conducted in six months in Main Operation Theatre Children Hospital and Institute of Child Health Lahore. 288 Patients were analysed in Main Operation theatre, which were selected through convenient sampling technique. Their age ranges from 1to 14 years. WHO Surgical Safety Checklist was used to evaluate patient safety in surgical block. Results: There were 288 patients analysed in the operating room block, for surgical management, to improve patient safety. Each step of standard surgical safety checklist was observed and filled. Checklist is divided into three steps before induction on anaesthesia, start of surgical intervention and before any team member leaves operating room. 96.9% consent forms, 96.6% patient identity site procedures confirmed, 75.3% surgical site marked, 88.9% anaesthesia machine and medication check complete, 8.7% patient have known allergy, 0% patient have difficult airway aspiration rate, 41.3% risk of >500ml blood loss, 28.8% team members introduced themselves, 95.5% patient name, 96.6% procedure site position planned, 61.8% if blood loss is anticipated, arranged and matched, 52.1% specific equipment required, 5.9% critical or unexpected steps. 23.3% patients specific concerns, 93.1% monitoring equipment e. g. blood, 86.8% sterility of instruments confirmed, 23% are there equipment issues or concerns, 99.7% surgical site bundle undertaken, 100% antibiotic prophylaxis, 29% patient warming, 22.2% hair removal, 100% glycemic control, 0% VTE prophylaxis, 86.1% essential imaging undertaken, 98.6% has name of procedure recorded, 99% has it confirmed instruments swabs counts complete, 93.1% specimen been labelled,10.1% have any equipment problems been identified that need to be addressed.
Keywords: airway; allergy; anesthesia gas machine; antibiotic prophylaxis; aspiration; bleeding; checklist; clinical evaluation; conference abstract; female; glycemic control; hair removal; human; human tissue; identity; infant; informed consent; major clinical study; male; monitoring; operating room; patient safety; pediatric hospital; plant leaf; prevention; sampling; study design; surgery; surgical error; warming

Intrapericardial gossypiboma: Rare cause of intrathoracic mass - Kumar, A.; Paswan, S.S.; Prashad, R.; Kumari, R.; Kumar, B. (International Journal of Surgery Case Reports, 2018)
Introduction: Gossypiboma is a retained surgical sponge inside our body after surgical intervention. It is most commonly found in abdominal cavity. Its occurrence in thoracic cavity as intrapericardial gossypiboma is extremely rare. Presentation of case: We present a 25 year old male with complaint of chest pain for 1 year. He had a history of total correction of Tetralogy of fallot 14 years back, at another hospital. On clinical examination and investigations including contrast enhanced computed tomography (CECT) of thorax; diagnosis of right anterior mediastinal mass of germ cell tumor was made and planned for thoracotomy. On exploration, the gauze piece of 31 cm was removed from the pericardial mass and a final diagnosis of gossypiboma was made. Discussion: Although gossypibomas are commonly reported in abdominal and pelvic surgery but a prolonged operative time, untrained staff, poor communication in sponge count may favour the occurrence in thoracic cavity. A patient with intrathoracic gossypiboma usually presents with chest pain, dyspnoea, thoracic mass or fever. CECT and Magnetic resonance Imaging (MRI) are useful imaging modality in such cases. Surgical exploration with histopathological examination confirms the diagnosis of gossypiboma. Conclusion: In a postoperative patient who presents with chest pain and intrathoracic mass, gossypiboma should be a differential diagnosis even it is rare to occur in thorax.
Keywords: surgical sponge; adult; article; case report; clinical article; computer assisted tomography; contrast enhancement; echocardiography; fine needle aspiration biopsy; follow up; foreign body; germ cell tumor; gossypiboma; histopathology; human; human tissue; male; mediastinum mass; pericardial disease; priority journal; retained instrument; thoracotomy; thorax pain; thorax radiography

Paranasal gossypiboma mimicking an aggressive tumor: a case report - Guerrouani, A.; Kairouani, M. (Clinical Case Reports, 2018)
Even if gossypibomas are extremely rare in the Oro-Maxillofacial region, they should be evoked in bizarre tumors when repeated histology tests are not contributive, especially in patients with a history of dento-sinusal surgery. As it is recommended in general surgery, gauzes should be carefully counted when used in dentistry.
Keywords: acetylsalicylic acid; biogaze; aged; aggression; article; basal cell carcinoma; blood pressure; blood transfusion; case report; clinical article; computer assisted tomography; coughing; endoscopy; epistaxis; epithelization; human; male; nose cavity; paranasal sinus disease; pharynx tumor; priority journal; suffocation; vascularization; very elderly; biogaze

Spontaneous hepatic rupture during emergency cesarean section in a patient with HELLP syndrome: A case report and literature review - Ma, B.; Cui, H.; Chen, X. (Clinical and Experimental Obstetrics and Gynecology, 2018)
Spontaneous hepatic rupture is a rare but life-threatening complication of pregnancy. Case Report: A 30-year-old woman with multi-para pregnancy was admitted to the hospital at 31+3 weeks of gestation who complained of abdominal pain localized in the right upper quadrant on the third day after admission. HELLP syndrome was diagnosed, and emergency cesarean section was performed. Within several hours, blood biochemistry revealed significant elevated liver enzymes and reduced platelet (PLT) count. HELLP syndrome was diagnosed and emergency cesarean section was performed. The authors also made a literature review on the reported cases with spontaneous hepatic rupture during pregnancy in mainland China. A total 39 cases were found. Maternal survival was 78.9% (30/38) and perinatal survival was 50% (21/42). Deaths occurred mainly due to disseminated intravascular coagulation (DIC), acute renal failure, respiratory failure, and so on. An emergency physician should be aware that early evaluation, appropriate diagnosis, and prompt surgical intervention are crucial to deal with such a life-threatening emergency. Multidisciplinary cooperation between obstetricians, surgeons, and pediatricians is required for treating spontaneous hepatic rupture during pregnancy.
Keywords: compression bandage; hemostatic sponge; alanine aminotransferase; antihypertensive agent; aspartate aminotransferase; bilirubin; blood clotting factor 7; cholinesterase; fresh frozen plasma; hemoglobin; lactate dehydrogenase; adult; alanine aminotransferase blood level; antihypertensive therapy; Apgar score; article; aspartate aminotransferase blood level; bilirubin blood level; bleeding; blood biochemistry; case report; cesarean section; cholinesterase blood level; clinical article; elevated blood pressure; emergency surgery; erythrocyte transfusion; female; gestational age; headache; HELLP syndrome; hemoglobin blood level; hemostasis; hepatomegaly; hospital admission; human; hypertransaminasemia; lactate dehydrogenase blood level; liver necrosis; liver rupture; multipara; pain severity; parenteral nutrition; peroperative complication; platelet count; postoperative care; spontaneous hepatic rupture; thrombocyte transfusion; upper abdominal pain

Transgastric endoscopic drainage of a peripancreatic abscess from a bbq brush bristle gastric perforation - Stewart, R.D.; Ellsmere, J. (Surgical Endoscopy and Other Interventional Techniques, 2018)
Introduction: Oropharyngeal and Gastrointestinal (GI) perforations from BBQ brush bristles are being reported in the literature with increasing frequency. Media attention to this problem has increased awareness by the public. Most commonly, BBQ bristles lodged in the GI tract can be removed endoscopically or pass without complication. Rarely, surgical intervention is required for removal of the bristle or drainage of an associated abscess. We report a case of gastric perforation by a BBQ bristle leading to a pancreatic abscess. Case Report: A 41-year-old male presented to a regional center with epigastric pain and malaise. His medical history included: hypertension, dyslipidemia, and smoking. His surgical history included: a tonsillectomy, excision of bronchial cleft cyst, and an umbilical hernia repair. On presentation, his laboratory investigations where unremarkable aside from an elevated white blood cell count. Investigations including an abdominal X-rays and an abdominal ultrasound were unremarkable. He was initially treated with a proton pump inhibitor for presumed peptic ulcer disease. He returned to the local emergency room, no better than before. A CT scan was arranged which demonstrated a foreign body at the pylorus consistent with a BBQ bristle and a peripancreatic fluid collection (Figs. 1 & 2). A gastroscopy failed to identify the bristle. He was admitted, placed on IV antibiotics and referred to our center. Despite several days of antibiotics prior to arrival, the collection size on repeat CT scan had increased and the patient had ongoing pain. We repeated the endoscopy with a side viewing endoscope. The perforation was identified posteriorly at the pylorus. The bristle had migrated into the peripancreatic space. The perforation was can-nulated with a Jagtome. Fluoroscopy was used to confirm the position of a wire in the fluid collection (Figs. 3 & 4). Pus was drained from the collection into the stomach by placement of a 5 French pigtail catheter (Fig. 5). [Image Presented] The patient was discharged pain free the following day. The patient was asymptomatic at 6 weeks' follow-up. A repeat CT scan showed resolution of the abscess and safe migration of the bristle and stent out of the GI tract (Fig. 6) Conclusion: To our knowledge, this is the first reported transgastric endoscopic drainage of a peripancreatic abscess caused by a BBQ bristle gastric perforation. This case is a demonstration of the ever-expanding role of therapeutic endoscopy in a surgical practice.
Keywords: antibiotic agent; proton pump inhibitor; abdominal radiography; adult; bronchus; case report; cell migration; clinical article; conference abstract; cyst; drainage catheter; dyslipidemia; emergency ward; endoscope; epigastric pain; excision; fluoroscopy; follow up; foreign body; gastrointestinal tract; gastroscopy; hernioplasty; hospital discharge; human; hypertension; leukocyte count; malaise; male; medical history; pancreas abscess; peptic ulcer; pus; pylorus; smoking; stent; stomach perforation; surgery; tonsillectomy; ultrasound; umbilical hernia; x-ray computed tomography

11 month old infant with a mediastinal mass with endobronchial extension presenting as persistent wheeze - Krich, D.A.; Krishnan, S.; Harris, K.N.; Arlievsky, N.; Dozor, A.J. (American Journal of Respiratory and Critical Care Medicine, 2018)
Introduction: Wheezing in infants is common, often unresponsive to bronchodilators, and usually improves over time. Therefore it can be challenging to determine when the benefits of an extensive diagnostic workup outweigh the risks. Unusual etiologies include anatomic anomalies, foreign body aspiration, endobronchial masses or external bronchial compression. Mediastinal masses in children are uncommon, and could have oncologic, infectious or embryologic origins. We report an 11 month-old with persistent wheeze unresponsive to therapy. Case Report: An 11 month previously health male infant was referred for evaluation of persistent wheeze for almost 2 months, unresponsive to inhaled bronchodilators and corticosteroids. There was no history suggestive of foreign body aspiration. There was a history of travel to Mexico, but no history of contact with tuberculosis. On physical examination, breath sounds seemed diminished on the left compared to the right, and there was an intermittent wheeze heard more loudly on the left. Previous chest x-rays were reported to be normal, but review suggested the left lung was more lucent than the right. CT and MRI suggested a middle mediastinal mass, 3 x 4 cm, with extension into the left main-stem bronchus. Blood counts, routine chemistry, ESR, CRP, quantitative immunoglobulins, fungal serology, and an interferon-gamma release assay for tuberculosis were all within normal limits. Mantoux was non-reactive. Blood cultures showed no growth. Flexible bronchoscopy confirmed an endobronchial mass, 1 cm in diameter, with > 90% occlusion of the left bronchus. With the assistance of Interventional Pulmonology, the mass was removed piecemeal with a biopsy forceps using a 4.0 mm OD flexible bronchoscope inserted through a laryngeal mask airway (LMA). Gram/Giemsa and AFB stains were non-conclusive. Histopathology reported necrotizing granuloma, etiology unknown. Subsequently, the mediastinal mass was removed by video-assisted thoracoscopic surgery. Smears/stains were negative, and histopathology confirmed necrotizing granulomas from which Mycobacterium avium complex was cultured. Subsequent history revealed the child often played in the soil/dirt on their family farm. Discussion: NTM presenting as a mediastinal mass with endobronchial occlusion has not been previously reported in infants less than 1 year of age. This case highlights the importance of close monitoring and evaluation of a young, otherwise healthy infant with persistent wheeze non-responsive to bronchodilators. Radiologic reports can be misleading. A detailed environmental history, even in very young children, can contribute to diagnosis. Interventional flexible bronchoscopic techniques can permit removal of endobronchial masses in young children without intubation and potential morbidities of rigid bronchoscopy.
Keywords: bronchodilating agent; corticosteroid; endogenous compound; immunoglobulin; biopsy forceps; blood cell count; blood culture; boy; chemistry; child; conference abstract; diagnosis; fiberoptic bronchoscopy; flexible bronchoscope; foreign body aspiration; granuloma; histopathology; human; human cell; human tissue; in vitro study; infant; interferon gamma release assay; intubation; laryngeal mask; left lung; male; mediastinum mass; Mexico; monitoring; morbidity; Mycobacterium avium complex; nonhuman; nuclear magnetic resonance imaging; occlusion; physical examination; pulmonology; serology; soil; stain; thorax radiography; travel; tuberculosis; video assisted thoracoscopic surgery; wheezing

Late presentation of retained intrathoracic foreign body - Kaur, P.; Elshimy, G.; Singh, B. (American Journal of Respiratory and Critical Care Medicine, 2018)
Introduction: In the great majority of cases of long-standing intrathoracic foreign bodies, patients are asymptomatic. Rarely, transthoracic foreign bodies cause problems when left lodged in the pulmonary parenchyma. Early removal is required only in cases of pneumonia, lung abscess, empyema or proximity to a major organ. When left in place, bullets or other foreign bodies become surrounded over time by fibrous tissue and do no harm. Only few cases in literature reported symptoms that occur decades after the injury. Case report: We report a case of 37 years old Hispanic female with past medical history of Hypertension who presented to the emergency department with hemoptysis 10 years after having a bullet injury to her chest when she was on her home roof in Dominican Republic. Patient remained asymptomatic for 10 years and no intervention was done at the time of the incident. However, she started having recurrent small amount of hemoptysis along with retrosternal non-radiating chest pain and exertional shortness of breath for the past year. The only abnormal physical findings were the old healed scar at left 2nd intercostal space in midclavicular line and minimal rhonchi in left upper and lower lung fields on auscultation. Laboratory testing was normal including platelet count, coagulation test, kidney functions, urine studies and sputum smears for malignancy and infection. The chest x ray showed bullet fragment in left upper lung field and Computerized Tomography Angiography of the chest showed bullet fragment with surrounding infiltration in left upper lobe, peri-hilar ground-glass infiltrates secondary to pulmonary hemorrhage. Patient was hospitalized and bronchoscopy was done that showed bloody secretions in the apical segment of LUL which was successfully suctioned without an obvious source of bleed. Thoracic surgery was consulted but the plan was made to manage conservatively. Patient was discharged and was followed up afterwards for 1 year. No more episodes of hemoptysis were documented. Conclusion: Complications caused by foreign bodies retained in the lungs may arise many years after the initial injury. Among the symptoms and signs, hemoptysis is the most common. Our patient has the symptoms 10 years after the initial bullet injury. The management depends upon clinical scenario, if the patient has persistent chest wall pain or persistent purulent expectoration or hemoptysis, foreign body should be removed otherwise with minor and self-resolving episodes, conservative management is the treatment of choice.
Keywords: glass; adult; auscultation; blood clotting test; bodily secretions; bronchoscopy; cancer patient; cancer recurrence; case report; clinical article; complication; computed tomographic angiography; conference abstract; conservative treatment; Dominican Republic; dyspnea; emergency ward; female; foreign body; gunshot injury; hemoptysis; Hispanic; hospital discharge; human; human tissue; hypertension; infection; kidney function; laboratory test; lung hemorrhage; malignant neoplasm; medical history; physical examination; platelet count; scar; sputum smear; thorax pain; thorax radiography; thorax surgery; urine

Novel Diagnostics in Revision Arthroplasty: Implant Sonication and Multiplex Polymerase Chain Reaction - Hischebeth, G.T.R.; Gravius, S.; Buhr, J.K.; Molitor, E.; Wimmer, M.D.; Hoerauf, A.; Bekeredjian-Ding, I.; Randau, T.M. (Journal of visualized experiments : JoVE, 2017)
In orthopedic patients, foreign body-associated infections, especially periprosthetic joint infections (PJIs), are a devastating complication of arthroplasty. Infection requires complex treatment, may result in long hospitalization and causes considerable costs. Multiple surgical revisions can be necessary in these patients, with a loss in function as well as in quality of life. The routine preoperative diagnostics include blood examination for C-reactive protein (CRP) and other biomarkers, as well as joint aspirate analysis for cell count, differentiation, and culture. Intraoperative specimens for histology and microbiology are also standard procedure. The microbiological examination of removed implants with sonication, in combination with the implementation of molecular biology techniques in microbiology, represent two novel techniques currently employed to enhance the differential diagnostics of PJI. We present here the step-wise procedure of analyzing joint aspirate and sonication fluid, using a cartridge-based multiplex polymerase chain reaction (PCR) system. Results were matched against conventional cultures and consensus criteria for PJI. Conventional microbiological cultures from tissue biopsies, joint aspirate and sonication fluid showed a sensitivity of 66.7%, 66.7%, and 88.9%, respectively, and a specificity of 82.3%, 54.6%, and 61.5%, respectively. The PCR diagnostic of the sonication fluid and the joint fluid showed a sensitivity of 50.0% and 55.6%, respectively, and both a specificity of 100.0%. Both PCR diagnostics combined had a sensitivity of 66.7% and a specificity of 100.0%. The multiplex PCR therefore presents a rapid diagnostic tool with moderate sensitivity but high specificity in diagnosing PJI.
Keywords: arthroplasty; human; infection; microbiology; polymerase chain reaction; procedures; prostheses and orthoses; ultrasound

A case of renal gossypibomas mimicking tumor pathological discovery - Doh, K.; Thiam, I.; Takin, R.C.A.; Bissirou, I.; Gaye, G.W. (African Journal of Urology, 2017)
Introduction The gossypibomas is an inflammatory granuloma centered by textile fibers forgotten during surgery. Renal gossypibomas is a rare post-operative complication. The authors report a case of gossypibomas simulating kidney tumor pathological discovery. Observation The patient A. G. 53 years old, with a history of left nephrolithotomy by lumbotomy 5 years earlier was admitted for left lumbar pain lasting for 4 months. The uro-scan was consistent with an upper polar cyst Bosniack III. Macroscopic examination of the nephrectomy piece noted, a cystic cavity 7x6 cm containing gauze surrounded by a gelatinous substance. The histological sections showed a thickened wall, including calcification foci and granulomatous reaction to foreign bodies. The diagnosis of a pseudo-tumor gossypibomas left kidney was retained. Conclusion The textile fibers may trigger an acute inflammatory reaction with formation of a perirenal abcess if aseptic resulting in the formation of fibrotic foci, encystment and calcification. Renal gossypibomas pose diagnostic difficulties in the absence of pathognomonic clinical and radiological signs. The presence of a renal mass associated with a history of kidney surgery on the same side should suggest first a gossypibomas. The treatment is surgical. Partial nephrectomy is the treatment of choice. The best treatment remains prevention by careful gauze counts, and surgical drapes in the beginning and end of intervention.
Keywords: adult; article; calcification; case report; clinical article; computer assisted tomography; cyst; disease duration; foreign body; granulomatosis; histopathology; hospital admission; human; human tissue; kidney disease; kidney tumor; low back pain; lumbotomy; medical history; middle aged; nephrolithotomy; postoperative complication; pseudotumor; pseudotumor gossypibomas left kidney; surgical technique

A missed diagnosis of multiple intraocular foreign bodies for 21 years - Yang, X.; Liu, C.; Liu, L.; Zhang, L. (Contact Lens and Anterior Eye, 2017)
A 30-year-old patient went to the emergency department because of a chemical burn to the left eye more than 10 days ago by toilet cleanser. Surprisingly, a small piece of glass was found in the inferior anterior chamber in the same eye. The visual acuity was counting fingers. There was conjunctival congestion, corneal oedema and Descemet's membrane striae. And there was also a corneal leukoma around 4 to 5 o'clock. Through repeated questioning he recalled that he was injured by an exploded light bulb around 21 years ago. He was asymptomatic until he saw “something moving” in front of the left eye one month ago. Computed tomography (CT) scanning, ultrasonography, ultrasound biomicroscopy (UBM), anterior segment optical coherence tomography (AS-OCT) verified the presence of multiple intraocular foreign bodies (IOFBs) in the anterior chamber and vitreous cavity. B-scan verified the IOFB in the vitreous cavity. Thus, he was diagnosed with corneal chemical burn, IOFBs and corneal leukoma of the left eye. The IOFB in the anterior chamber was removed through surgery. An attempt was made to remove the IOFB in the vitreous cavity with electromagnet, but it was not successful. Vitrectomy could not be performed as it was hindered by the opacity of cornea. After surgery, the visual acuity remained counting fingers and the corneal oedema still existed. This case is a reminder that a detailed history taking, a thorough physical examination and modern imaging techniques are beneficial for establishing the diagnosis and treatment of IOFBs.
Keywords: adult; article; B scan; biomicroscopy; case report; chemical burn; clinical article; clinical feature; computer assisted tomography; conjunctiva disease; conjunctival congestion; cornea disease; cornea edema; corneal leukoma; diagnostic error; disease duration; echography; human; intraocular foreign body; male; optical coherence tomography; priority journal; stria; visual acuity

Incidence, root cause, and outcomes of unintentionally retained intraabdominal surgical sponges: A retrospective case series from two hospitals in Togo - Tchangai, B.; Tchaou, M.; Kassegne, I.; Simlawo, K. (Patient Safety in Surgery, 2017)
Background: The term gossypiboma refers to a sponge that has been forgotten in the surgical field. It is the most common retained surgical item, and constitutes a continuing problem for surgical safety. We performed a hospital-based study to examine their incidence, root cause, and outcomes, as an effort toward improving prevention. Methods: This retrospective study covered 10 years (2006-2015) and included surgically confirmed cases of abdominal gossypibomas occurring after 45,011 abdominal and gynaecological operations in 2 public hospitals in Lome (Togo). Age, diagnosis, initial surgical procedure, evidence of textile count, and data related to the revision procedure were collected for descriptive analysis. Results: Fifteen cases of gossypibomas (11 women and 4 men) were recorded. The mean age of the patients was 27 (range 21-55) years. Initial procedures were gynaecological in 11 patients and 5 cases involved an emergency surgery. Evidence of sponge counting was found in 6cases. Gossypiboma was an incidental finding in 1 patient. The average time to onset of symptoms after the initial procedure was 2 months. The gossypiboma was removed within 7 days to 4 years after the initial procedure. Postoperative complications included enterocutaneous fistula in 2 patients, incisional hernia in 2 patients, and wound sepsis in 1 patient. Death occurred in 2 patients (13.3%). Conclusions: Although rare, the incidence of gossypibomas is still unacceptably high and reveals failures regarding patient safety standards. The associated morbidity and mortality are significant, yet can be reduced by an early diagnosis in the immediate postoperative period. A systematic methodical count of sponges is the cornerstone of prevention, and introducing surgical safety protocols, such as the WHO Safe Surgery Saves Lives checklist, can enhance effectiveness. There is a crucial need for safety-focused policies, which may include a never event reporting system, elaboration of prevention strategies, interventions, and evaluation.
Keywords: abdominal gossypiboma; abdominal mass; abdominal pain; abdominal surgery; abdominal tenderness; adult; article; causal attribution; clinical article; emergency surgery; enterocutaneous fistula; excision; female; fever; gynecologic surgery; hospital; human; human tissue; incidental finding; incisional hernia; male; outcome assessment; patient safety; postoperative complication; reoperation; retrospective study; surgical mortality; symptom; Togo; treatment failure; vomiting; wound infection

First identification of Gordonia sputi in a post-traumatic endophthalmitis patient - a case report and literatures review - Fang, W.; Li, J.; Cui, H.-S.; Jin, X.; Zhai, J.; Dai, Y.; Li, Y. (BMC ophthalmology, 2017)
BACKGROUND: We present a case of post-traumatic endophthalmitis with relatively good prognosis caused by Gordonia sputi, which, to our knowledge is the first case in the literature. CASE PRESENTATION: A 24 year old man, who underwent an intraocular foreign body extraction half a month before presentation in the left eye, was referred to us complaining of blurred vision and slight pain for 5 days. His first presentation showed moderate intracameral and intravitreous purulent inflammation with a best corrected vision of counting fingers. After gram staining of the intravitreous samples revealed a gram-positive bacilli infection, a combination of amikacin and vancomycin was initially injected intravitreously. The left eye kept stable for three days but deteriorated on the 4th day. On the 5th day after presentation conventional culture characterized the bacterium as an Actinomyces sp. while 16S ribosomal RNA gene sequencing confirmed it as Gordonia sputi. Thereby a complete pars plana vitrectomy combined with lensectomy and silicone oil tamponade was performed. During the surgery an intraocular irrigation with penicillin G was adopted, followed by administration of intravenous penicillin G twice one day for a week. A relatively normal fundus with slight intracameral inflammation was observed a week after the operation, and the best corrected vision recovered to 0.15. One year later his vision remained 0.1. CONCLUSION: Gordonia sputi should be taken into consideration in patients with post-traumatic endophthalmitis especially due to foreign body penetration. Compared to conventional laboratories, molecular methods are recommended for an accurate diagnosis. A comprehensive strategy of antimicrobial agents and vitrectomy may render a satisfactory result.
Keywords: antiinfective agent; bacterial RNA; penicillin G; RNA 16S; silicone oil; Actinomycetales infection; bacterial eye infection; case report; endophthalmitis; endotamponade; eye injury; genetics; Gordonia; human; intraocular foreign body; isolation and purification; lens; male; microbiology; multimodality cancer therapy; surgery; vitrectomy; young adult

Surfboard-related intraorbitalforeign bodies - A case series and adiological considerations - Leung, V.; Beshay, N.; Dunn, H.; Smith, J.; O'Donnell, B. (Clinical and Experimental Ophthalmology, 2017)
Purpose. Surfboard-related eye injuries are increasingly being reported. There is little clinical or radiological information of injuries with retained intraorbital foreign bodies. To our knowledge, this is the largest case series of such patients and the first description of a surfboard fibreglass foreign body misreported as a displaced bone fragment. Methods. Retrospective case series of surfboardrelated eye injuries with intraorbital foreign bodies collected from tertiary ophthalmology centres in Sydney, Australia. Results. Three male patients with an average age of 43 years presented with blunt orbital trauma from the nose of a surfboard. Visual acuity was comparable to baseline in two patients and count fingers in the third. All patients had proptosis, no evidence of penetrating ocular injury and no posterior segment pathology. Two patients had sluggish pupillary responses requiring urgent lateral canthotomy. CT imaging was performed in all patients. A fibreglass intraorbital foreign body of 1165 Hounsfield units was misreported as a displaced orbital wall fragment in one patient. Foreign bodies were correctly reported in remaining patients. All patients underwent surgical exploration, foreign body extraction and lacrimal apparatus/skin repair with no subsequent oculoplastic or visual sequelae. Conclusion. Surfboard-related eye injuries may involve retained intraorbital foreign bodies. Fibreglass used in surfboard construction has a similar radiological appearance and density to bone on CT imaging thus may be misinterpreted as a bone fragment. A high suspicion for fibreglass foreign bodies should be exercised in orbital surfboard injuries.
Keywords: adult; Australia; case report; case study; complication; exophthalmos; extraction; eye injury; finger; foreign body; human; lacrimal apparatus; male; nose; ophthalmology; orbit injury; pathology; retrospective study; skin; surgery; visual acuity

Small bowel obstruction in ileal J-pouch from coin ingestion - Ratra, A.; Conti, J. (American Journal of Gastroenterology, 2017)
Introduction Small bowel obstruction is a common complication after ileal J-pouch-anal anastomosis (IPAA). Adhesions are the most frequent cause. Foreign body ingestions are uncommon in adults. We report a rare case of a small bowel obstruction in an adult patient with IPAA after coin ingestion. Case Description A 72 year old man with history of refractory ulcerative colitis underwent protocolectomy with ileal J-pouch-anal anastomosis in 1999. He presented to the emergency department in December 2016 with complaint of crampy, lower abdominal pain, nausea and vomiting for two days. He denied any fever or chills. No constipation or diarrhea. Lab studies revealed a normal white blood cell count, normal lipase and normal liver function tests. CT scan of the abdomen revealed a dilatation of the distal ileum measuring 38 mm in diameter, small bowel wall thickening and mesenteric fat stranding proximal to the ilioanal anastomosis. Findings were concerning for small bowel obstruction with transition point at the ilioanal anastomosis. Patient underwent pouchoscopy which revealed erythematous mucosa in the j-pouch and presence of a severe stricture measuring about one cm in length and 7mm in diameter (Figure 1). The stricture was traversed after balloon dilation under fluoroscopic guidance (Figure 2). A United States penny coin was found proximal to the stricture which was retrieved from the j-pouch using a Roth Net® retriever (Figure 3). Patient had resolution of his symptoms after the procedure. Patient might have inadvertently swallowed the coin along with his daily pills which he routinely kept in his pants pocket. Discussion Coin and other foreign body ingestions are common in pediatric population but infrequent in adults. Swallowed items that pass beyond the pylorus are simply observed as they usually pass spontaneously through the gastrointestinal tract. Retained foreign bodies can increase the risk of complications by 50%, including formation of strictures, fistulas, abscesses, perforation, sepsis and death. It is estimated that up to 35% patients with IPAA experience small bowel obstruction most commonly due to extensive adhesions. It is possible that the high zinc content in the penny coin might have contributed to the inflammation and stricture formation in the j-pouch. Our case illustrates that retained foreign bodies can be safely and successfully removed endoscopically in patients with IPAA without need for open surgery. (Figure Presented).
Keywords: endogenous compound; triacylglycerol lipase; zinc; abdomen; abscess; adhesion; adult; aged; balloon dilatation; case report; child; chill; clinical article; complication; conference abstract; constipation; death; diarrhea; emergency ward; fever; fistula; foreign body; gastrointestinal tract; human; ileal pouch-anal anastomosis; ingestion; leukocyte count; liver function test; lower abdominal pain; male; mesenteric fat; mucosa; nausea and vomiting; open surgery; perforation; pill; pylorus; sepsis; small intestine obstruction; small intestine wall; stenosis; ulcerative colitis; United States; x-ray computed tomography

Stuck in the gut. An unusual duodenal bezoar following pyloric-exclusion gastrojejunostomy - Kukreja, K.; Meriwether, M.; Maiti, A.; Faruki, A.; Salahudeen, A.; Rahimi, E.F. (American Journal of Gastroenterology, 2017)
Introduction: Bezoars are foreign-bodies classified by their composition, with phytobezoars (indigested vegetable matter) being the most common. They are a rare entity usually found incidentally on imaging or routine endoscopy and tend to occur in patients with altered gastric anatomy such as following surgery. To our knowledge, no case reports exist of a small-intestinal phytobezoar following an unreversed pyloric-exlusion gastrojejunstomy. Case: A 19 year-old female with a history of blunt abdominal trauma at 18-months requiring pyloric-exclusion gastrojejunostomy presented with right-upper-quadrant (RUQ) abdominal pain, nausea, vomiting, and diarrhea associated with a 20-lb weight loss over the past few months. Her vital signs, complete blood count, and basic metabolic profile were unremarkable. Abdominal computed tomography with intravenous contrast revealed a large, ovoid, low-attenuation mass within the RUQ measuring 6.6 cm x 5.3 cm x 6.9 cm. Magnetic resonance imaging confirmed a mass in the duodenal bulb, most consistent with a bezoar (Panel A). Subsequent upper endoscopy exposed the yellow-colored bezoar extending from the 3rd portion of the duodenum into the proximal jejunum (Panel B). Additionally, it was noted on endoscopy that the patient's pyloric-exclusion was never reversed, suggesting the bezoar likely formed due to years of reflux from the jejunum into the duodenum. A schematic diagram of the location of the bezoar is provided (Panel C). Due to technical difficulty reaching the bezoar and insufficient pyloric dilatation endoscopically, she ultimately required surgical intervention with pyloroplasty to achieve complete removal of the bezoar. At follow-up, she reported resolution of symptoms and improvement in appetite with weight gain and regular bowel function. Discussion: Pyloric-exclusion gastrojejunostomy is performed as a temporizing measure when duodenal ischemia is suspected, as in our patient following blunt abdominal trauma. However, in unusual cases where patients do not have the pyloric exclusion reversed, reflux of food material into the duodenum can occur and result in a symptomatic bezoar formation. (Figure Presented).
Keywords: abdominal blunt trauma; abdominal pain; adult; ampulla of Vater; appetite; attenuation; bezoar; blood cell count; body weight gain; body weight loss; case report; clinical article; computer assisted tomography; conference abstract; diarrhea; dilatation; endoscopy; female; follow up; gastrointestinal tract; gastrojejunostomy; human; intestine function; ischemia; jejunum; nausea and vomiting; nuclear magnetic resonance imaging; pyloroplasty; surgery; vital sign; young adult

How many people work in your operating room? An assessment of factors associated with instrument recounts within plastic surgery - Reformat, D.D.; David, J.A.; Diaz-Siso, J.R.; Plana, N.M.; Wang, A.; Brownstone, N.D.; Ceradini, D.J. (Journal of Plastic, Reconstructive and Aesthetic Surgery, 2017)
Background Intraoperative instrument recounts are performed to avoid retained foreign surgical items. These additional counts, however, beget risks of their own, including prolonged operative times, exposure to radiation, and increased cost. Our study aimed to identify factors that increase the likelihood of instrument recounts during plastic surgery procedures, and use our findings to guide potential solutions for preventing unnecessary recounts across all surgical fields. Study design This is a retrospective review of all plastic surgical cases in the main operating setting at New York University Langone Medical Center (NYULMC) between March 2014 and February 2015. Results Of 1285 plastic surgery cases, 35 (2.7%) reported a missing instrument necessitating a recount. Of all subspecialties within plastic surgery, only microsurgery conferred an increased risk of a recount event. We identified multiple factors that increased the odds of a recount event, including increased operative time, number of surgical sites, and intraoperative instrument handoffs. Conclusion Instrument recounts, although designed to prevent inadvertently retained surgical items, present inherent risks of their own. In a large retrospective review of plastic surgery cases at our medical center, we identified many factors that increased the likelihood of an instrument recount. On the basis of our findings and prior literature, we recommend limiting the number of staff handling instrument, the number of handoffs, and a heightened awareness by surgeons and perioperative staff of specific procedures and factors that increase the risk of a miscount event.
Keywords: adult; article; clinical article; controlled study; human; instrument recount; intraoperative period; medical procedures; medical student; microsurgery; middle aged; operating room; operating room personnel; operation duration; patient safety; plastic surgery; priority journal; resident; retrospective study; risk factor; surgical equipment; work

Characterization of the T cell population in vaginal mesh removed from women with complications - Tennyson, L.; Palcsey, S.; Abramowitch, S.D.; Moalli, P.A. (Female Pelvic Medicine and Reconstructive Surgery, 2017)
Objectives: The macrophage is typically the predominant cell type in the foreign body response. In a recent study, T cells were almost as prevalent as mac-rophages in the cellular infiltrate surrounding polypropylene mesh fibers in a nonhuman primate model. It is well documented that T lymphocytes play a prominent role in the progression of pathologic tissue fibrosis. We aimed to further characterize the T cell response to vaginal mesh in the context of the overall foreign body response. Methods: Patients scheduled to undergo surgical excision of a mid-urethral sling for the complaint of pain vs. exposure were offered enrollment. 25 mesh-vaginal tissue complexes (exposure, n= 14; pain n= 11) were compared to 8 full thickness vaginal biopsies taken at the time of mesh excision from an uninvolved area on the anterior vaginal wall (control). Identification of T lymphocyte subsets was performed with immunofluorescent labeling. Tissue sections were quadruple-labeled for CD4+ (T helper), CD8 (cytotoxic T), Foxp3 (regulatory T cells) and nuclear marker DAPI. Six 200x images were taken from control tissue and two representative areas of mesh-tissue interface using a Nikon Eclipse 90i Imaging Microscope. Total numbers of cells were counted along with the number of cells that co-labeled with CD4, CD8 and Foxp3. A one-way ANOVA was performed with Tukey post hoc testing for multivariate analysis. Results: Demographics including age, BMI, parity, smoking history, meno-pausal status, hormone use and average time of mesh implantation did not differ between groups. Mesh-tissue complexes demonstrated a marked, but highly localized foreign body response similar to what has been described. We consistently observed a teardrop shaped fibroma encapsulating mesh fibers in both pain and exposure groups, with the T cells localized within the “cap”of this configuration away from the mesh-tissue interface. This is in contrast to the localization pattern of macrophages, which is limited to the area immediately surrounding mesh fibers. We found significantly more CD4+ (T helper) cells in both mesh groups (pain, p= 0.03; and exposure, p= 0.04) compared to controls. We also found more Foxp3+ (Tregs)in the exposure group comparedto controls (p= 0.02) but not in the pain group compared to controls (0.36). We did not find significant differences between the numbers of CD8+ (cytotoxic T) cells in either the pain (p= 0.86) or exposure group (p= 0.88) vs controls. When comparing the pain and exposure groups, we did not find significant differences between any of the T cell subtypes. On paired analysis there were significantly greater CD4+, CD8+, Foxp3+ and total number of cells in the mesh-tissue complexes compared to their controls (p=.0005, p=.01, p=.001 and p=.002, respectively.) Conclusions: T cells are present within a highly specific distribution area around vaginal mesh fibers explanted from women with complications. The complexity of the T cell response as it relates to mesh complications is not well understood but may be a central pathway with differing clinical presentations. Further research examining how T lymphocytes influence human response to vaginal mesh will broaden our understanding of mesh biology and clinical outcomes.
Keywords: CD4 antigen; CD8 antigen; endogenous compound; hormone; transcription factor FOXP3; adult; analysis of variance; biology; biopsy; body mass; cell population; clinical article; clinical outcome; complication; controlled study; cytotoxic T lymphocyte; excision; female; fiber; fibroma; foreign body; helper cell; human; human cell; human tissue; immunofluorescence; implantation; macrophage; multivariate analysis; outcome assessment; pain; parity; regulatory T lymphocyte; smoking; suburethral sling; T lymphocyte subpopulation; thickness; tissue section; vagina tissue

Leaks in fixed-ring banded sleeve gastrectomies: a management approach - Foo, J.W.; Balshaw, J.; Tan, M.H.L.; Tan, J.T.H. (Surgery for Obesity and Related Diseases, 2017)
Background The use of a Fobi ring to prevent pouch dilation is sometimes used in Roux-en-Y gastric bypass (RYGB). Recently, it has been extrapolated to laparoscopic sleeve gastrectomy (LSG) procedures by placing a fixed-ring band a few centimeters below the gastroesophageal junction (GEJ). Objectives What is the consequence if a patient develops a leak? Setting Tertiary metropolitan referral center, Australia. Methods Over 18 months, all patients with either a conventional LSG or a fixed-ring banded sleeve gastrectomy (BLSG) who presented with a proven leak complication were included. The management approaches along with the surgical, endoscopic, and percutaneous procedures used were examined. Results Six patients had a BLSG leak and 6 had a LSG leak. All patients had leak resolution. There was no significant difference in body mass index (BMI), time to leak, initial white cell count (WCC), and C-reactive protein (CRP) levels between the 2 groups. LSG patients required a median of 2 endoscopic procedures (range: 1–3). Stents were deployed in 3 patients. All BLSG patients required a single surgical intervention with laparoscopic washout, drainage, removal of band±feeding jejunostomy. One stent was deployed in 1 BLSG patient. BLSG leak resolution was found at 34±12 days versus 85±12 days in the LSG group (P<.05). Conclusion The BLSG is a new modification of the sleeve gastrectomy procedure. This study presents a management strategy for leak resolution employed in BLSG patients. The presence of a foreign body as a persistent nidus of infection mandates band removal.
Keywords: C reactive protein; adult; article; Australia; body mass; clinical article; computer assisted tomography; diet supplementation; endoscopic surgery; enteric feeding; female; fixed ring banded sleeve gastrectomy; gastric banding; gastric leak; human; jejunostomy; laparoscopic sleeve gastrectomy; length of stay; leukocyte count; male; middle aged; percutaneous drainage; postoperative complication; priority journal; reconstructive surgery; sleeve gastrectomy; stomach disease

Cutaneous necrobiotic xanthogranuloma due to B-cell chronic lymphocytic leukaemia with full remission from treatment with chlorambucil and obinutuzumab - Asfour, L.; Mortimer, P. (British Journal of Dermatology, 2017)
A 66-year-old woman presented with an asymptomatic yellow nodule on her left cheek that rapidly progressed to encroach on her eyelid. She had undergone a biopsy 5 months earlier from a similar infraorbital lesion, which suggested a diagnosis of necrobiotic xanthogranuloma (NXG). She required multiple re-excisions, but was systemically well with no evidence of underlying malignancy at the time. On examination, there was a xanthomatous indurated plaque extending from her left zygoma up to her medial canthus with associated superficial telangiectasia. Her blood results and paraprotein screen were initially unremarkable apart from a persistently raised alkaline phosphatase. Her full blood count initially had been normal, but following her recurrence she developed mild neutropenia. She underwent further biopsies from the left side of her nose, zygoma, medial canthus and cheek. All four lesions demonstrated a lymphohistiocytic cellular infiltrate, multinucleated giant cells of foreign body and Touton types, and areas of fibrinoid necrosis containing cholesterol crystals consistent with NXG. There was an infiltrate of mature lymphocytes, morphologically consistent with chronic lymphocytic leukaemia (CLL). Immunohistochemistry confirmed CD20-positive B cells, with coexpression of CD23 and CD5. Bone marrow trephine biopsy confirmed classical CLL. At first her haemato-oncologist was reluctant to treat her CLL as it was not severe enough, but chemotherapy was commenced because of the aggressive nature of the NXB. There was an excellent response following completion of four cycles of chlorambucil and obinutuzumab, an anti-CD20 monoclonal antibody, with complete remission of the NXG, which has remained in remission after 12 months with no need for further chemotherapy. NXG is a rare non-Langerhans cell histiocytosis involving skin and extracutaneous tissues, with approximately 100 reported cases. Cutaneous manifestations are progressive and destructive, with infiltrating plaques predominantly affecting the periorbital region. NXG is often associated with paraproteinaemia; 80% of patients have a serum monoclonal gammopathy, 10% develop multiple myeloma and it is infrequently linked to CLL. The pathogenesis of NXG remains unclear. Data on therapeutic options are limited with currently no consensus on first-line treatment. Several treatments have been described with variable results, including topical or systemic corticosteroids, thalidomide, intravenous immunoglobulin, alkylating agents, rituximab, melphalan, infliximab, interferon-alpha, laser therapy, radiotherapy, surgery, psoralen-ultraviolet A and plasmapheresis. A systematic review suggested that several case reports have demonstrated good response with chlorambucil, as seen in our case, which has prompted the authors to design an algorithm with chlorambucil as the first-line treatment. There are no reported cases on the effect of obinutuzumab on NXG.
Keywords: alkaline phosphatase; alpha interferon; CD20 antigen; CD23 antigen; CD5 antigen; chlorambucil; cholesterol; corticosteroid; endogenous compound; human immunoglobulin; infliximab; melphalan; obinutuzumab; paraprotein; psoralen; rituximab; thalidomide; unclassified drug; aged; blood cell count; bone marrow biopsy; cell infiltration; cheek; chemotherapy; chronic lymphatic leukemia; consensus; diagnosis; drug combination; excision; eyelid; female; gene expression; giant cell; histiocytosis; human; human tissue; immunohistochemistry; leukemia remission; low level laser therapy; monoclonal immunoglobulinemia; multiple myeloma; necrobiotic xanthogranuloma; necrosis; neutropenia; nose; oncologist; plasmapheresis; radiotherapy; relapse; skin; surgery; systematic review; telangiectasia; topical drug administration; ultraviolet A radiation; xanthomatosis; zygoma

Leaks in fixed-ring banded sleeve gastrectomies: A management approach. Post-operative complications - Tan, J.; Foo, J.; Balshaw, J.; Tan, M. (Obesity Surgery, 2017)
Background: Tertiary metropolitan referral center, Australia. Introduction: The use of a Fobi ring to prevent pouch dilatation is sometimes used in Roux-en-Y gastric bypass (RYGB). Recently, it has been extrapolated to laparoscopic sleeve gastrectomy (LSG) procedures by placing a fixed-ring band a few centimeters below the gastro-esophageal junction (GEJ). Objectives: What is the consequence if a patient develops a leak? Methods: Over 18 months, all patients with either a conventional LSG or a fixed-ring banded sleeve gastrectomy (BLSG) who presented with a proven leak complication were included. The management approaches along with the surgical, endoscopic and percutaneous procedures used were examined. Results: 6 patients had a BLSG leak and 6 had a LSG leak. All patients had leak resolution. There was no significance difference in body mass index (BMI), time to leak, initial white cell count (WCC) and C-reactive protein (CRP) levels between the two groups. LSG patients required a median of 2 endoscopic procedures (range 1-3). Stents were deployed in three patients. All BLSG patients required a single surgical intervention with laparoscopic washout, drainage, removal of band +/-feeding jejunostomy. One stent was deployed in one BLSG patient. BLSG leak resolution was demonstrated at 34±12 days versus 85±12 days in the LSG group (p<0.05). Conclusion: The BLSG is a new modification of the sleeve gastrectomy procedure. This study presents a management strategy for leak resolution employed in BLSG patients. The presence of a foreign body as a persistent nidus of infection mandates band removal.
Keywords: C reactive protein; endogenous compound; adult; body mass; case report; clinical article; complication; conference abstract; controlled study; endoscopy; feeding; female; foreign body; gene expression; human; infection; jejunostomy; laparoscopic sleeve gastrectomy; leukocyte count; male; postoperative complication; stent; surgery

Team Training in the Perioperative Arena: A Methodology for Implementation and Auditing Behavior - Rhee, A.J.; Valentin-Salgado, Y.; Eshak, D.; Feldman, D.; Kischak, P.; Reich, D.L.; LoPachin, V.; Brodman, M. (American journal of medical quality : the official journal of the American College of Medical Quality, 2017)
Preventable medical errors in the operating room are most often caused by ineffective communication and suboptimal team dynamics. TeamSTEPPS is a government-funded, evidence-based program that provides tools and education to improve teamwork in medicine. The study hospital implemented TeamSTEPPS in the operating room and merged the program with a surgical safety checklist. Audits were performed to collect both quantitative and qualitative information on time out (brief) and debrief conversations, using a standardized audit tool. A total of 1610 audits over 6 months were performed by live auditors. Performance was sustained at desired levels or improved for all qualitative metrics using χ2 and linear regression analyses. Additionally, the absolute number of wrong site/side/person surgery and unintentionally retained foreign body counts decreased after TeamSTEPPS implementation.
Keywords: checklist; clinical audit; human; in service training; interpersonal communication; medical error; operating room; organization and management; patient care; patient safety; perioperative period; prevention and control; safety; standards; total quality management

Clinical Issues-July 2017 - Ogg, M.J.; Johnstone, E.M. (AORN journal, 2017)
Operation of fluoroscopy equipment Key words: fluoroscopy, mini C-arm, scope of practice, radiologic device. Patient education after radionuclide implantation Key words: radionuclides, brachytherapy, prostate cancer, radiation safety. Personal protective equipment Key words: clean, decontamination, instruments, PPE, tray assembly. Safe staffing patterns Key words: on-call staffing, schedules, safe staffing levels. Counting instruments when laparoscopy procedures convert to open procedures Key words: counts, instrument, laparoscopy, retained surgical items.
Keywords: adult; article; brachytherapy; cancer radiotherapy; cancer surgery; decontamination; drug safety; fluoroscopy; human; implantation; laparoscopy; male; patient education; pharmacokinetics; prostate cancer; protective equipment; scope of practice; surgery; radioisotope

Interval follow up of a 4-day pilot program to implement the WHO surgical safety checklist at a Congolese hospital - White, M.C.; Peterschmidt, J.; Callahan, J.; Fitzgerald, J.E.; Close, K.L. (Globalization and Health, 2017)
Background: The World Health Organisation Surgical Safety Checklist (SSC) improves surgical outcomes and the research question is no longer 'does the SSC work?' but, 'how to make the SSC work?' Evidence for implementation strategies in low-income countries is sparse and existing strategies are heavily based on long-term external support. Short but effective implementation programs are required if widespread scale up is to be achieved. We designed and delivered a four-day pilot SSC training course at a single hospital centre in the Republic of Congo, and evaluated the implementation after one year. We hypothesised that participants would still be using the checklist over 50% of the time. Method: We taught the four-day SSC training course at Dolisie hospital in February 2014, and undertook a mixed methods impact evaluation based on the Kirkpatrick model in May 2015. SSC implementation was evaluated using self-reported questionnaire with a 3 point Likert scale to assess six key process measures. Learning, behaviour, organisational change and facilitators and inhibitors to change were evaluated with questionnaires, interviews and focus group discussion. Results: Seventeen individuals participated in the training and seven (40%) were available for impact evaluation at 15 months. No participant had used the SSC prior to training. Over half the participants were following the six processes measures always or most of the time: confirmation of patient identity and the surgical procedure (57%), assessment of difficult intubation risk (72%), assessment of the risk of major blood loss (86%), antibiotic prophylaxis given before skin incision (86%), use of a pulse oximeter (86%), and counting sponges and instruments (71%). All participants reported positive improvements in teamwork, organisation and safe anesthesia. Most participants reported they worked in helpful, supportive and respectful atmosphere; and could speak up if they saw something that might harm a patient. However, less than half felt able to challenge those in authority. Conclusion: Our study demonstrates that a 4-day pilot course for SSC implementation resulted in over 50% of participants using the SSC at 15 months, positive changes in learning, behaviour and organisational change, but less impact on hierarchical culture. The next step is to test our novel implementation strategy in a larger hospital setting.
Keywords: anesthesia; antibiotic prophylaxis; article; bleeding; change management; checklist; Congo; education program; educational model; follow up; health care planning; hospital; human; information processing; intubation; Kirkpatrick model; Likert scale; patient safety; pilot study; priority journal; program evaluation; pulse oximeter; questionnaire; risk assessment; self report; skin incision; structured interview; surgical safety checklist; surgical sponge; teamwork; work environment; World Health Organization

Incidence, patterns and different modalities in extraction of aero-digestive tract foreign bodies in patients attending alexandria main university hospital - Elhamady, H.A.E.; Ramadan, A.E.M.; Gaafar, A.H.; Baess, A.I.; Hammad, S.W. (Journal of the Egyptian Society of Cardio-Thoracic Surgery, 2017)
Background: Aero-digestive tract foreign bodies (FB) are commonly seen either in children or in elderly age group. Various methods have been described in literature for their removal. In our study we aimed to analyze the incidence, risk factors, site, clinical presentations, different modalities used to extract tracheobronchial and esophageal foreign bodies in patients presented with FB aspiration or ingestion to the Emergency, Cardiothoracic Surgery, ENT and Chest disease departments in Alexandria Main University Hospital during the period between 1-11-2014 to 1-11-2015. Methods: A review of ninety patients with alleged FB aspiration and one hundred patients with alleged FB ingestion underwent complete history taking including personal data, date of presentation, date of aspiration or ingestion, circumstances of aspiration or ingestion, and past history of any previous medical or surgical conditions. Clinical assessment included vital signs and complete physical examination & investigations e.g.; complete blood count, random blood sugar, coagulation profile, renal function tests and liver function tests. Imaging including plain X-ray, CT scan, ultrasound, and virtual bronchoscopy were done. Some patients underwent rigid esophagoscopy/bronchoscopy under general anesthesia, based on clinical and radiological evidence. Some patients underwent surgical interventions. Results: Regarding FB aspiration, we found that sex difference was statistically significant in teenagers and adult group; females were found to be more commonly affected than males. Also most of cases of pin aspiration were teenagers (>10–20 years) and adults (>20 years). We noticed that right main bronchus FB was found more frequently in children below 10 years. Rigid bronchoscopic extraction of the FBs was the most common modality of extraction seen in 70 patients (77.8%). Regarding FB ingestion we noticed that females were commonly affected than males, coins were the most commonly ingested FB; and upper oesophageal sphincter (UES) was the commonest site of FB entrapment. Conclusions: FBs in the aero-digestive tract constituted a constant hazard in all age groups especially in children and the elderly, which demanded immediate action and management.
Keywords: antibiotic agent; atropine; beta adrenergic receptor stimulating agent; corticosteroid; halothane; hydrocortisone; oxygen; suxamethonium; adolescent; adult; aged; article; blood cell count; blood clotting; bradycardia; bronchoscope; bronchoscopy; bronchospasm; catheter removal; child; clinical assessment; echography; esophageal bougie; esophagoscopy; esophagus foreign body; esophagus perforation; esophagus stenosis; female; fiberoscope; fluoroscopy; Foley balloon catheter; forceps; foreign body aspiration; glucose blood level; human; incidence; ingestion; kidney function test; liver function test; major clinical study; male; mediastinitis; medical nebulizer; percussion; physical examination; postural drainage; radiography; risk factor; sex difference; thorax radiography; upper esophagus sphincter; vital sign; x-ray computed tomography

Emergency laparoscopic repair of rectosigmoid perforation caused by toilet bursh-demage control surgery by noncolorectal laparoscopic surgeon - Mahmood, S. (Surgical Endoscopy and Other Interventional Techniques, 2017)
Aims: A case report with video of young patient admitted as emergency with peritonitis, there was history of insertion of foreign body (toilet Brush) in his rectum. Methods: 32 years old male was admitted in accident and emergency with abdominal pain. Pain started 6 h ago after he inserted the toilet brush in his back passage. He was septic with four quadrant peritonitis. His white cell count and C-reactive proteins were elevated. Plain X-ray abdomen showed free gas under the diaphragm. No further images were done. Patient was prepared for theatre and laparoscopy was carried out by general surgeon, three 5 mm and two 10 mm ports were used. Found to have faecal peritonitis due to iatrogenic perforation just above the recto-sigmoid junction. The perforation was closed with Ethibond stitches. All quadrant under vision peritoneal wash was done with 8 litres of saline. The bowel clamp was applied to the sigmoid colon and flexible sigmidoscopy carried out and pelvis was flooded with saline, there was no air leak from the repaired perforation. The sigmoid colon was mobilized and loop colostomy was performed in left iliac fossa at the 10 mm port site. Results: The post operative period was uneventful the patient was referred to psychiatrist. And had now loop colostomy revered with no long term follow-up. Conclusion: Laparoscopic emergency colonic surgery is safe with good results by a laparoscopic general surgeon. We want to share the video and technical points with our colleagues.
Keywords: polyethylene terephthalate; sodium chloride; abdominal pain; accident; adult; clamp; colostomy; diaphragm; emergency; follow up; human; iliac bone; laparoscopy; leukocyte count; perforation; peritonitis; postoperative period; psychiatrist; sigmoid; surgeon; surgery; vision; X ray

Foreign body induced empyema in an adolescent: Challenges of management in a resource-poor setting - Eze, J.N.; Ayuk, A.C.; Okoh, O.K.; Oguonu, T. (Pediatric Pulmonology, 2017)
Background Foreign body aspiration usually presents with cough which is of sudden onset, respiratory distress and wheeze. Complications such as recurrent pneumonia, bronchiectasis, and rarely empyema and atelectasis occur when the foreign body has been retained in the lungs for a long period of time. This case highlights the complications of the delayed diagnosis of retained foreign body in the bronchus. Methods The case record file of the index case was retrieved from the hospital records. Information extracted from the records included: age, sex, date of presentation, symptoms and signs at presentation and on subsequent review, final diagnosis, investigations and treatment, and outcome of treatment. Case Report AC is a 15-year-old adolescent female who developed right atelectasis and loculated empyema secondary to a foreign body aspirated 3yrs earlier. The foreign body (an office pin) was lodged in the right main bronchus. She presented to a nearby clinic but referral to a tertiary center for appropriate treatment was delayed. She had repeated chest infections. Symptoms were recurrent episodes of cough, fast breathing and hemoptysis over a period of 3 years for which she took over the- counter (OTC) medications. She presented to our facility when the symptoms progressively worsened. Findings on examination were tachypnea, splinting of the chest to the right, deviation of the trachea to the left, dull percussion note, reduced breath sounds, and crepitations on the right hemithorax. Oxygen saturation in roomair (SPO2) was 93%. Apex beat was displaced. Chest X-ray (CXR) and chest ultrasonography showed features in keeping with right lung collapse with right sided pleural effusion. Computerized tomography scan was not performed owing to financial constraints. Pleural fluid microscopy yielded pus cells while culture yielded no bacterial growth. Complete blood count showed leucocytosis with predominant granulocytosis, anemia, and reactive thrombocytosis (platelet count >1000000/mm3). The Erythrocyte Sedimentation Rate (ESR) was 130mm/hr. Screening for tuberculosis and retroviraldisease was negative. She receivedi ntravenous Ceftriazone and Vancomycin. Following some degree of resolution of the opacities in the CXR, the pin was located in the right main bronchus. The patient was referred to the cardiothoracic surgeons for furthermanagement. A chest tube was inserted which drained minimally. She underwent a decortication for the loculated empyema. An attempt to search for and retrieve the foreign body through a right main bronchotomy was unsuccessful. She is scheduled for bronchoscopy in order to remove the foreign body. Conclusions This case highlights the need for early diagnosis and prompt removal of aspirated foreign body in order to avert the long term complications such as empyema, atelectasis and bronchiectasis which invariably reduces the individual's quality of life.
Keywords: non prescription drug; vancomycin; abnormal respiratory sound; adolescent; anemia; atelectasis; bacterial growth; bronchiectasis; bronchoscopy; case report; chest infection; chest tube; computer assisted tomography; coughing; crackle; decortication; diagnosis; early diagnosis; echography; empyema; erythrocyte sedimentation rate; female; foreign body aspiration; granulocytosis; hemoptysis; human; main bronchus; medical record; microscopy; oxygen saturation; patient referral; percussion; pleura effusion; pleura fluid; pus; quality of life; right lung; screening; splinting; symptom; tachypnea; thoracic surgeon; thorax radiography; platelet count; thrombocytosis; trachea; tuberculosis

Retained surgical gauze swab migration in a paraplegic patient: A case report and literature review - Vogel, R.; Ladurner, A.; Rudin, D. (Swiss Medical Weekly, 2017)
Introduction: Gossypiboma is a serious but uncommon complication of surgical interventions. Most case reports and reviews refer to abdominal or thoracic surgery. Retained postoperative foreign bodies in limb or spine surgery are less commonly encountered. We present a case of gossypiboma in a paraplegic patient originating from pararectal surgery and detected 15 years after index surgery for infectious migration to the left thigh. Methods: We present an unusual clinical case and performed a systematic literature review on the subject. Case presentation: A 56-year-old paraplegic patient with complete sensory deficit in both legs presented with signs of an infected haematoma at the left thigh. At the time of surgical evacuation cotton tissue originating from a surgical gauze swab was retrieved. After a thorough investigation of the patient's medical history, polytrauma treatment consisting of emergent laparotomy with abdominal gauze packing in 1986 and surgical treatment of a fistulating pararectal abscess in 2001 were stated possible origins of the intraoperative findings. Further surgical interventions with a more extended approach were necessary. Another gauze tissue conglomerate was found next to the ischial tuberosity, revealing the surgical treatment of a pararectal abscess (developed from sacral decubiti) as the origin of the retained gauze swabs. Conclusion: Retained surgical gauze (RSG) swab is a serious and, due to medicolegal reasons, underreported complication of surgical intervention. Diagnosis can be challenging because patients may present with only vague symptoms. In the presented case the patient remained asymptomatic for 15 years, mainly due to his paraplegia. Prevention of RSG is far more important than cure. Awareness of the problem, staff training and the use of preventive measures as radiopaque labelled gauze swabs or monitored counting should be mandatory in every surgical intervention.
Keywords: abscess; adult; awareness; cell migration; complication; conference abstract; cotton; fistula; foreign body; hematoma; human; human tissue; ischial tuberosity; laparotomy; male; medical history; middle aged; multiple trauma; paraplegia; sensory dysfunction; staff training; surgery; surgical swab; systematic review; thigh

SURGICAL COUNTING: A PERIOPERATIVE NURSE'S PERSPECTIVE - Warwick, V.; Gillespie, B. (Australian nursing & midwifery journal, 2017)
The Australian College of Perioperative Nurses (ACORN) have developed a set of standards to guide clinical practice within the perioperative setting. The ACORN standard 'Management of accountable items used during surgery and procedures' (ACORN 2016) details a process for perioperative nurses to follow when undertaking a surgical count.
Keywords: foreign body; human; medical error; nurse attitude; operating room personnel; patient safety; prevention and control

Prepubertal girl with vaginal bleeding - Diaz, P.; LLor, J.; Russo, M.; Cheseaux, J.J.; Tabin, R.; Alexe, E.; Ramseyer, P. (Swiss Medical Weekly, 2017)
Case report: A 4 y.o. african girl was hospitalized for vaginal bleeding that had started few hours before. Her medical and surgery histories were uneventful. She denied pain, fever, lethargy, abdominal distension or dysuria. She had no history suggestive of sexual abuse, trauma or foreign body to the genital area. The patient was kept by her big siblings during the day without a remarkable event. Her vital signs and physical examination were normal. Tanner: P1S1A1. Examination of the genitalia revealed vaginal blood clot without any local injury. Complete blood count and clotting factors were normal. Further examination wasn't possible at bedside. A cystoscopy and vaginoscopy were done under a general anesthesia. A tumor was found in the urethral inferior lip. No gynecologic disease was observed. Biopsy revealed an overlay with inflammatory and fibrin tissue, and no malignancy. An urethral caruncle was diagnosed. 1 week later urethral inflammation was still present; corticoid cream was prescribed for 2 weeks allowing disappearance of residual mass. Follow up was free of recurrence. Discussion: Common causes of vaginal bleeding in pre-puberty girls are neonatal withdrawal bleeding, trauma, foreign bodies, infections (vulvo-vaginitis / peri-urethral gland abscess), hematuria, urethral prolapse, precocious puberty, tumor and sexual abuse. An exhaustive anamnesis and physical examination, usually under general anesthesia, are crucial for the diagnosis. If a tumor is found, biopsy is required to exclude malignant tumors. Urethral caruncles are usually confined to women urethra and are rarely found in pre-puberty girls. They are present in the urethral meatus and bleeding is the most common symptom, but persistent pain or urination difficulties are also described. Microscopic findings are interstitial oedema with inflammatory cell infiltration and hyperplasia of the connective tissue. Two therapy approaches are possible: steroid ointment (because of chronic inflammation) and/or surgical resection. A potential problem is meatal stenosis. No relapse is described in the literature. Conclusions: Urethral caruncles are one of the rare causes of vaginal bleeding in children. Topical steroids are recommended for a few weeks. If this treatment fails or suspicion of malignancy exists biopsy ± excision is required. Surgery side effect is meatal stenosis and steroid ointment may be required if inflammation (or incomplete resection) persists after surgery.
Keywords: corticosteroid; endogenous compound; fibrin; abdominal distension; abscess; African; anamnesis; biopsy; blood cell count; blood clot; cancer recurrence; cancer surgery; case report; cell infiltration; child; chronic inflammation; clinical article; conference abstract; connective tissue; cystoscopy; drug withdrawal; dysuria; edema; excision; female; fever; follow up; foreign body; general anesthesia; girl; hematuria; human; hyperplasia; inflammatory cell; lethargy; malignant neoplasm; newborn; ointment; physical examination; precocious puberty; prepuberty; relapse; sexual abuse; sibling; side effect; stenosis; surgery; topical drug administration; treatment failure; urethral prolapse; urethritis; vagina bleeding; vaginitis; vital sign; withdrawal bleeding

Three years evaluation of retained foreign bodies after surgery in Iran - Zarenezhad, M.; Gholamzadeh, S.; Hedjazi, A.; Soltani, K.; Gharehdaghi, J.; Ghadipasha, M.; Hosseini, S.M.V.; Zare, A. (Annals of Medicine and Surgery, 2017)
Background Medical errors such as retained foreign bodies (RFB) during surgery are not well studied. To define risk factors associated with this type of error, we performed retrospective study. Methods We reviewed medical records for unintentional foreign object remaining in the body during surgery such as gender, age, surgery ward, and incident reports referred to several forensic medicine administrations as well as adverse effects of retained foreign bodies and methods for detection of them over a 3-years period from January 2008 through May 2011. Results Thirty eight patients were involved in the study to have retained foreign bodies (73% sponges and 27% other instruments including 7 (18.42%) cases of other bandages, 2 cases (5.26%) of scissor and 1 case (2.63%) of forceps). The general surgery ward was most commonly involved (47%) followed by the gynecology surgery ward (34%). Men (58%) were more involved with RFB than women (42%). Conclusion Considering the most frequent type of retained foreign bodies and also more frequent involved surgery wards besides detection methods for RFB, a mixed of preventing protocols such as regular counting of devices, post-operative X-ray with radiopaque markers and exact evaluation of surgery site should be employed to reduce the occurrence of retained foreign bodies and its complications.
Keywords: abdominal abscess; adult; article; bandage; clinical article; clinical evaluation; female; fever; forceps; gynecologic surgery; human; intestine obstruction; intestine perforation; male; pain; priority journal; reoperation; retained foreign body; retained instrument; retrospective study; risk factor; scissors; surgical error; X ray

Surgical count process: evidence for patient safety - Freitas, P.S.; Mendes, K.D.; Galvão, C.M. (Revista gaucha de enfermagem, 2017)
Keywords: cross-sectional study; foreign body; human; patient safety; statistics and numerical data; surgical equipment

A retained resectoscope beak: are we missing the point of surgical checklists? - Smith, S.F.; Miakhil, S.I.; Johnston, T.J.; Lockett, C. (Journal of Clinical Urology, 2017)
We present an unusual case of a retained resectoscope beak detected 10 months following transurethral resection of a bladder tumour. We describe this rare complication after transurethral surgery and present a safe method for removing a resectoscope beak from the urethra. This case prompted several improvements in our local surgical checklists to prevent such an event from recurring. It is important to check the integrity of surgical equipment in addition to counting equipment in and out during theatre; without checking, as exemplified by the resectoscope in this case, we risk missing the point.
Keywords: adult; article; bladder tumor; case report; cystectomy; cystoscope; cystoscopy; device removal; forceps; foreign body; human; male; middle aged; resectoscope; retained instrument; urethra obstruction

Gossypibomas in India - A systematic literature review - Patial, T.; Thakur, V.; Ganesun, N.K.V.; Sharma, M. (Journal of Postgraduate Medicine, 2017)
Purpose of Review: Gossypibomas remain a dreaded and unwanted complication of surgical practice. Despite significant interest and numerous guidelines, the number of reported cases remains sparse due to various factors, including potential legal implications. Herein, we review related data from India to ascertain if the problem is better or worse than that reported in world literature. Materials and Methods: A literature search was performed on PubMed and Google Scholar, to collect and analyze all case reports and case reviews regarding the condition in India. Results: On analysis of the results, there were 100 publications reporting a total of 126 events. The average patient age was 38.65 years. Average time to discovery was 1225.62 days. Forty-nine percent of reported cases were discovered within the 1 st year. The most common clinical features were pain (73.8%), palpable mass (47.6%), vomiting (35%), abdominal distention (26%), and fever (12.6%). Spontaneous expulsion of the gossypiboma was noted in five cases (3.96%). Transmural migration was seen in 36 cases (28.57%). Conclusions: Despite advancements in surgical approaches and preventive measures, gossypibomas continue to be a cause of significant morbidity. A safe working culture, open communication, teamwork, and an accurate sponge count remain our best defence against this often unpredictable complication of surgery.
Keywords: clinical feature; gossypibomas; human; India; Medline; postoperative complication; practice guideline; publication; retained instrument; review; surgical sponge; systematic review

Detection of Retained Foreign Objects in Upper Extremity Surgical Procedures With Incisions of Two Centimeters or Smaller - Tofte, J.N.; Caldwell, L.S. (The Iowa orthopaedic journal, 2017)
BACKGROUND: While the true incidence of retained foreign bodies after surgery is unknown, it has been approximated at 1:5,500 operations overall, with substantially less frequency in hand and upper extremity procedures. Despite the rarity of foreign body retention in hand and upper extremity surgery, universal radiofrequency scanning for electronically-tagged sponges and automatic radiographic evaluation for incorrect sponge counts are employed for all surgical procedures at our institution. We demonstrate the infeasibility of retaining an operative sponge of a standard size in commonly performed hand and upper extremity procedures with incision sizes of two centimeters or less, and establish that visual detection of sponges in these cases is adequate. METHODS: Eighteen trigger finger releases, five carpal tunnel releases, three trigger thumb releases, and three de Quervain's tenosynovitis releases were successfully performed upon five cadaveric specimens by residents under supervision of fellowship-trained hand surgeons for a total of 29 two-centimeter or smaller incisions. Randomized surgical sponge placement was evaluated by a blinded observer at two distances and incision sizes were quantified. Kappa values were calculated to determine the acuity of visual detection versus the actual presence of a sponge. RESULTS: The maximum length of the standard surgical sponge that could be contained within an incision was three centimeters. When compared with the gold standard (whether the sponge had been placed or not by the operating resident), the placement of a standard surgical sponge could be detected correctly in 100% of cases at both "across the room" and "at the table" distances, for kappa values of 1.0 and 1.0 respectively. This did not vary with incision size or surgical procedure. CONCLUSIONS: The added cost and time from radiofrequency detection of retained sponges and radiographic evaluation in the event of incorrect sponge counts can be safely eliminated if sponges can be reliably visually detected. CLINICAL RELEVANCE: This cadaveric study informs patient safety practices by demonstrating that visual detection of surgical sponges is adequate for certain upper extremity procedures.
Keywords: foreign body; human; orthopedic surgery; surgery; surgical sponge; upper limb

Benign xanthogranulomatous cyst of the hip following total hip arthroplasty: A case report - Sahran, Y.; Nadiah, N.H.; Din, M.H.; Faisham, W.I.; Othman, H.; Najmiyah, W.A.B. (Malaysian Orthopaedic Journal, 2017)
INTRODUCTION: The occurrence of cyst around total hip arthroplasty (THA) is rare. There are several well-described causes of mass following THA, including polyethylene and metal wear debris, infection, expanding hematoma, and synovial cysts. However, formation of benign xanthogranulomatous cyst of the hip following THR has never been reported before, to the best of our knowledge. CASE REPORT: We report a case of a 68-year-old gentleman, with underlying end stage renal failure, had bilateral THA done 10 years ago. He presented with progressively increasing size of painless right hip swelling for one-year duration. He had no fever or constitutional symptom. The mass sized 15 × 8cm over the anterolateral aspect of the hip joint. It was fluctuant with smooth surface. There was an ulcer discharging clear yellowish fluid over the mass. Plain radiograph showed increased soft tissue shadow over the lateral aspect of the right hip and proximal femur (figure 1). No periprosthetic radiolucency to suggest loosening or osteolysis. ESR and CRP were raised, while total white count within the normal range. With suspicion of infection, patient was planned for debridement surgery. Intra-operative finding was a large cyst which contained about 1.5 liter of clear fluid, lower viscosity in comparison with synovial fluid. The cyst wall enveloped the hip joint from anterior to posterior, connecting with lining of the acetabulum. Posteriorly, the cyst wall covered the gluteus maximus muscle and overlying the sciatic nerve. Laterally, the cyst wall extended and wrapped the proximal femur almost 80 percent of the circumferential perimeter (figure 2). The cyst wall was excised. The prosthesis was found to be stable. Patient was covered with short term antibiotic. One-year post surgery, patient was asymptomatic and no implant loosening to date. (Figure Parsented) Histopathological examination of the cyst showed two different morphologies. One is massive collection of foamy macrophages, foreign body giant cells surrounding by numerous cholesterol cleft which occupies the entire dermis up to subcutis with chronic inflammatory cells where eosinophils seen throughout the lesion and thickened fibrous wall This represents the xanthogranulomatous changes secondary to lipid base foreign body. DISCUSSIONS: It was thought that wear debris may function as a foreign body and phagocytosed by macrophages, resulting in a granulomatous reaction. These cysts also believed to be subclinical infections which currently known as granulomatous pseudotumours. However, in our case, we didn't observe any implant loosening. Microscopic wear from the polyethylene is a possible cause. CONCLUSION: Benign xanthogranulomatous cyst around the THA in this case did not associate with visible prosthesis problem, and was treated with excision and short term antibiotic. This is a rare clinical scenario, and long term follow up of the patient will better show the natural history of the disease.
Keywords: antibiotic agent; cholesterol; polyethylene; acetabulum; aged; asymptomatic infection; case report; clinical article; conference abstract; cyst; debridement; dermis; end stage renal disease; eosinophil; fever; follow up; giant cell; gluteus maximus muscle; granulomatous inflammation; histopathology; history; human; human cell; infection; inflammatory cell; macrophage; male; osteolysis; perimeter; proximal femur; pseudotumor; sciatic nerve; soft tissue; subcutaneous tissue; surgery; surgical patient; swelling; synovial fluid; thinking; total hip prosthesis; ulcer; viscosity; X ray film

Activated immune response in ventricular assist device implanted patients identified through a platelet activation biomarker - Jeske, W.; Walenga, J.M.; Torres, T.; Escalante, V.; Schwartz, J.; Bakhos, M. (Blood, 2016)
Introduction: Mechanical circulatory support using an implanted ventricular assist device (VAD) is an important means of enhancing or maintaining the quality of life for heart failure patients awaiting heart transplant (bridge to transplant), during the recovery of their own heart (bridge to recovery) or for long-term destination therapy (no transplant). The non-physiologic continuous blood flow of a VAD (CF-VAD) exposes blood and vasculature to abnormal shear stress and leads to a variety of hemostatic derangements that likely contribute to the development of bleeding complications, neurologic dysfunction and venous thromboembolism in these patients. Additionally, the implanted CF-VAD likely stimulates the body's natural innate immune response to a foreign object. We hypothesize that the continuous activation of platelets due to the non-physiologic blood flow and the foreign nature of the CF-VAD combine to stimulate an immune response. Previous studies have suggested thatanti- PF4/heparin antibodies [as targeted in a diagnosis of heparin-induced thrombocytopenia (HIT)] can develop in the absence of heparin. It is believed that these antibodies are not related to heparin per se but rather are generated as a physiological response by platelets, in their capacity to generate an innate immune response, reacting to non-self substances. This study evaluated the time course of anti- PF4/heparin titers in patients supported by CF-VADs. Methods: Blood samples were collected from 13 randomly selected patients prior to implantation of a HeartMate II CF-VAD and at routine clinic visits following implantation. Median follow-up was 183 days (range: 32-352 days). Anti-PF4/heparin antibody titers were determined by the PF4 Enhanced X-45 Assay (Immucor GTI Diagnostics, Waukesha, WI). Patients were treated with heparin at the time of implant; long-term anticoagulation was maintained with warfarin (INR 1.5-2.0) and low-dose aspirin. Results: Following CF-VAD implantation, there was an acute increase in median platelet count from 169,000 to 420,000/μl. With increasing time post-implant, the median platelet count returned to preimplant levels; no patients became thrombocytopenic. Pre-implant, 6 of 13 patients had 'positive' anti- PF4/heparin titers (OD >0.4 using the HIT criteria); the median OD for all patients was 0.433. There was a progressive increase in median titer with increasing time post-implant. At 1 month the median OD was 0.54. By 2 months all patients had an OD >0.4 with a median value of 0.82 (>0.750 is high clinical thrombosis risk using the HIT criteria). The median OD continued to rise through 8 months postimplant. At 5 months and later OD values >1.5 were common. OD values >1.5 were present in some patients as early as 1 month post-implant. Discussion: The mechanism(s) associated with CF-VAD pump thrombosis and other adverse events remains unclear. The above data shows that long-term implant of a CF-VAD leads to the development of anti-PF4/heparin antibodies. Such a response may result from shear-induced platelet activation and subsequent release of PF4. This response is similar to a previous report in which patients who underwent total knee or hip arthroplasty and subsequently received dynamic mechanical thromboprophylaxis demonstrated an anti-PF4/heparin immune response even in the absence of heparin (Bito et al, Blood 2016). CF-VAD-related infection may also contribute to the generation of anti-PF4/heparin antibodies as PF4 bound to bacteria has previously been shown to induce antibody formation (Krauel et al, Blood 2011). Data from our lab has shown that patients with implanted CFVADs are frequently in heightened states of inflammation (ASH 2016 abstract) with excessive levels of C-reactive protein in patients who develop pump thrombosis. CRP has been shown to activate platelets and accelerate thrombogenesis (Xu et al, BMC Immunology 2015). Thus, it is plausible that the development of anti-PF4/heparin antibodies may be an indicator of an early activation mechanism of adverse events in CF-VAD implanted patients through the cross-talk between the hemostatic and immune systems. Larger studies are required to determine whether the presence of such antibodies confers any risk to LVAD patients. The presence of anti-PF4/heparin antibodies may be of particular concern for LVAD patients undergoing a subsequent surgery for pump replacement or heart transplant.
Keywords: acetylsalicylic acid; antibody; biological marker; C reactive protein; endogenous compound; heparin; thrombocyte factor 4; warfarin; adverse device effect; adverse drug reaction; animal model; antibody production; antibody titer; anticoagulation; blood flow; chemical binding; clinical article; clinical trial; device infection; diagnosis; drug therapy; follow up; gene expression; heart graft; heparin induced thrombocytopenia; hip arthroplasty; hospital; human; human cell; human tissue; immunology; implant; inflammation; innate immunity; international normalized ratio; knee; left ventricular assist device; low drug dose; side effect; surgery; thrombocyte activation; platelet count; thrombosis

A rare case of aorto-esophageal fistula in a child presenting with massive hematemesis - Sharma, V.; Sharma, R.; Sharma, S.D. (Journal of Gastroenterology and Hepatology (Australia), 2016)
Introduction: Aortoesophageal fistula (AEF) in children is rare and results in very high mortality. Foreign body ingestions remain the commonest cause of AEF in children. Case Report: A two-year-old girl child presented with massive hematemesis, fresh blood per rectum, and melena for 2 h. No previous history of massive hematemesis. One day back, there was ingestion of meat with bone piece 2 days back, felt pain in chest for 1 day. On examination, the child was restless and irritable. She had features s/o rate of 140 per minute and blood pressure of 70/ 40 mmHg. Systemic examination was unremarkable. The child was resuscitated with fluids and packed red blood cells (PRBCs). Bleeding continued resulting in progressive worsening of hemodynamic status over the next few hours. Intubated for prevention of aspiration and put on support. The preliminary reports revealed hemoglobin of 3.2 g/dl, total leucocyte count of 18,500/mm3, platelet count of 250,000/mm3. Upper GI endoscopy showed rounded ulcer of around 7 × 7mm diameter with overturned margins and clot just above GE junction. Bleeding started while observing it. Hemostatic procedures failed. Resuscitative and ionotropes started. Patient referred to pediatric surgeon, CECT thorax planned, but due to active bleed and shock could not be done, the child was taken up for emergency thoracotomy. AEF usually results in a very high mortality. Many succumb to the bleed, neurological deficit, and spinal ischemia developed during repair of aortic defect. In our case, the child could not survive post surgery.
Keywords: endogenous compound; hemoglobin; aorta; aortoesophageal fistula; aspiration; blood pressure; bone; case report; child; emergency; endoscopy; erythrocyte; female; gastroesophageal junction; girl; hematemesis; human; ingestion; leukocyte count; liquid; melena; mortality; pediatric surgeon; preschool child; rectal drug administration; spinal cord ischemia; surgery; thoracotomy; thorax pain; platelet count; ulcer

The situate detection system-a cost-effective approach to preventing retained surgical sponges - Leinwand, B.; Hughes, K.E. (Value in Health, 2016)
Objectives: Estimate the cost-effectiveness of utilizing the SituateTM radiofrequency (RF) Detection System plus manual tracking of surgical sponges versus manual tracking alone, to prevent the incidence of retained surgical sponges (RSS). Methods: We developed a one-year decision analytic model to assess the clinical and economic impacts of utilizing SituateTM Detection System to prevent RSS in a surgical facility performing 10,000 surgeries annually, using inputs from literature and clinical expert opinion. We estimated the incremental costs per RSS avoided by modeling the following parameters: counting discrepancy rates; diagnostic performance of SituateTM Detection System, manual counting, and intraoperative radiographs; time associated with searching inside/outside the surgical field and waiting for/reading radiographs; and cost of operating room (OR) time, radiographs, RF-tagged sponges and SituateTM Detection System wand covers, and infections, unreimbursed procedure, and legal costs associated with RSS. Model parameters were varied through one-way sensitivity and scenario analyses to test the robustness of model results. Results: Under base case assumptions, SituateTM Detection System dominated manual counting alone by preventing 2 additional RSS while resulting in $620,789 fewer costs. Cost reductions were due to the efficiencies gained by using the device, lower utilization of radiographs, and fewer medical/legal costs resulting from RSS. Model results were robust to the sensitivity analyses. Even with legal costs removed from the model, which was by far the greatest cost, to conservatively reflect an ex-U. S. medical malpractice landscape, SituateTM Detection System still reduced costs by $65,448 and continued to dominate manual counting. Conclusions: The implications of RSS can be both clinically and economically significant for patients and healthcare facilities, and the literature suggests that standard manual counting is not optimal in preventing RSS. Our model suggests that, even using conservative estimates, SituateTM Detection System can avert medical and legal costs, decrease unproductive OR time, and most importantly, more effectively prevent RSS.
Keywords: diagnostic value; disease simulation; human; infection; landscape; malpractice; operating room; radiofrequency; surgery; surgical sponge; X ray film

The epidemiology of open globe injuries presenting to a tertiary referral eye hospital in Australia - Beshay, N.; Keay, L.; Watson, S. (Clinical and Experimental Ophthalmology, 2016)
Purpose: To review the epidemiology of open globe injuries (OGI) presenting to a tertiary referral eye hospital in Sydney, Australia, over a 6-year period. Methods: Details of OGI presenting to the Sydney Eye Hospital over 6 years were reviewed. The Birmingham Eye Trauma Terminology system was used to classify injuries as globe ruptures, penetrating eye injuries (PEIs), intraocular foreign bodies (IOFBs) or perforating injuries. Demographic data, ocular history, mechanism of trauma, ocular injuries and bestcorrected visual acuity (BCVA) were recorded. The ocular trauma score (OTS) was calculated for each case and correlated with visual acuity following treatment. Results: There were 195 OGI: 78 globe ruptures, 65 PEIs, 46 IOFBs and six perforating injuries. Thirtytwo globe ruptures occurred due to a fall with 81.3% having previous intraocular surgery. Of 46 patients who sustained globe ruptures from causes other than a fall, 45.7% (21/46) had had intraocular surgery. Globe rupture patients had a lower OTS. Of 59 globe rupture patients who had their BCVA recorded following treatment, 88.1% had a BCVA of counting fingers or worse. Alcohol was implicated in 18 cases of OGI, with 10 due to assault. The OTS and initial BCVA correlated well with final BCVA. PEIs and IOFBs commonly occurred while working with metal. Conclusion: Intraocular surgery is associated with OGI, particularly globe rupture, with a poor visual outcome. Australia should consider a national registry for the collection of prospective data on severe ocular injuries.
Keywords: alcohol; assault; Australia; best corrected visual acuity; demography; eye injury; eye surgery; finger; hospital; human; intraocular foreign body; major clinical study; nomenclature; patient referral; register; rupture

A 10-year review of traumatic open globe injuries at a tertiary referral hospital in New South Wales, Australia: Assessing the epidemiology, aetiology, complications and final visual outcomes of traumatic open globe injuries - Birrell, H.; Viswanathan, D.; Haider, A.; Singh, R. (Clinical and Experimental Ophthalmology, 2016)
Purpose: To assess the epidemiological characteristics, types of injury, visual outcomes and complications in patients presenting with open globe injuries (OGIs). Methods: Retrospective chart review. Results: This study included 115 eyes of 114 patients (77% males, 23% females) with a mean age of 41.15 ± 23.0 years (range 1-98). Mean follow up was 10.00 ± 14.4 months. Injuries were penetrating (60.5%), rupture (36.7%) and perforating (2.8%) in nature, and of these, 14.6% were associated with intraocular foreign bodies. Ocular injuries were graded as zone 1 (53%), zone 2 (25%) and zone 3 (21%). Visual acuity (VA) at presentation ranged from: no light perception (NLP) (8%), light perception (LP) (27%), hand movements (HM)(12%), counting fingers (CF)(11%), 6/60-6/36 (4%) and better than 6/ 24 (19%). All but 7 cases underwent primary repair (94 eyes) or evisceration (14 eyes) within 24 hours of presentation. Final VA ranged from: NLP (9%), LP (9%), HM (2%), CF (9%), 6/60-6/36 (13%) and better than 6/24 (58%). Of patients with Final VA better than 6/24, zone 1 injuries made up (70%), zone 2 (20%) and zone 3 (10%). Pre-hospital intubation was required in 7.3% of patients and significant extraocular injuries were noted in 30% of patients. Nineteen eyes had post-operative complications, including wound leak (9), wound infection (4), endophthalmitis (3), raised IOP (2) and graft rejection (1). Conclusions: The Hunter-New England network encounters a broad range of OGIs, often associated with traumatic co-morbidities. Visual outcomes and complication rates are equivalent to previous studies.
Keywords: adolescent; adult; aged; child; comorbidity; controlled study; endophthalmitis; evisceration; eye injury; female; finger; follow up; graft rejection; hand movement; human; infant; intraocular foreign body; intraocular pressure; intubation; major clinical study; male; medical record review; New South Wales; perception; rupture; tertiary care center; United States; visual acuity; wound infection

Supra-aural gossypiboma: case report of a retained textile surgical sponge in an unusual location - Chawla, N.; Gupta, N.; Dhawan, N. (Annals of the Royal College of Surgeons of England, 2016)
Gossypiboma or retained surgical sponge is an infrequently encountered surgical complication, more so in the head and neck region. A literature search did not reveal a previously reported case of retained or concealed surgical sponge after microscopic ear surgery. We present a unique and previously unreported case of a 25-year-old male who presented with a cystic swelling in the right supra-aural region 5 months post-modified radical mastoidectomy of the right ear. Surgical excision of the swelling revealed a retained surgical sponge. We emphasise the importance of counting surgical sponges after every surgical step to minimise the incidence of such retained surgical items.
Keywords: adult; adverse event; case report; foreign body; human; inner ear; male; mastoid; medical error; surgical sponge

Novel case report of small bowel obstruction secondary to pica for sandstone - Court, E.L.; Courtney, E.D. (Colorectal Disease, 2016)
Introduction: The commonest causes of mechanical small bowel obstruction are postoperative adhesions and hernias. Other aetiologies include disease intrinsic to the bowel wall (e.g. tumour, stricture) and intraluminal obstruction (e.g. gallstones, foreign bodies). Here we report a case where pica caused obstruction secondary to ingestion of sandstone fragments. Case presentation: A 72 year old female with a virgin abdomen, presented to her GP with a 2 day history of abdominal pain, distension and vomiting. Her bowels had not opened for 4 days, but she was passing flatus. Upon arrival in the Emergency Department, she was dehydrated, tachycardic and tachypnoeic. On examination, her abdomen was soft, distended and maximally tender on the left side. Her white cell count was 31.8 and lactate 2.0. Other admission blood tests were unremarkable. A CT scan revealed a thickened segment of small bowel of uncertain aetiology. She underwent an emergency laparotomy. Findings were small bowel obstruction secondary to accumulation of sandstone fragments ranging in size from 0.5-3.0 cm, with multiple fragments in the large bowel. A small bowel enterotomy was performed, to remove the larger particles. Post-operative recovery was complicated by a lower respiratory tract infection, but the patient was discharged at Day 5. Conclusion: The patient denied ingestion of foreign bodies during initial assessment, but post operatively, she admitted pica for sandstone dating back a number of years. This novel case highlights the need to keep an open mind during the initial assessment of patients in the emergency setting.
Keywords: lactic acid; abdominal pain; aged; case report; computer assisted tomography; emergency ward; female; flatulence; foreign body; human; ingestion; intestine surgery; laparotomy; large intestine; leukocyte count; lower respiratory tract infection; pica; small intestine obstruction; tachycardia; vomiting

Every cent counts: A case of foreign body ingestion - Colizzo, J.; Gill, J. (American Journal of Gastroenterology, 2016)
Foreign body ingestion represents a relatively common reason for gastroenterologist consultation. While over 80% of swallowed foreign bodies will ultimately pass uneventfully through the gastroin- testinal tract, 10-20% of cases will require endoscopic retrieval. We present an unusual case of foreign body ingestion involving a patient presenting with abdominal pain and melena. A 68 year-old man with a history of coronary artery disease presented to the hospital with a 3 day history of unremitting, burning epigastric pain associated with 1 episode of melenic stool. He denied hematochezia and weakness but did endorse a history of non-steroidal anti-inflammatory use. Upon admission he was found to be hemodynamically stable. Laboratory values including complete blood count, basic metabolic panel, and protime were unremarkable. Plain abdominal film on admission revealed an elongated radiopaque object concerning for foreign body in the antrum. The patient denied ingestion of any known non-food items. Upper endoscopy was performed. An elongated Forrest 2c 7mm x 2cm pyloric ulcer was discovered (figure 1). On retroflexion in the stomach, a quarter was visible in the greater curvature (figure 2). Closer inspection revealed a dime underneath the first coin (figure 3). Both coins were successfully retrieved with the Roth retrieval net. Biopsies for Helicobacter Pylori were negative. The patient was started on 40mg esomeprazole daily and was soon discharged with a plan for repeat upper endoscopy in 3 months. While the majority of ingestions can be managed with conservative measures, cases with airway compromise or peritoneal signs often call for urgent endoscopic or surgical evaluation. Concerning ingestions include sharp objects, disk batteries, magnets, or items with diameter greater than 25mm as they are less likely to pass through the pylorus. Ingestion of foreign non-food objects is more commonly encountered in the pediatric population with coins representing the majority of cases. When seen in adults, there is usually concomitant alcoholism or cognitive and psychiatric disorders. In our patient's case, there was a history of excessive alcohol abuse. It is likely that the coins were ingested while intoxicated. The patient's use of non-steroidal anti-inflammatory drugs likely lead to ulcer development; however, it is possible that the coins may also have contributed as ulcers have been reported with similar blunt objects. (Figure Presented).
Keywords: esomeprazole; nonsteroid antiinflammatory agent; abdominal pain; adult; adverse drug reaction; aged; airway; alcohol abuse; alcoholism; biopsy; blood cell count; burn; case report; child; cognitive defect; coronary artery disease; endoscopy; epigastric pain; foreign body; Helicobacter pylori; hospital; human; human tissue; information retrieval; ingestion; magnet; male; melena; nonhuman; pylorus; rectum hemorrhage; side effect; surgery; ulcerogenesis; weakness

Massive submucosal esophageal tear from meat impaction in candida esophagitis - Alexandre, C.; Partiula, B.; Teagle, K.; Mudireddy, P.; Caguiat, K.F. (American Journal of Gastroenterology, 2016)
Candida species are commensal organisms of different mucous membranes in healthy individuals with the esophagus being a common site of colonization. Candida esophagitis involves the superficial mucosa and transmural invasive candida infection is rare even in immunocompromised patients. Here we report a 49 year-old male who presented with hematemesis after a piece of steak was stuck in his esophagus. He was found on upper endoscopy to have deep esophageal tears, extensive ulcerations and whitish plaque. Biopsies were positive for candida esophagitis and he was subsequently diagnosed with HIV. The patient is a 49 year-old male with history of hypertension that presents with a food impaction in his esophagus after eating steak. He tried to relieve the impaction with self-induced vomiting without relief followed by multiple episodes of hematemesis associated with dysphagia, odynophagia, and severe chest pain. He reports being in usual state of health prior to that incident. He is not on chronic steroids, PPI, or anticoagulant and denies any history of NSAIDs or alcohol abuse. Physical examination was negative for any icteric sclera, palpable crepitus over chest wall or neck, or abdominal findings. CT chest showed no radiopaque foreign body or pneumomediastinum. On emergent EGD the findings were two large submucosal esophageal tears extending 27 to 37 cm from the incisors, diffuse whitish plaques covering the upper esophagus extending to the distal esophagus, and ulcerations of esophageal mucosa but no obvious perforation or food bolus in the esophagus. He was admitted under CT surgery and was kept NPO, on IVF, IV antibiotics and antifungal. Tissue biopsy of the esophagus revealed acute and chronic esophagitis, abundant candida and bacteria. He was positive on HIV screening with a viral load 12,214 and absolute CD4 count 169. A barium esophagram revealed no contrast extravasation. Candida esophagitis is known to occur in immunocompromised hosts but severe complications (i.e perforation, fistula) with esophageal candidiasis are rare and have been mainly reported in diabetic patients with renal transplantations and patients with hematologic malignancy. Unlike eosinophilic esophagitis, food impaction is not often seen in candida esophagitis. The unique highlights of this case are the absence of any prior esophageal or constitutional symptoms and the extent of esophageal mucosal injury sustained from the food impaction in the setting of esophageal candidiasis. (Figure Presented).
Keywords: anticoagulant agent; antifungal agent; nonsteroid antiinflammatory agent; steroid; adult; alcohol abuse; biopsy; case report; CD4 lymphocyte count; complication; contrast medium extravasation; diabetic patient; diagnosis; disease duration; eating; endoscopy; eosinophilic esophagitis; esophagus candidiasis; esophagus fistula; esophagus mucosa; esophagus ulcer; foreign body; hematemesis; hematologic malignancy; human; Human immunodeficiency virus; human tissue; hypertension; immunocompromised patient; incisor; jaundice; kidney transplantation; male; middle aged; neck; nonhuman; odynophagia; perforation; physical examination; pneumomediastinum; sclera; screening; surgery; symptom; thorax pain; thorax wall; virus load; vomiting

A rare case of gastric emphysema secondary to cannabinoid hyperemesis syndrome - Kumar, S.T.; Nazli, A.; Vadada, D.; Kalman, J.; Yiachos, C.; Prakash, S. (American Journal of Gastroenterology, 2016)
24 year old female with no past medical history was admitted for intractable nausea and vomiting for two days. Patient has history of chronic marijuana use and reported multiple episodes of nausea with vomiting occurring after smoking marijuana for 48 hours. She also reported severe retching with these episodes. She has a known history of recurrent episodes of nausea and vomiting with long standing marijuana use. She denied any recent travel, ill contacts, fever, hematemesis, alcohol ingestion, and foreign body ingestion. She denied any prior surgeries or home medications. Her labs including complete blood count, comprehensive metabolic profile, lipase, amylase, urinalysis, and pregnancy test were unremarkable. Urine drug screen was positive for marijuana. CT scan of the abdomen was performed which revealed air in the gastric wall consistent with gastric emphysema. No evidence of perforation was seen. Surgery was consulted and patient was managed conservatively with supportive care and antibiotics. The patient improved clinically with subsequent improvement on repeat radiographic imaging. Gastric emphysema, seen when intramural air accumulates within the stomach wall, is a rare finding with 18 reported cases in literature. The acidic environment of the stomach creates a protective mucosal barrier preventing air penetration. However, there are several proposed mechanisms that can disrupt the mucosal barrier including infections, increased intragastric pressure, foreign body ingestion, and dissection of air from the mediastinum. There are 2 variants of intramural gas within the stomach wall: emphysematous gastritis and gastric emphysema. Emphysematous gastritis is proposed to have an infectious etiology and usually presents with an acute abdomen with a mortality rate reported up to 60%. Gastric emphysema is proposed to have a traumatic/mechanical/inflammatory etiology causing air to dissect through the stomach wall. Gastric emphysema tends to have a more benign clinical course and typically resolves with conservative management. Gastric emphysema is a rare finding with significant clinical importance. We report an unusual case of gastric emphysema secondary to excessive retching and vomiting resulting from cannabinoid hyperemesis syndrome. A favorable prognosis is seen with early recognition and appropriate medical management. (Figure Presented).
Keywords: alcohol; amylase; antibiotic agent; cannabis; endogenous compound; triacylglycerol lipase; acute abdomen; adult; blood cell count; cannabis use; case report; computer assisted tomography; conservative treatment; dissection; emphysema; female; fever; foreign body; gastritis; hematemesis; human; human tissue; hyperemesis gravidarum; imaging; infection; ingestion; mediastinum; mortality rate; patient history of surgery; perforation; pregnancy test; prognosis; recognition; retching; smoking; stomach pressure; stomach wall; surgery; travel; urinalysis; young adult

A case of osteomyelitis in patient with remaining assist device driveline after heart transplantation-a case report - Harmel, E.; Barten, M.J.; Philipp, S.; Rybczynski, M.; Reichenspurner, H.; Sill, B. (Transplant International, 2016)
Introduction and Background: Implantable ventricular assist devices (VADs) might be a key tool to counter organ scarcity. Despite technological improvements VADs are still related to complications e.g. bleeding, driveline infection, thrombosis or stroke causing an increasing number of patients receiving HTX from device. Due to numerous tissue adhesions HTX is getting technically more challenging. The time-consuming approach often leads to an incomplete removal of driveline and outflow graft material. Methods: We report about a 49 years old male pat. with ischemic cardiomyopathy who received a VAD in 2013 and HTX in 2014. 1 year later the pat. was admitted to hospital with left sided chest pain. Apart from swelling local findings didn't reveal further signs of inflammation. Inflammatory markers were slightly increased, blood culture sets remained negative. Thoracic CT revealed signs of osteomyelitis in the ventral parts of the left 4th rib. After operative removal osteoid material was sent for microbiol. testing which revealed colonization with Candida and Staph. epidermidis. An anti-infective therapy was initiated. Due to persistent pain despite opioids we reevaluated the thoracic images and a 15 cm long piece of remaining driveline located in the 4th to 5th intercostal space was identified. Indication for driveline removal was set. Afterward a sudden pain relief and decrease of WBC count and CRP was seen and the pat. was discharged. Results and Conclusions: In long-term VAD support driveline infections are still a key problem. Whether this also affects remaining driveline after HTX is still not known. Due to obligatory immunosuppression after HTX the general risk for infection is increased and the complete VAD excision including the removal of all foreign material seems to be the most appropriate approach. In the described case remaining driveline caused persistent pain and several readmissions to hospital accompanied by social isolation, reduced quality of life, disability to work and a great financial burden for public health system.
Keywords: adult; adverse device effect; analgesia; anti-infective therapy; blood culture; Candida; case report; disability; driveline infection; excision; foreign body; heart transplantation; hospital readmission; human; immunosuppressive treatment; ischemic cardiomyopathy; leukocyte count; male; middle aged; nonhuman; osteoid; osteomyelitis; public health; quality of life; rib; social isolation; swelling; thorax pain

Correlation between word recognition score and intracochlear new bone and fibrous tissue after cochlear implantation in the human - Kamakura, T.; Nadol, J.B. (Hearing Research, 2016)
Cochlear implantation is an effective, established procedure for patients with profound deafness. Although implant electrodes have been considered as biocompatible prostheses, surgical insertion of the electrode induces various changes within the cochlea. Immediate changes include insertional trauma to the cochlea. Delayed changes include a tissue response consisting of inflammation, fibrosis and neo-osteogenesis induced by trauma and an immunologic reaction to a foreign body. The goal of this study was to evaluate the effect of these delayed changes on the word recognition scores achieved post-operatively. Seventeen temporal bones from patients who in life had undergone cochlear implantation were prepared for light microscopy. We digitally calculated the volume of fibrous tissue and new bone within the cochlea using Amira® three-dimensional reconstruction software and assessed the correlations of various clinical and histologic factors. The postoperative CNC word score was positively correlated with total spiral ganglion cell count. Fibrous tissue and new bone were found within the cochlea of all seventeen specimens. The postoperative CNC word score was negatively correlated with the % volume of new bone within the scala tympani, scala media/vestibuli and the cochlea, but not with the % volume of fibrous tissue. The % volume of new bone in the scala media/vestibuli was positively correlated with the degree of intracochlear insertional trauma, especially trauma to the basilar membrane. Our results revealed that the % volume of new bone as well as residual total spiral ganglion cell count are important factors influencing post-implant hearing performance. New bone formation may be reduced by limiting insertional trauma and increasing the biocompatibility of the electrodes.
Keywords: aged; article; basilar membrane; cell count; clinical article; cochlea; cochlea duct; cochlea injury; cochlea prosthesis; cochlear implantation; software; Consonant Vowel Nucleus Consonant Word Test; female; fibrous tissue; human; human tissue; image reconstruction; male; microscopy; ossification; priority journal; scala tympani; scala vestibuli; spiral ganglion; temporal bone; tissues; very elderly; volumetry; word memory test; word recognition; Amira

Operations in “Damage Control” System -common in extreme conditions - Hájek, M.; Dobeš, D. (European Surgery - Acta Chirurgica Austriaca, 2016)
Introduction: Operations in the “Damage control” system (hereinafter only DC) are a modern surgical procedure for very serious injuries in situation when the patient is in life-threatening conditions caused not only by the injury itself, but by a delay in treatment and developing internal processes that are manageable, when the surgical reparation procedure is minimalized as for time. The main focus is on the Lethal Trias, which means: a/hypothermy, b/coagulopathy, c/acidosis. This trias (Shapiro et al. - 2000), hypothermy, haemocoagulopathy and acidosis, are the patophysiolological condition leading to death if not solved or solved late. System DC is suitable to use in mass casualties in extreme conditions. Definition: DAMAGE CONTROL is a multiphase approach to patient with life-threatening injuries, during which we try to re-establish or at least approximate patient's normal homeostasis, Rather than definitive trauma treatment in one phase, it attempts to keep the patient alive by dividing the treatment into several phases: 1. Admission and necessary examinations - in accordance with common procedure 2. First phase: quick stop bleeding, drainage or eventually stoma, tamponade of parenchymal organs, temporary laparotomy closure, examination of intrathoracic injuries - max. 40-50 minutes 3. ICU treatment: 24-48 hours, homeostatic adjustment 4. Second phase: resection surgeries, definitive treatment of bleeding arteries, tamponade removal max. 60-90 minutes 5. ICU treatment - 24-48hours, repetitive care leading to full stabilization of the patient - inner environment acidity normalization, temperature stabilization, normal volume, acceptable blood count and ionogram, coagulation approaching the norm 6. Third phase: restoration of intestinal continuity, definitive treatment of life non-threatening injuries in a longer time period. 7. ICU treatment .. etc. Damage Control Concept: The surgeon must decide for DC before the surgery. During the treatment the surgeon can reconsider the decision in case the DC approach does not seem to be beneficial. The following is thus important: 1. Timely indication which patient requires DC 2. decision for urgent surgery. In polytrauma it is necessary to consider which action will have priority and if more operational teams will be working simultaneously. 3. During the first phase sufficient perfusion of vital organs must be preserved, adequate ventilation, attempt for normothermia and maintenance or renewal of normocoagulation. 4. Decision how many surgical performances will be necessary, the right estimate of definitive surgery time and definitive wound closure. Hypothermy: - Drop in metabolic heat production during the hypovolemic shock - Unprotected body, unfavourable temperature conditions during the transport, wet closing and an open body cavity. - Cold fluids administrated intravenously during massive volume resuscitation/mentioned above/ - Temperature drop by 4-8 degrees C in 1 hour. At the temperature of 35°C mortality rate is almost 40x higher. - Lowering coagulation and cardiac output per minute Acidosis: - Hypovolemia leads to development of metabolic lactic acidosis - Metabolic acidosis is accompanied by heart arrhythmia, coagulation system disorder and lowered effect of catecholamines Coagulopathy: - Has multi factor basis (hypothermy, metabolic acidosis, blood loss, blood dilution from administered solutions, lowered thermoregulation, lowered synthesis of hemocoagulation factors and at the same time their increased consumption - DIC) - Hypocoagulation - twice increased Quick test and APTT - Hypercoagulation - consumption of coagulation factors -venous thrombosis, ARDS Indication for operation in the DC system: 1. Metabolic indications: Hypothermy with body temperature lower than 35°C. Absolute indication is temperature below 34°C, when hours lasting surgery leads almost certainly to death, acidosis with pH lower than 7.2 and with deficit of bases higher or equal 8, coagulopathy with APTT longer than 60 seconds. 2. Clinical indications: Penetrating abdominal trauma with hypotension (systolic BP is lower than 90 mmHg), high speed and/or multiple gunshot abdominal injury, blast abdominal injury, polytrauma with serious blunt abdominal injury, polytrauma with multiple serious bleeding sources, polytrauma without clear priorities of surgical treatment, complex pelvic injury combined with abdominal trauma, and mainly a higher number of casualties exceeding the possibilities of the medical institution (mass disasters, armed conflict). DAMAGE CONTROL in abdominal trauma 1. In the first phase laparotomy is carried out as a part of patient's resuscitation. The bleeding is kept under control (using vascular clamps and ligatures, tamponade of parenchymatous organs, pelvis and retroperitoneum) as well as contamination (removal of foreign bodies or quick catheterization of hollow organs into the wound without reconstruction attempts). Examination of all abdominal quadrants must be done to check the bleeding and serous bleeding mustn't be omitted because of haste! A quick closure of abdominal wall follows - we do not close aponeurosis! The key to success is in immediacy and simplicity. 2. The second phase continues by resuscitation in ICU or inpatient part of Critical Care Department. It involves above all proper warming up of the patient and optimizing ventilation and perfusion of the organism. 3. The third phase is reoperation considering a definitive reconstruction of organs. The decision is up to the surgeon after agreement with an anesthesiologist. If one of the definitive reconstruction surgeries lead to homeostasis deterioration or if other blood losses occur, this could be postponed to the later phase after recurrent stabilization at ICU. In the third phase arteries and hollow organs are reconstructed, definitive treatment of tamponed organs and areas is done as well as search and follow-up treatment of omitted minor injuries. It is then followed, according to the results, by temporary or definitive abdominal closure. DAMAGE CONTROL in chest injury 1. Urgent ambulatory thoracotomy (UAT) is often suitable, which is thoracotomy carried out at the hospital emergency admission room. It is considered as a part of the first operation phase, which continues after the patient's transfer to the operating theatre. The aim of UAT is above all to release the pericardial tamponade and in case of penetrating heart injury to provide its temporary treatment. According to the authors' experience, it is possible to use skin staplers. Direct cardiac massage is also possible, as well as temporary stapling the pulmonary hilum as a short term solution of vast pulmonary laceration. Another reason is a relatively easy closure of the distal part of thoracic aorta in left hemithorax in expected massive bleeding in abdominal cavity. Blind stapling in abdominal cavity under the diaphragm, recommended as emergency ambulatory surgery in many scientific resources, is technically much more demanding and requires considerable experience of the performing surgeon. 2. As a part of the first phase after a prospective UAT heart and lungs are treated in the operation theatre (parenchymal suturing, extra-anatomic resection etc.), artery ligation, or building an inner by-pass using a shunt (according to localization and the state of the patient). Treatment of the main bronchus or trachea is necessary. Esophagus treatment can be left for secondary treatment or potential second operation after the patient stabilization. A catheter probe is necessary to be placed over the injury to the stomach. 3. ICU treatment represents the second phase and is identical with the above mentioned second phase in abdominal trauma using DC. (Figure Presented) 4. The third phase is usually thorax reopening and definitive treatment of esophagus, pericardium or the by-passed injured arteries. Pericardium should be left open unless cardiac herniation may occur.
Keywords: blood clotting factor; catecholamine; endogenous compound; abdominal blunt trauma; abdominal cavity; abdominal penetrating trauma; abdominal wall; acidity; adult respiratory distress syndrome; ambulatory surgery; anesthesiologist; aponeurosis; artery ligation; artificial ventilation; bleeding; blood cell count; blood clotting disorder; catheterization; cold stress; contamination; deterioration; diaphragm; follow up; foreign body; gunshot injury; heart arrhythmia; heart injury; heart massage; heart output; heart tamponade; hemodilution; hiatus hernia; homeostasis; hospital patient; human; hypotension; hypovolemic shock; intestine; intravenous drug administration; laceration; lactic acidosis; laparotomy; lung hilus; main bronchus; mass disaster; metabolic acidosis; mortality rate; multiple trauma; operating room; partial thromboplastin time; pelvis; perfusion; plastic surgery; reoperation; resuscitation; retroperitoneum; skin; stoma; surgeon; surgery; synthesis; systolic blood pressure; thermogenesis; thermoregulation; thoracic aorta; thoracotomy; thorax injury; trachea; vascular clamp; vein thrombosis; velocity; war; warming; wound closure

Unilateral recurrent anterior uveitis as the presenting sign of bladder carcinoma - Şatırtav, G.; Donbaloğlu, M.; Oltulu, R.; Oltulu, P.; Kerimoğlu, H.; Özkağnıcı, A. (Turk Oftalmoloiji Dergisi, 2016)
A 79-year-old male patient was followed for unilateral uveitis with 3 attacks in 10 months, despite initial improvement with steroid therapy. The patient had visual acuity (VA) of counting fingers in right eye, hypopyon and vitritis with no chorioretinal lesions. The left eye was normal. The patient was evaluated for intraocular foreign body, intraocular lymphoma and associated systemic disease and malignancy. Computed tomography of the abdomen showed a mass in the bladder. Biopsy confirmed bladder carcinoma. After resection of the mass, intraocular inflammation improved completely and no attack was noted in the follow-up. In his last examination, two years after the operation, VA was light perception; seclusio pupilla and mature cataracts were seen on biomicroscopy. There was no sign of vitritis on ocular ultrasonography. Evidence is discussed that suggests a link and potential etiology between refractory uveitis with hypopyon and bladder carcinoma. This is the first case of unilateral recurrent uveitis with hypopyon as the initial presenting sign of bladder carcinoma.
Keywords: dexamethasone; tropicamide; acute myeloid leukemia; aged; article; biomicroscopy; bladder biopsy; bladder carcinoma; case report; cataract; chronic myeloid leukemia; computer assisted tomography; echography; eye inflammation; fluorescence angiography; histopathology; human; hypopyon; intraocular foreign body; intraocular lymphoma; iridocyclitis; lymphatic leukemia; male; retina macula cystoid edema; steroid therapy; uveitis; dekort; dexasine; sikloplejin; tropamid

Unilateral recurrent anterior uveitis as the presenting sign of bladder carcinoma - Şatırtav, G.; Donbaloğlu, M.; Oltulu, R.; Oltulu, P.; Kerimoğlu, H.; Özkağnıcı, A. (Turkish Journal of Ophthalmology, 2016)
A 79-year-old male patient was followed for unilateral uveitis with 3 attacks in 10 months, despite initial improvement with steroid therapy. The patient had visual acuity (VA) of counting fingers in right eye, hypopyon and vitritis with no chorioretinal lesions. The left eye was normal. The patient was evaluated for intraocular foreign body, intraocular lymphoma and associated systemic disease and malignancy. Computed tomography of the abdomen showed a mass in the bladder. Biopsy confirmed bladder carcinoma. After resection of the mass, intraocular inflammation improved completely and no attack was noted in the follow-up. In his last examination, two years after the operation, VA was light perception; seclusio pupilla and mature cataracts were seen on biomicroscopy. There was no sign of vitritis on ocular ultrasonography. Evidence is discussed that suggests a link and potential etiology between refractory uveitis with hypopyon and bladder carcinoma. This is the first case of unilateral recurrent uveitis with hypopyon as the initial presenting sign of bladder carcinoma.
Keywords: cyclopentolate; dekort; dexamethasone; dexamethasone sodium phosphate; dexasine; sikloplejin; triamcinolone; tropamid; tropicamide; aged; article; best corrected visual acuity; biomicroscopy; biopsy; bladder carcinoma; case report; cataract; clinical article; computer assisted tomography; conjunctival hyperemia; drug dose reduction; echooculography; eye fundus; eye inflammation; fluorescence angiography; foreign body; human; human tissue; hypopyon; ischemia; male; nuclear magnetic resonance imaging; optic disk; paraneoplastic syndrome; recurrent anterior uveitis; retina macula cystoid edema; transurethral resection; uveitis; vascular disease; visual impairment; vitritis; dekort; dexasine; sikloplejin; tropamid

Guideline Implementation: Prevention of Retained Surgical Items - Fencl, J.L. (AORN journal, 2016)
A surgical item unintentionally retained in a patient after an operative or other invasive procedure is a serious, preventable medical error with the potential to cause the patient great harm. Perioperative RNs play a key role in preventing retained surgical items (RSIs). The updated AORN "Guideline for prevention of retained surgical items" provides guidance for implementing a consistent, multidisciplinary approach to RSI prevention; accounting for surgical items; preventing retention of device fragments; reconciling count discrepancies; and using adjunct technologies to supplement manual count procedures. This article focuses on key points of the guideline to help perioperative personnel provide optimal care during a procedure. Key points addressed include taking responsibility for RSI prevention as a team; minimizing distractions, noise, and interruptions during counts; using consistent counting methods; reconciling discrepancies; and participating in performance-improvement activities. Perioperative RNs should review the complete guideline for additional information and for guidance in writing and updating policies and procedures.
Keywords: foreign body; human; nursing education; practice guideline

Surgical count process for prevention of retained surgical items: an integrative review - Freitas, P.S.; Silveira, R.C.; Clark, A.M.; Galvão, C.M. (Journal of clinical nursing, 2016)
AIMS AND OBJECTIVES: To analyse the evidence reported in the literature concerning the surgical count process for surgical sponges, surgical instruments and sharps and to identify knowledge gaps for future research on the surgical count process. BACKGROUND: The surgical count process stands out among the practices advocated by the World Health Organization to ensure surgical safety. The literature indicates that this practice should be performed in all surgical processes. However, surgical items are still retained. DESIGN: Integrative review. METHODS: The literature search was conducted in the PubMed, CINAHL and LILACS databases and included studies on the surgical count process published in English, Spanish and Portuguese from January 2003-December 2013. RESULTS: A total of 28 primary studies were included in the sample, allowing the knowledge on the surgical count process to be summarised and grouped into three categories: risk factors for retained surgical items, how the surgical count process should be performed in the intraoperative period and the accompanying technologies that collaborate to improving the manual count process. CONCLUSIONS: The correct implementation of the surgical count process by the perioperative nurse may contribute to preventing retained surgical items, thereby improving surgical patient safety. RELEVANCE TO CLINICAL PRACTICE: Nurses can use this review to assist in decision-making directed towards preparing, updating and implementing a reliable system for the surgical count process based on recent evidence because the perioperative nurse plays a key role in the implementation of this practice in health services.
Keywords: foreign body; human; medical error; nursing; patient safety; perioperative nursing; practice guideline; prevention and control; surgery

The Pathogenesis of Implant-Related Reactive Lesions: A Clinical, Histologic and Polarized Light Microscopy Study - Halperin-Sternfeld, M.; Sabo, E.; Akrish, S. (Journal of periodontology, 2016)
BACKGROUND: Peri-implant soft tissue reactive lesions (I-RLs) may jeopardize implant success and survival. To the best of the authors' knowledge, its pathogenesis is unknown. The objective of this study is to conduct a clinicopathologic and polarized light microscopy (PLM) analysis of 14 new I-RLs and compare them with comparable tooth-associated cases (T-RLs) to better understand I-RL pathogenesis. METHODS: Fifty-eight new cases of I-RL and T-RL were retrieved from the pathology department archives of Rambam Health Care Campus, Haifa, Israel. Retrospective analysis of histopathologic and clinical features was conducted, documented, and then compared for: 1) I-RL (n = 14), 2) peri-implant pyogenic granuloma (I-PG) (n = 5), 3) peri-implant peripheral giant cell granuloma (I-PGCG) (n = 9), 4) T-RL (n = 44), 5) tooth-associated pyogenic granuloma (T-PG) (n = 21), and 6) tooth-associated peripheral giant cell granuloma (T-PGCG) (n = 23). Presence of foreign bodies was assessed using PLM. RESULTS: Foreign bodies were found more commonly in I-RLs (n = 13/14; 93%) when compared with T-RLs (n = 18/44; 41%), which was a statistically significant difference (P = 0.01) with an odds ratio of 7.9. Microscopically, I-PGCG was associated with: 1) lower multinucleated giant cell count (P = 0.04); 2) lower density of mesenchymal cells (P = 0.05); and 3) more diffuse, non-lobulated stromal morphology (P = 0.001). Clinically, I-RLs were found in patients who were older, and all cases were located in the posterior region: mandible (n = 12/14; 86%) and maxilla (n = 2/14; 14%). CONCLUSIONS: In cases of implant failure, implantation of foreign bodies may play a role with subsequent development of I-PG and I-PGCG-like lesions. Clinicians should be aware of this risk so they can implement measures to minimize adverse implant outcomes.
Keywords: diagnostic imaging; gingiva disease; human; Israel; polarization microscopy; retrospective study; tooth implant

Pancreatic and hepatic abscesses in a diabetic patient simulating a malignancy - Bulcha, N.A.; Khanapara, D.B.; Slinchenkova, O. (Journal of General Internal Medicine, 2016)
LEARNING OBJECTIVE #1: Identify Streptococcus Aginosus as an emerging cause of pyogenic liver and pancreatic abscesses. . LEARNING OBJECTIVE #2: Recognize that uncontrolled DM is a risk factor for pancreatic and hepatic abscesses. CASE: A 72 year old man presented with 6 months of progressively worsening lethargy and epigastric discomfort. He had a history of DM and an episode of acute pancreatitis 2 years prior. On presentation, he was febrile and had diffuse abdominal tenderness. He had a white count of 14,700. His liver function tests and pancreatic enzymes were normal. His hemoglobin A1C was 8.8 %. A CT scan of the abdomen revealed a 3.5 cm necrotic mass in the uncinate process and numerous hepatic masses. Blood culture grew Streptococcus Aginosus. EUS guided FNA of the pancreatic mass and a CT guided FNA of a sentinel hepatic lesion revealed inflammatory cells and was negative for malignant cells. The patient received 4 weeks of IV antibiotics and was discharged on a 2 week course of oral antibiotics. Three months later, a repeat CT scan revealed complete resolution of the pancreatic and hepatic lesions. DISCUSSION: A suspicious abdominal mass on imaging is a common finding encountered by the internist. As illustrated in our case, pyogenic intra-abdominal abscesses can present as mass lesions with vague symptoms and laboratory investigation results. The liver is the most common site for pyogenic intra-abdominal abscesses with a prevalence rate of 8-16 cases per 100,000 among hospitalized patients and an estimated 2.3 cases per 100,000 in the population. Pancreatic abscesses are rare but are associated with greater mortality. The underlying mechanisms of pancreatic and liver abscess formation are variable. In the liver, about 60% of abscesses can be attributed to biliary tract obstruction. Other frequent causes of liver abscess include infections of the portal bed infections and direct extension from local infections. Most cases of pancreatic abscess occur following an episode of acute pancreatitis and infection of a pancreatic cyst. Penetrating abdominal trauma, surgery and bowel perforation due to foreign body, inflammatory bowel disease and ischemic colitis have been implicated in both pancreatic and liver abscesses, but are less common. Escherichia Coli is the most frequently identified pathogen from intraabdominal abscesses. Among gram positives, Streptococcus Millieri is an important cause of pyogenic bacterial abscess. This group of bacteria is present in 12 % of liver abscesses and has been identified in up to 20-40 % of isolates from healthy appendices. Streptococcus Millieri are also known as the streptococcus Aginosus group after the most commonly encountered bacteria in the group. Streptococcus Aginosus has been found in 64 % of isolates from healthy individuals containing streptococcus Millieri species. Streptococcus Aginosus also has the highest predilection to cause intra-abdominal abscess formation. The other members of this group are Streptococcus Intermedius and Streptococcus Constellatus. All members of this group are normal flora, found in the oral cavity, the GI and the GU tracts. Infectious abscesses due to these organisms usually occur in patients with cancer and impaired immunity or following surgery and abdominal trauma Diabetes Mellitus is also a risk factor for infectious abscesses, particularly in the liver. Patients with DM can have a 3.6 fold increased risk of developing pyogenic liver abscesses. This risk is attributable to the hyperglycemic environment in DM which leads to neutrophil dysfunction and promotes the growth of pathogenic bacteria. Patients with DM have decreased chemo taxis, phagocytosis and oxidative action of phagocytes. Other features of inflammation such as protein leakage and edema formation in response to inflammatory mediators are also impaired in diabetic patients. One mechanism for neutrophilic dysfunction in hyperglycemia is thought to be the result of accumulation of advanced glycation end products. (AGEs), formed due to the interaction of glucose with proteins and lipids. Advanced glycation products modify several receptors on endothelial cells, smooth cells and mononuclear phagocytes, altering membrane structure and function. The interaction between AGEs and phagocyte cell membranes leads to decreased fluidity and leukocyte migration. Hyperglycemia also causes increased levels of sorbitol in phagocytic cells via activation of the polyol pathway which further impairs leukocyte and endothelial cell interactions. The mechanisms leading to neutrophilic dysfunction are related to the degree of hyperglycemia and can be reversed with improved glycemic control. In our patient, his uncontrolled DM was a likely predisposing factor for his liver and pancreatic abscesses. Good glycemic control can thus prevent intraabdominal infections and complement antibiotic therapy. Streptococcus Aginosus is sensitive to commonly used antibiotics but there is data suggesting emerging resistance to antibiotics which could pose a significant problem in the management of infections caused by this organism. Further studies are warranted to better understand resistance patterns and guide antibiotic therapy.
Keywords: antibiotic agent; protein; glucose; receptor; hemoglobin; pancreas enzyme; advanced glycation end product; lipid; sorbitol; polyol; diabetic patient; human; society; internal medicine; liver abscess; Streptococcus; liver; patient; infection; pancreas abscess; abscess; abdominal abscess; hyperglycemia; phagocyte; bacterium; liver injury; glycemic control; risk; computer assisted tomography; endothelium cell; acute pancreatitis; risk factor; antibiotic therapy; pancreas cyst; blood culture; mortality; epigastric discomfort; population; inflammation; phagocytosis; tax; cholestasis; glycation; hospital patient; abdominal penetrating trauma; prevalence; neutrophil; pyogenic liver abscess; diabetes mellitus; laboratory; abdomen; lethargy; abdominal injury; surgery; neoplasm; flora; internist; Streptococcus intermedius; imaging; species; Streptococcus constellatus; mouth cavity; pathogenesis; immunity; abdominal mass; liver function test; Escherichia coli; environment; ischemic colitis; abdominal infection; cancer cell; edema; inflammatory bowel disease; leukocyte; inflammatory cell; foreign body; intestine perforation; mononuclear phagocyte; leukocyte migration; cell membrane; cell interaction; membrane structure; traumatology; disease predisposition; organisms; abdominal tenderness; male

Endoscopic resection of a 30mm gastric stromal tumor - Singh, A.; Ali, M.A.; Bagby, C.; Marks, J.M.; Chak, A. (Gastrointestinal Endoscopy, 2016)
Case: A 35- year old patient was referred to us after a 30 mm gastric subepithelial mass was noted on upper endoscopy. Technique: Endoscopic ultrasound showed a 30 mm mass arising from the muscularis propria on the lesser curvature. The margins were well defined and no cystic spaces within the mass were noted. Patient was offered the options of laparoscopic or endoscopic removal, and she chose the latter. Patient was brought to the operating room and general anesthesia was administered. A detatchable, plastic ligature was carefully placed around the base on the lesion to decrease the risk of bleeding and also in an attempt to separate the tumor capsule from the outer muscle fibers. A 30-mm oval snare was then used to resect the base of the subepithelial tumor. Using a foreign body retrieval net the resected tumor was brought in to the esophagus but we were unable to retrieve it beyond the upper esophageal sphincter. An esophageal overtube was then advanced into the distal esophagus and the tumor was pulled into the overtube and the overtube was withdrawn. Two over the scope closure devices were used to close the resection defect. Pathology revealed a 30 mm tumor with an intact capsule and bland spindle cells. The mitotic count was 4 per 50 high power fields. Immunohistochemistry for CD117 was strongly positive. Discussion: The National Comprehensive Cancer Network guidelines recommend that while gastrointestinal stromal tumors smaller than 2 cm can be managed conservatively with surveillance, lesions larger than 2 cm should be surgically. There are no recommendations for the role of endoscopic resection of these tumors. A recent study comparing surgical with endoscopic resection for GISTs, showed that endosopic resection had shorter procedure time and length of stay but also had lower R0 resection rates. Still there was no significant difference in the recurrence rates. The challenges to endoscopic resection include achieving a tumor free margin, closure of the full thickness defect and en-bloc tissue extraction. Technical considerations for endoscopic resection of GISTs include the use of EUS to define the anatomy and the use of endoscopic ligature to separate the tumor from outer muscle fibers. Meticulous attention to closure of the defect is imperative and overtube can be used to facilitate tumor extraction. Conclusion: Loop and snare resection of gastric stromal tumors can be considered prior to laparoscopic resection in selected cases where the tumor resection defect can be successfully closed with endoscopic techniques.
Keywords: plastic; neoplasm; endoscopic surgery; surgery; human; patient; muscle cell; esophagus; extraction; bleeding; risk; gastrointestinal stromal tumor; procedures; pathology; endoscopic ultrasonography; upper esophagus sphincter; devices; general anesthesia; cancer surgery; spindle cell; immunohistochemistry; thickness; length of stay; recurrence risk; foreign body; tissues; operating room; endoscopy

Abnormal uterine bleeding asociated to actinomices endometritis in perimenarcheal adolescent - Menéndez, M.; Zajer, C.; Ralph, C.; Canessa, M.J.; Zuñiga, P.; Vizcaya, C. (Journal of Pediatric and Adolescent Gynecology, 2016)
Background: Abnormal uterine bleeding in adolescence is caused by multiple factors, being the most frequent anovulatory dysfunctional uterine bleeding (DUB), coagulopathies, pregnacy complications and infections. Pelvic infection due to Actinomices has been described in long term IUD users, or other foreign bodies, in which infection is ascendent. Less frequently it is secondary to an appendectomy. Common symptoms are abdominal pain, pelvic tumor, uterine bleeding or fever. These kind of infections are extremely rare in adolescence. Case: 12-year old girl, carrier of a mild Von Willebrand disease, presents with repeated metrorrhagia since menarche, up to 20 days. No history of abuse or sexual initiation was present. Due to poor response to tranexamic acid, oral contraceptives pills (OCP) were initiated. Patient presented with a new episode of bleeding during OCP use, with no response to tranexamic acid, OCP in high doses (up to 90 etinylestradiol mcg a day), and only temporary response to desmopresin. Disabling pelvic pain and purulent vaginal discharge without fever was added. Initial blood count showed 19000 leukocytes and 22 ERS. Vaginal culture: normal flora, Chlamydia and Gonococco NAATs were negative. Pelvic ultrasound (Figure 1) revealed a significant increase in uterine volume (11.5 x 5.3 cm length) and cavity occupied by an image resembling a clot, measuring 6 x 2.5 cm. An hysteroscopy was performed, showing fibrinolitic, purulent material. Curettage culture was positive for Actinomyces spp. (MALDI-TOF MS) and biopsy findings were compatible with the diagnosis. An MRI performed post curettage (Figure 2), showed no abdominal or pelvic collections, nor tumoral images. Patient is currently in her third month of antibiotic treatment and was cycled succesfully with progestagens. The bleeding had a total duration of 2 months, ceased 25 days after curettage and abdominal pain subsided after 2 months of antibiotic treatment, with progressive normalization of uterine volume. Comments: Causes for AUB in adolescence may be multiple and combined. This is how our patient presents a coagulopathy, anovulatory cycles and finally an infection was added. Chlamydial and gonococal endometritis might present with abnormal heavy bleeding, associated with pelvic pain in adolescents. Actinomices endometritis is not a common diagnosis, especially in the absence of a foreign body. In this case we hypothesize that an intracavitary organized clot might have acted as a foreign body, allowing Actinomices to ascend from a dilated cervix. Actinomices, an anaerobic bacteria, is hard to culture, and diagnosis is frecuently done with anatomopathological findings. Treatment with antibiotics is prolonged, 3 to 12 months, being Betalactams the first choice. This case emphasizes that every time a patient presents with non responsive AUB, rare causes should be ruled out. (Figure Presented).
Keywords: tranexamic acid; ethinylestradiol; oral contraceptive agent; antibiotic agent; human; adolescent; gynecology; endometritis; uterus bleeding; clinical research; North American; society; female; infection; patient; curettage; foreign body; adolescence; diagnosis; bleeding; abdominal pain; pelvic pain; fever; metrorrhagia; antibiotic therapy; uterus; pelvis; von Willebrand disease; leukocyte; girl; blood cell count; vagina discharge; drug megadose; pelvis tumor; pelvic inflammatory disease; appendectomy; flora; anaerobic bacterium; anovulation; abuse; menarche; blood clotting disorder; biopsy; Actinomyces; hysteroscopy; ultrasound; Chlamydia; pill; nuclear magnetic resonance imaging; intrauterine contraceptive device

In-vivo efficacy of a novel Leu-t-RNA synthatase inhibitor compound a against MDR Pseudomonas aeruginosa 1594965 in a foreign body associated urinary tract infection model - Kumar, M.; Rao, M.; Barman, T.K.; Pandya, M.; Dube, S.; Purnapatre, K.P. (International Journal of Infectious Diseases, 2016)
Background: Pseudomonas aeruginosa is one of the major pathogens causing morbidity and mortality in hospital acquired infections (HAI).MDRP. aeruginosa are resistant to 3 or more classes of antibiotics. In cUTI cases catheter associated infections are incurable by most of the antibiotics. Compound A a novel Leu-t-RNA synthetase inhibitor showed efficacy in mouse ascending urinary tract infection (AUTI) model against P. aeruginosa biofilms formed on urinary catheters. Methods & Materials: In this study we established a mouse model of foreign body associated AUTI. A spiral polyethylene tube (PT) was placed transurethrally into bladder without surgical manipulation, followed by transurethral inoculation with Pseudomonas aeruginosa 1594965 (MDR) strain. Scanning electron microscopy (SEM) was done after 4h of inoculation of bacteria and bacterial counts were taken in kidneys, bladders and catheter pieces for respective samples. In vivo efficacy of Compound A was tested using this established model against P. aeruginosa 1594965(Compound A MIC: 1μg/ml, meropenem MIC: 32μg/ml). Compound A was tested at 30 and 220mg/kg SC q6h and meropenem was tested at human simulated dose of 60 mg/kg SC q6h. The treatment was initiated 4h post infection and continued daily for 7 days. Bacterial counts of placebo 4h, 7 days and 7 days treated group's samples of kidneys, bladders and catheters were calculated. Data was analysed using bacterial counts of each group and compared with those of 4 h placebo control group. Results: SEM showed good establishment of biofilm in 4 h samples. In foreign body associated mouse infection model. LRS inhibitor Compound A at 30, 220 mg/kg SC q6h showed log10 difference of -2.38, -2.18 log10 CFU/kidney respectively compared to 4h placebo and meropenemat 60 mg/kg SC q6h was inefficacious. In bladders this log difference was -2.30, -1.21, -0.78 respectively. On catheter only Compound A at 220mg/kg SC q6h showed log10 difference of -1.59 log10CFU/ml. No efficacy was observed in remaining groups Conclusion: Efficacy of Compound A in foreign body associated mouse AUTI infection model against MDR Pseudomonas aeruginosa 1594965 proves its efficacy on biofilm. These results warrant its further investigation in HAI associated Pseudomonas aeruginosa infections.
Keywords: RNA; transfer RNA; placebo; meropenem; antibiotic agent; 1 (5 isoquinolinesulfonyl) 2 methylpiperazine; synthetase; polyethylene; urinary tract infection; foreign body; Pseudomonas aeruginosa; model; infection; mouse; bladder; biofilm; catheter; bacterial count; human; scanning electron microscopy; kidney; inoculation; hospital infection; Pseudomonas infection; minimum inhibitory concentration; catheter infection; mortality; tube; bacterium; morbidity; mouse model; control group; urinary catheter; pathogenesis

Disposition and ultimate fate of a PLA-peg sustained release polymer after intra-articular injection - Hurtig, M.; Shive, M.; Kapoor, M.; Mahomed, N.; Marshall, W. (Osteoarthritis and Cartilage, 2016)
Purpose: Chronic inflammation after injury and surgical intervention drives catabolic metabolism and many downstream events that lead to osteoarthritis. Pain, altered gait or muscle recruitment tissue destruction is some of the consequences that occur in both animals and human patients. Oral Non-steroidal anti-inflammatory drugs (NSAIDs) are associated with cardiovascular, hepatic, renal and gastrointestinal complications. NSAIDs also alter hemostasis, so they are often avoided when anti-coagulant therapy is used. Intra-articular injection of joints with drugs and proteins utilizing a sustained release carrier is a relatively novel method of delivering active pharmacological ingredients to the synovial environment. This method could be cost effective and safer than daily oral NSAIDs. The purpose of the current experiments was to gain a better understanding of the fate of a polymer carrier after intra-articular injection and potential mechanisms by which it delivers active ingredients to the synovial environment. Methods: Eighteen female adult sheep were assigned to 6 groups of n = 3 and their right stifle joint was injected with 0.6 mL of a biodegradable mix of two polymers comprising D,L-lactide and polyethylene glycol (PDL-PEG) proprietary polymer (BEPO™) combined with 102 mg of celecoxib and a biocompatible green dye (D&C #6). The contralateral limb was injected with 0.6 mL of physiologic saline USP. Plasma and synovial fluid were collected at times 0,1, 7,14 28, 42 and 90 days post injection. The sheep were sacrificed in groups of three at 0, 1, 7, 14 28, 42 and 90 days to collect articular cartilage, synovial membrane, menisci and any residual polymer in the synovial cavity. Macroscopic and histological observations (OARSI scoring) were conducted to characterize the polymer formulation and its interaction with synovial tissues. Plasma, synovial fluid and synovial tissue were analyzed for celecoxib concentration using HPLC. Automated counting to determine the synovial fluid leukocyte and protein concentration was measured using the total solids method. Results: Sheep that received polymer injections into the stifle joint experienced mild effusion for 3 days without lameness throughout the study. There was mild elevation in SF leukocyte concentrations (11.0 and 4.1 109/L) on days 1 and 7 respectively but protein concentration did not normalize until day 28. Very low (<10 ng/mL) levels of celecoxib were detectable in plasma on Day 1 only. Higher levels of celecoxib above the estimated therapeutic level were detected in the synovial fluid on Day 1 and declined to zero over 28 days, but celecoxib was detectable in synovial tissue until the end of the study at 90 days. Macroscopically, small polymer particles were found in all compartments, cul de sacs and gutters of the stifle joint demonstrating that the original polymer depot had been morselized and widely distributed. Most particles were adherent to the synovial membrane by day 7 and increasingly incorporated into the synovial tissues over time. Histology of the synovial membrane demonstrated that larger polymer particles were engulfed within folds of the synovial lining and hypertrophied synovial lining cells appeared to phagocytose smaller particles (Fig 1- left panel). Interestingly, where polymer was found within the synovial membrane a typical foreign body reaction was observed dominated by macrophages and giant cells resulting in degradation of the polymer particles (Fig. 1 right panel). The reactions were focal and localized to polymer; areas of synovial membrane lacking polymer displayed normal morphology. By day 28 there were minimal reactions to polymer particles and by day 90, no polymer was detected. There were no adverse effects on other synovial tissues. Conclusions: This study shows that the primary target of this sustained release drug formulation is likely to be the synovial membrane where the polymer matrix undergoes cellular degradation and hydrolysis whilst releasing the active ingredient. Celecoxib exposure in the circulation was minimal eliminating the potential for systemic complications, but celecoxib persisted in the synovial membrane longer than in synovial fluid. This mechanism of uptake and degradation suggests that the synovial membrane can be a depot for release of active pharmacological ingredients into the synovial environment. (Figure Presented).
Keywords: polymer; celecoxib; protein; anticoagulant agent; nonsteroid antiinflammatory agent; hexamethonium bromide; sodium chloride; dye; macrogol; sustained drug release; intraarticular drug administration; osteoarthritis; society; synovium; synovial fluid; plasma; human; environment; sheep; leukocyte; injection; adult; pain; knee meniscus; therapy; surgery; articular cartilage; hemostasis; injury; limb; patient; female; tissues; neurophysiological recruitment; hydrolysis; adverse drug reaction; gait; macrophage; solid; effusion; foreign body reaction; histology; giant cell; morphology; drug formulation; metabolism; exposure; chronic inflammation; high performance liquid chromatography

Food bolus impaction in children is nearly always from eosinophilic esophagitis - Bradley, T.C.; Withers, G.D.; Ee, L.C. (Gastroenterology, 2016)
Introduction: Eosinophilic esophagitis (EoE) is a chronic, immune-mediated esophageal disease characterized clinically by symptoms related to esophageal dysfunction and histologically by eosinophil-predominant inflammation. Incidence and prevalence of this condition is increasing. The presentation of EoE varies with age but dysphagia is common in adults and older children. We hypothesize that most children requiring endoscopic management of food bolus impaction will have EoE. Methods: Retrospective review of all patients presenting or referred with food bolus impaction to a tertiary paediatric hospital between 1st Nov 2011 and 31st Dec 2014 inclusive. ICD-10 codes for endoscopy and removal of foreign body (30478-00, 30478-10) were used to identify patients who required endoscopy. All patients with esophageal foreign bodies were reviewed but only those with food in the esophagus were included in the study. EoE was defined as the presence of ≥15 eosinophils/ high power field on biopsy in either proximal and/or distal esophagus. Results: 138 endoscopies were performed in 133 children. Esophageal foreign bodies were noted in 78 procedures of which 76 were performed emergently. Procedures were mainly performed by gastroenterologists (n=50) and otolaryngologists (n=23). Common foreign bodies include coins (n=33), food (n=22), button battery (n=3), dental wire (n=3), and toys (n=3). 22 endoscopies were performed in 19 patients for food bolus impaction, and histology available in 14/19 (74%) patients. 79% (15/19) of these patients were male and median age at presentation was 12.08 (range 0.85-15.05) years. 79% (11/14) of those biopsied fulfilled histologic criteria for EoE. Interestingly the remaining 3 patients who had biopsies all demonstrated esophageal eosinophilia although their count (range 3-13eos/hpf) was insufficient to be diagnostic of EoE. 2/5 patients who did not have biopsies were known to have an esophageal stricture after previous surgery. Most children presenting with food bolus impaction therefore had underlying esophageal pathology. Conclusions: Food bolus impaction in children is nearly always a consequence of underlying esophageal disorder, of which EoE is the most common. We recommend that all children presenting with food bolus impaction have esophageal biopsies for EoE.
Keywords: child; human; eosinophilic esophagitis; gastrointestinal disease; food; patient; endoscopy; biopsy; procedures; esophagus; esophagus foreign body; foreign body; inflammation; eosinophil; ICD-10; esophagus biopsy; pediatric hospital; pathology; esophagus stenosis; male; diagnosis; histology; adult; dysphagia; prevalence; dental wire; electric battery; otolaryngologist; eosinophilia; gastroenterologist; patient history of surgery; diseases; esophagus disease

Simulation as an adjunct to didactics to increase knowledge retention: One year follow-up - Ionescu, B.; Young, N.; Patterson, D.; Grim, R.; Bell, T.; Ahuja, V. (Gastroenterology, 2016)
Purpose: Previous research has identified intra-operative high blood loss, unplanned emergencies in operation , and multi-operative teams increases the risk of an unidentified retained foreign object (URFO). Our community hospital's URFO policy was revised to incorporate changes that mandate a “full stop for counts” prior to closure of incision. An initial didactic session was held to educate the staff and residents on the new policy. Three months later a survey indicated a need for improvement in retention. A simulation was then created as an adjunct to didactics to educate on systematic approaches to preventing URFO in the operating room (OR) and utilizing root cause analysis to analyze the simulated sentinel event and highlight the new URFO policy. A survey was subsequently done at the one year interval to measure follow up retention of knowledge. Methods: The “baseline knowledge” and “knowledge retention” was assessed by pre (before simulation) and post (1 year) survey. Education on policy was conducted at the onset and six month interval with simulation incorporated in the latter. A multi-disciplinary team including residents, OR and anesthesia staff, designed and simulated a scenario with an emergency operation that is susceptible to URFO error. The Patient Safety Officer (PSO) gave a report that 5 days after abdominal closure a retained sponge was found on abdominal x-ray. A root cause analysis was then performed allowing the residents to verify the role of our new URFO policy on preventing such events (Figure 1). Results: Using a survey (n=62), the majority of trainees improved in recognizing crew resource management as the primary way of preventing a sentinel event during a simulation at one year follow-up (78.6% to 98.4%) (Figure 2). Retention had improved, with 91.3% correctly indicated that standardized method (debrief, closed loop, sponge counting) were a better check than varying practices for preventing URFOs. The trainees correctly indicated (93.5%) from baseline of 75% that “finding the individual responsible for the mistake” was not the goal, and 91.9% correctly identified the primary focus of the root cause analysis of this scenario was failure in “system design.” However only 71% of trainees at one year indicated confidence in their understanding of the URFO policy and could assist others in performing URFO-related roles. Conclusions: Simulation can be integrated into the residency curriculum as an adjunct to increase retention in teaching safety policy. The trainees were given the opportunity to learn the concept of root cause analysis and identify factors that lead to URFO. Simulation is a methodology that needs to be explored further to develop a framework for a patient safety curriculum in graduate medical education. (Figure Presented).
Keywords: follow up; gastrointestinal disease; simulation; policy; human; student; root cause analysis; patient safety; sentinel event; curriculum; methodology; safety; teaching; operating room; resource management; emergency; incision; emergency surgery; error; education; medical education; community hospital; risk; graduate; bleeding; anesthesia; abdominal radiography

Back to Basics: Counting Soft Surgical Goods - Spruce, L. (AORN journal, 2016)
Retained surgical items (RSIs) pose serious consequences for patients and are a significant threat to patient safety. Perioperative team members are morally and ethically responsible for the prevention of RSIs and should understand how to reduce the risk of occurrence. The prevention of RSIs does not rest in the hands of one individual. It is a multidisciplinary endeavor that aims to reduce the risk of RSIs, and team members should hold each other accountable. This Back to Basics article focuses on the process of counting soft surgical goods, which are the most common RSIs.
Keywords: continuing education; foreign body; human; workforce; medical error; nursing organization; operating room; patient safety; prevention and control; surgical sponge

Negligence to nightmare: Gossypiboma - case reports - Patnaik, S. (Surgical Endoscopy and Other Interventional Techniques, 2016)
Introduction: GOSSYPIBOMA describes a mass within a patient's body comprising a cotton matrix surrounded by a foreign body granuloma due to retained pieces of gauze; is an infrequent surgical complication & serious surgical malpractice resulting from negligence. Either detected early due an exudative inflammatory reaction with the formation of an abscess or can present late as a mass due to aseptic fibrotic reaction to the cotton material. Case Report: First case was that of a 45 year old male presenting with pain abdomen & vomiting after an open cholecystectomy done 2 months back and on laparotomy a surgical sponge was retrieved from jejunal lumen. Second is a female patient 45 yr old who had fever and purulent discharge P/V 3 months after a vaginal hysterectomy and a gauze was found in the POD on opening the vaginal vault. Third was also a female 36 year old with pain in epigastrium, vomiting & occasional rise of temperature, following open cholecystectomy 3months back. After endoscopic confirmation of a foreign body a square size surgical sponge was removed from the duodenum via laparotomy. The fourth one being the most interesting one where a 29 yr old female after a LSCS for a twin pregnancy complained of mild lower abdominal pain and constipation and while she had been planned for a cholecystectomy and repair of a divarication of recti, an accidental injury to the small bowel during first umbilical trochar entry led to discovery of a surgical sponge in the bowel lumen partially obstructing it. Discussion: Despite all considerations during operation the incidence of retained foreign bodies following surgery has a reported rate of 0.01% to 0.001%, of which gossypibomas make up 70-80%; only a third being correctly diagnosed. Symptoms either relate to recurrence, occlusion or septic changes. With an infrequent incidence & frequent misdiagnosis, this surgical malpractice is easily avoidable by mere watchfulness of the surgeon and rest of the OT staff. Simply keeping the sponge count and thorough exploration of the operative field before & after the procedures and use of surgical textiles impregnated with radiological markers would not only spare the patient of unnecessary morbidity but also the surgeon of serious medicolegal consequences. Conclusion: Though a rarity it must be suspected in every post operative case presenting with pain, obstruction etc. once confirmed gossypiboma is best removed by open surgery though laparoscopic and percutaneous removal has been reported in few selected cases.
Keywords: marker; human; nightmare; surgeon; society; case report; American; negligence; surgical sponge; pain; cholecystectomy; patient; female; malpractice; vomiting; cotton; surgery; laparotomy; foreign body; postoperative complication; fever; morbidity; vaginal hysterectomy; textile; procedures; diagnostic error; foreign body granuloma; occlusion; intestine; small intestine; accidental injury; constipation; abdomen; lower abdominal pain; twin pregnancy; abscess; duodenum; temperature; inflammation; male; obstruction

Unintentionally retained foreign bodies after surgical procedures. Analysis of 4547 cases - Birolini, D.V.; Rasslan, S.; Utiyama, E.M. (Revista do Colegio Brasileiro de Cirurgioes, 2016)
METHODS: A questionnaire was sent to surgeons by electronic mail, between March and July 2012. The questions analyzed their experience with foreign bodies (FB), foreign bodies' types, clinical manifestations, diagnoses, risk factors and legal implications. RESULTS: in the 2872 eligible questionnaires, 43% of the surgeons asserted that they had already left FB and 73% had removed FB in one or more occasions, totalizing 4547. Of these foreign bodies, 90% were textiles, 78% were discovered in the first year and 14% remained asymptomatic. Among doctors with less than five years after graduation, 36% had already left a FB. The most frequently surgical procedures mentioned were the elective (57%) and routine (85%) ones. Emergency (26%), lack of counting (25%) and inadequate conditions of work contributed (12.5%) to the occurrence. In 46% of the cases patients were alerted about the FB, and 26% of them sued the doctors or the institution. CONCLUSIONS: challenging medical situations, omission of security protocols and inadequate work conditions contributed to RFB. However, RFB occurs mostly in routine procedures such as cesarean or cholecystectomy, and at the beginning of the professional career, highlighting, particularly in poorest countries, the need for primary prevention. Textiles predominated causing clinical repercussions and they were diagnosed in the first postoperative months. Surgeons were sued in 11.3% of the RFB cases. OBJECTIVE: this study aims to explore the experience of Brazilian surgeons on Unintentionally Retained Foreign Bodies (RFB) after surgical procedures.
Keywords: Brazil; cross-sectional study; foreign body; human; self report; surgery

Gossypiboma mimicking a mesenchymal tumor: A report of a rare case - Eken, H.; Soyturk, M.; Balci, G.; Firat, D.; Cimen, O.; Karakose, O.; Somuncu, E. (American Journal of Case Reports, 2016)
Objective: Challenging differential diagnosis Background: Gossypiboma is the term for a surgical complication resulting from foreign materials such as a surgical sponge or gauze that was accidentally left inside a patient’s body. Case Report: Here, we report the case of a 62-year-old woman with gossypiboma. She underwent surgery due to an abdominal mass that was preoperatively considered a tumor. Intra-postoperatively, it was diagnosed as gossypiboma. Conclusions: For the prevention of gossypiboma during the pre-operative and post-operative periods, counting sponges and surgical equipment must be done very carefully. If there is any doubt postoperatively, direct abdominal imaging may be helpful.
Keywords: contrast medium; abdominal mass; abdominal tenderness; adult; article; case report; clinical feature; computer assisted tomography; constipation; diagnostic error; diagnostic imaging; female; gossypiboma; human; human tissue; laparotomy; middle aged; myomectomy; nuclear magnetic resonance imaging; peritoneum adhesion; postoperative complication; preoperative period; stomach distension; stomach pain

Outcomes of retinal detachment repair after posterior open globe injury - Reed, D.C.; Juhn, A.T.; Rayess, N.; Hsu, J.; Chiang, A. (Retina, 2016)
Purpose: To report outcomes of retinal detachment (RD) repair following posterior open globe injury. Methods: This retrospective, consecutive case series examined patients who underwent RD repair following Zone II and/or III open globe injury repair between January 1, 2007 and October 31, 2013. Patients with<3 months of follow-up since their last vitreoretinal surgery, and those who underwent pars plana vitrectomy (e.g., for intraocular foreign body) during their initial open globe injury repair were excluded. Results: Of 30 patients who met inclusion criteria, reattachment of the retina was achieved in 25 (83%) during the first vitreoretinal surgical procedure and 5 (17%) were deemed inoperable intraoperatively. Ten patients (30%) developed recurrent RD, and 8 underwent additional surgery. At last follow-up, reattachment was observed in 4 of these 8. The overall rate of final reattachment was 63% (19 patients). The mean number of surgeries for RD was 1.5 (range, 1-3). Fifteen patients (50%) achieved final visual acuity of counting fingers or better. Mean follow-up from the last vitreoretinal surgery was 23 months (range, 3-52). Conclusion: Although RD following posterior open globe injury confers a grave prognosis, successful anatomic reattachment of the retina was achieved in the majority of patients in this series, with half achieving ambulatory vision.
Keywords: balanced salt solution; silicone oil; adolescent; adult; aged; article; child; clinical article; eye injury; female; follow up; human; intraocular pressure; laceration; male; penetrating trauma; perforating eye injury; posterior open globe injury; prognosis; recurrent disease; retina detachment; retinopexy; retrospective study; treatment outcome; visual acuity; vitreoretinal surgery

Gossypiboma revisited: A never ending issue - Rabie, M.E.; Hosni, M.H.; Al Safty, A.; Al Jarallah, M.; Ghaleb, F.H. (International Journal of Surgery Case Reports, 2016)
Introduction Leaving a surgical item inside the patient at the end of surgery, is one of the most dreadful complications. The item is frequently a surgical sponge and the resultant morbidity is usually severe. Additionally, the event poses considerable psychic strain to the operating team, notably the surgeon. Presentation of cases Here we describe the clinical course of three patients in whom a surgical sponge was missed, despite a seemingly correct count at the end of difficult caesarean sections. In two patients, who presented shortly after surgery, the pad was extracted with no bowel resection. In the third patient, who presented several years after surgery, colectomy was performed. Discussion Gossypiboma is under reported and the true incidence is largely unknown. Depending on the body reaction and the characters of the retained sponge, the patient may present within months to years after surgery. Risk factors for retained foreign objects include emergency surgery, an unplanned change in the surgical procedure, higher body mass index, multiple surgical teams, greater number of major procedures done at the same time and incorrect count recording. The surgical procedure needed to extract the retained sponge may be a simple one, as in the first case, or it may be more complex, as seen in the other two cases. Although holding the correct count at the end of surgery is the gold standard safeguard against this mishap, human errors continue to occur, as happened in our patients. For that reason, the correct count should be supplemented by employing one of the several new technologies currently available. Conclusion Gossypiboma continues to occur, despite precautionary measures. As its consequences might cost the patient his life and the surgeon his professional reputation, extra preventive measures should be sought and implemented. New advances in technology should be incorporated in the theatre protocol as additional safeguard against human error. When encountered, a direct incision over the encapsulated swelling, in contrast to a formal laparotomy incision, might simplify the surgical procedure.
Keywords: surgical sponge; adult; article; body mass; case report; cesarean section; colon resection; computer assisted tomography; disease course; emergency surgery; female; follow up; foreign body; gossypiboma; human; hysterectomy; laparotomy; middle aged; priority journal; risk factor; suction drainage; surgical sponge

The role of radio frequency detection system embedded surgical sponges in preventing retained surgical sponges: A prospective evaluation in patients undergoing emergency surgery - Inaba, K.; Okoye, O.; Aksoy, H.; Skiada, D.; Ault, G.; Sener, S.; Lam, L.; Benjamin, E.; Demetriades, D. (Annals of Surgery, 2016)
Objective: To prospectively evaluate the ability of radio frequency detection (RFD) system-embedded sponges to mitigate the incidence of retained surgical sponges (RSS) after emergency surgery. Background: Emergency surgery patients are at high risk for retained foreign bodies. Methods: All emergent trauma and nontrauma cavitary operations over a 5-year period (January 2010-December 2014) were prospectively enrolled. For damage-control procedures, only the definitive closure was included. RFD sponges were used exclusively throughout the study period. Before closure, the sponge and instrument count was followed by RFD scanning and x-ray evaluation for retained sponges. RSS and near-misses averted using the RFD system were analyzed. Results: In all, 2051 patients [median (range)], aged 41 (1-101) years, 72.2% male, 46.8% trauma patients, underwent 2148 operations (1824 laparotomy, 100 thoracotomy, 30 sternotomy, and 97 combined). RFD detected retained sponges in 11 (0.5%) patients (81.8%laparotomy, 18.2% sternotomy) before cavitary closure. All postclosure x-rays were negative. No retained sponges were missed by the RFD system. Body mass index was 29 (23-43), estimated blood loss 1.0L (0-23), and operating room time 160 minutes (71-869). Procedures started after 18:00 to 06:00 hours in 45.5% of the patients. The sponge count was incorrect in 36.4%, not performed due to time constraints in 45.5%, and correct in 18.2%. The additional cost of using RFD-embedded disposables was $0.17 for a 4X18 laparotomy sponge and $0.46 for a 10 pack of 12ply, 4X8. Conclusions: Emergent surgical procedures are high-risk for retained sponges, even when sponge counts are performed and found to be correct. Implementation of a RFD system was effective in preventing this complication and should be considered for emergent operations in an effort to improve patient safety.
Keywords: adolescent; adult; aged; child; conference paper; emergency surgery; female; foreign body; human; injury; laparotomy; major clinical study; male; observational study; patient safety; priority journal; prospective study; radio frequency identification device; sternotomy; surgical patient; surgical sponge; thoracotomy; very elderly; X ray

Surgical sponge forgotten for nine years in the abdomen: A case report - Susmallian, S.; Raskin, B.; Barnea, R. (International Journal of Surgery Case Reports, 2016)
Introduction Retained surgical sponge or other items in patients’ bodies happens more frequently than is reported. Healthcare personnel can forget to remove textile material or instruments during complicated, extended, or emergency surgery. In addition, changes in the operating team can influence the occurrence of such errors. Presentation of case We present a case with a symptomatic gossypiboma nine years after a previous cesarean section. A 34-year-old woman was admitted to the emergency room having experienced abdominal pain and fever for the previous month. An abdominal computed tomography revealed an abscess in the lower abdomen. A laparotomy was performed, and a resection and block were carried out. A surgical sponge was extracted from an omental abscess. Discussion Surgical sponges are the most common foreign materials retained (70%) in the abdominal cavity because of their frequent usage and small size. Moreover, a blood-soaked sponge in a hemorrhagic abdomen can be difficult to distinguish from blood. Conclusion Whenever the accounting for material depends on humans, mistakes will continue to be committed. A falsely correct sponge count was reported in 71.42% of cases [14]; therefore, a new count system must be developed for post-surgical situations.
Keywords: abdomen; abdominal abscess; abdominal pain; abdominal radiography; abdominal tenderness; abdominal tumor; adult; article; case report; cesarean section; computer assisted tomography; device removal; emergency ward; female; fever; foreign body; gossypiboma; human; laboratory test; laparotomy; pelvis abscess; peritoneum; physical examination; postoperative pain; priority journal; retained instrument; surgical infection; surgical sponge; surgical technique; tumor volume

Clinical curative effect comparison of pipe extractor of improved collar style and traditional foreign body forceps in the extubation of the double-J stent - Gu, J.; Zhang, Y.; Li, J.; Zhao, Q. (Journal of Endourology, 2016)
Introduction & Objective: To analyze the safety and efficacy of pipe extractor of improved collar style and traditional foreign body forceps in the extubation of the double-J stent. Materials and Methods: A total of 120 cases, who underwent extubated the double-J stent by urethral cystoscopy from September 2013 to August 2014, were randomly divided into two groups, 60 of which underwent pipe extractor of improved collar style and the other 60 patients underwent traditional foreign body forceps. The difference of operation time, the numeric rating scale (NRS) of operation, the numeric rating scale (NRS) of the 10 minutes after operation, the number of patients of gross hematuria after operation between the two groups were compared and analyzed. Results: The numeric rating scale (NRS) of operation, the numeric rating scale (NRS) of the 10 minutes after operation, the number of patients of gross hematuria, red blood cell count after operation of pipe extractor of improved collar style and traditional foreign body forceps were (4.9 ± 1.6) scores and (6.9 ± 0.9) scores, (1.7 ± 1.0) scores and (3.1 ± 0.7) scores, (41/60) (68.3%) and (51/60) (85.0%), (38.9 ± 13.7)/μl and (89.5 ± 26.6)/μl, respectively. There were statistical significance between the two groups (P < 0.05). The operation time was (65.1 ± 12.1) s and (63.6 ± 17.8) s, there was not statistical significance between the two groups (P > 0.05). Conclusions: Relative to the traditional foreign body forceps, the self-designed pipe extractor of improved collar style in the extubation of the double-J stent is simple and little injury, which is worth to recommand its clinical use. (Figure presented).
Keywords: controlled clinical trial; controlled study; cystoscopy; double J stent; erythrocyte count; extubation; forceps; foreign body; hematuria; human; major clinical study; operation duration; randomized controlled trial; rating scale; statistical significance; urethra

Penetrating ocular trauma with retained intraocular foreign body: Management, follow-up and medico-legal evaluation - Sorrentino, S.; Marsella, L.T.; Feola, A.; Marino, V.; Billi, B. (West Indian Medical Journal, 2016)
Ocular trauma is the leading cause of acquired monocular blindness, accounting for 1.97-6% of such cases. Particularly, penetrating ocular injuries are among the most common eye injuries with this kind of outcome. Early diagnosis and prompt management are crucial to avoid complications, and the especially dreaded enucleation. In this article, the authors describe the clinical management, and evaluate the visual and anatomical results obtained in a case of ocular injury with retained intraocular foreign body (IOFB) in a 20-year old female patient. The course of treatment involved a combination of penetrating keratoplasty with a temporary keratoprosthesis, phacoemulsification with intraocular lens implantation and pars plana vitrectomy. At three years from the initial injury, the patient was able to count fingers at 30 centimetres and anatomical restitutio ad integrum of the globe had been achieved.
Keywords: Ahmed valve; keratoprosthesis; lens implant; vancomycin; adult; anterior eye chamber; anterior maxillary sinus fracture; article; case report; cataract; clavicle fracture; clinical article; clinical outcome; computer assisted tomography; conjunctival hyperemia; cornea edema; corticosteroid therapy; endotamponade; eye examination; eye injury; eye pain; female; follow up; glaucoma; graft rejection; human; intraocular foreign body; intraocular pressure; lacrimation; medicolegal aspect; orbit fracture; outpatient care; paranasal sinus disease; penetrating keratoplasty; phacoemulsification; photophobia; slit lamp microscopy; traffic accident; visual acuity; young adult

Retained Foreign Body: "Needle in a Haystack" - O'Brien, L.; Eyster, K.M.; Hansen, K.A. (Journal of patient safety, 2015)
Retained foreign bodies remain an area of potential patient harm. This case describes a retained needle from distant surgery discovered at the time of the needle count after myomectomy.
Keywords: adult; case report; female; foreign body; general surgery; human; medical error; mortality; needle; risk factor; statistics and numerical data; surgical equipment

Inattention blindness in surgery - Hughes-Hallett, A.; Mayer, E.K.; Marcus, H.J.; Pratt, P.; Mason, S.; Darzi, A.W.; Vale, J.A. (Surgical Endoscopy, 2015)
Background: Inattention blindness (IB) can be defined as the failure to perceive an unexpected object when attention is focussed on another object or task. The principal aim of this study was to determine the effect of cognitive load and surgical image guidance on operative IB. Methods: Using a randomised control study design, participants were allocated to a high or low cognitive load group and subsequently to one of three augmented reality (AR) image guidance groups (no guidance, wireframe overlay and solid overlay). Randomised participants watched a segment of video from a robotic partial nephrectomy. Those in the high cognitive load groups were asked to keep a count of instrument movements, while those in the low cognitive load groups were only asked to watch the video. Two foreign bodies were visible within the operative scene: a swab, within the periphery of vision; and a suture, in the centre of the operative scene. Once the participants had finished watching the video, they were asked to report whether they had observed a swab or suture. Results: The overall level of prompted inattention blindness was 74 and 10 % for the swab and suture, respectively. Significantly higher levels of IB for the swab were seen in the high versus the low cognitive load groups, but not for the suture (8 vs. 47 %, p < 0.001 and 90 vs. 91 %, p = 1.000, for swab and suture, respectively). No significant difference was seen between image guidance groups for attention of the swab or suture (29 vs. 20 %, p = 0.520 and 22 vs. 22 %, p = 1.000, respectively). Conclusions: The overall effect of IB on operative practice appeared to be significant, within the context of this study. When examining for the effects of AR image guidance and cognitive load on IB, only the latter was found to have significance.
Keywords: article; attention; blindness; clinical article; controlled study; foreign body; human; inattention blindness; partial nephrectomy; priority journal; randomized controlled trial; surgical swab; suture; videorecording; vision

Endovascular embolization for managing anastomotic bleeding after stapled digestive tract anastomosis - Li, T.-F.; Duan, X.-H.; Li, Z.H.E.N.; Ren, J.-Z.; Zhang, K.A.I.; Huang, G.-H.; Han, X.-W.; Jiao, D.-C.; Zhang, M.-F. (Acta Radiologica, 2015)
Background Anastomotic bleeding is an infrequent but life-threatening complication after stapled digestive tract anastomosis. Endovascular embolization is one of the available treatments, but precise clinical outcomes are yet to be evaluated. Purpose To evaluate the efficacy and safety of endovascular embolization for managing anastomotic bleeding after stapled digestive tract anastomosis. Material and Methods Twenty-eight patients were diagnosed with anastomotic bleeding after stapled digestive tract anastomosis by digital subtraction angiography (DSA). Curative effect was summed for analysis. Results All bleeding arteries were located in the stoma and were identified by contrast agent spillover by DSA. The offending arteries were superselectively catheterized and embolized with microcoils and/or gelatin sponge particles. Laboratory examinations showed normal hemoglobin and red blood cell counts when the patients' abdominal cavity drainage tubes stopped draining blood. The follow-up period was 3.2-84.7 months (median, 19.7 months). Four patients died during this time, of which two had cholangiocarcinoma, one had gastric cancer with tumor recurrence and multiple organ failure, and the final patient had a subarachnoid hemorrhage 4 months after embolization. In the surviving patients, no rebleeding occurred after embolization and no additional intervention or surgery was required. Conclusion Endovascular embolization is safe and effective for managing anastomotic bleeding after stapled digestive tract anastomosis.
Keywords: epinephrine; adult; aged; anastomosis; anastomosis bleeding; arteriography; artery catheterization; article; artificial embolization; clinical article; clinical effectiveness; controlled study; digital subtraction angiography; embolization coil; endovascular embolization; feasibility study; female; gastric artery; gastroduodenal artery; gastroscopy; human; image analysis; intestine endoscopy; male; microcoil; patient safety; postoperative complication; priority journal; stapled digestive tract anastomosis; superior mesenteric artery; surgical sponge

The Hidden Costs of Reconciling Surgical Sponge Counts - Steelman, V.M.; Schaapveld, A.G.; Perkhounkova, Y.; Storm, H.E.; Mathias, M. (AORN journal, 2015)
Retained surgical sponges are serious adverse events that can result in negative patient outcomes. The primary method of prevention is the sponge count. Searching for sponges to reconcile counts can result in inefficient use of OR time. The purpose of this descriptive study was to estimate the cost of nonproductive OR time (ie, time spent not moving forward with the surgical procedure) spent reconciling surgical sponge counts and the cost of using radiography to rule out the presence of retained sponges. We included 13,322 patient surgeries during a nine-month period. Perioperative personnel required from one to 90 minutes of additional time to reconcile each of 212 incorrect/unresolved counts. The total annualized cost of OR time spent searching for sponges and ruling out the presence of potentially retained sponges using radiography was $219,056. These costs should be included in comprehensive cost analyses when considering alternatives to supplement the surgical count.
Keywords: economics; foreign body; health care cost; human; medical error; surgical sponge

Intracranial abscess due to endobronchial foreign body in an adult - Beesley, S.J.; Timm, J.; Swaminathan, S.; Elstad, M.R. (American Journal of Respiratory and Critical Care Medicine, 2015)
Introduction Endobronchial foreign bodies have been occasionally reported to cause pediatric brain abscesses. We present the unusual case of an adult with brain abscess caused by an occult endobronchial foreign body. Case Report A 43 year old man presented with 1 month of fever and headaches worsening over 2 days prior to presentation. He also noted 4-5 days of nausea, vomiting, sore throat and cough. His past medical history was significant for post-traumatic stress disorder, anxiety, depression and substance abuse. Home medications included suboxone, fluoxetine, prazosin and trazodone. Physical exam on presentation showed fever (101.3F) but was otherwise normal. Lumbar puncture revealed white blood cell count 5742 (93% neutrophils, 2% lymphocytes, 4% monocytes), no red blood cells, protein 259 mg/dl and glucose 18 mg/dl. Cultures of the blood and CSF were negative. MRI brain showed a 1.8 cm abscess in the temporal lobe with rupture into the ventricle (Figure 1A). Chest CT, performed to characterize a subtle left lower lobe opacity on CXR, showed an abnormality at the carina (Figure 1B). Flexible bronchoscopy revealed a foreign body at the carina extending into the right mainstem bronchus with significant purulent secretions and granulation tissue (Figure 1C). A dental bridge was removed using foreign body forceps (Figure 1D). (Figure Presented) Further history revealed that his current dental bridge was replacement for one that had been “lost” 1 year prior to presentation. He denied any recollection of this aspiration event. The patient was diagnosed with brain abscess and bacterial meningitis secondary to an occult chronic endobronchial foreign body. His symptoms resolved, and he was discharged on antibiotics. Discussion Brain abscess is uncommon in adults and usually develops through hematogenous spread or from a contiguous source. Pulmonary sources (chronic lung abscess, empyema or bronchiectasis) are implicated in less than 10% of cases. Foreign body aspiration leading to brain abscess is rare, with only a handful of case-reports primarily in the pediatric literature. It has been proposed that sharp objects in the airway penetrate the mucosal barrier and allow infiltration of bacteria into the pulmonary circulation with hematogenous spread to the brain. Flexible bronchoscopy may be used for airway inspection and initial attempts at removal of foreign bodies. However, had we known the nature of this object (large dental bridge), we would have opted to perform rigid bronchoscopy. Pulmonary sources, including foreign body aspiration, should be investigated in cases of brain abscess with an unknown cause.
Keywords: buprenorphine plus naloxone; trazodone; prazosin; glucose; fluoxetine; protein; antibiotic agent; brain abscess; foreign body; adult; American; society; human; dental bridge; bronchoscopy; case report; fever; foreign body aspiration; airway; brain; nausea; lymphocyte; anxiety; lumbar puncture; neutrophil; substance abuse; drug therapy; headache; posttraumatic stress disorder; medical history; coughing; sore throat; granulation tissue; bacterial meningitis; leukocyte count; lung abscess; lung circulation; male; monocyte; vomiting; blood; abscess; temporal lobe; rupture; thorax; erythrocyte; bronchus; suppuration; forceps; aspiration; patient; empyema; bronchiectasis; bacterium; nuclear magnetic resonance imaging; cerebrospinal fluid

Ingestion of multiple batteries: A case report - Tejada, J.; Campo, L.; Culliford, A.; Babich, J.P. (American Journal of Gastroenterology, 2015)
Introduction: Single foreign body ingestion is a scenario that gastroenterologists commonly see. However, multiple foreign body ingestion provides the endoscopist with significant challenges in management. We describe a case of ingestion of sixteen AA batteries that successfully passed the gastrointestinal track with conservative management after endoscopic attempt at removal. Case: 32-year-old female with history of schizoaffective disorder, presented with epigastric pain after ingested sixteen AA batteries in a suicide attempt. Patient underwent upper endoscopy with successful retrieval of 2 batteries. The other fourteen batteries had already passed beyond the ligament of Treitz. Surgical management was not indicated. Patient was kept NPO during the first two days, with intravenous fluid, proton-pump inhibitors and stool softener. Since abdominal pain improved, diet was advanced to clear liquids. During the hospital course, electrolytes, white blood cell count and kidney function remained stable. Daily abdominal x-rays were performed to monitor progression. After multiple failed oral therapy attempts, a nasogastric tube was placed to guarantee compliance with laxatives. After therapy with rapid colonoscopy preparation protocol, the patient successfully passed the remaining 14 batteries without complications at day 8. Discussion: Ingestion and/or insertion of foreign objects is seen in young, alcoholic or psychiatric patients. The incidence has not been established, but in a study between 2000 and 2006, in a urban hospital among 262 cases, 92% were intentional ingestion, 85% involved psychiatric patients, and 84% had history of prior ingestion. The dilemma is whether to allow the foreign body to pass spontaneous or to remove either endoscopically or surgically. Endoscopic approaches are recommended, especially for objects wider than 2.5 cm because they are less likely to pass the pylorus, although limited data exists to support this recommendation. Objects that fail to pass beyond the stomach by 3 to 4 weeks should be removed endoscopically to prevent obstruction. In this case evidence of progression throughout the gastrointestinal track was proved by daily abdominal x-ray without clinical deterioration. Successfully expulsion of the objects without further endoscopic intervention was possible. (Figure Presented).
Keywords: infusion fluid; proton pump inhibitor; electrolyte; laxative; human; case report; American; college; gastroenterology; ingestion; foreign body; patient; hospital; mental patient; therapy; gastroenterologist; abdominal pain; schizoaffective psychosis; epigastric pain; female; alcoholism; surgery; conservative treatment; diet; liquid; ligament; leukocyte count; kidney function; endoscopy; nasogastric tube; colonoscopy; suicide attempt; endoscopist; pylorus; stomach; obstruction; deterioration; abdominal radiography

Food bolus impaction in children is nearly always from eosinophilic oesophagitis - Bradley, T.; Withers, G.; Ee, L. (Journal of Gastroenterology and Hepatology (Australia), 2015)
Introduction: Eosinophilic oesophagitis (EoE) is a chronic, immunemediated oesophageal disease characterized clinically by symptoms related to esophageal dysfunction and histologically by eosinophilpredominant inflammation.1 Incidence and prevalence of this condition is increasing.2 The presentation of EoE varies with age but dysphagia is common in adults and older children.3 We hypothesize that most children requiring endoscopic management of food bolus impaction will have EoE. Methods: Retrospective review of all patients presenting or referred with food bolus impaction to a paediatric hospital between 1st Nov 2011 and 31st Dec 2014 inclusive. ICD-10 codes for endoscopy and removal of foreign body (30478-00, 30478-10) were used to identify patients who required endoscopy. All patients with oesophageal foreign bodies were reviewed but only those with food in the oesophagus were included in the study. EoE was defined as the presence of ≥15 eosinophils/high power field on biopsy in either proximal and/or distal oesophagus.4 Results: 138 endoscopies were performed in 133 children. Oesophageal foreign bodies were noted in 78 procedures of which 76 were performed emergently. Procedures were mainly performed by gastroenterologists (n = 50) and otolaryngologists (n = 23). Common foreign bodies include coins (n = 33), food (n = 22), button battery (n = 3), dental wire (n = 3), and toys (n = 3). 22 endoscopies were performed in 19 patients for food bolus impaction, and histology available in 14/19 (74%) patients. 79% (15/19) of these patients were male and median age at presentation was 12.08 (range 0.85-15.05) years. 79% (11/14) of those biopsied fulfilled histologic criteria for EoE. Interestingly the remaining 3 patients who had biopsies all demonstrated oesophageal eosinophilia although their count (range 3-13 eos/hpf) was insufficient to be diagnostic of EoE. 2/5 patients who did not have biopsies were known to have an oesophageal stricture after previous surgery. Most children presenting with food bolus impaction therefore had underlying oesophageal pathology. Conclusions: Food bolus impaction in children is nearly always a consequence of underlying oesophageal disorder, of which EoE is the most common. We recommend that all children presenting with food bolus impaction have oesophageal biopsies for EoE.
Keywords: child; human; eosinophilic esophagitis; Australian; gastroenterology; food; patient; endoscopy; biopsy; esophagus foreign body; esophagus; procedures; foreign body; prevalence; gastroenterologist; ICD-10; esophagus biopsy; otolaryngologist; pathology; patient history of surgery; esophagus stenosis; pediatric hospital; diagnosis; eosinophilia; histology; male; dental wire; diseases; electric battery; adult; dysphagia; inflammation; esophagus disease

Bacterial endophthalmitis associated with a broken and retained small-gauge vitrectomy cannula - Wong, R.W. (Retinal Cases and Brief Reports, 2015)
Purpose: To report a case of bacterial endophthalmitis associated with a retained smallgauge vitrectomy trocar. Methods: Retrospective case report of a 66-year-old woman who underwent 25-gauge vitrectomy surgery for an epiretinal membrane who presented with postoperative bacterial endophthalmitis and hand motions vision 3 weeks later. Results: Aqueous and vitreous biopsy revealed Corynebacterium species sensitive to vancomycin. The patient was initially treated with intravitreal and subconjunctival injections of vancomycin, ceftazidime, and dexamethasone. Surgical exploration during a subsequent vitrectomy surgery revealed a retained, transscleral 25-gauge cannula beneath a subconjunctival abscess. The cannula was removed, and the patient was treated with vitrectomy, debridement and closure of the transscleral wound, and injection of intravitreal antibiotics. Fifteen months of follow-up revealed no recurrence of infection and improvement of vision to 20/150. Conclusion: Although rare, retained small-gauge vitrectomy cannulas may lead to vision threatening ocular infection. Care should be taken to inspect both the wound and the removed trocar system to ensure complete removal of this surgical device. Detailed counts of all surgical equipment should be routinely performed at the conclusion of vitrectomy surgery. © 2015 by Ophthalmic Communications Society, Inc.
Keywords: cannula; trocar; vitrectomy cannula; ceftazidime; dexamethasone; vancomycin; abscess; aged; article; bacterial endophthalmitis; bacterium detection; cannula; case report; Corynebacterium; debridement; device removal; diabetic retinopathy; endophthalmitis; epiretinal membrane; eye examination; female; foreign body; human; human tissue; laser coagulation; nonhuman; retrospective study; trocar; visual acuity; vitrectomy; vitrectomy cannula; vitreous biopsy

Interpretation of 18F-fluorodeoxyglucose uptake by arterial grafts in patients with large vessel vasculitis-a conundrum - Youngstein, T.; Mukherjee, J.; Tombetti, E.; Humphreys, E.; Nash, J.; Andrews, J.; Mason, J.C. (Annals of the Rheumatic Diseases, 2015)
Background: 18F-Fluorodeoxyglucose positron emission computerised tomography (FDG-PET-CT) is commonly used to aid the diagnosis of large vessel vasculitis (LVV). Its precise role and sensitivity during follow-up of LVV remains to be defined, and use is typically restricted to investigation of an unexplained acute phase response. We have encountered an additional limitation in LVV patients with synthetic arterial grafts, namely interpretation of FDG uptake confined to the graft. This is typically reported as vasculitic activity or infection, even in the absence of supportive clinical data. Objectives: To investigate non-specific uptake of FDG by synthetic arterial grafts in LVV. Methods: Twelve patients with FDG-uptake localised to arterial grafts were identified, 10 with LVV, and 2 with non-inflammatory aortopathy. The maximum standardised uptake values (SUV) for the grafts were quantified. The intensity of uptake by each graft and the native aorta was scored against constitutive hepatic uptake. Time after surgery, C-reactive protein, and infection screen results were obtained. Disease progression was estimated by magnetic resonance angiography (MRA). Results: Twelve patients (10 female, mean age 41.4 yrs, range 23-60) who had undergone graft surgery and FDG-PET scanning were identified, 8 with Takayasu arteritis (TA), 2 giant cell aortitis, 1 Marfan's syndrome and 1 non-inflammatory aortic wall degeneration (Table). The index case (patient 1) presented with fatigue 2 years post-surgery. An FDG-PET-CT demonstrated increased FDG uptake specifically localised to the graft site, raising concerns regarding active LVV or graft infection. However, blood indices including leukocyte count and acute phase reactants were normal, and repeat blood cultures revealed no infection. Study of nine other LVV patients revealed directly comparable findings (Table). The 2 patients with non-inflammatory disease also demonstrated significant uptake in aortic grafts, with no identifiable cause. The mean time post-surgery to first scan was 40 months (range 6-90). The mean maximum SUV of the grafts was (4.29±1.22). The uptake score in the grafts and native aorta relative to the liver were 2.83±0.39 versus 0.42±0.67 respectively (p<0.001). The CRP was not raised (mean ± SD 5.95±4.82, NR<10 mg/L), no infections were identified. Eight patients had repeat FDG-PET-CT scans with similar graft specific uptake identified. In 9 patients treatment was left unchanged. In 2 cases immunosuppression was increased and one received antibiotics, both without any change in FDG uptake. In those with LVV, immunosuppression has been subsequently weaned/withdrawn in all cases with no disease progression at 76.5 months (range 9-180). Conclusions: Although FDG-PET-CT scanning has proved useful for the diagnosis of active LVV, its role in the follow-up of patients on treatment remains undecided. FDG uptake confined to synthetic graft sites in LVV does not necessarily equate to infection or active vasculitis requiring treatment escalation. (Table Presented ) Uptake may represent a macrophage-driven foreign body reaction to the graft. Scans need to be interpreted cautiously and in conjunction with other clinical indices.
Keywords: fluorodeoxyglucose f 18; C reactive protein; acute phase protein; antibiotic agent; contact lens solution; European; artery graft; human; patient; vasculitis; rheumatology; rheumatic disease; infection; surgery; computer assisted tomography; immunosuppressive treatment; aorta; follow up; diagnosis; disease course; blood culture; leukocyte count; blood; graft infection; fatigue; degeneration; clinical study; positron; aortic wall; aortitis; acute phase response; female; aortic arch syndrome; giant cell; macrophage; positron emission tomography; magnetic resonance angiography; liver; aortic graft; foreign body reaction; inflammatory disease; Marfan syndrome

Large pelvic gossypiboma diagnosed at the time of radical prostatectomy 30 years after inguinal hernioplasty - Siena, G.; Campi, R.; Mari, A.; Minervini, A.; Carini, M.; Lapini, A.; Serni, S. (Anticancer Research, 2015)
Case Report: A 71-year-old man was referred to our centre for obstructive lower urinary tract symptoms (LUTS) and history of a vague, chronic discomfort in the right groin and testis since many years. Prostate-specific antigen (PSA) level was 12 ng/dl. The diagnostic work up revealed a Gleason score 4+4=8 adenocarcinoma of the prostate. No bone metastases were present. At the preoperative computed tomography (CT) scan, there was no evidence of pathologic pelvic lymph nodes on the left side of the pelvis, while a 3.0×5.0 cm solid mass of unknown nature was found close to the right iliac vessels (Figure 1). The central area was dishomogeneous as due to necrotic tissue; in turn, the peripheral, hypodense crown contained several hyperdense spots. The densitometric aspect of the prostate was highly irregular. The patient was then scheduled for open radical prostatectomy and extended pelvic lymph node dissection (ePLND). During the right lymph node dissection, a solid mass, firmly adherent to the right iliac vessels, was carefully isolated and removed intact. The intraoperative examination revealed a retained surgical sponge with a peripheral fibrous pseudocapsule resulting from an inflammatory foreign-body reaction, known in literature as gossypiboma or textiloma (Figure 2) (1). Indeed, the patient underwent emergency surgery for incarcerated inguinal hernia 30 years before. Discussion and Conclusion: Although more infrequent with standardized surgical counting (2), gossypibomas can still be either asymptomatic occasional findings or, if not promptly diagnosed, life threatening causes of intestinal obstruction and acute abdomen. Moreover, they can simulate intra-abdominal gastrointestinal stromal tumors making the differential diagnosis challenging. The problem of retained surgical items affects both open and minimally invasive surgery (3). Prevention is a key aspect to ensure the maximal safety of surgical patients. (Figure Presented).
Keywords: prostate specific antigen; prostatectomy; hernioplasty; society; oncology; pelvis; human; male; lymph node dissection; pelvis lymph node; patient; solid; prostate; bone metastasis; testis; Gleason score; case report; intestine obstruction; adenocarcinoma; differential diagnosis; minimally invasive surgery; safety; computer assisted tomography; examination; diagnosis; inguinal region; tissues; surgical sponge; foreign body reaction; emergency surgery; inguinal hernia; acute abdomen; gastrointestinal stromal tumor; lower urinary tract symptom; prevention; surgical patient

A rare complication of ethyl acetate poisoning - Chen, C.K. (Clinical Toxicology, 2015)
Objective: Ethyl acetate poisoning is rarely reported and is of low toxicity. Mucosal irritation and central nervous system (CNS) depression in high concentration is most commonly described. We present a case of ethyl acetate poisoning in a patient who required surgery due to foreign body formation. Case report: A 57-year-old female presented to the emergency department (ED) after a suicide attempt with ethyl acetate ingestion (about 200 mL) thirty minutes earlier. The initial vital signs were all within normal ranges and the initial symptom was vomiting. No nasogastic (NG) tube irrigation or activated charcoal were given due to low toxicity. The initial laboratory data including complete blood count, differential count, creatinine, sodium, potassium, and alanine transaminase were all within normal range. However, the patient became drowsy with respiratory distress due to stridor one hour after arrival. Emergency intubation was then performed for airway protection and desaturation followed by NG insertion for decompression. She was then admitted to intensive care unit. She was extubated 4 days later in a stable condition but during attempted removal it became clear that her NG tube was stuck in the stomach. Panendoscopy (PES) was then performed and showed a gastric foreign body attached to NG tube with hard content. The foreign body could not be removed via PES. Surgical intervention for foreign body removal was performed the next day. The patient recovered well after surgery and was discharged after 14 days in hospital. We then did a small experiment and put both a polyvinylchloride (PVC) NG tube and a silicon NG tube in ethyl acetate solution. Six hours later, the PVC NG tube was dissolved and the silicon NG was intact. When we mixed ethyl acetate with hydrochloric acid to mimic the gastric environment, some suspended solid materials formed and attached to NG tube. Conclusion: Ethyl acetate is of low toxicity with few cases reported; however, it can lead to formation of a hard solid foreign body in the stomach and cause obstruction. In addition, PVC NG tubing can dissolve in ethyl acetate solution. Hence, we recommend using silicon NG tubing for ethyl acetate ingestion if necessary.
Keywords: poison; acetic acid ethyl ester; silicon; polyvinylchloride; creatinine; hydrochloric acid; sodium; potassium; activated carbon; alanine aminotransferase; intoxication; European; nasogastric tube; foreign body; human; patient; toxicity; surgery; irrigation (agriculture); ingestion; stomach; vital sign; emergency ward; blood cell count; laboratory; suspended particulate matter; suicide attempt; intensive care unit; decompression; fatty acid desaturation; case report; protection; airway; tube; intubation; emergency; vomiting; stridor; hospital; respiratory distress; environment; solid; obstruction; female; central nervous system depression

Rectus fascia spiral sling (RFSS) technique for women with multiple failed stress incontinence surgery due to severe intrinsic sphincteric deficiency - Onol, F.F.; Onol, S.Y.; Gürbüz, M.C.; Tahra, A.; Küc¸ük, E.V. (Journal of Urology, 2015)
INTRODUCTION AND OBJECTIVES: Severe intrinsic sphincter deficiency (ISD) is a common cause of failed stress urinary incontinence (SUI) surgery. Management of women with multiple failed surgeries is particularly challenging, and these women are candidates for artificial sphincter implantation or continent urinary diversion. We present our experience with rectus fascia spiral sling (RFSS) in women with treatment-refractory ISD. METHODS: Four women (age: 19-64) underwent RFSS between 2011-2014. All women had severe incontinence with minimal activity or a slight change in body position. All had undergone multiple (range: 2-5) surgeries for SUI. Clinical evaluation included subjective assessment with ICIQ-SF questionnaire, pelvic physical examination, and urodynamic studies. All patients demonstrated marked ISD with a valsalva leak point pressure <60 cm H2O. The severity of SUI was evaluated by measuring the amount of urine leaked during a 24-h pad test and by counting the number of pads per day. A combined transvaginal+retropubic approach was utilized to remove all foreign material (permanent sutures and/or synthetic mesh) from previous surgeries and to completely dissect the urethra from the surrounding fibrosis. Using a right-angle clamp introduced from the anterior vaginal wall incision, the dorsal urethral plane was dissected with its tip advancing towards the contralateral side of the incision. The mid-urethra was thus mobilized circumferentially, followed by placement of a 8-10 cm × 1-1.5 cm rectus fascia sling around the mid-urethra in a tension-free manner. Urethral catheter was removed after 3-5 days. Postoperative visits were scheduled at 1, 3, 6, 12 months, and yearly thereafter. RESULTS: Bladder neck was entered in one patient during retropubic dissection. RFSS was completed without any consequence after primary repair. One patient received concomitant ileocystoplasty due to small-capacity (ie. 100 cc) bladder. No women developed urinary retention or voiding dysfunction necessitating intermittent catheterization. With a mean follow-up of 10 months (range: 3-24), SUI was cured in 2 (0-1 pad/day) and significantly improved in 2 women. Mean number of pads/ day decreased from 6.25 preoperatively to 1.25 postoperatively (p=0.03). Mean ICIQ-SF score decreased from 18.75±1.5 preoperatively to 6.5±2.5 postoperatively (p=0.01, Wilcoxon signed-rank test). CONCLUSIONS: RFSS is an effective option in women with treatment-refractory ISD, which may be considered before proceeding to more invasive treatment modalities.
Keywords: fascia; female; human; stress incontinence; surgery; American; urethra; patient; incision; ICIQ (incontinence); sphincter; patient history of surgery; foreign body; urinary diversion; aorta root prosthesis; follow up; Wilcoxon signed ranks test; invasive procedure; urine; suture; intermittent catheterization; urine retention; physical examination; pelvis; dissection; questionnaire; bladder neck; urethral catheter; bladder; clinical evaluation; clamp; fibrosis; body position; incontinence; implantation

Imaging findings of suspected retained surgical materials in postoperative pediatric patients; How can the radiologist become aware? - Ntoulia, A.; Kerwood, J.; Mahboubi, S. (Pediatric Radiology, 2015)
Purpose or Case Report: To become familiar with the radiographic appearance of the most common surgical materials intended for use during surgical procedures in children and identify the frequency of queries for missing or incorrect count of surgical materials in clinical practice. Methods & Materials: We performed in-vitro X-rays of surgical materials, including needles, sutures, sponges, cotton balls, and compresses, intended for use during pediatric surgical procedures. Additionally, during an 8-year-period (2005-2013) we retrospectively reviewed medical records of children who underwent surgery and intra- or post-operative imaging examinations for suspected retained surgical material(s). Results: Thirty-eight queries for suspected retained surgical materials were identified in 20 male and 18 female patients, mean age 7.6 years (range:5 days-24.5 years), who underwent abdominal (n=18), cardiothoracic (n=13), brain (n=1), head and neck (n=3), upper extremity (n=1), or complex (n=2) surgical procedures. Queries were for missing needle (n=29) or needle tip (n=2), missing sponge (n=4), missing forceps (n=1), and indeterminate incorrect count (n=2). In all cases portable x-rays were performed in the operating room and findings were correlated with in vitro obtained X-rays. Thirty-eight cases were negative for retained material, and in seven cases accurate localization of the material was provided to the surgical team, while the patient was still in the operating room. Conclusions: Awareness of the radiographic appearance of surgical materials commonly used in pediatric surgery, allows for correct diagnosis and appropriate management before the patient leaves the operating room, preventing potential complications. The providing history of incorrect count or missing of surgical materials increases radiologists' diagnostic suspicion.
Keywords: nitrogen 13; human; radiologist; radiology; society; patient; imaging; needle; surgical technique; operating room; X ray; in vitro study; child; diagnosis; pediatric surgery; forceps; neck; clinical practice; male; examination; surgery; medical record; brain; arm; cotton; plant leaf; suture; case report; female

Recurrent abscess due to retained appendicolith after laparoscopic appendectomy - Reyhani Calvo, A.; Martin Martin, E.; Cendoya Ansola, I.; Arteche Daubagna, E.; Gómez Portilla, A.; López De Heredia Armentia, E.; Magrach Barcenilla, L.A.; Palacios Bazan, E.E.; Ezurmendia Sinisterra, B.; Larrañaga Zabaleta, M.; Etxart Lopetegui, A. (Surgical Endoscopy and Other Interventional Techniques, 2015)
Introduction: Retained or dropped appendicolith is an uncommon complication that can occur as a consequence of stone expulsion from the appendix before or during appendectomy. This phenomenon is frequently associated with intra-abdominal abscess of variable locations; therefore, recognition of its presence is of great clinical significance in the care of patients with post appendectomy abscesses. Case Report: A 45-year-old woman underwent a laparoscopic appendectomy for perforated appendicitis. She was discharged asymptomatic on the 3rd postoperative day. She developed fever and epigastric abdominal pain 5 days later and she also had a white blood cell count of 13,000. Computed tomography (CT) showed a collection in epigastric region containing a small calcified stone; she was placed on IV antibiotics and underwent a CTguided percutaneous drainage. Despite this, 3 weeks after she was discharged asymptomatic the epigastric collection recurred. A new CT showed the persistence of the retained appendicolith and the abscess in the epigastric region. A small open laparotomy was performed, during which the abscess was drained and the appendicolith was removed. Conclusions: Laparoscopic appendectomy is complicated by postoperative abscess five times more frequently than open surgery. Retained appendicolith can cause abscess formation after surgery and can be a source of persistent infection. The abscess can appear within weeks or months after the initial appendectomy. A systematic division of the appendix performed between double ligature helps to avoid this postoperative complication. Removal of retained appendicolith is necessary because it may act as an infected foreign body, which cannot be sterilized by antibiotics or with simple drainage alone. Treatment options include open, percutaneous, or laparoscopic drainage of the abscess and retrieval of the appendicolith; Percutaneous drainage is commonly used to treat intra-abdominal abscess, but it is in some cases ineffective for retained appendicolith removal, requiring laparoscopic access or, using an open access as it was required in our case.
Keywords: antibiotic agent; endoscopic surgery; appendectomy; European; abscess; human; abdominal abscess; surgery; percutaneous drainage; persistent infection; appendix perforation; patient; computer assisted tomography; leukocyte count; abdominal pain; laparotomy; foreign body; postoperative complication; fever; case report; female

Sealing of the hepatic resection area using hemostat device does not result in furtherimproved results of adequate surgery but in induction of a detectable reactiveinflammatory response onto foreign material indicated by an enlarged drainagevolume and leucocytosis - Petersen, M.; Kropf, S.; Steinert, R.; Jannasch, O.; Venerito, M.; Meissner, C.; Frank, M. (Gastroenterology, 2015)
Introduction: In hepatic resections, there has been a high quality demand. The aim of this systematic study was to investigate whether hemostat device can significantly improve outcome in resecting liver surgery, in particular, in high risk patients. Methods: All consecutive patients (mean age, 60.5 [range, 17-96] years) who underwent hepatic resection (nTotal= 770) were prospectively documented in a computer-based registry at a university hospital (tertiary center) over a time period of 10 years and retrospectively evaluated specifically with regard to the use (-/+) of hemostat device (Tissucol®, n=59 / Tachocomb®, n=202 / combination, n=55) indicated (among others) by drainage volume, inflammatory parameters and rate of specific complications (nValidated=541 [100 %]). Results: Most frequently, (a-)/ typical segmental resections were used: n=192/90 (3-segment resection, n=38 only). 1.) For the assignment of patients to the two different groups (-/+hemostat device), weight loss and type of resection were found as significant factors (trend: ASA, cirrhosis), for the amount of drainage volume, ASA, sex, Karnofsky Performance Scale and also type of resections using independent distributed statistical tests such as (χ2, U test [Mann/Whitney]; H test [Kruskal- Willis]; correlation coefficient by Spearman)- no impact: smoking, diabetes, BMI, ethanol. 2.) Not taking into account these parameters, the use of hemostat device was characterized by an increased drainage volume (negative control < Tissucol=Tachocomb < combination). 3.) Using multifactorial analysis of variance, it was found even under correction by the factors with significant impact elucidated in the single test that the application of hemostat device onto the hepatic resection area resulted unexpectedly rather in an increase than a decrease of the drainage volume but 4.) under accompanying more pronounced increase of the white blood cell count (leucocytosis). 5.) General and specific complications such as postoperative bleeding, biliary fistula and subhepatic abscess were not further lowered in a significant manner using hemostat device. Conclusion: Adequate surgery in the operative management of hepatic resection area cannot further be improved or optimized using hemostat device. In this context, drainage volume may not be considered a sufficient rather an orienting parameter. However, there is an inflammatory response detectable most likely indicated by a(n un-)specific effusion and increase of white blood cell count, which can be interpreted as reactive inflammation to foreign material.
Keywords: hemostatic agent; fibrin glue; tachocomb; alcohol; devices; surgery; foreign body; leukocytosis; gastrointestinal disease; liver resection; human; leukocyte count; Tertiary (period); parameters; inflammation; patient; computer; abscess; body weight loss; effusion; bile duct fistula; postoperative hemorrhage; analysis of variance; diabetes mellitus; high risk patient; smoking; correlation coefficient; Karnofsky Performance Status; liver cirrhosis; university hospital; register; liver surgery

Laparoscopically detected and nonsurgically managed ileal perforation by an ingested fish bone: A case report - Chandrasinghe, P.C.; Pathirana, C.K. (Journal of Medical Case Reports, 2015)
Introduction: Ileal perforation due to fish bone is a rare event. The condition is difficult to diagnose due to lack of specific clinical features and low sensitivity of imaging techniques. We report a case of ileal perforation by a fish bone that was detected laparoscopically and managed nonsurgically. Case presentation: A 45-year-old Sinhalese man presented with acute onset right iliac fossa pain and fever for three days. On examination, he had significant right iliac fossa tenderness and guarding. His white cell count and C-reactive protein level were elevated and an ultrasound scan was indicative of a bowel mass formation. A clinical diagnosis of acute appendicitis was made and laparoscopic appendicectomy was scheduled. At initial survey, a thin spike-like structure was retrieved from the bowel mass, which was revealed to be a fish bone. Our patient was managed with antibiotics only and did not develop any complications. Conclusions: Ileal perforation due to fish bone is a rare condition that can mimic common conditions like appendicitis. Preoperative diagnosis is rarely made. The slow process of fish bone migration results in concomitant sealing of the perforation, reducing contamination. Use of laparoscopy may be useful in diagnosing this condition and preventing the morbidity of laparotomy in these patients.
Keywords: C reactive protein; cefuroxime; clopidogrel; metronidazole; acute appendicitis; adult; appendectomy; article; bone; case report; coronary stenting; disease duration; echography; fever; fish; foreign body; gastrointestinal radiography; hospital discharge; human; ileum disease; iliac fossa pain; ischemic heart disease; laparoscopy; leukocyte count; male; middle aged; pain; physical examination; priority journal; protein blood level; Sinhalese (people); small intestine perforation; treatment outcome

Bronchiectasis diagnosis and treatment - Organtzis, I.; Papakosta, D.; Foyka, E.; Lampaki, S.; Lagoudi, K.; Moumtzi, D.; Kostanta, S.; Sourla, E.; Papadaki, E. (Journal of Thoracic Disease, 2015)
Background: Bronchiectasis, with was once thought to be an orphan disease, is now being recognized with increasing frequency around the world. Patients with bronchiectasis have chronic cough and sputum production, and bacterial infections develop in that result in the loss of lung function. Bronchiectasis occurs in patients across the spectrum of age and gender, but the highest prevalence is in older women. The diagnosis of bronchiectasis is made by high-resolution CT scans. Bronchiectasis, which can be focal or diffuse, may occur without antecedent disease but is often a complication of previous lung infection or injury or is due to underlying systemic illnesses. Patients with bronchiectasis may have predisposing congenital disease, immune disorders, or inflammatory disease. The treatment of bronchiectasis is multimodality, and includes therapy with antibiotics, anti-inflammatory agents, and airway clearance. Resectional surgery and lung transplantation are rarely required. The prognosis for patients with bronchiectasis is variable given the heterogeneous nature of the disease. A tailored, patient-focused approach is needed to optimally evaluate and treat in individuals with bronchiectasis. Bronchiectasis is destruction and widening of the large airways. If the condition is present at birth, it is called congenital bronchiectasis. Causes: Bronchiectasis is often caused by recurrent inflammation or infection of the airways. Sometimes it begins in childhood after a more severe lung infection or inhaling a foreign object. Cystic fibrosis causes about a third of all bronchiectasis cases in the United States. Certain genetic conditions can also cause bronchiectasis, including primary ciliary dyskinesia and immunodeficiency syndromes. The condition can also be caused by routinely breathing in food particles while eating. Symptoms: Symptoms often develop gradually, and may occur months or years after the event that causes the bronchiectasis. The may include: (I) bluish skin color; (II) breath odor; (III) chronic cough with large amounts of foul-smelling sputum; (IV) clubbing of fingers; (V) coughing up blood; (VI) fatigue; (VII) paleness; (VIII) shortness of breath that gets worse with exercise; (IX) weigh loss and (X) wheezing. Exams and tests: When listening to the chest with a stethoscope, the doctor may hear small clicking, bubbling, wheezing, rattling, or other sounds, usually in the lower lobes of the lungs. Test may include: (I) aspergillosis precipitin test; (II) aipha-1; (III) antitrypsin blood test; (IV) chest X-ray; (V) chest CT; (VI) sputum culture; (VII) complete blood count; (VIII) genetic testing, including sweat test for cystic fibrosis; (IX) PPD skin test to check for a prior tuberculosis infection and (X) serum immunoglobulin electrophoresis. Treatment: Treatment is aimed at controlling infections and bronchial secretions, relieving airway obstruction, and preventing complications. Regular, daily drainage to remove bronchial secretions is a routing part of treatment. A respiratory therapist can show the patient coughing exercises that will help. Antibiotics, bronchodilators, and expectorants are often prescribed for infections, Surgery to resect the lung may be needed if medicine does not work or if the patient has, massive bleeding. Prognosis: The outlook depends on the specific causes of the disease. With treatment, most people can lead normal lives without major disability. Possible complications: (I) coughing up blood; (II) low oxygen levels; (III) recurrent pneumonia. Prevention: The risk may be reduced if lung infections are promptly treated. Childhood vaccinations and a yearly flu vaccine help reduce the change of some infections. Avoiding upper respiratory infections, smoking, and pollution may also reduce your risk or infection.
Keywords: alpha 1 antitrypsin; antiinflammatory agent; bronchodilating agent; endogenous compound; expectorant agent; influenza vaccine; macrolide; oxygen; airway obstruction; aspergillosis; bleeding; blood cell count; bronchus secretion; child; childhood; chronic cough; clinical study; complication; cystic fibrosis; destruction; diagnosis; digital clubbing; disability; drug therapy; dyspnea; eating; electrophoresis; fatigue; female; food; gender; genetic screening; hemoptysis; high resolution computer tomography; human; human tissue; immune deficiency; immunoglobulin blood level; injury; Kartagener syndrome; lung clearance; lung infection; lung transplantation; male; medicine; odor; pallor; pneumonia; prevalence; prognosis; rare disease; respiratory therapist; serodiagnosis; skin color; skin test; smoking; sound; spirometry; sputum culture; stethoscope; surgery; sweat test; symptom; thinking; thorax radiography; tuberculosis; United States; upper respiratory tract infection; vaccination; wheezing

Intraoperative Radiography for Evaluation of Surgical Miscounts - Walter, W.R.; Amis, E.S.; Sprayregen, S.; Haramati, L.B. (Journal of the American College of Radiology, 2015)
Purpose Retained surgical items result in substantial morbidity, health care-related expense, and legal liability. This study determines the performance of a protocol for locating surgical items after a miscount, in which intraoperative radiography included a radiograph of the unaccounted for item. Methods Institutional review board approval was obtained. In 20,820 operations performed between January 1, 2011 and April 1, 2013, a total of 183 consecutive surgical miscounts occurred, involving 180 patients (97 male, 83 female; median age: 55 years). Departmental protocol mandated that a radiograph of an example of the potentially retained item be taken simultaneously with each patient intraoperative radiograph. Three board-certified radiologists retrospectively reviewed these radiographs and follow-up imaging, achieving consensus on interpretation. Adherence to institutional protocol was assessed. Demographic data, surgical documentation, and clinical follow-up data were recorded. Results The incidence of surgical miscounts was 0.9% (183 of 20,820). Only 9% (17 of 183) were resolved by discovery: outside the patient (8 cases); on intraoperative radiographs (5 cases); incidentally on follow-up radiographs (2 cases); and on retrospective review (2 cases). The false-negative rate was 44% (4 of 9). Neither of the 2 retained needles discovered postoperatively was removed. The procedures most prone to miscounts were: esophagogastrectomy (33%; 2 of 6); liver transplant (18%; 12 of 66); and Whipple procedure (16%; 7 of 44). Needles (65%) and sponges (9%) were the items that were overlooked most often. Adherence to the protocol of imaging an example of a potentially retained item was 91% (167 of 183). Conclusions Despite good adherence to a protocol of imaging the potentially retained items, small needles often were not visualized on intraoperative radiographs and were not subsequently removed, without known adverse events. This finding suggests that intraoperative radiography for small needles may be unnecessary, but further study is required.
Keywords: adult; article; clamp; esophagogastrectomy; false negative result; female; follow up; human; liver transplantation; major clinical study; male; medical record review; middle aged; pancreaticoduodenectomy; peroperative echography; retained instrument; retractor; retrospective study; scissors; surgical error; surgical miscount; surgical sponge; suture needle

Wrong-site surgery, retained surgical items, and surgical fires a systematic review of surgical never events - Hempel, S.; Maggard-Gibbons, M.; Nguyen, D.K.; Dawes, A.J.; Miake-Lye, I.; Beroes, J.M.; Booth, M.J.; Miles, J.N.V.; Shanman, R.; Shekelle, P.G. (JAMA Surgery, 2015)
IMPORTANCE Serious, preventable surgical events, termed never events, continue to occur despite considerable patient safety efforts. OBJECTIVE To examine the incidence and root causes of and interventions to prevent wrong-site surgery, retained surgical items, and surgical fires in the era after the implementation of the Universal Protocol in 2004. DATA SOURCES We searched 9 electronic databases for entries from 2004 through June 30, 2014, screened references, and consulted experts. STUDY SELECTION Two independent reviewers identified relevant publications in June 2014. DATA EXTRACTION AND SYNTHESIS One reviewer used a standardized form to extract data and a second reviewer checked the data. Strength of evidence was established by the review team. Data extraction was completed in January 2015. MAIN OUTCOMES AND MEASURES Incidence of wrong-site surgery, retained surgical items, and surgical fires. RESULTS We found 138 empirical studies that met our inclusion criteria. Incidence estimates for wrong-site surgery in US settings varied by data source and procedure (median estimate, 0.09 events per 10 000 surgical procedures). The median estimate for retained surgical items was 1.32 events per 10 000 procedures, but estimates varied by item and procedure. The per-procedure surgical fire incidence is unknown. A frequently reported root cause was inadequate communication. Methodologic challenges associated with investigating changes in rare events limit the conclusions of 78 intervention evaluations. Limited evidence supported the Universal Protocol (5 studies), education (4 studies), and team training (4 studies) interventions to prevent wrong-site surgery. Limited evidence exists to prevent retained surgical items by using data-matrix-coded sponge-counting systems (5 pertinent studies). Evidence for preventing surgical fires was insufficient, and intervention effects were not estimable. CONCLUSIONS AND RELEVANCE Current estimates for wrong-site surgery and retained surgical items are 1 event per 100 000 and 1 event per 10 000 procedures, respectively, but the precision is uncertain, and the per-procedure prevalence of surgical fires is not known. Root-cause analyses suggest the need for improved communication. Despite promising approaches and global Universal Protocol evaluations, empirical evidence for interventions is limited.
Keywords: article; bibliographic database; communication disorder; data extraction; human; incidence; meta analysis; operating room; patient safety; priority journal; quality control; regional anesthesia; resource management; retained instrument; surgical error; surgical fire; surgical patient; surgical sponge; surgical training; systematic review; wound closure; wrong site surgery

Novel hemostatic patch achieves sutureless epicardial wound closure during complex cardiac surgery, a case report - Jainandunsing, J.S.; Al-Ansari, S.; Woltersom, B.D.; Scheeren, T.W.; Natour, E. (Journal of cardiothoracic surgery, 2015)
Treatment of damaged cardiac tissue in patients with high bleeding tendency can be very challenging, damaged myocardial tissue has a high rupture risk when being sutured subsequently on-going bleeding is a major risk factor for poor clinical outcome. We present a case demonstrating the feasibility in using a novel haemostatic collagen sponge for the management of a myocardial wound. This report is the first description in cardiac surgery where Hemopatch sponges are used to successfully seal a left ventricle wound. Our patient was diagnosed with endocarditis, had a low pre-operative haemoglobin count and underwent cardiac surgery for multiple valve repairs. The procedure was performed on cardiopulmonary bypass, which meant our patient had to be heparinized. Despite these major risk factors for bleeding Hemopatch managed to contain bleeding and seal the wound, no sutures were needed.
Keywords: aortic valve stenosis; case report; complication; coronary artery disease; devices; heart rupture; heart surgery; heart valve replacement; hemostasis; human; male; middle aged; mitral valve stenosis; procedures; surgical sponge; suture technique

Retained surgical needle post myomectomy, an uncommon mishap - Obajimi, G.O.; Oranye, B.C. (African journal of medicine and medical sciences, 2014)
BACKGROUND: Retained foreign bodies are relatively uncommon and probably underreported in the tropics. Largely preventable errors, they cause harm to both the patient and the medical practitioner. CASE PRESENTATION AND MANAGEMENT: A 32 year old primigravida with recurrent lower abdominal pain in pregnancy. She had myomectomy a year earlier at a private hospital in which the endometrium was inadvertently breached. She subsequently had an elective caesarean section at 38 weeks and 2 days gestational age. Intra-operative findings were adhesive bands between the uterus and loops of bowel and a round bodied surgical needle attached by adhesions anteriorly to the lower segment. Her post operative care was uneventful and she was discharged home on the 3rd day post operation. CONCLUSION: Retained surgical foreign body (RSFB) could pose a diagnostic dilemma as in the case of this patient with recurrent lower abdominal pain in pregnancy. Meticulous instrument count should include sutures and needles.
Keywords: adult; adverse event; case report; cesarean section; devices; female; foreign body; human; myomectomy; needle; pregnancy; surgical equipment; tissue adhesion

Where is my peg tube? - Alastal, Y.; Hammad, T.; Bawany, M.; Alaradi, O.; Nawras, A. (American Journal of Gastroenterology, 2014)
Introduction: Enteral nutrition by percutaneous gastrostomy tube (PEG) is generally safe and effective, but serious complication can occur in 1.5-4 % of cases. Here, we report a case of small bowel obstruction from inadvertent dislodgment and migration of the PEG tube into the terminal ileum, causing small bowel obstruction with successful endoscopic retrieval of the dislodged tube. Case Report: A 96-year-old male with severe dementia presented to the emergency department from a nursing home with abdominal discomfort and distension for 2 days. The patient had PEG tube placed a few years ago at an outside facility to maintain adequate calorie intake. However, the tube was not utilized since the patient was able to handle food by mouth. His nurse at the facility reported that the PEG tube had been missing for few days. At presentation, vital signs were stable. Abdominal examination revealed moderately distended abdomen with generalized tenderness but no guarding or rigidity. Bowel sounds were hyperactive. Lab work showed white blood cell counts of 3.3 thou/mm3 and hemoglobin of 8.9 g/dL, platelets 85 Thou/mm3. Abdominal x-ray showed small bowel obstruction (SBO) with foreign object seen close to the ileocecal valve region possibly a PEG tube bumper. Abdominal CT scan confirmed the partial SBO secondary to PEG tube with its bumper located in the distal ileum. After hydration, nasogastric decompression, patient underwent colono-ileoscopy under general anesthesia. The PEG tube and its bumper were seen about 20 cm proximal to the ileocecal valve and were successfully retrieved with a snare. After the procedure, the patient developed sepsis from the bowel obstruction. He was transferred to the ICU. As his condition continued to decline, support was withdrawn according to the patient and the family wishes. Conclusion: SBO due to internal migration of PEG tube is a potentially unreported complication; retrieving it endoscopically is a feasible option in an appropriate clinical setting. (Figure Presented).
Keywords: hemoglobin; American; college; gastroenterology; tube; human; patient; small intestine obstruction; ileum; ileocecal valve; enteric feeding; case report; nurse; stomach tube; dementia; caloric intake; computer assisted tomography; thrombocyte; food; general anesthesia; vital sign; examination; male; rigidity; intestine sound; abdominal discomfort; nursing home; leukocyte count; emergency ward; hydration; decompression; procedures; sepsis; intestine obstruction; abdomen; abdominal radiography

A multi-disciplinary approach to foreign body removal - Siegel, N.; Ortega, A.; Kaufman, A.; DiFabrizio, L.; Harkin, T.J. (American Journal of Respiratory and Critical Care Medicine, 2014)
Introduction: Foreign body (FB) aspiration is typically observed in children, with 75-85% of cases occurring before age fifteen. The presence of airway foreign bodies in adults is usually associated with compromised airway protection mechanisms. We present an adult with an obstructing FB in his right main-stem bronchus (RMB), which was removed with flexible bronchoscopy by operating under a multi-disciplinary approach. Case Report: A 64-year old man with human immunodeficiency virus (CD4 count 232) presented with six months of cough exacerbated by swallowing, but denied aspiration of food or foreign objects. Physical exam: normal. Laboratory values: WBC 8.2x10∧3/uL with a normal differential. Chest CT: large obstructing high density FB in RMB. Clinical course: Endotracheal tube (ETT) was placed for flexible bronchoscopy. A cylindrical FB (Figure) was identified in the RMB and grasped with large rat tooth forceps, but dislodged within the trachea. Attempts to remove the FB were made with a variety of instruments (balloon catheter, net basket and cryoprobe). Though initially successful, these efforts ultimately failed due to the object's dimensions. The FB moved proximally causing tracheal obstruction, hypoxemia and pulseless electrical activity arrest. To relieve the tracheal obstruction, the FB was pushed distally into the left main-stem bronchus and the patient was resuscitated. Thoracic surgery assistance with rigid bronchoscopy was requested. Rigid forceps via rigid bronchoscope could not maintain reliable grasp of the FB. Flexible bronchoscopy via ETT demonstrated the FB in the trachea at a more advantageous angle, enabling stable grasp with large rat tooth forceps. Simultaneous withdrawal of the bronchoscope, ETT and FB resulted in successful removal. The FB was a plastic pill bottle desiccant measuring 1.5x2cm. Patient was transferred to the intensive care unit and subsequently discharged home. Discussion: This case highlights the difficulties of removing a large aspirated FB, particularly when the exact shape and dimensions are unknown. Bronchoscopy revealed a large cylindrical FB initially not amenable to standard modalities of removal. Although clinical instability led to use of rigid bronchoscopy, success was ultimately achieved with flexible bronchoscopy. The potential for tracheal or glottic obstruction during removal increases with widened FB diameter. This case emphasizes the need for cautious protection of the airway, which allows for experimentation of different techniques until identification of a successful approach. A coordinated, multi-disciplinary approach in a controlled environment led to removal of this FB. (Figure Presented).
Keywords: desiccant; CD4 antigen; plastic; American; society; foreign body; bronchoscopy; human; forceps; airway; trachea obstruction; bronchus; rat; trachea; patient; tooth; adult; protection; aspiration; Human immunodeficiency virus; endotracheal tube; disease course; density; rigid bronchoscope; bronchoscope; male; case report; thorax; hypoxemia; laboratory; food; cryoprobe; swallowing; balloon catheter; electric activity; coughing; thorax surgery; pill; child; intensive care unit; obstruction; microclimate; foreign body aspiration

Retained surgical sponges: findings from incident reports and a cost-benefit analysis of radiofrequency technology - Williams, T.L.; Tung, D.K.; Steelman, V.M.; Chang, P.K.; Szekendi, M.K. (Journal of the American College of Surgeons, 2014)
BACKGROUND: Retained surgical items (RSIs) are serious events with a high potential to harm patients. It is estimated that as many as 1 in 5,500 operations result in an RSI, and sponges are most commonly involved. The adverse outcomes, additional medical care needed, and medico-legal costs associated with these events are substantial. The objective of this analysis was to advance our understanding of the occurrence of RSIs, the methods of prevention, and the costs involved. STUDY DESIGN: Incident reports entered into the University HealthSystem Consortium (UHC) Safety Intelligence database on incorrect surgical counts and RSIs were analyzed. Reported cases of retained surgical sponges at organizations that use radiofrequency (RF) technology and those that do not were compared. A cost-benefit analysis on adopting RF technology was conducted. RESULTS: Five organizations that implemented RF technology between 2008 and 2012 collectively demonstrated a 93% reduction in the rate of reported retained surgical sponges. By comparison, there was a 77% reduction in the rate of retained sponges at 5 organizations that do not use RF technology. The UHC cost-benefit analysis showed that the savings in x-rays and time spent in the operating room and in the medical and legal costs that were avoided outweighed the expenses involved in using RF technology. CONCLUSIONS: Current standards for manual counting of sponges and the use of radiographs are not sufficient to prevent the occurrence of retained surgical sponges; our data support the use of adjunct technology. We recommend that hospitals evaluate and consider the use of an adjunct technology.
Keywords: cost benefit analysis; diagnostic use; economics; foreign body; human; radiofrequency radiation; retrospective study; risk management; surgical sponge

Throat pack safety-critical incidents as a catalyst for audit and improvement - Donohue, C.; Ranasinghe, U.; Bouras, I.; Clarke, S. (Anaesthesia, 2014)
Throat packs (TP) may be inserted to absorb and prevent debris created by intra-oral surgery tracking into the oesophagus or trachea. Retention of a TP can lead to airway obstruction with potential morbidity and mortality. The National Patient Safety Agency (NPSA) produced a safety notice in 2009 aimed at reducing risk of TP retention by improving and standardising visual and documentary safety procedures [1]. In the 2012 Department of Health update retention of foreign body post surgery was stated as a never event [2]. Following two critical incidents in our trust involving retention of TP, practice was reviewed and improvements implemented to minimise future risk. In one case procedural failure led to retention of pack while in the other a portion of an inadvertently torn TP remained concealed. Neither patient came to harm but willingness to learn from near misses focused attention on the issue. Interventions included introduction of a tear-resistant TP, emphasis on inclusion of TP in the swab count and as part of the world health organization (WHO) checklist and circulation of locally adapted safety procedures to staff. Following this, awareness of the NPSA safety procedures and a snapshot of actual practice were audited. Methods Awareness of safety procedures was assessed with a survey distributed to the multi-disciplinary team (MDT). Statistical analysis was performed using chisquared with significance at P < 0.05. During 20 cases in which a TP was used, practice was assessed against the NPSA algorithm. Results Fifty three survey responses were obtained. Labelling the patient/airway was the most commonly cited visual safety procedure (89% of responders). Scrub staff were more likely to identify inclusion of TP in the swab count as a documentary safety procedure than anaesthetic trainees, with statistical significance (X2 (1) = 4.68, P = 0.03), reflecting differences in roles. Only 15% of responders were aware of the local safety policy to keep the TP visible until the patient has left theatre in order to confirm removal. Audit of practice revealed 100% achievement of minimum safety procedures: in all 20 cases at least one visual and one documentary procedure were implemented. Discussion Critical incidents can be a catalyst for education and safety development. Awareness of procedures was good across the MDT though there is room for improvement. Implementation of safety measures exceeded the minimum standards set by the NPSA. Regular education and ongoing attention to the quality of communication and WHO checklists will be required to maintain standards. TPs are rarely used in the US compared with the UK suggesting subjectivity rather than evidence based practice [1]. Rationalising TP usage represents an important additional safety measure.
Keywords: anesthetic agent; safety; catalyst; clinical audit; human; throat; procedures; checklist; risk; patient; education; World Health Organization; morbidity; lacrimal fluid; airway obstruction; surgery; trachea; United Kingdom; foreign body; interpersonal communication; achievement; policy; health; statistical analysis; patient safety; algorithm; mortality; student; statistical significance; esophagus; evidence based practice; oral surgery

Outcomes of retinal detachment repair after scleral laceration - Reed, D.C.; Juhn, A.; Rayess, N.; Hsu, J.; Chiang, A. (Investigative Ophthalmology and Visual Science, 2014)
Purpose: To report the outcomes of retinal detachment (RD) repair following recent scleral laceration repair. Methods: This retrospective, observational, consecutive case series consisted of patients who underwent RD repair for a retinal detachment that was diagnosed within two weeks of scleral laceration repair at our institution between January 1, 2007 and June 8, 2013. Patients with less than 5 months of follow-up and those with intraocular foreign bodies were excluded. Results: Twenty patients met inclusion criteria. Five of these cases were deemed inoperable at the time of retina surgery. Among the 15 who had successful primary RD repair, the average follow-up was 23 months (range 5-52). Six had redetachments requiring additional surgery. The average number of surgeries for RD in this group was 1.6 (range 1-4). At the last visit, 10 of 15 were still attached . The final visual acuities were as follows: better than counting fingers in 3, counting fingers in 5, hand motions in 5, light perception in 1, and no light perception in 1. None of the patients were known to have undergone enucleation or evisceration. No cases of sympathetic ophthalmia developed. Conclusions: Retinal detachment after scleral laceration carries a grave prognosis, but preservation of the eye was common and attempted repair gave ambulatory vision in over half of patients.
Keywords: case study; clinical article; complication; diagnosis; evisceration; female; finger; follow up; human; intraocular foreign body; laceration; male; motion; prognosis; retina detachment surgery; sclera; surgery; sympathetic ophthalmia; vision; visual acuity

Retinal detachment in traumatic chorioretinal rupture (sclopetaria) - Papakostas, T.D.; Yonekawa, Y.; Wu, D.M.; Miller, J.B.; EldmanP.B VPeter B V,; Chee, Y.E.; Husain, D.; Eliott, D. (Investigative Ophthalmology and Visual Science, 2014)
Purpose: Based on the current literature, retinal detachment (RD) is not associated with traumatic chorioretinal rupture (TCR, also known as sclopetaria). The purpose of this study is to present a series of patients with rhegmatogenous retinal detachment associated with TCR. Methods: The records from 3 consecutive patients who sustained TCR were reviewed. The mechanism of TCR, initial presentation and visual acuity, extent of detachment and surgical management are presented Results: Case 1: A 40-year-old man presented one week after an injury with an 8 cm nail embedded in the right orbit extending into the frontal lobe. Visual acuity (VA) was light perception (LP) and there was dense vitreous hemorrhage. TCR and hemorrhagic choroidal detachment were noted as the vitreous hemorrhage cleared. Serial B-scans showed a new retinal detachment 2 weeks after presentation. The patient underwent pars plana vitrectomy (PPV) and lensectomy (PPL), peeling of tractional membranes (MP), and silicone oil (SO) tamponade. One month later, he developed a recurrent inferior detachment which was treated with a repeat PPV with a 180 degree inferior retinectomy and SO tamponade. Case 2: A 14-year-old boy sustained a BB pellet injury in his left orbit. VA was count fingers at one foot and he had vitreous hemorrhage and superior TCR. B-scan demonstrated an attached retina. The vitreous hemorrhage started to clear, but one month after the injury, he developed a new macula-off retinal detachment with a break superiorly at the edge of the TCR with proliferative vitreoretinopathy (PVR). The patient underwent PPV/scleral buckle (SB)/SO tamponade. Case 3: A 65-year-old man sustained a blast injury that resulted in a metallic foreign body that penetrated his right orbit and lodged in the left frontal lobe. VA was LP. Fundus exam revealed vitreous hemorrhage, bullous subhyaloid hemorrhage inferiorly and TCR superiorly. One week after the injury he developed a shallow RD noted on serial B-scans. He underwent a PPV/SB/MP/SO with a 180-degree superior retinectomy, and was also found to have subretinal hemorrhage and PVR. Three months later, the patient developed a recurrent inferior RD with PVR that was treated with a repeat PPV/PPL/180 degree inferior retinectomy and SO tamponade. Conclusions: TCR can be associated with subacute RD in the post-traumatic period and these patients should be followed very closely.
Keywords: endogenous compound; silicone oil; T lymphocyte receptor; adolescent; adult; aged; B scan; blast injury; case report; child; choroid detachment; finger; foot; foreign body; frontal lobe; human; information processing; lensectomy; male; membrane; pars plana vitrectomy; perception; retina detachment; retina macula lutea; rupture; scleral buckle; stomach fundus; surgery; visual acuity; vitreoretinopathy; vitreous hemorrhage

Characteristics and demographics of patients with posterior segment intraocular foreign bodies - Misra, P.; Abbassi, S.M.; Bauza, A.; Zarbin, M.; Bhagat, N. (Investigative Ophthalmology and Visual Science, 2014)
Purpose To describe the demographics, outcomes, and posterior segment (PS) complications in eyes with PS intraocular foreign bodies (IOFBs) that presented to University Hospital in Newark, NJ between 2004 and March 2013. Methods Retrospective chart review. Results Of the 65 eyes identified with IOFBs, 30 had IOFBs in the PS only, 4 had IOFBs in both segments. The average age of patients was 37.8 years (range 20-63). Thirty-one IOFBs (91%) were metal, 2 glass (6%), and 1 plastic (3%). The size of IOFBs ranged from <1 to 24mm, with 21(62%) being 1-5 mm. Diagnosis was made by clinical exam, B-scan, and/or CT scans. Pre-operative visual acuity (VA) ranged from count fingers (CF) to 20/20, an average of 20/462. Final VA ranged from CF to 20/25, an average of 20/204. Twenty-six IOFBs (77%) were removed through surgical sclerotomies. All 34 eyes underwent open globe repair (OGR) within 24 hours of presentation; 30 underwent concurrent pars plana vitrectomy (PPV). The mean duration between time of injury and OGR was 2.35 days. IOFBs were removed from 32 (97%) eyes at the primary repair; in two cases, the PS IOFBs were not seen initially but noted on follow up B scan and CT scan, respectively. Five of 34 eyes received intravitreal antibiotics, Vancomycin and Ceftazidime, at OGR. All patients were given IV antibiotics for an average of 3.90 days. Twenty-four (71%) eyes presented with cataracts, 22 were left aphakic after pars plana lensectomy (PPL) with OGR. At presentation, 26 of 34 (77%) eyes had vitreous hemorrhage, 19 (56%) retinal detachment (RD), 1 (3%) hemorrhagic choroidals and 2 (6%) with endophthalmitis. Eleven eyes were noted to have retinal tears (without RD) intra-operatively. Eighteen of 19 eyes (95%) with RD underwent RD repair (RDR) at presentation (1 eye had RDR one week later). Six of 19(32%) underwent silicone oil tamponade, 14 (41%) endolaser photocoagulation, 9 (47%) gas tamponade, and 3 (9%) scleral buckle procedure. Two eyes were lost to follow-up. Anatomic success of after one RDR was 33% (6/17). Eleven of 17 (65%) eyes had recurrent RD with proliferative vitreoretinopathy (PVR). The overall anatomic success was 94% (16/17). Conclusions Posterior segment IOFBs are associated with vitreous hemorrhage, retinal tears and RDs. Overall anatomic success of retinal reattachment in patients was 94% in our series.
Keywords: ceftazidime; silicone oil; vancomycin; adult; B scan; cataract; choroid; clinical article; diagnosis; endolaser; endophthalmitis; female; finger; follow up; human; intraocular foreign body; laser coagulation; lensectomy; male; pars plana vitrectomy; retina detachment surgery; retina tear; scleral buckle; sclerotomy; surgery; visual acuity; vitreoretinopathy; vitreous hemorrhage; x-ray computed tomography

Covalent attachment of antibiotics to bone allograft - Swisher, N.; Adams, C.; Dattilo, V.; Saunders, R. (FASEB Journal, 2014)
Peri-prosthetic infection (PPI) poses a serious threat to the continued health of any patients implanted with foreign material. Tethering anti-microbials to the surface of implanted materials for the prevention of PPI might ultimately prove to be the safest and most cost-effective strategy. PPIs can be the result of infection by either gram-positive bacteria (GPB) or gram-negative bacteria (GNB), or both. Thus, broad spectrum coverage will be ultimately required. Previous work has shown the efficacy of anti-microbial tethered surfaces. This study sought to show that antibiotics effective against both GPB and GNB could be tethered in combination to morselized bone. Vancomycin (Vanc) and tetracycline (Tet) were covalently bound to demineralized, morselized rat bone. Immunohistochemistry showed that both antibiotics were attached to allograft individually as well as in combination. To test the hypothesis that covalently attached Vanc and Tet will prevent bacterial colonization by either type of bacteria, surfaces were challenged by both S. aureus and E. coli. The antibacterial properties and efficacy were determined using confocal microscopy and colony counting. Vanc tethered bone prevented colonization by S. aureus, and Tet tethered bone prevented colonization by E. coli. A combination of both antibiotics prevented colonization by both species. These results indicate that covalent attachment of combinations of broad spectrum antibiotics to bone allograft could potentially prevent PPIs.
Keywords: antibiotic agent; tetracycline; vancomycin; bone allograft; bone; Escherichia coli; prosthesis infection; human; allograft; foreign body; prevention; infection; patient; Gram negative bacterium; rat; immunohistochemistry; confocal microscopy; hypothesis; bacterial colonization; bacterium; Gram positive bacterium; health; antibacterial activity; species

Acute abdomen caused by through and through small bowel perforation due to clinically unsuspected fish bone: Laparoscopic resection and anastomosis - Dural, A.C.; Yigitbas, H.; Dogan, M.; Kankaya, B.; Kones, O.; Celik, M.F.; Akarsu, C.; Dogan, Y.; Alis, H. (Surgical Endoscopy and Other Interventional Techniques, 2014)
Objective: We aimed to present a patient with acute abdominal pain secondary to small bowel perforation caused by fish bone penetration through the jejunal wall. Case: A 52-year-old man presented to the emergency department with a 3-day history of abdominal pain. He had no nausea, vomiting or diarrhea. The abdominal examination revealed diffuse tenderness and muscle guarding. The plain abdominal X ray showed free subdiaphragmatic air. His laboratory results revealed an elevated white blood cell count (11,700 with 78 % neutrophils) and normal serum amylase (43 U/L). The presumptive diagnosis was peptic ulcer perforation and the patient underwent diagnostic laparoscopy. Laparoscopy showed several inflamed, edematous jejunal loops with a foreign body causing through and through perforation of the jejunum and protruding from the two opposite wall on the anti-mesenteric side. It also caused impaction and obstruction at the same level and could not be removed. Intracorporeal resection and anastomosis with a laparoscopic linear stapler, which was inserted through two small enterotomies approximately 5 cm proximal and distal to the stricture site, was performed using a 15, a 10 and a 5 mm trocar. The segment of resected bowel was removed through the 15 mm trocar site. The postoperative period was uneventful, and the patient was discharged on the fourth day. Conclusion: Through and through perforation and obstruction of small bowel is a unique presentation of fish bone. In the current case it caused acute abdominal symptoms and free subdiaphragmatic air on the plain abdominal X ray and was managed laparoscopically.
Keywords: small intestine; intestine perforation; fish; bone; surgery; anastomosis; endoscopic surgery; acute abdomen; human; patient; abdominal radiography; perforation; diagnosis; trocar; obstruction; laparoscopy; laboratory; laryngeal mask; muscle; examination; implantable cardioverter defibrillator; leukocyte count; intestine; diarrhea; stapler; jejunum; vomiting; ulcer perforation; nausea; foreign body; amylase blood level; neutrophil; postoperative period; abdominal pain; emergency ward; male

Duke it out: Finding the right diagnosis - Kaiksow, F.; Putnam, P.J. (Journal of General Internal Medicine, 2014)
LEARNING OBJECTIVE 1: Diagnose bacterial endocarditis in the absence of echocardiographic evidence of endocardial involvement. CASE: A42-year-old man presented with a two-day history of right hand pain and swelling, which began the day prior while injecting heroin into his hand. He had been awoken from sleep that morning by a sharp, left-sided chest pain that worsened with deep inspiration and was associated with shortness of breath. Temperature was 104.4 °F, heart rate was 122 beats per minute, blood pressure was 169/109, respirations were 22 breaths per minute, and oxygen saturation was 84 % on room air. Past medical history was significant for opiate abuse, hypertension, Type 2 diabetes, and previous trauma to the right hand with residual orthopedic hardware. The patient's hand was warm, swollen, and tender to palpation along the dorsum. Peripheral white blood cell count was significantly elevated and a plain radiograph of the hand showed soft tissue swelling with foreign bodies and no evidence of osteomyelitis. A chest x-ray was normal; CT PE protocol revealed multiple nodules in each lung, concerning for cavitation. A transthoracic echocardiogram was negative, but given the high suspicion for endocarditis, a transesophageal echocardiogram was performed, and was also negative. All three sets of blood cultures, drawn on admission, quickly resulted as grampositive cocci in clusters, ultimately identified as Methicillin-Resistant Staphylococcus aureus. Despite the lack of visual evidence of endocardial involvement, the patient was diagnosed with acute bacterial endocarditis based on the Modified Duke Criteria. DISCUSSION: Bacterial endocarditis is a life-threatening condition frequently treated by general internists. The estimated annual incidence is between three to nine cases per 100,000 people, with twice as many men as women effected. Patients classified as 'highrisk' include intravenous drug users and individuals with prosthetic valves or a prior history of valvular disease, and have a much higher infection rate. The diagnosis of bacterial endocarditis is made based on the Modified Duke Criteria, which have a greater than 80 % sensitivity, specificity, and negative predictive value. In 90 % of cases, vegetations are seen on transthoracic or transesophageal echocardiogram, which is one of the two major Duke Criteria. The other major criterion is bacteremia by an organism commonly known to cause endocarditis; if both major criteria are met the diagnosis of definitive bacterial endocarditis is made. In the other 10%of cases, diagnosis must include at least three minor criteria, such as a predisposing condition, fever, vascular or immune phenomena, or positive blood cultures with an organism not commonly known to cause endocarditis. Definitive endocarditis can be diagnosed in a patient with one major and three minor criteria, or with no major but all five minor criteria. In this case, the patient met one major and three minor criteria: Staphylococcus aureus bacteremia, a predisposing condition (intravenous drug use), fever, and a vascular phenomenon (septic pulmonary emboli as seen on chest CT). With intravenous drug use on the rise, general internists should be familiar with the Modified Duke Criteria for diagnosing endocarditis, particularly when echocardiography does not correlate with clinical presentation.
Keywords: diamorphine; opiate; society; internal medicine; diagnosis; human; bacterial endocarditis; endocarditis; patient; echocardiography; blood culture; organisms; male; endocardium; fever; internist; soft contact lens; drug use; thorax; blood pressure; foreign body; hand pain; soft tissue; heart rate; palpation; temperature; female; computer; dyspnea; X ray film; injury; non insulin dependent diabetes mellitus; staphylococcal bacteremia; lung embolism; leukocyte count; swelling; edema; infection rate; osteomyelitis; thorax pain; hypertension; heart valve prosthesis; abuse; sleep; intravenous drug abuse; methicillin resistant Staphylococcus aureus; medical history; ambient air; predictive value; vegetation; bacteremia; oxygen saturation; lung; breathing; thorax radiography

Staphylococcus lugdunensis: The great cons artist - Collins, J.M.; Miller, C.S. (Journal of General Internal Medicine, 2014)
LEARNING OBJECTIVE 1: Demonstrate the pathogenicity of coagulase-negative staphylococcus. LEARNING OBJECTIVE 2: Review the clinical presentation of infective endocarditis. CASE: A 49-year-old woman with HIV (CD4 count 101 cells/uL) and end stage renal disease presented with 9 days of progressive shortness of breath after a revision of her arteriovenous (AV) fistula for dialysis. She also noted generalized fatigue, subjective fever, four-pillow orthopnea and new-onset paroxysmal nocturnal dyspnea. Her temperature was 99.2 ° F, blood pressure 132/74, respirations 16, and saturation 99% on room air. She had a 3/6 systolic ejection murmur noted at previous admissions as well as a new regurgitant murmur loudest in the mitral position, jugular venous distention, and 1+ lower extremity pitting edema. There was no erythema surrounding her right upper extremity AV fistula. WBC count was 14.2×10e3/uL with left shift. On day 2, she developed a fever to 101.6 ° F. Blood cultures from two sites grew coagulase-negative staphylococcus and repeat cultures were drawn. Blood cultures remained persistently positive for Staphylococcus lugdunensis for 8 days. A transthoracic echocardiogram (TTE) with bubble study showed an ejection fraction of 55-60 %, no shunt, and a vegetation on the atrial aspect of the anterior mitral leaflet. She was treated with nafcillin while inpatient and then transitioned to 6 weeks of cefazolin with dialysis. DISCUSSION: Internists commonly encounter heart murmurs, and their etiology can be either benign or pathogenic. A high degree of suspicion for infective endocarditis (IE) with a new or changed heart murmur is imperative because endocarditis can rapidly cause irreversible damage to the heart. IE in chronic hemodialysis patients is significantly more common and causes greater morbidity and mortality than in the general population, being second only to cardiovascular disease as the leading cause of death in this group. Staphylococcus lugdunensis is a coagulase-negative staphylococcus (CONS) that like other CONS infections can range from a harmless skin flora to a life-threatening pathogen. S. lugdunensis affects native valves with greater frequency than prosthetic valves, unlike other CONS. IE due to this organism is characterized by a high mortality and rapid tissue destruction. Often, hospital laboratories will report non-aureus isolates only as CONS, but speciation of the organism can assume great importance in defining therapeutic approach. For example, the clinical outcome in the treatment of S. lugdunensis is much more favorable with valvular replacement than with antibiotics alone. Despite their frequency as contaminants, CONS have become important nosocomial pathogens, accounting for 9 % of all nosocomial infections. CONS are also the third most common cause of blood stream infections. The incidence of CONS bacteremia in patients with foreign bodies such as a port is increased compared to the general population due to their strong adherence to polymer surfaces and biofilm formation. It is important to assess the clinical picture when faced with CONS-positive blood cultures because these organisms are not always contaminants, and can cause significant morbidity and mortality when not treated appropriately.
Keywords: CD4 antigen; cefazolin; nafcillin; antibiotic agent; polymer; Staphylococcus lugdunensis; society; internal medicine; human; blood culture; mortality; coagulase negative Staphylococcus; organisms; bacterial endocarditis; population; pathogenesis; morbidity; heart murmur; fever; dialysis; arteriovenous fistula; blood pressure; heart; temperature; etiology; paroxysmal dyspnea; fatigue; vegetation; female; pathogenicity; hospital patient; heart ejection fraction; patient; biofilm; bacteremia; internist; bloodstream infection; echocardiography; endocarditis; hemodialysis; hemodialysis patient; hospital infection; tissues; heart valve prosthesis; leukocyte count; dyspnea; arm; erythema; skin flora; edema; end stage renal disease; hospital laboratory; infection; cause of death; leg; cardiovascular disease; systolic heart murmur; ambient air; foreign body; Human immunodeficiency virus

Postpartum tuberculous peritonitis with ascites and elevated serum CA125 - Tuzcuoglu, I. (International Journal of Infectious Diseases, 2014)
Background: The peritoneum is one of the most common extrapulmonary sites of tuberculous infection. Peritoneal tuberculosis remains a significant problem in parts of the world where tuberculosis is prevalent. Tuberculous peritonitis is a rare condition especially in the post-partum era. We report a case of postpartum tuberculous peritonitis mimicking a malignant tumor. Methods & Materials: We report a case of postpartum tuberculous peritonitis mimicking a malignant tumor. 26 year old lady who had a cesarean section 50 days ago presented with ascites and elevated serum CA125 (420 U/ml). In her past story she had another sectio-cesarean 13 months ago and her son was healthy. She had mild anemia with hemoglobin 11 gr/ml with moderately high wbc count. (11300/mm3) Her blood biochemical profile was normal.The viral hepatitis and the HIV profile was negative. Ascidic fluid “ascites-albumin gradient” was lower than 1.1 excluding portal hypertension. Chest X-ray findings did not indicate pulmonary tuberculosis, and neither the smear method nor culture in ascitic fluid obtained by paracentesis indicated an infection of Mycobacterium tuberculosis. Abdominal ultrasound, thorax and abdominal CT revealed massive ascites, mild plevral effusion and servical conglomerated lymphadenopathy of 4X4 cm. The ovaries were normal in CT findings. The ascites fluid had marked lymphocytes and some foreign body particules whichwasthought to be the suture material resolving after the cesarean operation. Results: Ascites fluid adenosine deaminase levels were markedly high. (65 IU/ml) The cervical conglomerated lymph nodes were taken out for pathological examination. Pathologic examination revealed tuberculosis lymphadenitis with marked caseification necrosis. The case was thought to be tuberculosis peritonitis and lymphadenitis. Conclusion: Following treatment using the 4-drug antituberculosis regimen of isoniasid, rifampicin, ethambutol and pyrazinamide; the patient recovered with disappearance of ascites and the CA125 serum level returned to the normal range after six months.
Keywords: pyrazinamide; hemoglobin; albumin; adenosine deaminase; suture material; rifampicin; ethambutol; tuberculous peritonitis; ascites; serum; infection; tuberculosis; ascites fluid; malignant neoplasm; examination; lymphadenitis; female; virus hepatitis; cesarean section; thorax; Mycobacterium tuberculosis; ovary; lymphocyte; paracentesis; blood; leukocyte count; lung tuberculosis; human; smear; thorax radiography; son; ultrasound; effusion; lymphadenopathy; portal hypertension; lymph node; foreign body; necrosis; peritonitis; liquid; anemia; patient; blood level; peritoneum; Human immunodeficiency virus

Risk factors for retained surgical items: A meta-analysis and proposed risk stratification system - Moffatt- Bruce, S.D.; Cook, C.; Steinberg, S.; Stawicki, S.P. (Journal of Surgical Research, 2014)
Introduction: Retained surgical items (RSI) are designated as completely preventable “never events”. Despite numerous case reports, clinical series, and expert opinions, few studies provide quantitative insight into RSI risk factors and their relative contributions to the overall RSI risk profile. This meta-analysis examines the best available data for RSI risk factors thereby seeking to provide a clinically relevant risk stratification system. Methods: Twenty relevant studies were considered for this meta-analysis. Three retrospective, case-control studies of RSI related risk factors (Gawande et al, Lincourt et al, Stawicki et al) contained suitable group comparisons between patients with/without RSI, thus qualifying for further analysis. The following “common factor” variables compiled fromthe above studies: body-mass index (BMI), emergency procedure, estimated operative blood loss >500 mL, incorrect surgical count, lack of surgical count, >1 sub-procedure, >1 surgical team, nursing/staff shift change, operation “after hours” (i.e., between 5pm-7am), operative time, trainee presence, and unexpected intraoperative factors were analyzed. Results: Our analysis of pooled data demonstrates that 9 risk factors are significantly associated with increased RSI risk, and 1 factor (trainee presence) was associated with lower RSI risk (OR 0.46). Variables found to be synergistically associated with increased RSI risk include duration of operation (1.6); BMI (OR 1.7); intraoperative blood loss >500 mL (OR 1.7); >1 sub-procedure (OR 2.1); emergency procedure (OR 2.4); lack of surgical counts (OR 2.5); >1 surgical team (OR 3.0); unexpected intraoperative factors (OR 3.3); and incorrect surgical count (OR 4.1). Changes in nursing staff and operation “after hours” were not significantly associated with RSI risk in the current meta-analysis. Based on the current analysis, we stratified RSI risk factors into low, intermediate, and high-risk groups (Figure). Conclusions: This analysis demonstrated that among the “common risk factors” reported by all three case-control studies, 9 synergistically show elevated RSI risk across the pooled data. Based on these results, the authors propose a risk stratification scheme and a “call to arms” for large, prospective, multi-center studies evaluating effects of specific changes at the institutional level on the risk of RSI. Overall, our findings provide a meaningful foundation for future patient safety initiatives and clinical studies of RSFB occurrence and prevention.
Keywords: meta analysis; risk; stratification; surgery; society; university; surgeon; human; risk factor; meta analysis (topic); procedures; student; case control study; emergency; non profit organization; multicenter study; arm; high risk population; nursing staff; patient; bleeding; operation duration; operative blood loss; patient safety; prevention; clinical study; body mass; case report

Intrathoracic gossypiboma - Hameed, A.; Naeem, A.; Azhar, M.; Fatimi, S.H. (BMJ Case Reports, 2014)
Gossypiboma refers to retained sponge or swab in any body cavity after surgery. Although it is a rare occurence, it can lead to various complications which include adhesions, abscess formation and subsequent infections. Gossypiboma occurs as a result of not using radioopaque sponges, poorly performed sponge counts, inadequate wound explorations on suspicion and misread intraoperative radiographs. Therefore, this event can be avoided if strict preventive measures are taken. Moreover, further complications can be avoided following the correct and early diagnosis of gossypiboma. Gossypiboma is an important topic as it carries great medicolegal consequences for the surgeon. We have presented three cases of intrathoracic gossipiboma following previous cardiothoracic surgeries. They presented years after their surgeries, with features varying from patient to patient, ranging from cough and fever to no sypmtoms at all. CT scan only showed a mass lesion in all cases, therefore we proceeded for CT-guided biopsy which was also found to be inconclusive. It was only after entering the thoracic cavity via video-assisted thoracoscopy/ thoracotomy that the diagnosis was made and sponges were taken out successfully. All our cases recovered with no further complications.
Keywords: adult; aged; article; case report; computer assisted tomography; coughing; differential diagnosis; follow up; gossypiboma; histopathology; human; human tissue; male; middle aged; outcome assessment; postoperative complication; priority journal; thoracoscopy; thoracotomy; thorax radiography; wedge resection

Ingestion of multiple magnets: The count does matter - Kim, Y.; Hong, J.; Moon, S.-B. (Journal of Pediatric Surgery Case Reports, 2014)
Ingestion of multiple magnets poses a particular risk for various intraabdominal complications in children. We herein report a case of ingestion of multiple magnets, of which 3 were spontaneously expelled, and the remaining magnets were surgically removed. Since the total amount of ingestion was unknown upon presentation and the remaining intraabdominal magnets failed to pass after 24 h, emergency surgery was performed. Two magnets sandwiched the bowel walls and formed a jejunoileal fistula. There was no peritoneal contamination. We found that not all the ingested multiple magnets attracted each other, and multiple magnets could appear as single material on a plain radiograph. Confirming the exact count of ingested magnets is important; if the count is in doubt or two or more attachments are evident, prompt surgical intervention is warranted. © 2014 The Authors. Published by Elsevier Inc. All rights reserved.
Keywords: article; case report; emergency surgery; female; foreign body; gastroscopy; human; ileocecal valve; infant; ingestion; intestine anastomosis; intestine necrosis; magnet; priority journal; small intestine

A case of acute retinal toxicity caused by an intraocular foreign body composed of cobalt alloy - Kang, J.Y.; Lee, S.U.; Nam, K.Y.; Kim, T.W.; Lee, S.J. (Cutaneous and Ocular Toxicology, 2014)
Context: We describe a case of acute retinal toxicity caused by an intraocular foreign body composed of a cobalt alloy. Case presentation: A 36-year-old man presented to an outside clinic with a traumatic cataract and corneal laceration of his left eye, which had occurred while grinding a shelf. The lacerated cornea was closed primarily and the traumatic cataract was phacoemulsified. He was transferred to our hospital due to identification of a metallic intraocular foreign body in the vitreous. On arrival at our institution, the intraocular foreign body was removed as soon as possible after vitrectomy. On the first postoperative day, vasculitis and serous retinal detachment were observed on the retina at the previous site of the foreign body. Two months after surgery, atrophy of nearly half of the inferior retina was noted on funduscopy, and visual acuity was such that the patient could only count fingers at 30cm. Analysis of the foreign body revealed that it was composed of 84.99% tungsten carbide, 15% cobalt and had traces of titanium and alumina. Discussion: Cobalt containing metallic foreign bodies should be immediately removed, as they have the potential to cause permanent visual disturbance. © 2014 Informa Healthcare USA, Inc.
Keywords: aluminum oxide; cobalt; prednisolone; quinolone derivative; silicone oil; titanium; tungsten; acute retinal toxicity; adult; article; atrophy; best corrected visual acuity; case report; cataract extraction; chorioretinal atrophy; cornea injury; cornea laceration; eye toxicity; fluorescence angiography; human; intraocular foreign body; laceration; male; ophthalmoscopy; phacoemulsification; postoperative period; retina detachment; retina disease; traumatic cataract; vasculitis; visual acuity; vitrectomy; vitreous body

Translational research: The CD34+ cell is crucial for large-volume bone regeneration from the milieu of bone marrow progenitor cells in craniomandibular reconstruction. - Marx, R.E.; Harrell, D.B. (The International journal of oral & maxillofacial implants, 2014)
This study investigated the role of the bone marrow-derived CD34+ cell in a milieu of osteoprogenitor cells, bone marrow plasma cell adhesion molecules, recombinant human bone morphogenetic protein (rhBMP), and a matrix of crushed cancellous allogeneic bone in the clinical regeneration of functionally useful bone in craniomandibular reconstructions. The history and current concepts of bone marrow hematopoietic stem cells and mesenchymal stem cells are reviewed as they relate to bone regeneration in large continuity defects of the mandible. Patients with 6- to 8-cm continuity defects of the mandible with retained proximal and distal segments were randomized into two groups. Group A received an in situ tissue-engineered graft containing 54 ± 38 CD34+ cells/mL along with 54 ± 38 CD44+, CD90+, and CD105+ cells/mL together with rhBMP-2 in an absorbable collagen sponge (1 mg/cm of defect) and crushed cancellous allogeneic bone. Group B received the same graft, except the CD34+ cell concentration was 1,012 ± 752 cells/mL. The results were analyzed clinically, radiographic bone density was measured in Hounsfield units (HU), and specimens were analyzed histomorphometrically. Forty patients participated (22 men and 12 women; mean age, 57 years). Eight of 20 group A patients (40%) achieved the primary endpoint of mature bone regeneration, whereas all 20 group B patients (100%) achieved the primary endpoint. CD34+ cell counts above 200/mL were associated with achievement of the primary endpoint. Bone density was lower in group A (424 ± 115 HU) than in group B (731 ± 98 HU). Group A bone showed a mean trabecular bone area of 36% ± 10%, versus 67% ± 13% for group B. The CD34+ cell functions as a central signaling cell to mesenchymal stem cells and osteoprogenitor cells in bone regeneration. The mechanism of bone marrow-supported grafts requires a complete milieu to regenerate large quantities of functionally useful bone. CD34+ cell counts in a concentration of at least 200/mL in composite grafts are directly correlated to clinically successful bone regeneration.
Keywords: bone morphogenetic protein 2; CD34 antigen; cell surface receptor; collagen; ENG protein, human; Hermes antigen; leukocyte antigen; recombinant bone morphogenetic protein 2; recombinant bone morphogenetic protein 2; recombinant protein; Thy 1 membrane glycoprotein; transforming growth factor beta; alveolar bone grafting; article; bone marrow cell; bone regeneration; controlled clinical trial; controlled study; female; human; injury; male; mandible; mesenchymal stem cell transplantation; mesenchymal stroma cell; middle aged; physiology; randomized controlled trial; surgical sponge; tissue engineering

Surgical swab counting: a qualitative analysis from the perspective of the scrub nurse. - D'Lima, D.; Sacks, M.; Blackman, W.; Benn, J. (Journal of perioperative practice, 2014)
The aim of the study was to conduct a qualitative exploration of the sociotechnical processes underlying retained surgical swabs, and to explore the fundamental reasons why the swab count procedure and related protocols fail in practice. Data was collected through a set of 27 semistructured qualitative interviews with scrub nurses from a large, multi-site teaching hospital. Interview transcripts were analysed using established constant comparative methods, moving between inductive and deductive reasoning. Key findings were associated with interprofessional perspectives, team processes and climate and responsibility for the swab count. The analysis of risk factors revealed that perceived social and interprofessional issues played a significant role in the reliability of measures to prevent retained swabs. This work highlights the human, psychological and organisational factors that impact upon the reliability of the process and gives rise to recommendations to address contextual factors and improve perioperative practice and training.
Keywords: article; clinical nursing research; clinical protocol; foreign body; human; organization; organization and management; perioperative nursing; public relations; surgical equipment

Bromfenac ophthalmic solution 0.07% dosed once daily for cataract surgery: Results of 2 randomized controlled trials - Walters, T.R.; Goldberg, D.F.; Peace, J.H.; Gow, J.A. (Ophthalmology, 2014)
Purpose To evaluate the efficacy and ocular safety of bromfenac ophthalmic solution 0.07% (Prolensa) dosed once daily for the treatment of ocular inflammation and pain in subjects who underwent cataract surgery with posterior chamber intraocular lens implantation. Design Two phase 3, randomized, double-masked, placebo-controlled, multicenter clinical trials. Participants Four hundred forty subjects (440 study eyes: 222 in the bromfenac group and 218 in the placebo group). Methods Two phase 3, prospective, randomized, double-masked, placebo-controlled clinical trials were conducted at 39 ophthalmology clinics in the United States. Subjects 18 years of age or older were randomized to receive either bromfenac 0.07% or placebo dosed once daily beginning 1 day before cataract surgery, on the day of surgery, and continuing for 14 days after surgery (for a total of 16 days). Subjects were evaluated on days 1, 3, 8, 15, and 22 after surgery. The primary efficacy end point was cleared ocular inflammation, as measured by the summed ocular inflammation score of zero (anterior chamber cell count = 0 and absence of flare) by day 15. Secondary end points included cleared ocular inflammation at day 15 and the number of subjects who were pain free at day 1. The data from the 2 clinical trials were integrated for analyses. Main Outcome Measures Summed ocular inflammation score and ocular pain. Results A significantly higher proportion of subjects treated with bromfenac 0.07% achieved complete clearance of ocular inflammation by day 15 and at day 15 compared with placebo (P < 0.0001). A statistically significantly higher proportion of subjects in the bromfenac 0.07% group were pain free at all study visits compared with those in the placebo group (P < 0.0001). Fewer subjects in the bromfenac group (3.2%) discontinued investigational product early because of a lack of efficacy than in the placebo group (23.9%; P < 0.0001). The incidence of adverse events was significantly lower in the bromfenac 0.07% group compared with the placebo group (P = 0.0041). Conclusions Bromfenac ophthalmic solution 0.07% dosed once daily was clinically safe and effective compared with placebo for the treatment of ocular inflammation and pain in subjects who had undergone cataract surgery and may be a beneficial addition to the current standard of care, which commonly includes ophthalmic antibiotics and corticosteroids. © 2014 by the American Academy of Ophthalmology.
Keywords: bromfenac; eye drops; nonsteroid antiinflammatory agent; placebo; prednisolone acetate; aged; anterior eye chamber; article; blurred vision; cataract extraction; cell count; conjunctival hyperemia; controlled study; cornea edema; drug efficacy; drug safety; eye inflammation; eye pain; female; foreign body; human; implant; incidence; intention to treat analysis; intraocular pressure abnormality; lens implantation; major clinical study; male; multicenter study; ocular pruritus; patient compliance; phase 3 clinical trial; photophobia; posterior chamber lens; priority journal; prospective study; randomized controlled trial; prolensa

Risk factors for retained surgical items: A meta-analysis and proposed risk stratification system - Moffatt-Bruce, S.D.; Cook, C.H.; Steinberg, S.M.; Stawicki, S.P. (Journal of Surgical Research, 2014)
Background Retained surgical items (RSI) are designated as completely preventable "never events". Despite numerous case reports, clinical series, and expert opinions few studies provide quantitative insight into RSI risk factors and their relative contributions to the overall RSI risk profile. Existing case-control studies lack the ability to reliably detect clinically important differences within the long list of proposed risks. This meta-analysis examines the best available data for RSI risk factors, seeking to provide a clinically relevant risk stratification system. Methods Nineteen candidate studies were considered for this meta-analysis. Three retrospective, case-control studies of RSI-related risk factors contained suitable group comparisons between patients with and without RSI, thus qualifying for further analysis. Comprehensive Meta-Analysis 2.0 (BioStat, Inc, Englewood, NJ) software was used to analyze the following "common factor" variables compiled from the above studies: body-mass index, emergency procedure, estimated operative blood loss >500 mL, incorrect surgical count, lack of surgical count, >1 subprocedure, >1 surgical team, nursing staff shift change, operation "afterhours" (i.e., between 5 PM and 7 AM), operative time, trainee presence, and unexpected intraoperative factors. We further stratified resulting RSI risk factors into low, intermediate, and high risk. Results Despite the fact that only between three and six risk factors were associated with increased RSI risk across the three studies, our analysis of pooled data demonstrates that seven risk factors are significantly associated with increased RSI risk. Variables found to elevate the RSI risk include intraoperative blood loss >500 mL (odds ratio [OR] 1.6); duration of operation (OR 1.7); >1 subprocedure (OR 2.1); lack of surgical counts (OR 2.5); >1 surgical team (OR 3.0); unexpected intraoperative factors (OR 3.4); and incorrect surgical count (OR 6.1). Changes in nursing staff, emergency surgery, body-mass index, and operation "afterhours" were not significantly associated with increased RSI risk. Conclusions Among the "common risk factors" reported by all three case-control studies, seven synergistically show elevated RSI risk across the pooled data. Based on these results, we propose a risk stratification scheme and issue a call to arms for large, prospective, and multicenter studies evaluating effects of specific changes at the institutional level (i.e., universal surgical counts, radiographic verification of the absence of RSI, and radiofrequency labeling of surgical instruments and sponges) on the risk of RSI. Overall, our findings provide a meaningful foundation for future patient safety initiatives and clinical studies of RSI occurrence and prevention. © 2014 Elsevier Inc. All rights reserved.
Keywords: article; body mass; case control study; emergency surgery; human; meta analysis; nursing staff; operation duration; operative blood loss; patient safety; priority journal; retrospective study; risk assessment; risk factor; surgical risk

Retained surgical sponges: Findings from incident reports and a cost-benefit analysis of radiofrequency technology - Williams, T.L.; Tung, D.K.; Steelman, V.M.; Chang, P.K.; Szekendi, M.K. (Journal of the American College of Surgeons, 2014)
Background Retained surgical items (RSIs) are serious events with a high potential to harm patients. It is estimated that as many as 1 in 5,500 operations result in an RSI, and sponges are most commonly involved. The adverse outcomes, additional medical care needed, and medico-legal costs associated with these events are substantial. The objective of this analysis was to advance our understanding of the occurrence of RSIs, the methods of prevention, and the costs involved. Study Design Incident reports entered into the University HealthSystem Consortium (UHC) Safety Intelligence database on incorrect surgical counts and RSIs were analyzed. Reported cases of retained surgical sponges at organizations that use radiofrequency (RF) technology and those that do not were compared. A cost-benefit analysis on adopting RF technology was conducted. Results Five organizations that implemented RF technology between 2008 and 2012 collectively demonstrated a 93% reduction in the rate of reported retained surgical sponges. By comparison, there was a 77% reduction in the rate of retained sponges at 5 organizations that do not use RF technology. The UHC cost-benefit analysis showed that the savings in x-rays and time spent in the operating room and in the medical and legal costs that were avoided outweighed the expenses involved in using RF technology. Conclusions Current standards for manual counting of sponges and the use of radiographs are not sufficient to prevent the occurrence of retained surgical sponges; our data support the use of adjunct technology. We recommend that hospitals evaluate and consider the use of an adjunct technology. © 2014 by the American College of Surgeons.
Keywords: adverse outcome; article; cost benefit analysis; cost control; human; incident report; intraoperative period; operating room; priority journal; radiofrequency; radiofrequency identification; retained instrument; surgical sponge; technology; X ray

Retained surgical sponges: Findings from incident reports and a cost-benefit analysis of radiofrequency technology - Williams, T.L.; Tung, D.K.; Steelman, V.M.; Chang, P.K.; Szekendi, M.K. (Journal of the American College of Surgeons, 2014)
Background: Retained surgical items (RSIs) are serious events with a high potential to harm patients. It is estimated that as many as 1 in 5,500 operations result in an RSI, and sponges are most commonly involved. The adverse outcomes, additional medical care needed, and medico-legal costs associated with these events are substantial. The objective of this analysis was to advance our understanding of the occurrence of RSIs, the methods of prevention, and the costs involved. Study Design: Incident reports entered into the University HealthSystem Consortium (UHC) Safety Intelligence database on incorrect surgical counts and RSIs were analyzed. Reported cases of retained surgical sponges at organizations that use radiofrequency (RF) technology and those that do not were compared. A cost-benefit analysis on adopting RF technology was conducted. Results: Five organizations that implemented RF technology between 2008 and 2012 collectively demonstrated a 93% reduction in the rate of reported retained surgical sponges. By comparison, there was a 77% reduction in the rate of retained sponges at 5 organizations that do not use RF technology. The UHC cost-benefit analysis showed that the savings in x-rays and time spent in the operating room and in the medical and legal costs that were avoided outweighed the expenses involved in using RF technology. Conclusions: Current standards for manual counting of sponges and the use of radiographs are not sufficient to prevent the occurrence of retained surgical sponges; our data support the use of adjunct technology. We recommend that hospitals evaluate and consider the use of an adjunct technology.
Keywords: radio frequency identification device; adverse outcome; article; controlled study; cost benefit analysis; cost control; health care cost; human; incidence; incident report; intraoperative period; law suit; malpractice; medicolegal aspect; operation duration; predictive value; prevention and control; radio frequency identification device; radiofrequency; radiography; reoperation; retained instrument; retrospective study; risk reduction; sensitivity and specificity; surgical error; surgical sponge; wound closure

Every wound counts: A case of undiscovered wound in mons pubis resulting in a chronic foreign body granuloma of the abdominal wall - Ramman, S.; Al-Rubayee, H. (International Wound Journal, 2014)
A 33-year-old male patient presented to clinic with a tender, discharging wound at mons pubis area. Three months before, he was a victim in a blast injury and received lifesaving emergency laparotomy at a field hospital in Baghdad, where shrapnel was removed from the abdomen and he was subsequently discharged. We present this unusual case of chronic wound from an undiscovered injury that was not formally explored at initial treatment, highlighting the importance of systematic exploration of all wounds particularly in sensitive body areas, despite cultural barriers both for the assessing clinicians and for the patients in that part of the world.
Keywords: abdominal wall; adult; anastomosis; antibiotic therapy; article; attitude to illness; blast injury; case report; chronic disease; clinical feature; debridement; disease duration; foreign body granuloma; human; intestine resection; Iraq; laparotomy; male; medical history; pain severity; pelvis radiography; priority journal; pubis symphysis; skin injury; social stigma; thorax radiography; wound dressing

"count on Me!": Urgent Public Health and Safety Policies to Avoid Complications Associated with Foreign Body Retention in Neurosurgical Procedures, with Special Attention to "miscellaneous Small Items" - Mattei, T.A.; Goulart, C.R. (World Neurosurgery, 2014)
Keywords: clinical practice; clip; computer assisted tomography; diffusion weighted imaging; fever; foreign body; headache; health care policy; health care quality; human; letter; medical society; nausea; neurosurgery; nuclear magnetic resonance imaging; patient safety; posterior lumbar spinal surgery; postoperative complication; postoperative period; public health; retained instrument; soft tissue swelling; spine surgery; surgical drainage; surgical equipment; surgical error; surgical mortality; surgical sponge; swelling

Gossypiboma mimicking a retroperitoneal tumour: A case report and review of literature - George, A.J.P.; Mukha, R.P.; Kekre, N.S. (Indian Journal of Urology, 2014)
Gossypiboma Abstract Background: “Gossypiboma”, or “textiloma” denotes a mass of cotton that is retained in the body following surgery. Gossypiboma is a medico-legal problem especially for surgeons. To the best of our knowledge, the patient presented herein is the first reported patient in whom it mimicked a tumour and following a nephrectomy. Case presentation: A 46-year-old woman presented with right flank pain, for 6 months following a right nephrectomy in 2005 for a non-functioning kidney (biopsy unavailable). On examination abdomen was non-tender and non-distended. An ill-defined non-tender mass was palpable on bimanual examination in the right hypochondrium and lumbar region. A Pfannensteil and right flank scar were present. Plain abdominal radiography did not show any sign of a radio-opaque marker in the abdomen. However, contrast enhanced abdominal computerized tomography revealed a well-defined heterogenous spherical, soft-tissue mass of 13 x 9 x 9cm size in the right renal fossa, with a dense, enhanced wall, abutting the right psoas muscle and right posterior abdominal wall. Right adrenal and contralateral kidney appeared normal. Surgical excision was done which revealed an abdominal sponge surrounded by foreign body granuloma, densely adherent to surrounding structures. Conclusions: Gossypiboma, though rare, can mimick a tumour, and is a diagnostic challenge. There should be a high index of suspicion in patients who have previously been operated and present with non specific complaints and equivocal imaging findings. Prevention is by meticulous count of surgical materials and by use radio-opaque marker impregnated sponges and gauze.
Keywords: marker; human; case report; society; India; neoplasm; patient; examination; telecommunication; kidney; abdomen; nephrectomy; surgery; computer assisted tomography; psoas muscle; biopsy; flank pain; cotton; abdominal radiography; scar; female; hypochondriasis; surgeon; imaging; soft tissue; diagnosis; abdominal wall; adrenal gland; excision; foreign body granuloma; prevention

The perfect count: Multidisciplinary strategy for the prevention of retained surgical items - Bhatti, A.; Ferguson, K.; Duffy, D.; Afshar, K. (Irish Journal of Medical Science, 2013)
Current studies indicate a 0.3-1 % rate of retained surgical items per 1,000 cases in the United States1. This type of adverse event is considered a “never” event; a medical error that should never occur because it is serious and usually preventable. The purpose of this project is twofold; first, to identify risk factors for retained surgical items at BC Children's Hospital and second, to engage front line clinicians in improving current processes for counting and handling incorrect counts. Retrospective chart reviews of the last 50 patients with reported incorrect surgical counts (2012-2013) at BCCH in Vancouver, Canada were conducted to identify common trends. Operating room observations were performed in order to identify themes in team communication and interaction during the count process. Preliminary results from the chart reviews demonstrate trends in the occurrence of incorrect counts and inconsistency in follow-up documentation of investigative measures performed to resolve count discrepancies. Operating theatre observation has enabled the identification of common distractions (e.g.: loud conversations, pagers) and interruptions that can lead to avoidable count discrepancies. Preliminary findings indicate distractions and/or interruptions occurred during the count of 69 % of randomly audited cases. Results indicate that in order to reduce the risk for retained surgical items, we must focus on culture change within the operating theatre that will enhance team communication and aid in the incorporation of evidence-based best practices. Results have also indicated opportunities to improve our current count policy, count process and documentation of the resolution of incorrect counts.
Keywords: school; medicine; summer; student; human; awards and prizes; prevention; operating room; documentation; medical record review; interpersonal communication; follow up; conversation; risk; policy; medical error; Canada; patient; risk factor; evidence based practice; pediatric hospital

Severe pulmonary hemorrhage in patient with group a streptococcal sepsis requiring ECMO - Khilanani, A.; Smith, C. (Critical Care Medicine, 2013)
Introduction: Pulmonary hemorrhage is a condition with high morbidity that can occur as a result of multiple causes; including pulmonary vasculitis, drug toxicity, aspiration of blood, thrombocytopenia, stem-cell transplant, or sepsis. In many cases no definitive cause is identified. Here, we present an unusual pediatric case of severe pulmonary hemorrhage and respiratory failure with group A streptococcus (GAS) septicemia requiring extracorporeal membrane oxygenation (ECMO). To date, there are few case reports that describe pulmonary hemorrhage in the setting of GAS sepsis. In most published reports, patients presented with a typical prodrome of fever and sore throat that was followed by pulmonary hemorrhage and death. To our knowledge, this is the only report of a patient with pulmonary hemorrhage associated with GAS sepsis that progressed to severe hypoxemic respiratory failure requiring veno-arterial ECMO. A 5-year old boy with a history of mild-persistent asthma presented to a local emergency department with acute onset of inspiratory stridor that rapidly progressed to respiratory failure. History was not concerning for infectious symptoms, foreign body ingestion, or an anaphylactic reaction. Direct laryngoscopy revealed significant airway and vocal cord edema. Initial chest x-ray was unremarkable. The child was stable on minimal ventilatory and oxygen support, and transferred to a tertiary care facility. Nasopharyngeal PCR identified parainfluenza. Dexamethasone was administered for laryngotracheobronchitis and he was observed on positive pressure ventilation overnight. 12 hours later, he developed an episode of acute hypoxemia associated with pulmonary hemorrhage requiring high frequency oscillatory ventilation. Chest x-ray demonstrated bilateral infiltrates. He developed new leukopenia and neutropenia (white blood cell 2200, absolute neutrophil count 830) presumably due to sepsis and he was started on vancomycin and ceftriaxone. Clotting times, fibrinogen, and platelet counts were not consistent with disseminated intravascular coagulopathy. There was no laboratory evidence of autoimmune disease and vasculitis. The following day, he developed hypotension with cardiovascular dysfunction requiring a continuous infusion of epinephrine. Blood and endotracheal cultures grew GAS, and clindamycin was added for anti-toxin effects. His oxygenation continued to deteriorate (oxygenation index mid 40's, PaO2/FiO2 ratio of <75) despite a mean airway pressure of 28 cm water pressure, and he was cannulated for veno-arterial ECMO. On ECMO his lungs were recruited with airway positive release ventilation (APRV). There was no further pulmonary hemorrhage and his pulmonary compliance and native gas exchange eventually improved. He was decannulated after 9 days on ECMO and extubated 6 days later. The patient's lack of prodrome and initially negative blood culture on admission suggest that his GAS infection occurred as a superinfection of a primary viral process. V-A ECMO was successfully implemented in this case of GAS sepsis/pneumonitis with pulmonary hemorrhage and cardiorespiratory failure to provide oxygenation and hemodynamic support.
Keywords: fibrinogen; oxygen; vancomycin; ceftriaxone; dexamethasone; epinephrine; clindamycin; toxin; water; intensive care; lung hemorrhage; human; sepsis; hospital patient; society; respiratory failure; oxygenation; patient; blood; airway; air conditioning; pulmonary vasculitis; Streptococcus group A; vocal cord; laryngoscopy; septicemia; extracorporeal oxygenation; soft contact lens; stridor; transplantation; stem cell; thrombocytopenia; mild persistent asthma; positive pressure ventilation; boy; emergency ward; leukocyte; foreign body; ingestion; anaphylaxis; platelet count; disseminated intravascular clotting; edema; vasculitis; child; tertiary care center; Parainfluenza virus infection; laryngotracheobronchitis; death; morbidity; sore throat; thorax radiography; fever; aspiration; hypoxemia; male; leukopenia; neutropenia; neutrophil count; blood clotting time; blood culture; case report; laboratory; autoimmune disease; hypotension; continuous infusion; airway pressure; lung compliance; lung; gas exchange; group A streptococcal infection; superinfection; cardiopulmonary insufficiency; drug toxicity

Intentional foreign object ingestions: Need for endoscopy and surgery - Dalal, P.P.; Otey, A.J.; McGonagle, E.A.; Whitmill, M.L.; Levine, E.J.; McKimmie, R.L.; Thomas, A.C.; Cook, C.H.; Papadimos, T.J.; Reilley, T.E.; Bergese, S.D.; Steinberg, S.M.; et al. (Journal of Surgical Research, 2013)
Background: Intentional ingestion of foreign objects (IIFO) is common in the incarcerated population. This study was undertaken in order to better define clinical patterns of IIFO among prisoners. We sought to determine factors associated with the need for endoscopic and surgical therapy for IIFO. Methods: After obtaining permission to conduct IIFO research in incarcerated populations, study patients were identified by ICD-9 codes. Patient charts were reviewed for demographics; past medical history; IIFO characteristics; and diagnostic, endoscopic, and surgical findings. Univariate and multivariate analyses were performed using statistical software. Results: Thirty patients with 141 episodes of IIFO were identified. The mean number of ingested items per episode was 4.60. Endoscopy was performed in 97 of 141 IIFO instances, with failure to retrieve the ingested object in 21 of 97 cases (22%). Eleven instances (7.8%) required surgical intervention. On multivariate analyses, hospital admission was associated with elevated white blood cell count (odds ratio [OR] 1.4, P < 0.05) and number of items ingested (OR 1.3, P < 0.05). The need for endoscopy was independently associated with ingestion of multiple objects (OR 3.3, P < 0.05) and elevated white blood cell count (OR 1.3, P < 0.05). Surgical therapy was significantly associated with elevated white blood cell count (OR 1.6, P < 0.01) and with increasing number of ingested items (OR 1.07 per item, P < 0.05). Endoscopy is associated with significantly lower odds of surgery (OR 0.13, P < 0.01). Conclusions: Intentional ingestion of foreign objects continues to pose a significant human and economic burden. The need for admission or therapy is frequently associated with leukocytosis. Further investigation is warranted into resource-appropriate triage of patients who present with IIFO. © 2013 Elsevier Inc. All rights reserved.
Keywords: adult; article; clinical article; software; demography; economic aspect; emergency health service; female; foreign body; gastrointestinal endoscopy; gastrointestinal surgery; hospital admission; human; ICD-9; ingestion; leukocyte count; leukocytosis; male; medical history; medical record; priority journal; prisoner

Miscount incidents: a novel approach to exploring risk factors for unintentionally retained surgical items. - Judson, T.J.; Howell, M.D.; Guglielmi, C.; Canacari, E.; Sands, K. (Joint Commission journal on quality and patient safety / Joint Commission Resources, 2013)
An estimated 1,500 operations result in retained surgical items (RSIs) each year in the United States, resulting in substantial morbidity. The rarity of these events makes studying them difficult, but miscount incidents may provide a window into understanding risk factors for RSIs. A cohort study of all consecutive operative cases during a 12-month period was conducted at a large academic medical center to identify risk factors for surgical miscounts. A multidisciplinary electronic miscount reconciliation checklist (necessitating both surgeon and nurse input) was introduced into the internally developed electronic Perioperative Information Management System to build a predictive model for RSI cases. Among 23,955 operations, 84 resulted in miscount incidents (0.35% [95% confidence interval: 0.28% to 0.43%]). Increased case duration was strongly associated with increased risk of a miscount in unadjusted analyses (p < .0001). In the nested case-control analysis, both the case duration and the number of providers present were independently associated with a more than doubling of the odds of a miscount, even after adjustment for one another, the elective/urgent/emergent status of a case, and personnel changes occurring during the case. The finding that both the length of the case and the number of providers involved in the case were independent risk factors for miscount incidents may offer insight into risk-targeted strategies to prevent RSIs, such as postoperative imaging, bar-coded surgical items, and radiofrequency technology. Miscounts trigger use of the Incorrect Count Safety Checklist, which can be used to determine whether a count completed at the procedure's conclusion is consistent across disciplines (circulating nurses, scrub persons, surgeons).
Keywords: age; article; classification; cohort analysis; foreign body; health care quality; hospital personnel; human; risk factor; statistics; surgery; time; United States; university hospital

Miscount incidents: a novel approach to exploring risk factors for unintentionally retained surgical items - Judson, T.J.; Howell, M.D.; Guglielmi, C.; Canacari, E.; Sands, K. (Joint Commission journal on quality and patient safety / Joint Commission Resources, 2013)
BACKGROUND: An estimated 1,500 operations result in retained surgical items (RSIs) each year in the United States, resulting in substantial morbidity. The rarity of these events makes studying them difficult, but miscount incidents may provide a window into understanding risk factors for RSIs. METHODS: A cohort study of all consecutive operative cases during a 12-month period was conducted at a large academic medical center to identify risk factors for surgical miscounts. A multidisciplinary electronic miscount reconciliation checklist (necessitating both surgeon and nurse input) was introduced into the internally developed electronic Perioperative Information Management System to build a predictive model for RSI cases. RESULTS: Among 23,955 operations, 84 resulted in miscount incidents (0.35% [95% confidence interval: 0.28% to 0.43%]). Increased case duration was strongly associated with increased risk of a miscount in unadjusted analyses (p < .0001). In the nested case-control analysis, both the case duration and the number of providers present were independently associated with a more than doubling of the odds of a miscount, even after adjustment for one another, the elective/urgent/emergent status of a case, and personnel changes occurring during the case. CONCLUSIONS: The finding that both the length of the case and the number of providers involved in the case were independent risk factors for miscount incidents may offer insight into risk-targeted strategies to prevent RSIs, such as postoperative imaging, bar-coded surgical items, and radiofrequency technology. Miscounts trigger use of the Incorrect Count Safety Checklist, which can be used to determine whether a count completed at the procedure's conclusion is consistent across disciplines (circulating nurses, scrub persons, surgeons).
Keywords: age; classification; cohort analysis; foreign body; health care quality; hospital personnel; human; risk factor; statistics and numerical data; surgery; time; United States; university hospital

Gossypiboma-a gynecologist's legacy-case report of gossypiboma with severe malabsorbtion - Tuzcuoglu, I.; Karatas, I.; Acilar, K. (Journal of Gastroenterology and Hepatology, 2013)
Objective: Gossypiboma or retained surgical textile is an ubiquitous medical error that is avoidable. It can cause serious morbidity and possibly even mortality. Because it is not anticipated, it is frequently misdiagnosed, and often-unnecessary radical surgical procedures are performed. It should be considered in the differential diagnosis of any postoperative case with unresolved or unusual problems. We report a woman with severe malabsorbtion signs caused by a gossypiboma. Methods: 35 year old woman who admitted to our clinic with abdominal pain, severe waterry diarrhea of 10 stools/day and weight lose with a duration of 6 months. She had a cesarean operation 7 months ago. The patients complaints started after the cesarean operation. Body mass index was 34.3 kg/cm2 (88 kg/ 160 cm). In her physical examination she had a pale skin and she had marked edema in the pretibial areas. Abdominal examination did not reveal a palpable organ or mass as she was obese. In laboratory tests hemoglobin was 8 gr/dl (mcv 69), wbc and plt counts were in the normal range. Albumin was 1.6 gr/dl with normal fasting glucose, liver and renal function tests. INR was in the normal range. Serum Ferritin, B12 levels were markedly low. Tumour markers were in the normal range. Abdominal ultrasound revealed fatty liver, marked ascites in the abdomen. Intestinal walls were markedly thickened and there was an unidetified mass between intestinal walls. Upper gastrointestinal endoscopy findings were not spesific except in the duodenum there was marked white dotting in the mucosa showing intestinal lymphangiectasia while in colonoscopy all the colon and the terminal ileum wall had edema obscuring the vasculature. Results: Abdominal CT and MRI revealed a mass in the right lower quadrant suggesting a closed perforation or a pericaecal abcess. Laparotomy revealed an encapsulated mass of 10 cm in diameter surrounded by omentum, which was removed. The mass turned out to be a forgotten surgical towel used during the previous operation. We could not identify the situation before the operation because the material did not have a radio-opaque marker. Postoperative course was uneventful. Conclusion: Retained surgical materials are seldom reported due to medicolegal implications. Although it is a rare situation in routine clinical practice, Gossypiboma should be considered as a differential diagnosis in the patients who had a diagnosis of intestinal lymphangiectasia and malabsorption. As Gossypiboma may lead to situations which cause mortality, all precautions should be taken to prevent it. Altough human errors cannot be completely abolished, continuous medical training and strict adherence to regulations should reduce the incidence to a minimum. New technologies are needed which will hopefully decrease the incidence of retained foreign bodies. An electronic article surveillance system which uses a tagged surgical sponge that can be identified electronically can be developed. Bar codes can be applied to all sponges, and with the use of a bar code scanner the sponges can be counted on the back table. (Figure Presented).
Keywords: glucose; albumin; cyanocobalamin; tumor marker; hemoglobin; marker; human; gynecologist; gastroenterology; case report; Asian; intestine; mortality; female; patient; intestine wall; edema; intestine lymphangiectasia; differential diagnosis; textile; body mass; surgical technique; examination; diarrhea; malabsorption; weight; liver; kidney function test; physical examination; skin; fatty liver; abdomen; laboratory test; leukocyte; abdominal pain; diet restriction; morbidity; medical error; ferritin blood level; ultrasound; colonoscopy; ascites; gastrointestinal endoscopy; mucosa; duodenum; hospital; ileum; vascularization; perforation; laparotomy; omentum; telecommunication; clinical practice; diagnosis; error; medical education; technology; foreign body; surgical sponge; nuclear magnetic resonance imaging; international normalized ratio

Unusual case of intestinal obstruction by patency capsule for enteroscopy - Garg, S.; Kaur, S.; Dutta, S. (American Journal of Gastroenterology, 2013)
Purpose: Patency capsules are used commonly to test the patency of small bowel prior to performing a capsule enteroscopy. Although these capsules designed to dissolve in the intestine, we encountered a case of intestinal obstruction at the site of ileostomy after ingestion of a patency capsule. A 58-year-old Caucasian woman presented to the emergency room with abdominal pain in the right lower quadrant, around the ileostomy site for 12 hours. It was associated with marked decrease in ileostomy output. She had undergone total colectomy with ileostomy for ulcerative colitis 15 years ago. Recently, she was also diagnosed with iron deficiency anemia for which she had an upper endoscopy, which did not reveal any abnormality. A capsule enteroscopy was scheduled; however, prior to the procedure, it was noticed that the ileostomy opening was small and stenotic. Consequently, a patency capsule was administered to determine the ability of enteroscopy capsule to traverse the small intestine, on the day of presentation. On admission, her examination was remarkable for tenderness around the stoma and diminished bowel sounds. Laboratory evaluation was significant for microcytic hypochromic anemia (Hemoglobin 8.2 g/dL) and leukocytosis (WBC count 12.18 x 103/ml, 90% neutrophils). An upright abdominal X-ray showed a rectangular density (2.3 x 1.3 cm) in the right lower quadrant. CT scan of the abdomen showed the rectangular foreign body to be located in the ileostomy with proximal dilatation and multiple air fluid levels in the small bowel. An ileoscopy was performed which demonstrated an ileal stricture at 3 cms from the stoma. The stricture was dilated with a 12-15 mm CRE balloon. The intact patency capsule was located proximal to the stricture and it was retrieved with a Rothnet. After the procedure, patient's symptoms improved remarkably and she was discharged home with recommendation of push enteroscopy for work up of anemia. Patency capsules are made of lactose impregnated with barium and are designed to start dissolving 40 hours after oral ingestion. The dissolution is supposed to be complete by 80 hours, however, it may remain intact in patients with lactase deficiency. Similarly, in patients with severe stricture the patency capsule may not dissolve due to lack of contact with intestinal lactase. In the literature, there are 5 reported cases of patency capsule induced small bowel obstruction requiring surgery and all of the patients had underlying Crohn's disease or small bowel stricture. Therefore, it appears even patency capsules should be used with great caution in patients with small bowel stricture. Patients should be made aware of the potential complication prior to patency capsule administration.
Keywords: lactose; barium; hemoglobin; lactase; intestine endoscopy; college; gastroenterology; intestine obstruction; human; ileostomy; patient; small intestine; capsule endoscopy; iron deficiency anemia; stoma; ingestion; procedures; female; examination; Caucasian; endoscopy; ulcerative colitis; computer assisted tomography; liquid; push enteroscopy; lactase deficiency; density; neutrophil; total colon resection; emergency ward; abdominal radiography; leukocytosis; intestine; abdomen; foreign body; dilatation; small intestine obstruction; leukocyte count; abdominal pain; anemia; dissolution; laboratory; intestine sound; surgery; Crohn disease

Crohn's disease: An uncommon cause of appendicitis - McLean, L.; Chun, J.; Cross, R. (American Journal of Gastroenterology, 2013)
Purpose: A 48-year-old man with ulcerative pancolitis diagnosed 6 years prior to admission was transferred to our institution with sharp non-radiating right lower quadrant pain. There was no history of fever, chills, nausea, vomiting, or diarrhea. The patient had been in remission on azathioprine 100 mg and mesalamine 2,000 mg per day after a single course of prednisione at the time of diagnosis. Physical exam was significant for tenderness to palpation in the right lower quadrant. The white blood cell count and hemoglobin were normal. A computed tomography scan of the abdomen with oral and intravenous contrast demonstrated an inflammatory process at the cecal apex with associated 5 cm phlegmon. The appendix was not visualized. Mild lymphadenopathy was present. The small bowel and colon appeared normal with the exception of possible narrowing and hypertrophy of the terminal ileum at the ileocecal valve. The patient was diagnosed with appendicitis and managed conservatively with intravenous antibiotics and bowel rest. His diet was slowly advanced and he was discharged home on a 2-week course of ciprofloxacin 500 mg twice daily and metronidazole 500 mg three times daily. Subsequent colonoscopy revealed a 4 cm non-obstructing mass in the cecum. The colon distal to the cecum was normal without mucosal breaks or friability. Biopsies of the cecal mass revealed normal colonic mucosa with mild inflammation and mild architectural change. Diagnostic laparoscopy demonstrated an abnormal appearing inflamed appendix. A laparoscopic appendectomy was performed. The surgical specimen measured 5.6 x 4.5 x 3.0 cm and contained no masses. Architectural distortion, transmural acute and chronic inflammation, and epithelioid cell aggregates with giant cell reaction were present. The patient's diagnosis was changed to Crohn's colitis with appendiceal involvement. Crohn's disease (CD) involves the appendix in up to 50% of patients with colonic CD. CD isolated to the appendix is rare and has been described in fewer than 160 cases. We believe that this is the first report of a patient diagnosed with UC to have his diagnosis changed due to symptomatic appendiceal CD. Symptoms of granulomatous disease of the appendix are similar to acute appendicitis and include fever, right lower quadrant pain, nausea, and anorexia. Other causes of appendiceal granulomatous disease include infection (e.g., Yersinia, Mycobacterium tuberculosis, Campylobacter), foreign body reaction, appendiceal or cecal diverticulitis, chronic beryllium poisoning, and sarcoidosis. Our patient did well post-operatively. Azathioprine and mesalamine were continued.
Keywords: azathioprine; mesalazine; antibiotic agent; ciprofloxacin; hemoglobin; metronidazole; appendicitis; college; gastroenterology; Crohn disease; human; patient; diagnosis; inflammation; nausea; pain; fever; cecum; granulomatosis; diet; intestine; ileocecal valve; berylliosis; ileum; hypertrophy; lymphadenopathy; Mycobacterium tuberculosis; phlegmon; computer assisted tomography; acute appendicitis; anorexia; abdomen; Campylobacter; diverticulitis; small intestine; remission; colitis; leukocyte count; diarrhea; pancolitis; palpation; appendectomy; laparoscopy; colon mucosa; biopsy; chronic inflammation; epithelioid cell; cell aggregation; giant cell; vomiting; colonoscopy; infection; Yersinia; foreign body reaction; sarcoidosis; male

Successful endoscopic management of retained suture related complication in a gastric bypass patient - Aswath, G.; Manocha, D.; Rawlins, S. (American Journal of Gastroenterology, 2013)
Purpose: Gastric bypass (GBP) surgery is becoming an increasingly popular surgery in the management of obesity. Marginal ulcers (MU) are a common immediate/intermediate complication, with reported incidences up to 3-23%. Suture remnants have been seen in ulcer beds in up to 32% of the cases in one study. Mucosal ischemia, foreign body reaction, traction and bezoar like effect of food have been proposed as the mechanisms causing the ulcers. We present the case of a 57-year-old male s/p GBP surgery for obesity 8 months ago, with a 100-pound weight loss coming to the hospital with severe 10/10 epigastric pain with non-bilious, non-bloody vomiting, abdominal distension, and hypoactive bowel sounds. Basic metabolic work-up and blood counts were normal. Abdominal films and CT scan showed multiple air fluid levels. He was kept NPO and was started on IV hydration. EGD was then performed, which showed evidence of a Roux-en-Y gastrojejunostomy. the G-J anastomosis was characterized by congestion, edema, erythema and an impacted suture. This was traversed. the pouch to jejunum limb was characterized by congestion, edema, erythema and ulceration. the duodenumto- jejunum limb was not reached. the impacted sutures were then cut with a hot biopsy forceps. there were multiple ulcerations in the efferent limb over the jejunal folds in a linear pattern consistent with traction injury from the suture. the patient was started on pantoprazole 40 mg twice a day resulting in complete symptom resolution and ulcer healing. Endoscopy is evolving as a novel technique for the management of GBP related complications. Redundant suture is typically regarded as a normal part of the postoperative anatomy. However, they should be considered a potential etiology of chronic pain in symptomatic patients, and removal is shown to be beneficial and helps prevention and healing of the ulcers. Suture cutting can be accomplished with simple hot biopsy forceps or with regular/flexible endoscopic scissors.
Keywords: pantoprazole; gastric bypass surgery; patient; human; college; gastroenterology; suture; ulcer; limb; surgery; jejunum; obesity; traction therapy; erythema; biopsy forceps; edema; vomiting; epigastric pain; jejunum ulcer; body weight loss; injury; hospital; etiology; food; gastrojejunostomy; bezoar; hydration; liquid; computer assisted tomography; anastomosis; foreign body reaction; blood cell count; intestine sound; scissors; abdominal distension; ischemia; ulcer healing; endoscopy; chronic pain; prevention; healing; male; bypass surgery

Current surgical instrument labeling techniques may increase the risk of unintentionally retained foreign objects: A hypothesis - Ipaktchi, K.; Kolnik, A.; Messina, M.; Banegas, R.; Livermore, M.; Price, C. (Patient Safety in Surgery, 2013)
Background: Marking of surgical instruments is essential to ensure their proper identification after sterile processing. The National Quality Forum defines unintentionally retained foreign objects in a surgical patient as a serious reportable event also called "never event.". Presentation of the hypothesis: We hypothesize that established practices of surgical instrument identification using unkempt tape labels and plastic tags may expose patients to "never events" from retained disintegrating labels.Testing of the hypothesis: We demonstrate the near miss of a "never event" during a surgical case in which the breakage of an instrument label remained initially unwitnessed. A fragment of the plastic label was accidentally found in the wound upon closing. Further clinical testing of the occurrence of this "never event" appears not feasible. As the name implies a patient should never be exposed to the risk of fragmenting labels.Implication of the hypothesis: Current practice does not mandate verifying intact instrument markers as part of the instrument count. The clinical confirmation of our hypothesis mandates a change in perioperative practice: Mechanical labels need to undergo routine inspection and maintenance. The perioperative count must not only verify the quantity of surgical instruments but also the intactness of labels to ensure that no part of an instrument is left behind. Proactive maintenance of taped and dipped labels should be performed routinely. The implementation of newer labeling technologies - such as laser engraved codes - appears to eliminate risks seen in traditional mechanical labels.This article reviews current instrument marking technologies, highlights shortcomings and recommends safe instrument handling and marking practices implementing newer available technologies. © 2013 Ipaktchi et al.; licensee BioMed Central Ltd.
Keywords: article; clinical practice; human; hypothesis; materials handling; patient safety; perioperative period; quantitative analysis; retained instrument; risk assessment; risk reduction; surgical equipment; surgical equipment labeling; wound closure

Transepithelial corneal collagen crosslinking for progressive keratoconus in a pediatric age group - Salman, A.G. (Journal of Cataract and Refractive Surgery, 2013)
Purpose: To evaluate the effectiveness and safety of transepithelial corneal collagen crosslinking (CXL) in children with keratoconus and the refractive changes induced by this treatment. Setting: Ophthalmology Department, Ain-Shams University Hospitals, Cairo, Egypt. Design: Prospective comparative case series. Methods: Patients younger than 18 years with bilateral keratoconus had transepithelial CXL with the use of transepithelial riboflavin. The other eye was used as a control and was treated conservatively. The uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and corneal tomography at 12 months were the main outcome measures. Results: The mean age of the 22 patients (22 eyes) was 15.7 years ± 2.1 (SD). After transepithelial CXL, the improvement in the mean UDVA was statistically significant (from 0.95 ± 0.34 logMAR to 0.68 ± 0.45 logMAR) (P<.05). No eye lost lines of preoperative UDVA; 1 eye lost 1 line of preoperative CDVA. There was no improvement in the control group in UDVA or CDVA (P>.05). The mean simulated keratometry (K) decreased by a mean of 2.03 diopters (D), with mean flattening of the apical K by 2.20 D; both results were statistically significant (P<.05). In the control group, the simulated K increased by a mean of 0.59 D (P>.05), with mean steepening of the apical K by 2.9 D (P<.05). No significant changes occurred in the endothelial cell count in either group. Conclusion: Preliminary results of transepithelial CXL in children with keratoconus were encouraging, with no evidence of progression of keratoconus over 12 months. Financial Disclosure: The author has no financial or proprietary interest in any material or method mentioned. © 2013 ASCRS and ESCRS.
Keywords: riboflavin; adolescent; adult; article; cell count; childhood disease; clinical article; comparative study; conservative treatment; controlled clinical trial; controlled study; corneal collagen crosslinking; corneal pachymetry; disease course; Egypt; endothelium cell; female; foreign body; human; hyperemia; keratoconus; keratometry; male; outcome assessment; preoperative period; priority journal; prospective study; radiological procedures; skin defect; therapy effect; tomography; ultraviolet irradiation; university hospital; visual acuity

A 15 year old male with an unusual presentation of coartation of the aorta - Okada, C.R.; Mourani, P.M.; Dobyns, E.L.; Grayck, E.N.; Ibrahim, J.E. (American Journal of Respiratory and Critical Care Medicine, 2013)
Introduction:A case of aortoesophageal fistula from an undiagnosed coarctation of the aorta and mycotic aneurysm presenting with a massive upper gastronintestinal hemorrhage. Case Description:A 15 year old Caucasian male without significant past medical history presented with epigastric pain and hematemesis. He reported 3 weeks of intermittent fevers, malaise, and weight loss. One week prior to admission, he developed epigastric pain that radiated to his back and non-bloody emesis. On the day of admission, he vomited bright red blood with clots. His physical exam revealed an ill-appearing, pale male. His temperature was 38.4°C, and heart rate was 130 beats per minute. His blood pressure was 133/62. He had a systolic ejection murmur at the left sternal border. His upper and lower extremity pulses were normal, but he had delayed capillary refill and cool extremities. He had tenderness to palpation over the epigastrum without peritoneal signs. Labs revealed a hemoglobin of 6.1 g/dL, platelet count of 244,000, INR of 1.41, and prothrombin time of 23 seconds. Blood culture was positive for Streptococcus pneumoniae. He underwent an upper endoscopy, visceral arteriogram, and abdominal CT angiography without identification of bleeding source. Due to continued bleeding, a second visceral arteriogram was done and was extended to include thoracic aortography. This study showed coarcation of the aorta, presumed mycotic aneurysm distal to the coarctation, and an aortoesophageal fistula. He required excision of the infected tissue, repair of the aorta with an interposition graft, repair of esophageal perforation, diversion esophagostomy, gastrostomy tube placement, and prolonged antibiotic therapy. (Figure presented) Discussion: Aortoesophageal fistula represents a rare but often fatal cause of upper gastrointestinal bleeding. The leading causes are esophageal foreign body and congenital cardiac or vascular anomalies with prolonged nasogastric and/or endotracheal intubations. A protracted unrepaired aortic coarctation led to this patient's mycotic aneurysm and subsequent aortoesophageal fistula. Although it is unclear whether echocardiography would have clearly identified the coarctation or mycotic aneurysm, this quick, noninvasive test may have proven useful on two separate occasions. First, prior to his acute presentation, he likely had long-standing hypertension, which could have prompted work-up including evaluation for coarctation. Earlier diagnosis and treatment would have prevented this near-lethal complication. Second, echocardiography may have been a useful in this unstable patient after the initial radiographic studies revealed no source of bleeding. A high index of suspicion and early multidisciplinary intervention are essential for survival of patients with aortoesophageal fistula.
Keywords: hemoglobin; aorta; American; society; male; aortoesophageal fistula; human; mycotic aneurysm; bleeding; patient; arteriography; epigastric pain; echocardiography; blood; vomiting; computed tomographic angiography; blood culture; body weight loss; platelet count; prothrombin time; Caucasian; malaise; palpation; fever; capillary; congenital blood vessel malformation; aortic coarctation; diagnosis; survival; pulse rate; Streptococcus pneumoniae; endoscopy; esophagus foreign body; upper gastrointestinal bleeding; leg; aortography; hematemesis; systolic heart murmur; stomach tube; blood pressure; esophagostomy; esophagus perforation; heart rate; antibiotic therapy; endotracheal intubation; tissue repair; excision; hypertension; temperature; medical history; international normalized ratio

Aspiration of microcrystalline cellulose leading to hypersensitivity pneumonitis-like reaction - Anderson, T.B.; Parsons, J.P. (American Journal of Respiratory and Critical Care Medicine, 2013)
Introduction: Hypersensitivity pneumonitis is a type IV hypersensitivity reaction of the lung to inhaled antigens. Typically organic materials serve as the antigenic stimulus for this reaction. Acute, subacute and chronic manifestations of this condition have been described. Case description: We present a case of a 37 year old white male who is referred to Pulmonary Clinic for evaluation of cough and hypoxia. His medical history was significant for laparoscopic gastric banding for obesity, depression and chronic back pain. Two months prior to presentation he was in his normal state of health when he developed an acute flu-like illness. At that time, he complained of cough, fever and dyspnea that progressed until he ultimately required hospitalization. On admission he was hypoxemic and a CT scan of his chest revealed multi-focal ground glass opacities in his upper lobes along with innumerable centrilobular nodules bilaterally. He did have a peripheral leukocytosis, but all cultures including blood, sputum and bronchoalveolar lavage were negative. Symptoms gradually improved and he was discharged home on 2 liters of continuous oxygen. Over the next two months he developed similar symptoms requiring two subsequent hospitalizations. No infectious etiology was identified to explain his clinical symptoms and pulmonary infiltrates. He was then sent for second opinion. Complete blood count, chemistry, liver function, auto-immune serologies and hypersensitivity pneumonitis panel were all unremarkable. Bronchoscopy revealed slightly inflamed airways but no exudate. Upon removal of the bronchoscope, he coughed up a partially digested pill fragment. Trans-bronchial lung biopsy was negative for infection but did reveal a granulomatous inflammation associated with birefringent rod-like foreign particles. The morphology and histochemical features were consistent with microcrystalline cellulose which is a common tablet filler. He was started on systemic corticosteroids and quickly improved clinically and radiographically. Ultimately, he required revision of his gastric banding to prevent further aspiration events. Discussion: The presence of microcrystalline cellulose in the lungs commonly results from intravenous injection of dissolved oral tablets. This substance along with other tablet excipients like talc, elicit a foreign body granulomatous reaction within the pulmonary vasculature when injected. Rarely, aspiration of pill contents can produce a similar inflammatory response. This patient had recently undergone laparoscopic gastric banding which, although rare, can predispose to aspiration events. The clinical and radiographic syndrome he developed was similar to hypersensitivity pneumonitis. Systemic steroids and antigen removal led to prompt recovery.
Keywords: microcrystalline cellulose; antigen; oxygen; steroid; glass; talc; corticosteroid; excipient; allergic pneumonitis; American; society; aspiration; tablet; gastric banding; foreign body; hospitalization; human; granulomatous inflammation; coughing; lung; pill; influenza; health; male; backache; serology; exudate; lung infiltrate; obesity; etiology; stimulus; sputum; blood; medical history; leukocytosis; lung blood vessel; lung lavage; thorax; computer assisted tomography; blood cell count; liver function; hypoxia; bronchoscopy; airway; bronchoscope; intravenous drug administration; morphology; dyspnea; infection; lung biopsy; fever; diseases; inflammation; patient; hospital; allergic reaction

An unusual black nodule in a renal transplant recipient - Fleming, J.; Howell, S.; Robson, A.; Calonje, E.; Pattison, J.; Attard, N.; Wain, M. (British Journal of Dermatology, 2013)
A 45-year-old diabetic renal transplant recipient attended the transplant dermatology clinic with an 8-week history of an enlarging lesion on her left great toe. She had phototype VI skin, and had been immunosuppressed with tacrolimus 4- 5 mg twice daily and prednisolone 5 mg daily since her renal transplant in October 2011. Four months prior to presentation she underwent a laparotomy for Escherichia coli salpingitis with abscess formation, necessitating treatment with meropenem and discontinuation of mycophenolate mofetil. On examination, she had a solitary, tender 3.5 9 3-cm violaceous and slightly eroded nodule on the dorsal aspect of her left great toe. Full skin examination revealed no other lesions and no lymphadenopathy. Wound swabs grew normal skin flora, white-cell count and C-reactive protein were normal and HIV testing was negative. An incisional biopsy showed a fibrotic dermis and loose granulomatous inflammation with a foreign body giant cell reaction. The giant cells contained pigmented fungal elements and hyphae; periodic acid-Schiff and Grocott staining further highlighted fungi. Ziehl-Neelsen and Wade Fite were negative for acid fast bacilli and Gram staining was negative. The features were consistent with a deep fungal infection with black fungus or phaeohyphomycosis. Culture of the fungi then grew Exophiala jeanselmei. The patient was reviewed by the renal team and her tacrolimus dose was reduced gradually to 2 mg twice daily and she was commenced on voriconazole 200 mg twice daily. At review, 5 weeks into treatment, the lesion had reduced in size, and no new lesions or lymphadenopathy had developed. In conjunction with the renal and microbiology teams, we plan to continue voriconazole for 6 months and hope to avoid surgical intervention. E. jeanselmei is a dematiaceous fungus seen widely in plants, soil, water and decaying wood. Despite being a natural saprophyte, it is pathogenic in humans and the Exophiala species are part of a family of infectious fungi termed phaeohyphomycosis. These can produce subcutaneous infections such as mycetoma and chromoblastomycosis. Such infections are usually acquired via traumatic inoculation and are often associated with immunosuppression. As well as infection in subcutaneous tissues, prosthetic valvular vegetations, fungaemia and disseminated infections due to Exophiala spp. have been reported. While there is no standard treatment, combination surgical and antifungal treatment is usually required. Amphotericin B, flucytosine, itraconazole and terbinafine have been used. Prompt diagnosis of this rare opportunistic fungal infection ensures treatment can commence prior to systemic dissemination. A multi disciplinary approach with renal, microbiology, mycology, histology and dermatology input is essential for the successful management of such cases.
Keywords: tacrolimus; voriconazole; prednisolone; C reactive protein; flucytosine; periodic acid; mycophenolate mofetil; soil water; meropenem; antifungal agent; amphotericin B; itraconazole; terbinafine; kidney graft; graft recipient; dermatologist; human; fungus; infection; Exophiala; microbiology; phaeohyphomycosis; mycosis; giant cell; lymphadenopathy; hallux; dermatology; salpingitis; acid fast bacterium; abscess; dermis; transplantation; diabetes mellitus; leukocyte count; Escherichia coli; fungemia; HIV test; biopsy; granulomatous inflammation; diagnosis; fungus hyphae; staining; mycetoma; skin flora; Gram staining; skin; wound; patient; saprotroph; laparotomy; skin examination; plant; examination; surgery; hope; species; chromomycosis; inoculation; immunosuppressive treatment; subcutaneous tissue; vegetation; hospital; mycology; histology; Human immunodeficiency virus

Pediatric infectious endophthalmitis: A case series - Jones, B.; Athwal, L.; Zarbin, M.; Langer, P.; Bhagat, N. (Investigative Ophthalmology and Visual Science, 2013)
Purpose To describe the etiology, diagnosis, management, and outcomes of pediatric infectious endophthalmitis cases at University Hospital, Newark, NJ over 11 years, 2001-2011. Methods Retrospective series. Data were collected on demographics, presenting clinical findings, management, culture results, and visual and anatomic outcomes. Results Seven cases of infectious pediatric endophthalmitis were identified in six patients. Two patients were male, and four were female. Mean presenting age was 6 years (range 4 weeks to 16 years). The most common etiology was trauma, accounting for 3 out of 7 cases (43%), of which one featured an intraocular foreign body. Two of 7 cases were caused by endogenous bacterial spread (29%), and 2 of 7 were secondary to bleb infection (29%). Patients presented most commonly with symptoms of pain (71%), photophobia (43%), and blurred vision (43%) and signs of vitritis (100%), anterior chamber fibrinous exudates (57%), conjunctival hyperemia (57%), chemosis (71%), and hypopyon (29%). All 3 trauma cases had uveal prolapsed in zone III. None presented with retinal detachment. Only one of three vitreous cultures was positive (33%) and grew Group B Streptococcus. Three cases underwent both pars plana vitrectomy (PPV) and intravitreal antibiotics (43%), and one only intravitreal antibiotics (14%). Best recorded visual acuity after resolution of infection was 20/400 in one patient, counts fingers in another, and no light perception in the remaining 5 eyes. One underwent primary enucleation (14%), one secondary enucleation (14%), and 2 became phthisical (29%). Conclusions Endophthalmitis is a rare but calamitous condition usually resulting in blindness. Our small series finds traumatic open globe injury as the most common cause of infectious endophthalmitis. Despite emergent treatment, patients are frequently left with no light perception in the affected eye.
Keywords: antibiotic agent; adolescent; anterior eye chamber; blindness; blurred vision; case study; chemosis; child; complication; conference abstract; conjunctival hyperemia; endophthalmitis; exudate; female; finger; human; hypopyon; intraocular foreign body; major clinical study; male; nonhuman; pain; pars plana vitrectomy; perception; photophobia; preschool child; retina detachment; retrospective study; Streptococcus agalactiae; visual acuity; vitreous body; vitritis

Sugammadex: A one-year prospective audit of its use - Bramma, Y.L.; Alcorn, D. (European Journal of Anaesthesiology, 2013)
Background and Goal of Study: Our hospital has a total of 13 in-patient theatres and we report on a one year audit of our department's experience of the use of Sugammadex for the reversal of neuromuscular blockade. We sought to gain an idea of common specific indications for its use, following pressure to justify the rising drug budget for this relatively new agent. Anaesthetists were asked to fill in an audit form every time Sugammadex was used. Materials and Methods: The reason for using the drug, which NDMR, time from last dose, TOF count, whether the patient was extubated, age, discharge destination, co-morbidities, operation, and other comments were all recorded. We also asked if Sugammadex was used to reverse blockade, did the drug prevent an ITU admission. The audit form was kept next to the Sugammadex in theatre recovery's drug cupboard. Results and Discussion: 72 audit forms were completed (6 patients had no form or missing data) over a one year period. While many patients had multiple co-morbidities, obesity (30), IHD (27), Age>75 (20), Tachycardia (20) and COPD (19) were the most common. 47 patients were admitted to the ward, 21 to HDU, 2 to labour ward and interestingly, only 2 in a year were admitted to ITU. Added comments (though subjective) showed that at least 7 ITU admissions were prevented, and about the same number of HDU admissions. Only one patient received Sugammadex following an RSI, though he was extubated successfully 20 minutes later. All patients got rocuronium as the NDMR. No patients were given Sugammadex in a “Can't Intubate, Can't Ventilate” situation. Conclusion(s): While Sugammadex has been available in Scotland for over 3 years, at present the SMC only recommends its use in the reversal of profound blockade following RSI using rocuronium1. The use to facilitate extubation in the context of serious co-morbidities has been studied and its ability to reverse profound blockade has also been shown2,3. We conclude that our use has been appropriate and has reduced costs by preventing ITU and HDU admissions.
Keywords: sugammadex; rocuronium; clinical audit; human; anesthesiology; patient; morbidity; ward; neuromuscular blocking; tachycardia; obesity; anesthesist; budget; hospital patient; hospital; United Kingdom; extubation

The assessment of history, physical examination, radiological findings and bronchoscopic findings of childhood tracheobronchial foreign body aspirations - Can, B.; Şen, M.C.; BaŞaklar, A.C.; Sönmez, K.; Türkyilmaz, Z.; Karabulut, R. (European Surgical Research, 2013)
Introduction: Foreign body aspiration (FBA) is still an important cause of mortality and morbidity in all over the world which is preventable. in this study, the analyse of our clinical data of the patients who underwent bronchoscopy for FBA and review of the literature was done. Objectives: The aim of the study is to analyse the epidemiological and clinical data of the patients who underwent bronchoscopy for FBA from November 2006 - August 2012 at Gazi University Faculty of Medicine Pediatric Surgery Department, retrospectively and to compare the findings with the literature to determine preventing strategies. Material/Patients and Methods: The patients' genders, ages, symptoms, physical findings, witnessed choking crisis, the activity during event, time elapsed from aspiration to presentation, radiological findings, type of the bronchoscopy, presentation of foreign body (FB), negative bronchoscopy rate, type of the FB, localization of the FB, complications, hospital stay, white blood cell counts, existance of siblings, diagnosis and treatment for upper respiratory tract infections before bronchoscopy, the medications applied before and after bronchoscopy were recorded after an archive scanning. Results: 35,82% of the patients were girls, 64,18% were boys. the median age was 31,1 months. FBA mostly seen in 1-3 age group (71,64%). a FB was found in 79,1% of patients, the negative bronchoscopy rate was 20,9%. 87,74% of FBs were organic and 12,26% were inorganic. Most common organic FBs were hazelnut, seed and walnut (respectively 18%, 16% and 14%). the FBs were found 49,53% in the right and 41,69% in the left bronchial tree. But in the group of 1-3 age the left and right bronchial tree localizations were found equal (43,84%). 26,87% of patients were presented with a history of aspiration at the same day and 14,93% with a history of more than 2 weeks. Adult presentation during the aspiration was 77%. Most common sypmtoms were wheezing (30,1%) and coughing (29,77%). Most common oscultation findings were unilateral loss of breath sounds (33,33%) and wheezing (20,11%). Most common radiological finding was unilateral air trapping with 66% the radiological examination were normal in 35,82% of the patients. Steroids, ventolin and antibiotics were given 39,55%, 55% and 93% respectively. 52,9% of the patients had siblings. 42,54% were diagnosed and treated for upper respiratory tract infections before bronchoscopy. Mean hospital stay was 1,9 days the complication rate was 8,9% and the mortality rate was 0%. Conclusion: FBA is a worldwide public health problem in pediatric population the numbers of cases can be reduced by determining proper preventions for the children under risk. It is needed to define regulatory standards for baby and child products manufacture and appropriate labelling practices like developed countries; public education campaigns and enhancing the public awareness about FBA.
Keywords: steroid; salbutamol; antibiotic agent; foreign body aspiration; human; childhood; society; surgery; physical examination; bronchoscopy; patient; aspiration; upper respiratory tract infection; wheezing; tracheobronchial tree; mortality; hospitalization; child; sibling; clinical study; drug therapy; diagnosis; male; abnormal respiratory sound; public health problem; leukocyte count; coughing; female; adult; foreign body; morbidity; walnut; plant seed; hazelnut; gender; groups by age; boy; radiodiagnosis; pediatric surgery; baby; girl; risk; population; prevention; information center; university; developed country; education

Generalized vesicular skin lesions presented at birth in a newborn - Davila-Seijo, P.; Florez-Menendez, A.; De La Torre, C.; Vilas-Gonzalez, J. (Journal of the American Academy of Dermatology, 2013)
Background: Congenital cutaneous candidiasis (CCC) is a rare disease that results from infection from Candida spp. acquired in utero. Case report: A full-term, 3350-g male infant was delivered by cesarean section to 29-year-old healthy woman because of fetal distress. Vaginal candidiasis, diagnosed by culture, was managed with topical therapy during the first trimester of pregnancy. No history of membranes rupture before deliver was recorded. The child presented at birth with generalized erythematous maculopapular and vesicular skin lesions over the face, trunk, and extremities, including palms and soles. The scalp and mucous membranes were spared. The remainder of the physical examination was normal. His white blood cell count was 26,000/mm3 with 71% polymorphonuclear cells, 19% lymphocytes, and 6% eosinophils. Cerebral and abdominal ecography were normal. Cultures of the blood, urine, and spinal fluid were normal. Culture of vesicle exudate was positive to Candida albicans. Skin biopsy revealed intra-epidermic pustule dermatitis. Funguses within stratum corneum were showed with periodic acideSchiff stain. Topical ketoconazol was started with progressive resolution of lesions. He was discharged from the hospital on the ninth day of life without sequelae. Discussion: The CCC is though to appear by the ascension of organism from candidal vulvovaginitis during pregnancy. CCC can produce a clinical spectrum of disease ranging from a cutaneos skin eruption without systemic involvement to a severe systemic disease with a potential risk of neonatal death. Risk factors to CCC are history of maternal candidal vulvogaginitis, intrauterine foreign body, prematurity and low birth weight <1000g. Premature low birth weight infants show higher risk of systemic involvement. The most common cutaneous presentation is a generalized eruption of erythematous macules, papules, vesicles and pustules that appears within the first six days of birth. Palms and soles are usually affected. Isolated nail dystrophy has also been documented. CCC is diagnosed by the evidence of fungus structures in the skin scrapings and skin biopsy and the positive cultures from lesions. Topical fungal therapy may be used in isolated skin involvement but systemic therapy should be used if systemic disease is suspected. We present a new case of this rare entity with lesions present at birth, in which the only identifiable risk factor, maternal vaginal candidiasis, was diagnosed and treated at the first trimester.
Keywords: ketoconazole; skin defect; newborn; dermatology; human; fungus; pregnancy; low birth weight; skin biopsy; vagina candidiasis; pustule; systemic disease; risk; skin; risk factor; first trimester pregnancy; rupture; membrane; case report; Candida albicans; skin candidiasis; cerebrospinal fluid; urine; topical treatment; blood; eosinophil; Candida; fetus distress; lymphocyte; therapy; infection; exudate; female; newborn death; cesarean section; rare disease; dermatitis; polymorphonuclear cell; leukocyte count; vulvovaginitis; boy; rash; organisms; physical examination; hospital; mucosa; foreign body; prematurity; male; stain; scalp; stratum corneum; child; papule; nail dystrophy; systemic therapy

Silastic synovitis: A case and review of the literature - Seth, R.; McCrae, F. (Rheumatology (United Kingdom), 2013)
Background: A 50-year-old lady presented with a 5-month history of persistent left wrist pain and swelling. She was known to have degenerative cystic changes in the base of the thumb metacarpal and had had a left thumb carpometacarpal joint arthroplasty and resection of the trapezium with insertion of a Swanson Silastic implant 4 years previously in 2008. Her past medical history included ovarian carcinoma 7 years ago. For her wrist pain, she was taking naproxen and paracetamol which helped provide some pain relief. Her niece has RA. She was a 30-pack year smoker and drank a minimal amount of alcohol. She worked in a warehouse, which involved heavy manual work. Examination revealed left wrist synovitis with reduced range of movement. She also had some tenderness around the left 3rd and 4th PIPJ. In comparison, examination of her right wrist was normal. Examination of her nails, skin, and other joints was unremarkable. Her cardiorespiratory and abdominal examinations were also unremarkable. Methods: Initial investigations including rheumatoid factor, anti-CCP, ANA and inflammatory markers and radiographs of the hands and wrists were performed. Further investigations included a MRI of the left wrist and a synovial biopsy. Results: Blood tests revealed a negative rheumatoid factor and ANA, and her anti-CCP was normal. Her ESR 17, CRP<5 and normal full blood count, renal and liver function. A radiograph of the left wrist showed a previous left trapeziectomy with a silastic prosthetic replacement. There was evidence of a considerable erosive process affecting her carpometacarpal, carpal and radiocarpal joints of the left wrist. This suggested that the arthropathy was crossing ligamentous boundaries. Fracture was excluded. A MRI scan of her left wrist (with gadolinium) was performed and confirmed the presence of an erosive process and a suggestion of fragmentation of the implant. A synovial biopsy was then taken. Histopathology of the left wrist synovium revealed multiple pale grey fragments together measuring 0.7x0.7x0.3 cm. Microscopy showed a florid giant cell reaction to refractile, granular material. The appearances were consistent with previous surgery at this site with a giant cell reaction to foreign material. The acid-fast bacilli culture was negative. Conclusions: This patient's wrist pain was due to a giant cell synovitis secondary to particulate silastic from a previous silastic implant. Silastic synovitis can occur at any joint where there is a prosthetic implant in place. Involvement of the hand and wrist is however most common at the carpal bones which are more susceptible to stress forces. An inflammatory process occurs in response to foreign particles, which are sloughed off the implant, resulting in erosion of bone and articular cartilage with intraosseous cystic changes. Histopathology reveals an inflammatory infiltrate with giant cells around silicone-elastomer particles. A review of the literature will also be presented.
Keywords: silastic; rheumatoid factor; alcohol; paracetamol; naproxen; gadolinium; marker; alprazolam; rheumatology; society; synovitis; health practitioner; human; wrist; examination; giant cell; wrist pain; X ray film; surgery; silicone prosthesis; thumb; joint biopsy; histopathology; foreign body; implant; ovary carcinoma; skin; arthroplasty; swelling; nuclear magnetic resonance imaging; carpal bone; analgesia; manual labor; synovium; arthropathy; blood cell count; blood; liver function; prosthesiology; fracture; microscopy; acid fast bacterium; patient; endoprosthesis; inflammation; bone; articular cartilage; inflammatory infiltrate; medical history; carpometacarpal joint; smoking

Severe diffuse alveolar haemorrhage after TAVI with CoreValve in patient with AAV and Horton disease in remission. An immuno-allergic reaction? - Gregorini, G.A.; Fiorina, C.; Bonetti, M.F. (Presse Medicale, 2013)
Introduction.- Transcatheter aortic valve implantation (TAVI) has recently emerged as alternative treatment for symptomatic aortic stenosis in pts at high surgical risk. Two bioprosthesis valves are commonly implanted nowadays, one is the self-expanded valve - Medtronic CoreValve, a valve in porcine pericardium mounted on a nitinol stent. Usually a transient increase of inflammatory indices and mild fever are observed 24-48 h post-TAVI. Results.- A 81-year-old male patient (pt) was admitted to cardiology Department in October 2012 for a planned TAVI with CoreValve. At admission he was afebrile, the chest X-ray showed no lesions, CRP and ANCA were negative. He only presented new slight anemia (Hb 10.3 g/dl) (FOB repeatedly positive, pt on OAT). Since January 2007 pt was seen at the vasculitis clinic because of anti-MPO positive MPA. Pt was treated with steroids and ev cyclophosphamide and then with Methotrexate until February 2010. In May 2010 he started to complain of symptoms that in Nov 2010 were found consistent with Horton arteritis. He resumed steroids and symptoms remitted. At the time of admission, the steroid dosage was 7.5 mg/day. TAVI was uneventful except for a valve in valve procedure due to a “low” valve implantation with a final mild aortic regurgitation. Twelve hours later, pt developed a rash that persisted for 4 days. From day 5, severe increase in CRP with normal procalcitonin values and reduction in plts count (nadir on the day 680,000/μl) were demonstrated. On day 6, pt started to complain of shortness of breath and hemoptysis, and from day 8, of fever. Chest X-ray and CT-scan showed diffuse interstitial-alveolar infiltrates. ANCA were confirmed negative as were anti-GBM, anti-DsDNA, anti-phospholipids. Complement fractions were normal. Sputum cultures were repeatedly negative, as was an extensive work up for infectious conditions. Normal valve position and ventricular function were demonstrated by frequent echocardiographic controls. Pt was treated with steroids and supportive care. Pt continued to cough blood until day 19 and 20, when he was treated with nebulized rFVIIa that stopped bleeding. After a transient improvement of clinical and radiological picture, respiratory conditions deteriorated and on day 32 pt died. Autopsy revealed hyperemic lungs at gross examination, with firm gray-brown or pale edematous areas. Histologically pneumonia organizing aspect was prevalent, associated to rare suppurative foci. Only minimal intra-alveolar blood was observed at the periphery of organizing areas. Both septal and interstitial vessels were dilated and congested. Only focal alveolar or interstitial hemosiderin-laden macrophages were present at Pearls stain. Conclusion.-The clinical spectrum of diffuse alveolar haemorrhage is wider than previously considered. Besides the well-known vasculitic syndromes, immune or hypersensitivity reactions to medications and foreign materials, direct toxic effects to alveolar capillaries, coagulation defects, hemodynamic and vascular conditions, infectious causes should be taken into account. Identification of different causes and treatment based on the different etiologies are challenging tasks.
Keywords: steroid; methotrexate; cyclophosphamide; procalcitonin; phospholipid; hemosiderin; temporal arteritis; human; hospital patient; lung hemorrhage; remission; allergic reaction; vasculitis; workshop; transcatheter aortic valve implantation; thorax radiography; blood; fever; computer assisted tomography; patient; male; rash; dyspnea; cardiology; nitinol stent; procedures; pericardium; bioprosthesis; arteritis; implantation; aortic regurgitation; macrophage; hemoptysis; surgical risk; pneumonia; aortic stenosis; lung; hospital; autopsy; bleeding; examination; coughing; heart ventricle function; sputum culture; stain; drug therapy; foreign body; toxicity; capillary; blood clotting disorder; etiology; anemia

Retained surgical sponges, needles and instruments - Hariharan, D.; Lobo, D.N. (Annals of the Royal College of Surgeons of England, 2013)
Introduction Retained sponges and instruments (RSI) due to surgery are a recognised medical 'never event' and have catastrophic implications for patients, healthcare professionals and medical care providers. The aim of this review was to elucidate the extent of the problem of RSI and to identify preventative strategies. Methods A comprehensive literature search was performed on MEDLINE®, Embase™, the Science Citation Index and Google™ Scholar for articles published in English between January 2000 and June 2012. Studies outlining the incidence, risk, management and attempts to prevent RSI following surgical intervention were retrieved. Results The overall incidence of RSI is low although its incidence is substantially higher in operations performed on open cavities. Sponges are the most commonly retained item when compared with needles and instruments. Clinical presentation is varied, leading to avoidable morbidity, and the error is indefensible medicolegally. Risk factors include emergency operations, operations involving unexpected change in procedure, raised body mass index, and a failure to perform accurate sponge and instrument counts. The existing strategy for prevention is manual counting of sponges and instruments undertaken by surgical personnel. This, however, is fallible. Computer assisted counting of sponges using barcodes and gauze sponges tagged with a radiofrequency identification device aiding manual counting have been trialled recently, with success. Conclusions Vigilance among operating theatre personnel is paramount if RSI is to be prevented. Prospective multicentre trials to assess efficacy of new technologies aiding manual counting should be undertaken if this medical error is to be eliminated completely.
Keywords: early diagnosis; foreign body; human; incidence; medical error; needle; review; risk factor; surgical equipment; surgical sponge

Stromal rejection after big bubble deep anterior lamellar keratoplasty: Case series and review of literature - Sharma, N.; Kandar, A.K.; Singh Titiyal, J. (Eye and Contact Lens, 2013)
PURPOSE:: The aim of this study was to report three cases of stromal rejection after deep anterior lamellar keratoplasty using big bubble technique in keratoconus. METHODS:: Deep anterior lamellar keratoplasty was performed in 3 cases of keratoconus (11-19 years of age) using the "big bubble" technique. All of them presented 4 to 19 months after uneventful surgeries with variable decrease of vision (1/200-20/200) along with foreign body sensation, mild pain, and corneal edema. Suture infiltrates were present in all eyes. Ultrasound pachymetry showed variable increase in central corneal thickness (711-894 μm). These patients with stromal rejection were administered pulse intravenous methylprednisolone, 500 mg in 150 mL of 5% dextrose and were started on 1% prednisolone acetate eye drops 1 hourly, moxifloxacin hydrochloride 0.5% 4 times a day along with homatropine 2% eye drops 4 times a day. RESULTS:: Complete recovery of the stromal rejections was attained with clear graft and recovery of visual acuity (≥20/40) in all eyes. Central corneal thickness returned to prerejection values in all the eyes after 7 days. There was no significant change in specular count. CONCLUSIONS:: Deep anterior lamellar keratoplasty does not eliminate the risk of stromal rejection. Suture-related factors in the form of suture infiltrates and loose suture are an important risk factor for graft rejection. Graft rejection if treated promptly is reversible. © 2013 Lippincott Williams & Wilkins.
Keywords: betamethasone; dexamethasone; fluorometholone; homatropine; methylprednisolone sodium succinate; moxifloxacin; povidone iodine; pred acetate; prednisolone acetate; steroid; unclassified drug; adult; big bubble technique; case report; central corneal thickness; child; cornea edema; deep anterior lamellar keratoplasty; eye discomfort; eye pain; eye redness; female; graft rejection; human; inflammatory infiltrate; intraocular foreign body; keratoconus; keratoplasty; male; medical literature; medical procedures; nylon suture; pachymetry; priority journal; review; risk factor; school child; slit lamp; Staphylococcus aureus; suture; visual acuity; visual disorder; pred acetate; solu medrol; vigamox

Intentional foreign object ingestions: Determining factors associated with hospital admission, therapeutic endoscopy, and surgery - Dalal, P.P.; Otey, A.J.; McGonagle, E.A.; Whitmill, M.L.; Thomas, A.C.; Cook, C.H.; Papadimos, T.J.; Reilley, T.E.; Bergese, S.D.; Steinberg, S.M.; Stawicki, S.P.; Evans, D.C. (Journal of Surgical Research, 2013)
Introduction: Intentional ingestions of foreign objects (IIFO) are often associated with compulsive behavioral patterns and constitute a manifestation of a more profound, chronic underlying problem. This study was undertaken in order to better define clinical patterns of IIFO among predominantly incarcerated individuals admitted to a major academic institution. We sought to determine factors associated with IIFO-attributable hospital admission and procedural (both endoscopic and surgical) therapy. Methods: After obtaining IRB and state permission to conduct IIFO research in both incarcerated and non-incarcerated populations, study patients were identified by CPT codes. The following variables were collected: patient demographics; past medical history (including psychiatric conditions); characteristics related to recurrent IIFO events, hospital admission data, diagnostic testing, and endoscopic/surgical procedure information. Univariate and multivariate analyses were performed using SPSS 19. Results: 30 patients (26 male, mean age 25 years) with a total of 141 episodes of IIFO were identified. Nine patients (30%) had history of IIFO; 27 (90%) reported psychiatric diagnosis; and 10 (33%) had history of substance abuse. The median number of known IIFO's per patient was 3 (range 1-27, mean 4.7). The median number of days between episodes of IIFO was 33 (range 1-1563, mean 116). Mean therapeutic duration (i.e., emergency and/or hospital services) was 41 hours per episode. Most commonly ingested item types, alone or in combination, included plastic utensils (61/141), pens/pencils (57/141), toothbrushes and razor blades (24/141 each). The mean number of ingested items was 4.60 (median 2, range 1-68). Most ingested objects were >5 cm in largest dimension (97/141) and were identified on plain imaging. Endoscopy was performed in 98/141 IIFO instances, with failures to retrieve the ingested object in 20/98 (20%) cases. Fifteen instances (10.6%) required surgical intervention. On multivariate analyses, hospital admission was associated with elevated white blood cell count (OR 1.4, p<0.04) and post-gastric location of the ingested object (OR 22.9, p<0.034). The need for endoscopy was independently associated with ingestion of multiple objects (OR 4.6, p<0.03). Surgical therapy was significantly associated with elevated white blood cell count (OR 1.5, p<0.01) and with increasing number of ingested items (OR 1.086 per item, p<0.04). Endoscopy is associated with significantly lower odds of surgery (OR 0.16, p<0.01). Conclusion: Intentional ingestions of foreign objects continue to pose a significant human and economic burden. Most ingestions involve incarcerated individuals swallowing easily obtainable items of daily use. Prompt endoscopy may reduce admissions and prevent surgical interventions. Further investigation is warranted into methods of preventing recurrence of clinically significant IIFO and resource-appropriate triage of patients who present with IIFO.
Keywords: plastic; surgery; human; hospital admission; surgeon; endoscopy; society; university; ingestion; diagnosis; patient; multivariate analysis; leukocyte count; procedures; imaging; medical history; hospital service; Current Procedural Terminology; emergency; substance abuse; psychiatric diagnosis; toothbrush; male; population; swallowing; emergency health service; therapy

Inflammatory pseudotumor of liver secondary to migrated fishbone - A rare cause with an unusual presentation - Srinivasan, U.P.; Duraisamy, A.B.; Ilango, S.; Rathinasamy, A.; Chandramohan, S.M. (Annals of Gastroenterology, 2013)
A 35-year-old woman presented with a history of vague epigastric pain which lasted for one day. She had no other gastrointestinal symptoms and had an unremarkable past history and physical examination. An ultrasound scan abdomen showed a 3x3.5 cm mass in the left lobe of liver. A CT scan showed an abnormal hypodense lesion with mild enhancement in the arterial phase, with a central calcification. Complete blood count, liver function test and alpha-fetoprotein were normal. A left lateral segmentectomy was performed after adequate pre-operative assessment. The specimen contained a 3 cm long fishbone. The post-operative period was uneventful. Histopathological examination revealed chronic non-specific inflammation with fibrosis. Inflammatory pseudotumor of liver is a rare benign tumor with uncertain etiopathogenesis. Suggested etiologies include a septic or a viral origin and it can occur after migration of sharp objects, including migrated fishbone. Inflammatory pseudotumor of liver can be a diagnostic challenge and may end up in major resection. © 2013 Hellenic Society of Gastroenterology.
Keywords: adult; article; case report; computer assisted tomography; contrast enhancement; echography; epigastric pain; female; foreign body; histopathology; human; human tissue; hepatic inflammatory pseudotumor; laparoscopy; laparotomy; liver fibrosis; liver surgery; pseudotumor

Surgical safety practices in Pakistan - Toor, A.A.; Nigh-e-Mumtaz, S.; Syed, R.; Yousuf, M.; Syeda, A. (Journal of the Pakistan Medical Association, 2013)
Objectives: To evaluate the current practices regarding formal or informal implementation of individual elements of the World Health Organisation's Surgical Safety Checklist in tertiary care hospitals of Karachi and to establish a pre-checklist baseline to suggest a plan for implementation of the checklist. Methods: The qualitative knowledge-attitude-practice (KAP) survey was conducted from May 1, 2009 to January 31, 2010, during whch 103 surgeries were observed in 10 hospitals across Karachi based on simple stratified sampling. Initially, 15 tertiary care hospitals were selected, but response and consent was received from 10 of them. The WHO checklist was applied after some basic changes according to local needs and perspectives. The surgical teams were also observed for coordination and working harmony. The data was analysed on SPSS version 12 and statistical tests were applied accordingly. Results: Of the 103 surgeries observed, 13 (13.4%) patients did not confirm their identity, site of surgery or procedure. There was no concept of timeout in 91 (88.5%) cases, while in 52 (53.8%) cases, the anaesthetist did not ask for known allergy, and prophylaxis antibiotic was not given in 36 (37.5%) cases. In 20 (21.2%) cases, sponge, needle and instruments were not counted. Conclusion: The results suggest that the safety of surgical patients in the operating theaters in hospitals under review was far from satisfactory. Introduction of and adherence to a safety checklist would result in significant reduction in death and complication rate.
Keywords: allergy; anesthesist; antibiotic prophylaxis; checklist; health care survey; human; multicenter study; needle; operating room; questionnaire; review; surgical equipment; surgical patient; surgical sponge; surgical technique

Sympathetic ophthalmia with sensorineural deafness - report of a case - Venkatesh, R.; Agarwal, M.; Ramesh, V.J.; Singh, S.; Kantha, M.; Biswas, J. (Journal of Ophthalmic Inflammation and Infection, 2013)
Background: The aim of this study is to report a case of sympathetic ophthalmia with sensorineural hearing loss following penetrating trauma. This is an interventional case report. A 23-year-old male presented with bilateral, sudden, profound visual and hearing loss, disorientation, and dizziness. He had a past history of penetrating trauma with an iron rod in the right eye for which he underwent scleral tear repair, vitreo-retinal surgery with intraocular foreign body removal and silicon oil injection. His best corrected visual acuity in the right eye was counting fingers close to the face and was perception of light in the left eye. Clinical evaluation with slit biomicroscopy, indirect ophthalmoscopy, ultrasonography, and pure tone audiometry was suggestive of sympathetic ophthalmia with sensorineural hearing loss. Treatment was started with intravenous methyl prednisolone, oral corticosteroids, and immunosuppressants. Findings: Following treatment, signs of panuveitis showed resolution and improvement in visual, hearing, and neurological symptoms. Conclusions: Sympathetic ophthalmia associated with sensorineural deafness and neurological symptoms is a rare clinical syndrome. Prompt diagnosis and treatment with systemic corticosteroids and immunosuppressant medication may result in clinical improvement. © 2013 Venkatesh et al.
Keywords: atropine; azathioprine; corticosteroid derivative; methylprednisolone; prednisolone acetate; silicone oil; adult; anterior eye chamber; article; auditory threshold; B scan; bilateral hearing loss; case report; clinical evaluation; corticosteroid therapy; disorientation; dizziness; human; immunosuppressive treatment; intervention study; intraocular foreign body; intraocular pressure; iridocyclitis; male; ophthalmoscopy; optic disk; perception deafness; perforating eye injury; pigment epithelium; priority journal; pure tone audiometry; retina detachment; retina fluorescein angiography; slit lamp; sympathetic ophthalmia; topical treatment; visual acuity; visual impairment; vitreoretinal surgery; vitritis; young adult

Spinal textiloma (gossypiboma): A report of three cases misdiagnosed as tumour - Şahin, S.; Atabey, C.; Şimşek, M.; Naderi, S. (Balkan Medical Journal, 2013)
Background: Textile products commonly used in surgery (e.g., sponges or gauze) have been known to cause complications after spinal surgery. Associated complications usually arise months or even years after the primary surgery. In case of spine surgery, these bodies are often detected during neuroradiological evaluations to investigate reported back pain; however, this complication often remains asymptomatic. Aims: The research is intended to increase awareness among both spinal surgeons and neuroradiologists of this potential complication. Study Design: Retrospective study. Methods: This study is a retrospective case series of three patients with retained surgical textile products who had been misdiagnosed with spinal tumour. The medical records of the patients were reviewed and demographic data, clinical aspects, initial diagnosis, surgical procedures, time interval between previous operation and onset of symptoms, laboratory findings, radiological findings, treatment, and outcome were analysed. Results: The three patients included two women and one man aged between 64 and 67 years. All patients had a previous surgery for lumbar disc herniation. The time from the previous surgical procedures to presentation ranged from 3 to 17 years. All patients presented with non-specific lower back pain and/or radiculopathy without clinical findings of infection. Laboratory parameters were otherwise normal. All three cases had been misdiagnosed as a spinal tumor based on magnetic resonance imaging findings. During new surgical procedures, gauze bandages, i.e., surgical textiles left during a previous operation, were found. Conclusion: Textiloma is an important and rarely mentioned potential neurosurgical complication that may remain asymptomatic for years. They are more common in obese patients, after emergency surgery, and with unplanned changes in surgical procedure such as bleeding and unintended neurosurgical complications. Neuroradiological findings are variable and non-specific; thus, patients could be misdiagnosed with a spinal tumor or abscess. Likewise, in patients with a history of spinal surgery, spinal abscesses, haematomas, hypertrophic scars, fibrosarcomas, rhabdomyosarcomas, and schwannomas should definitely be considered in the differential diagnosis and considered when planning diagnostic procedures. Appropriate antibiotic therapy is recommended when a suppurative complication is present or suspected. Textiloma is a medico-legal complication that can be prevented by the education of surgical staff, the counting method (preoperatively, at closure, and at the end), and use of products with radiopaque barcodes. © Trakya University Faculty of Medicine.
Keywords: abscess; adult; aged; article; bone biopsy; case report; clinical feature; diagnostic error; diagnostic imaging; differential diagnosis; erythrocyte sedimentation rate; female; gossypiboma; histopathology; human; laminectomy; low back pain; lumbar disk hernia; male; medical history; nuclear magnetic resonance imaging; peroperative care; postoperative complication; postoperative pain; spine tumor

Retained surgical items: A problem yet to be solved - Stawicki, S.P.A.; Moffatt-Bruce, S.D.; Ahmed, H.M.; Anderson III, H.L.; Balija, T.M.; Bernescu, I.; Chan, L.; Chowayou, L.; Cipolla, J.; Coyle, S.M.; Gracias, V.H.; Gunter, O.L.; et al. (Journal of the American College of Surgeons, 2013)
Background: Retained surgical items (RSI) continue to occur. Large RSI studies are few due to low RSI frequency in single institutions and the medicolegal implications. Consequently, RSI risks are not fully defined, with discrepancies persisting among published studies. The goals of this study were to better define risk factors for RSI, to clarify previously discrepant risk factors, and to evaluate other potential contributors to RSI occurrence, such as trainee presence during an operation. Study Design: Multicenter case-match study of RSI risk factors was conducted between January 2003 and December 2009. Cases complicated by RSI were identified at participating centers using clinical quality improvement and adverse event reporting data. Case match controls (non-RSI) were selected from same or similar-type cases performed at each respective institution. Retained surgical item risk factors were evaluated by univariate and multivariate conditional logistic regression. Results: Fifty-nine RSIs and 118 matched controls were analyzed (RSI incidence 1 in 6,975 or 59 in 411,526). Retained surgical items occurred despite use of confirmatory x-rays (13 of 27 instances) and/or radiofrequency tagging (2 of 32 instances). Among previously discrepant results, we confirmed that body mass index, unexpected intraoperative events, and procedure duration were associated with increased RSI risk. The occurrence of any safety variance, and specifically an incorrect count at any time during the procedure, was associated with elevated RSI risk. Trainee presence was associated with 70% lower RSI risk compared with trainee absence. Conclusions: Longer duration of surgery, safety variances, and incorrect counts during the procedure result in elevated RSI risk. The possible positive influence of trainee presence on RSI risk deserves additional study. Our findings highlight the need for zero tolerance for safety omissions, continued study and development of novel approaches to RSI reduction, and establishing anonymous RSI reporting systems to better track both the incidence and risks associated with this problem, which has yet to be solved. © 2013 American College of Surgeons.
Keywords: adult; article; body mass; case control study; controlled study; female; health care quality; human; incidence; logistic regression analysis; major clinical study; male; multicenter study; operation duration; postoperative complication; priority journal; radiofrequency; retained instrument; surgical risk; X ray

Application of an engineering problem-solving methodology to address persistent problems in patient safety: a case study on retained surgical sponges after surgery. - Anderson, D.E.; Watts, B.V. (Journal of patient safety, 2013)
Despite innumerable attempts to eliminate the postoperative retention of surgical sponges, the medical error persists in operating rooms worldwide and places significant burden on patient safety, quality of care, financial resources, and hospital/physician reputation. The failure of countless solutions, from new sponge counting methods to radio labeled sponges, to truly eliminate the event in the operating room requires that the emerging field of health-care delivery science find innovative ways to approach the problem. Accordingly, the VA National Center for Patient Safety formed a unique collaboration with a team at the Thayer School of Engineering at Dartmouth College to evaluate the retention of surgical sponges after surgery and find a solution. The team used an engineering problem solving methodology to develop the best solution. To make the operating room a safe environment for patients, the team identified a need to make the sponge itself safe for use as opposed to resolving the relatively innocuous counting methods. In evaluation of this case study, the need for systematic engineering evaluation to resolve problems in health-care delivery becomes clear.
Keywords: article; biomedical engineering; foreign body; human; medical error; methodology; patient safety; postoperative complication; standard; surgical sponge

Ocular golden galaxy - Naderi, M.; Jadidi, K.; Alishiri, A.; Mosavi, S.A. (JCRS Online Case Reports, 2013)
A 27-year-old man presented to the emergency department with metallic-like foreign-body deposition on the entire aspect of both corneas associated with intense irritation, tearing, and photophobia. The corrected distance visual acuity (CDVA) was counting fingers in the right eye and light perception (LP) in the left eye. Slitlamp examination revealed diffuse, galaxy-like, golden-brown confluent deposits on the cornea, sclera, and conjunctiva of both eyes. The eyes were irrigated several times, followed by foreign-body removal and corneal repair. A penetrating keratoplasty was later performed in the right eye. After 1 year of follow-up, the patient was asymptomatic and the CDVA improved in the right eye but remained LP in the left eye due to macular scar formation secondary to severe tractional macular edema.
Keywords: betamethasone; erythromycin; gold; tropicamide; adult; article; case report; cornea opacity; cornea perforation; drug withdrawal; epiphora; eye examination; eye irritation; eye lavage; eyelid edema; human; intraocular foreign body; iris disease; keratoplasty; laceration; lens implantation; lensectomy; low vision; photophobia; priority journal; pupil disease; scar; slit lamp; vitrectomy; young adult; mydriacyl

Retained vaginal foreign body in minimally invasive gynecological surgeries - Toubia, T.; Sangha, R. (Journal of Minimally Invasive Gynecology, 2013)
Study Objective: To raise awareness of the potential problem of retained vaginal foreign body in minimally invasive gynecological surgeries and to suggest ways to avoid it. Design: Case review of 2 consecutive cases of minimally invasive gynecological surgeries that were complicated by retained surgical object in the vagina and occurred within 2 consecutive years. Setting: Tertiary care teaching hospital in Southeast Michigan. Patients: 2 patients who had minimally invasive gynecological surgeries that were complicated by a retained surgical object in the vagina and occurred within 2 consecutive years in the same institution. Measurements and Main Results: The first case is a retained asepto bulb after a robotic-assisted total laparoscopic hysterectomy. The second case is a retained surgical sponge after a laparoscopic ovarian cystectomy. Both patients did well after removal of the foreign body from the vagina without major complications. Conclusion: Unfortunately, the counting system and radiographic screening for high risk cases are not reliable methods to prevent retained foreign objects. Communication is always key and standardization of the language in the operating room is essential. Performing two separate counts for the vaginal and the abdominal procedures as well as applying a routine systematic digital vaginal exam at the end of the procedure are two easy steps that could decrease the risk of retained surgical items in a patient's body. (Figure Presented).
Keywords: gynecologic surgery; gynecology; foreign body; human; patient; vagina; risk; procedures; United States; surgical sponge; operating room; cystectomy; hysterectomy; teaching hospital; language; standardization; interpersonal communication; screening; tertiary health care

Counting matters: lessons from the root cause analysis of a retained surgical item. - Agrawal, A. (Joint Commission journal on quality and patient safety / Joint Commission Resources, 2012)
BACKGROUND: Retained surgical items (RSIs), such as a sponge, instrument, or needle, after a surgery or invasive procedure is an uncommon but potentially serious event associated with significant morbidity and mortality. A 27-year-old woman was discovered to have a retained vaginal sponge a week after she underwent the repair of a vaginal tear following normal vaginal delivery. The retained sponge was removed with no further complications. ROOT CAUSE ANALYSIS: The fundamental error involved the obstetric team's failure to perform the standard protocol of counting sponges before, as well as after, the procedure. This was attributed to a lack of reminders to perform the count, relatively recent implementation of the sponge-count policy, and a breakdown in teamwork and communication between physicians and nurses. CORRECTIVE ACTIONS: The corrective actions focused on systems improvement, as opposed to the human error of the memory lapse. The sponge-counting process was reinforced by incorporating a sign-out at the end of obstetric procedures to ensure that the counts have been done and any discrepancies addressed. A specialized delivery note with mandatory field to document sponge count was implemented in the electronic health record as an additional reminder. All staff participated in a teamwork and communication training program. TRACKING COMPLIANCE: Since the incident's occurrence in 2010, the staff has demonstrated 100% compliance with the corrective actions, and a retained surgical item complication has not recurred. CONCLUSION: Individual accountability must be balanced with systems improvement, given that most medical errors are a result of fallible humans working in chaotic, unpredictable, and complex clinical environment.
Keywords: adult; article; case report; obstetric delivery; female; foreign body; human; medical error; root cause analysis; surgical sponge; tertiary health care

A study of the bioengineered surgical sponge. - Asiyanbola, B. (Technology and health care : official journal of the European Society for Engineering and Medicine, 2012)
The postoperatively retained foreign body (PORFB) can induce complications leading to the need for follow-up surgery to ensure its removal, to treat or prevent the formation of an abscess, and to minimize the risk of death for the patient and liability for the surgeon and hospital. The most common cause of PORFB complications is the surgical sponge. Previously, PORFB prevention was focused on improved efficiency in RFB counting; however, because of the inability to entirely eliminate human error, cost, and the potentially unproven patient outcome improvement, new approaches have been sought. We examined the use of a novel bioengineered, biodegradable sponge (BSS) to reduce the risk of complications due to PORFBs, thus potentially improving patient outcomes.
Keywords: animal; article; biomedical engineering; cost benefit analysis; disease model; economics; foreign body; human; methodology; postoperative complication; surgical sponge; pig; time

Interview with a quality leader: Dr. Verna Gibbs on surgical safety. Interview by Susan V. White. - Gibbs, V. (Journal for healthcare quality : official publication of the National Association for Healthcare Quality, 2012)
Dr. Verna Gibbs describes the "NoThing Left Behind" Program designed to eliminate retained devices from surgical procedures. She explains the genesis of the program along with adjuncts to counting including computer-assisted sponge count, radiofrequency detection system, radiofrequency identification system, and the Sponge ACCOUNTing system. She provides comments on the use of these adjuncts with responses on their effectiveness on improving safety. © 2011 National Association for Healthcare Quality.
Keywords: article; checklist; foreign body; human; interview; medical error; methodology; patient safety; standard; surgery; surgical sponge; total quality management

Assessment of radiofrequency device sensitivity for the detection of retained surgical sponges in patients with morbid obesity - Steelman, V.M.; Alasagheirin, M.H. (Archives of Surgery, 2012)
Hypothesis: Retained surgical sponges are serious medical errors that result in negative patient outcomes.Aradiofrequency( RF)matfor the operatingroombedhas recently been introduced to detect the presence of a retained surgical sponge. The study objectives were to evaluate the sensitivity and specificity of the RF mat for the detection of surgical sponges through the torso of individuals with varying body habitus and to compare the sensitivity of the RF mat with that of the RF wand. We hypothesized that the sensitivity and specificity of the RF technology would be comparable to published findings of themanual sponge count by operating room personnel. Design: Aprospective, crossover, double-blinded study design was used. Participants served as theirowncontrols. Setting: Large Midwestern academic medical center. Participants: In total, the first phase of the study enrolled 203 participants, including 129 (63.5%)with morbid obesity. One hundred seventeen of 203 participants were also enrolled in the second phase of the study. Main Outcome Measures: The study participants reclined in a supine position on top of an RF mat. Four surgical sponges were sequentially placed on top of the torso in locations approximating the abdominal quadrants. The torso was scanned for sponges. In a subset of participants, 4 surgical sponges were sequentially placed underneath the torso, and an RF wand was passed over the abdomen. Results: Overall, 812 readings were obtained with the RF mat, and 468 readings were obtained with the RF wand. Twelve false-negative readings were obtained with the RF mat, exclusively in participants with super morbid obesity (body mass index [calculated as weight in kilograms divided by height in meters squared] >50.0). Overall, the sensitivity of the RF mat was 98.1%, and the specificity of the RF mat was 100.0%. In the subset of 117 participants in whom the RF wand was also used, the sensitivity and specificity of the wand were each 100.0%. Conclusions: The sensitivity and specificity of RF device technology are much higher than those of surgical sponge counts or published findings on the use of intraoperative radiographs to identify retained surgical sponges. The RF wand is more sensitive than the RF mat in individuals with morbid obesity. ©2012 American Medical Association. All rights reserved.
Keywords: abdomen; adult; aged; article; body mass; Caucasian; controlled clinical trial; controlled study; crossover procedure; double blind procedure; false negative result; female; human; intraoperative period; major clinical study; male; morbid obesity; operation duration; patient safety; peritoneal cavity; predictive value; priority journal; prospective study; radiation equipment; radiofrequency; radiofrequency identification; radiofrequency mat; retained instrument; sensitivity and specificity; supine position; surgical sponge; trunk; Blair-Port Wand model 0020; RF Assure Detection System

Effectiveness of a radiofrequency detection system as an adjunct to manual counting protocols for tracking surgical sponges: A prospective trial of 2,285 patients - Rupp, C.C.; Kagarise, M.J.; Nelson, S.M.; Deal, A.M.; Phillips, S.; Chadwick, J.; Petty, T.; Meyer, A.A.; Kim, H.J. (Journal of the American College of Surgeons, 2012)
Background: Despite rigorous manual counting protocols and the classification of retained surgical items (RSIs) as potential "never events," RSIs continue to occur in approximately 1 per 1,000 to 18,000 operations. This study's goals were to evaluate the incorporation of a radiofrequency detection system (RFDS) into existing laparotomy sponge- and Raytec-counting protocols for the detection of RSIs and define associated risk factors. Study Design: All patients undergoing surgery at the University of North Carolina Hospitals from September 2009 to August 2010 were enrolled consecutively. The performance of an RFDS-incorporated accounting protocol for detecting RSIs was prospectively evaluated. Several operative metrics were recorded to identify risk factors for miscounts. Results: A total of 2,285 patients were enrolled. One near miss was detected by the RFDS. Thirty-five miscounts occurred, for a rate of 1.53%. The ultimate locations of miscounted items were surgical site (n = 11), within operative suite (n = 10), surgical drapes (n = 2), and emergency protocol deviations (n = 12). Perioperative variables associated with miscounts were higher estimated volume of blood lost, longer operations, higher number of laparotomy sponges used, open surgical approach, "after hours" operations, change of surgical team during operation, weekend or holiday operations, unanticipated changes in operative plan during surgery, and emergency operations. Body mass index was not associated with miscounts. Surveys completed by participating surgical staff suggested high confidence in the RFDS for prevention of RSIs. Conclusions: The incorporation of the RFDS assisted in the resolution of a near-miss event (1 of 2,285) not detected by manual counting protocols and assisted in the resolution of 35 surgical-sponge miscounts. No known RSIs occurred during the study period. Risk factors for miscounts were identified and can help identify at-risk surgical populations. © 2012 American College of Surgeons.
Keywords: adult; article; bleeding; body mass; emergency surgery; female; heart surgery; human; information processing device; laparotomy; major clinical study; male; operating room personnel; operation duration; patient safety; perioperative period; peritoneal cavity; priority journal; prospective study; radiofrequency detection system; radiofrequency identification; risk factor; surgical approach; surgical drape; surgical sponge; thorax surgery

“picking” the problem of an upset stomach - Nabh, A.; Gangireddy, V.G.R.; Singh, E.; Spurr, C.; Sridhar, S. (American Journal of Gastroenterology, 2012)
Case: An 85-year-old male patient presented with a history of loss of appetite and vague upper abdominal discomfort of 1 month duration. The vital signs were stable. The physical examination revealed mild epigastric tenderness. The liver enzymes, CEA, CA19-9, AFP and the complete blood counts were all normal. A contrast-enhanced CT scan of the abdomen revealed air and hyperdense tracking from the lefthepatic lobe adjacent to the stomach causing a concern for a fistula between the stomach and the liver possibly secondary to a gastric tumor. An upper GI endoscopy revealed a toothpick which had penetrated the gastric walls and bridging the greater and the lesser curve of the antrum with a minimally raised area around the points of penetration. The toothpick was removed with difficulty using a snare and mucosal biopsies were obtained from the raised area. An immediate surgical consultation was sought, however, no surgical intervention undertaken as the patient had no signs of acute abdomen. The patient was given antibiotics for 2 weeks. A follow-up CT scan of the abdomen 2 weeks later demonstrated an interval resolution of the previously noted gastro-hepatic fistula without any evidence of extravasation of the contrast confirming a complete healing of the fistulous tract. All gastric biopsies were negative for malignancy. Upon questioning, the patient admitted to chewing on a toothpick 3-4 weeks previously while watching an exciting football game and going to bed at night. Later he realized that the toothpick had disappeared from his mouth. Discussion: We presented an interesting patient who developed a gastro-hepatic fistula caused by a toothpick. Gastrohepatic fistula have been rarely reported following transarterial chemoembolizaton (A Jain, et al), radiofrequency ablation (SH Lee, et al) for hepatocellular cancer treatment and cholangiocarcinoma (Aung, et al). Our case is the first case of gastro-hepatic fistula from accidentally ingesting a foreign body.
Keywords: antibiotic agent; liver enzyme; carcinoembryonic antigen; college; gastroenterology; stomach; patient; human; fistula; abdomen; computer assisted tomography; appetite; blood cell count; endoscopy; surgery; stomach tumor; mastication; liver; bile duct carcinoma; stomach wall; biopsy; consultation; acute abdomen; follow up; physical examination; stomach biopsy; healing; extravasation; abdominal discomfort; football; night; radiofrequency ablation; cancer therapy; male; foreign body; vital sign

Endoscopic treatment of intermittent gastric outlet obstruction caused by a prolapsing gastric antral polyp - Brozovic, S.; Saltzman, J. (American Journal of Gastroenterology, 2012)
Purpose: Gastric outlet obstruction often presents with nausea and vomiting and usually develops over weeks to months. The most common causes of gastric outlet obstruction are peptic ulcers, malignancy, bezoars, foreign bodies, and pyloric stenosis. Methods: We report a case of intermittent gastric obstruction caused by a prolapsing hyperplastic gastric antral polyp. Results: A healthy 44-year-old female presented with 3 months of intermittent dull mid abdominal pain, nausea and intermittent non-bloody, non-bilious vomiting. She also described early satiety and a weight loss of 8 pounds over the 3 months. She was otherwise healthy and took no medications. On physical exam she had normal bowel sounds, and mild tenderness over the epigastric region. She had a negative Murphy's sign, and the spleen and liver were normal. Her complete blood count was normal, with no anemia. Upper endoscopy was recommended to further investigate the patient's pain, nausea, vomiting and weight loss. On upper endoscopy, a 3 cm pedunculated, prolapsing, polyp was found arising in the gastric antrum and causing ball-valve effect within the pylorus and near complete obstruction of the pyloric channel. The polyp was observed to cause intermittent gastric outlet obstruction. The polyp was completely resected by a monopolar polypectomy using a large snare and sent for pathology. Pathology showed a hyperplastic polyp without evidence of metaplasia, dysplasia or malignancy. Random gastric biopsies showed chronic inactive gastritis and no evidence of Helicobacter pylori. At the follow-up 12 months after the polypectomy, the patient remained symptom free. Conclusion: We report the case of a patient with intermittent symptomatic gastric outlet obstruction caused by a benign prolapsing gastric polyp treated by endoscopic snare resection. There are 39 previously reported cases of gastric polyps leading to gastric outlet obstruction. Gastric polyps causing gastric outlet obstruction are more common in females (23 cases) with median age of onset of 72 years in females. Previously reported polyps arise from the antrum and have a median size of 5 cm (1.5-8 cm). They can be managed surgically with excision, or endoscopically with snare polypectomy or endoscopic mucosal resection (EMR) of sessile polyps. The median size of endoscopically removed polyps is 3 cm, with largest reported in the literature being 8 cm. Complications of endoscopic management include bleeding and perforation. Gastric polyps should be considered in the differential diagnosis of a patient who present with intermittent gastric outlet obstruction. Endoscopic management with snare resection is a good option if technically feasible and can result in a long term response.
Keywords: stomach obstruction; polyp; college; gastroenterology; human; stomach polyp; patient; polypectomy; female; endoscopy; vomiting; pathology; nausea; body weight loss; surgery; pylorus stenosis; intestine sound; follow up; drug therapy; spleen; Helicobacter pylori; gastritis; foreign body; stomach biopsy; satiety; bezoar; nausea and vomiting; metaplasia; obstruction; pylorus; stomach antrum; pain; dysplasia; peptic ulcer; anemia; blood cell count; endoscopic mucosal resection; liver; onset age; abdominal pain; excision; bleeding; perforation; differential diagnosis

Retained intraabdominal gossypiboma 12 years after laparatomy - Umobong, E.O.; Ibrahim, I.O.; Ezemamma, J.C.; Taiwo, K.E. (Histopathology, 2012)
Introduction: Gossypiboma is used to describe a retained surgical swab in the body after an operation. Intra-abdominal surgical sponge is an uncommon surgical error. Among retained foreign bodies, a surgical gauze or sponge constitutes the most frequently encountered object because of its common usage, small size and amorphous structure. Gossypiboma may cause serious morbidity and may lead to mortality. Case Report: A 32 year old woman presented with a week history of lower back pain and suprapubic pain associated with whitish vaginal discharge. Vaginal examination revealed caseous discharge around an open cervix, with a bulky uterus and a solitary firm mass posterior to the uterus measuring 4 × 5 cm. An initial impression of cystic torsion with adhesion was made. Previous surgical procedures were performed at another medical facility in 2000. An exploratory laparatomy for left sided adnexal mass was performed about 1 year after the initial presentation. Intraoperative findings yielded numerous adhesions and a walled gauze measuring 5 × 5 × 4 cm. The histological diagnosis was in keeping with Gossypiboma and chronic granulomatous inflammation. The patient responded well to post operative management. Conclusion: The policy that prevention is better than cure is highly appreciated. Accurate sponge and instrument counts, with radiologic evaluation when a discrepancy is found, can be helpful. Although human errors cannot be completely avoided, continuous medical training and strict adherence to rules of the operation room should reduce the incidence of gossypiboma to a minimum.
Keywords: pathology; human; adhesion; uterus; surgical error; foreign body; surgical sponge; mortality; histology; patient; case report; female; vagina discharge; morbidity; pain; pelvic examination; low back pain; torsion; surgical technique; granulomatous inflammation; policy; prevention; error; medical education; operating room; surgical swab

Aspiration of fake gold teeth leading to severe pneumonia and granulation tissue formation - Patel, A.; Nunnery, E.; Adhyaru, B. (Chest, 2012)
INTRODUCTION: Foreign body aspirations, although more common amongst children and the elderly, can lead to severe infections. CASE PRESENTATION: A 33 year old male with no known past medical history presented with a 3 month history of fatigue, episodic fevers, and cough with productive sputum. Patient was seen in a walk in clinic at the onset of symptoms and was told that he had a bronchitis and he was prescribed a 5 day course of azithromycin which did not resolve his symptoms. He denied any weight loss or other constitutional symptoms. Also he denied having any recent sick contacts. Furthermore he had a recent HIV test which was negative. On admission, the patient was febrile to 39.2â°C, BP 90/56, HR 120, RR 26, 91% on 2L NC. Exam was significant for tachycardia, decreased breath sounds on the right lung base as compared to the left, and diaphoresis. Labs was significant for a wbc count of 39 K/mcL. Otherwise unrevealing. An XR of the chest revealed foreign body aspiration in the right intermediate bronchus with superimposed pneumonia. Upon further questioning, it was illicited that the patient was involved in an altercation where he presumably lost his imitation gold teeth cover. The patient was started on broad spectrum Vancomycin and Zosyn. He continued to remain hypotensive and febrile despite broad antibiotic coverage. Interventional pulmonology was consulted. A bronchoscopy was performed with retrieval of the foreign object. The retrieval of the object was complicated by formation of granulation teeth; however it was finally able to be retrieved. Given the extent of granulation tissue, the patient underwent a significant amount of laser ablation of lung tissue. Over the next few days, the patient deferversed and improved clinically. DISCUSSION: Foreign body in the bronchus can present with variable symptoms depending on the severity. These can range from nonspecific respiratory complaints to long-term irreversible damage. Prompt recognition of the aspiration of the foreign body is important to identify as inflammatory granulation can develop as occurred with our patient. CONCLUSIONS: Foreign body aspiration can lead to severe infections. Prompt recognition is essential to prevent the sequelae of inflammatory granulation.
Keywords: gold; antihypertensive agent; vancomycin; azithromycin; piperacillin plus tazobactam; antibiotic agent; aspiration; tooth; pneumonia; granulation tissue; human; patient; foreign body aspiration; foreign body; infection; bronchus; thorax; bronchitis; hospital; pulmonology; bronchoscopy; lung parenchyma; body weight loss; imitation; child; sputum; leukocyte count; coughing; diaphoresis; fever; fatigue; lung; abnormal respiratory sound; tachycardia; medical history; HIV test; laser surgery; male; aged; Human immunodeficiency virus

Predictors of retained foreign body among patients undergoing abdominal/pelvic surgery and costs of “routine” abdominal radiographs in their detection - Vallabh-Patel, V.; Appleton, K.; Wilson, B.; Mulla, Z.; Saldivar, J.S. (International Journal of Gynecological Cancer, 2012)
Background: There is limited data on the use of abdominal radiographs in the intra-operative/post-operative period for detection of RFBs. As medical costs rise, hospitals have now planned to decrease reimbursement on conditions acquired during inpatient stays, including “unnecessary” radiologic studies. Objective: To identify the clinical and demographic predictors of RFBs among patients undergoing major abdominal/pelvic surgery and associated costs of detection abdominal radiographs. Materials and methods: Preliminary records of 125 patients who underwent selected abdomino-pelvic procedures from January 2002 to December 2010 at a tertiary-care academic hospital were reviewed. Cross-sectional prevalence study was conducted to identify predictors of RFBs. Results: Median patient age was 47. Median weight was 80 kg. Median estimated blood loss(EBL) was 200cc. The most common procedures were an exploratory laparotomy (33.6%), open hemi-colectomy (22.4%), reopening of recent laparotomy (18.4%) and total abdominal hysterectomy (16.8%). Thirty-one (24.8%) of cases were trauma. Four (3.9%) patients had a RFB. Three RFB cases were trauma laparotomies and one scheduled open hemi-colectomy. Adjusted ORs were calculated for five possible risk factors: Age≥50 y vs. age< 50 y OR=1.70 (P=0.70), weight≥100 kg vs. weight< 100 kg OR=2.50 (P=0.73), EBL≥500cc vs. EBL< 500cc OR=0.82 (P=0.44), exploratory laparotomy (yes vs. no) OR=1.78 (P=0.61), trauma vs. non-trauma case OR=1.11 (P=0.93), and length of surgery (>3hours vs. < 3hours) OR=1.74 (0.66). Conclusions: There were 4 RFBs, 75% were trauma cases. The other variables were not significantly associated with risk of RFBs. A policy on performing “routine” abdominal radiographs after a correct count in major surgery is unwarranted in certain cases.
Keywords: patient; human; surgery; X ray film; female genital tract cancer; society; foreign body; injury; laparotomy; weight; colon resection; hospital; procedures; risk factor; abdominal hysterectomy; pelvis; hospital patient; reimbursement; bleeding; prevalence; major surgery; policy; risk; tertiary health care

Small bowel adenocarcinoma: A case of atypical CT scan appearance - Eltweri, A.M.; Bowrey, D.; Taylor, M. (BMJ Case Reports, 2012)
A 73-year-old man presented to the surgical assessment unit with recurrent episodes of central abdominal pain and vomiting for 18 months. He has the past medical history (PMH) of hypertension and has been using his denture for 35 years; he had no past surgical history; he drinks alcohol socially and not a smoker. This patient was investigated for iron defi ciency anaemia with upper and lower gastrointestional endoscopy, as the patient had positive faecal occult blood; rectal biopsy showed no sign of inflammation and no evidence of malignancy; blood investigation showed Hb 9.8 g/dl, white cell count 14.8, mean cell volume 86.3, mean cell haemoglobin 26.9 and C reactive protein 13. This patient underwent a CT scan of the chest, abdomen and pelvis; the latest one showed that there is a short segment of the middle part of the small bowel that looks thickened and within which there is a high-density calcified shadow which is reported as an ingested foreign body or a tooth fragment; the patient underwent laparotomy and the histology results revealed 30 mm well differentiated/moderately differentiated adenocarcinoma.
Keywords: C reactive protein; ferrous sulfate; hemoglobin; abdominal pain; abdominal tenderness; aged; article; blood analysis; cancer adjuvant therapy; cancer staging; case report; cell volume; computer assisted tomography; disease duration; foreign body; gastrointestinal endoscopy; histopathology; human; human tissue; image analysis; intestine anastomosis; iron deficiency anemia; laparotomy; leukocyte count; male; occult blood; physical examination; priority journal; rectum biopsy; recurrent disease; small intestine adenocarcinoma; small intestine carcinoma; small intestine resection; tumor differentiation; tumor perforation; tumor volume; vomiting

Anaesthetic management of a patient with cerebellar ataxia, scoliosis and spinal surgery (Harrington Rods) complicated by severe preeclampsia (Hellp Syndrome) with fetal growth retardation - Kapoor, A.; Jones, S.; Wight, W. (Regional Anesthesia and Pain Medicine, 2012)
A 36 year old female with cerebellar ataxia and severe lumbothoracic scoliosis presented with uncontrolled hypertension, epistaxis and difficult venous access at 26 week gestation. She had a HELLP syndrome with raised ALT, low platlets count (32) and required stabilization and urgent caesarean section. She had modified RSI with propofol and rocuronium and given a transversus abdominus plane block. She showed significant weakness on emergence, although respiratory function was adequate. The baby weight was 425gm and required further management in SCBU. There was a persistence of raised ALT in postoperative period although platelet count improved to normal levels following surgery. Discussion: 1. The complex spinal surgery excluded any neuraxial block 2. The presence of Cerebellar ataxia, muscular hypotonia and severe preeclampsia lead to a careful choice of anaesthetic and neuromuscular block. In her case, we were able to safely perform RSI without suxamethonium. 3. Attenuation of the hypertensive response to intubation must be achieved in cases of severe pre-eclampsia. The BP control was achieved with MgSO4, labetalol intravenously and remifentanil infusion. 4. She also had a difficult venous access. The venous access was gained using ultrasound and then a central line was inserted. 5. The severe thrombocytopenia at her operation raised concerns with increased bleeding tendency. Also performance of TAP block was risky as any concealed bleeding could manifest later on in recovery. She had a normal clotting screen. The surgical team confirmed adequate clotting at her operation and TAP block was performed safely at end of her operation.
Keywords: anesthetic agent; rocuronium; propofol; labetalol; remifentanil; suxamethonium; human; cerebellar ataxia; HELLP syndrome; spine surgery; intrauterine growth retardation; preeclampsia; scoliosis; patient; society; regional anesthesia; female; hypertension; cesarean section; intubation; attenuation; thrombocytopenia; bleeding tendency; bleeding; weakness; pregnancy; epistaxis; neuromuscular blocking; muscle hypotonia; surgery; platelet count; postoperative period; weight; baby; infusion; ultrasound; respiratory function

Innovation of polyurethane coated stent for treatment against severe tracheobronchomalacia in children - Matsui, H.; Hiroma, T.; Ogiso, Y.; Hasegawa, H. (American Journal of Respiratory and Critical Care Medicine, 2012)
Stent implantation in the trachea, using polyurethane-coated metallic stents, reduces granulomatous reaction, demonstrating the possible treatment for severe form of tracheobronhomalacia in children. Methods: Materials and live experiments were performed using the newly invented metallic stent (LASER-cut stainless steel with a 100 micrometer coating of polyurethane). In the materials experiment, the relationship between the holding force and deformity was tested by a compressor. In the animal examination, coated stents were orally implanted into the trachea in five rabbits, while non-coated stents were implanted in another five rabbits. After three weeks observation, the inner diameter was measured by 3D computed tomography, and the number of granulation tissues was counted by broncho-fiberscope. Histological investigation followed in both groups. Results: In the materials experiment, new stents demonstrated a holding force similar to PALMAZ stents, and significantly higher holding force than self-expandable metallic stents (LUMINEX). (Figure1) In the animal experiment, no difference was found in the inner diameter of the coated and non-coated stent groups by 3D computed tomography (p=0.07). In the broncho-fiberscopy, no obvious granulation tissues were found in the trachea with coated stents and metallic frame seems covered in tracheal membrane while protrusion and significant bulging of granulation tissue recognized in non-coated stents. (Figure2A and B) The number of granulation tissues was higher in non-coated stents than in coated stents (p<0.01). (Figure2C) Histological investigation showed infiltration of inflammatory cells around the non-coated stents where epithelial structure was destroyed, while tracheal epithelia were preserved in the group of coated stents. Conclusions: The new polyurethane-coated metallic stent maintains enough holding force, and reduces histo-biological reaction to foreign bodies, suggesting new possibilities for use in treatment against tracheobronchomalacia in children. (Figure Presented).
Keywords: polyurethan; stainless steel; stent; human; tracheobronchomalacia; child; American; society; granulation tissue; trachea; computer assisted tomography; metal stent; Leporidae; animal experiment; laser; fiberoscope; trachea mucosa; examination; inflammatory cell; fiberscope endoscopy; membrane; deformity; foreign body; granulomatous inflammation; implantation

True-true-related: An unusual cause of bowel obstruction - Shoeb, M.; Wlodarczyk, S.; Mookherjee, S. (Journal of General Internal Medicine, 2012)
LEARNING OBJECTIVE 1: Recognize that catastrophic sequela of blunt abdominal trauma can occur many weeks after the event. LEARNING OBJECTIVE 2: Recognize radiological mimickers of intussusception and small bowel obstruction. CASE: A previously healthy 38 year-old man presented with abdominal distention, nausea, and vomiting. Two weeks prior, he was admitted to an outside hospital with the same symptoms. At the time, computerized tomography (CT) scan showed small bowel obstruction (SBO) with transition point in the left mid-abdomen and terminal ileum wall thickening. He was treated with nasogastric tube decompression, but left against medical advice without a diagnosis when his symptoms improved. He presented to our emergency department with recurrentf abdominal distention and new feculent emesis. He denied fevers, chills, blood in his stool, melena, or history of abnormal bowel movements. He reported that three weeks prior to the first hospitalization, he had suffered a bicycle collision in which the handlebars struck his abdomen, resulting in severe abdominal pain. There had been no open wound or blood per rectum after the accident. On physical exam at the time of admission, he had normal vital signs and mild abdominal distention and tenderness. Laboratories showed normal complete blood count, electrolytes, aminotransferases, bilirubin, and lipase. CT scan of the abdomen and pelvis with intravenous contrast showed wall thickening of the distal jejunum and proximal ileum, probable ileal enteroenteric fistula, two segments of jejunojejunal intussusception with upstream bowel dilation, and diffuse lymphadenopathy. Taken together, the findings were thought to be most consistent with inflammatory bowel disease (IBD). Unfortunately, before a diagnostic colonoscopy was done, the patient ate a large meal. Overnight, he developed severe abdominal pain, went into shock and was taken emergently to the operating room. He was found to have obstruction of the terminal ileum due to an adhesion and upstream perforation with food in the peritoneal cavity. He underwent resection of 140 centimeters of terminal ileum and end-ileostomy. Final pathology showed a mixed acute and chronic inflammatory reaction within the serosa associated with small vessel proliferation, organization, and foreign material; there was no evidence of IBD or cancer. The diagnosis was felt to be intussusception and SBO as a result of intestinal trauma from his bicycle accident. DISCUSSION: Inpatient providers often care for patients with undifferentiated SBO. Blunt abdominal trauma can cause injury to the mesentery, hemorrhagic mucosal infarction, and subclinical bowel perforation. Subsequent healing with fibrosis and stricture can lead to intussusception and SBO with a delayed onset of symptoms. Intussusception and SBO after abdominal trauma are rare; there are 22 reports representing 91 cases in the literature. Patients typically present with intermittent abdominal pain and vomiting within 4 to 8 weeks of the trauma, but symptoms can be delayed by years. Diagnostic criteria include (1) prior blunt abdominal trauma, (2) absence of intestinal disease, (3) new intestinal symptoms, (4) radiographic confirmation of stenosis, and (5) lack of inflammatory or neoplastic changes in resected segment of bowel. In managing patients with abdominal pain or SBO, inpatient providers should consider prior blunt abdominal trauma in the differential and appreciate the variable timing in symptom onset.
Keywords: bilirubin; electrolyte; aminotransferase; triacylglycerol lipase; society; internal medicine; intestine obstruction; human; intussusception; patient; abdominal blunt trauma; abdominal pain; diagnosis; ileum; intestine; abdomen; computer assisted tomography; bicycle; hospital patient; small intestine obstruction; blood; vomiting; injury; accident; operating room; colonoscopy; inflammatory bowel disease; fever; hospital; fistula; jejunum; pelvis; emergency ward; nausea and vomiting; blood cell count; decompression; laboratory; intestine perforation; stenosis; vital sign; nasogastric tube; rectal drug administration; lymphadenopathy; mesentery; wound; intestine injury; foreign body; inflammation; hospitalization; pathology; ileostomy; serosa; surgery; neoplasm; peritoneal cavity; melena; food; perforation; adhesion; obstruction; infarction; healing; fibrosis; abdominal injury; enteropathy; male

“A dangerous wolf in sheep's clothing: ” A case report of destructive endocarditis caused by staphylococcus lugdunensis - Morikawa, D.; Keijinkai, T. (Journal of General Internal Medicine, 2012)
LEARNING OBJECTIVE 1: Recognize that a positive blood culture of coagulase-negative staphylococci may not always be a contaminant LEARNING OBJECTIVE 2: Recognize the clinical signs and symptoms of endocarditis caused by Staphylococcus lugdunensis CASE: A 70 year-old Japanese woman with a past medical history of cerebral palsy presents with 1-month's history of decrease in appetite and weight. She also reports generalized body weakness while denying fevers, chills, chest pain, palpitations, shortness of breath, cough, urinary changes, and rashes. Her significant physical findings include temperature of 35.3°Celsius, blood pressure of 85/48 mmHg, heart rate of 87 beats/minute, respiratory rate of 30 breaths/minute, and oxygen saturation of 100% on 10 liters of oxygen. She is lethargic and disoriented to time, place, and person; she also has poor oral hygiene with saprodontia. She has no heart murmurs, costovertebral angle tenderness, back pain, or skin lesions. The remainder of her examination is unremarkable. In addition, significant laboratory findings consist of white blood cell count (WBC) of 23,240/μL (4% bands, 93% segmented neutrophils), hemoglobin of 7.9 g/dL, platelets of 65,000/ μL, blood urea nitrogen of 68 g/dL, and creatinine of 1.2 mg/dL. Urinalysis shows 2+ protein , 3+ heme, >100 red blood cells/high power field (HPF), >100 WBC /HPF, and 3+ bacteria. A computed tomographic scan of the chest, abdomen, and pelvis reveals bilateral pleural effusions and bladder masses with hydronephrosis. Given her septic shock from presumed urinary tract infection, she has been empirically started on meropenem. Her encephalopathy, however, does not improve, and she even develops right-sided hemiparesis; a magnetic resonance imaging of the brain shows multiple areas of embolic cerebral infarcts. She also develops a renal infarction, splenic abscess, and iliopsoas abscess for which their drainage shows no bacteria. Her antimicrobial regimen has thus been changed to ceftriaxone and vancomycin for suspicion of infectious endocarditis; a transesophageal echocardiogram shows a vegetation on the mitral valve with regurgitation. During this time, all 3 sets of blood cultures have grown coagulase-negative staphylococcus (CNS), Staphylococcus lugdunensis in particular. Despite aggressive medicalmanagement and scheduledmitral valve replacement, the patient dies after 18 days of admission. DISCUSSION: As part of the normal skin flora, CNS has often been identified as a blood culture contaminant but has become increasingly recognized as a clinically significant pathogen even in cases of native valve endocarditis (NVE). In particular, S. lugdunensis can cause severe infections frequently attributable to Staphylococcus aureus. While both of these species produce a bound coagulase, S. lugdunensis, however, does not produce a free coagulase. Patients with immunosuppression and foreign bodies such as prosthetic devices and intravascular catheters are at a higher risk of infection with S. lugdunensis. The clinical presentation of NVE caused by CNS is indistinguishable from Streptococcus viridans and includes fever, generalized weakness, weight loss, and anorexia; about 25-33% of patients exhibit Osler's nodes, Janeway lesions, and splinter hemorrhages. While this case may have clinical signs and symptoms similar to S. viridans, one must not discount blood culture results initially showing CNS as just a blood culture contaminant.
Keywords: coagulase; oxygen; vancomycin; creatinine; synapsin II; heme; meropenem; antiinfective agent; ceftriaxone; hemoglobin; sheep; clothing; case report; endocarditis; Staphylococcus lugdunensis; society; internal medicine; wolf; human; blood culture; patient; physical disease by body function; infection; coagulase negative Staphylococcus; fever; bacterium; weakness; central nervous system; thorax pain; skin defect; weight; heart murmur; examination; laboratory; leukocyte count; appetite; oxygen saturation; cerebral palsy; breathing rate; heart rate; computer assisted tomography; blood pressure; pleura effusion; urinary tract infection; mouth hygiene; brain; backache; kidney infarction; spleen abscess; neutrophil; blood; medical history; female; urinalysis; temperature; risk; prosthesis; body weight loss; thorax; abdomen; pelvis; bladder; hydronephrosis; septic shock; rash; brain disease; hemiparesis; nuclear magnetic resonance imaging; urea nitrogen blood level; brain infarction; thrombocyte; coughing; abscess; Staphylococcus aureus; bacterial endocarditis; echocardiography; dyspnea; pathogenesis; skin flora; heart valve replacement; mitral valve; species; vegetation; immunosuppressive treatment; foreign body; intravascular catheter; alpha hemolytic Streptococcus; anorexia; bleeding; heart palpitation; Japanese (people)

Comparative economic analyses of patient safety improvement strategies in acute care: A systematic review - Etchells, E.; Koo, M.; Daneman, N.; McDonald, A.; Baker, M.; Matlow, A.; Krahn, M.; Mittmann, N. (BMJ Quality and Safety, 2012)
Background: The objective was to systematically review comparative economic analyses of patient safety improvements in the acute care setting. Methods: A systematic review of 15 patient safety target conditions and six improvement strategies was conducted. The authors searched the published literature through Medline (2000eNovember 2011) using the following search terms for costs: 'costs and cost analysis', 'cost-effectiveness', 'cost' and 'financial management, hospital'. The methodological quality of potentially relevant studies was appraised using Cochrane rules of evidence for clinical effectiveness in quality improvement, and standard economic methods. Results: The authors screened 2151 abstracts, reviewed 212 potentially eligible studies, and identified five comparative economic analyses that reported a total of seven comparisons based on at least one clinical effectiveness study of adequate methodological quality. Pharmacist-led medication reconciliation to prevent potential adverse drug events dominated (lower costs, better safety) a strategy of no reconciliation. Chlorhexidine for vascular catheter site care to prevent catheter-related bloodstream infections dominated a strategy of povidone-iodine for catheter site care. The Keystone ICU initiative to prevent central line-associated bloodstream infections was economically dominant over usual care. Detecting surgical foreign bodies using standard counting compared with a strategy of no counting had an incremental cost of US$1500 (CAN$1676) for each surgical foreign body detected. Several safety improvement strategies were less economically attractive, such as bar-coded sponges for reducing retained surgical sponges compared with standard surgical counting, and giving erythropoietin to reduce transfusion requirements in critically ill patients to avoid one transfusion-related adverse event. Conclusions: Five comparative economic analyses were found that reported a total of seven comparisons based on at least one effectiveness study of adequate methodological quality. On the basis of these limited studies, pharmacist-led medication reconciliation, the Keystone ICU intervention for central line-associated bloodstream infections, chlorhexidine for vascular catheter site care, and standard surgical sponge counts were economically attractive strategies for improving patient safety. More comparative economic analyses of such strategies are needed.
Keywords: antibiotic agent; chlorhexidine; contrast medium; povidone iodine; recombinant erythropoietin; antibiotic resistance; blood transfusion; blood transfusion reaction; catheter infection; central venous catheter; clinical effectiveness; Cochrane Library; comparative study; contrast induced nephropathy; cost benefit analysis; cost effectiveness analysis; critically ill patient; disinfection; drug safety; economic evaluation; emergency care; evidence based medicine; financial management; health care cost; health care quality; hospital care; human; intensive care unit; intravascular catheter; medicine; Medline; meta analysis; patient safety; pharmacist; postoperative hemorrhage; retained instrument; review; risk reduction; surgical sponge; systematic review; total quality management

Fatal pulmonary embolism: When the cause is not a thrombus - Franco, E.; Pinneri, F. (Giornale Italiano di Cardiologia, 2012)
Study design. We report a case of pulmonary embolism of polymethylmethacrylate material after percutaneous vertebroplasty. Purpose. To describe a severe vertebroplasty complication, the pulmonary embolism, which proved to be fatal in a patient with many chronic disabilities. Summary of background. Until 2007, the literature noted that the risk of embolism of polymethylmethacrylate (PMMA) following a percutaneous vertebroplasty counted a small number of pulmonary cement embolism (PCE) and a smaller number of fatal consequences. The most recent researches revealed that the risk of a PCE ranges from 3.5 to 23% for osteoporotic compression fractures. Data and method. This case report of a 80-year-old patient with multiple medical comorbid factors, chronic obstructive pulmonary disease, mild renal failure, osteoporosis, hepatic cirrhosis. Symptoms of pulmonary embolism developed 1 month following a percutaneous vertebroplasty. An echocardiography reported suspected that the cement infiltrated the right atrium (Fig. 1) and the right pulmonary artery, suspects confirmed by a CT scan (Fig. 2). As therapy with oxygen and low-molecular-weight heparin failed to solve the thrombus the patient required surgical tricuspid annuloplasty and extirpation of the right atrial and right pulmonary masses. Results. The course of the operation was complicated by pulmonary infection and the patient ultimately succumbed to infection/respiratory failure. Conclusions. The presence of intravascular/intracardiac foreign bodies is under-reported in literature, but it is quite common in clinical practice. We need to discuss the choice of some non risk-free interventions like vertebroplasty in older patients already affected by multiple main disabilities. (Figure Presented).
Keywords: cement; poly(methyl methacrylate); low molecular weight heparin; oxygen; lung embolism; thrombus; human; patient; percutaneous vertebroplasty; risk; disability; embolism; foreign body; lung infection; tricuspid annuloplasty; therapy; computer assisted tomography; pulmonary artery; heart right atrium; echocardiography; liver cirrhosis; osteoporosis; kidney failure; chronic obstructive lung disease; case report; compression fracture; clinical practice; study design

Fatal pulmonary embolism: When the cause is not a thrombus - Franco, E.; Frea, S.; Solaro, C.; Conti, V.; Pinneri, F. (Spine, 2012)
Study Design.: We report a case of pulmonary embolism of polymethylmethacrylate material after percutaneous vertebroplasty. Objective.: To describe a severe vertebroplasty complication, the pulmonary embolism, which proved to be fatal in a patient with many chronic disabilities. Summary of Background Data.: Until 2007, the literature noted that the risk of embolism of polymethylmethacrylate after a percutaneous vertebroplasty counted a small number of pulmonary cement embolism and a smaller number of fatal consequences. The most recent research revealed that the risk of a pulmonary cement embolism ranges from 3.5% to 23% for osteoporotic compression fractures. Methods.: This study is a case report of an 80-year-old patient with multiple medical comorbid factors, chronic obstructive pulmonary disease, mild renal failure, osteoporosis, and hepatic cirrhosis. Symptoms of pulmonary embolism developed 1 month after a percutaneous vertebroplasty. An echocardiography report suggested that the cement infiltrated the right atrium and the right pulmonary artery, and this was confirmed by a computed tomographic scan. As the therapy with oxygen and low-molecular-weight heparin failed to solve the thrombus, the patient required a surgical tricuspid annuloplasty and the extirpation of the right atrial and right pulmonary masses. Results.: The course of the operation was complicated by pulmonary infection, and the patient ultimately succumbed to infection/respiratory failure. Conclusion.: The presence of intravascular/ intracardiac foreign bodies is underreported in literature, but it is quite common in clinical practice. We need to discuss the choice of some non-risk-free interventions such as vertebroplasty in older patients already affected by multiple main disabilities. © 2012 Lippincott Williams and Wilkins.
Keywords: antibiotic agent; contrast medium; enoxaparin; oxygen; poly(methyl methacrylate); aged; antibiotic therapy; anticoagulant therapy; article; case report; chronic obstructive lung disease; contrast enhancement; echocardiography; fatality; heart left ventricle ejection fraction; human; kidney failure; liver cirrhosis; lung embolism; male; mitral valve regurgitation; osteoporosis; oxygen therapy; percutaneous vertebroplasty; pneumonia; priority journal; septic shock; tricuspid annuloplasty

Response to a quality improvement project on improving the surgical count - Hackney, C. (AORN Journal, 2012)
Keywords: human; letter; safety; surgical sponge

Response to a quality improvement project on improving the surgical count - Moore, S. (AORN Journal, 2012)
Keywords: human; letter; safety; surgical sponge

Open Versus Endovascular Stent Graft Repair for Abdominal Aortic Aneurysms: An Historical View - Rutherford, R.B. (Seminars in Vascular Surgery, 2012)
Development of endovascular abdominal aortic aneurysms repair (EVAR), now in its 4th decade, has involved at least 16 different devices, not counting major modifications of some, only 4 of which have emerged from clinical trials and gained US Food and Drug Administration approval. The main impetus behind EVAR has been its potential for significantly reducing procedural mortality and morbidity, but it was also expected to speed recovery and reduce costs through decreased use of hospital resources. At the outset, EVAR was touted as a better alternative to OPEN in high-risk patients with large abdominal aortic aneurysms, and to "watchful waiting" (periodic ultrasound surveillance) for those with small abdominal aortic aneurysms. This new technology has evoked a mixed response with enthusiasts and detractors debating its pros and cons. Bias and conflict of interest exist on both sides. This review will attempt to present a balanced review of the development and current status of this controversial competition between EVAR and OPEN, comparing them in terms of the following key considerations: mortality and morbidity, complications, failure modes and durability, and costs. © 2012 Elsevier Inc.
Keywords: abdominal aortic aneurysm; aortointestinal fistula; article; disease severity; endoleak; endovascular aneurysm repair; endovascular stent graft repair; false aneurysm; foreign body; health care cost; high risk patient; hospital cost; human; intermethod comparison; morbidity; mortality; open surgery; priority journal; quality of life; stent; surgical approach; surgical technique; survival rate; survival time; thrombosis; treatment response; AneuRx

A serious medicolegal problem after surgery: gossypiboma. - Gümüş, M.; Gümüş, H.; Kapan, M.; Onder, A.; Tekbaş, G.; Baç, B. (The American journal of forensic medicine and pathology, 2012)
After surgery, the most common foreign bodies retained in the abdominal cavity are the surgical sponges. The aim of the present study was to emphasize the importance of gossypiboma, which is a serious and medicolegal problem. The records of 12 patients with a confirmed diagnosis of gossypiboma after abdominal surgery at Dicle University Hospital were retrospectively reviewed between January 1994 and December 2009. Eight of the 12 patients were females, and 4 were males. Previously, 7 patients had been operated on electively, and 5 had undergone operations on an emergency basis. Abdominal ultrasonography clearly demonstrated gossypibomas in 5 patients, and computed tomography demonstrated a more precise image of retained surgical sponges in 3 patients. One patient died because of ventricular fibrillation; the other 11 patients were discharged in good health. To eliminate the risk of gossypibomas, all sponges should be counted at least twice (once preoperatively and once postoperatively); use of small sponges should be avoided during laparotomy, and only sponges with radiopaque markers should be used. The surgeon should explore the abdomen before closure. In cases in which the sponge count is uncertain, an abdominal x-ray should be performed before closure.
Keywords: abdominal radiography; adult; aged; article; computer assisted tomography; echography; female; foreign body; human; male; medical error; middle aged; retrospective study; surgery; surgical sponge

Postoperative bleeding after dental extraction in liver pretransplant patients - Perdigão, J.P.V.; De Almeida, P.C.; Rocha, T.D.S.; Mota, M.R.L.; Soares, E.C.S.; Alves, A.P.N.N.; Sousa, F.B. (Journal of Oral and Maxillofacial Surgery, 2012)
Purpose: The aim of this prospective observational study was to evaluate the incidence of postoperative bleeding after dental extraction in candidates for liver transplantation and the efficacy of the association of tranexamic acid and absorbable hemostatic sponges. Patients and Methods: All individuals referred for oral health evaluation requiring extraction were considered in this study. Patients were included in the analysis when the blood examinations showed a platelet count of 30,000/mm3 or greater and an international normalized ratio (INR) of 3.0 or less. In group 1 local pressure was applied by use of gauze soaked with tranexamic acid, and in group 2 gauze without tranexamic acid was used. Absorbable hemostatic sponges and cross sutures were used as a standard hemostatic measure. Results: In the 23 patients included in this study, 84 simple extractions were performed during 35 dental surgical procedures. The main preoperative blood tests found the following: a mean hematocrit level of 34.54% (SD, 5.84%; range, 21.7%-44.4%), platelet counts from 31,000/mm3 to 160,000/mm3, and a mean INR of 1.50 (SD, 0.39; range, 0.98-2.59). Postoperative bleeding occurred during only 1 procedure (2.9%), and local pressure with gauze was effective for achieving hemostasis. No statistically significant difference in the time to hemostasis was found between the 2 groups. Conclusions: This study found a low risk of bleeding for tooth extractions in patients with liver cirrhosis, INRs of 2.50 or less, and platelet counts of 30,000/mm3 or greater. Blood transfusions were not needed, and in the case of postoperative bleeding, the use of local hemostatic measures was satisfactory. © 2012 American Association of Oral and Maxillofacial Surgeons.
Keywords: dipyrone; paracetamol; tranexamic acid; absorbable hemostatic sponge; adult; aged; article; blood sampling; controlled study; cross-sectional study; female; gauze dressing; hemostasis; human; incidence; international normalized ratio; liver transplantation; major clinical study; male; observational study; postoperative hemorrhage; postoperative pain; preoperative period; prospective study; surgical sponge; therapy effect; platelet count; tooth extraction

Implementing AORN recommended practices for prevention of retained Surgical Items - Goldberg, J.L.; Feldman, D.L. (AORN Journal, 2012)
Retention of a surgical item is a preventable event that can result in patient injury. AORN's "Recommended practices for prevention of retained surgical items" emphasizes the importance of using a multidisciplinary approach for prevention. Procedures should include counts of soft goods, needles, miscellaneous items, and instruments, and efforts should be made to prevent retention of fragments of broken devices. If a count discrepancy occurs, the perioperative team should follow procedures to locate the missing item. Perioperative leaders may consider the use of adjunct technologies such as bar-code scanning, radio-frequency detection, and radio-frequency identification. Ambulatory and hospital patient scenarios are included to exemplify appropriate strategies for preventing retained surgical items. © 2012 AORN, Inc.
Keywords: article; foreign body; human; medical error; methodology; nursing; perioperative nursing; practice guideline; standard; surgery; surgical equipment; surgical sponge

A Nurse-led Approach to Developing and Implementing a Collaborative Count Policy - Norton, E.K.; Micheli, A.J.; Gedney, J.; Felkerson, T.M. (AORN Journal, 2012)
During the 2007 meeting of the Child Health Corporation of America Operating Room Director's Forum, members identified two major discrepancies in surgical count policies among the member hospitals: variations for instrument counts in pediatrics and exceptions to radiographic verification when needle counts were incorrect. The group agreed to collaboratively develop a pediatric count policy based on directors' expertise and current literature to help improve count practices. The task force members reviewed the literature as well as count policies from 30 member hospitals to identify and combine best practices and to create a single, standardized count policy. The project exemplifies a successful nurse-led, national group effort. The outcome is a policy that represents best practice in pediatrics and is a first step toward future opportunities to improve patient safety. © 2012 AORN, Inc.
Keywords: article; foreign body; human; medical error; methodology; needle; nurse; nursing; patient safety; pediatrics; perioperative nursing; practice guideline; standard; surgery; surgical equipment

Surgical Count Practice Variability and the Potential for Retained Surgical Items - Edel, E.M. (AORN Journal, 2012)
Validating existing count practices and reducing individual practice variance are necessary to decrease the risk for retained surgical items. A quality improvement project was undertaken at one large city hospital to identify best practice and eliminate variability in count practices. The project included an analysis of 20 surgical count policies from hospitals across the country and a review of count practices among nurses and surgical technologists at the facility. Assessment of the policies and practices indicated that clinical practice requirements in the policies varied greatly, and there was a high degree of count practice variability among staff members. The facility OR manager and OR quality coordinator collaborated with staff nurses and surgical technologists to identify practices that created variability and then addressed each one to create a new count policy and reduce the risk of retained surgical items. © 2012 AORN, Inc.
Keywords: article; foreign body; hospital; human; medical error; methodology; needle; nursing; patient safety; perioperative nursing; practice guideline; standard; surgery; surgical equipment

Implementation of the world health organization surgical safety checklist at a university hospital in Thailand - Kasatpibal, N.; Senaratana, W.; Chitreecheur, J.; Chotirosniramit, N.; Pakvipas, P.; Junthasopeepun, P. (Surgical Infections, 2012)
Background: Compliance with the World Health Organization (WHO) surgical safety checklist may reduce preventable adverse events. However, compliance may be difficult to implement in Thailand. This study was conducted to examine compliance with the WHO checklist at a Thai university hospital. Methods: A descriptive study was conducted among 4,340 patients undergoing surgery in nine departments from March to August 2009. The compliance rates were computed. Results: The highest compliance rate (91.4%) during the sign-in period was with patients' confirmation of their identity, operative site, procedure, and consent. However, only 19.4% of the surgical sites were marked. In the time-out period, surgical teams had introduced themselves by name and role in 79% of the operations; and in 95.7% of the cases, the patient's name, the incision site, and the procedure had been confirmed. Antibiotic prophylaxis had been given within 60 min before the incision in 71% of the cases. For 83% of the operations, the surgeons reviewed crucial events whereas only 78.4% were reviewed by the anesthetists. Sterility had been confirmed by the operating room nurses for every patient, but the essential imaging was displayed at a rate of only 64.4%. In the sign-out period, nurses correctly confirmed the name of the procedure orally in 99.5% of the cases. Instrument, sponge, and needle counts were completed and the specimen was labeled in most cases, 96.8% and 97.6%, respectively. Equipment-related problems were identified in 4.4% of the cases, and 100% of them were addressed. The surgeon, anesthetist, and nurse reviewed the key concerns for recovery and management of the patient at the rate of 85.1%. Conclusions: The WHO checklist can be implemented in a developing country. However, compliance with some items was extremely low, reflecting different work patterns and cultural norms. Additional education and enforcement of checklist use is needed to improve compliance. © 2012, Mary Ann Liebert, Inc.
Keywords: anesthesist; antibiotic prophylaxis; article; checklist; female; health care planning; human; imaging; incision; informed consent; major clinical study; male; needle; nurse; operating room personnel; practice guideline; priority journal; safety; surgeon; surgery; surgical equipment; surgical safety checklist; surgical sponge; university hospital; World Health Organization

Paraspinal textiloma after posterior lumbar surgery: A wolf in sheep's clothing - Akhaddar, A.; Boulahroud, O.; Naama, O.; Al-Bouzidi, A.; Boucetta, M. (World Neurosurgery, 2012)
Objective: Paraspinal textiloma (ParaTex) is a well-known complication after posterior lumbar surgery. However, there are few articles on this topic, probably because of medicolegal concerns. In addition, patients with ParaTex can remain asymptomatic for months or even years unless it causes complications. The purpose of this study is to review our experience on this "undesirable" topic to increase awareness among spinal surgeons and radiologists and avoid unnecessary morbidity, which is still being encountered. Methods: This study is a retrospective case series of six patients with ParaTex who underwent posterior lumbar spinal surgery in our neurosurgical department between January 2000 and December 2010. The medical records of each patient were reviewed and demographic data, clinical characteristics, initial diagnosis, surgical procedures, time interval between operation and onset of symptoms, biological and radiologic findings, treatment, and outcome were analyzed. Results: The six patients included four women and two men with a mean age of 48 years. Four patients had a history of lumbar disc herniation, one had undergone a laminectomy for a lumbar spinal stenosis, and a Gill's procedure was performed in one patient with a lumbar spondylolisthesis. The time from the causative operation to presentation ranged from 2 months to 6 years. All patients presented with nonspecific lower back pain and/or surgical site infection without fever or neurological symptoms. Laboratory parameters showed increased blood sedimentation rates and/or C-reactive protein level in four patients. Bacteria were isolated in only one patient. Five patients were evaluated with computed tomography scan, and this showed the spongiform pattern with gas bubbles in three cases. Magnetic resonance imaging was performed in two patients. The signal intensity varies according to stage and fluid content of the lesion. The ParaTex was removed surgically in all patients with a good outcome. Conclusions: ParaTexs are more common in obese patients, after emergency surgery, and with unplanned changes in surgical procedure. On computed tomography scan, the classic spongiform appearance is highly suggestive. Magnetic resonance imaging findings are variable and less specific, but confrontation of imaging data with the surgical history helps with the preoperative diagnosis. In the early postoperative period symptoms are related to the exudative response; at later times symptoms may be linked to pseudotumor formation clinically and radiologically. Appropriate antibiotic therapy is recommended when a septic complication is present or suspected. Strict measures must be taken to prevent this complication. Surgical sponges should always be counted at least three times (preoperatively, at closure, and at the end), radiopaque markers should be used, and if there is doubt, intraoperative radiography must be performed. © 2012 Elsevier Inc.
Keywords: adult; clinical article; clinical feature; diagnostic imaging; female; foreign body granuloma; human; image analysis; lumbar spine; male; paraspinal textiloma; retrospective study; review; spine surgery; symptom; treatment outcome

Patients Count on It: An Initiative to Reduce Incorrect Counts and Prevent Retained Surgical Items - Norton, E.K.; Martin, C.; Micheli, A.J. (AORN Journal, 2012)
Retained surgical items were the most frequently reported sentinel event in 2010, according to The Joint Commission. Perioperative nurse leaders at Children's Hospital Boston, a pediatric teaching hospital, conducted a quality improvement initiative to reduce or eliminate incorrect counts and count discrepancies, which increase the risk of an item being unintentionally retained after surgery. Work included educating the perioperative staff members, standardizing count practices, formally reviewing every reported count discrepancy with the nursing team, and reviewing and revising the count policy for prevention of retained surgical items. The initiative reduced the number of incorrect counts and count discrepancies by 50% between 2009 to 2010. These initiatives continue to be expanded, and the results have been sustained on an ongoing basis. © 2012 AORN, Inc.
Keywords: article; documentation; foreign body; hospital; human; length of stay; methodology; organization and management; patient care; perioperative nursing; peroperative complication; program development; risk assessment; standard; surgical equipment; surgical sponge; total quality management; United States

Policy for prevention of a retained sponge after vaginal delivery - Garry, D.J.; Asanjarani, S.; Geiss, D.M. (Case Reports in Medicine, 2012)
Background. Policies for sponge count are not routine practice in most labor and delivery rooms. Ignored or hidden retained vaginal foreign bodies has potentially significant health care morbidity. Case. This was a case of a retained vaginal sponge following an uncomplicated spontaneous vaginal delivery. Delivery room policy resulted in the discovery of the sponge on X-ray when an incorrect sponge count occurred and physical exam did not find the sponge. Conclusion. This emphasizes the use of protocols to enhance patient safety and prevent medical error. © Copyright 2012 David J. Garry et al.
Keywords: azithromycin; oxytocin; adolescent; article; case report; Chlamydia; delivery room; epidural anesthesia; epidural catheter; female; foreign body; health care policy; human; labor induction; laceration; maternal morbidity; medical error; oligohydramnios; patient safety; pelvis radiography; periurethral laceration; physical examination; prenatal care; priority journal; retained instrument; retained sponge; surgical sponge; uterine cervicitis; vagina laceration; vaginal delivery

Resection and radiofrequency ablation in the treatment of hepatocellular carcinoma: A single-center experience - Karabulut, K.; Aucejo, F.; Akyildiz, H.Y.; Siperstein, A.; Berber, E. (Surgical Endoscopy, 2012)
Background We have been utilizing both resection and laparoscopic radiofrequency ablation (RFA) to treat hepatocellular carcinoma (HCC). The aim of this study is to describe patient characteristics and outcome for each treatment modality from a single institution. Methods Medical records of HCC patients who underwent resection (n = 92) or laparoscopic (RFA) (n = 92) between 1997 and 2010 were reviewed. Univariate Kaplan- Meier and multivariate Cox proportional-hazards model were used to analyze survival. Results Patients with normal liver function and larger tumors were resected, and those with liver dysfunction, portal hypertension, and multiple tumors were ablated. Tumor size was larger in the Resection group, whereas number of tumors was higher in the RFA group. Child class and Barcelona Clinic Liver Cancer (BCLC) staging were more advanced in the RFA group. Hospital stay was longer, and morbidity and mortality higher in the Resection versus the RFA group. There was no difference in diseasefree survival, but the 5-year actual survival was significantly higher (40% versus 21%) in the Resection group. On univariate analysis, number of tumors, tumor size, platelet count, BCLC stage, Child class, and type of surgery were predictors of overall survival. On multivariate analysis, Child class and number of tumors were independent predictors of overall survival. Conclusions To our knowledge, this is the largest North American series reporting on RFA and resection for HCC from a single institution. Herein, we describe the perioperative and oncologic outcomes to be expected when these modalities are used in a certain treatment algorithm. © Springer Science+Business Media, LLC 2011.
Keywords: antineoplastic agent; abdominal abscess; adolescent; adult; aged; article; bile leakage; cancer staging; cancer survival; chemoembolization; conservative treatment; controlled study; deep vein thrombosis; delirium tremens; disease free survival; esophagus varices bleeding; female; hematoma; hemihepatectomy; human; laparoscopic surgery; length of stay; liver cell carcinoma; liver dysfunction; liver failure; liver function; liver resection; major clinical study; male; medical record review; morbidity; mortality; multiple cancer; overall survival; percutaneous drainage; portal hypertension; prediction; priority journal; radiofrequency ablation; reoperation; respiratory distress; retained instrument; seroma; surgical infection; surgical technique; platelet count; treatment outcome; tumor volume; wedge resection

Unusual spine anatomy contributing to wrong level spine surgery: A case report and recommendations for decreasing the risk of preventable 'never events' - Lindley, E.M.; Botolin, S.; Burger, E.L.; Patel, V.V. (Patient Safety in Surgery, 2011)
Background: Wrong site surgery is one of five surgical "Never Events," which include performing surgery on the incorrect side or incorrect site, performing the wrong procedure, performing surgery on the wrong patient, unintended retention of a foreign object in a patient, and intraoperative/immediate postoperative death in an ASA Class I patient. In the spine, wrong site surgery occurs when a procedure is performed on an unintended vertebral level. Despite the efforts of national safety protocols, literature suggests that the risk for wrong level spine surgery remains problematic.Case Presentation: A 34-year-old male was referred to us to evaluate his persistent thoracic pain following right-sided microdiscectomy at T7-8 at an outside institution. Postoperative imaging showed the continued presence of a herniated disc at T7-8 and evidence of a microdiscectomy at the level immediately above. The possibility that wrong level surgery had occurred was discussed with the patient and revision surgery was planned. During surgery, the site of the previous laminectomy was clearly visualized; however, we also experienced confusion when verifying the level of the previous surgery. We ultimately used the previous laminectomy site as a landmark for identifying and treating the correct pathologic level. Postoperative consultation with Musculoskeletal Radiology revealed the patient had two abnormalities in his spinal anatomy that made intraoperative counting of levels inaccurate, including a pair of cervical ribs at C7 and the absence of a pair of thoracic ribs.Conclusion: This case highlights the importance of strict adherence to a preoperative method of vertebral labeling that focuses on the landmarks used to label a pathologic disc space, rather than simply relying on the reference to a particular level. That is, by designating the pathological level as the disc space associated with the fourth rib up from the last rib-bearing vertebrae, rather than calling it "T7-8", then the correct level can be found intraoperatively even in the case of abnormal segmentation. We recommend working closely with radiology during preoperative planning to identify unusual anatomy that may have been overlooked. We also recommend that radiology colleagues use the same system of identifying pathological levels when dictating their reports. Together, these strategies can reduce the risk of wrong level surgery and increase patient safety. © 2011 Lindley et al; licensee BioMed Central Ltd.
Keywords: nonsteroid antiinflammatory agent; adult; article; backache; case report; clinical decision making; clinical feature; computer assisted tomography; lack of drug effect; human; intervertebral disk hernia; discectomy; laminectomy; male; nuclear magnetic resonance imaging; patient assessment; practice guideline; rib fracture; spine fusion; spine malformation; spine surgery; surgical error; surgical risk; thorax epidural anesthesia; thorax pain

Prevention of retained surgical items - Feldman, D.L. (Mount Sinai Journal of Medicine, 2011)
Reduction in retained surgical items is an important part of any operating room patient-safety effort. Any item used in an operation can result in a retained surgical item, but sponges are the most frequent and the abdomen is the most common location. Retained sponges can cause significant morbidity, and the costs associated with both prevention and treatment of retained surgical items, including legal costs, can be considerable. This review will examine counting, teamwork, radiography, and new technology as methods used to prevent retained surgical items. Even though none of these techniques individually is likely to completely prevent retained surgical items, when used together the numbers can be reduced. Mt Sinai J Med 78:865-871, 2011. © 2011 Mount Sinai School of Medicine.
Keywords: article; body mass; human; medical record; medical staff; patient safety; radiography; surgical equipment; teamwork

A 61-year-old man with recurrent pneumonia - Li, M. (Respirology, 2011)
A 61-year-old male, a company staff for 30 years and on leave for 2 years, presented to the pulmonary department with one week of moderate fever and nonproductive cough. The physical examination showed temperature of 37.5 °C, heart rate of 90 beats/minute, respiratory rate of 20 breaths/minute and BP if 150/90 mmHg. The findings of his cardiac examination were normal. Pulmonary examination revealed decreases tactile fremitus, dullness and decreased breath sound at right lower lobe. No rales could be heard throughout both lung fields. The results of remainder of the examinations were unremarkable. Admission laboratory results showed elevated WBC count (10400/ll) with a normal differential, an increased C reactive protein level (108 mg/l), partial arterial oxygen pressure (PO2) of 78 mmHg, the carbon dioxide pressure (POC2) of 32 mmHg, and PH 7.45. The forced vital capacity was 2.16 l (62.8% of predicted) and the forced expiratory volume in 1 second (FEV1) was 1.97 l (72.8% of predicted). A chest computerized tomography (CT) showed consolidation and atelectasis if the right lower lobe and obstruction of the right intermediate bronchus at the level of right pulmonary artery (Figure 1). Multiplanar and three-dimensional (3D) imaging of the central airway demonstrated a spherical foreign body in the right intermediate bronchus (Figure 2). In autofluorescence bronchoscopy, a mobile, pedunculated, and pinkish polypoid tumor protruding from the right lower lobe bronchus was observed. No invasion of bronchial wall was detected. As it was difficult to get through the bronchus, we performed an inferior bronchoscopy high-frequency electrosurgical snare resection. The pathological examination revealed that the specimen was a 15×25 mm ellipsoid covered by normal ciliated pseudostratified columnar epithelium and stratified squamous epithelium. The polyps consisted of fibrovascular stroma with scattered lymphocytes, plasma cells and vessels. Diagnosis: Fibroepithelial polyp of the bronchus. Tumors in the tracheobronchial tree are distinctly uncommon and account for 0.1-0.4% of malignant diseases. After the review of literature, we found the morbidity of this polyp was still uncertain. Ans over the past few decades, about 21 patients with tracheobronchial fibroepithelial polyp were reported. Only 10 case reports are available for analysis. To our knowledge, this is the first report in china population. Although the pathogenesis of fibroepithelial polyp is still unresolved, chronic inflammatory processes may play a key role. Several chronic inflammatory etiologic factors such as chronic smoke inhalation, chronic inflammation of asthma and COPD, repeated airway infections, foreign body aspiration, and prolonged mechanical ventilation may potentially be the cause.
Keywords: C reactive protein; society; human; Asian; male; pneumonia; bronchus; polyp; examination; neoplasm; bronchoscopy; forced vital capacity; forced expiratory volume; thorax; computer assisted tomography; obstruction; pulmonary artery; imaging; airway; atelectasis; autofluorescence; surgery; columnar epithelium; squamous epithelium; foreign body; lymphocyte; plasma cell; stroma; diagnosis; tracheobronchial tree; morbidity; patient; China; pathogenesis; inflammation; etiology; smoke; case report; inhalation; chronic inflammation; asthma; respiratory tract infection; foreign body aspiration; population; fever; coughing; physical examination; temperature; heart rate; breathing rate; abnormal respiratory sound; lung; laboratory; leukocyte count; arterial oxygen tension; carbon dioxide tension; pH; artificial ventilation

Orbital compartment syndrome: A case series - Sun, M.; Chan, W.O.; Selva, D. (Clinical and Experimental Ophthalmology, 2011)
Purpose: Ocular compartment syndrome (OCS) is a rare ocular emergency where urgent surgical treatment is required to avoid irreversible visual loss. We describe the clinical presentation and management for patients presenting to our centre with OCS. Methods: Single centre, retrospective case series. We included patients with a diagnosis of OCS that presented to the Royal Adelaide Hospital from 2004 to 2011. We reviewed the clinical features, imaging and timing of intervention from their clinical records. Results: 9 patients were included. 5/9 of our patient had preceding trauma, while other etiologies included post-operative cellulitis, foreign body, prolonged prone position during surgery, and cavernous sinus thrombosis. All had acute, painful decrease in visual acuity. Common examination findings included proptosis, relative afferent papillary defect, periorbital oedema, ophthalmoparesis and chemosis. Globe tenting was evident on radiological imaging for 6/9 cases. All the patients underwent surgical decompression. Three patients had visual recovery of more than 3 lines of Snellen acuity after having decompression less than two hours after onset of symptoms. The remaining patients had minimal visual recovery, with postoperative visual acuities ranging from count fingers to no perception to light. Conclusion: Delayed decompression more than two hours after the onset of OCS leads to irreversible visual loss. All patients presenting with history and examination findings suggestive of OCS should undergo emergency canthotomy and cantholysis prior to any additional investigations to minimize visual loss.
Keywords: orbit; compartment syndrome; case study; New Zealand; college; human; patient; visual impairment; surgery; visual acuity; emergency; imaging; decompression; examination; clinical feature; cavernous sinus thrombosis; hospital; diagnosis; body position; foreign body; cellulitis; ophthalmoplegia; etiology; periorbital edema; chemosis; decompression surgery; exophthalmos; injury

A system-wide initiative to prevent retained vaginal sponges - Chagolla, B.A.; Gibbs, V.C.; Keats, J.P.; Pelletreau, B. (MCN The American Journal of Maternal/Child Nursing, 2011)
As any perinatal nurse knows, retained vaginal sponges are an obstetrical and postpartum patient safety problem. As surgical sponge counts are not routine in some obstetrical units for vaginal births, our healthcare system chose to institute a rigorous process to eliminate retained sponges in all vaginal births. This article describes this process, along with the lessons learned, when Catholic Healthcare West implemented the Sponge ACCOUNTing System in its 32 hospitals in California, Arizona, and Nevada. Implementation of this process involved the standardization of practice for obstetricians, certified nurse midwives, nurses, obstetric technicians, radiologists, and radiology technicians in the management and accounting of surgical sponges. Copyright © 2011 Lippincott Williams & Wilkins.
Keywords: article; female; foreign body; human; medical error; methodology; nurse midwife; obstetrical nursing; obstetrics; pregnancy; radiology; safety; standard; surgical sponge; United States

Differences in Attentional Strategies by Novice and Experienced Operating Theatre Scrub Nurses - Koh, R.Y.I.; Park, T.; Wickens, C.D.; Ong, L.T.; Chia, S.N. (Journal of Experimental Psychology: Applied, 2011)
This study investigated the effect of nursing experience on attention allocation and task performance during surgery. The prevention of cases of retained foreign bodies after surgery typically depends on scrub nurses, who are responsible for performing multiple tasks that impose heavy demands on the nurses' cognitive resources. However, the relationship between the level of experiences and attention allocation strategies has not been extensively studied. Eye movement data were collected from 10 novice and 10 experienced scrub nurses in the operating theater for caesarean section surgeries. Visual scanning data, analyzed by dividing the workstation into four main areas and the surgery into four stages, were compared to the optimum expected value estimated by SEEV (Salience, Effort, Expectancy, and Value) model. Both experienced and novice nurses showed significant correlations to the optimal percentage dwell time values, and significant differences were found in attention allocation optimality between experienced and novice nurses, with experienced nurses adhering significantly more to the optimal in the stages of high workload. Experienced nurses spent less time on the final count and encountered fewer interruptions during the count than novices indicating better performance in task management, whereas novice nurses switched attention between areas of interest more than experienced nurses. The results provide empirical evidence of a relationship between the application of optimal visual attention management strategies and performance, opening up possibilities to the development of visual attention and interruption training for better performance. © 2011 American Psychological Association.
Keywords: adult; article; attention; clinical competence; eye movement; human; nursing staff; operating room; task performance; workload

The breast: A clean-contaminated surgical site - Bartsich, S.; Ascherman, J.A.; Whittier, S.; Yao, C.A.; Rohde, C. (Aesthetic Surgery Journal, 2011)
Background: Capsular contracture is one of the most common complications associated with breast implants. While the cause of this process has not yet been elucidated, subclinical infection is a likely culprit. Objectives: The authors assess the hypothesis that a probable source of contamination is endogenous breast bacteria, likely originating in the ducts themselves and most concentrated near the nipple. Methods: Twenty-five healthy patients presenting for routine reduction mammaplasty were recruited as study participants. Tissue samples were taken intraoperatively from the periareolar, inframammary, and axillary regions of each sampled breast. Specimens were then processed in the microbiology laboratory, and quantitative bacterial counts were obtained. Results: Of the 50 breasts sampled, 19 yielded positive culture results, for a rate of 38%. There was a significant difference in the positive culture rate among all three sites, with increasing quantitative bacterial counts in the axillary, inframammary, and periareolar regions, respectively. The most commonly-identified organisms in this study included various species of Staphylococcus and Propionibacterium acnes, with S. epidermidis being the most common. Conclusions: The breast harbors significant endogenous bacteria that can become the source of spontaneous or postoperative infection. Positive intraoperative cultures with high quantitative counts suggest that breast tissue harbors more bacteria than normal skin flora. Routine perioperative antibiotic prophylaxis may be suboptimal for the prevention of foreign body seeding in this setting. Furthermore, bacterial concentrations are highest in areas with the most ductal tissue, namely the periareolar region. These findings may be helpful when considering which incision site to select for augmentation mammaplasty. © 2011 The American Society for Aesthetic Plastic Surgery, Inc.
Keywords: article; bacterial count; bacterium culture; bacterium identification; breast reconstruction; clinical article; female; human; human tissue; implant capsular contracture; intraoperative period; priority journal; Propionibacterium acnes; skin flora; Staphylococcus; Staphylococcus epidermidis; surgical infection; tissue section

Designing a Safer Process to Prevent Retained Surgical Sponges: A Healthcare Failure Mode and Effect Analysis - Steelman, V.M.; Cullen, J.J. (AORN Journal, 2011)
A retained surgical sponge is a sentinel event that can result in serious negative outcomes for the patient. Current standards rely on manual counting, the accuracy of which may be suspect, yet little is known about why counting fails to prevent retained sponges. The objectives of this project were to describe perioperative processes to prevent retained sponges after elective abdominal surgery; to identify potential failures; and to rate the causes, probability, and severity of these failures. A total of 57 potential failures were identified, associated with room preparation, the initial count, adding sponges, removing sponges, the first closing count, and the final closing count. The most frequently identified causes of failures included distraction, multitasking, not following procedure, and time pressure. Most of the failures are not likely to be affected by an educational intervention, so additional technological controls should be considered in efforts to improve safety. © 2011 AORN, Inc.
Keywords: article; human; public hospital; safety; sentinel surveillance; surgical sponge; United States

Ketorolac 0.45% ophthalmic solution - McCormack, P.L. (Drugs and Aging, 2011)
Ketorolac 0.45 ophthalmic solution is a topical NSAID indicated in the US for the treatment of ocular pain and inflammation following cataract surgery.In animal studies, the ocular relative bioavailability of single-dose topical ketorolac 0.45 ophthalmic solution was 2- to 3-fold higher than that of ketorolac 0.4 ophthalmic solution.In two identically designed, randomized, double-masked, multicentre trials in adult patients undergoing cataract extraction, the proportions of patients with a summed ocular inflammation score of zero for anterior chamber cell count plus anterior chamber flare on day 14 after surgery were significantly greater in those treated with topical ketorolac 0.45 ophthalmic solution than in those treated with vehicle placebo.Compared with placebo, topical ketorolac 0.45 ophthalmic solution significantly increased the proportion of patients who were pain-free on the day after surgery in both trials.Ketorolac 0.45 ophthalmic solution was generally well tolerated in clinical trials with lower overall incidences of treatment-emergent and treatment-related adverse events than placebo, and with no single treatment-related adverse event having a higher incidence than with placebo. © 2011 Adis Data Information BV. All rights reserved.
Keywords: ketorolac trometamol; amfenac; bromfenac; cyclooxygenase 1; cyclooxygenase 2; gatifloxacin; ketorolac; nepafenac; paracetamol; placebo; unclassified drug; analgesic activity; anterior eye chamber cell; anterior eye chamber cell; anterior eye chamber disease; anterior eye chamber flare; anterior eye chamber flare; anterior eye chamber inflammation; anterior eye chamber inflammation; antiinflammatory activity; antipyretic activity; area under the curve; article; blurred vision; cataract extraction; conjunctival hemorrhage; conjunctival hyperemia; cornea edema; drug bioavailability; drug blood level; drug efficacy; drug induced headache; drug penetration; drug tolerability; enzyme inhibition; epiphora; eye burning; eye inflammation; eye pain; eyelid edema; face pain; foreign body; human; intraocular pressure; iritis; maximum plasma concentration; nonhuman; phacoemulsification; photophobia; postoperative pain; priority journal; Leporidae; recommended drug dose; side effect; single drug dose; time to maximum plasma concentration; uveitis; visual acuity; wound healing; acuvail

Detecting patient safety indicators: How valid is "foreign body left during procedure" in the Veterans Health Administration? - Chen, Q.; Rosen, A.K.; Cevasco, M.; Shin, M.; Itani, K.M.F.; Borzecki, A.M. (Journal of the American College of Surgeons, 2011)
Background: The Agency for Healthcare Research and Quality (AHRQ) developed patient safety indicator (PSI) 5, "Foreign body left during procedure," to flag accidental foreign bodies in surgical and medical procedures. This study examined how well this indicator identifies true foreign body events in the Veterans Health Administration (VA). Study Design: This was a retrospective study within 28 selected VA hospitals from fiscal year 2003 to 2007. Trained abstractors reviewed medical charts flagged by PSI 5 and determined true foreign body cases. We calculated the positive predictive value (PPV) of this indicator and performed descriptive analyses of true positive and false positive cases. Results: Of the 652,093 eligible cases, 93 were flagged by PSI 5 (0.14 per 1,000). Forty-two were true positives, yielding a PPV of 45% (95% CI 35% to 56%). False positives were due to a foreign body that was present on admission (57%) or coding errors (43%). True foreign bodies were associated with surgical (n = 23) and medical (n = 19) procedures. The most common type of surgical foreign body was a sponge (52%). Overall, approximately 40% of foreign bodies were related to a device failure or malfunction (30% surgical vs 53% medical foreign bodies). Postoperative complications included pain (24%), infection (12%), adhesions (5%), and bowel obstruction (5%). Conclusions: The reported rate of foreign body events as detected by PSI 5 is low in the VA, but occurs in both surgical and medical procedures. Despite widespread implementation of surgical counts, quality improvement efforts should focus on novel ways to eliminate this "never event" from operations. Future studies are needed to better understand the preventability of medical procedure-associated foreign bodies and particularly, device failure-related foreign bodies. © 2011 by the American College of Surgeons.
Keywords: aged; article; clinical indicator; descriptive research; false positive result; female; foreign body; foreign body left during procedure; gauze dressing; hospital admission; human; intestine obstruction; major clinical study; male; medical device; medical record review; patient coding; patient safety; postoperative complication; postoperative infection; postoperative pain; predictive value; priority journal; retrospective study; surgical sponge; tissue adhesion; treatment failure

Multiple pulmonary nodules in a smoker - Got it? - Kern, L.; Rüdiger, J.; Meyenberger, C.; Rodriguez, R.; Brutsche, M.H. (Respiration, 2011)
Introduction: The incidental detection of multiple pulmonary nodules in a smoking patient is highly suspicious for the presence of malignant disease of either pulmonary or metastatic origin. However, pulmonary nodules can also be seen in non-malignant extrapulmonary diseases including inflammatory bowel disease. Case presentation: A 46-year old patient was referred after the detection of multiple pulmonary nodules in both lower lung lobes in an abdominal computed tomography (CT) scan performed for the investigation of frequent loose stools (Figure 1). The patient had a smoking history of 20 pack years and was otherwise healthy. He complained of temperatures of around 37.2° Celsius, night sweats and weakness. Symptoms started six weeks prior to admission and did not respond to antibiotics. Upon presentation, the patient was alert and in no distress. Abdominal examination and chest auscultation were unremarkable. Positron emission tomography (PET) scan showed an elevated uptake with a standardized uptake value (SUV) of 4.6. Pulmonary function tests and arterial blood gas analysis were normal. Bronchoscopy with brushings was non-diagnostic. Bronchoalveolar lavage (BAL) revealed normal total- and differential cell counts. A transthoracic biopsy showed foreign-body type granuloma and intraalveolar fibroblasts, consistent with organizing pneumonia (Figure 2). Colonoscopy revealed pancolitis without terminal ileitis. Biopsies of the colonic mucosa showed changes compatible with ulcerative colitis (UC). The diagnosis of organizing pneumonia (OP) in the context of UC was retained. A therapy with mesalazin was started and the patient's bowel symptoms resolved rapidly. However, he still complained of subfebrile temperatures, weakness and night sweats. Even though no functional impairment induced by OP was found, a course of systemic steroids was started. One week later, the patient was free of symptoms. Discussion: UC is an inflammatory bowel disease usually limited to the colon mucosa. However, extraintestinal manifestations are well described and include also lung disease. Airway involvement is mostly seen and often presents as chronic cough, mucoid impaction, bronchial obstruction and bronchiectasis. OP in the context of UC has been described before in a few case reports, but seems to be a rare entity with the last publication dating back to 2003. Furthermore, pulmonary manifestations of UC usually appear years after diagnosis, unlike in this case.
Keywords: steroid; antibiotic agent; society; multiple pulmonary nodules; otorhinolaryngology; smoking; head and neck surgery; thorax surgery; patient; human; diagnosis; enteritis; organizing pneumonia; temperature; night sweat; weakness; colon mucosa; lung disease; airway; bronchus obstruction; bronchiectasis; case report; lung nodule; lung lobe; computer assisted tomography; loose feces; examination; thorax; auscultation; positron emission tomography; lung function test; arterial gas; blood gas analysis; coughing; lung lavage; leukocyte differential count; transthoracic biopsy; foreign body; granuloma; fibroblast; colonoscopy; bronchoscopy; ileitis; biopsy; ulcerative colitis; therapy; intestine; functional disease

Improvement of the biocompatibility of alloplastic materials for surgery due to hernia, incontinence and organ prolapse - Eimer, C.; Gerullis, H.; Bagner, J.; Lammers, B.; Theuerkauf, I.; Ramon, A.; Otto, T. (International Urogynecology Journal and Pelvic Floor Dysfunction, 2011)
Hypothesis/Aim of study:The american Food and Drug Administration (FDA) Issued a warning concerning the application of alloplastic materials for thesurgical treatment of female Incontinence and prolapse reporting more than 1000 severe adverse events associated with theused materials.Special surgical training together with the management of risk and AE's are recommended [1, 2]. The Improvement of thebiocompatibility coating foreign materials with e.g. autologous substances seems to be mandatory and was performed In an Invitrosetting using autologous plasma for the coating of meshs.Material and Methods:In order to answer the question whether coating of alloplastic materials with autologous material can lead to Improvedbiocompatibility, the following study approach was established:12 patients were Included. Written Informed consent of each patient was obligatory prior to the start of the procedure. 10ml ofblood, plasma and serum of each patient were preserved. Myoblasts, endothelial cells and fibroblasts of each patient werecultivated separately. Cell count and growth are comparable In all approaches within a test duration of 6 weeks.Immunohistochemical and microscopic evaluation of cell count and adherence Is performed considering the chosen coating forthe alloplastic material.Results:The In vitro analyses are Independent from gender and Individual patient features.Regarding tissue specifity different cell growth can de defined In favour of fibroblasts:fibroblasts > myoblasts > endothelial cells. Improved cell adhesion Is found on alloplastic meshs covered with autologousplasma compared to non- covered meshs. This finding Includes all types of cells being tested. A covering of meshs with serumor collagen seems to be of disadvantage. Looking at the Intensity of cell adhesion on the different meshs the following rankingcan be disposed:1. TFT Motifmesh ®, ProxyBiomedical2. Dynamesh®, FEG Textiltechnik3. Surgimesh ®, Aspide Medical, Resorba4. PDS Plate ®, Johnson & Johnson5. Mersilene Band, Johnson & Johnson6. Vitamesh ®, ProxyBiomedical7. Vicryl Band, Johnson & Johnson8. TiLoop ®, PFMCell adhesion on the following alloplastic materials could be verified neither In the uncovered nor In the covered approach:Ethisorb Patch ®, EthiconProceed surgical mesh ®, EthiconCollagenmeshResodont mesh ®, ResorbaParasorb mesh ®, ResorbaDualmesh®, Fa.GoreMycromesh®, Fa.GorePCL scaffoldAdVance male sling ®, AMSSeratim®, Serag-Wiessner Interpretation of results:Cell adhesion to the tested alloplastic materials regarding cells of the pelvic floor Is Insufficient. This observation may explainthe occurrence of foreign-body reaction and missing Integration of alloplastic materials Into the pelvic floor.Concluding message:Coating of meshs with autologous plasma results In an Improvement of the biocompatibility of alloplastic materials.
Keywords: collagen; polyethylene terephthalate; polyglactin; tissue injury; incontinence; biocompatibility; hernia; society; continence; surgery; human; patient; fibroblast; cell adhesion; myoblast; endothelium cell; blood autotransfusion; cell count; female; surgical training; risk; foreign body; informed consent; procedures; serum; in vitro study; gender; tissues; cell growth; adhesion; surgical equipment; male; pelvis floor; foreign body reaction; pelvis; Food and Drug Administration; plasma

Clinical presentation and outcome of perforating ocular injuries due to BB guns: A case series - Nili Ahmadabadi, M.; Karkhaneh, R.; Kord Valeshabad, A.; Tabatabai, A.; Jager, M.J.; Nili Ahmadabadi, E. (Injury, 2011)
Purpose: To describe the clinical presentations and treatment modalities of a series of BB gun-related perforating ocular injuries. Methods: Clinical records of all consecutive cases of perforating BB gun injuries to the globe seen between September 2004 and September 2008 were reviewed retrospectively. At the time of the trauma and after final treatment, all patients underwent a complete ocular examination, including visual acuity, applanation tonometry for intraocular pressure, slit lamp biomicroscopy, indirect ophthalmoscopy and fundus photography, if possible. In all cases, primary globe repair was performed in the first session, and then appropriate surgery took place based on the individual situation. Results: In this study, 13 patients (11 males and 2 females) with a mean age of 20.8 years (range 9-50 years) were enrolled. The mean follow-up period was 7.2 ± 4.3 months (range 1-25 months). Initial visual acuity (VA) ranged from no-light perception (NLP) to finger counting (CF). Vitreous haemorrhage and retinal detachment were present in all involved eyes. Hyphema (30.76%), uveal and retinal prolapse (30.8%), retinal incarceration (30.8%) and retinal haemorrhage (53.8%) were other ocular findings. VA remained stable in 46.2% of the patients (6 cases). The best achieved final VA was CF at 2 m in one case after 6 months follow-up. After several surgical procedures, enucleation was necessary in only 2/13 (15.4%) cases. Conclusion: Despite several surgical procedures which decreased the number of enucleations, BB gun-perforating ocular injuries still lead to a grim visual outcome. This implies the importance of political strategies targeting on education of parents and restriction for children to access to these guns. © 2010 Elsevier Ltd. All rights reserved.
Keywords: adolescent; adult; article; ball bearing gun; child; clinical article; computer assisted tomography; eye examination; eye fundus; eye injury; eye photography; female; firearm; follow up; foreign body; human; hyphema; intraocular pressure; male; oculoplethysmography; ophthalmoscopy; penetrating trauma; priority journal; retina detachment; retrospective study; school child; slit lamp; tissue injury; vision; visual acuity; vitreous hemorrhage

Leiomyoma of the female urethra - Perugia, G.; Di Viccaro, D.; Chinazzi, A.; Antonini, F.; De Cillis, A.; Borgoni, G.; Croce, F.; Liberti, M. (Anticancer Research, 2011)
Background: Paraurethral leiomyoma is a rare benign hormone-dependent neoplasm of mesenchymal origin affecting women. Clinical evidence is variable but it tends to be asymptomatic or associated with the sensation of a foreign body, while urinary symptoms are rarely described. Excision of the mass is the recommended treatment and diagnosis is confirmed by pathological analysis to rule out the presence of a sarcoma. A case of paraurethral leiomyoma associated with dysuria, dyspareunia and obstructive voiding symptoms is reported here. Case Report: A 28-year-old woman, presented with dysuria, dyspareunia and occasional urinary retention, associated with the presence in the vaginal introitus of a palpable, smooth, solid mass located above the urethral orifice just beneath the clitoris. Transvaginal ultrasonography showed a 25×25 mm hypoechoic mass, highly vascularized on colored Doppler imaging. The voiding cystogram did not show communication of the mass with the lower urinary tract but a constriction of the urethra was revealed. Axial T1-and T2-weighted MRI scans were performed and a neoplasm with signal similar to that of a uterine fibroid, compressing the urethra, was diagnosed. The patient underwent surgical excision of the mass, which was easily performed by blunt dissection, after 4-cm longitudinal incision of the anterior vaginal wall. The pathological analysis showed the presence of a paraurethral leiomyoma with less than 1 mitotic figure per 10 high-power fields. The patient had no immediate postoperative complications, the urethral catheter was removed two days after surgery and micturition was immediately restored. Urinary flow evaluation performed one month later revealed a normal Qmax nomogram and dyspareunia had disappeared. Discussion: Distinction between urethral, paraurethral, and anterior vaginal wall leiomyoma may be difficult due to their close anatomical proximity. Differential diagnosis of these lesions includes urethral diverticulum, Skene duct abscess, Bartolini gland cyst, Gartner duct cyst, vaginal wall cyst and urethral carcinoma. The literature supports the excision of these lesions to determine the mitotic count, which differentiates leiomyoma from locally recurrent or metastatic leiomyosarcoma, and this can help to predict the possibility of recurrence, which is extremely rare if there are fewer than 5 mitotic figures per 10 high-power fields. The case described here was unusual because of the symptoms (usually, there is paraurethral mass and increased urinary frequency, while voiding dysfunction and urinary retention, as presented here, are very rare) and the young age of the patient (28 years of age while the average age of patients at presentation is 47 years, with a range from 39 to 62 years).
Keywords: hormone; leiomyoma; urethra; oncology; society; patient; cyst; dyspareunia; excision; female; neoplasm; dysuria; urine retention; leiomyosarcoma; urinary frequency; sensation; foreign body; diagnosis; case report; solid; clitoris; transvaginal echography; imaging; cystography; interpersonal communication; ligation; nuclear magnetic resonance imaging; uterus myoma; dissection; incision; postoperative complication; urethral catheter; surgery; micturition; nomogram; differential diagnosis; urethra diverticulum; abscess; urethra carcinoma; sarcoma

A pictorial essay of orthopedic surgical sponges missing in action - Wu, R.; Scalcione, L.; Kulesa, M.; Luchs, J. (American Journal of Roentgenology, 2011)
Background Information: The purpose of this educational exhibit is to demonstrate the radiographic imaging characteristics of various orthopedic sponges to heighten awareness and aid in detection of foreign bodies in the intraoperative and perioperative setting. Educational Goals/Teaching Points: The educational exhibit will be organized using a pictorial approach to demonstrate the radiographic characteristics of various orthopedic sponges. Teaching points would include a literature review of the prevalence of retained operative foreign bodies as well as the sensitivity of conventional radiographs in detection. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: Various types of sponges, including lap sponges, peanut dissectors, etc., have been collected and conventional radiographs have been performed to document their appearance. The surgical sponges were imaged under wet and dry conditions both with and without a phantom to simulate the in vivo appearance of missing sponges. Comparison of radiographs with digital photographs was made. Conclusion: In various clinical settings, including emergent orthopedic trauma surgery, radiologists are often consulted to review intraoperative radiographs for sponge miscounts. It is essential for radiologists to be aware of the radiographic appearance of various orthopedic sponges to aid in accurate detection of potential foreign bodies.
Keywords: surgical sponge; society; X ray; X ray film; foreign body; imaging; radiologist; prevalence; teaching; peanut; phantom; photography; traumatology

Associations between operative site microbial counts and procedure classification in neurosurgery - Kourbeti, I.; Tsiodras, S.; Maraki, S.; Karabetsos, D.; Neophytou, C.; Filippou, M.; Ioannou, A.; Vakis, A. (Clinical Microbiology and Infection, 2011)
Objective: Correlation between operative site skin bacterial counts in neurosurgical procedures and the development of surgical site infections (SSI) has not been proven. We evaluated the association of bacterial Colony Forming Units (CFU), type of procedure and development of SSI in a prospective pilot study. Methods: Skin swab cultures were obtained within 1 cm from the incision;pre-,post-preparation and preclosure samples were obtained. Bacterial counts were enumerated and the most prevalent organisms were recorded. Procedures were classified as clean, clean with a foreign body, clean contaminated, contaminated and dirty. Results: 157 procedures (43.9% clean, 19.1% clean-contaminated, 26.1% clean with foreign body, 7.6% contaminated and 3.2% dirty) in 118 patients (62.4% male) were evaluated prospectively. 38.9%patients were hospitalized in the ICU. Oncology and trauma were the most common reasons for surgery (28% and 26.8% respectively). 157 sample sets were cultured. 85.4% pre-prep,27% post-prep and 43.9% of the preclosure samples tested positive. Coagulase-negativestaphylococci (CoNS) were the most frequently isolated organisms irrespectively of sampling time (65%, 17.8% and 27.4% for samples 1, 2 and 3 respectively) and independently of procedure classification followed by P. acnes. The median cfu count log for CoNS were 2.97log (IQR 2.47- 3.73), 2.48 (range 2-2.76) and 2.47 (IQR 2-2.69) respectively for each sampling.P. acnes was the second most frequentpathogen isolated. The median cfu count log for P. acnes were 4.25log (IQR 3-4.58), 2.87 (IQR 2.48-3.43) and 4.3 (IQR 3.35-4.69)respectively for each sampling. There was a significant difference in rates of pathogens in preprep samples for the head compared to other sites (OR 2.9,p= 0.028). The same was true for the P. acnes isolated from head versus other sites for preprep and postprep samples (OR 5.2, p = 0.01 and OR 1.16, p = 0.024 repectively). Procedure classification or prolonged surgery duration were not associated with microbial counts irrespectively of sampling time. SSI development was not associated with bacterial CFU at any sampling but with ICU stay (p<0.001). Conclusion: CoNS and P. acnes were the most frequent bacterial pathogen cultured irrespectively of sampling. The pathogen cfu log did not significantly differ among the samples. P. acnes isolation correlated with head specimens. Procedure classification was not associated with microbial skin counts at any sampling. SSI was associated with ICU stay.
Keywords: coagulase; classification; neurosurgery; sampling; Propionibacterium acnes; skin; pathogenesis; human; patient; foreign body; bacterial count; colony forming unit; infection; operation duration; bacterium colony; incision; male; oncology; pilot study; surgery; acne; injury

The effects of lipoic acid eye drops in HIV-positive patients - Uglietti, A.; Pezzotta, S.; Antoniazzi, E.; Maserati, R. (Infection, 2011)
Background: Decreased tear production has been reported in<1.0% of the general population but in 20-39% in HIV-positive individuals. The incidence of the dry-eye syndrome (DES) under HAART remains unchanged compared to the incidence in the pre-HAART era. DES, likely caused either by HIV itself and HAART, is a tear film alteration involving both lipid and mucous lacrimal layers. Usually DES is treated with tear drops (ipromellosa or ialuronic acid) to avoid further corneal alterations. A new compound, lipoic acid, featured with antioxidant, epitheliotropic and neurotropic characteristics was evaluated in a eye drop association with ipromellosa in HIV-positive patients. Methods: This study (prospective, randomized, controlled, single blinded) assessed the effect of ipromellosa plus lipoic acid (group A) versus ipromellosa only (group B) eye drops on DES in HIV-positive patients. Patients were enrolled if complaining any eye drynessassociated symptom (burning, itching, foreign body sensation, photophobia) and hyperaemia. We excluded patients with infectious kerato-conjunctivitis, ocular inflammation, erosions and corneal ulcers, severe systemic comorbidities or previous surgery in anterior or posterior segment in the last 6 months. One drop of the randomized preparation was given in each eye three times a day for 3 months. The evaluation consisted in: physical examination, biomicroscopic exam, visual acuity, Schirmer test and tear break-up time test (BUT) measured in both eyes. Questionnaire about dry-eye symptoms and quantitative tests have been performed in baseline visit, then at 15, 30 and 90 days. Results: Eighteen patients (36 eyes) were randomized but only 32 eyes were analyzed. The demographic characteristics were similar in two groups. Mean age was 43 years (range 28-56), males were 11. All patients were on combination antiretroviral therapy (cART), HIVRNA was undetectable and median CD4 cell counts was 421 cells/ll (range 133-720). BUT improved significantly in group A versus B (at baseline: 5 s ± 2 and 6.17 s ± 1.60; after 90 days: 10.2 s ± 1.48 and 7 s ± 1.9, respectively, p = 0.01). Photophobia and hyperaemia also improved in a significant way (p = 0.03 for both parameters) in the group A versus B at the 3-month evaluation. A significant trend favouring group A was noted for other symptoms. The immune status as measured by CD4+ cell count and percentage did not changed during the observational period. Discussion: Patients treated with lipoic acid-containing eye drops showed a significant improvement in their inflammatory process when compared to a control treatment. This may be due to a quick stabilization of lacrimal film (already present at 15 days), irrespective of immune-virological status. Although the number of patients was limited, our results confirmed the epithelio-neuroprotective activity and epithelio-neurotropic, anti-oxidant functions of lipoic acid.
Keywords: thioctic acid; eye drops; CD4 antigen; acid; antioxidant; oxidizing agent; lipid; Human immunodeficiency virus; Human immunodeficiency virus infected patient; Retroviridae; acquired immune deficiency syndrome; patient; eye; highly active antiretroviral therapy; lacrimal fluid; dry eye; cell count; photophobia; hyperemia; pruritus; foreign body; sensation; keratoconjunctivitis; cornea ulcer; surgery; physical examination; visual acuity; Schirmer test; questionnaire; demography; male; therapy; immune status; inflammation; population; tear film; eye inflammation

Retained foreign body in surgical setting: A single center experience - Thakur, M.; Kumar, S.; Gill, N.; Bahado-Singh, R.O. (Journal of Pelvic Medicine and Surgery, 2011)
Objectives: To review risk factors and complications associated with retained foreign bodies in surgical patients. Materials and Methods: Retrospective review of medical records and litigation claims at Detroit Medical Center between 1998 and 2010. Chi square test and logistic regression were used for analysis. Results: There were a total of 67 patients who had 70 retained foreign bodies. These included 26 sponges (37.1%), 12 drains and catheters (17.1%), 6 instruments (8.5%), 3 needles (4.2%), 3 packings (4.2%) and 20 miscellaneous (including one resected bowel loop). Median age was 51years (range 1 day - 95 years), median BMI was 31.03 kg/m 2. Abdomen (35.7%) and thorax (12.8%) were the most commonly involved body cavities. Most common reason for search for foreign body was pain (27.5%). Median latency time of detection was 84 days (range 0 days - 14 years). Sponge count was available in 68.9% of the cases. Primary count was incorrect in 30% of the cases where a count was available. The common risk factors identified in the operative cases with retained foreign bodies were torrential bleeding(63.6%), extensive adhesions(36.3%), 91 surgical team(27.2%) and intra-op change of procedure(18%). Of these cases, 34.4% were emergency surgeries. Morbidity rate was 100% as all the patients required reoperation for removal of foreign body. Associated complications included fever, ileus, abscess, wound infection, acute ischemia and delayed recovery. There were no deaths. Conclusion: Retained surgical foreign body is a persistent medical error with severe complications. The surgeon should be cognizant of this possibility, especially in cases complicated by obesity, emergency situations, bleeding, adhesions and change of surgical teams or procedures.
Keywords: foreign body; surgeon; society; bleeding; risk factor; human; patient; adhesion; emergency surgery; morbidity; reoperation; fever; ileus; abscess; wound infection; ischemia; death; medical error; obesity; emergency; surgical patient; medical record; chi square test; logistic regression analysis; catheter; needle; intestine; abdomen; thorax; pain; latent period; law suit

Sensitivity of detection of radiofrequency surgical sponges: A prospective, cross-over study - Steelman, V.M. (American Journal of Surgery, 2011)
Background: A retained surgical sponge is a serious medical error that results in negative patient outcomes. Radiofrequency (RF) technology has recently been introduced to evaluate for the presence of a retained sponge. The aim of this study was to evaluate the sensitivity and specificity of the detection of surgical sponges embedded with an RF chip through the torsos of subjects of varying body habitus, including the morbidly obese. Methods: A prospective, crossover, and observer blinded study design was used. Subjects served as their own controls. With the subject supine, 4 surgical sponges were sequentially placed behind the subject's torso in locations approximating abdominal quadrants. Results: Two hundred ten subjects were enrolled in the study. Nearly half (n = 101) were morbidly obese. Eight hundred forty readings were taken. There were no false-positive or false-negative readings. The sensitivity and specificity of detection of the RF sponges through the torsos of subjects of varying body habitus were 100%. Conclusions: The sensitivity and specificity of RF sponge technology are much higher than published reports of surgical counts or published findings of intraoperative radiographs for retained sponges. Copyright © 2011 Published by Elsevier Inc.
Keywords: adult; aged; article; clinical trial; controlled clinical trial; controlled study; crossover procedure; diagnostic accuracy; diagnostic test accuracy study; false negative result; false positive result; female; human; major clinical study; male; morbid obesity; multicenter study; priority journal; radiofrequency; retained instrument; sensitivity and specificity; single blind procedure; supine position; surgical sponge; trunk; Blair-Port Wand

Using a data-matrix-coded sponge counting system across a surgical practice: impact after 18 months. - Cima, R.R.; Kollengode, A.; Clark, J.; Pool, S.; Weisbrod, C.; Amstutz, G.J.; Deschamps, C. (Joint Commission journal on quality and patient safety / Joint Commission Resources, 2011)
Retained surgical items (RSIs), most commonly sponges, are infrequent. Yet despite sponge-counting standards, failure to maintain an accurate count is a common error. To improve counting performance, technology solutions have been developed. A data-matrix-coded sponge (DMS) system was evaluated and implemented in a high-volume academic surgical practice at Mayo Clinic Rochester (MCR). The primary end point was prevention of sponge RSIs after 18 months. Two trials were conducted before implementation. A randomized-controlled trial assessed the system's function, efficiency, and ergonomics. The second, larger trial was conducted to validate the prior findings and test product improvements. After the trials, the system was implemented in all 128 operating/procedure rooms across the MCR campus on February 2, 2009. The institutionwide implementation was intended to avoid the possibility of having standard unmarked sponges and DMSs in the operating room suite concurrently. Before implementation, a retained sponge occurred on average every 64 days. Between February 2009 and July 2010, 87,404 procedures were performed, and 1,862,373 DMSs were used without an RSI (p < .001). After four cases, the average time to count a DMS decreased from 11 to 4 seconds. Total sponge counting time/operation increased without any increase in overall operative time. After 18 months, a DMS system eliminated sponge RSIs from a high-volume surgical practice. The DMS system caused no work-flow disruption or increases in case duration. Staff satisfaction was acceptable, with a high degree of trust in the system. The DMS system is a reliable and cost-effective technology that improves patient safety.
Keywords: article; cost benefit analysis; foreign body; health care quality; human; information processing; medical error; methodology; observer variation; pilot study; surgery; surgical sponge; time

Case report on textiloma of uterus - Begum, R.; Khanum, S. (Bangladesh Journal of Obstetrics and Gynecology, 2011)
A 30years of old hypothyroid lady, presented with foul smelling excessive whitish per vaginal discharge, associated with itching in vulva & pain in the lower abdomen following caesarean section 3 months back. Her uterus was palpably enlarged and firm. USG revealed bulky uterus with wall echo shadow sign. A CT scan of whole abdomen was done that revealed intra-uterine textiloma. During laparotomy huge amount of pus came out through wound and a mob was found within uterine cavity. Textiloma is a rare problem of surgery arising from retained gauze during operation. Careful counting of surgical gauze before closure and identification by newer techniques is required to prevent this iatrogenic complication.
Keywords: adult; article; benign uterus tumor; body mass; case report; cesarean section; colposcopy; computer assisted tomography; cytology; endometrium; female; human; human tissue; hypothyroidism; laparotomy; obesity; omentum; patient assessment; pelvis; uterine cervicitis; uterine cervix; uterine cervix dysplasia; uterus biopsy; uterus textiloma; vagina discharge; vagina pain

IgG4-related meningeal disease: Clinico-pathological features and proposal for diagnostic criteria - Lindstrom, K.M.; Cousar, J.B.; Lopes, M.B.S. (Acta Neuropathologica, 2010)
IgG4-related disease has evolved from originally being recognized as a form of pancreatitis to encompass diseases of numerous organs including the hypophysis and one reported case of dural involvement. A search of the University of Virginia, Division of Neuropathology files for 10 years identified ten cases of unexplained lymphoplasmacytic meningeal inflammation that we then evaluated using immunohistochemical stains for IgG4 and IgG. Ten control cases including sarcoidosis (4), tuberculosis (1), bacterial abscess (2), Langerhans cell histiocytosis (2), and foreign body reaction (1) were also examined. The number of IgG4-positive plasma cells was counted in five high power fields (HPFs) and an average per HPF was calculated. Cases that contained greater than ten IgG4-positive cells/HPF were considered to be IgG4- related. Five of the study cases met these criteria, including one case of leptomeningeal inflammation. All cases exhibited the typical histological features of IgG4-related disease including lymphoplasmacytic inflammation, fibrosis, and phlebitis. The dural-based lesions appear to represent a subset of the cases historically diagnosed as idiopathic hypertrophic pachymeningitis. While the leptomeningeal process most closely resembles non-vasculitic autoimmune inflammatory meningoencephalitis. Given these findings, IgG4-related meningitis should be considered in the differential diagnosis of meningeal inflammatory lesions after stringent clinical and histologic criteria are used to rule out other possible diagnoses. © Springer-Verlag 2010.
Keywords: immunoglobulin G; immunoglobulin G4; steroid; adult; aged; article; brain surgery; cell count; clinical article; clinical feature; controlled study; diagnostic test accuracy study; differential diagnosis; dura mater; female; fibrosis; follow up; histopathology; human; human tissue; immunohistochemistry; immunoreactivity; leptomeninx; male; meningitis; meningoencephalitis; meninx disorder; phlebitis; plasma cell; priority journal; treatment response

Flexible scaffolds based on poly(trimethylene carbonate) networks for cardiac tissue engineering - Bat, E.; Harmsen, M.C.; Plantinga, J.A.; Van Luyn, M.J.A.; Feijen, J.; Grijpma, D.W. (Journal of Controlled Release, 2010)
Poly(trimethylene carbonate) (PTMC) crosslinked by gamma irradiation was evaluated as a scaffolding material for cardiac tissue engineering. The PTMC networks allowed adhesion and proliferation of neonatal mouse cardiomyocytes and preservation of their phenotype. Highly porous structures having tuneable mechanical properties were prepared. The stiffness of these structures was close to that of myocardium. Upon implantation on rat hearts, gamma irradiated porous scaffolds were found to be eroded by macrophages and foreign body giant cells. Introduction: In engineering of soft tissues such as cardiovascular tissues, the stiffness of the scaffolds is of great importance in maintaining proper function of cells and controlling the differentiation of stem cells [1,2]. Cyclic stresses are often applied to cell-seeded constructs to control cell phenotype and to enhance production of extracellular matrix [3], which also requires flexible and elastic materials. PTMC is a biocompatible and biodegradable polymer with a low elastic modulus of approximately 6 MPa that can be crosslinked into an elastomeric network by gamma irradiation under vacuum [4,5]. In this study, we assessed the suitability of PTMC networks in preparing flexible porous scaffolds for cardiac tissue engineering. Experimental methods: PTMC was synthesized by ring opening polymerization of TMC monomer [5,6]. To characterise the networks formed upon gamma irradiation, equilibrium swelling experiments were performed on compression moulded films using chloroform [6]. For cell culturing studies, PTMC spin-coated glass discs (15 mm in diameter) and non-coated glass discs (controls) were gamma irradiated at 50 kGy under vacuum. Also controls in which fibronectin (1% in gelatine solution in phosphate buffer) was used to coat the films were employed. Neonatal cardiomyocytes (CMs) isolated from one-day old mice were seeded on the materials at a density of 5×104 cells/cm2 (n=3 per time point). The number of adhering CMs was determined by counting the nuclei stained with 4',6-diamidino-2-phenylindole on eight pictures per disc at 200× magnification. To determine the percentage of proliferating cells, 5- bromo-2-deoxyuridine was added to the cell cultures one day prior to fixation. Porous PTMC scaffolds were prepared by a process involving polymer coagulation, compression moulding and particulate leaching. Salt particles previously sieved to a size range of 106-250 μm were dispersed in polymer solutions in chloroform and then precipitated into a non-solvent. Porogen-to-polymer ratios were 85:15, 90:10, and 93:7 w/w. After drying, the salt-polymer composites were compression moulded and gamma irradiated (0, 50, and 100 kGy). The salt particles were leached out using Milli-Q water at 4 °C for 3-4 days. The porosities of the scaffolds were determined by measuring their size and mass. Their pore size and pore interconnectivity were assessed by scanning electron microscopy (SEM). Tensile measurements were performed on rectangular slabs of the porous specimens (n=5, measuring approximately 100×5×1 mm) according to ASTM-D 882-91. For supra-epicardial implantations on the hearts of Albino Oxford rats, salt leaching was done with cold sterile water under sterile conditions. All scaffolds were endotoxin-free. The disk-shaped scaffolds (n=4, 10 mm in diameter and approximately 500 μm in thickness) were implanted supra-epicardially through a small incision made on the pericardium and then fixated with a Safil® suture to the left ventricle. After 5 days of implantation, the hearts with the scaffolds were explanted. Histological and immunohistochemical analyses were performed to evaluate the response to the porous PTMC scaffolds. Histological sections were stained with toluidine blue. Macrophages and T-lymphocytes were stained using ED1 and R73 antibodies, respectively and the extent of vascularisation was assessed using anti-collagen IV. Results and discussion The purified PTMC polymer had a number average molecular weight of 306 kg/mol with a polydispersity index of 1.33. Gamma irradiation led to simultaneous sterilisation and crosslinking of the PTMC films. Upon irradiation at 50 kGy, networks with gel contents of 48±1% and swelling ratios of 84±1 vol/vol were formed. At 100 kGy, the respective values were 61±1% and 43± 1 vol/vol. Initially, the adhesion and proliferation of neonatal cardiomyocytes (CMs) on gamma irradiated PTMC surfaces were evaluated. The CMs adheredwell to the PTMC networks, in a time dependent fashion. After 2, 4, and 8 h of culturing, the total numbers of CMs adhering to the PTMC networks were 528±57, 603±360, and 1314±169, respectively. The values for the non-coated glass disc controls were lower at 2 h and 4 h (299±42 and 451±335, respectively), but comparable to those of the PTMC networks at 8 h (1626±137). It should be noted that, the adhesion of CMs onto PTMC networks was comparable to the adhesion onto the fibronectin-coated PTMC networks. The values were 607±380, 887±67, and 1559±667 after 2, 4 and 8 h of culturing, respectively. The CMs had a more spread morphology on the PTMC networks than when compared to non-coated glass discs, especially on the early days of culturing (Fig. 1A and B). The CMs also proliferated very well on the networks, almost reaching confluency after 14 days of culture (Fig. 1D). Importantly, the cells beat spontaneously, suggesting that they had preserved their phenotype. The percentage of proliferating cells increased during culturing, reaching 20.9±3.3% for PTMC networks and 25.1±4.2 for the noncoated controls. Figure Presented Porous PTMC structures were prepared by a salt-leaching technique. Porous structures with high porosities ranging from 70.8±1.7 to 86.1±0.1% depending on the porogen-to-polymer ratio were obtained. SEM analysis of the porous structures revealed that the pores were interconnected and their sizes ranged from 100 to 200 μm(data not shown). Crosslinking by gamma irradiation resulted in form-stable porous structures: upon incubation in PBS at 37 °C for two days, non-irradiated porous structures shrunk by 35 to 55 vol.% depending on the porogen-to-polymer ratio, whereas no significant shrinkage was observed for the crosslinked structures. Shrinkage of scaffolds is not desired, as it would lead to lower porosities and pore sizes. The porous PTMC structures were highly flexible, with elastic moduli that could be varied from 373±60 to 84±12 kPa by adjusting the porogen-to-polymer ratio (porosity) and (to a lesser extent) by adjusting the irradiation dose (Fig. 2A). This allowed the preparation of structures with stiffness values close to those of human myocardium (20-500 kPa) [7]. The stress at break values of the porous structures also depended on porosity and the applied irradiation dose, the values ranged from 469±30 to 72±8 kPa. All materials exhibited high elongations at break ranging from 145±20 to 209± 24%. A significant dependence on porosity or irradiation dose was not observed. Figure Presented The host response to tissue engineered constructs is a key factor in determining their success [8.9]. These responses can be towards the biomaterial component and/or the implanted cells, which can also influence each other. Moreover, the biodegradation process and its rate can modulate these responses. We investigated the response to bare PTMC scaffolds (porosity of approximately 80% and irradiated at 50 kGy) which were supraepicardially implanted on the hearts of rats. After five days of implantation, macroscopically no abnormalities were observed on the explanted hearts. At the implant site large numbers of newly formed blood vessels were present, which is highly desired in tissue engineering (Fig. 3A). The density of lymphocytes at the implant sitewas not high (115±27 cells/mm2). However, already at this early time point, high numbers of macrophages and foreign body giant cells had infiltrated the scaffolds and their surroundings (Fig. 3B and C). These cells were found to have phagocytosed fragments of the scaffolds. These histological and immunohistochemical evaluations show that the PTMC scaffoldswere angiogenic and had been rapidly degraded upon implantation on rat hearts. Figure Presented. Conclusion: Networks based on PTMC are useful materials for cardiac tissue engineering, as they allow the adhesion and proliferation of neonatal cardiomyocytes and can be easily processed into flexible porous scaffolds with tuneable mechanical properties. However, the erosion of these materials needs to be tuned to achieve an appropriate balance between scaffold degradation and tissue regeneration.
Keywords: cyclopropane; carbonic acid; polymer; glass; chloroform; fibronectin; tolonium chloride; antibody; collagen type 4; biomaterial; monomer; gelatin; phosphate; 4',6 diamidino 2 phenylindole; broxuridine; solvent; water; sterile water; endotoxin; heart; drug delivery system; tissue engineering; porosity; adhesion; gamma irradiation; implantation; rat; irradiation; compression; rigidity; phenotype; leaching; macrophage; density; giant cell; swelling; Young modulus; implant; cell proliferation; mouse; cross linking; tissues; vacuum; cardiac muscle; suture; heart left ventricle; tissue section; T lymphocyte; vascularization; scanning electron microscopy; molecular weight; instrument sterilization; morphology; human; immune response; biodegradation; blood vessel; lymphocyte; tissue regeneration; preservation; engineering; soft tissue; stem cell; extracellular matrix; ring opening; cell culture; albinism; thickness; incision; pericardium; polymerization

Incorrect surgical counts: A qualitative analysis - Rowlands, A.; Steeves, R. (AORN Journal, 2010)
Ensuring that patients remain free of unintended retained foreign bodies is a primary responsibility of perioperative nurses and surgical technologists. However, these incidents continue to occur despite hospital policies and AORN recommended practice guidelines for their prevention. To provide insight into how incorrect surgical counts occur, researchers conducted a qualitative analysis of the tasks and challenges faced by perioperative nurses and surgical technologists in an academic medical center and a community hospital. Using hermeneutic phenomenological methodology, we identified bad behavior, general chaos, and communication difficulties as problems associated with incorrect surgical counts. As point-of-care providers, perioperative RNs are well poised to identify problematic areas and design systems and processes that protect patients. Perioperative RNs should consider using red rules or a code of conduct as tools for improving the manual counting process. These strategies could be developed in the shared governance council or a perioperative staff-led committee to ensure adherence to AORN standards. © 2010 AORN, Inc.
Keywords: article; human; medical error; nursing staff; perioperative nursing

Increasing patient safety and surgical team communication by using a count/time out board - Edel, E.M. (AORN Journal, 2010)
Communication and collaboration in patient care settings is vital for promoting the best possible patient outcomes. The counting of sponges, sharps, and instruments, and the surgical time out before the start of any surgical procedure are opportunities for the surgical team to address patient safety risks. Personnel in the surgical services department at St Luke's Episcopal Hospital, Houston, Texas, implemented the use of a hanging, magnetic, dry-erase board that includes the elements of a time out (eg, patient name and identifiers, procedure, site, allergies) and provides a means to document countable items. The board promotes team awareness of this time out and count information at all times during a procedure. Specific magnets on the count board identify items intentionally packed inside the patient to remind the team of the location of these items when the count is reconciled at the end of the procedure. In addition, a process of obtaining an radiograph of items similar to any missing items assists radiologists in identifying the location of retained surgical items. As a result of implementing both changes, our ability to locate missing items has significantly increased. © 2010 AORN, Inc.
Keywords: article; human; interpersonal communication; medical error; safety; United States

Surgical clip as the nidus for common bile duct stone formation: A very rare cause for a common condition - Karanth, N.; Sonpal, N.; Zlatanic, J.; Haber, G. (American Journal of Gastroenterology, 2010)
Purpose: Foreign bodies as the nucleus for formation of gallstones are not frequently seen as the cause of choledocholithiasis. We present a case of a surgical clip applied across the cystic duct during laparoscopic cholecystectomy, which subsequently migrated into the common bile duct. This clip resulted in choledocholithiasis and subsequent cholangitis just one year after cholecystectomy. Methods: A 41-year-old female with past medical history of GERD, hypertension, and alcohol abuse presents with complaints of persistent right upper quadrant pain and fever for one week. Physical exam was notable for right upper quadrant and epigastric tenderness, and was otherwise unremarkable. Laboratory findings demonstrated a WBC of 12.5 x 103, AST/ALT ratio of 615/409, alkaline phosphatase of 484 and total bilirubin of 2.1 with direct bilirubin of 1.1. Computerized tomography (CT) scan revealed dilation of the biliary tree with two surgical clips observed in the gallbladder fossa and one clip appreciated within the lumen of the distal common bile duct. The patient was diagnosed with acute cholangitis in the setting of choledocolithiasis. Results: The patient was started on empiric piperacillin/tazobactam and Endoscopic Retrograde Cholangiopancreatography (ERCP) was scheduled. Upon cannulation of the papilla using an Ultratome sphinctertome over a 0.035in Jagwire, extrusion of frank pus was appreciated. A cholangiogram revealed a dilated intrahepatic duct and a filling defect in the distal CBD with a central fluoroscopic “line” through the defect representing the surgical clip. The cystic duct with two surgical clips attached was also noted. A generous sphincterotomy was performed and bile duct sweep using a retrieval wire basket extruded a pigmeted stone with a surgical clip at its core. Subsequent retrieval balloon sweeps of the CBD with cholangiogram revealed no further filling defects. A 7 Fr 7cm straight plastic biliary stent was placed with drainage of clear bile. The patient's white count and liver function tests normalized, and the patient was discharged home. Conclusion: Any foreign bodies in the biliary tract, including non-absorbable surgical clips, can serve as the substrate for stone formation. For those patients who have undergone cholecystectomy, clip migration should be considered as a cause of recurrent pain in the right upper quadrant.
Keywords: bilirubin glucuronide; fenamisal; plastic; bilirubin; alkaline phosphatase; common bile duct stone; stone formation; college; gastroenterology; clip; human; patient; cholecystectomy; cholangiography; cholangitis; cystic duct; pain; foreign body; common bile duct; computer assisted tomography; bile; liver function test; tree; bile duct; laboratory; sphincterotomy; fever; pus; cannulation; endoscopic retrograde cholangiopancreatography; alcohol abuse; hypertension; medical history; gallstone; stent; female; hepatobiliary system; gallbladder

Chylous ascites in an AIDS patient with a history of mycobacterium avium complex infection - Beyda, D.; Korman, A.; Hudesman, D.; Favila, K.; Horowitz, M.; Bernstein, B. (American Journal of Gastroenterology, 2010)
Purpose: Background: Chylous ascites has been associated with AIDS however only in a rare report of Mycobacterium avium complex (MAC) infection. Case Report: A 37-year-old male presented with abdominal pain and distension over one week. Past medical history was significant for AIDS and disseminated MAC diagnosed two years prior. He denied a history of liver disease, alcohol or drug use. He recently started Highly Active Anti-Retroviral Therapy (HAART) and over the last nine months increased his CD4 count from 11 ccm to 230 ccm. On admission he was hemodynamically-stable however was noted to be tachypneic. Physical exam was significant for shift ing dullness suggesting ascites and inguinal lymphadenopathy bilaterally. Initial blood work was normal, but CT of the abdomen showed a soft -tissue mass at the base of the small bowel mesentery with areas of central low attenuation. This lymph node conglomeration measured approximately 7.0 × 4.6 cm and encased several vessels exerting moderate masseffect. Also, jejunal wall thickening surrounded the mass which can be a nonspecific finding for MAC. Abdominal paracentesis was performed revealing a milky ascitic fluid with a white blood cell count of 1078/uL, triglyceride level of 245 mg/dL, total protein of 2.4 g/dL, lactate dehydrogenase of 257 U/L and glucose of 86 mg/dL. While initial fluid culture returned negative for MAC, biopsy of the mesenteric lymph nodes found granulomatous inflammation with epithelioid cells, histiocytes and foreign body giant cells. These changes have been reported as pathognomonic for MAC. As no adenopathy or splenomegaly was found by imaging, lymphoma was of low suspicion and Immune Reconstitution Inflammatory Syndrome (IRIS) associated with known history of MAC was substantiated. Thus, treatment for suspected MAC infection with azithromycin was started which resulted in an improvement of his abdominal pain and distention. Conclusion: IRIS is commonly seen in AIDS patients after HAART therapy is started. As the immune system recovers, it may cause an overwhelming inflammatory response to prior infections. Thus, recognition of IRIS in an AIDS patient presenting with new onset ascites may facilitate early diagnosis and treatment of opportunistic infections. (Figure presented).
Keywords: CD4 antigen; glucose; protein; triacylglycerol; azithromycin; lactate dehydrogenase; AIDS patient; human; chylous ascites; atypical mycobacteriosis; college; gastroenterology; acquired immune deficiency syndrome; infection; lymphadenopathy; therapy; abdominal pain; ascites; paracentesis; lymph node; attenuation; male; mesentery; small intestine; histiocyte; lymphoma; immune reconstitution inflammatory syndrome; ascites fluid; leukocyte count; drug use; soft tissue; mesentery lymph node; abdomen; alcohol liver disease; biopsy; liquid; granulomatous inflammation; epithelioid cell; blood; giant cell; splenomegaly; imaging; immune system; inflammation; early diagnosis; opportunistic infection; medical history; case report; highly active antiretroviral therapy

Drainage of esophageal leakage using endoscopic vacuum therapy: A prospective pilot study - Ahrens, M.; Schulte, T.; Egberts, J.; Schafmayer, C.; Hampe, J.; Fritscher-Ravens, A.; Broering, D.C.; Schniewind, B. (Endoscopy, 2010)
Background and study aims: Major leakage from an esophageal anastomosis is a life-threatening surgical complication. Endoscopically guided endoluminal vacuum therapy using polyurethane sponges is a new method for treating such leakage. Patients and methods: Between June 2007 and June 2009, five patients (mean age 68 years) who developed anastomotic leakage after esophageal surgery were prospectively evaluated. After endoscopic diagnosis of a major leakage, polyurethane sponges were endoscopically positioned in the wound cavity of the anastomosis. Continuous suction was applied via drainage tubes fixed to the sponges. Initially sponges were endoscopically changed three times per week. Results: In all five patients treatment was successful. Median time to reduce levels of inflammation markers by 50% was 10 days for white blood cell (WBC) count and 7 days for C-reactive protein (CRP). The smallest initial wound cavity size was 42cm3 and the largest was 157cm3. The median duration of drainage was 28 days, with a median of 9 sponge changes and a median time to total cavity closure of 42 days. Two patients needed anastomotic dilation by Savary-Miller bougienage due to stenosis found on further follow-up. One of these patients died of acute severe hemorrhage from an aortoanastomotic fistula after the dilation procedure. Conclusions: Endoscopically assisted vacuum therapy is a well-tolerated and effective therapeutic option for treatment of major esophageal leaks after surgery. Additional surgery was avoided in all cases. However, the occurrence of a delayed aortoesophageal fistula calls for careful further investigation of this new technique. © Georg Thieme Verlag KG Stuttgart.
Keywords: C reactive protein; inotropic agent; polyurethan; adult; aged; anastomosis leakage; aortoesophageal fistula; article; cardiovascular disease; clinical article; clinical evaluation; clinical trial; disease marker; disease severity; endoscopic therapy; endoscopic vacuum therapy; endoscopy; esophageal leakage; esophagus anastomosis; esophagus dilatation; esophagus disease; esophagus stenosis; esophagus surgery; female; hemorrhagic shock; human; inflammation; leukocyte count; male; pilot study; postoperative hemorrhage; priority journal; prospective study; suction drainage; surgical sponge; surgical technique; treatment outcome; upper gastrointestinal bleeding; vacuum assisted closure; wound drainage

Nail puncture wound through a rubber-soled shoe: A retrospective study of 96 adult patients - Rubin, G.; Chezar, A.; Raz, R.; Rozen, N. (Journal of Foot and Ankle Surgery, 2010)
Nail punctures through rubber-soled shoes expose the foot to the possibility of deep infection and foreign body retention. In this article, we describe characteristics of adult patients who sustained nail puncture wounds through a rubber-soled shoe and were treated at our institution from January 1, 2000, to January 8, 2008. Of the 96 patients, 36 (37.5%) were treated conservatively and 60 (62.5%) were treated surgically in the operating room. Of those treated surgically, 15 (25%) had a foreign body extracted during the operation. The operated group had a longer duration of time from injury to hospital admission than did the nonoperated group (5.0 ± 6.8 days versus 2.7 ± 3.8 days, P < .05). Treatment success was observed in 91 (94.8%) of the patients, and the median lag time before admission for the less successfully treated group was longer than that for the successfully treated group (10 days versus 2 days, P < .002); and, the less successfully treated group was more likely to receive antibiotics in the community before hospitalization (100.0% versus 47.2%, P < .06), and was more likely to be diabetic (40.0% versus 9.9%, P < .10). Fever, white blood cell count, and erythrocyte sedimentation rate were not significantly associated with treatment outcome. Success of the treatment did not depend on white blood cell count, erythrocyte sedimentation rate, or fever. Ultrasonography was useful in detecting the presence of a foreign body. © 2010 American College of Foot and Ankle Surgeons.
Keywords: amoxicillin; amoxicillin plus clavulanic acid; cefalexin; cefonicid; ciprofloxacin; cloxacillin; gentamicin; adolescent; adult; aged; article; conservative treatment; controlled study; demography; diabetes mellitus; echography; erythrocyte sedimentation rate; female; fever; foot injury; foot surgery; foreign body; hospital admission; human; leukocyte count; major clinical study; male; nail puncture wound; retrospective study; shoe

A bizarre abdominal cystic lesion - Zucchini, G.; Pezzilli, R.; Ricci, C.; Casadei, R.; Santini, D.; Calculli, L.; Corinaldesi, R. (Journal of the Pancreas, 2010)
In spite of careful intraoperative precautions and gauze counts, mistakes can still occur during surgery. In the case reported, a retained gauze leaved during a surgical approach for removing a solid-cystic papillary tumor localized in the pancreatic tail, caused both persistent abdominal discomfort and the presence of an abdominal cystic lesion at imaging techniques. When a previous operative history is present, a foreign body should be taken into account in the differential diagnosis of a patient with an intraabdominal cystic mass. Finally, radio-opaque marker should be routinely used by surgeons in order to reach a correct diagnosis in operated patients having retained gauze.
Keywords: abdominal discomfort; adult; anamnesis; article; case report; computer assisted tomography; contrast enhancement; dyspepsia; female; foreign body; gauze dressing; human; incidental finding; laparotomy; pancreas cyst; pancreatectomy; pancreas solid cystic papillary tumor; papilloma; retained instrument; tumor volume; upper abdominal pain

In vitro test system for the evaluation of the biocompability of alloplastic materials and its improvement by autologous coating - Bagner, J.; Gerullis, H.; Karig, R.; Ramon, A.; Otto, T. (Urology, 2010)
Introduction and Objective: Alloplastic materials are widely applied in the surgical therapies for hernia, incontinence and prolapse situations. The FDA issued a warning concerning the application of alloplastic materials for the surgical treatment of female incontinence and prolapse. The improvement of the biocom-patibility of foreign materials seems to be mandatory. Materials and Methods: In order to investigate if coating of alloplastic materials with autologous material can lead to improved biocompatibility the following study approach was established: 12 patients were included. Blood, plasma and serum of each patient were preserved. Myoblasts, endothelial cells and fibroblasts of each patient were cultivated separately with the alloplastic materials. Cell count and growth are comparable in all approaches within a test duration of 6 weeks. Immunohistochemical and microscopic evaluation of cell count and adherence is performed considering the chosen coating for the alloplastic material. Adherence, cell count and typing are assessed microscopically and by immunohisto-chemistry after co-incubation of the cells with different types of alloplastic meshes with and without coatings. Results: Regarding tissue specify different cell growth can de defined in favor of fibroblasts: fibroblasts > myoblasts > endothelial cells. Improved cell adhesion is found on alloplastic meshes covered with autologous plasma compared to noncovered meshes. This finding includes all types of cells being tested. Eighteen different, commonly used alloplastic materials were investigated. Cell count and growth were comparable in all approaches within a test duration of 6 weeks. Only on cPTFE are cells showing adherence and growth. On all other uncovered meshes there is no evidence of cell adherence to the respective alloplastic materials. Looking at the intensity of cell adhesion through plasma-coating on the different meshes a ranking can be compiled. Conclusions: Cell adhesion to the tested alloplastic materials regarding cells of the pelvic floor is insufficient. This observation may explain the occurrence of foreign-body reaction and missing integration of alloplastic materials into the pelvic floor. Coating of meshes with autologous plasma results in an improvement of the biocompatibility.
Keywords: in vitro study; lower urinary tract symptom; cell adhesion; cell count; fibroblast; patient; tissue injury; myoblast; plasma; biocompatibility; endothelium cell; blood autotransfusion; pelvis floor; incontinence; surgery; female; hernia; serum; tissues; foreign body; cell growth; foreign body reaction; Food and Drug Administration

Complications of endografting: Prevention and management - Rousseau, H.; Chabbert, V.; Marcheix, B. (CardioVascular and Interventional Radiology, 2010)
Endovascular treatment for aortic disease has emerged as an alternative mode of treatment that is particularly attractive for patients with severe comorbidities who would not be ideal candidates for open surgery. Although endoluminal interventions are minimally invasive, they are associated with complications, as are all surgical methods. The aim of this paper is to give an overview on thoracic aortic stent-graft complications with focus on failure modes and potential improvements. Procedure-Related Problems Successful thoracic aneurysm repair could be attained today in 98% to 100% of cases. Adverse events will occur after stent-graft placement in a minority of cases, and many of these complications can be diagnosed and managed with minimally invasive techniques. Access Vessel Issues Access related issues comprise a major reason for failure or conversion to open repair and can contribute to a significant amount of morbidity and mortality. Iliac artery trauma may occur when a stentgraft is forced through a small or tortuous iliac artery. Vascular trauma is especially likely in cases involving small, heavily or circumferentially calcified iliac arteries. Most iliac artery traumas may be treated with stents or stent-grafts, although surgical endarterectomy or bypass may also be required. Preoperative imaging is paramount to the success of endovascular procedures. Occasionally, challenging iliac or femoral anatomy may preclude access through these vessels and may need to gain direct access through the aorta or via the carotid or subclavian artery. Stent-Graft Misplacement Stent-graft misplacement may occur when: (a) the blood pressure is too high during deployment or balloon dilation of the stent-graft and caused a “wind sock” effect, particularly when proximal fixation is at or near the aortic arch. To avoid this problem, blood pressure must be lowered with vasodilator or beta-blocker drugs, or (b) the stent-graft is positioned across an angulated arterial segment, which may cause the introducer sheath to kink. Stent-graft misplacement can be prevented by using a more flexible stent-graft and by covering a longer segment in an angulated anatomic structure. Whenever insufficient lesion coverage results from stent-graft misplacement, a stent-graft extension should be put in place to adequately cover the landing zone. Accidental coverage of a branch vessel with the stentgraft is more difficult to manage. However, treatment may consist of positioning a bare stent so that it protrudes from within the origin of the covered vessel, thereby displacing the covering stent-graft membrane and restoring blood flow to the branch vessel. Aortic Perforation Aortic perforation may occur during stent-graft insertion and is easily recognized as a rapidly enlarging hematoma or hemothorax. Rapid covering of the perforation with a stent-graft is the first treatment option. Aortic perforation may also occur after stent-graft insertion due to erosion of the aortic wall by stent-graft struts. These perforations may be asymptomatic or may lead to aortic rupture or fistula formation. Endoleaks Type 1 endoleaks result from incomplete sealing of the stent-graft at the proximal or distal attachment site. They occur more frequently when: (a) the stent-graft landing zones are short, irregular, or ulcerated, (b) a suboptimal stent-graft diameter has been selected, or (c) the stent-graft is positioned across an angulated neck or in a narrow aortic arch and does not conform to the curved aortic contour. To maximize the neck length, we can use the distance between the origins of the left common carotid artery and left subclavian artery, occluding the LSA when necessary. In our experience, overstenting the left subclavian artery has not led so far to any particular complications. However, prior to doing so, we make sure that there is no right vertebral artery stenosis or absent vertebral collateral pathway. Secondary to obstruction of the LSA, if there is reduced perfusion of the left arm, surgical bypass can be performed electively in a second procedure. Type 2 endoleaks result from persistent circulation in the aneurysm from a tributary to the aortic lumen excluded by the stent-graft. These endoleaks are less common in the region of the thoracic aorta than in the abdominal aortic region. In case of aortic diameter increase, selective embolisation by the collaterals or injection of thrombin by a direct puncture of the aorta can be proposed. Type 3 endoleaks arise from a defect of the stent-graft membrane itself or from the separation of components in modular stent-grafts. These endoleaks often result from stent-graft disconnection, which is more likely to occur when multiple stent-grafts with short overlapping areas are used. Type 1 and type 3 endoleaks may be treated with insertion of another stent-graft. Retrograde Dissection The most alarming complication is the retrograde type A dissection after implantation of the stent-graft. Bare springs of the stent-graft could perforate the medial layer of the aortic wall during the implantation in a very kinked arch but cases of secondary dissection were also described with other devices. For these reasons, some prefer not to use stent-grafts that are too rigid or with bare-springs. Also, ballooning for stent-graft apposition is one of the possible etiologic factors of intimal tear. In a recent European Registry on EVAR Complications, it was demonstrated that incidence of retrograde dissection was low (1.33%) and was associated with significant mortality (42%) (H. Eggebrecht et al., Circulation, 2009). Patients undergoing TEVAR for (acute) type B dissection appeared to be most prone for the occurrence of this complication which occurred during the index hospital ization as well as after discharge and during mid-term follow-up. Recently, many authors reported the late formation of new intimal tear resulting in pseudoaneurysm or dissection at the margin of the stent-graft. Many articles suggested that the causes of intimal tears were mechanical injury secondary to sharp stent tip, inflexibility of the stent-graft and the pulsatile forces in the aorta normally at curved portion of aorta where stent-graft and intima meet at an angle. If found, additional stent-graft placement must be performed for the management of these patients. To avoid these complications, many authors suggest covering longer portions of the descending aorta until it fits the parallel portion of the aortic wall or intima and the development of stent-grafts with smoother edges and more flexible bodies. Mortality Mortality is the most important criterion in appraising the results of TAA treatment. Conventional intervention carries a mortality rate that ranges between 3 and 26%, up to 75% for emergency repair. In a recent meta-analysis of thoracic stent grafts (Walsh S et al. JVS 2008), the thirty-day mortality was 5.57% in elective situation versus 16% in emergency. Post Implantation Syndrome The incidence of transient post-implantation syndrome (fever, leukocytosis and elevated C-reactive protein) is known to be 20 to 60%. The syndrome is suggested to be a nonspecific systemic inflammatory reaction rather than a true infection. Patients usually recover with conservative treatments in 2 to 10 days. Pleural effusion and platelet count drop are frequent but mysterious complications of stent-graft in aortic dissection. It could originate from foreign body irritation to the adjacent pleura. It usually resolves spontaneously within 3 months after the intervention. The platelet count drop is observed in 1/3 of cases 1 to 3 days after stent-graft insertion. It returned to initial base line values in 5 to 10 days without transfusion or any other treatment. Because all cases of platelet count drop occurred in patients whose former patent false lumen had been obliterated by thrombus formation, consumptive coagulopathy is suggested to be the cause of this transient complication. Paraplegia and Cerebrovascular Accidents Although no randomized trials have been conducted comparing stent-graft placement with surgery for thoracic aortic disease, paraplegia seems less likely with stent-graft placement than with surgery. Paraplegia is crucially influenced by the duration of aortic clamping in the open thoracic aortic operation. Despite many improvements in the technique, the rates of paralysis in conventional open surgery range from 1.5 to 19% in high-volume centers. Absence of thoracotomy and cross-clamping of the aorta are the main advantages of endovascular repair. However, since a large number of intercostal arteries are acutely occluded, especially when long stent-grafts are implanted, paralysis can still occur. In the largest meta-analysis of endovascular TAA repairs reported, the rate of paraplegia is 5.4% (Walsh S et al. JVS 2008). This complication seems to be significantly more frequent in patients undergoing concurrent AAA repair or who had undergone AAA repair earlier. Successful treatment of stent-graft-induced paralysis with drainage of cerebrospinal fluid has been reported. The neurological complications are less frequent in case of dissection (0.8% of paraplegia and 1.9% of stroke in the meta-analysis of H. Eggebrecht et al., Eur Heart J 2006) Strokes are caused by the manipulation of wires and catheters in an atherosclerotic aortic arch. The incidence of this complication is actually now lower with the new endografts. To keep the embolic risk low, the tip of the delivery system should be as short and flexible as possible, no manipulation on artificial aortic valves should be done where clots could be present and good anticoagulation is mandatory.
Keywords: vasodilator agent; beta adrenergic receptor blocking agent; thrombin; C reactive protein; Europe; prevention; society; stent; dissection; mortality; patient; aorta; paraplegia; perforation; surgery; implantation; iliac artery; platelet count; lacrimal fluid; paralysis; aortic wall; subclavian artery; aortic arch; meta analysis; cerebrovascular accident; intima; membrane; neck; aortic disease; artery injury; emergency; blood pressure; aneurysm; anticoagulation; morbidity; endarterectomy; minimally invasive procedure; carotid artery; blood flow; hematoma; hematothorax; imaging; fistula; common carotid artery; vertebral artery stenosis; obstruction; perfusion; arm; thoracic aorta; artificial embolization; injection; puncture; devices; etiology; register; hospital; aortic rupture; false aneurysm; injury; descending aorta; fever; leukocytosis; inflammation; infection; conservative treatment; pleura effusion; aortic dissection; foreign body; pleura; transfusion; patent; blood clotting; disseminated intravascular clotting; cerebrovascular accident; aortic clamping; thoracotomy; artery; cerebrospinal fluid; follow up; neurological complication; heart; catheter; risk; aortic valve; blood vessel injury

Courts rejected RIL: did nurses botch sponge count? Baxter v. Ash Samaritan Hospital, LLC, 2008-CA-000541-MR KYCA (1/15/2010)-KY. (Nursing law's Regan report, 2010)
Keywords: appendectomy; article; cesarean section; female; foreign body reaction; homicide; human; legal aspect; malpractice; newborn; operating room personnel; pregnancy; premature labor; surgical sponge; United States

Analysis of intrathoracic esophageal perforations in a tertiary center - Chiera di Vasco Freitas, M.; Gustavo Parreira, J.; Cesar Assef, J.; Gagliardi, D.; Castro Pochini, C.; Campos Padovese, C. (Diseases of the Esophagus, 2010)
Purpose: Although relatively uncommon, esophageal peforations still carry high morbidity and mortality. There are controversies about the management, especially concerning the thoracic esophagus, which have a higher mortality. We reviewed our experience in treating intrathoracic esophageal perforations and evaluated etiology, management, outcome and the factors associated with a poor outcome. Methods: Between 2004 and 2008, 30 patients were treated in our deparment with perforations of the intrathoracic esophagus. Etiology, time interval between clinical presentation and treatment, therapeutic management and outcome were analyzed as wells as heart rate, systolic blood pressure, albumin, leukocyte count upon arrival and need for blood transfusion or thoracothomy. Results: The most frequent cause was postdilatation corrosive stricture perforation (46.6%), followed by removal of foreign body (20.2%). Esophagectomy was the treatment of choice in 26 patients (86.8%), 65.4% of those through a transhiatal approach. Three patients underwent suture of the esophagus (10%), and one of the three received combined esophagostomy. One patient (3.3%) was submitted to an endoscopic clip placement. There was a 33% mortality rate. A high leukocytes count was statistically associated with complications. Conclusion: Our series had a survival rate similar to other publications. Esophagectomy was performed in the majority of cases due to a high incidence of underlying esophageal diseases. Besides the diagnostic interval linked to mortality we also found an association with high leukocytes count.
Keywords: albumin; esophagus; esophagus perforation; society; human; mortality; patient; leukocyte; esophagus resection; perforation; etiology; suture; esophagostomy; survival rate; esophagus disease; diagnosis; morbidity; heart rate; systolic blood pressure; leukocyte count; blood transfusion; foreign body; clip

Retained surgical sponges: what the practicing clinician should know - Sakorafas, G.H.; Sampanis, D.; Lappas, C.; Papantoni, E.; Christodoulou, S.; Mastoraki, A.; Safioleas, M. (Langenbeck's Archives of Surgery, 2010)
Retained surgical sponges (RSS) are an avoidable complication following surgical operations. RSS can elicit either an early exudative-type reaction or a late aseptic fibrous tissue reaction. They may remain asymptomatic for long time; when present, symptomatology varies substantially and includes septic complications (abscess formation, peritonitis) or fibrous reaction resulting in adhesion formation or fistulation into adjacent hollow organs or externally. Plain radiograph may be useful for the diagnosis; however, computed tomography is the method of choice to establish correct diagnosis preoperatively. Removal of RSS is always indicated to prevent further complications. This is usually accomplished by open surgery; rarely, endoscopic or laparoscopic removal may be successful. Prevention is of key importance to avoid not only morbidity and even mortality but also medicolegal consequences. Preventive measures include careful counting, use of sponges marked with a radiopaque marker, avoidance of use of small sponges during abdominal procedures, careful examination of the abdomen by the operating surgeon before closure, radiograph in the operating theater (either routinely or selectively), and recently, usage of barcode and radiofrequency identification technology. © 2010 Springer-Verlag.
Keywords: marker; surgical sponge; surgery; morbidity; fistula; foreign body; X ray film; diagnosis; surgeon; operating room; radiofrequency; technology; tissue reaction; symptomatology; adhesion; computer assisted tomography; prevention; peritonitis; mortality; examination; abdomen; abscess

Efficacy and safety of polyacrylamide hydrogel (Bulkamid1) for treating stress urinary incontinence in women: A single centre study - Giovanni, B.; Paola, B.; Luisella, S.; Mario, V.; Roberto, C.; Alessandro, G. (Neurourology and Urodynamics, 2010)
Introduction and Aim of the Study: Bulking therapy has been developed since the beginning of the 20th century with the aim to increase urethral coaptation and hence restore continence. The ideal agent is not absorbable, causes no immunological or inflammatory reaction, does not stimulate fibrosis, is not toxic, does not migrate (i.e. has a particle diameter of >80 mm), and has viscosity and cohesiveness that allow easy injection. The materials studied to date have varying success rates that leave space for improvement. In this study we evaluate the safety and efficacy of transurethral injectionwith Bulkamid (hydrogel cross-linked with polyacrylamide - PAHG) for treating women with urodynamic stress urinary incontinence (SUI). Materials and Methods: Between March 2008 and May 2009, 48 women with urodynamic SUI were treated with transurethral Bulkamid injection. Median age was 65.5 (interquartile range: 54.75-70.75 years). The women were evaluated at baseline with a history, physical examination, evaluation of the urethral mobility using trans-labial ultrasound, urine dipstick test, a micturition diary, daily pad count, 24-h padweight test for 3 days, Personal Global Impression of Severity Questionnaire (PGI-S) and International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF). Urodynamic evaluation was performed including spontaneous uroflowmetry, PVR measurement, urethral pressure profilometry and water cystometry while seated (filling rate 50 ml/min) followed by a pressure-flow study. The injection was given under local anaesthesia (5 ml of 5%lidocaine).With thewoman in the lithotomy position, Bulkamid (2 ml) was injected transurethrally into the submucosa using a 23 G needle and a special cystoscope that can be rotated of almost 360 (Bulkamid Urethral Bulking System) (Fig. 1). The deposits were placed 0.5- 1 cm distal to the bladder neck at 3, 6 and 9 o'clock. After satisfactory urethral occlusion, the bladder was emptied via a 10 ch catheter. Before injection, the women received prophylactic antibiotics, and they were discharged the day after surgery after successful voiding (PVR <50 ml, assessed using ultrasonography). Patients were re-evaluated 1, 3, 6, 12 and 18 months later. The efficacy was estimated by daily pad count, 24-h pad-weighing test for 3 days, ICIQ-SF and Personal Global Impression of Improvement Questionnaire (PGI-I). Results: All patients were affected by urodynamic SUI. In 9 cases (19%) trans-labial ultrasound showed urethral hypermobility. Sixteen (33%) patients reported previous pelvic floor rehabilitation and 22 (46%) had undergone pelvic surgery for organ prolapse or incontinence. At baseline the median number of pads was 4 (range 1-16), the median urine leakage/ 24 h was <50 g in 14 patients (29%), 50 < 250 g in 8 (17%) and >250 g in 26 (54%). The median maximum urethral closure pressure (MCPU)was 42 cmH20 (interquartile range: 34,25-60) and median Valsalva leak point pressure (VLPP) 47 cmH20 (I-III quartile 39,5-60). Eleven (23%) patients had detrusor overactivity before injection.Median PGI-S score was 4 and ICIQ-SF score was 16,5. The mean volume of Bulkamid injected was 2ml (range 1-4 ml) per session. Forty-four women (92%) received 2ml of Bulkamid, three patients (6%) were injected with 4ml to obtain a satisfactory urethral occlusion, in one patient (2%) the urethral occlusion was obtained with 1 ml. Two patients (4%)were re-injected after the 3-month follow-up visit because of insufficient effect. Mean follow-up was 11 months (interquartile range: 9-17). No patients were lost at follow-up.All patients completed at least 6months of followup, 23 completed at least 12 months of follow-up and 11 completed 18 months of follow-up after the last injection. At follow-up 36 (75%) patients were found to be dry (i.e. 0-1 safety pad) or significantly improved (i.e. >50% reduction in daily pad usage and pad test result with a PGI-I Score of 1-2), twelve (25%) demonstrated no improvement (i.e. <50% reduction in daily pad usage and pad test result with a PGI-I Score of 3-4). In the entire cohort of patients the median number of pads/24 hwas significantly reduced after treatment from 4 pads/day to 1 pad/day (P < 0,001) (Fig. 2) and the median ICQ-SF score decreased significantly after treatment from 16,5 to 7,5 (P < 0,001) (Fig. 3). These results are stable at 12 months of follow-up. The most common adverse event was postoperative urinary retention (14 patients, 29%), treated by self-catheterization. Forty-four women (92%) were discharged the day after the injection. (Graph presented) Interpretation of Results: Polyacrylamides have been used for more than 10 years in plastic surgery and in themanufacture of contact lenses.1 No adverse events related to the composition of the implant have been reported to date. Polyacrylamides are atoxic due to their resistance to biodegradation and because their large molecular size prevents them from passing biological membranes; they show good elasticity as a soft-tissue filler, they arewell accepted by human tissue and foreign-body reaction is either absent or minimal.2 Bulkamid is a biocompatible and non-absorbable hydrogel consisting of 97.5%water and 2.5% cross-linked polyacrylamide. The hydrogel exchanges water with the surrounding tissue. The visco-elastic properties are optimized for urethral bulking. Bulkamid is homogeneous as it does not contain any particles (micro balls, micro crystals and the suchlike), so there is no tissue hardening or other impairment to the urethral function. The procedure is minimally invasive and is performed under endoscopic control to ensure correct placement of the bulking agent.3 Our preferred indication is Intrinsic Sphincter Deficiency (ISD) with fixed urethra, but it is our opinion that the procedure may be proposed in all patients affected by urodynamic SUI with or without urethral hypermobility, after an assessment of the risks and benefits, especially when a minimally invasive procedure is desired. In our experience there was a subjective success rate of 75% with only minor complications, the most prevalent ofwhich was retention. These results aremaintained at mid follow-up. Conclusions: This study provides evidence that Bulkamid can be a safe and efficacy bulking agent for treating SUI.
Keywords: polyacrylamide; water; bulking agent; lidocaine; antibiotic agent; female; hydrogel; safety; stress incontinence; patient; follow up; injection; questionnaire; occlusion; urine; ultrasound; incontinence; tissues; membrane; elasticity; soft tissue; human tissue; foreign body reaction; crystal; sphincter; urethra; risk; minimally invasive procedure; continence; inflammation; fibrosis; viscosity; physical examination; micturition; consultation; uroflowmetry; cystometry; local anesthesia; lithotomy position; submucosa; needle; cystoscope; bladder neck; therapy; bladder; catheter; surgery; echography; pelvis floor; rehabilitation; pelvis surgery; tissue injury; overactive bladder; urine retention; catheterization; contact lens; implant; biodegradation; molecular size; plastic surgery

Gossypiboma: A lesson to learn: Case report - Ilter, E.; Manukyan, M.N.; Haliloǧlu, B.; Çelik, A.; Özden, S. (Turkiye Klinikleri Jinekoloji Obstetrik, 2010)
The term "gossypiboma" denotes foreign bodies retained after surgery. The most common gossypiboma is the iatrogenic surgical sponge. Usually, hysterectomy, appendectomy and cholecystectomy operations are associated with these retained sponges. They may be misdiagnosed as incisional endometriosis. We present a patient who had a caesarean section operation eleven years ago with a mass at the abdominal wall between the umbilicus and the caesarean section scar on the left paramedian region approximately 5 x 2 cm in diameter. We must keep in mind that prevention is more important for cure. As we knew that most reported cases occur in the presence of a normal pack count, we think that the surgical team must be very careful in the operation room.
Keywords: abdominal pain; adult; article; case report; cesarean section; cholecystectomy; cholelithiasis; clinical examination; echography; endometrium tumor; female; foreign body; gauze dressing; gossypiboma; human; laparoscopic surgery; treatment outcome

Plasminogen deficiency with tracheobronchial involvement - Sotomayor, T.B.; Shin, E.; Ziss, B.; Carpio, K. (American Journal of Respiratory and Critical Care Medicine, 2010)
Introduction: Plasminogen (PLG) deficiency is a rare inherited disorder that can involve multiple systems leading to deficient fibrinolysis and subsequent impairment of the wound healing capacity of mucus membranes. Type 1 hypoplasminogenemia, is defined by low plasminogen levels and normal or decreased PLG activity. Patients exhibit multi-organ ligneous inflammation with conjunctiva, gingival lesions or, less frequently, involving the tracheobronchial tree or hydrocephalus. Type 2 dysplasminogenemia, a polymorphic variant, presents with normal or slightly decreased PLG levels but significantly decreased activity and has no known reported clinical associations. Our report describes a two year old male with clinical, serologic, and genetic findings of PLG deficiency with tracheobronchial involvement. Case description: A 2 year old male was admitted with persistent cough, wheezing, and hypoxia due to an adenovirus infection. He developed recurrent left lower lobe pneumonia partially responsive to IV antibiotics. Flexible bronchoscopy (FB) revealed raised lesions at the left lower lobe bronchus which resolved spontaneously, but recurred at the left main stem. Repeated bronchoalveolar lavages (BAL) grew multiple organisms including S. viridans, M catarrhalis, H influenzae, S pneumoniae, and Staph. aureous; foreign bodies were not seen. Past medical history was significant for urosepsis, GERD at infancy, failure to thrive, myringotomy complicated by granuloma formation. Subsequently, the child developed a right lower lid conjunctival lesion which recurred after multiple attempts at manual and surgical removal but resolved after Restasis therapy. Immune workup, including vaccination antibody response, immunoglobulin levels, CD4 and CD8 counts, and sweat chloride, were normal. Lymphocyte mitogen screen showed a decreased response to candida in an otherwise normal screen despite prior episodes of thrush. Chest Ct persistently showed LLL bronchiectasis with unresolved infiltrates. Pneumonias did not resolve fully with prolonged antibiotics, nebulized bronchodilators, steroids, DNAse dornase, and vest therapy. Due to history of recurrent pneumonias, tympanic membrane granulomas and conjunctival findings, the child was tested for plasminogen deficiency. He had normal levels of plasminogen with a markedly decreased level of plasminogen activity and antigen. DNA testing revealed the most common missense mutation Lys19>Glu (K19E) in a homozygous manner. Furthermore, several known homozygous PLG gene polymorphisms were identified. Discussion: Plasminogen deficiency must be considered in children with ligneous inflammation of the upper and lower respiratory tract, especially if associated with conjunctiva, or gingival involvement. There is a need for more research understanding this condition, where incidence may be underestimated, particularly looking for therapeutic options when the tracheobronchial system is involved.
Keywords: plasminogen; antibiotic agent; deoxyribonuclease; CD4 antigen; antigen; steroid; cyclosporine; mitogenic agent; chloride; CD8 antigen; DNA; society; human; pneumonia; child; conjunctiva; tracheobronchial tree; granuloma; inflammation; male; therapy; immunoglobulin blood level; adenovirus infection; wound healing; hypoxia; book; vaccination; antibody response; myringotomy; wheezing; patient; fibrinolysis; mucosa; coughing; urosepsis; infancy; hydrocephalus; medical history; foreign body; lymphocyte; lung lavage; bronchus; bronchoscopy; sweat; Candida; thorax; bronchiectasis; eardrum; diseases; missense mutation; DNA polymorphism; lower respiratory tract; failure to thrive

All that's hilar is not sarcoid - Taji, J.; Goyal, R.; Mattar, Z.; Assaly, R. (American Journal of Respiratory and Critical Care Medicine, 2010)
Introduction: Sarcoidosis is the great mimic. It has so many presentations that it becomes easy to label everything as Sarcoid. This is one such case where appearances were deceiving on many levels. HPI: This is a case of a previously health 33 y/o African American male who presented to the pulmonary service because of Tachycardia, and Hypoxia with an SaO2 of 90% on room air. Past History: No previous medical history of significance; no surgical history; denied drug, alcohol and tobacco abuse. He used to work in the demolition of houses, including burnt and old houses. A Chest X-Ray was ordered and showed classical bilateral hilar lymphadenopathy. A CTA of the chest was ordered at the time to rule out a pulmonary embolism as well. There was no PE, however Adenopathy was confirmed. Diagnoses including Sarcoidosis, Lymphoma, and Fungal Disease were entertained at that time. To this end, various labs were ordered of which the significant ones were as follows: Fungal serologies negative; CBC normal except for differential showing a eosinophil count of 10.7%; LDH 223; Negative autoimmune workup; Serum ACE level at 119 (normal 8.0 - 52.0); Protein Electrophoresis showing elevated levels of IgG, Kappa chains, and Lambda chains; All tumor markers were negative. Bronchoscopy done which showed a lymphocyte count of 74% with all cultures negative, including negative fungal smear. Transbronchial biopsies taken came back showing no evidence for malignancy but positive for foreign body granulomas. Suspicion for Sarcoidosis was strong until that point but with this new evidence it seemed possible that he was abusing IV drugs either in addition to Sarcoid or separately. The patient however denied this despite several different physicians trying several approaches. His wife confirmed that he never had done drugs. Electron microscopy and spectroscopy of the foreign bodies was then done which showed them to be consistent with Talc silicates. At this point it was felt that the likelihood was occupational exposure to silicates/talc during his years in demolition. Discussion: African American, Hilar Adenopathy, Elevated ACE levels, Granulomas, and no significant medical history. Although this is classical for Sarcoidosis we should always be aware of reliability of the various tests we order even when all point in the same direction. Specifically we should be aware of inhalational Talcosis without necessarily being exposed to IV drugs is an entity which can and does mimic sarcoidosis, despite our classical association of Talc with IV drugs.
Keywords: talc; alcohol; tumor marker; immunoglobulin kappa chain; silicate; lactate dehydrogenase; sarcoidosis; society; human; lymphadenopathy; African American; medical history; lung embolism; lymphocyte count; transbronchial biopsy; ambient air; male; thorax; protein electrophoresis; hypoxia; thorax radiography; eosinophil count; granuloma; serum; tachycardia; serology; bronchoscopy; mycosis; smear; foreign body granuloma; patient; lymphoma; physician; tobacco dependence; foreign body; spectroscopy; diagnosis; electron microscopy; occupational exposure; health; reliability; inhalational drug administration

Bacterial colonization and infection of electrophysiological cardiac devices detected with sonication and swab culture - Rohacek, M.; Weisser, M.; Kobza, R.; Schoenenberger, A.W.; Pfyffer, G.E.; Frei, R.; Erne, P.; Trampuz, A. (Circulation, 2010)
BACKGROUND-: Electrophysiological cardiac devices are increasingly used. The frequency of subclinical infection is unknown. We investigated all explanted devices using sonication, a method for detection of microbial biofilms on foreign bodies. METHODS AND RESULTS-: Consecutive patients in whom cardiac pacemakers and implantable cardioverter/defibrillators were removed at our institution between October 2007 and December 2008 were prospectively included. Devices (generator and/or leads) were aseptically removed and sonicated, and the resulting sonication fluid was cultured. In parallel, conventional swabs of the generator pouch were performed. A total of 121 removed devices (68 pacemakers, 53 implantable cardioverter/defibrillators) were included. The reasons for removal were insufficient battery charge (n=102), device upgrading (n=9), device dysfunction (n=4), or infection (n=6). In 115 episodes (95%) without clinical evidence of infection, 44 (38%) grew bacteria in sonication fluid, including Propionibacterium acnes (n=27), coagulase-negative staphylococci (n=11), Gram-positive anaerobe cocci (n=3), Gram-positive anaerobe rods (n=1), Gram-negative rods (n=1), and mixed bacteria (n=1). In 21 of 44 sonication-positive episodes, bacterial counts were significant (≥ 10 colony-forming units/mL of sonication fluid). In 26 sterilized controls, sonication cultures remained negative in 25 cases (96%). In 112 cases without clinical infection, conventional swab cultures were performed: 30 cultures (27%) were positive, and 18 (60%) were concordant with sonication fluid cultures. Six devices and leads were removed because of infection, growing Staphylococcus aureus, Streptococcus mitis, and coagulase-negative staphylococci in 6 sonication fluid cultures and 4 conventional swab cultures. CONCLUSIONS-: Bacteria can colonize cardiac electrophysiological devices without clinical signs of infection. © 2010 American Heart Association, Inc.
Keywords: adult; aged; anaerobic bacterium; article; artificial heart pacemaker; bacterial colonization; bacterial growth; bacterial infection; bacterium culture; biofilm; cardiovascular equipment; clinical observation; coagulase negative Staphylococcus; defibrillator; device infection; device removal; female; foreign body; Gram negative bacterium; Gram positive bacterium; Gram positive cocci; heart electrophysiology; human; major clinical study; male; priority journal; Propionibacterium acnes; Staphylococcus aureus; Streptococcus mitis; ultrasound

Periprocedural trombus formation during transcatheter closure of atrial septal defect with amplatzer® septal occluder - Canpolat, U.; Yorgun, H.; Ates, A.H.; Ulgen, A.; Kaya, E.B.; Okutucu, S.; Aytemir, K.; Oto, A. (International Journal of Cardiology, 2010)
Objective: Transcatheter closure of ASD become feasible and safe alter native to surgical closure. Although excellent results have been reported for transcatheter occlusion with devices, concerns have arises about peri-interventional complications. Despite implanting an intracardiac, potentially thrombogenic foreign body, reports on thromboembolic complications related to an interatrial device are rare. This case report illustrates that periprocedural thrombus formation occur at transport catheter. Methods: A 45 years old man presented emergency service with cerebrovascular accident. He had no past medical history except smoking (30 pocket/year). During his evaluation at emergency service, complete blood count, biochemical tests including renal-liver function tests and thyroid function tests, thrombophilia panel parameters (prothrombin time, activated partial thromboplastin time, international normalized ratio, protein C activity, protein S (total and free), antithrombin III, anticardiolipin antibodies, homocysteine, factor V Leiden mutation, and prothrombin gene PCR) were in normal limits. The ECG was in sinus rhytm, incomplete RBBB and telecardiogram was normal. Imaging with cranial MR and MRA revealed milimetric acute ischemic lesions in left precentral gyrus, superior temporal and frontal areas. Transcranial doppler ultrasound showed right to left shunt like waterspout pattern. So PFO or ASD were suspected in differential diagnosis. Interatrial septal aneurysm was detected with TTE. TEE revealed ASD with 10mm diameter in bicaval position, was relevant for percutaneous closure. There was no any other pathology. Patient was taken for transcatheter closure of ASD with TEE control under general anesthesia. Amplatzer® Septal Occluder device in 13mm diameter prepared for closure. After passing through the left atrium, there was thrombus formation at the tip of transport catheter of device. The occluder device deployed under TEE imaging and thrombus was taken in between arms of the device. The patient was anticoagulated with UFH infusion immediately during procedure. Results: Control TEE after implantation of device revealed no thrombus around occluder device. Patient was asypmtomatic after procedure with no neurological signs. Patient was discharged with oral anticoagulation. Control TTE before discharging showed that the device was positioned flat against the septum and appeared to be in complete contact with the septum. Patient was asymptomatic at 4th week control with normal TTE. Conclusions: Although percutaneous ASD closure is associated with low complication rate, it is not risk free. Patients shoul be followed closely and over a long term after closure. It is essential that the cardiology community should be aware of these rare complications.
Keywords: homocysteine; blood clotting factor 5 Leiden; prothrombin; protein C; protein S; antithrombin III; cardiolipin antibody; heart atrium septum defect; cardiovascular surgery; cardiology; society; devices; patient; blood clotting; emergency health service; catheter; imaging; thrombus; mutation; nuclear magnetic resonance; Doppler ultrasonography; Doppler flowmetry; heart right left shunt; differential diagnosis; gene; pathology; general anesthesia; heart left atrium; arm; implantation; neurologic disease; anticoagulation; aneurysm; community; occlusion; intracardiac drug administration; foreign body; thromboembolism; case report; male; infusion; medical history; smoking; risk; electrocardiogram; heart right bundle branch block; liver function test; thyroid function test; thrombophilia; blood cell count; prothrombin time; partial thromboplastin time; international normalized ratio; cerebrovascular accident

In vitro test system for the evaluation of the biocompatibility of alloplastic materials - Eimer, C.; Gerullis, H.; Bagner, J.; Lammers, B.J.; Theuerkauf, I.; Ramon, A.; Otto, T. (European Urology, Supplements, 2010)
Introduction & Objectives: Alloplastic materials are widely applied in the surgical therapies for hernia, incontinence and prolapse situations. The American Food and Drug Administration (FDA) issued a warning concerning the application of alloplastic materials for the surgical treatment of female incontinence and prolapse reporting more than 1000 severe adverse events associated with the used materials. Special surgical training together with the management of risk and AE's are recommended (www.fda.gov/cdrh/safety/102008-surgicalmesh.html). The improvement of the biocompatibility coating foreign materials with e.g. autologous substances seems to be mandatory. Material & Methods: In order to investigate if coating of alloplastic materials with autologous material can lead to improved biocompatibility and if alloplastic materials are integrated into the structure of the pelvic floor, the following study approach was established:12 patients were included. Myoblasts, endothelial cells and fibroblasts of each patient were cultivated separately. Cell count and growth are comparable in all approaches within a test duration of 6 weeks. Immunohistochemical and microscopic evaluation of cell count and adherence is performed considering the chosen coating for the alloplastic material. Additionally we performed immunocytochemistry in order to verify the presence of these cells proving the expression of specific cell markers. The detection of myoblasts was realised by α-sarcomeric actin and desmin as markers of myogene differentiation. Fibroblasts were demonstrated by the use of antibodies targeting vimentin whereas antibodies against CD34 were utilised for the detection of endothelial cells. Adherence and cell count are assessed microscopically and by immunohistochemistry after co-incubation of the cells with different types of alloplastic meshs. Results: 14 different, commonly used alloplastic materials were investigated. Cell count and growth were comparable in all approaches within a test duration of 6 weeks. Only on TFT Motifmesh cells are showing adherence and growth. On all other meshs there is no evidence of cell adherence to the respective alloplastic materials. The in vitro analyses were independent from gender and individual patient features. Regarding tissue specify different cell growth can de defined in favour of fibroblasts: fibroblasts > myoblasts > endothelial cells. Improved cell adhesion was found on alloplastic meshs covered with autologous plasma compared to non-covered meshs. This finding includes all types of cells being tested. A covering of meshs with serum or collagen seems to be of disadvantage. Looking at the intensity of cell adhesion on the different meshs the following ranking can be disposed:! TFT Motifmesh®, ProxyBiomedical 2. Dynamesh®, FEG Textiltechnik 3. Surgimesh®, Aspide Medical, Resorba 4. PDS Plate®, Johnson & Johnson 5. Mersliene Band, Johnson & Johnson 6. Vitamesh®, ProxyBiomedical 7. Vicryl Band, Johnson & Johnson 8. TiLoop®, PFMCell adhesion on the following alloplastic materials is not seen neither in the uncovered nor in the covered approach: Ethisorb Patch®, EthiconProceed surgical mesh®, EthiconCollagenmeshResodont mesh®, ResorbaParasorb mesh®, ResorbaDualmesh®, Fa.GoreMycromesh®, Fa.GorePCL scaffoldAdVance male sling®, AMSSeratim®, Serag-Wiessner Conclusions: TFT Motifmesh represents the only alloplastic material that shows in vitro biocompatibility for the cell types characterising the pelvic floor and abdominal wall. Cell adhesion to the tested alloplastic materials regarding cells of the pelvic floor is insufficient. This observation may explain the occurrence of foreign-body reaction and missing integration of alloplastic materials into the pelvic floor. Coating of meshs with autologous plasma results in an improvement of the biocompatibility of alloplastic materials.
Keywords: antibody; actin; desmin; marker; vimentin; collagen; polyglactin; cell marker; biocompatibility; in vitro study; urology; fibroblast; cell adhesion; cell count; pelvis floor; patient; myoblast; endothelium cell; surgery; blood autotransfusion; tissue injury; incontinence; immunohistochemistry; gender; tissues; cell growth; abdominal wall; adhesion; surgical equipment; male; cells by body anatomy; foreign body reaction; hernia; Food and Drug Administration; female; surgical training; risk; foreign body; immunocytochemistry; serum

Total laparoscopic repair of foreign body perforation of jejunum - Herman, F.; Patel, N.; Yung, M.; Christian, D. (Surgical Endoscopy and Other Interventional Techniques, 2010)
Introduction: Foreign body ingestion is a common occurrence in both adults and in children. It is usually a benign occurrence with 75.6% of all FB ingestions passing through the GI tract spontaneously. Rarely, does the foreign body perforate the intestinal wall (0.73%). Perforation is difficult to diagnose as history, symptoms, laboratory and imaging tests are often vague and non-specific Case Presentation: We present a case of a 55 year old Hispanic woman with a 3 day history of abdominal pain associated with anorexia, nausea and one episode of vomiting. Physical examination demonstrated tachycardia at 110 beats per minute, and an obese abdomen that was diffusely tender, with rebound tenderness in the right lower quadrant. Routine laboratory studies revealed an elevated white blood cell count and alkaline phosphatase level. CT of the abdomen demonstrated mural thickening of a small segment of small bowel. No intraperitoneal free air or fluid was seen. After 48 hours, laboratory values returned to normal but right lower quadrant tenderness persisted. Diagnostic laparoscopy was performed and a foreign body was seen protruding through the bowel wall 100cm proximal to the ileal cecal valve. A 3cm fragment of chicken bone was removed with laparoscopic graspers and the perforation was primarily repaired. Postoperatively, the patient improved significantly and was discharged home on post operative day 1. Discussion: Bowel perforation by foreign body can be difficult to diagnose as the most common clinical presentation is of diffuse abdominal pain (67%). Risk factors for foreign body ingestion include orthodontic appliances (75%), mental illness and alcoholism. Sensitivity of CT is low, detecting only 10% of all foreign body intestinal perforations. 90% of foreign body perforations are diagnosed during laparotomy, with most pre-operative diagnoses being acute appendicitis, acute diverticulitis or acute abdomen of unknown origin. The majority of foreign body perforations are repaired with laparotomy and resection of the injured bowel with or without colostomy. We demonstrated that laparoscopic removal of the foreign body with primary repair can result in a satisfactory outcome with minimal hospital stay.
Keywords: alkaline phosphatase; perforation; jejunum; society; surgeon; human; foreign body; ingestion; laboratory; intestine; abdomen; intestine perforation; laparotomy; diagnosis; abdominal pain; intraperitoneal drug administration; anorexia; female; alcoholism; tachycardia; Hispanic; leukocyte count; diverticulitis; small intestine; acute abdomen; liquid; child; physical examination; risk factor; vomiting; imaging; patient; bone; nausea; chicken; laparoscopy; orthodontic device; mental disease; hospitalization; acute appendicitis; surgery; colostomy; intestine wall; adult

Conductive keratoplasty for the treatment of astigmatism induced by corneal trauma or incision - Xu, W.; Ye, P.; Yao, K.; Ma, J.; Xu, H. (Journal of Refractive Surgery, 2010)
PURPOSE: To assess the efficacy, safety, and predictability of conductive keratoplasty for the treatment of corneal trauma/incision-induced hyperopic or compound astigmatism. METHODS: Thirteen eyes with corneal trauma/incision- induced astigmatism underwent conductive keratoplasty in this prospective study. The main outcome measures included distance uncorrected visual acuity (UCVA), near UCVA, best spectacle-corrected visual acuity (BSCVA), manifest refraction cylinder, keratometric astigmatism, manifest refraction spherical equivalent (MRSE), contrast sensitivity, glare sensitivity, intraocular pressure, tear break-up time, endothelial cell count, and pachymetry. Patients were followed 1 week and 1, 3, and 6 months postoperatively. RESULTS: Mean logMAR scores for distance UCVA, near UCVA, and BSCVA significantly improved from 0.87±0.31, 1.32±0.41, and 0.18±0.18, respectively, to 0.32±0.21, 0.59±0.21, and 0.08±0.11 (P≤.05), respectively, 6 months after conductive keratoplasty. Mean manifest refraction cylinder, keratometric astigmatism, and MRSE significantly reduced from 4.12±2.86 diopters (D), 4.15±2.40 D, and 0.73±2.56 D, respectively, to 1.46±1.35 D, 1.66±1.44 D, and -0.52±0.99 D (P≤.05), respectively, at 6 months postoperatively. Contrast sensitivity and glare sensitivity showed significant improvement at spatial frequencies of 1, 1.6, 2.5, 4, and 6.3 cycles per degree (P≤.05). Surgically induced astigmatism calculated by vector analysis highly correlated to target induced astigmatism (P≤.05). No severe complications occurred postoperatively. CONCLUSIONS: This study suggests that conductive keratoplasty is an effective and safe treatment for hyperopic or compound astigmatism after corneal trauma or incision. Copyright ©SLACK Incorporated.
Keywords: adult; aged; article; astigmatism; blurred vision; cell count; clinical article; contrast; contrast enhancement; cornea injury; endothelium cell; eye discomfort; female; foreign body; human; intraocular pressure; keratometry; keratoplasty; male; outcome assessment; postoperative complication; postoperative period; priority journal; prospective study; refraction error; scoring system; spatial frequency discrimination; surgical patient; visual acuity

Retained surgical foreign bodies: Can these be prevented? - Sushel, C.; Khanzada, T.W.; Samad, A. (Pakistan Journal of Medical Sciences, 2010)
Objectives: To determine the frequency and modes of presentation of retained surgical foreign bodies. Methodology: This study was carried out mainly at a private teaching hospital i.e. Isra University Hospital and four other non-teaching private hospitals of Hyderabad city over a period of five years from June 2004 to May 2009. Results: A total of 15 patients with retained surgical foreign body were found during the above mentioned study period. Female patients were more common than male patients. Gynaecological procedures were more frequently associated with surgical retained foreign bodies. Most (60%) of the causative procedures were performed as emergency procedures. Retained sponge was the most frequent foreign body (60%) followed by gauze piece. Discharging sinuses and abdominal masses (33.3% each) were the most frequent presentations followed by intestinal obstruction (20%). Conclusion: Retained surgical foreign body is a rare but well known iatrogenic complication of surgery mostly seen in procedures done as emergency. Discharging sinuses, abdominal mass and intestinal obstruction are the most common modes of presentation. Proper frequent double sponge count and use of radioopaque markers are the major preventive measures to safeguard against this dangerous complication.
Keywords: abdominal mass; adult; article; child; clinical article; female; foreign body; gauze dressing; human; intestine obstruction; male; school child; surgical foreign body; teaching hospital

Transmural migration of a surgical compress into the stomach after splenectomy: A case report - Akbulut, S.; Sevinc, M.M.; Basak, F.; Aksoy, S.; Cakabay, B. (Cases Journal, 2009)
A surgical compress retained in the abdominal cavity following surgery is a serious problem. Here, we describe a 33-year-old female who was admitted with abdominal pain, vomiting, no passage of gas or feces, and abdominal distension for 3 days. She had a splenectomy at another medical center 4 years previously. An upright plain abdominal film revealed small bowel obstruction with marked small bowel air-fluid levels. The physical examination revealed muscular guarding and rebound tenderness in the periumbilical region. Therefore, a laparotomy was performed. A surgical compress was removed at enterotomy and the final diagnosis was gossypiboma. Because a retained surgical compress may lead to medicolegal problems, it is important to count the material used before and after a surgical procedure to reduce the risk of this problem. © 2009 Akbulut et al.; licensee Cases Network Ltd.
Keywords: abdominal distension; abdominal pain; adult; article; case report; emergency surgery; female; gossypiboma; human; intestine surgery; laparotomy; phytobezoar; postoperative complication; small intestine obstruction; splenectomy; vomiting

Safe surgery: reducing the risk of retained items. - Woodhead, K. (Journal of perioperative practice, 2009)
Research from the United States which explores events related to the surgical count has identified that there are opportunities to review our practice in order to reduce risks to surgical patients. The Safe Surgery Saves Lives Campaign highlights this aspect of perioperative patient safety, ensuring that poor processes and poor communication, often the reasons for retained surgical items, become part of the team 'sign-out' at the end of every operation.
Keywords: article; checklist; human; medical error; risk management; safety; United Kingdom; United States

Enterocolic fistula associated with small bowel lymphoma - Chun, H.B.; Baek, I.H.; Lee, M.S.; Kim, H.J.; Kim, J.B.; Shin, S.R.; Kim, B.C.; Jung, S.Y. (Journal of Gastroenterology and Hepatology, 2009)
Introduction: Enterocolic fistulas are usually caused by inflammatory conditions such as inflammatory bowel disease. The other causes are prior surgery, foreign bodies, pancreatitis, diverticulitis, intestinal tuberculosis and malignancies. Lymphoma accounts for up to 20% of all primary tumours of the small bowel, occurring most frequently in the terminal ileum and becoming progressively less frequent proximally. This study describes enterocolic fistula in a patient with jejunal lymphoma. Case report: An 56-year-old man presented with an acute diarrheal illness starting 14 days prior to hospital. He had daily fevers, chills, night sweat 1 month prior to hospital. His past medical history was significant for pulmonary tuberculosis in his 3rd decades, There was no prior history of abdominal surgery. The patient was ill looking, His laboratory tests showed hyponatremia, hypokalemia, hypoalbuminemia, the complete blood count revealed a normocytic normochromic anemia. The infectious diarrhea work-up was negative. A computed tomographic scan of the abdomen with intravenous contrast showed focal wall thickening in distal transverse colon with regional Lymph nodes During the colonoscopiy an fistula was identified at the distal-transverse colon with a communication to the small bowel. Colonoscope was not advanced through the fistula due to the risk of perforation. He was admitted to the hospital for operation and extended Rt. hemicolectomy and segmental jejunectomy was done. lymphoma was confirmed at surgical pathology. After surgery, the patient showed rapid recovery and the chemotherapy will be performed after full recovery from surgery.
Keywords: colon fistula; lymphoma; small intestine; Asia; surgery; hospital; patient; transverse colon; fistula; history of medicine; lung tuberculosis; abdominal surgery; laboratory test; hyponatremia; hypokalemia; hypoalbuminemia; blood cell count; normochromic normocytic anemia; infectious diarrhea; computer assisted tomography; abdomen; lymph node; interpersonal communication; colonoscope; risk; perforation; hemicolectomy; pathology; chemotherapy; inflammation; enteritis; pancreatitis; intestinal tuberculosis; primary tumor; ileum; case report; diverticulitis; human; general aspects of disease; fever; night sweat; foreign body

In vitro test pattern for determination of biocompability of alloplastic materials used for treatment of urinary incontinence - Gerullis, H.; Eimer, C.; Bagner, J.; Otto, T. (Urology, 2009)
Introduction and Objective: Alloplastic materials are increasingly applied in continence surgery. GMP conformable trials do not exist. Many of the materials have a strong tissue adherence thus resulting in a foreign material reaction. The purpose of the study was to evaluate the biocompability of different alloplastic materials. Materials and Methods: An in vitro pattern using myoblasts has been established in order to investigate the ability of alloplastic materials to integrate into the pelvic floor muscle or act as foreign material. The expression of the following specific markers of myogenic differentiation was measured (α-SM-actin, SM-actin, Desmin, MyoD1). Each measurement was performed double blinded under identical circumstances regarding cell culture and myoblasts count. The allogenic materials were investigated for six weeks in myoblastic culture. Myoblast count and adherence were evaluated using light optical microscope. Results: The following alloplastic materials have been investigated: Vitamesh, TFT Motifmesh, Ethisorb Patch, Vicrylsling, PDS Plate, Proceed surgical mesh, Mersilan sling, Surgimesh, Collagenmesh, Resodont mesh, Parasorb mesh, PCL scaffold. Cell count and cell growth were compared over 6 weeks. Myoblasts were merely adherent and growing in culture with TFT Motifmesh (Tetrafluoroethylen). We fixed TFT Motifmesh in the tissue with bio adhesive. Myoblast compability was measured using the bio adhesive, resulting in equal myoblast growth and tissue adherence. All other materials investigated in this study did not show myoblast adherence and therefore no myoblast growth on the material. Conclusions: In our study TFT Motifmesh has been the only material showing in vitro biocompability for myoblasts.
Keywords: adhesive agent; actin; guanosine phosphate; marker; desmin; in vitro study; urine incontinence; myoblast; tissues; foreign body; surgical equipment; cell count; surgery; cell growth; continence; pelvis floor; cell culture; microscope; optics

So who's counting? - Avery, J.K. (Tennessee medicine : journal of the Tennessee Medical Association, 2009)
Keywords: adult; article; case report; economics; female; foreign body; human; legal liability; malpractice; pelvis pain syndrome; postoperative complication; surgical equipment; surgical sponge

Visual outcome and complications after removal of posterior segment intraocular foreign bodies through pars plana approach - Memon, A.A.; Saeed Iqbal, M.; Cheema, A.; Niazi, J.H. (Journal of the College of Physicians and Surgeons Pakistan, 2009)
Objective: To assess the visual outcome and complications after removal of posterior segment retained intraocular foreign bodies through pars plana approach. Study Design: Case series. Place and Duration of Study: Department of Ophthalmology, Jinnah Postgraduate Medical Centre, Karachi, from May 2005 to May 2006. Methodology: Fifty patients with history of ocular foreign body were admitted through outpatient department and emergency. History, visual acuity, ocular and general examination was done. The foreign body was localized with the radiograph of the skull and ultrasonography. Primary repair was done in patients with open wounds. Pars plana vitrectomy, magnetic or forceps extraction of foreign body was done as required visual outcomes and complications were noted. Results: Among the 50 patients, there were 45 (90%) males and 5 (10%) females. Average age of the patients was 31.52 ±9.52 (ranging from 20 to 50) years. The pre-operatively visual acuity finger counting to perception of light was 78% cases. The best corrected final visual acuity was 6/6 in 1 (2%) patient, 6/9 in 5 (10%) patients, 6/12 in 5 (10%) patients, 6/18 in 3 (6%) patients, 6/24 and 6/36 in 4 (8%) patients each, 6/60 in 4 (8%) patients, finger counting in 8 (16%) patients, hand movement in 4 (8%) patients, projection of light in 9 (18%) patients and no projection of light in 3 (6%) patients. The postoperative complications were corneal opacity in 8 (16%) patients, anterior chamber inflammatory reaction in 6 (12%) patients, increased intraocular pressure in 1 (2%) patient, silicone oil in anterior chamber in 1 (2%) patient, macular scar in 7 (14%) patients, cystoid macular edema in 1 (2%) patient, endophthalmitis in 4 (8%) patients, retinal detachment in 11 (22%) patients and phthisis bulbi in 3 (6%) patients. Conclusion: Acceptable visual results were achieved after the removal of posterior segment intraocular foreign bodies by vitrectomy. However, multiple complications can be encountered which require meticulate postoperative care.
Keywords: silicone oil; adult; anterior eye chamber; article; clinical article; cornea opacity; echography; endophthalmitis; eye examination; female; hand movement; human; intraocular foreign body; intraocular pressure; light; male; phthisis bulbi; postoperative care; postoperative complication; postoperative inflammation; preoperative evaluation; retina detachment; retina macula cystoid edema; skull radiography; surgical approach; vision; visual acuity; vitrectomy

Retained surgical sponges after craniotomies: Imaging appearances and complications - Kim, A.K.; Lee, E.B.; Bagley, L.J.; Loevner, L.A. (American Journal of Neuroradiology, 2009)
Imaging within 24 to 48 hours after most neurosurgical procedures is a routine practice. Nonresorbable surgical sponges have radiopaque filaments readily visible on CT scans and plain film radiographs. However, the proton-poor barium sulfate responsible for this radio-opacity is generally not detectable on MR imaging in the immediate post-operative period. Findings on MR imaging become more evident with elapsing time and when a foreign-body reaction to the sponge manifests as a mass lesion, which can mimic residual or recurrent intracranial tumor or abscess. Although preventive measures by our surgical colleagues to ensure accurate and correct sponge counts before and after wound closure is paramount, even the most fastidious efforts may rarely result in an inadvertently retained surgical sponge. The role of the radiologist is to recognize the imaging findings of this entity and its potential complications so that appropriate and prompt management can be initiated.
Keywords: adult; adverse outcome; amnesia; article; blood examination; brain abscess; brain biopsy; brain edema; brain hemorrhage; case report; cerebrospinal fluid analysis; computer assisted tomography; confusion; craniotomy; differential diagnosis; female; fever; follow up; foreign body reaction; head injury; headache; human; human tissue; image display; intracranial tumor; leukoencephalopathy; male; meningioma; mental deterioration; nuclear magnetic resonance imaging; postoperative complication; reoperation; retained instrument; surgical sponge; wound closure

Prevention of retained surgical sponges: A decision-analytic model predicting relative cost-effectiveness - Regenbogen, S.E.; Greenberg, C.C.; Resch, S.C.; Kollengode, A.; Cima, R.R.; Zinner, M.J.; Gawande, A.A. (Surgery, 2009)
Background: New technologies are available to reduce or prevent retained surgical sponges (RSS), but their relative cost effectiveness are unknown. We developed an empirically calibrated decision-analytic model comparing standard counting against alternative strategies: universal or selective x-ray, bar-coded sponges (BCS), and radiofrequency-tagged (RF) sponges. Methods: Key model parameters were obtained from field observations during a randomized-controlled BCS trial (n = 298), an observational study of RSS (n = 191,168), and clinical experience with BCS (n ∼ 60,000). Because no comparable data exist for RF, we modeled its performance under 2 alternative assumptions. Only incremental sponge-tracking costs, excluding those common to all strategies, were considered. Main outcomes were RSS incidence and cost-effectiveness ratios for each strategy, from the institutional decision maker's perspective. Results: Standard counting detects 82% of RSS. Bar coding prevents ≥97.5% for an additional $95,000 per RSS averted. If RF were as effective as bar coding, it would cost $720,000 per additional RSS averted (versus standard counting). Universal and selective x-rays for high-risk operations are more costly, but less effective than BCS-$1.1 to 1.4 million per RSS event prevented. In sensitivity analyses, results were robust over the plausible range of effectiveness assumptions, but sensitive to cost. Conclusion: Using currently available data, this analysis provides a useful model for comparing the relative cost effectiveness of existing sponge-tracking strategies. Selecting the best method for an institution depends on its priorities: ease of use, cost reduction, or ensuring RSS are truly "never events." Given medical and liability costs of >$200,000 per incident, novel technologies can substantially reduce the incidence of RSS at an acceptable cost. © 2009 Mosby, Inc. All rights reserved.
Keywords: article; cost effectiveness analysis; decision making; medical liability; priority journal; surgical risk; surgical sponge

Associations between operative site microbial counts and procedure classification in neurosurgery - Maraki, S.; Karabetsos, D.; Tsiodras, S.; Kourbeti, I.; Ioannou, A.; Neophytou, C.; Filippou, M.; Vakis, A. (Clinical Microbiology and Infection, 2009)
Objectives: Correlation between operative site skin bacterial counts in neurosurgical procedures and the development of surgical site infections (SSI) has not been proven. We evaluated the association of bacterial Colony Forming Units(CFU), type of procedure and development of SSI in a prospective pilot study Methods: Skin swab cultures were obtained within 1 cm from the incision; pre-, post-preparation and preclosure samples were obtained. Bacterial counts were enumerated and the most prevalent organisms were recorded. Procedures were classified as clean, clean with foreign body, clean contaminated, contaminated and dirty Results: 83 procedures (42.1% clean, 21.7% clean-contaminated, 18% clean with foreign body, 14.5% contaminated and 4.8% dirty) in 70 patients(70% male) were evaluated prospectively. Trauma was the most common reason for surgery (31.8%). 93 sample sets were cultured. 88.2% preprep, 28% postprep and 43.5% of the preclosure samples tested positive. Coagulase-negative staphylococci (CoNS) were the most frequently isolated organisms irrespectively of sampling time (62.4%, 18.3% and 29.3% for samples 1, 2 and 3 respectively) and independently of procedure classification. The median cfu count log for CoNS were 3 log(range 2-6.3), 2.6(range 2-3.7) and 2.4(range 2-4) respectively for each sampling. P. acnes was the second most frequent pathogen isolated. The median cfu count log for P. acnes were 3.9 log (range 2.2-6.6), 3.2 (range 2-3.8) and 4.3 (range 2-5.4) respectively for each sampling. There was a significant difference in the P. acnes counts isolated from head versus other sites. Procedure classification or prolonged surgery duration were not associated with microbial counts irrespectively of sampling time. SSI development was not associated with bacterial CFU at any sampling, therefore there was a trend for association with CoNS pre-preparation CFU. Conclusion: CoNS was the most frequent bacterial pathogen cultured irrespectively of sampling. The pathogen cfu log did not significantly differ among the samples. P. acnes was significantly more isolated from head specimens. Procedure classification was not associated with microbial skin counts at any sampling but CoNS prepreparation CFU carried a trend for statistical association with SSI development in this pilot study.
Keywords: classification; infection; neurosurgery; microbiology; sampling; Propionibacterium acnes; colony forming unit; pathogenesis; skin; pilot study; foreign body; bacterial count; bacterium colony; incision; patient; male; injury; surgery; coagulase negative Staphylococcus; operation duration

Lung Parasite Ova Granuloma Mimicking Lung Malignancy on FDG PET-CT - Kao, P.-F.; Tsao, T.C.-Y.; Kuo, K.-T.; Yue, C.-T.; Lim, K.-R.; Chou, Y.-H. (Clinical Nuclear Medicine, 2009)
A 60-year-old lady with mild fever, blood tinged sputum, and a left upper lung mass had whole body F-18 2-deoxy-D-glucose (FDG) positron emission tomography (PET)-computer tomography (CT) for cancer staging. The PET-CT imaging revealed FDG accumulation in the left upper lung lesion. The histopathology of the left upper lobe lung resection showed a parasite tunnel with necrosis, parasite ova, and foreign body giant cells. After surgery, eosinophiles in the peripheral blood dropped from 20% of white cell counts before operation to 5.5% at 7 weeks postoperation. © 2009 by Lippincott Williams & Wilkins.
Keywords: fluorodeoxyglucose f 18; adult; article; bronchoscopy; case report; computer assisted emission tomography; computer assisted tomography; disease severity; eosinophil; female; fever; foreign body; giant cell; hemoptysis; histopathology; human; leukocyte count; lung granuloma; lung resection; oocyte; Paragonimus; postoperative period; body weight loss

Improving safety in the operating room: A systematic literature review of retained surgical sponges - Wan, W.; Le, T.; Riskin, L.; Macario, A. (Current Opinion in Anaesthesiology, 2009)
PURPOSE OF REVIEW: Gossypibomas are surgical sponges that are unintentionally left inside a patient during a surgical procedure. To improve this patient safety indicator, anesthesiologists will need to work with operating room personnel. This study's goal was to systematically review the literature on retained sponges to identify body location, time to discovery, methods for detection, and risk factors. RECENT FINDINGS: Two hundred and fifty-four gossypiboma cases (147 reports from the period 1963-2008) were identified via the National Library of Medicine's Medline and the Cochrane Library. Gossypibomas (mean patient age 49 years, range 6-92 years) were most commonly found in the abdomen (56%), pelvis (18%), and thorax (11%). Average discovery time equaled 6.9 years (SD 10.2 years) with a median (quartiles) of 2.2 years (0.3-8.4 years). The most common detection methods were computed tomography (61%), radiography (35%), and ultrasound (34%). Pain/irritation (42%), palpable mass (27%), and fever (12%) were the leading signs and symptoms, but 6% of cases were asymptomatic. Complications included adhesion (31%), abscess (24%), and fistula (20%). Risk factors were case specific (e.g. emergency) or related to the surgical environment (e.g. poor communication). Most gossypibomas occurred when the sponge count was falsely pronounced correct at the end of surgery. SUMMARY: More is being discovered about the patterns leading to a retained sponge. Multidisciplinary approaches and new technologies may help reduce this low frequency but clinically significant event. However, given the complexity of surgical care, eliminating retained sponges may prove elusive. © 2009 Lippincott Williams & Wilkins, Inc.
Keywords: abdomen; abscess; adhesion; age distribution; calcification; Cochrane Library; computer assisted tomography; diagnostic imaging; emergency; fever; fistula; human; incidence; interpersonal communication; mass; Medline; operating room; pain; patient safety; pelvis; priority journal; retained instrument; review; risk assessment; surgical sponge; systematic review; thorax; ultrasound

Micafungin plus fluconazole in an infected knee with retained hardware due to candida albicans - Bland, C.M.; Thomas, S. (Annals of Pharmacotherapy, 2009)
objective: To describe the use of micafungin and fluconazole in the management of a fungal prosthetic joint infection caused by Candida albicans. case summary: A 55-year-old female who had undergone total left knee arthroplasty due to rheumatoid arthritis presented with symptoms of a left knee infection. Intravenous vancomycin 1 g every 12 hours and intravenous ampicillin/ sulbactam 1.5 g every 6 hours were initiated. Arthrocentesis produced cloudy synovial fluid with a white blood cell (WBC) count of 5.995 × 10 3/μL C-reactive protein (CRP) was 19.8 mg/dL and erythrocyte sediment rate (ESR) was greater than 120 mm/h. Gram stain was negative, but intraoperative cultures grew C. albicans. Four days later the patient's condition worsened and repeat arthrocentesis showed WBC count of 16.8 × 103/μL with budding yeast in the synovial fluid. Antibiotics were stopped and liposomal amphotericin B 5 mg/kg once daily was started but was stopped after a few doses due to renal failure. Intravenous micafungin 100 mg daily was initiated: intravenous fluconazole 400 mg daily was added 2 days later and subsequently changed to oral fluconazole after 2 days of therapy. The patient received combination micafungin/fluconazole therapy for 8 weeks. After approximately 8 weeks of therapy, the CRP level and ESR had decreased from 19.8 to 7.1 mg/dL and greater than 120 to 81 mm/h. respectively. The patient's pain and range of motion in her knee had returned to baseline levels at last follow-up after the total knee arthroplasty. After 8 weeks of combination therapy, micafungin was discontinued but oral fluconazole was continued; approximately 8 weeks later the patient relapsed, requiring removal of the prosthetic knee hardware. discussion: Fungal prosthetic joint infections are rare, but definitive data regarding appropriate treatment are lacking. Echinocandins are an attractive treatment option due to their enhanced biofilm penetration. In our patient, treatment with micafungin plus fluconazole for 8 weeks followed by fluconazole monotherapy was associated with an initial good outcome in the treatment of a C. albicans prosthetic knee infection with retained hardware. This was, to our knowledge, the first case using micafungin in a prosthetic joint infection. conclusions: Although micafungin plus fluconazole showed positive results in our patient, more data are needed regarding combination therapy for fungal prosthetic joint infections.
Keywords: amphotericin B lipid complex; antibiotic agent; C reactive protein; fluconazole; micafungin; polyethylene; sultamicillin; vancomycin; adult; arthrocentesis; article; bacterium culture; Candida albicans; candidiasis; case report; clinical feature; computer; disease exacerbation; drug withdrawal; erythrocyte sedimentation rate; female; human; intraoperative period; joint prosthesis; knee pain; leukocyte count; monotherapy; priority journal; range of motion; retained instrument; rheumatoid arthritis; synovial fluid; total knee arthroplasty; treatment duration; treatment outcome

Histological Inflammatory Response to Transvaginal Polypropylene Mesh for Pelvic Reconstructive Surgery - Elmer, C.; Blomgren, B.; Falconer, C.; Zhang, A.; Altman, D. (Journal of Urology, 2009)
Purpose: We prospectively evaluated the histological inflammatory response to the large polypropylene transvaginal mesh used for pelvic organ prolapse surgery. Materials and Methods: Ten patients and 8 controls underwent vaginal punch biopsy sampling before surgery and patients also underwent it 1 year after pelvic reconstructive surgery using polypropylene mesh. Foreign body response to the mesh was assessed using a combination of histological, semiquantitative and computerized image based analysis. Results: Compared to preoperative histology there was a significant postoperative increase in macrophage and mast cell counts (p = 0.03 and 0.01) but no significant changes in the count of cells involved primarily in the infectious cell response or collagen density and the elastin area fraction at the mesh-tissue interface (p = 0.2 and 0.3, respectively). Three cases of mild granuloma formation and 2 of mild erosion were observed. There was no significant change in epithelial thickness when comparing preoperative and postoperative samples. Conclusions: When used for pelvic reconstructive surgery, macroporous monofilament polypropylene mesh induces a mild but persistent foreign body reaction. © 2009 American Urological Association.
Keywords: collagen; elastin; polypropylene; aged; article; cell count; clinical article; clinical assessment; control group; controlled study; erosion; female; foreign body reaction; granuloma; histology; human; image analysis; macrophage; mast cell; mesh sling; pelvis surgery; plastic surgery; postoperative period; priority journal; prospective study; punch biopsy; quantitative analysis

Comparative evaluation of men's depilatory products versus razor - Oresajo, C.; Kindred, C.; Yatskayer, M.; Halder, R. (Journal of the American Academy of Dermatology, 2009)
Shaving with razors is often problematic in sensitive skin, especially skin of African Americans. This method of shaving often leads to erythema and irritation. Moreover, African American men are prone to pseudofolliculitis barbae (PFB), a common and distressing disorder in which growing hair shaft curve back into the skin, producing a foreign body inflammatory reaction. Depilatory creams chemically remove hair from the skin surface. The active ingredients of depilatory creams are chemicals that dissolve the keratin of hair. This controlled, single-center, split-faced, randomized trial was undertaken to compare shaving with two different depilatory products (product A, containing calcium hydroxide, guanidine carbonate, and calcium thioglycolate; and product B, containing calcium hydroxide, lithium hydroxide, and thioglycolic acid) to shaving with a razor on 45 African Americans male volunteers, 18 years of age or older, with skin prone to razors bumps. They were all current or previous users of depilatory cream. The volunteers underwent a sensitivity test and only qualified volunteers were enrolled into the study. The volunteers were required to shave at home with their normal method 2 days before the first visit. At the first visit, a dermatologist performed a preshave evaluation to assess irritation, skin roughness, and lesion count. Volunteers were asked to shave one half of the face with the provided razor and shaving cream and the other side with one of the depilatory creams (according to randomization). Immediately after shaving, a dermatologist performed the postshave evaluation by reassessing for irritation and efficacy, photographing both sides of the face, and counting lesions. The participant returned 2 and 4 days later and repeated the shaving technique. At each visit, a dermatologist repeated evaluation as described at the first visit. Volunteers completed a self-assessment questionnaire at each study visit. In this short study, the results indicate that there were fewer papules that developed on the depilatory-treated side compared to the razor shaved side in most subjects who used either of two products. While both depilatory products produced more irritation immediately after use and to a greater extent than the razor, the irritation was transient, and more often subjective than objective. The result of using either depilatory product was that the skin looked and felt smoother than shaving with a razor. Product A generated more irritant contact dermatitis than product B. All cases of irritant contact dermatitis resolved in 2 to 5 days without scarring or dyspigmentation.
Keywords: thioglycolic acid; calcium hydroxide; guanidine; carbonic acid; calcium; lithium; keratin; dermatology; volunteer; skin; hair; African American; irritant dermatitis; randomization; self evaluation; questionnaire; papule; inflammation; skin surface; scar formation; foreign body; male; erythema

Transconjunctival 20-gauge vitrectomy: A pilot study - Aguni, J.S.; Meyer, C.H.; Rodrigues, E.B. (Ophthalmologica, 2009)
Purpose: To determine the efficacy of a novel technique for a 'transconjunctival 20-gauge vitrectomy' (T20V). Methods: In total, 12 eyes of 12 consecutive patients were included in a prospective study. The mean age was 58 years (range: 38-74 years); 4 patients were male and 8 were female. The T20V was indicated when short-duration vitrectomy was envisioned: macular surgery for macular hole and epiretinal membrane therapy, moderate vitreous hemorrhage due to retina vein occlusions or diabetic retinopathy, or neurotomy for central retinal vein occlusion. Results: The average time for each procedure was 35 ± 30 min (SD). The preoperative visual acuity ranged from 20/200 to hand motions, while postoperative vision was between 20/30 and counting fingers. The average intraocular pressure changed from 16.1 ± 5.6 mm Hg preoperatively to 15.8 ± 8.1 mm Hg in the first postoperative day, and 17.8 ± 9.4 mm Hg 1 week after surgery - these differences were not statistically significant (p > 0.05). Subjective postoperative pain and foreign body sensation at postoperative day 1 and week 1 were mild to moderate. The chemosis observed 1 h after surgery was minimal, and disappeared quickly during the 1-week follow-up. Conclusion: The T20V is suitable to perform short-duration vitrectomy surgery, and has a low rate of ocular complications, similar to 25- or 23-gauge sutureless vitrectomy systems. Copyright © 2008 S. Karger AG.
Keywords: aged; article; central retina vein occlusion; chemosis; clinical article; clinical effectiveness; clinical trial; diabetic retinopathy; epiretinal membrane; female; foreign body; hand movement; human; hypotony maculopathy; intraocular pressure; male; operation duration; patient safety; pilot study; postoperative complication; postoperative pain; postoperative period; preoperative evaluation; prospective study; retina detachment; retina macula hole; retina vein occlusion; sclerotomy; surgical approach; visual acuity; vitrectomy; vitreous hemorrhage

Gossypiboma: a case report and review of the literature. - Kiernan, F.; Joyce, M.; Byrnes, C.K.; O'Grady, H.; Keane, F.B.; Neary, P. (Irish journal of medical science, 2008)
INTRODUCTION: Post-operative complications in surgery may frequently be unavoidable. However, some complications result from human error, both in the intra-operative and post-operative period. One such complication, which is frequently underreported, is the retained swab, or gossypiboma. CASE REPORT: We report a case from our hospital of a patient who presented with unexplained pyrexia, 4 years post-gynaecological surgery in another institution. A 67-year-old woman from overseas presented to our emergency department with a 2-day-history of pyrexia, collapse and confusion. Following a CT guided biopsy, which was inconclusive, she was scheduled for retroperitoneal biopsy. In theatre, a retained swab was discovered. CONCLUSION: Prevention of gossypiboma is far better than cure. Strict adherence to swab counts, and the avoidance of change of staff during procedures is important in decreasing the incidence. Perhaps, with the increasing use of minimally invasive procedures, the incidence of gossypiboma will fall dramatically.
Keywords: aged; case report; confusion; female; fever; foreign body; gynecologic surgery; human; iatrogenic disease; medical error; review; risk factor; surgical equipment; surgical sponge

The Surgical Instrument Counting Process: A Statistician's Plea for Terminology Clarification - Selvan, M.S.; Skibber, J.M.; Walsh, G.L. (Journal of Surgical Research, 2008)
Keywords: editorial; foreign body; medical error; medical literature; nomenclature; postoperative period; priority journal; surgical equipment

Perforating Globe Injuries during Operation Iraqi Freedom - Colyer, M.H.; Chun, D.W.; Bower, K.S.; Dick, J.S.B.; Weichel, E.D. (Ophthalmology, 2008)
Objective: To report the injury patterns associated with perforating (through-and-through) injuries of the globe and the visual impact of these injuries on patients with combat ocular trauma (COT) seen at Walter Reed Army Medical Center (WRAMC) from March 2003 through October 2006. Design: Retrospective, noncomparative, interventional case series. Participants: Sixty-five eyes of 61 United States military soldiers deployed during Operation Iraqi Freedom sustaining perforating globe injuries and treated subsequently at WRAMC. Intervention: Principal procedures included enucleation and 20-gauge 3-port pars plana vitrectomy with or without intraocular foreign body removal. Main Outcome Measures: Final visual acuity and rates of proliferative vitreoretinopathy, enucleation, and endophthalmitis. Results: Average patient age was 29 years, with an average of 200 days of postinjury follow-up (median, 97 days; range, 4-1023 days). Nineteen patients confirmed the use of eye protection at the time of injury, whereas 25 patients did not use eye protection. The median presenting visual acuity at WRAMC was no light perception (range, no light perception to hand movements). Twenty-five patients underwent primary enucleation, 1 was eviscerated, and 12 patients underwent secondary enucleation within 2 weeks of surgery. Of 19 patients undergoing pars plana vitrectomy, median visual acuity at presentation was light perception and the median final visual acuity was counting fingers, whereas 4 eyes (21%) achieved final visual acuity of better than 20/200, and in 11 (61%) of 17, proliferative vitreoretinopathy developed over a follow-up of at least 6 months. There were no cases of endophthalmitis or sympathetic ophthalmia. Neither mechanism of injury nor timing of surgery correlated with favorable outcomes. However, entry and exit wounds localized to the anterior half of the globe were associated with favorable anatomic outcome (P<0.005, Fisher exact test, 2-tailed) and visual outcome (P = 0.041, Fisher exact test, 2-tailed). Conclusions: Perforating globe injuries associated with COT generally result in poor visual and anatomic outcomes despite surgical intervention. Prophylactic measures, such as eye protection, are helpful in reducing the likelihood of perforating injuries; however, novel surgical and pharmacologic therapies will be required to improve the functional and anatomic outcomes of these devastating injuries. Financial Disclosure(s): The authors have no proprietary or commercial interest in any materials discussed in this article. © 2008 American Academy of Ophthalmology.
Keywords: adult; army; article; cataract; controlled study; enucleation; human; intraocular foreign body; Iraq; major clinical study; perforating eye injury; priority journal; retina detachment; retina hemorrhage; retina tear; visual acuity; visual impairment; vitrectomy; vitreoretinopathy; vitreous hemorrhage

Radio-opaque marker of a surgical sponge appearing as an intra-articular foreign body after total hip arthroplasty - Takigami, I.; Itoh, Y.; Itokazu, M.; Shimizu, K. (Archives of Orthopaedic and Trauma Surgery, 2008)
We report a 73-year-old female patient who underwent total hip arthroplasty for osteoarthritis of the right hip. An anteroposterior radiograph obtained 1 week after surgery showed an intra-articular striated foreign body. This was subsequently removed and found to be a radio-opaque marker of a surgical sponge that had been used during the operation. The patient made an uneventful recovery. In recent years, cases of retained surgical sponge after surgery have been reported occasionally. Counting surgical sponges and using sponges with radio-opaque markers are methods for preventing them from being accidentally left in situ. However, to our knowledge, there has been no report of retention of a surgical sponge radio-opaque marker at the operation site, appearing as a foreign body on an X-ray film. © Springer-Verlag 2007.
Keywords: barium sulfate; vinyl chloride; aged; article; case report; computer assisted tomography; female; foreign body; hip osteoarthritis; hip radiography; hip surgery; human; leg movement; leg pain; priority journal; range of motion; surgical sponge; total hip prosthesis

The frequency and significance of discrepancies in the surgical count - Greenberg, C.C.; Regenbogen, S.E.; Lipsitz, S.R.; Diaz-Flores, R.; Gawande, A.A. (Annals of Surgery, 2008)
OBJECTIVE:: To prospectively evaluate and accurately describe the rate and type of discrepancies encountered in the surgical count. INTRODUCTION:: Despite near-universal implementation of manual counting protocols for surgical instruments and sponges, incidents of retained sponges and instruments (RSI) persist. Retrospective analyses have shown that RSI are rare and most often involve final counts erroneously thought to be correct, leading some surgeons to question the value of counting. Crucial data regarding how often the surgical count successfully detects meaningful problems before the patient leaves the operating room is lacking. METHODS:: Trained physician-observers documented prospective field observations during 148 elective general surgery operations using standardized intake forms. Data collection focused on the performance of the counting protocols, and the frequency and outcomes of discrepancies (instances in which a subsequent count does not agree with the previous count). RESULTS:: A mean of 16.6 counting episodes occurred per case, occupying 8.6 minutes per case. A total of 29 discrepancies involving sponges (45%), instruments (34%) or needles (21%) were observed among 19 (12.8%) operations. Most discrepancies indicated a misplaced item (59%) as opposed to a miscount (3%) or error in documentation (38%). Each discrepancy took on average 13 minutes to resolve. Counting activities after personnel changes were significantly more likely to involve a discrepancy than those for which the original team was present. CONCLUSIONS:: One in 8 surgical cases involves an intraoperative discrepancy in the count. The majority of these discrepancies detect unaccounted-for sponges and instruments, which represent potential RSI. Thus, despite the recognized limitations of manual surgical counts, discrepancies should always prompt a thorough search and reconciliation process and never be ignored. © 2008 by Lippincott Williams & Wilkins.
Keywords: adult; article; elective surgery; female; general surgery; human; male; medical personnel; needle; operating room; physician; priority journal; prospective study; retained instrument; retrospective study; surgical equipment; surgical error; surgical equipment; surgical sponge; surgical technique; training

Cost-effectiveness of routine radiographs after emergent open cavity operations - Dossett, L.A.; Dittus, R.S.; Speroff, T.; May, A.K.; Cotton, B.A. (Surgery, 2008)
Background: Emergency surgery increases the risk of a retained surgical sponge (RSS) by 9-fold. In most cases, surgical counts are falsely reported as correct. We hypothesized that the institutional costs resulting from a RSS would make routine intraoperative radiography (IOR) more cost-effective than surgical counts in preventing RSS after emergent open cavity cases. Methods: A cost-effectiveness analysis was performed to compare routine IOR with surgical counts after emergent open cavity operations. Parameter estimates were obtained from the literature, expert opinion via a standardized survey, and existing institutional data. Results: Routine IOR was the preferred strategy ($705 vs $1155 per patient) under the assumptions of the base case. The surgical count strategy was dominated by the institutional costs incurred after a RSS. Routine IOR was preferential as long as the sensitivity of surgical counts was less than 98% and the legal fees were more than $44,000 per case of RSS. Conclusions: Routine IOR is a simple, cost-effective option to reduce the occurrence of this preventable medical error. Institutional costs and legal fees associated with RSS dominate the cost of the surgical count strategy, making routine IOR a more cost-effective strategy than surgical counts given the best available parameter estimates. © 2008 Mosby, Inc. All rights reserved.
Keywords: article; cost effectiveness analysis; emergency surgery; health care cost; priority journal; radiography; retained instrument; surgical approach; surgical error; surgical sponge

Radio-frequency surgical sponge detection: a new way to lower the odds of leaving sponges (and similar items) in patients. (Health devices, 2008)
Radio-frequency (RF) tags are now being embedded in items such as surgical sponges, towels, and pads to reduce the chances that these objects will be left in patients after a procedure. Find out how--and how well--RF sponge-detection systems work, including our view of the two systems currently on the market: ClearCount Medical's SmartSponge System, which counts sponges in addition to detecting them. RF Surgical's RF Surgical Detection System, which is a detect-only system.
Keywords: article; foreign body; human; information processing; medical error; operating room; organization and management; postoperative complication; radiofrequency radiation; radiography; surgical sponge

Incidence and Characteristics of Potential and Actual Retained Foreign Object Events in Surgical Patients - Cima, R.R.; Kollengode, A.; Garnatz, J.; Storsveen, A.; Weisbrod, C.; Deschamps, C. (Journal of the American College of Surgeons, 2008)
Background: Incidence of retained foreign objects (RFOs) after operations is unknown, as many can go unrecognized for years. We reviewed the incidence and characteristics of surgical RFO events at a tertiary care institution during 4 years. Study Design: All RFO events, near misses and actual, reported on an adverse event line during 2003 to 2006 were reviewed. Results: During 2003 to 2006, there were 191,168 operations performed, with 68 reported events resulting in a potential RFO defect rate of 0.356/1,000 patients. After review, 34 patients had no RFOs (near misses) and 34 were actual RFOs, resulting in a true RFO defect rate of 0.178/1,000 operations or approximately 1:5,500 operations. In the near-miss patient, needles were miscounted 76% of the time. In the 34 actual RFO patients, items retained were 23 sponges (68%), 7 miscellaneous other items (20%), 3 needles (9%), and 1 instrument (3%). The 34 actual RFOs occurred in incidents where the count had been reported as correct in 21 patients (62%). In 18 patients where an RFO was eventually discovered, intraoperative imaging detected only 12 objects (67%). In operations involving a body cavity, our practice is to obtain a high-resolution x-ray survey film, in a dedicated x-ray suite, before entering the recovery room. Twenty RFOs were identified from survey films and all occurred in patients with correct counts. No RFOs occurred during emergency or high blood-loss procedures and none resulted in demonstrable clinical harm. Two patients left the hospital with an RFO. Twenty-two patients (64.8%) underwent reoperation, with 1 object not removed, 6 (17.6%) retrieved without operation, and 6 (17.6%) where the clinical decision was not to remove. Conclusions: RFOs at an institution that routinely performs postprocedure x-rays indicate that RFOs can occur more frequently than expected from the literature. The majority occur in patients with correct counts. Relying on counting as the primary mechanism to avoid RFOs is unreliable, and investigating new technologies designed to achieve reliable counts is warranted. © 2008 American College of Surgeons.
Keywords: adult; aged; article; bleeding; clinical practice; decision making; female; health care; health hazard; human; incidence; male; malpractice; needle; outcome assessment; patient care; priority journal; surgical technique; X ray

Effect of mitomycin C in pterygium surgery on corneal endothelium - Avisar, R.; Avisar, I.; Bahar, I.; Weinberger, D. (Cornea, 2008)
PURPOSE: To evaluate changes in endothelial cell count after pterygium surgery with 5-minute application of mitomycin C (MMC) 0.02%. METHODS: The study participants included 24 consecutive patients (17 men and 7 women) who underwent pterygium surgery with MMC at a major tertiary center between September and October 2005. The bare sclera technique was used in all cases. After excision of the head and neck of the pterygium, a surgical sponge soaked with MMC 0.02% was placed on the exposed sclera for 5 minutes, with the conjunctival layer draped over the sponge. Thereafter, the sclera was irrigated with balanced salt solution, and surgery was completed. Endothelial images were acquired at the center of the cornea with a specular microscope (average of 3 measurements) before surgery and at 1 week, 1 month, and 3 months after surgery. RESULTS: Mean preoperative endothelial cell count was 2254 ± 128 cells/mm. The percentage of postoperative cell loss was 21.25% ± 2.8% at 1 week, 24.26% ± 1.8% at 1 month, and 21.05% ± 3.2% at 3 months. The difference in cell count from the preoperative value was significant at all time points (P < 0.02). There were no adverse drug effects and no serious operative complications. CONCLUSIONS: A 5-minute application of MMC 0.02% to the bare sclera during pterygium surgery has an immediate and significant effect on endothelial cell density, which remains stable for up to 90 days. Furthermore, longer-term studies are needed of different concentrations and durations of the drug and of procedures wherein MMC is applied before excision of the pterygium head. © 2008 by Lippincott Williams & Wilkins.
Keywords: balanced salt solution; carbon tetrachloride; chloramphenicol; mitomycin; polymyxin B; prednisolone acetate; absence of side effects; article; cell count; cell density; cell loss; clinical article; cornea endothelium; drug effect; endothelium cell; excision; eye pain; female; foreign body reaction; human; keratitis; lacrimation; lavage; male; outcome assessment; photophobia; priority journal; pterygium; sclera; sex ratio; specular microscopy; surgical sponge; tertiary health care; treatment duration; phenixin

Managing the prevention of retained surgical instrument: What is the value of counting? - Cole, P.; Hollier, L. (Journal of Craniofacial Surgery, 2008)
Keywords: foreign body; health care cost; health care system; human; medical practice; note; priority journal; surgical approach; surgical technique

Beyond counting: Current evidence on the problem of retaining foreign bodies in surgery? - Cole, P.; Hollier, L. (Journal of Craniofacial Surgery, 2008)
Keywords: clinical practice; foreign body; morbidity; needle; note; priority journal; surgery; surgical equipment

Bar-coding surgical sponges to improve safety: A randomized controlled trial - Greenberg, C.C.; Diaz-Flores, R.; Lipsitz, S.R.; Regenbogen, S.E.; Mulholland, L.; Mearn, F.; Rao, S.; Toidze, T.; Gawande, A.A. (Annals of Surgery, 2008)
OBJECTIVE: A randomized, controlled trial was performed to evaluate a computer-assisted method for counting sponges using a bar-code system. BACKGROUND: Retained sponges are a rare and preventable problem but persist in surgery despite standardized protocols for counting. Technology that improves detection of counting errors could reduce risk to surgical patients. METHODS: We performed a randomized controlled trial comparing a bar-coded sponge system with a traditional counting protocol in 300 general surgery operations. Observers monitored sponge and instrument counts and recorded all incidents of miscounted or misplaced sponges. Surgeons and operating room staff completed postoperative and end-of-study surveys evaluating the bar-code system. RESULTS: The bar-code system detected significantly more counting discrepancies than the traditional protocol (32 vs.13 discrepancies, P = 0.007). These discrepancies involved both misplaced sponges (21 vs. 12 sponges, P = 0.17) and miscounted sponges (11 vs. 1 sponge, P = 0.007). The system introduced new technical difficulties (2.04 per 1000 sponges) and increased the time spent counting sponges (5.3 vs. 2.4 minutes, P < 0.0001). In postoperative surveys, there was no difference in surgical teams' confidence that all sponges were accounted for, but they rated the counting process and team performance lower in operations randomized to the bar-code arm. By the end of the study, however, most providers found the system easy to use, felt confident in its ability to track sponges, and reported a positive effect on the counting process. CONCLUSIONS: Use of automated counting using bar-coded surgical sponges improved detection of miscounted and misplaced sponges and was well tolerated by surgical staff members. © 2008 Lippincott Williams & Wilkins, Inc.
Keywords: NCT00282750; adult; analytical error; article; automation; bar code system; clinical protocol; clinical trial; coding; comparative study; computer system; controlled clinical trial; controlled study; female; general surgery; health survey; human; incidence; male; measurement; operating room personnel; patient safety; postoperative care; postoperative period; priority journal; randomization; randomized controlled trial; risk reduction; standard; surgical patient; surgical sponge; surgical technology; technical aid

Intra luminal gossypiboma - Agarwal, A.Kr.; Bhattacharya, N.; Mukherjee, R.; Akash Bora, A. (Pakistan Journal of Medical Sciences, 2008)
Intraluminal gossypiboma is a serious but avoidable complication during surgery which can be averted. The whole surgical team has to be vigilant especially during the closure of surgery, the time when fatigue makes every one a bit careless which can be costly both for the surgeon and increases the morbidity and mortality of the patient. Simple precautions like gauze pieces counting and tagging the gauze pieces with markers can prevent this.
Keywords: abdominal radiography; adult; article; case report; cholecystectomy; female; gauze dressing; gossypiboma; human; intestine obstruction; laparotomy; postoperative complication; surgical technique

Acute abdomen: peritonitis - Skipworth, R.J.E.; Fearon, K.C.H. (Surgery, 2008)
Peritonitis is inflammation of the peritoneum and represents an important cause of surgical morbidity and mortality. It may be localized or generalized, and is thought to pass through three phases: firstly, a phase of rapid removal of contaminants from the peritoneal cavity into the systemic circulation; secondly, a phase of synergistic interactions between aerobes and anaerobes; and thirdly, an attempt by host defences to localize infection. Peritonitis is commonly caused by bacteria, but can be chemical (aseptic), biliary, tuberculous, chlamydial, drug-induced or induced by other, rarer causes. Bacterial peritonitis is subclassified into primary or secondary on the basis of whether or not the integrity of the gastrointestinal tract has been compromised. Typically, the patient with peritonitis complains of severe abdominal pain and may exhibit the characteristic Hippocratic facies. Abdominal palpation demonstrates tenderness, guarding and rebound tenderness. Initial laboratory investigations should include urea and electrolytes, full blood count and blood gases. An erect radiograph of the chest demonstrates pneumoperitoneum in about 70-80% of visceral perforations. CT often plays a role in confirming specific diagnoses (e.g. subphrenic abscess). Immediate management should include fluid resuscitation, high-flow oxygen, appropriate antibiotics (i.v.) and analgesia. Definitive management is surgical except for a small group of patients in whom conservative management with fluids (i.v.) and antibiotics (i.v.) is indicated. Surgical management can be via a laparotomy or, in some conditions, laparoscopy. Control of the primary site of sepsis is the main determinant of outcome. Most patients recover quickly. However, major generalized peritonitis is associated with organ dysfunction/failure, and mortality can up to 20-40% in the UK. © 2008 Elsevier Ltd. All rights reserved.
Keywords: amylase; antibiotic agent; antiemetic agent; antifungal agent; antineoplastic agent; cephalosporin; electrolyte; isoniazid; meropenem; metronidazole; opiate; oxygen; piperacillin plus tazobactam; practolol; urea; abdominal abscess; abdominal drainage; abdominal pain; abdominal tenderness; acute abdomen; adhesion; amebiasis; amylase blood level; analgesia; antibiotic therapy; aspiration; aspiration pneumonia; bacterial peritonitis; biliary peritonitis; blood cell count; blood gas analysis; chlamydiasis; clinical feature; computer assisted tomography; conservative treatment; differential diagnosis; disease classification; disease severity; drug withdrawal; emergency surgery; familial Mediterranean fever; fluid resuscitation; foreign body; human; hyperlipidemia; intensive care; laboratory test; laparoscopic surgery; laparotomy; lead poisoning; liver function test; nasogastric tube; oxygen therapy; pancreas juice; pathogenesis; pathophysiology; patient positioning; peritonitis; pneumoperitoneum; porphyria; priority journal; prognosis; review; risk reduction; scoring system; sepsis; septic shock; Streptococcus pneumoniae; thorax radiography; treatment response; tuberculous peritonitis; urea blood level

Study examines counts, retained items. (OR manager, 2008)
Keywords: article; foreign body; health services research; human; medical error; methodology; operating room; perioperative period; safety; standard; surgical equipment; system analysis; United States

Counting difficulties: retained instruments, sponges, and needles. - Jackson, S.; Brady, S. (AORN journal, 2008)
Patients in whom a sponge or instruments is left after surgery may suffer complications including pain, infection, abscess, or intestinal obstruction. Consequences or retained items for surgical team members may include malpractice lawsuits and adverse actions from the National Practitioner Data Bank and state licensing board. Adherence to AORN recommended practices for counting and facility counting policies can protect both patients and practitioners.
Keywords: case report; foreign body; health care facility; human; legal aspect; medical error; organization and management; patient care; review; surgical equipment; surgical sponge; United States

Trauma: when there's no time to count. - Murdock, D. (AORN journal, 2008)
Trauma is the leading cause of death for people younger than age 45 in the United States. To help prevent death or disability, critically injured trauma patients must reach definitive care within the "golden hour."Often, the perioperative team has no more than 10 minutes to prepare the room before a patient who has suffered multiple, critical, traumatic injuries is rushed into the OR. For the trauma patient's safety, the perioperative team must be diligent and use creative measures to efficiently ensure that all surgical counts are completed. Foregoing surgical counts places the trauma patient at an increased risk for unintentionally retained foreign objects.
Keywords: abdominal injury; adolescent; case report; female; foreign body; human; medical error; multiple trauma; nursing; organization and management; patient care; perioperative nursing; review; surgical equipment; surgical sponge; time

Managing the prevention of retained surgical instruments: What is the value of counting? - Egorova, N.N.; Moskowitz, A.; Gelijns, A.; Weinberg, A.; Curty, J.; Rabin-Fastman, B.; Kaplan, H.; Cooper, M.; Fowler, D.; Emond, J.C.; Greco, G. (Annals of Surgery, 2008)
OBJECTIVE: Preventing retained foreign bodies is critical for patient safety. However, the value of counting surgical instruments and the reliability of the information provided have never been quantified. This study examines the diagnostic characteristics of counting and its impact on surgical costs. METHODS: We examined data from the Medical Event Reporting System-Total HealthSystem (MERS-TH), administrative hospital, and the New York State Cardiac Surgery Report databases (2000-2004). The cost per count discrepancy was examined by studying a cohort of patients undergoing coronary artery bypass graft (CABG) surgery. Linear and logistic multivariable regression models were used for statistical analysis. RESULTS: Of 153,263 operations, there were 1062 count discrepancies. The rate of retained items was 1 of 7000 surgeries or 1 of 70 discrepancy cases. Final count discrepancies identified 77% and prevented 54% of retained items. The sensitivity of counting was 77.2%, specificity was 99.2%, but the positive predictive value was only 1.6%. Count discrepancies increased with surgery duration, late time procedures, and number of nursing teams. Bypass time, intravenous nitroglycerin injections, or myocardial infarction in the previous 24 hours were independent predictors of count discrepancies in CABG surgery. The incremental OR cost for CABG because of a count discrepancy was $932. Nationally, this would amount to an additional $24 million/yr in OR CABG cost. CONCLUSIONS: This study, for the first time, quantifies the diagnostic accuracy of counting and defines the parameters against which alternative strategies of prevention should be measured, before being adopted in standard practice. © 2008 Lippincott Williams & Wilkins, Inc.
Keywords: article; coronary artery bypass graft; foreign body; health care cost; heart infarction; human; linear regression analysis; logistic regression analysis; operation duration; patient safety; priority journal; sensitivity and specificity; surgical equipment

Beyond counting: Current evidence on the problem of retaining foreign bodies in surgery? - Greenberg, C.C.; Gawande, A.A. (Annals of Surgery, 2008)
Keywords: cost benefit analysis; editorial; evidence based medicine; foreign body; human; incidence; malpractice; manual counting; needle; operating room; postoperative complication; primary prevention; priority journal; radiodiagnosis; sensitivity and specificity; surgical equipment; surgical sponge; procedures

Impact of different texture of polypropylene mesh on the inflammatory response - Di Vita, G.; Patti, R.; Sparacello, M.; Balistreri, C.R.; Candore, G.; Caruso, C. (International Journal of Immunopathology and Pharmacology, 2008)
Over the past decade, hernia surgery has undergone a considerable transformation with the use of prosthetic materials. The most used polypropylene meshes induce a rapid acute inflammatory response followed by chronic foreign body reaction. Many factors influence this response such as density, size, physical characteristics, different texture and porosity of each biomaterial. The aim of this study is to assess whether the implant of monofilament or multifilament meshes, in the inguinal hernioplasty, determine a different inflammatory response. Thirty-two male patients were included in the study and were randomly divided into two groups. In the first group (MO) inguinal hernioplasty was performed using monofilament polypropylene mesh, while in the second one (MU) multifilament prosthesis was used. Peripheral venous blood samples were collected 24 hours before surgery and then 6, 24, 48 and 168 hours posto-peratively. Modifications in leukocyte count, C-reactive protein (CRP), alpha-1 antitrypsin (α1-AT), interleukin (IL)-1, IL-6, IL-1 ra and IL-10 serum levels were recorded at all sampling times. We present evidence that serum levels of CRP, (α1-AT), leukocytes and cytokines were significantly increased post-operatively in both groups, returning to basal values 168 hours afterwards. In particular, the production of all pro-inflammatory mediators was higher in the MU group, whereas the anti-inflammatory cytokine (IL-10, IL-1ra) production was higher in MO patients. Our results indicate that polypropylene multifilament mesh allows a higher intense acute inflammatory response as compared to monofilament mesh implantation. Copyright © by Biolife, s.a.s.
Keywords: alpha 1 antitrypsin; C reactive protein; interleukin 1; interleukin 1 receptor accessory protein; interleukin 10; interleukin 6; polypropylene; adult; article; clinical article; controlled study; hernioplasty; human; inflammation; inguinal hernia; leukocyte count; male; priority journal; prosthesis; venous blood

Complications of AlphaCor keratoprosthesis: A clinicopathologic report - Chalam, K.V.; Chokshi, A.; Agarwal, S.; Edward, D.P. (Cornea, 2007)
PURPOSE: To describe the clinical and histopathologic features of intractable secondary glaucoma induced by AlphaCor keratoprosthesis. METHODS: An elderly woman with pseudoexfoliation glaucoma and pseudophakic bullous keratopathy in the right eye had graft failures after penetrating keratoplasty. Her best-corrected visual acuity at presentation was counting fingers in the right eye and 20/30 in the left eye. Examination showed severe corneal neovascularization. Chirila keratoprosthesis type II was implanted in 2 stages. Ten months later, the patient developed dense retrocorneal membrane, 360° occlusion of angles, intractable glaucoma, no light perception, and nasal stromal melting associated with partial extrusion of the keratoprosthesis. RESULTS: Histopathology revealed invasion of the porous material of the keratoprosthesis by reactive fibroblasts and multinucleated foreign-body giant cells. In the area of dehiscence, we noted thinning and lysis of the collagen fibers, infiltration of lymphocytes, and plasma cells with a sheet of fibroinflammatory tissue extending into the anterior chamber. CONCLUSIONS: Corneal stromal melting and retrocorneal prosthetic membrane formation after AlphaCor keratoprosthesis implantation led to intractable glaucoma and extrusion of the implant. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: aged; anterior eye chamber; article; case report; cornea neovascularization; cornea stroma; Descemet membrane; female; glaucoma; graft failure; histopathology; human; human tissue; keratopathy; keratoprosthesis; penetrating keratoplasty; priority journal; pseudoexfoliation; visual acuity; Chirila Kpro

Retained foreign bodies after emergent trauma surgery: Incidence after 2526 cavitary explorations - Teixeira, P.G.R.; Inaba, K.; Salim, A.; Brown, C.; Rhee, P.; Browder, T.; Belzberg, H.; Demetriades, D. (American Surgeon, 2007)
Trauma patients are thought to be at high risk for iatrogenic retained foreign bodies (RFBs). The objective of this study was to evaluate this incidence. All cases of RFB after cavitary trauma surgery were identified by review of Morbidity and Mortality reports at a Level 1 trauma center from January 1998 to December 2005 and confirmed by the Octagon Risk Management System. Over 8 years, 10,053 trauma operations were performed (2075 laparotomies, 377 thoracotomies, and 74 sternotomies). Three cases (0.1%) of RFB (all sponges) occurred during one single-stage and two damage control laparotomies. The counts were correct before definitive closure in two of three cases. No postoperative x-rays were obtained in any of the cases. RFB diagnosis occurred between days 3 and 9, one on a routine chest x-ray and the other two on abdominal computed tomography scans during a septic workup. Four-month to 8-year follow up documented one pleural effusion and one abscess resulting from the RFB. Iatrogenic RFBs after emergent cavitary trauma surgery occur at a rate of 0.12 per cent and are associated with significant morbidity. In addition to standard preventive strategies, in emergent cases with risk factors such as requiring damage control, before final cavity closure, even with a correct sponge count, radiographic evaluation is warranted.
Keywords: adolescent; adult; article; computer assisted tomography; emergency surgery; foreign body; human; incidence; laparotomy; major clinical study; morbidity; mortality; pleura effusion; retained foreign body; sternotomy; thoracotomy; traumatology; X ray analysis

Surgical sponge counting system earns food and drug administration clearance - Sempeles, S. (Journal of Clinical Engineering, 2007)
Keywords: accuracy; Food and Drug Administration; foreign body; gossypiboma; health care cost; health economics; human; malpractice; medical error; note; nurse; patent; radiofrequency; radiography; surgeon; surgical equipment; surgical sponge; surgical sponge counting system; surgical technique; SmartSponge

A retained surgical sponge presenting as chronic pelvic pain - Nieves, L.; Schnatz, P.F.; Sahakyan, M.; Sorosky, J.I. (Connecticut Medicine, 2007)
Background: Gossypiboma, the term for a retained sponge, is an underestimated occurrence related to gynecologic surgery. The postoperative presentation can be acute or subacute with symptoms that include pelvic pain. Case: A 39-year-old G7P3043 female presented with chronic pelvic pain. Her only past surgeries were 16 and 21 years prior. After failing to respond to conservative options, she was taken to the operating room for a hysterectomy and possible salpingoophorectomy. During the surgery, a retained sponge was found and removed. Postoperatively, the pain resolved completely. Conclusion: Although gossypiboma is an uncommon cause of chronic pelvic pain, patients can present years later with minimal complications other than discomfort. Accurate sponge and instrument counts, along with radiologic evaluation when a discrepancy is found, can be helpful. Newer technologies are also being developed to help avoid this complication.
Keywords: adult; article; case report; chronic disease; female; foreign body; human; pathology; pelvis pain syndrome; peritoneum; surgical sponge; treatment outcome

Radio frequency identification (RFID) applied to surgical sponges - Rogers, A.; Jones, E.; Oleynikov, D. (Surgical Endoscopy and Other Interventional Techniques, 2007)
Use of gauze sponges that have been embedded with passive radio frequency identification (RFID) tags presents a high probability of reducing or eliminating instances of gossypiboma, or retained surgical sponge. The use of human counts during surgical operations, especially during instances where unexpected or emergency events occur, can result in errors where surgical instruments, most often gauze sponges, are retained within the patient's body, leading to complications at a later date. Implementation of an automatic inventory record system, for instance, RFID, may greatly reduce these incidences by removing the human factor and would improve patient safety by eliminating the current sponge count protocol. Experiments performed by placing RFID-labeled sponges within an animal and removing them have demonstrated that tags are at least partially readable inside the body cavity and fully readable once removed, suggesting the possibility of an automated sponge count system pending further development of this technology. © 2007 Springer Science+Business Media, LLC.
Keywords: article; biosafety; clinical audit; medical record; priority journal; radiofrequency; retained instrument; risk reduction; surgical risk; surgical sponge

An Evaluation of a Numbered Surgical Sponge Product - Pelter, M.M.; Stephens, K.E.; Loranger, D. (AORN Journal, 2007)
• SURGICAL SPONGE COUNTING is an essential patient safety measure in the OR in which all members of the surgical team must participate. The RN acting as circulator is responsible for accurately documenting sponge counts during the surgical procedure. • A SEQUENTIALLY NUMBERED sponge product was evaluated in a survey of OR personnel to determine ease of use and whether the product affected the flow of the surgical procedure. • SURVEY RESPONDENTS reported that the numbered sponge product was easy to use and did not lengthen or affect the flow of the surgical procedure. Respondents also indicated that the product may contribute to patient safety. AORN J 85 (May 2007) 931-940. © AORN, Inc, 2007. © 2007 AORN, Inc.
Keywords: article; evaluation study; foreign body; human; methodology; operating room; operating room personnel; safety; standard; statistics; surgical sponge

Retained Foreign Bodies After Surgery - Lincourt, A.E.; Harrell, A.; Cristiano, J.; Sechrist, C.; Kercher, K.; Heniford, B.T. (Journal of Surgical Research, 2007)
Background: Medical errors during surgery are not well studied. To define risk factors associated with this type of error, we performed a case control analysis. Methods: We retrospectively reviewed medical records involving the ICD-9 code (998.4) for unintentional foreign object remaining in the body during surgery and incident reports gathered by the Department of Risk Management over a 10 year period from 1996 to 2005. Thirty cases were matched with at least four randomly selected controls (131 control patients) that underwent the same type of operation during the same time period. Results: Thirty patients had retained foreign objects (52% sponges and 43% instruments). The abdominal cavity was most commonly involved (46%) followed by the thoracic cavity (23%) although no body cavity remained uninvolved. Eight patients required readmission (30%), 25 patients required reoperation (83%), and there was no mortality. When compared with controls, patients with retained foreign objects were more likely to have had a greater number of major surgical procedures at the same time (2.7 versus 1.8, P = 0.004), to have multiple surgical teams (13% versus 2%, P = 0.02), and more likely to have had an incorrect instrument/sponge count recorded (13% versus 2%, P = 0.01). In multivariate analysis, factors associated with a significantly higher risk of retained foreign objects were the total number of major procedures performed [odds ratio 1.6; 95% confidence interval (CI), 1.1-2.3; P = 0.008] and an incorrect count (odds ratio 16.2; 95% CI, 1.3-197.8; P = 0.02). Conclusion: Retained foreign objects after surgery are associated with multiple major surgical procedures being performed at the same time and an incorrect instrument or sponge count. Identification of these risk factors using case-control analysis should influence operating room policy and reduce these types of errors. © 2007 Elsevier Inc. All rights reserved.
Keywords: abdominal abscess; adult; article; case control study; confidence interval; controlled study; female; foreign body; hospital admission; human; devices; International Classification of Diseases; intestine obstruction; major clinical study; male; medical record; multivariate analysis; outcome assessment; peritoneal cavity; priority journal; reoperation; retained instrument; retrospective study; risk assessment; risk factor; risk management; sepsis; small intestine perforation; surgical approach; surgical error; surgical patient; surgical risk; thoracic cavity

An unusual abdominal mass: case report. - Saidi, H.; Mohammed, U.; Machoki, M. (East African medical journal, 2007)
The causes of intra-abdominal masses associated with chronic abdominal pain range from the benign to malignant; common to bizarre and some raise major medical-legal issues. We present a case of a 40-year old African lady who presented with chronic right-sided abdominal pain with an associated mass on the right mid-abdomen. She had had a Caesarian section one year prior to presentation. Antecedent history of surgery and typical imaging features enabled a preoperative diagnosis of abdominal mass secondary to retained surgical gauze. The case illustrates the fallibility of the men and women in the operating theatres and the vital role of correct instrument and sponge counts.
Keywords: abdominal pain; abdominal tumor; adult; article; case report; cesarean section; chronic disease; female; foreign body; human; laparotomy; pathology; surgical sponge

Correlation of clinical outcome of integra application with microbiologic and pathological biopsies - Muangman, P.; Deubner, H.; Honari, S.; Heimbach, D.M.; Engrav, L.H.; Klein, M.B.; Gibran, N.S. (Journal of Trauma - Injury, Infection and Critical Care, 2006)
BACKGROUND: Integra, a dermal replacement template consisting of bovine collagen, chondroitin-6-sulfate, and a silastic sheet is a postexcisional treatment for deep partial to full thickness burns where autograft is limited. This study correlates Integra histology and quantitative microbiology cultures with clinical outcomes after autografting. METHODS: Charts of 29 burn patients who underwent Integra treatment and neodermis biopsy at the time of ultra thin autografting were reviewed. We analyzed microbial contamination, inflammatory reaction, and autograft take. RESULTS: The mean burn size and age were 43% total body surface area and 39 years old, respectively. In quantitative neodermis cultures, 90% of samples had bacterial growth; nine samples (31%) had >10 colony forming units per gram. The most common organism was Staphylococcus aureus (31%). Patients with quantitative bacterial counts >10 CFU/g received targeted systemic antibiotics. Integra take (83%) and autograft take (92%) were acceptable even in patients with high bacterial counts (78% Integra take; 86% autograft take). More than 50% of biopsies had dermal regeneration similar to normal dermis; foreign body reactions were unusual. Histologic evidence of inflammation, especially polymorphonuclear cells, was increased in biopsies with high bacterial counts. CONCLUSION: Integra and autograft take can be acceptable even with high bacterial counts if wounds are treated with appropriate targeted topical and systemic antibiotics in the presence of microbial contamination. Neodermis biopsies showed fibrous in-growth congruent with existing Integra fibers with minimal foreign body reaction. These data support Integra use as a safe and effective treatment modality in patients with major burns. © 2006 Lippincott Williams & Wilkins, Inc.
Keywords: antibiotic agent; animal cell; article; artificial skin; bacterial count; bacterial growth; bacterial infection; bacterium culture; body surface; burn; colony forming unit; controlled study; foreign body reaction; histology; human; human tissue; inflammation; microbial contamination; nonhuman; polymorphonuclear cell; postoperative care; postoperative infection; priority journal; skin autograft; skin biopsy

RFID tags help alert surgeons to problems. (Healthcare benchmarks and quality improvement, 2006)
Estimates say 1,500 objects are left inside patients after surgery each year in the United States; two-thirds are sponges. A handheld wand scanning device successfully detects sponges in seconds. The author recommends conducting an initial count prior to surgical incision, a second count at the beginning of wound closure, and a third count before the skin is closed.
Keywords: article; hospital department; human; medical error; methodology; physician; radiofrequency radiation; safety; surgical sponge; United States

Governing the surgical count through communication interactions: Implications for patient safety - Riley, R.; Manias, E.; Polglase, A. (Quality and Safety in Health Care, 2006)
Background: Intermittently, the incidence of retained surgical items after surgery is reported in the healthcare literature, usually in the form of case studies. It is commonly recognised that poor communication practices influence surgical outcomes. Aim: To explore the power relationships in the communication between nurses and surgeons that affect the conduct of the surgical count. Methods: A qualitative, ethnographic study was undertaken. Data were collected in three operating room departments in metropolitan Melbourne, Australia. 11 operating room nurses who worked as anaesthetic, instrument and circulating nurses were individually observed during their interactions with surgeons, anaesthetists, other nurses and patients. Data were generated through 230 h of participant observation, 11 individual and 4 group interviews, and the keeping of a diary by the first author. A deconstructive analysis was undertaken. Results: Results are discussed in terms of the discursive practices in which clinicians engaged to govern and control the surgical count. The three major issues presented in this paper are judging, coping with normalisation and establishing priorities. Conclusions: The findings highlight the power relationships between members of the surgical team and the complexity of striking a balance between organisational policy and professional judgement. Increasing professional accountability may help to deal with the issues of normalisation, whereas greater attention needs to be paid to issues of time management. More sophisticated technological solutions need to be considered to support manual counting techniques.
Keywords: article; controlled study; ethnography; health care; hospital policy; human; interpersonal communication; operating room; patient safety; physician; surgeon; surgical equipment; surgical technique

No difference in early cellular response of the pseudo-synovial membrane after total hip arthroplasty: Comparison of 3 combinations of bearing materials - Nygaard, M.; Elling, F.; Bastholm, L.; Søballe, K.; Borgwardt, A. (Acta Orthopaedica, 2006)
Background: Wear-resistant bearing materials may hypothetically reduce chronic inflammation in the pseudosynovial membrane as compared to less wear-resistant bearing materials such as polyethylene. We assessed the foreign body response in the pseudosynovial membrane in vivo after total hip replacement. Methods: 37 patients from a larger prospective randomized trial of 225 patients had biopsies taken arthroscopically from the artificial hip joint (i.e. the pseudosynovial membrane) 1 year after insertion of the implant. All patients had an identical hip prosthesis (Bimetric-RingLoc) except for the bearing materials, which consisted of polyethylene on zirconia, CoCr on CoCr, or alumina on alumina. Histological quantification was performed on 2-μm-thick semi-thin plastic sections or paraffin sections by point counting technique to compare the volume fraction of macrophages, granulomas and endothelial cells in biopsies of the pseudosynovial membrane. Results: The median macrophage volume fractions for polyethylene-on-zirconia bearing material (n = 15), CoCr-on-CoCr (n = 9), and alumina-on-alumina (n = 11) were 0.02, 0.04, and 0.004, respectively. The median granuloma volume fractions for polyethylene-on-zirconia (n = 13), CoCr-on-CoCr (n = 9), and alumina-on-alumina (n = 13) were 0.02, 0.04, and 0.02, respectively. The median endothelial cell volume fractions for polyethylene-on-zirconia (n = 15), CoCr-on-CoCr (n = 9), and alumina-on-alumina (n = 11) were 0.03, 0.02, and 0.05, respectively. Statistical analysis showed no significant differences between the three groups with the different bearings with respect to volume fraction of macrophages, granulomas and endothelial cells. Interpretation: Our study demonstrated that a granulomatous inflammation is a common finding in non-loose implants as early as 1 year after the operation not demonstrating a difference in macrophages and granuloma formation with the various bearing materials. Thus a high volume fraction of macrophages was found in the osteoarthritis control group compared to the operated group. Copyright© Taylor & Francis 2006.
Keywords: aluminum oxide; chromium derivative; cobalt derivative; polyethylene; zirconium oxide; article; clinical article; clinical trial; controlled clinical trial; controlled study; endothelium cell; foreign body reaction; granuloma; granulomatous inflammation; human; human tissue; inflammation; macrophage; osteoarthritis; randomized controlled trial; synovium; total hip prosthesis; Bimetric-RingLoc; Ti-alloy; Universal RingLoc

Perioperative patient safety: a multisite qualitative analysis. - Chappy, S. (AORN journal, 2006)
This study was undertaken to identify specific events that affected patient safety in perioperative service areas during a three-year period. The three most common types o reported incidents were incorrect counts, equipment malfunction, and medication errors. Data revealed significant disparities between health care facilities regarding what types of incidents were reported. Standardized language and rporting mechanisms would aid in the consistency and validity of current incident reporting and could help to improve perioperative patient safety.
Keywords: article; clinical trial; devices; foreign body; human; medical error; multicenter study; safety; standard; statistics; surgery; surgical equipment; United States

Perforation of the gastrointestinal tract secondary to ingestion of foreign bodies - Goh, B.K.P.; Chow, P.K.H.; Quah, H.-M.; Ong, H.-S.; Eu, K.-W.; Ooi, L.L.P.J.; Wong, W.-K. (World Journal of Surgery, 2006)
Introduction: Ingesting a foreign body (FB) is not an uncommon occurrence. Most pass through the gastrointestinal (GI) tract uneventfully, and perforation is rare. The aim of this study was to report our experience with ingested FB perforations of the GI tract treated surgically at our institution. Methods: A total of 62 consecutive patients who underwent surgery for an ingested FB perforation of the GI tract between 1990 and 2005 were retrospectively reviewed. Three patients with no definite FB demonstrated intraoperatively were included. Results: The patients had a median age of 58 years, and 37 (60%) were male. Of the 59 FBs recovered, 55 (93%) were toothpicks and dietary FBs such as fish bones or bone fragments. A definitive preoperative history of FB ingestion was obtained for only two patients, and 36 of 52 patients (69%) wore dentures. Altogether, 18 (29%) perforations occurred in the anus or distal rectum, and 44 perforations were intraabdominal, with the most common abdominal site being the distal ileum (39%). Patients with FB perforations in the stomach, duodenum, and large intestine were significantly more likely to be afebrile (P = 0.043), to have chronic symptoms (> 3 days) (P < 0.001), to have a normal total white blood cell count (P < 0.001), and to be asymptomatic or present with an abdominal mass or abscess (P < 0.001) compared to those with FB perforations in the jejunum and ileum. Conclusions: Ingested FB perforation in the adult population is most commonly secondary to unconscious accidental ingestion and is frequently caused by dietary FBs especially fish bones. A preoperative history of FB ingestion is thus rarely obtained, although wearing dentures is a common risk factor. FB perforations of the stomach, duodenum, and large intestine tend to present with a longer, more innocuous clinical picture than perforations in the jejunum or ileum. © 2006 by the Société Internationale de Chirurgie.
Keywords: abdominal abscess; abdominal mass; adult; aged; article; clinical feature; controlled study; digestive system perforation; duodenum perforation; female; foreign body; human; large intestine perforation; leukocyte count; major clinical study; male; postoperative complication; rectum perforation; small intestine perforation; stomach perforation; treatment outcome

Ulcerated Gastrointestinal Stromal Tumor (GIST) with Ingested Bone Foreign Body Mimicking a Perforation with Abscess - Kriegshauser, J.S.; Hara, A.K. (Radiology Case Reports, 2006)
Gastrointestinal stromal tumors (GIST) have a variety of appearances and can present as an intraluminal, extraluminal, solid or ulcerated mass. We present an unusual case of a patient presenting with pain, elevated white count, and computed topography (CT) findings suggesting an abscess containing bone. CT guided drainage was performed, and resulted in bowel perforation, leading to surgical intervention and the diagnosis of an ulcerated gastrointestinal stromal tumor containing bone.
Keywords: abscess; adult; article; bone; case report; clinical article; female; foreign body; gastrointestinal stromal tumor; human; intestine perforation; male; pain; surgery; topography

Patient safety practices in the operating room: Correct-site surgery and nothing left behind - Gibbs, V.C. (Surgical Clinics of North America, 2005)
Attention has turned to issues of surgical patient safety. Essential patient safety practices in the operating room include the application of standard processes of care, the use of protocols and checklists to reduce reliance on memory, the employment of simpler processes as much as possible, the alleviation of conditions that predispose to human error (eg, interruptions, fear, anger, time pressure, anxiety), and the design and use of error-proof devices coupled with frequent training in the use of these devices. These practices can be applied to two issues in surgical patient safety: assurance of correct site surgery and prevention of incidents involving retained foreign bodies. Both of these safety problems involve poor communication between perioperative care personnel and faulty processes of care. Recommendations to ensure that the correct procedure is performed on the correct patient at the correct site have been mandated by the JACHO Universal Protocol. The protocol mandates using a preoperative verification process, marking the operative site, and taking a "time out" immediately before starting the procedure. All health care facilities where invasive procedures that expose patients to harm are performed are required to comply with this protocol. Recommendations to prevent the retention of sponges, sharps, instruments, and other miscellaneous items include consistent application and adherence to standardized counting procedures, performance of a methodical wound exploration before closure of the surgical site, use of radiograph-detectable items in the surgical wound, maintenance of an optimal operating room environment to allow focused performance of operative tasks, and application of radiographs or other technology as indicated to ensure there is no item left by mistake in the operative field. All perioperative care personnel can work together to ensure that these events never happen. Getting to zero is possible.
Keywords: accreditation; foreign body; general surgery; human; medical error; medical device; medical practice; medical record; neurosurgery; operating room; orthopedic surgery; patient care; policy; priority journal; quality control; review; risk assessment; standardization; surgical technique; urologic surgery

Complete intraluminal migration of a retained surgical lap sponge 4 years after appendicectomy: A case report - Moosavi Naeeni, S.M.; Panahi, F.; Assari, S. (European Surgery - Acta Chirurgica Austriaca, 2005)
Background: Retained foreign bodies after surgery constitute an occasional misadventure in modern surgery and cause returns to the operating room. Approximately, two-thirds of retained objects are sponges. Methods: We report on a 10-year-old boy presenting with a retained surgical sponge that had migrated completely into the lumen of the ileum. Removal was performed by laparotomy and ileotomy. Radiological and intraoperative findings are discussed, and a review of the recent relevant literature is provided. Results: Laparotomy revealed an intraluminal 30 cm long lap sponge (25 cm in the ileum and 5 cm in the cecum) which had completely migrated into the interior of the intestine. Complications, i.e., adhesion bands and fistulae, were treated subsequently. Conclusions: The case highlights the importance of a careful count of sponges before and after surgery and thorough exploration of all quadrants of the abdomen at the termination of surgical cases. © Springer-Verlag 2005.
Keywords: abdomen; adhesion; appendectomy; article; case report; cecum; fistula; foreign body; human; ileum; intestine; laparotomy; male; radiodiagnosis; school child

Palmar-plantar fibromatosis in children and preadolescents: A clinicopathologic study of 56 cases with newly recognized demographics and extended follow-up information - Fetsch, J.F.; Laskin, W.B.; Miettinen, M. (American Journal of Surgical Pathology, 2005)
Palmar-plantar fibromatosis, the most common type of fibromatosis, is well recognized in the adult population, but many clinicians and pathologists are unfamiliar with the fact that children may also be affected by this process. This report describes the clinicopathologic findings in 56 cases of palmar-plantar fibromatosis in children and preadolescents. Our study group included 19 males and 37 females, ranging from 2 to 12 years of age at the time of their first surgical procedure (median age, 9 years). The patients typically presented with solitary, lobular or multilobular masses in the 0.5- to 2.5-cm size range. The preoperative duration of the lesions ranged from 1 month to 6 years, with 1 patient purportedly having clinical evidence of disease since birth. All but two of the initial lesions occurred on the plantar aspect of the feet, typically in the region of the arch. Only 2 patients presented with palmar disease. The tumors were usually painless, except when pressure was applied. Seven patients had a history of trauma, sometimes involving a foreign body. One patient presented with concurrent disease involving both feet, and 12 additional patients subsequently developed palmar-plantar fibromatosis in another extremity, knuckle pads on the hands, or had other clinical findings linked to this disease. A family history was available for 25 patients, and 11 individuals had relatives with palmar-plantar fibromatosis, and 4 others had relatives with a history that was either suspicious for palmar-plantar disease or positive for other disorders associated with this disease. Histologically, the tumors involved aponeurosis and commonly formed discontinuous, moderately cellular, nodular masses composed of spindled cells with intervening collagen. Mitotic counts for 79 separately submitted tumor specimens ranged from 0 to 31 mitotic figures per 25 wide-field high power fields (mean mitotic count, 3.4 mitotic figures per 25 wide-field high power fields). Eight tumor had ≥ 10 mitoses per 25 wide-field high power fields. All patients were initially managed by local excision, and in most of cases, histologic examination showed tumor extending to the tissue edge. Thirty-two of 38 patients (84.2%) with clinical follow-up, ranging from 4 months to 33 years (mean, 14 years 9 months; median, 16 years 1 month), had one (n = 16) or more (n = 16) local recurrence of their fibromatosis. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: adolescent; aponeurosis; article; birth; child; clinical feature; clinodactyly; demography; Dupuytren contracture; epilepsy; excision; family history; female; fibromatosis; follow up; foot; foreign body; hand; histopathology; human; human tissue; infant; injury; keloid; major clinical study; male; mitosis; palmar plantar fibromatosis; preoperative evaluation; soft tissue tumor

Patient care. The right count. - Dalton, A. (Hospitals & health networks / AHA, 2005)
Keywords: article; foreign body; human; medical error; methodology; radiography; safety; standard; surgery; surgical equipment; surgical sponge; utilization review

Encapsulating peritonitis and familial Mediterranean fever - Dabak, R.; Uygur-Bayramiçli, O.; Aydin, D.K.; Dolapçioglu, C.; Gemici, C.; Erginel, T.; Turan, C.; Karadayi, N. (World Journal of Gastroenterology, 2005)
Aim: To investigate the relationship between encapsulating peritonitis and familial Mediterranean fever (FMF). Methods: The patient had a history of type 2 diabetes and laparoscopic cholecystectomy was performed one year ago for cholelithiasis. Eleven months after the operation she developed massive ascites. Biochemical evaluation revealed hyperglycemia, mild Fe deficiency anemia, hypoalbuminemia and a CA-125 level of 2 700 IU. Ascitic evaluation showed characteristics of exudation with a cell count of 580/mm3. Abdominal CT showed omental thickening and massive ascites. At exploratory laparotomy there was generalized thickening of the peritoneum and a laparoscopic clip encapsulated by fibrous tissue was found adherent to the uterus. Biopsies were negative for malignancy and a prophilactic total abdominal hysterectomy and bilateral salpingooophorectomy were performed. Results: The histopathological evaluation was compatible with chronic nonspecific findings and mild mesothelial proliferation and chronic inflammation at the uterine serosa and liver biopsy showed inactive cirrhosis. Conclusion: The patient was evaluated as sclerosing encapsulating peritonitis induced by the laparoscopic clip acting as a foreign body. Due to the fact that the patient had FMF the immune response was probably exaggerated. © 2005 The WJG Press and Elsevier Inc. All rights reserved.
Keywords: albumin; CA 125 antigen; colchicine; glucose; oral antidiabetic agent; prednisolone; abdominal hysterectomy; aged; article; ascites; ascites fluid analysis; bloating; case report; cell count; cell proliferation; chronic inflammation; comorbidity; computer assisted tomography; echography; encapsulation; familial Mediterranean fever; female; follow up; foreign body reaction; histopathology; human; hyperglycemia; hypoalbuminemia; iron deficiency; laparotomy; liver biopsy; liver cirrhosis; mesothelium cell; non insulin dependent diabetes mellitus; omentum; peritoneal biopsy; peritoneum exudate; salpingooophorectomy; peritoneal fibrosis; surgical equipment; symptomatology; treatment outcome; uterus

Complications of missile craniocerebral injuries during the Croatian Homeland War - Tudor, M.; Tudor, L.; Tudor, K.I. (Military Medicine, 2005)
Objective: Complications of penetrating craniocerebral injuries in war can be early (during the first week after wounding) or late (after that period). Postoperative hematomas, infections, seizures, and cerebrospinal fluid fistulas (CSFFs) are counted among the early complications, whereas foreign bodies migrating intracranially, seizures, infections, and posttraumatic hydrocephalus represent late complications. A total of 176 patients with well-defined head injuries from missiles, sustained during the Croatian Homeland War (1991-1995), developed a total of 61 (34.5%) complications. Methods: A retrospective statistical analysis of the medical records of the patients in our series was performed to determine the risk factors for the onset of complications, which have unfavorable effects on outcomes. Results: There were a total of 28 (15.9%) infections (deep or superficial), 21 (11.9%) cases of CSFFs, 9 (5.11%) cases of early epilepsy, and 3 cases of post-traumatic hydrocephalus. A total of 47.6% of patients with CSFFs developed intracranial infections. Of eight patients with meningoencephalitis, five had CSFFs and four had intracranially retained foreign bodies. Only one patient developed a cerebral abscess. Two patients died because of infectious complications (13.3%). Post-traumatic hydrocephalus (1.7%) required shunt placement. For 60% of patients with deep-seated intracranial infectious complications and 76% of patients with CSFFs, reoperations had to be performed, whereas this was the case for only 8% of patients without infections (χ2 = 43.6, p = 0.00001). Conclusions: Intracranially retained foreign bodies, wound age, wound site, and operations performed outside the neurosurgical services were the main risk factors for the development of complications. Complications themselves exerted a very unfavorable influence on outcomes. The development of complications reflects very reliably the neurosurgical technique applied.
Keywords: adult; article; brain infection; cerebrospinal fluid fistula; craniotomy; Croatia; female; head injury; hematoma; human; hydrocephalus; major clinical study; male; meningoencephalitis; missile wound; neurosurgery; postoperative complication; reoperation; retrospective study; seizure; statistical analysis; surgical technique; treatment outcome; war

Retained surgical sponges (gossypiboma) - Bani-Hani, K.E.; Gharaibeh, K.A.; Yaghan, R.J. (Asian Journal of Surgery, 2005)
OBJECTIVE: Retained surgical sponges are seldom reported due to medicolegal implications. Awareness of this problem among surgeons and radiologists is essential to avoid unnecessary morbidity. We present our experience with this entity and review the related literature. METHODS: The medical records of 11 patients who were diagnosed as having retained surgical sponges from 1990 to 2003 were reviewed. RESULTS: The incidence was 1:5,027 inpatient operations. There were four males and seven females with a median age of 45 years. The original operations were gynaecological (n = 4), general (n = 4), urological (n = 2) and laminectomy (n = 1). In seven cases, the original operation was performed on an emergency basis. Five patients were obese. A presumed correct sponge count was documented in eight cases. The median time between the original procedure and diagnosis of retained sponges was 12 months. The tentative diagnosis was intestinal obstruction (4 patients), urinary tract infection (1 patient), Crohn's disease (1 patient) and tumour recurrence (1 patient). The correct diagnosis was suggested in the remaining four patients. Surgical removal of the retained sponges was carried out in all cases except one, in which the patient passed the sponge spontaneously through the rectum. CONCLUSION: Retained sponges are more common in obese patients and after emergency surgery. A high degree of suspicion is important for preoperative diagnosis. Despite the use of radio-opaque sponges and thorough sponge counting, this moribund mishap still occurs. Although human errors cannot be completely abolished, continuous medical training and strict adherence to regulations should reduce the incidence to a minimum. © 2005 Elsevier. All rights reserved.
Keywords: adult; barium enema; clinical article; computer assisted tomography; Crohn disease; differential diagnosis; emergency surgery; female; foreign body; general surgery; gossypiboma; gynecologic surgery; human; incidence; intestine obstruction; Jordan; laminectomy; male; medical record; obesity; preoperative evaluation; retained surgical sponge; review; surgical sponge; tumor recurrence; urinary tract infection; urologic surgery

Tuberculosis verrucosa cutis: Antitubercular therapy, a well-conceived diagnostic criterion - Sehgal, V.N.; Sardana, K.; Bajaj, P.; Bhattacharya, S.N. (International Journal of Dermatology, 2005)
A 39-year-old housewife sustained inadvertent trauma to the right index finger about 6 years ago, whilst stitching clothes. A couple of weeks later, the site of trauma became hard and gritty. Ever since, it has progressed slowly, without any appreciable outward sign. It was not associated with any discomfort /pain. Consequent on an opinion from a surgeon, it was decided to operate on the right index finger. During the operation, under local anesthesia, a hard and gritty material was removed. The material was subjected to histopathologic study. Several stitches were applied to the wound. It failed to respond to antimicrobial therapy over a 4-week period, prompting the patient to seek another opinion. Examination of the skin surface revealed a plaque with an irregular configuration on and around the distal interphalangeal joint of the right index finger. It was erythematous and pigmented. The top of the plaque was irregular and had alternating elevations and depressions (Fig. 1). Diascopy was negative for apple jelly nodule. A bacillus Calmette-Guérin (BCG) vaccination scar was identified on the left deltoid. There was no regional lymphadenopathy or systemic abnormality. Mantoux test with intradermal injection of 0.1 mL SPAN's tuberculin (purified protein derivative/5 tuberculin units/0.1 mL) (Span Diagnostic Ltd., Murat, India) was negative after 72 h. Investigations, including total and differential leukocyte count, erythrocyte sedimentation rate, serum biochemistry, and renal and liver function tests, were within the normal range, as was a chest X-ray. Hematoxylin and eosin-stained sections prepared from the biopsy taken from the lesion revealed noteworthy changes in the epidermis and the dermis. The former was marked by the presence of hyperkeratosis, acanthosis, and papillomatosis, whilst the latter contained tubercle granulomas. Each of the granulomas was well formed and consisted of large numbers of lymphocytes, histiocytes, and foreign body (Langerhans') giant cells (Fig. 2). Caseation necrosis and acid-fast bacilli could not be demonstrated. The preceding revelations were fairly conducive to the diagnosis. Accordingly, antitubercular therapy (ATT), comprising 450 mg of rifampicin, 300 mg of isonicotinic acid hydrazide, and 800 mg of ethambutol, was recommended for oral administration each day for 60 days. The outcome of the treatment was satisfactory, resulting in perceptible regression of the skin lesion (Fig. 1b). The patient was advised to continue the treatment for another 30 days, after which 450 mg of rifampicin and 300 mg of isonicotinic acid hydrazide were to be continued for another 6 months. © 2004 The International Society of Dermatology.
Keywords: antiinfective agent; BCG vaccine; eosin; ethambutol; hematoxylin; isoniazid; rifampicin; tuberculostatic agent; acanthosis; adult; article; BCG vaccination; case report; clinical feature; dermis; diagnostic procedure; disease course; epidermis; female; histopathology; human; human tissue; hyperkeratosis; papillomatosis; patient satisfaction; physical examination; skin biopsy; skin injury; skin tuberculosis; surgical technique; treatment outcome

Surgical counts can be risky business! - Porteous, J. (Canadian operating room nursing journal, 2004)
The surgical count plays a vital role in enabling perioperative nurses to provide a safe environment to surgical patients. Counting errors are preventable. Although national standards of care provide excellent guidelines for developing effective count protocols, counting procedures are often modified according to individual health care policy. This article will discuss the risk factors for retained items, rate of occurrence, what objects are being left in patients, role of x-rays and consequences of leaving an object in a patient. It will also highlight points to be considered when implementing new count policies.
Keywords: Canada; case report; foreign body; human; male; medical error; middle aged; nurse attitude; nursing; operating room; operating room personnel; organization and management; peroperative complication; policy; practice guideline; radiography; review; risk factor; safety; statistics; surgical sponge; United States

A proactive treatment approach for eyes with perforating injury - Kuhn, F.; Mester, V.; Morris, R. (Klinische Monatsblatter fur Augenheilkunde, 2004)
Background: Perforating injuries continue to have a poor prognosis with less than two-thirds of eyes having at least ambulatory final vision, due to proliferation originating from the exit wound. Materials and Methods: We developed a new, proactive treatment method, which is applicable in most eyes with perforating trauma. The strategy involves limited, indirect ophthalmoscopic vitrectomy during the primary repair; heavy topical corticosteroid therapy postoperatively; and complete vitrectomy on day 3, including prophylactic retinectomy around the exit wound, evacuation of subretinal blood, laser retinopexy, and silicone oil implantation. Results: In the five consecutive eyes in which the proactive treatment approach was used, no " enscarceration" of the retina into the exit wound, proliferative vitreoretinopathy, retinal detachment, or retinal folding has occurred. The median visual acuity improved from count fingers to 0.6 in the three eyes without macular involvement. Conclusions: Far-reaching conclusions must not be made based on such a small series, but the proactive treatment approach appears promising in preventing proliferation-related complications such as fractional retinal detachment or retinal fold development. A similar approach should be considered for eyes with deep impact trauma from intraocular foreign bodies and in eyes with incarcerated retina in the rupture wound.
Keywords: corticosteroid; adult; case report; foreign body; human; implantation; injury; laser; male; ophthalmoscopy; penetrating trauma; retina blood flow; retina detachment; retina macula lutea; review; visual acuity; vitrectomy; wound dehiscence

Uveal and capsular biocompatibility of a single-piece, sharp-edged hydrophilic acrylic intraocular lens with collagen (Collamer) 1-year results - Schild, G.; Amon, M.; Abela-Formanek, C.; Schauersberger, J.; Bartl, G.; Kruger, A. (Journal of Cataract and Refractive Surgery, 2004)
Purpose: To analyze uveal and capsular biocompatibility 1 year following implantation of a sharp-edged, hydrophilic, collagen-containing posterior chamber intraocular lens (IOL). Setting: Department of Ophthalmology, University of Vienna Medical School, Vienna, Austria. Method: In a prospective study, a Collamer CC4204BF IOL was implanted in 30 eyes of patients with senile cataract. A standardized surgical technique and postoperative regimen were applied. To assess uveal biocompatibility, cellular inflammation on the anterior IOL surface was evaluated with a specular microscope. Capsular biocompatibility was registered semiquantitatively with a biomicroscope, based on an assessment of fibrosis on the anterior and posterior capsules. Tyndall values were measured with the Kowa FC-1000 laser flare-cell meter. Decentration of the lens was also registered. Results: One year after implantation, the values of flare and cell count in the anterior chamber were lower than preoperatively. Round and spindle-shaped, epithelioid, and foreign-body giant cells were not found on the anterior surface of the IOL. The capsulorhexis rim was moderately fibrosed in 56.6% of cases. Fibrosis of the capsule over the optic was also moderate in 36.6%. The central portion of the posterior capsule was devoid of fibrosis in 43.3% and mildly fibrosed in 50%. Three lenses revealed outgrowth of lens epithelial cells to the anterior surface of the IOL. A neodymium:YAG capsulotomy had to be performed in 1 case. All lenses were well centered in the capsular bag 1 year after implantation. Conclusions: The absence of inflammatory cells on the anterior surface of the IOL indicates the high uveal biocompatibility of the lens. In terms of capsular biocompatibility, the results were satisfactory. © 2004 ASCRS and ESCRS.
Keywords: acrylic acid copolymer; collagen implant; anterior eye chamber; article; biocompatibility; capsulotomy; clinical article; controlled study; female; human; laser surgery; lens capsule; lens implant; long term care; male; neodymium laser; ocular fibrosis; phacoemulsification; posterior eye chamber; postoperative period; priority journal; senile cataract; specular microscopy; standard; surface property; surgical technique; treatment outcome; uvea

Migration of Polyethylene Particles Around Nonloosened Cemented Femoral Components from a Total Hip Arthroplasty - An Autopsy Study - Massin, P.; Chappard, D.; Flautre, B.; Hardouin, P. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2004)
Three cemented femoral components from total hip arthroplasties retrieved at autopsy were examined in regard to the migration of birefringent polyethylene particles across the fixation interfaces. They were obtained from two patients who died from unrelated causes. They had been in place, respectively, for 8 and 9 years (first patient) and for 9 years (second patient). Osteolysis was present in the acetabular side only. The femoral components were not loosened. Histologic sections were performed at four levels of the femoral components, and polyethylene particles were counted with the use of a semiautomatic image analyzer. Sections below the tip of the stem were treated by deorganification and the lysate was centrifuged in the attempt to isolate wear debris. Particles were found at both interfaces (bone-cement and metal-cement) and in the cancellous bone between the trabeculae. They were also present in the Haversian canals of the cortical bone. Particles of various sizes were found in the medullary canal beneath the tip of the stem. In scanning electron microscopy, they appeared to have irregular shapes. Wear debris can migrate across the cement-bone interface of nonloosened implants. They appear to progress through the porosity of the cancellous bone. © 2004 Wiley Periodicals, Inc.
Keywords: polyethylene; aged; article; autopsy; case report; female; femur; femoral neck fracture; foreign body; hip arthroplasty; hip prosthesis; histology; human; implant; osteolysis; scanning electron microscopy; total hip prosthesis

Debridement - Steed, D.L. (American Journal of Surgery, 2004)
Debridement is defined as the removal of nonviable material, foreign bodies, and poorly healing tissue from a wound. Although surgeons recognize the importance of debridement, few data have been generated in randomized trials to support its use. Debridement provides for removal of tissue with the highest bacterial count, reliable cultures, and identification of osteomyelitis. The most direct form of debridement is surgical excision. For patients who are poor candidates for surgical debridement or have limited access to a surgeon, other forms of debridement (including mechanical, autolytic, enzymatic, and biologic) can be used. Although operative debridement is best performed by those with surgical training, the other forms of debridement can be accomplished by other allied health care professionals. Debridement remains an important adjunct to good wound care, but questions of what type, how much, and how often it should be performed remain unresolved. © 2004 Excerpta Medica, Inc. All rights reserved.
Keywords: anesthetic agent; antibiotic agent; becaplermin; collagenase; corticosteroid; enzyme; fibrin; growth factor; hemostatic agent; oxidized cellulose; papain; platelet derived growth factor; sodium chloride; thrombin; transforming growth factor beta; urea; autolysis; bacterial count; bacterium culture; biology; bleeding; cauterization; debridement; excision; foreign body; health care cost; health care personnel; human; osteomyelitis; pain; priority journal; review; surgeon; surgical training; tissue necrosis; wound care; wound dressing; wound healing

Patterns of Microbiology in Intra-abdominal Packing for Trauma - Granchi, T.S.; Abikhaled, J.A.; Hirshberg, A.; Wall, M.J.; Mattox, K.L.; Fry, D.E.; Smathers, H.M.; Salomone, J.P.; Ivatury, R.R.; Feliciano, D.V.; Granchi, T. (Journal of Trauma - Injury, Infection and Critical Care, 2004)
Introduction: This study tracks the microbiology of packs and infections in damage-control trauma patients to determine whether the packs cause infections. Methods. The peritoneum and abdominal packs were cultured in patients who survived to re-operation. The study recorded all positive cultures, pack count, packing duration, number of operations, and infections. Results: Thirty-five patients were studied. Twenty-eight patients survived; seven died. Packs were cultured in 29 patients. Data for 291 cultures collected. Pack cultures were positive in 20 patients and negative in nine. Positive pack cultures grew skin and gut flora. Twenty-one patients had infections, 14 did not. Organisms from positive pack cultures did not contribute to subsequent infections or mortality. Microbes and sites of infections were consistent with SICU patients. Conclusions. Intra-abdominal packs are contaminated with skin and gut flora. These contaminants, however, do not contribute to subsequent infections. Pathogens from subsequent infections were typical for ICU infections.
Keywords: Acinetobacter; adolescent; adult; clinical article; conference paper; female; gauze pack; human; injury; intensive care unit; intestine flora; male; microbiological examination; mortality; priority journal; reoperation; Staphylococcus; surgical sponge; survival

Treatment of Pseudofolliculitis Barbae Using the Long-Pulse Nd:YAG Laser on Skin Types V and VI - Weaver III, S.M.; Sagaral, E.C. (Dermatologic Surgery, 2003)
BACKGROUND. Pseudofolliculitis barbae (PFB) is a foreign body inflammatory condition that is caused by in-grown hairs of the face and body. An effective treatment to alleviate this condition without the risk of side effects has yet to be found. OBJECTIVE. The objective of this study was to evaluate the Lyra 1064-nm long-pulse ND:YAG laser in the treatment of PFB on skin types V and VI. METHODS. Twenty subjects (12 males and 8 females) were given two treatments approximately 3 to 4 weeks apart and were assessed by objective papule/pustule and hair counts at 1, 2, and 3 months after final treatment. Laser treatments with the Lyra Nd:YAG laser were applied onto 2 × 2-cm regions on the upper and lower mandible and neck regions. Contralateral controls were used to assess overall effectiveness. Subjective evaluations were also obtained from both subjects and investigators. Assessments of any abnormal side effects caused by laser treatment, including dyspigmentation and/or scarring, were also evaluated. RESULTS. A reduction in the quantity of papules/pustules and hairs when compared with baseline data was statistically significant for treatment of PFB in the mandibular and neck regions at the 1-, 2-, and 3-month follow-up evaluations. Subject evaluations ranged from satisfied to very satisfied. Side effects included transient hyperpigmentation, transient hypopigmentation, mild erythema, and itching. CONCLUSIONS. The use of the 1064-nm long-pulse Nd:YAG laser for the treatment and management of PFB on skin types V and VI is both safe and effective, with positive results lasting for up for to 3 months after two treatments.
Keywords: article; clinical article; clinical trial; controlled clinical trial; controlled study; erythema; female; foreign body; hair growth; human; hyperpigmentation; hypopigmentation; inflammatory disease; laser surgery; male; neodymium laser; papule; pigment disorder; postoperative complication; priority journal; pruritus; pseudofolliculitis barbae; pustule; scar formation; surgical technique; treatment outcome

Transscleral fixation of a foldable intraocular lens in aphakic vitrectomized eyes - Ahn, J.K.; Yu, H.G.; Chung, H.; Wee, W.R.; Lee, J.-H. (Journal of Cataract and Refractive Surgery, 2003)
Purpose: To evaluate the clinical outcomes of transscleral fixation of a foldable intraocular lens (IOL) in eyes that had pars plana lensectomy combined with pars plana vitrectomy for severe vitreoretinal disease. Setting: Seoul National University Hospital, Seoul, Korea. Methods: The medical records of 21 patients who had a transscleral fixation of a foldable IOL after previous vitrectomy combined with lensectomy for severe posterior segment pathology were reviewed. The underlying vitreoretinal diseases were complicated proliferative diabetic retinopathy (n = 9), proliferative vitreoretinopathy (n = 5), traumatic retinal detachment (n = 3), intraocular foreign body (n = 2), and uveitic retinal detachment (n = 2). The postoperative best corrected visual acuity (BCVA) was compared with the preoperative BCVA. Autorefractometry and keratometry measurements and central endothelial cell counts were evaluated 1 day preoperatively and 6 months postoperatively. Results: The mean age of the patients was 54.5 years. The preoperative aphakic period ranged from 2 to 22 months. The visual acuity reached the preoperative BCVA by 2 months after surgery and was better than the preoperative BCVA at 6 months (P = .006) and at the final visit (P = .003). Six months postoperatively, the mean myopic shift by cycloplegic autorefractometry was -1.0 diopter (D) and the mean scalar shift in surgically induced keratometric cylinder, 1.0 D. The mean central corneal endothelial loss at 6 months was 6.7% (range 2.4% to 22.2%). The only vitreoretinal complications were a transient vitreous hemorrhage and a reopened macular hole that was reattached after fluid-gas exchange. Conclusion: Transscleral fixation of a foldable IOL was safe and led to favorable visual outcomes in aphakic vitrectomized eyes with previous severe vitreoretinal disease. © 2003 ASCRS and ESCRS.
Keywords: adult; aged; aphakia; article; ciliary disk; clinical article; controlled study; cornea endothelium; diabetes mellitus; diabetic retinopathy; disease severity; eye refraction; female; gas; human; intraocular foreign body; keratometry; Korea; lens implant; lensectomy; liquid; male; medical record; posterior eye chamber; postoperative period; preoperative evaluation; priority journal; retina detachment; retina macula hole; review; safety; sclera; treatment outcome; university hospital; vitreoretinopathy; vitreous hemorrhage

An unusual cause of small bowel obstruction: Gossypiboma - Case report - Gencosmanoglu, R.; Inceoglu, R. (BMC Surgery, 2003)
Background: The term "gossypiboma" denotes a mass of cotton that is retained in the body following surgery. Gossypiboma is a medico-legal problem especially for surgeons. To the best of our knowledge, the patient presented herein is the second reported patient in whom the exact site of migration of a retained surgical textile material into the intestinal lumen could be demonstrated by preoperative imaging studies. Case presentation: A 74-year-old woman presented with symptoms of small bowel obstruction due to incomplete intraluminal migration of a laparotomy towel 3 years after open cholecystectomy and umbilical hernia repair. Plain abdominal radiography did not show any sign of a radio-opaque marker in the abdomen. However, contrast enhanced abdominal computerized tomography revealed a round, well-defined soft-tissue mass with a dense, enhanced wall, containing an internal high-density area with air-bubbles in the mid-abdomen. A fistula between the abscess cavity containing the suspicious mass and gastrointestinal tract was identified by upper gastrointestinal series. The presence of a foreign body was considered. It was surgically removed with a partial small bowel resection followed by anastomosis. Conclusions: Although gossypiboma is rarely seen in daily clinical practice, it should be considered in the differential diagnosis of acute mechanical intestinal obstruction in patients who underwent laparotomy previously. The best approach in the prevention of this condition can be achieved by meticulous count of surgical materials in addition to thorough exploration of surgical site at the conclusion of operations and also by routine use of surgical textile materials impregnated with a radio-opaque marker.
Keywords: abdominal radiography; aged; article; case report; cholecystectomy; computer assisted tomography; digestive system fistula; end to end anastomosis; female; foreign body; gossypiboma; hernioplasty; human; laparotomy; small intestine obstruction; small intestine resection; textile; umbilical hernia

O.R. Left behind. Counting surgical instruments reduces medical errors. - Erickson, S. (Materials management in health care, 2003)
Keywords: article; foreign body; human; medical error; operating room personnel; organization and management; standard; surgical equipment; United States

Identifying lost surgical needles using radiographic techniques. - Macilquham, M.D.; Riley, R.G.; Grossberg, P. (AORN journal, 2003)
Many surgical procedures involve the use of very small surgical needles. In the event that a postoperative needle count is incorrect, traditionally an x-ray has been taken to find the needle. Little data exist to recommend the smallest surgical needle that can be identified with conventional radiographic techniques and the optimum technique for finding lost surgical needles. In this quality assurance project x-rays of various size surgical needles were taken. The smallest seen by the majority of observers was 17 mm. The radiographic technique of choice for optimum detection of lost surgical needles was imaging with a mobile image intensifier.
Keywords: abdomen; article; Australia; comparative study; foreign body; human; image quality; methodology; needle; radiography; randomization; surgical equipment; thorax; thorax radiography

Risk factors for retained instruments and sponges after surgery - Gawande, A.A.; Studdert, D.M.; Orav, E.J.; Brennan, T.A.; Zinner, M.J. (New England Journal of Medicine, 2003)
BACKGROUND: Risk factors for medical errors remain poorly understood. We performed a case-control study of retained foreign bodies in surgical patients in order to identify risk factors for this type of error. METHODS: We reviewed the medical records associated with all claims or incident reports of a retained surgical sponge or instrument filed between 1985 and 2001 with a large malpractice insurer representing one third of the physicians in Massachusetts. For each case, we identified an average of four randomly selected controls who underwent the same type of operation during the same six-month period. RESULTS: Our study included 54 patients with a total of 61 retained foreign bodies (of which 69 percent were sponges and 31 percent instruments) and 235 control patients. Thirty-seven of the patients with retained foreign bodies (69 percent) required reoperation, and one died. Patients with retained foreign bodies were more likely than controls to have had emergency surgery (33 percent vs. 7 percent, P<0.001) or an unexpected change in surgical procedure (34 percent vs. 9 percent, P<0.001). Patients with retained foreign bodies also had a higher mean body-mass index and were less likely to have had counts of sponges and instruments performed. In multivariate analysis, factors associated with a significantly increased risk of retention of a foreign body were emergency surgery (risk ratio, 8.8 [95 percent confidence interval, 2.4 to 31.91]), unplanned change in the operation (risk ratio, 4.1 [95 percent confidence interval, 1.4 to 12.4]), and body-mass index (risk ratio for each one-unit increment, 1.1 [95 percent confidence interval, 1.0 to 1.2]). CONCLUSIONS: The risk of retention of a foreign body after surgery significantly increases in emergencies, with unplanned changes in procedure, and with higher body-mass index. Case-control analysis of medical-malpractice claims may identify and quantify risk factors for specific types of errors.
Keywords: adult; article; body mass; case control study; controlled study; emergency surgery; female; foreign body; human; iatrogenic disease; major clinical study; male; malpractice; multivariate analysis; postoperative complication; priority journal; reoperation; risk factor; statistical analysis; surgical equipment; surgical sponge

Transmural migration of a retained laparotomy sponge - Dhillon, J.S.; Park, A. (American Surgeon, 2002)
The most common surgically retained foreign body is the laparotomy sponge. The clinical presentation of a retained sponge can vary from an incidental finding on plain radiograph to an intense inflammatory response with obstruction or perforation. In the case described here a patient reported abdominal pain 11 months after her hysterectomy. Although two sponge counts appeared in the operative record one laparotomy sponge had been overlooked. Apparently an inflammatory response created an abscess pocket around the sponge between the abdominal wall and the ileum resulting in perforation of the ileum. Through this opening the sponge migrated into the lumen of the small bowel, from which it was surgically removed. The patient recovered without complications. The case highlights the importance of a thorough exploration of all quadrants of the abdomen at the termination of surgical cases.
Keywords: abdominal radiography; abdominal surgery; adult; anamnesis; article; case report; clinical feature; female; foreign body; hospital discharge; human; laparotomy; physical examination; small intestine perforation; surgical error; surgical sponge

Results of hydrophilic acrylic, hydrophobic acrylic, and silicone intraocular lenses in uveitic eyes with cataract: Comparison to a control group - Abela-Formanek, C.; Amon, M.; Schauersberger, J.; Kruger, A.; Nepp, J.; Schild, G. (Journal of Cataract and Refractive Surgery, 2002)
Purpose: To evaluate the uveal and capsular biocompatibility of hydrophilic acrylic, hydrophobic acrylic, and silicone intraocular lenses (IOLs) in eyes with uveitis. Setting: Department of Ophthalmology, University of Vienna, Vienna, Austria. Methods: This prospective study comprised 72 eyes with uveitis and 68 control eyes having phacoemulsification and IOL implantation by 1 surgeon. Patients received 1 of the following IOLs: foldable hydrophilic acrylic (Hydroviewr®, Bausch & Lomb), hydrophobic acrylic (AcrySof®, Alcon), or silicone (CeeOn® 911, Pharmacia). Postoperative evaluations were at 1, 3, and 7 days and 1, 3, and 6 months. Cell reaction was evaluated by specular microscopy of the anterior IOL surface and the anterior and posterior capsule reaction, by biomicroscopy. Results: Small round cell deposition was observed on all IOLs in the immediate postoperative period, especially in eyes with uveitis. This reaction decreased 3 to 6 months after surgery. Although the CeeOn 911 had a higher mean grade of small cells, there was no statistical difference between the 3 IOL types after 6 months in the uveitis and control groups. Foreign-body giant cells (FBGCs) increased after 1 week to 1 month. The AcrySof IOLs had the highest number of FBGCs; after 6 months, there was a statistically significant difference between the AcrySof and Hydroview uveitis groups (P = .036) and the AcrySof and CeeOn 911 uveitis groups (P = .003) but there was no difference among the 3 IOL types in the control group. Lens epithelial cell outgrowth persisted on the Hydroview IOLs in control eyes and regressed on all 3 IOL types in uveitic eyes and on the AcrySof and CeeOn 911 IOLs in control eyes (P = .0001). Anterior capsule opacification (ACO) was more severe on all IOL types in uveitic eyes and on the CeeOn 911 IOL in control eyes. Posterior capsule opacification (PCO) was more severe in uveitic eyes. The Hydroview group had more severe PCO than the AcrySof and the CeeOn 911 groups in uveitis and control eyes. Six months postoperatively, the difference was significant (P = .0001). There was no significant difference between the AcrySof and CeeOn 911 IOLs. Conclusions: Intraocular lens biocompatibility is inversely related to inflammation. Hydrophilic acrylic material had good uveal but worse capsular biocompatibility. Hydrophobic acrylic material had lower uveal but better capsular biocompatibility. Silicone showed a higher small cell count (mild) and more severe ACO but achieved PCO results comparable to FBGC results and better than those with the AcrySof lens 6 months after surgery. Despite the differences in IOL biocompatibility, all patients benefited from the surgery. © 2002 ASCRS and ESCRS.
Keywords: silicon; adult; aged; article; biocompatibility; biomicroscopy; cataract; clinical trial; controlled clinical trial; controlled study; disease severity; female; giant cell; human; inflammation; lens capsule; lens epithelium; lens implant; major clinical study; male; phacoemulsification; postoperative period; priority journal; treatment outcome; uveitis; Acrysof MA60BM; CeeOn 911; Hydroview

Transmural migration of a retained laparotomy sponge. - Dhillon, J.S.; Park, A. (The American surgeon, 2002)
The most common surgically retained foreign body is the laparotomy sponge. The clinical presentation of a retained sponge can vary from an incidental finding on plain radiograph to an intense inflammatory response with obstruction or perforation. In the case described here a patient reported abdominal pain 11 months after her hysterectomy. Although two sponge counts appeared in the operative record one laparotomy sponge had been overlooked. Apparently an inflammatory response created an abscess pocket around the sponge between the abdominal wall and the ileum resulting in perforation of the ileum. Through this opening the sponge migrated into the lumen of the small bowel, from which it was surgically removed. The patient recovered without complications. The case highlights the importance of a thorough exploration of all quadrants of the abdomen at the termination of surgical cases.
Keywords: abdominal pain; adult; article; case report; female; foreign body; human; ileum; inflammation; injury; devices; intestine perforation; laparotomy; pathology; surgical sponge

Recognized standards and recommended guidelines for the swab, instrument and needle count. - Beesley, J. (British journal of perioperative nursing : the journal of the National Association of Theatre Nurses, 2002)
Keywords: article; female; foreign body; health care quality; human; male; needle; perioperative nursing; postoperative complication; practice guideline; primary prevention; standard; surgical equipment; United Kingdom

Conservative management of ingested foreign bodies. - Weiland, S.T.; Schurr, M.J. (Journal of gastrointestinal surgery : official journal of the Society for Surgery of the Alimentary Tract, 2002)
We reviewed the clinical benefits of hospitalization, esophagogastroduodenoscopy, and surgical intervention for ingested foreign bodies in adults. Patients with esophageal foreign bodies were not included in the study group. A 10-year experience is reported. Each patient's physical examination findings at presentation, white blood cell count, length of hospital stay, number and types of foreign bodies ingested, endoscopic interventions, surgical interventions, and complications were reviewed. There were 75 separate hospitalizations, all occurring in 22 male prison inmates. A total of 256 foreign bodies were ingested. Patients incurred 281 hospitalization days (average 3.7 days per admission). One patient had signs of peritonitis. White blood cell count was less than 10 K/microL in 85%. Sixty-four endoscopies were performed with removal of 79 of 163 foreign bodies (48% success rate). Five patients required general anesthesia because of a lack of cooperation. Complications occurred in four of them, one requiring laparotomy. Eight additional laparotomies were performed. One was performed for an acute abdomen on admission and one for the development of an acute abdomen after conservative management. Two were performed to remove metal bezoars. Four additional laparotomies were performed because of surgeon preference. Among the 23 patients admitted and managed conservatively, 77 (97%) of 79 foreign bodies passed spontaneously. One patient required laparotomy. Of the 256 ingested foreign bodies, 79 were removed endoscopically, 71 were removed surgically, and 106 passed spontaneously. The size, shape, and number were not predictive of the ability to transit the gastrointestinal tract. Foreign body ingestion is problematic in prison inmates. With conservative management, most foreign bodies will pass spontaneously. Endoscopy has a high failure rate and is associated with significant complications. Surgical intervention should be reserved for those who have acute conditions in the abdomen or large bezoars.
Keywords: adult; article; foreign body; gastrointestinal endoscopy; human; length of stay; male; middle aged; prisoner; treatment outcome

Uveal and capsular biocompatibility of hydrophilic acrylic, hydrophobic acrylic, and silicone intraocular lenses - Abela-Formanek, C.; Amon, M.; Schild, G.; Schauersberger, J.; Heinze, G.; Kruger, A. (Journal of Cataract and Refractive Surgery, 2002)
Purpose: To evaluate the long-term response of 6 types of 3-piece intraocular lenses (IOLs) by assessing the cellular reaction on the anterior IOL surface, the behavior of posterior and anterior capsule fibrosis, and flare. Setting: Department of Ophthalmology, Medical School, University of Vienna, Vienna, Austria. Methods: One hundred eighty eyes were prospectively randomized to receive 1 of 6 IOLs: hydrophilic acrylic Hydroview® (Bausch & Lomb) or MemoryLens® (ORC); hydrophobic acrylic AcrySof® MA60BM (Alcon) or AMO Sensar AR40® (Allergan); hydrophobic silicone CeeOn® 920 or CeeOn 911A (Pharmacia). The patients had standardized cataract surgery, postoperative medication, and follow-up. One year after surgery, 155 eyes were assessed. The cellular reaction was evaluated by specular microscopy of the antenor IOL surface. Anterior and posterior capsule opacification (PCO) was assessed semiquantitatively by biomicroscopy. Flare was measured with a Kowa FC-1000 laser flare-cell meter. Results: Regarding uveal biocompatibility, the hydrophobic acrylic IOLs showed the highest incidence of late foreign-body cell reaction (AcrySof, 30%; AR40, 17%) followed by the hydrophilic acrylic (MemoryLens, 8%; Hydroview, 4%) and silicone (CeeOn 920, 4%; CeeOn 911A, 0%) (P = .0044). In all cases, the cellular reaction was low grade and clinically insignificant. Regarding capsular biocompatibility, some eyes developed lens epithelial cell (LEC) outgrowth on the anterior IOL surface. The highest incidence was in the hydrophilic acrylic group (Hydroview, 85%; MemoryLens, 27%) followed by the hydrophobic acrylic (AcrySof, 4%; AR40, 3%). No silicone IOL had LECs on the anterior surface. The difference among IOL groups was significant (P = .0001). Anterior capsule opacification was more predominant in the hydrophobic IOL groups. Posterior capsule opacification of the central 3.0 mm area was lowest in the groups with a sharp-edged optic (CeeOn 911A, AcrySof) followed by the round-edged silicone (CeeOn 920), hydrophobic acrylic (AR40), and hydrophilic acrylic IOLs (P = .0001). There was a significant difference in flare between the AR40 lens and the Hydroview, MemoryLens, CeeOn 911A, and CeeOn 920 (P < .004). There was no statistically significant difference in the postoperative cell count at 1 year. The power calculation showed that the sample size was sufficient. Conclusions: The differences in cellular reaction, although clinically mild in normal eyes, indicate that there were more giant cells with hydrophobic acrylic IOLs and an increased tendency toward LEC outgrowth with hydrophilic lenses. The incidence of PCO was lowest in the hydrophobic IOL groups, especially in groups with a sharp-edged optic. Second-generation silicone IOLs with a sharp edge had good uveal and capsular biocompatibility 1 year after surgery. © 2002 ASCRS and ESCRS.
Keywords: acrylic acid; acrylic acid copolymer; silicon; adult; article; Austria; biocompatibility; biomicroscopy; cataract; cell count; clinical trial; comparative study; controlled clinical trial; controlled study; female; follow up; foreign body reaction; human; hydrophilicity; hydrophobicity; lens implant; major clinical study; male; postoperative complication; priority journal; randomized controlled trial; specular microscopy; treatment outcome; AcrySof MA60BM; AMO Sensar AR40; CeeOn 911A; CeeOn 920; Hydroview; Kowa FC-1000 laser flare-cell meter; MemoryLens

Imaging of surgical paraphernalia: what belongs in the patient and what does not. - Wolfson, K.A.; Seeger, L.L.; Kadell, B.M.; Eckardt, J.J. (Radiographics : a review publication of the Radiological Society of North America, Inc, 2000)
Many radiologists are not familiar with the names of various instruments, surgical sponges, and needles that may be seen on intraoperative and postoperative radiographs. These devices may be intentionally placed for localization or therapeutic intervention, discovered on radiographs obtained to evaluate incorrect sponge or needle counts, or incidentally encountered on postoperative radiographs. These paraphernalia are usually described in vague nonspecific terms in radiology reports. In this article, photographs and radiographs of several instruments commonly used for intraoperative localization or therapy are presented, as well as examples of sponges, needles, and other devices that should not be found on postoperative radiographs. Familiarity with their appearances will allow a more precise and knowledgeable description in radiology reports.
Keywords: article; foreign body; human; peroperative care; postoperative care; radiography; surgical equipment

Expanded polytetrafluoroethylene in external valvuloplasty for superficial or deep vein incompetence - Belcaro, G.; Nicolaides, A.N.; Errichi, B.M.; Incandela, L.; De Sanctis, M.T.; Laurora, G.; Ricci, A. (Angiology, 2000)
The authors evaluated the long-term safety of expanded polytetrafluoroethylene (ePTFE) implants used in external valvuloplasty for treatment of incompetence of the long saphenous and common and superficial femoral veins. During a 15-year period patients with superficial and/or deep venous disease and hypertension due to pure superficial or deep vein incompetence underwent an external valvuloplasty with ePTFE sutures, or an ePTFE cardiovascular patch placed as a sleeve around the incompetent vein segment, or an ePTFE tubular graft placed around the venous segment. Postoperative follow-up evaluations consisted of clinical examinations, high-resolution ultrasonography, and color duplex scanning, and a complete blood count performed at 1, 3 and 6 months, and repeated for at least 4 years, every 2 years after the procedure. A total of 101 patients (38 men and 63 women; mean [± sd] age, 44 ± 12 years) underwent external valvuloplasty between January 1983 and December 1998; 82 of them completed the 4-year follow-up. Forty of the 82 patients had been operated on for superficial vein incompetence, 42 for deep vein incompetence. Overall, the mean follow-up time was 7.8 ± 3.6 years (range, 4 to 13). There were no infections, thromboses, foreign-body reactions to the ePTFE implants, or other prosthesis-related complications requiring explantation. One granuloma (noninfected) developed in association with a tubular ePTFE implant around a long saphenous vein, but it did not necessitate implant removal. Seven patients required (at least after 4 years) a second procedure for recurrent or new venous incompetence. Therefore, in this observational study, ePTFE implants used to treat or correct venous incompetence were well tolerated on a long-term basis.
Keywords: cephalosporin; heparin; adult; article; blood cell count; clinical examination; color Doppler flowmetry; echography; female; femoral vein; follow up; graft infection; granuloma; human; hypertension; major clinical study; male; politef implant; postoperative care; recurrent disease; saphenous vein; thrombosis; valvuloplasty; vein insufficiency; Gore-Tex

Intraperitoneal gossypibomas: The need to count sponges - Lauwers, P.R.; Van Hee, R.H. (World Journal of Surgery, 2000)
Intraperitoneal forgotten foreign bodies are prone to create adhesions and to encapsulate, or to provoke an exudative response, with or without accompanying bacterial infection. Often a process of self-extrusion is initiated. This is also true for gossypibomas, retained surgical sponges. Presentation is possible as a pseudotumoral, occlusive, or septic syndrome; several cases, however, have remained asymptomatic for as long as several decades. Ultrasonography and radiology (especially computed tomography) contribute significantly to the detection of gossypibomas; magnetic resonance imaging is a less used technique. Detection by plain radiography is difficult. Ultrasonography demonstrates a hyperreflective mass with hypoechoic rim and a strong posterior shadow. Computed tomography shows a well defined mass with internal heterogenous densities. Therapy consists of operative removal of the foreign body in association with resolving its complications. Adding a series of five cases to the existing literature reports, the fate of intraperitoneal forgotten surgical sponges is reviewed.
Keywords: abdominal surgery; adult; article; clinical article; clinical feature; differential diagnosis; disease course; female; foreign body; gynecologic surgery; human; male; occlusion; pseudotumor; radiodiagnosis; reoperation; sepsis; sponge

Complications of foreign bodies in the esophagus - Loh, K.S.; Tan, L.K.S.; Smith, J.D.; Yeoh, K.H.; Dong, F. (Otolaryngology - Head and Neck Surgery, 2000)
Major complications of foreign bodies in the esophagus carry significant morbidity and mortality risks. A retrospective case control study was performed to assess the factors associated with major complications. In total, 273 patients seen within a 7-year period were divided into 2 groups; 253 had no or minor complications, and 20 had major complications. Age, sex, duration of the foreign body, total white cell count (TWC), and nature and site of the foreign body were analyzed in the 2 groups. The major complication rate was 7.3%. Duration of the foreign body and TWC were the only statistically significant factors associated with major complications. Six patients required open neck exploration, 1 had an open thoracotomy, and 13 were treated by endoscopic removal. There were 2 deaths. Given the significant morbidity and mortality risks, we conclude that patients with a prolonged history of a foreign body in the esophagus and a raised TWC should be treated urgently.
Keywords: adolescent; adult; aged; article; child; demography; disease course; endoscopic therapy; esophagus fistula; esophagus foreign body; female; human; leukocyte count; major clinical study; male; mediastinitis; morbidity; mortality; perforation; pneumonia; retropharyngeal abscess; sex ratio; thoracotomy

Recommended practices for sponge, sharp, and instrument counts. AORN Recommended Practices Committee. Association of periOperative Registered Nurses. (AORN journal, 1999)
Keywords: article; documentation; foreign body; human; medical record; methodology; nursing; perioperative nursing; practice guideline; standard; surgery; surgical equipment; surgical sponge; United States

Getting the sponge count right. - Langslow, A. (Australian nursing journal (July 1993), 1999)
Keywords: article; Australia; case report; female; foreign body; human; hysterectomy; malpractice; nursing; operating room personnel; postoperative complication; surgical sponge

Deep lamellar keratoplasty versus penetrating keratoplasty for corneal lesions - Panda, A.; Bageshwar, L.M.S.; Ray, M.; Singh, J.P.; Kumar, A. (Cornea, 1999)
Purpose. To compare the effectiveness of deep lamellar keratoplasty (DLK) with that of penetrating keratoplasty (PKP) in cases of corneal lesions not involving the endothelium. Methods. Forty-eight eyes with leukomatous corneal opacity (n = 33), keratoconus with apical scarring (n = 6), granular corneal dystrophy (n = 5), lattice corneal dystrophy (n = 2), and multiple corneal foreign bodies (n = 2) in an age group varying from 16 to 53 years underwent DLK (n = 24) and PKP (n = 24) by utilizing B and (B+ and A) grade M-K preserved donor tissue, respectively. The patients were followed up closely, and the graft clarity, visual achievement, astigmatism and endothelial cell count were evaluated at repeated occasions up to 1 year. Results. Astigmatism of <3 diopters (D) and ≥5D was obtained in 19 eyes and one eye, respectively, after DLK at 6 months, whereas six eyes of the PKP group had astigmatism <3D, and 12 eyes had ≥5D at the end of 6 months. The same at 1 year was observed in 20 and one eye in the DLK and eight and five eyes of the PKP group. Astigmatism of ≥5D at the end of 6 months in both the groups showed highly significant changes (p < 0.001). Best corrected visual acuity of 6/18 or more was achieved in 18 and 12 eyes at 6 months after DLK and PKP, respectively, which were statistically highly significant (p < 0.001), whereas at 1 year, it was seen in 17 and 15 eyes of the DLK and PKP groups, respectively, which was nonsignificant. The mean endothelial cell count was 2,233.3 ± 64.453 cells/mm2 and 2,219.6 ± 102.48 cells/mm2 at 6 months and 1 year, respectively, after DLK, which was nonsignificant. The mean cell count of the donor eyes used for PKP was 2,191 ± 52.164 cells/mm2, 1,902.8 ± 70.346 cells/mm2 at 6 months, and 1,579.0 ± 80.24 cells/ram2 at 1 year. All the values showed highly significant changes (p < 0.001). Further, the graft clarity of ≥3+ was achieved in 20 and 18 eyes at 6 months postoperatively in the DLK and PKP groups, whereas the same was observed in 19 and 13 eyes of both the groups, respectively, at 1-year follow-up. Conclusion. DLK is a promising procedure and should be practiced more frequently for corneal pathology not involving the endothelium.
Keywords: adolescent; adult; article; astigmatism; clinical article; cornea dystrophy; cornea opacity; female; foreign body; human; intermethod comparison; leukomalacia; male; penetrating keratoplasty; priority journal; surgical technique; visual acuity

Post-traumatic endophthalmitis: Causative organisms and visual outcome - Abu El-Asrar, A.M.; Al-Amro, S.A.; Al-Mosallam, A.A.; Al-Obeidan, S. (European Journal of Ophthalmology, 1999)
Purpose. Post-traumatic endophthalmitis makes up a distinct subset of intraocular infections. The purpose of the present study was to identify the causative organisms and record the visual outcome after infectious endophthalmitis in eyes with penetrating trauma. Methods. We reviewed 18 consecutive cases of culture-positive endophthalmitis that developed after penetrating ocular trauma. All cases were treated with pars plana vitrectomy and intravenous and intraocular antibiotics. Results. The 15 males and 3 females ranged in age from 4 to 43 years (mean 25.1 ± 11 years). Nine (50%) had intraocular foreign bodies. A single species was isolated in 16 cases, and multiple organisms in two. Staphylococcus epidermidis and gram-negative organisms were the most frequent and were cultured either alone or in association with other organisms in respectively five (27.7%) and four cases (22.2%). Clostridium perfringens was isolated in three cases (16.6%). Bacillus was not found as a cause of endophthalmitis. Final visual acuity was better than 20/400 in eight cases (44%). In five cases (27.7%), the eye was saved but visual acuity was counting fingers. Two eyes (11%) had no light perception. The remaining three eyes (16.6%) were enucleated or eviscerated. Clostridium perfringens was isolated from two eyes and Aspergillus niger from one. Postoperative retinal detachment developed in four eyes, which were successfully operated. Conclusions. Organisms isolated in this series were similar to those in previous reports of post-traumatic endophthalmitis from other parts of the world, except that the frequency of Clostridium perfringens isolation was high and no Bacillus species were cultured. In view of its devastating outcome, post-traumatic endophthalmitis must be treated promptly with vitrectomy and intravitreal antibiotics.
Keywords: antibiotic agent; cefazolin; gentamicin; prednisone; triamcinolone; vancomycin; adult; antibiotic therapy; article; Aspergillus niger; clinical article; Clostridium perfringens; endophthalmitis; enucleation; evisceration; eye injury; female; Gram negative bacterium; human; intraocular drug administration; intraocular foreign body; intravenous drug administration; intravitreal drug administration; male; penetrating trauma; postoperative complication; priority journal; retina detachment; Staphylococcus epidermidis; visual acuity; vitrectomy

Alternatives to spinal fusion - Kostuik, J.P. (Orthopedic Clinics of North America, 1998)
An underlying tenet of design in the biologic realm is that the optimal design of the prosthetic device reproduces exactly the healthy, intact biologic situation in every case (geometric, kinetic). Because the optimal solution is unobtainable, however, because of the limited resources available, compromises must be made. Every compromise inevitably produces complications because of the interdependent nature of biologic systems. The goal then becomes to minimize the detrimental effects of the implant system through the best possible use of the technologies available. It is the author's experience that whenever this fundamental tenet is forgotten in the design of an implant, either the system is affected adversely, or unforeseen complications arise in an associated system. An example can be seen in the evolution of solutions to the problem of loosening of the femoral component of hip prostheses. This loosening is caused, in part, by improper load transmission to the femur. Until recently, most hip implants transferred stress to the femur distally through the stem of the implant. Because of the lack of physiologic stress levels in the proximal femur bone, resorption was common, which often led to loosening of the implant. Many current designs are able to provide proximal loading of the femur through well-designed, proximal press fits. Although this seems to be a better solution, these prostheses fall short of the biologic situation in that they impose hoop stress to bone cells that naturally experience primarily axial stresses. The subsequent remodeling of bone because of the change in the load direction may not provide adequate stability for the implant in the long-term. In the same way, a best effort must be made in the present design to maintain near-physiologic load transfer and motion. Therefore, considerable effort was invested in the design stage of this project to consider the solutions available today to duplicate the stiffness (flexibility) of the lumbar disc in its principal plane of motion. This philosophy of restoration of function was also applied in specifying the geometry and the constraints to motion imposed by the prosthesis. The long life span required of an artificial spinal disc poses a significant challenge to the design effort. Plastics available today cannot be counted on to last for 40 years and 100 million cycles. The proposition of 40 years of metal-on-metal, however, was somewhat alarming. Therefore, quantitative wear-simulation testing has accompanied this development project since the second year of the project. Likewise, other factors, such as fatigue stress and corrosion resistance, become increasingly important because of the extended life span of the device. Therefore, as part of this project, standard material fatigue experiments (such as rotating bend tests) have been performed on the hot isostatatically pressed cobalt-chromium and titanium couples. The loads in the quadruped lumbar spine are largely in shear, which is in contrast to the more upright human lumbar spine, in which the loads are mainly in compression. The fact that bone ingrowth occurred in these animals under the worst-case scenario (shear loads) is most encouraging. There was no foreign body reaction in regional tissues and lymph nodes other than a mild fibrous tissue later over the implant. No soft tissue ingrowth was seen histologically in the springs. Although small numbers of animals were analyzed, the results were encouraging and would suggest that human implementation is feasible with little or no likelihood of mechanical failure, loosening, or disaster. A categoric list of design criteria relevant to the development of an articulating spinal disc implant has been presented. Each of these criteria and many of the questions posed are relevant in the synthesis of any new implant system. Constraints imposed by an implant have been discussed at length. A method of constraint analysis that simplifies specification of motion constraints has been described. Specifications of the preclinical trial design of an intervertebral disc prosthesis have been listed and evaluated on the basis of some of the pretrial experimental data. This design is the product of the detailed prospective design technique that has been the focus of this article. It is a design that will undergo future revisions based on clinical trial data, yet the implant's limitations and its in vitro performance has been assessed thoroughly during the past years to minimize the number of revisions necessary because of unsatisfactory results in clinical trials.
Keywords: biocompatibility; biomechanics; bone prosthesis; geometry; human; intervertebral disk; intervertebral disk hernia; discectomy; ischialgia; priority journal; review; spine fusion; surgical technique

Biocompatibility of poly(methylmethacrylate), silicone, and AcrySof intraocular lenses: Randomized comparison of the cellular reaction on the anterior lens surface - Hollick, E.J.; Spalton, D.J.; Ursell, P.G.; Pande, M.V. (Journal of Cataract and Refractive Surgery, 1998)
Purpose: To determine the foreign-body response to three intraocular lens (IOL) biomaterials (poly[methyl methacrylate] [PMMA], silicone, and AcrySof) and use this as an indicator of their comparative biocompatibility postoperatively within the eye. Setting: A British teaching hospital eye department. Methods: Ninety eyes were prospectively randomized to receive a PMMA, silicone, or AcrySof IOL. All lenses had 6.0 mm optics with PMMA haptics. A standardized surgical protocol was performed by a single surgeon using an extracapsular technique with capsulorhexis; eyes that experienced a surgical complications were excluded. All patients had standardized postoperative medication and follow-up. Specular microscopy of the anterior IOL surface was carried small cell and giant cell reactions. Results: All three IOL types produced a mild degree of nonspecific foreign-body response, which resolved over the study period without detrimental effect. The silicone group had significantly higher small cell counts than the PMMA and AcrySof groups (P = .02); the AcrySof group had significantly lower giant cell counts than the other two groups (P = .003). Conclusion: The three IOL types were sufficiently biocompatible to function in normal eyes with age- related cataracts. However, AcrySof of IOLs were associated with lower giant cell counts than PMMA and silicone IOLs and might produce better results in eyes with pre-existing blood-aqueous barrier damage.
Keywords: lens implant; biomaterial; poly(methyl methacrylate); silicone; unclassified drug; adult; aged; aging; article; biocompatibility; blood eye barrier; capsulorhexis; cataract; clinical trial; controlled clinical trial; controlled study; foreign body reaction; giant cell; human; lens capsule; lens implant; major clinical study; postoperative complication; priority journal; randomized controlled trial; AcrySof Alcon MA60BM; Alcon MC60BM IOL; Iolab l141U IOL

Postoperative textilomas: review of 14 cases. - Fernandez Lobato, R.; Marin Lucas, F.J.; Fradejas Lopez, J.M.; Diaz Gimenez, L.M.; Camarero Marina, E.; Moreno Azcoita, M. (International surgery, 1998)
BACKGROUND: Textile materials of surgical origin are found in the abdominal cavity in between 1/1300 and 1/1500 laparotomies, in spite of preventive measures. It is very difficult to ascertain the exact incidence due to the lack of descriptions in the literature. METHODS: Fourteen cases of postoperative foreign bodies or textilomas are reported. The cases were collected from two hospital centers between 1985 and 1997. RESULTS: There were 12 intra-abdominal cases, 1 thoracic and 1 paravertebral. In 8 (57.1%) diagnosis was made preoperatively by radiological techniques. The mortality rate was 14.2% with 2 deaths due to multiorganic failure in one case and sepsis in the other. Both patients were over 70, with malignant pathology. The morbidity rate was 21.4%, wall abscesses which evolved favorably being the most frequent cause of complications. CONCLUSIONS: Prevention of this complication is the best treatment. It is advisable to use textile material with radiopaque contrast, to count the pieces of material to be used and perform an X-ray before the laparotomy is closed specially in emergency (bleeding and trauma patients) because in these complex cases the possibility of material being left behind is more advisable.
Keywords: adult; aged; computer assisted tomography; female; foreign body granuloma; human; iatrogenic disease; laparoscopy; male; middle aged; mortality; postoperative complication; retrospective study; review; textile

The surgeon's nondelegable responsibility for the sponge count. Case on point: Johnston v. Southwest Louisiana Assn. 693 So. 2d 1195-LA (1997). - Tammelleo, A.D. (The Regan report on nursing law, 1997)
Keywords: article; case report; human; legal aspect; legal liability; male; operating room personnel; surgery; surgical sponge; United States

Correct surgical sponge count. - Miller, R.E. (Annals of surgery, 1997)
Keywords: human; methodology; note; peroperative care; postoperative complication; statistics; surgical sponge

Late complication of laparoscopic salpingoophorectomy: retained foreign body presenting as an acute abdomen. - Mendez, L.E.; Medina, C. (JSLS : Journal of the Society of Laparoendoscopic Surgeons / Society of Laparoendoscopic Surgeons, 1997)
BACKGROUND: Laparoscopy is widely used as a tool in many clinical situations allowing for diagnosis and/or surgical management in a minimally invasive fashion. Most laparoscopic cases are ambulatory and allow patients to recover quickly. Nonetheless, attention to surgical technique is paramount to avoid both short and long term complications. CASE: A 32-year-old woman had a laparoscopy and a reported left salpingoophorectomy for benign disease of the ovary in September, 1994. Shortly thereafter, in January, 1995, she was diagnosed with an intrauterine pregnancy and delivered in October of 1995 by spontaneous vaginal delivery. The pregnancy and delivery were both uncomplicated. The patient presented four weeks postpartum with clinical suspicion of appendicitis. However, at the time of laparotomy, the patient was found to have a retained foreign body from her prior laparoscopy in the right lower quadrant with a pelvic abscess and evidence of prior right salpingoophorectomy. The appendix appeared grossly normal. CONCLUSION: Laparoscopy is a safe, effective modality for various surgical and gynecologic conditions. Although laparoscopy is usually done on an outpatient basis, complications can manifest several weeks or months later. This case illustrates and reminds us of the importance of adherence to surgical laparoscopic principles. These include direct visualization when removing equipment and a complete count of surgical instrumentation to confirm the integrity of such at the end of each procedure.
Keywords: abscess; acute abdomen; adult; article; case report; female; follow up; foreign body; human; laparoscopy; methodology; omentum; ovariectomy; ovary cyst; peritoneal disease; time; treatment outcome; Fallopian tube

Comparative in vitro analysis of topical hemostatic agents - Wagner, W.R.; Pachence, J.M.; Ristich, J.; Johnson, P.C. (Journal of Surgical Research, 1996)
Hemostatic agents are broadly utilized across the surgical specialties. While specific characteristics desirable for individual applications may vary, these agents generally are expected to aid the patient's coagulation system in the rapid development of an occlusive clot. Six commonly utilized hemostatic agents were quantitatively compared in terms of their ability to mediate platelet aggregation, deposition and activation, and initiate gross clot formation in a series of in vitro tests. Three types of collagen sponges (Actifoam, Helistat, Instat), microfibrillar collagen (Avitene), a gelatin sponge (Gelfoam), and oxidized regenerated cellulose (Surgicel) were studied. Platelet aggregation: Citrated platelet rich plasma (PRP) was contacted with hemostatic agents both with and without thrombin in a stirred cuvette and the platelet count was measured over 5 min. Platelet deposition: To approximate arterial wounds, PRP was perfused in a controlled manner through hemostatic agents, and the effluent platelet count was measured over time. Platelet activation: ATP secretion from PRP contacted with hemostatic agents in a stirred cuvette was measured at 1 and 5 min. Clot formation: The clotting time of nonanticoagulated whole blood contacted with the hemostatic agents was measured. Materials which depleted platelets most rapidly and effectively in the perfusion system (Avitene, Helistat, and Actifoam) were also the most effective inducers of platelet aggregation and secretion. Clot formation (likely to be platelet dependent) was also more rapid in this group. An overall activity ranking combined the relative performance of each hemostatic agent on the various tests: Actifoam ~ Avitene > Helistat >> Gelfoam > Instat > Surgicel. The activity ranking generally reflects the materials used in these agents (collagen > gelatin > oxidized regenerated cellulose), as well as their processing (chemical crosslinking in collagen sponges may lower activity). Such in vitro assessment of the relative platelet and coagulation activities of hemostatic agents might serve as a useful screening tool before investigating properties which require more expensive animal or clinical testing.
Keywords: actifoam; adenosine triphosphate; collagen; gelatin; gelfoam; hemostatic sponge; hemostatic agent; instat; microcrystalline collagen; oxidized regenerated cellulose; thrombin; unclassified drug; article; blood clotting; controlled study; hemostasis; human; human tissue; priority journal; sponge; thrombocyte activation; thrombocyte aggregation; platelet count; thrombocyte function; topical drug administration; actifoam; avitene; gelfoam; helistat; instat; surgicel

The effect of pentoxifylline on the lung during cardiopulmonary bypass. - Türköz, R.; Yörükoglu, K.; Akcay, A.; Yilik, L.; Baltalarli, A.; Karahan, N.; Adanir, T.; Sagban, M. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 1996)
Cardiopulmonary bypass (CPB) produces an inflammatory response due to the interaction of blood with a foreign body surface. The lungs are most affected by this inflammatory response. Pentoxifylline (PTX), a phosphodiesterase inhibitor and an inhibitor of leukocyte activation, is used to minimize damage in lungs where leukocytes play an important role. Twenty patients with mitral valve stenosis with planned mitral valve surgery were included in the study. The ten patients receiving pentoxifylline (PTX group) were administered 400 mg PTX orally TID for 3 days preoperatively and, following anesthetic induction, a 300 mg PTX infusion was given. The ten patients receiving no PTX were the control group (CT). Platelet and leukocyte counts, mean pulmonary arterial pressure (mPAP), pulmonary capillary wedge pressure (PCWP), cardiac index (CI), pulmonary vascular resistance (PVR), alveolar-arterial PO2 gradient (AaDO2) were measured just before and after CPB, and 2 h postoperatively. The number of the leukocytes increased in the blood samples drawn 15 min after CPB in both groups and 2 h postoperatively showed no statistical change. The number of platelets had decreased significantly at the end of the CPB in both groups and, 2 h postoperatively, there was a further decrease in the blood count in the control group (P < 0.05). There was no significant difference in either the preoperative or postoperative PAP, PAWP, and CI. Pulmonary vascular resistance increased in both groups following the CPB (CT, before: 136 +/- 44, after: 177 +/- 94 dyne. sec.cm-5; PTX, before: 151 +/- 82, after 182 +/- 43 dynes.sec.cm-5). Two hours postoperatively, a considerable increase continued in the control group (CT 219 +/- 170 dynes.sec. cm-5), while there was an insignificant increase in the PTX group (PTX 193 +/- 51 dynes.sec.cm-5) (P < 0.05). The alveolar-arterial PO2 gradient increased after the CPB in both groups but a moderate decrease was observed 2 h postoperatively. In lung biopsy specimens taken before and after the CPB, there was marked leukocyte sequestration in the control group, whereas the number of leukocytes was seen to be insignificant in the PTX group (P < 0.005). This dosage regimen of PTX inhibits the postoperative increase in PVR and greatly minimized leukocyte sequestration in the lung due to CPB.
Keywords: pentoxifylline; phosphodiesterase inhibitor; adult; article; cardiopulmonary bypass; clinical trial; controlled clinical trial; controlled study; dose response; drug administration; drug effect; female; foreign body reaction; hemodynamics; human; immunology; leukocyte count; lung; lung alveolus; male; middle aged; mitral valve stenosis; neutrophil; premedication; systemic inflammatory response syndrome; platelet count; vascular resistance; vascularization

Nafamostat mesilate reduces blood-foreign surface reactions similar to biocompatible materials - Usui, A.; Hiroura, M.; Kawamura, M.; Hibi, M.; Yoshida, K.; Murakami, F.; Tomita, Y.; Ooshima, H.; Murase, M. (Annals of Thoracic Surgery, 1996)
Background. Nafamostat mesilate (FUT-175) is a synthetic serine protease inhibitor that inactivates coagulation, fibrinolysis, and platelet aggregation. Nafamostat mesilate may suppress the blood-foreign surface reaction similar to biocompatible materials by blocking factor XIIa. Methods. We performed an in vitro study of cardiopulmonary bypass (CPB) with fresh human blood among the following three groups: standard CPB sets (C), biocompatible CPB sets (B), and standard CPB sets with FUT-175 (10 mg/L) (F). A clinical study using these same CPB groups also was performed in 45 patients undergoing aortocoronary bypass operations (15 patients each). We injected FUT-175 at 40 mg/h during CPB. Results. In the in vitro study, both groups B and F showed significantly lower levels of coagulation factors, thrombin-antithrombin III complex, fibrinopeptide A, β-thromboglobulin, complement C3a, granulocyte elastase, and free hemoglobin than group C at the conclusion of the study. Thrombin-antithrombin III complex and free hemoglobin in group F also were lower than in group B. The platelet count remained at a higher level in group F than in the other groups. Separation of bradykinin was suppressed most significantly in group F. In the clinical study, group F also showed significantly lower levels of α2-plasmin inhibitor plasmin complex and C3a than both groups C and B. There were minimal levels of free hemoglobin in group F. Conclusions. Nafamostat mesilate may contribute major beneficial effects toward conservation of blood during CPB and prevention of coagulopathy after CPB.
Keywords: nafamstat mesilate; proteinase inhibitor; adult; aged; article; biocompatibility; blood storage; cardiopulmonary bypass; clinical article; clinical trial; controlled clinical trial; controlled study; coronary artery bypass graft; female; fibrinolysis; foreign body; human; human cell; male; priority journal; randomized controlled trial; fut 175

The retained surgical sponge - William Kaiser, C.; Friedman, S.; Spurling, K.P.; Slowick, T.; Kaiser, H.A. (Annals of Surgery, 1996)
Objective: A review was performed to investigate the frequency of occurrence and outcome of patients who have retained surgical sponges. Methods: Closed case records from the files of the Medical Professional Mutual Insurance Company (ProMutual, Boston, MA) involving a claim of retained surgical sponges were reviewed for a 7-year period. Results: Retained sponges occurred in 40 patients, comprising 48% of all closed claims for retained foreign bodies. A falsely correct sponge count after an abdominal procedure was documented in 76% of these claims. Ten percent of claims involved vaginal deliveries and minor non-body cavity procedures, for which no sponge count was performed. Total indemnity payments were $2,072,319, and defense costs were $572,079. In three cases, the surgeon was deemed responsible by the court despite the nursing staff's admitting liability and evidence presented that the surgeon complied completely with the standard of care. A wide range of indemnity payments was made despite a remarkable similarity of outcome in the patients studied. Conclusions: Despite the rarity of the reporting of a retained surgical sponge, this occurrence appears to be encountered more commonly than generally is appreciated. Operating teams should ensure that sponges be counted for all vaginal and any incisional procedures at risk for retaining a sponge. In addition, the surgeon should not unquestioningly accept correct count reports, but should develop the habit of performing a brief but thorough routine postprocedure wound/body cavity exploration before wound closure. The strikingly similar outcome for most patients would argue for a standardized indemnity payment being made without the need for adversarial legal procedures.
Keywords: abdominal surgery; article; foreign body; incidence; law suit; legal liability; medicolegal aspect; priority journal; sponge

Otology through the ages. - Pappas, D.G. (Otolaryngology--head and neck surgery : official journal of American Academy of Otolaryngology-Head and Neck Surgery, 1996)
Recounted are some, not all, of the most significant contributions to otology. The history of otology has, for the most part, followed the history of medicine: Little was known of otology by the ancient physicians, but their work must be reviewed to appreciate the progress that has been made. Most of the otology produced during the Middle Ages was limited to those structures that were readily accessible; otologic surgery was confined to trauma and removal of foreign bodies from the external auditory canals. Examination of the ear began after studies of the ear by Italian anatomists during the seventeenth century. It was not until the end of the eighteenth century that magnification was used so that the minute anatomic details could be observed. The clinical specialty of otology started in France (1850s), emerged as a scientific specialty in England, and received explosive progress from the German-speaking countries at the end of the nineteenth century. Otology has a remarkable background.
Keywords: art; article; ear; ear disease; Europe; foreign body; histology; history; human; injury; otorhinolaryngology

Debridement of bacterial and particulate-contaminated wounds - McDonald, W.S.; Nichter, L.S. (Annals of Plastic Surgery, 1994)
Debridement of contaminated wounds is an essential component of uncomplicated wound healing. Efficient techniques should be capable of removing bacteria as well as foreign matter because of the well-known ability of foreign bodies to potentiate infection. We have compared the ability of current debridement techniques with the relatively new ultrasound debridement to clean wounds contaminated with bacteria and particulate matter. In part I, we prepared dorsal wounds on 15 Sprague-Dawley rats, and 20 mg of Montmorillonite clay soil fraction, a well-known infection-potentiating factor, was placed in each wound. Animals were randomly assigned to one of three treatment groups: ultrasound debridement, soaking, and irrigation. The amount of clay removed from each wound was measured. In part II, 48 Sprague- Dawley rats were given a standard wound and inoculated with a subinfective dose of Staphylococcus aureus bacteria and 10 mg of Montmorillonite clay particles. Each rat was randomly assigned to a debridement technique-soaking, scrubbing, high-pressure irrigation, and ultrasound-and was examined after 7 days for inflammatory responses. Results of part I demonstrated that ultrasound debridement and irrigation remove statistically equal amounts of clay (p < 0.05). In part II, we found that high-pressure irrigation and ultrasound debridement effectively treat contaminated wounds (gross infection, p < 0.05; wound induration, p < 0.0001; bacteria counts, p < 0.002). This study presents ultrasound debridement as effective treatment of contaminated wounds.
Keywords: animal experiment; animal model; animal tissue; article; bacterium contamination; clay; debridement; foreign body; human; inflammation; particulate matter; priority journal; rat; surgical technique; wound closure; wound drainage; wound healing; wound infection; wound irrigation

Nurses' vs surgeons' responsibility for sponge counts. - Zuffoletto, J.M. (AORN journal, 1993)
Keywords: article; female; human; legal aspect; legal liability; malpractice; operating room personnel; surgery; surgical sponge; United States

Nurse and the law. Relying on the count. - Langslow, A. (The Australian nurses' journal, 1992)
Keywords: article; case report; cesarean section; cholecystectomy; female; foreign body; human; legal aspect; male; malpractice; medical staff; nursing staff; pregnancy; United States; uterine tube sterilization

Complications and demographic characteristics of patients undergoing lumbar discectomy in community hospitals - Ramirez, L.F.; Thisted, R.; Sypert, G.W.; Horwitz, N. (Neurosurgery, 1989)
We determined the incidence of acute, major complications in a population of 28,395 patients who underwent lumbar laminectomy for discogenic radiculopathy in the United States in 1980. This population was drawn from a broad cross-section of community hospital and represented 31% of all patients who underwent laminectomy that year for this condition. Our cohort excluded patients with a) operations exceeding two disc levels, b) fusion, c) previous lumbar laminectomy, or d) coexistent discitis, spondylosis, spinal stenosis, myelopathy, or arachnoiditis. The incidence of death was 5.9 per 10,000. The causes of death were septicemia, myocardial infarction, and pulmonary embolus. The incidence of at least one major complication was 157 per 10,000. The incidences of specific complications were as follows: infection requiring intravenously administered antibiotics, 30.7; major neurological deficit, 29.8; pulmonary embolus, 10.7; and myocardial infarction, 5.6. We studied four additional categories of complication. Patients were counted only when a second operation was required to treat the complication. The categories and incidence per 10,000 were as follows: incisional hematoma, 8.7; cerebrospinal fluid fistula, 10.5; ventral perforation, 1.6; and retention of a foreign body, 0.7. Among the patients whose hospitalizations were otherwise normal, 6.7% received a blood transfusion; of the patients whose hospitalizations were complicated, 24% required transfusion. The demographic characteristics of patients with a normal hospitalization were tabulated separately from those whose hospitalizations were complicated. Neurosurgeons performed 60% of the operations, and orthopedic surgeons performed 40%. The speciality of the surgeon was not a factor in determining the risk involved in surgery. Spinal anesthesia was used in 7% of the cases, and no pattern of complications emerged that was uniquely related to that technique.
Keywords: adult; aged; congestive heart failure; education; heart infarction; human; discectomy; lung embolism; major clinical study; mortality; priority journal; septicemia; side effect

Differentiation of aseptic and bacterial meningitis in postoperative neurosurgical patients - Ross, D.; Rosegay, H.; Pons, V. (Journal of Neurosurgery, 1988)
The differentiation of bacterial from aseptic meningitis in postoperative neurosurgical patients has traditionally been based on the clinical setting, a recent history of steroid administration, and cerebrospinal fluid (CSF) studies, including the total and differential leukocyte counts, Gram stain, glucose, and total protein. Recent reports questioning both the validity of a relative CSF lymphocytosis in excluding bacterial meningitis and the usefulness of standard CSF testing prompted the authors to reevaluate these standard criteria. The type of operation, the presence of a foreign body, use of steroids, postoperative day on which symptoms developed, altered mental status, neck stiffness, headache, and nausea were not helpful in the differential diagnosis. High fever, new neurological deficits, and active CSF leak, and elevated leukocyte counts in the CSF and peripheral blood favored a bacterial etiology. The CSF glucose level and the differential leukocyte count were less helpful. No criterion or combination of criteria was sensitive and specific enough to reliably differentiate aseptic from bacterial meningitis in the majority of patients. The possibility of improving diagnostic accuracy with newer tests, such as CSF lactate, ferritin, total amino acids, C-reactive protein, and amyloid-A, should be assessed.
Keywords: aseptic meningitis; bacterial meningitis; brain surgery; clinical article; complication; Haemophilus influenzae; human; priority journal; Staphylococcus aureus

Current concepts in the management of infections in bones and joints - Dickie, A.S. (Drugs, 1986)
Significant changes have taken place in the epidemiology, microbiology and antibiotic therapy of bone and joint infections. Gram-negative bacilli have become an increasingly common cause, particularly in immunocompromised patients; anaerobes have been implicated in osteomyelitis with metallic foreign bodies; and there is increasing use of oral antibiotic regimens following an initial period of parenteral treatment. Gram-negative bacilli and anaerobes are found in polymicrobial non-haematogenous osteomyelitis (e.g. post-traumatic, post-surgical), but Staphylococcus aureus remains the most common cause of acute haematogenous osteomyelitis, with streptococci and Haemophilus influenzae responsible for most of the remainder. A precise microbiological diagnosis is essential. Diagnosis is based on Gram stain and culture of bone biopsies or aspirated pus, or on blood cultures. Specimens should be obtained before starting therapy. Any suspected primary foci of infection should be cultured. Parenteral antibiotics are given as soon as specimens are obtained, and continued for at least 3 weeks. The common causative organisms in septic arthritis are the same as in osteomyelitis, with the addition of Neisseria gonorrhoeae in young, sexually active adults. As in osteomyelitis, a precise microbiological diagnosis is of paramount importance, ideally by joint aspiration for cell count, Gram stain, biochemical analysis and culture, or by blood cultures. Optimum therapy is with antibiotics, repeated therapeutic aspirations, and resting the joint. Parenteral antibiotics should be started as soon as specimens are obtained and continued for 4 to 6 weeks. Gonococcal arthritis, however, can be treated successfully with 1 week of antibiotics. When treatment of either osteomyelitis or septic arthritis is continued with oral antibiotics, serum antibiotic concentrations or serum bactericidal levels are mandatory to ensure adequate absorption.
Keywords: ampicillin; antibiotic agent; cefalotin; cefazolin; cefotaxime; cefoxitin; ceftriaxone; cefuroxime; chloramphenicol; clindamycin; cloxacillin; doxycycline; erythromycin; flucloxacillin; fusidic acid; metronidazole; penicillin G; piperacillin; rifampicin; ticarcillin; vancomycin; arthritis; bone; bone infection; clinical article; diagnosis; drug blood level; drug dose; drug efficacy; drug indication; drug therapy; Gram negative bacterium; human; intravenous drug administration; joint; oral drug administration; osteomyelitis; priority journal; survey; therapy

Doctors, nurses and "sponge counts". - Tammelleo, A.D. (The Regan report on nursing law, 1986)
Keywords: article; case report; cesarean section; female; foreign body; human; legal aspect; male; malpractice; newborn; operating room personnel; pregnancy; surgery; surgical equipment; United States

Incorrect counts; surgeon's negligence does not absolve nurses from liability. - Murphy, E.K. (AORN journal, 1986)
Keywords: adult; aged; article; case report; female; foreign body; human; legal aspect; male; malpractice; operating room personnel; pregnancy; surgery; surgical equipment

Evaluation of Pulsating Jet lavage in prevention of surgical wound infection - Lopez, V.; Yague Perez, S.; Llamas Zuniga, P.; Perez Trallero, E. (Journal of Abdominal Surgery, 1984)
Irrigation under pressure of contaminated surgical wounds causes the elimination of bacteria and foreign bodies from the wound. The Pulsating-Jet as an irrigation device, especially under high pressure, represents a useful method for the prevention of wound infections. In this study, the authors evaluate the results in 95 patients with purulent peritonitis who were subdivided in four groups: (a) Control, (b) Manual irrigation, (c) Pressure irrigation at 50 lbs/square inch, (d) Pressure irrigation at 70 lbs/square inch. In groups b, c, and d, semiquantitative evaluation of bacterial contamination was done before and after irrigation. The evaluation of the results was based on the percentage decrease in the bacterial counts after irrigation, the severity of the wound infection and the patients' morbidity understood as number of postoperative hospital days. The results show, with statistical significance, that manual irrigation is not effective when compared to Pulsating-Jet irrigation, especially at high pressures. The usage of of this irrigating method at high pressures and flows entails a reduction of the bacterial count and of the surgical wound infection rate and thus, shortens the postoperative hospital stay.
Keywords: abdominal lavage; clinical article; diagnosis; human; infection prevention; lavage; peritoneum; purulent peritonitis; therapy; wound; wound infection

Transsacral approach to repair of rectal prolapse in children - Chino, E.S.; Thomas Jr., C.G. (American Surgeon, 1984)
Rectal prolapse is not uncommon in the pediatric age group. Occurring more frequently in boys than girls and most often during the period of toilet training, the condition is usually self-limited. Treatment typically consists of nonoperative measures. There are patients, however, in whom operative intervention becomes necessary. Operative procedures described are based largely on adult experience and the most common repairs involve the use of a foreign body (Ripstein procedure) or colonic resection. These procedures are of considerable magnitude and may be attended by significant morbidity. As a result, there is reluctance to apply these techniques in children. There exists, then, a place for an efficacious method of repair for large prolapses that incurs minimal morbidity. This report recounts our experience with the treatment of four children with rectal prolapse using a transsacral rectopexy. The results indicate minimal perioperative morbidity, discharge within a few days, with the mechanisms of fecal continence being preserved. The longest follow-up is 17 years with a mean follow-up of 9 years. The overall treatment of rectal prolapse in children is reviewed with specific emphasis upon the indications for and technique of the transsacral approach.
Keywords: case report; child; continence; epidemiology; human; large intestine; methodology; morbidity; proctopexy; rectum prolapse; therapy

Perforation of the oesophagus. A comparison between surgical and conservative treatment - Erwall, C.; Ejerblad, S.; Lindholm, C.E.; Aberg, T. (Acta Oto-Laryngologica, 1984)
A series of 48 patients with oesophageal perforations was reviewed retrospectively. Eighty-seven per cent of the perforations were iatrogenic. Twenty-four patients were treated conservatively; 3 of this group died. The other 24 patients were treated surgically and 4 of them died. Patients with alarming symptoms and/or a large perforation underwent operative treatment unless there were contra-indications. Retained foreign bodies after perforation, and malignancy in the perforation area, were considered as indications for operation. Conservative treatment was reserved for patients with minor tears combined with a less turbulent course. The interval between perforation and therapy was not of decisive importance for the mortality in our series. The clinical picture, which was dominated by chest pain, gave the earliest indication of perforation, while the responses of the sedimentation rate, temperature and white blood count occurred later and were less reliable diagnostic signs.
Keywords: clinical article; esophagus; esophagus perforation; human; injury; surgery; therapy

Wound contamination. Assessment, prevention, and management - Georgiade, G.S. (Postgraduate Medicine, 1983)
The history of a wound and its clinical appearance help the clinician make appropriate decisions on management. The level of contamination in the wound can be determined with the rapid biopsy fixation technique. Extensive wound debridement, high-pressure irrigation, and cautious use of antibiotics should reduce the bacterial count to a level that allows primary healing. The use of sutures of appropriate chemical and physical characteristics should minimize suture contribution to the development of wound infection. Coverage of the wound after closure protects it from external contaminants and allows for completion of epithelialization. Immobilization and, if possible, elevation of the wounded part decrease secondary edema formation.
Keywords: polyethylene terephthalate; lidocaine; polyglycolic acid; diagnosis; drug therapy; foreign body; human; short survey; therapy; wound infection; wound irrigation; xylocaine

Legal case briefs for nurses. IN: Pediatrics: pre-discharge injury; ME: Surgery: sponge count error. - Regan, W.A. (The Regan report on nursing law, 1982)
Keywords: article; case report; female; femur fracture; foreign body; human; hysterectomy; malpractice; newborn; newborn disease; surgical equipment; United States

Natural history of the retained surgical sponge. - Hyslop, J.W.; Maull, K.I. (Southern medical journal, 1982)
Retained surgical sponge is an infrequently reported condition that may be recognized incidentally during the early postoperative period, produce serious complications, or remain dormant for years. Clinical manifestations of the retained surgical sponge are a function of bacterial contamination and of the location of the sponge within the body cavity. Few sequelae follow external extrusion but internal erosion may lead to abscess, fistulas, and intestinal obstruction. Prevention requires constant sensitivity of the surgeon to this potential threat to the safe practice of surgery. The surgeon must account for an incorrect sponge count by adequate examination of the operative field and by roentgenographic studies when the issue remains in doubt. A correct sponge count does not fully preclude a retained sponge, however, and inspection of the operative field should be routine in all patients at risk.
Keywords: abdominal radiography; article; bacterial infection; case report; female; human; intestine obstruction; male; malpractice; middle aged; peroperative complication; surgery; surgical equipment

Percutaneous nephrostomy: Techniques, indications, and results - Stables, D.P. (Urologic Clinics of North America, 1982)
Percutaneous nephrostomy has come a long way in the 27 years since Goodwin et al. devised the procedure as a natural extension of the then-new technique of antegrade pyelography. Our own experience and a review of percutaneous nephrostomy, published in 1978, yielded reports of only 516 such procedures through March of 1977, most of which had been performed during the preceding five years. Since then, the literature on percutaneous nephrostomy and related techniques has exploded, and the number of procedures performed is beyond count. Percutaneous nephrostomy is no longer merely an end in itself but also a convenient access to the upper urinary tract for insertion of ureteral stents; dissolution, extrusion, or extraction of calculi; closure of fistulas; administration of drugs; extraction of foreign bodies; insertion of brush biopsy instruments and nephroscopes; and the performance of ureteral meatotomy. These exciting spin-offs of percutaneous nephrostomy are described elsewhere in this symposium. This article reviews the status of percutaneous nephrostomy, and represents a synthesis of the literature and personal experience.
Keywords: diagnosis; kidney; methodology; nephrostomy; review; therapy

Management of the contaminated wound - Edlich, R.F.; Rodeheaver, G.T.; Stevenson, T.R. (COMPR.THER., 1977)
Traumatic wounds are always contaminated by bacteria, soil, and other foreign bodies. There is a delicate balance between the deleterious effects of the contaminants and the resistance of the host wound to infection. Successful management of the contaminated wound must include cleansing techniques that remove these contaminants while inflicting minimal injury to the tissue. The number of residual bacteria in the wound after cleansing is a critical determinant of infection. Most traumatic wounds containing >105 bacteria/g tissue are very likely to develop infection. When the bacterial count of a wound is below this level, and after soil and devitalized tissue are removed, wound healing without infection is consistently noted in healthy patients. Fortunately, most soft tissue wounds contain <105 organisms/g tissue. Those exhibiting high levels of bacterial inoculum must be subjected to treatments that reduce the bacterial count, remove all nonvital tissue, and prevent the development of infection.
Keywords: antibiotic agent; bacterial count; debridement; major clinical study; therapy; wound infection

Management of soft tissue injury. - Edlich, R.F.; Rodeheaver, G.T.; Thacker, J.G.; Winn, H.R.; Edgerton, M.T. (Clinics in plastic surgery, 1977)
The fate of a surgical wound is held in a delicate balance between the host's resistance to infection and the causal factors of infection. Considerable insight into this relationship between the host and pathogen can be gained from the results of quantitative bacteriologic measurements. Newer rapid slide techniques have been developed which provide the surgeon with this information within 20 minutes. In most soft tissue injuries, the wound bacterial count gives an accurate prediction of subsequent infection. Wounds combining greater than 10(5) bacteria per gram of tissue are destined to develop infection. When the bacterial count is below that level, the wounds will usually heal per primam without infection. This large number of bacteria required to elicit infection reflects the remarkable ability of soft tissues to resist infection. This state of high resistance to infection can be reduced by several factors which include circulatory embarrassment, tissue injury, dead space, and the presence of foreign bodies (dirt, sutures, drains, etc.). When treating soft tissue injuries, the surgeon must employ specific therapeutic modalities that allow the wound to heal per primam without infection. On the basis of experimental studies supported by clinical experience, the following treatment protocol for soft tissue injuries is recommended. Using strict aseptic technique, the wound must be first anesthetized with 1 per cent Xylocaine to permit painless sound cleansing. All wounds should be subjected to high pressure syringe irrigation to remove bacteria, foreign bodies, and blood clots. When necessary, debridement of all devitalized tissue should be performed with a stainless steel scalpel. Many wounds caused by sharp wounding agents contain no foreign bodies and few bacteria and exhibit considerable resistance to infection. In these wounds, primary closure can be initiated after irrigation without the development of infection. Wounds resulting from impact forces have a diminished resistance to infection and are susceptible to infection by low level of bacterial contamination. Immediate antibiotic treatment of patients with impact injuries subjected to meticulous debridement and cleansing will permit a safe primary closure. In wounds contacted by pus or feces, open wound management followed by delayed primary closure is usually indicated. Antimicrobial prophylaxis is also recommended for patients with such wounds. Ideal postoperative care of all traumatic wounds includes a surgical dressing and immobilization and elevation of the site of injury.
Keywords: article; debridement; human; injury; lavage; local anesthesia; postoperative care; suture; suture technique; wound infection

Is laminar airflow necessary for prophylaxis against wound infection? - Laufman, H. (Medical Instrumentation, 1976)
Abuse of an otherwise properly installed and maintained operating room system may result in rendering the environment unsatisfactory for critical types of surgery, especially when a patient's resistance is lowered by disease or drugs, or when a large foreign body is implanted. No type of special air handling system will correct these abuses even though it may reduce ambient bioparticle counts. From all available valid evidence, the conclusion is drawn that laminar flow is less effective against wound infection than adherence to proper techniques and correction of abuses of the operating room environment by the surgical team and support personnel.
Keywords: operating room; prevention; wound infection

Fiber embolization: a hazard of cardiac surgery and catheterization - Dimmick, J.E.; Bove, K.E.; McAdams, A.J.; Benzing III, G. (New England Journal of Medicine, 1975)
Fourteen (8%) of 173 patients who had undergone cardiac operations or catheterization, or both, had fiber emboli in routine autopsy sections. All 14 patients had previous angiographic examinations; 8 had also had intracardiac operations, 3 had had extracardiac procedures such as pulmonary artery banding, and 3 patients had not been operated on. Fibers occurred most commonly in pulmonary arteries (8 cases) but were also found within renal (4 cases), cerebral (1 case) and mesenteric arteries (1 case). These fibers were readily distinguished from talc or starch. When they were found in patients who had died during or immediately after an intracardiac procedure there was no associated inflammation, and there may or may not have been thrombus. At a somewhat later stage, the fibers elicited a typical intravascular foreign body inflammatory reaction. Regardless of the type of reaction, the embolized fiber and the associated reaction often resulted in narrowing or occlusion of the vascular lumen. Fibers removed from cotton and paper materials were either straight or twisted, and many appeared to have a less birefringent central core. Cotton fibers were more homogeneously birefringent than paper fibers and were less variable in width. In the assessment of materials used in the operating room, the number of fibers trapped by the membrane filter was determined and graded as follows: 1+ (zero to 15); 2+ (16 to 30); 3+ (31 to 45); and 4+ (46 and greater). All drapes, gowns, caps, masks and sponges tested, whether cotton or paper, readily shed fibers upon agitation (3+ or 4+). There was no difference in shedding qualities between cotton and disposable paper. No difference in fiber count was found between control specimens (1+) and the saline wash from the pump oxygenator (1+). The presence of small numbers of fibers entrapped by the filter membrane from all control specimens was attributed to contamination by airborne fibers.
Keywords: artery embolism; autopsy; brain embolism; catheterization; diagnosis; embolism; fiber; foreign body; heart catheterization; heart surgery; histology; kidney artery embolism; legal aspect; lung embolism; major clinical study; mesenteric artery; paper; therapy

Starch granulomatous peritonitis - Ehrlich, C.E.; Wharton, J.T.; Gallager, H.S. (Southern Medical Journal, 1974)
Two cases of starch granulomatous peritonitis, one symptomatic and one asymptomatic, are presented. Although starch glove powder is usually innocuous, the number of cases of starch peritonitis reported in the literature indicates that it is not always so. The typical syndrome consists of abdominal pain, fever, and signs of peritonitis. The leukocyte count is usually within the normal range, but sometimes eosinophilia is present. Signs and symptoms characteristically develop 10 to 40 days after an uneventful operation. The diagnosis can be confirmed by finding starch granules in the tissue and in foreign body giant cells. Reoperation may be avoided by suspecting the syndrome and searching for starch in ascitic fluid obtained by paracentesis. Therapy consists of steroids or an antiinflammatory agent such as indomethacin.
Keywords: glove powder; indometacin; starch; unclassified drug; article; ascites; clinical study; drug induced disease; drug therapy; eosinophilia; giant cell; granuloma; granulomatous peritonitis; histology; major clinical study; microscopy; oral drug administration; paracentesis; peritonitis; starch granuloma; therapy

Editorial: Medicolegal necessity for counting sharps. - Russell, J.B. (Surgery, gynecology & obstetrics, 1974)
Keywords: article; foreign body; human; malpractice; postoperative complication; surgery; surgical equipment

Survey into counting precautions in New South Wales operating theatres. - Woodcroft, R. (The Lamp, 1972)
Keywords: article; Australia; bandage; foreign body; needle; questionnaire; surgery; surgical equipment

Recording of fetal electrocardiogram by means of intrauterine transmitter (japanese) - Tazawa, H. (Japanese journal of medical electronics and biological engineering, 1968)
The fetal heart rate is one of the best indicators of the fetal status during labor. The heart rate is counted by means of the fetal ECG (FECG) obtained from the maternal abdominal wall or a direct ECG from the fetal scalp after rupture of the amnionic sac. However, these methods are not satisfactory by reason of poor signal-to-noise ratio, difficulty in continuous monitoring, and so on. Accordingly, radiotelemetry was employed for measurement of fetal heart rate (FHR), an adequate size transmitter combined with electrodes being inserted into the uterine space. The direct FECG was transmitted throughout all stages of labor and was received by a commercial short-wave radio receiver placed near by. The ECG of the newborn baby was also taken from the axilla with ease by a clip electrode-transmitter consisting of a clip electrode for adult limb leads and a smaller trans-mitter. The carrier frequency was chosen at about 6 Mc/s and the amplitude was modulated by the signal. The size and the form of the transmitter were arranged to allow easy insertion into the uterine space, complete contact with the amnionic sac and easy exchange of the battery, while not behaving as a foreign body and not being exhausted by delivery. After construction in the form of a printed circuit, the transmitter enclosed in a mold of silicon rubber to prevent injury to the body and to ensure insulation from the tissues. The total weight and volume were 15 g and 9 cm3, respectively. Drain current was 200 ìÁwith a receiving range of about 1.5 meter. ECGs of 6 fetuses including 3 cases of cesarean section were investigated throughout labor and delivery. Especially interesting results were obtained when FHRs were registered before and after rupture of the amnionic sac, labor, delivery and ligation of the umbilical cord and during cesarean section. (27, 2A).
Keywords: silastic; abdominal wall; adult; axilla; baby; cesarean section; clip; electrocardiogram; electrode; electroencephalogram; electromyogram; fetus; fetus electrocardiography; fetus heart rate; foreign body; heart rate; injury; Japanese (people); ligation; limb; monitoring; newborn; recording; rupture; scalp; signal noise ratio; telemetry; tissues; umbilical cord; uterine cervix; uterus; weight

Foreign body in the genio-glossus - Khan, A.A.; Huq, M. (Journal of Laryngology, 1968)
The case reported presented as an acute phase of chronic' respiratory symptoms with high leukocyte count and no history suggesting the presence of a foreign body. Investigation revealed a safety pin lodged at a very unusual site in the substance of the tongue and a large retropharyngeal abscess. Evidence suggested that the pin had been present there for 2 yr. Technical difficulties faced in localizing and removing the foreign body at operation are described. The authors have not found a reference of a foreign body lodged at this site.
Keywords: foreign body; leukocyte count; retropharyngeal abscess; safety; tongue

Statistic observation on pseudomonas corneal ulcer - Mikuni, M.; Oiehi, M.; Suda, S.; Imai, M.; Takahashi, T. (Acta Soc.Ophthal. Jap., 1967)
The number of patients with pseudomonas corneal ulcer was 135 out of 397, 380 cases in 21 eye departments during the period from Jan. 1961 to Sept. 1966. The incidence of the disease increased from 1964. The greatest number of patients was found in the age class 21-30 yr and much more in males than females. The rate of incidence was prevalent in August. The infection was caused much more frequently after removal of foreign bodies from the cornea, and almost all of them were caused by iron filings during grinding. Pseudomonas aeruginosa isolated from patients was most sensitive to polymyxin-B, colistin, and then SM, TC and FM. The disease was treated by colistin and CP. These were used frequently locally as well as systemically. SM, TC, KM and FM were employed too. Better visuel acuities (more than 0.5) were obtained frequently in cases treated within 3 days alter the onset of the infection, while poor visual acuities (less than finger counting) were attained in cases treated within more than 7 days and almost all were subjected to enucleation. Therefore, it. seems to be most important to treat as promptly as possible and with the most effective antibiotics.
Keywords: antibiotic agent; colistin; iron; polymyxin B; cornea; cornea ulcer; documentation; enucleation; eye; female; foreign body; grinding; infection; male; patient; Pseudomonas; Pseudomonas aeruginosa; visual acuity

THE PASSAGE of RAT and FOREIGN SPERMATOZOA THROUGH THE UTEROTUBAL JUNCTlONOF THE RAT - Marcus, S.L. (Amer.J.Obstet. Gynec., 1965)
There is abundant evidence that migration of spermatozoa through the female genital tract is not due to sperm mot il it y alone. This study was designed to test the role of peristalsis in the reproductive system of the rat by recording the passage of nonmotile rat and foreign spermatozoa through the uterotubal junction, and the effect of an int r a uterine foreign body on this function. Samples of nonmotile rat, guinea-pig, and human sperms were counted, suspended in Ringer's solution and inseminated into the uterine horns of albino rats after cervical ligation. These comprised 4 groups • the 1st exposed to rat, and the 2nd to foreign spermatozoa, the 3rd with different sperms in each horn, and the 4th after intraluminal insertion of a number 5O silk suture knot. Insemination by laparotomy was done in the estrus phase according to vaginal smears. One to 12 hr. later the oviduct was excised and the contents examined for spermatozoa. Both nonmotile rat and foreign sperms were found to have passed the uterotubal junction, and this occurred as well in some animals in whom the cervix had not been ligated. The presence of the intraluminal foreign body, which has been shown to be a contraceptive in the rat, did not prevent the passage of nonmotile guinea-pig, rat or human sperms into the oviduct. The motility of spermatozoa is not a prerequisite of their passage into the rat oviduct. Sturgis Boston, Mass. (X, 2a,3).
Keywords: contraceptive agent; Ringer solution; albinism; artificial insemination; bullet; estrus; female genital system; foreign body; genital system; guinea pig; horn; human; laparotomy; ligation; oviduct; peristalsis; rat; recording; silk; sperm; spermatozoon; suture; United States; uterus; uterus horn; vagina smear

Unusual corneal foreign body - True, W.R. (United States Armed Forces medical journal, 1951)
A man aged 22 was awakened by sharp, stabbing pains in the left eye, whereupon he discovered a 5 in. long scorpion lying across the eye and temporal area. The arachnid was brushed off and destroyed. The eye became red and throbbed with continuous pain. The eyelids swelled and vision was blurred within 1 hour; lacrimation and photophobia were marked. Emergency treatment consisted of 50 mg. of diphenhydramine hydrochloride, orally q.i.d., warm compresses every 2 hours, and the instillation of penicillin ophthalmic ointment in the conjunctival sac. Examination 3 days later by an ophthalmologist showed vision to be decreased to finger count at 3 feet, ciliary injection, punctate keratitis, and iritis. Slit-lamp microscopy revealed mild oedema of the entire cornea. A needle-like shaft about 3 mm. long was embedded horizontally deep in the substantia propria of the cornea. A slight reaction was noted about this shaft. No staining with fluorescein. Several minute punctate lesions were seen on the epithelial surface of the cornea. There was a slight flare in the anterior chamber but no cells were noted. The iris, vitreous, and fundus were normal. The foreign body was invisible to the naked eye. Under 0.5% pontocaine topical anaesthesia the foreign body was extracted using a small Graefe knife and forceps with the aid of slit-lamp visualization. Because of its friability it was removed in 4 separate pieces. The base was cleaned with a small dental burr. The eye was dressed with an ointment containing 0.1% aureomycin and 1% atropine. Cortisone solution (1:4 dilution) was instilled into the eye every 2 hours. The anti-histaminics were continued. The cornea was completely healed without scarring and the iritis had resolved within 6 days. Microscopic examination of the foreign body revealed a minute, tapering, thin shaft without segmentation. This was assumed to be the tail-tip of the scorpion.
Keywords: atropine; chlortetracycline; cortisone; diphenhydramine; eye ointment; fluorescein; penicillin G; tetracaine; aged; anesthesia; anterior eye chamber; arachnid; cornea; dilution; drill; edema; emergency treatment; examination; eye; eyelid; forceps; foreign body; human; injection; injury; iris; iritis; lacrimation; microscopy; needle; ointment; pain; photophobia; punctate keratitis; recumbency; scar formation; scorpion; slit lamp; staining; tail; vitreous body

A case of pyocyaneus ring abscess of the cornea treated with streptomycin - Maschler, J. (British Journal of Ophthalmology, 1948)
Three days after extraction of a foreign body from the centre of the right cornea a 15-year-old boy showed an acute ring abscess with a greenish hypopyon. The strain was sensitive to streptomycin (1:500). Treatment was (after a short trial of penicillin) with intramuscular streptomycin (three-hourly) instillation, subconjunctival injection and introduction into anterior chamber (1.0 Gm streptomycin in all). Corneal Saemisch's section was performed. Healing resulted. After iridectomy ab externo finger counting was possible.
Keywords: penicillin G; streptomycin; abscess; anterior eye chamber; boy; cornea; extraction; foreign body; healing; hypopyon; iridectomy; subconjunctival drug administration

Cyst of the iris - Lewis, P.M. (American Journal of Ophthalmology, 1947)
Eight years after a penetrating steel foreign body had been removed from the eye of a 26-year-old male a glaucoma developed. A cataract and a large iris cyst was discovered. Following intracapsular lens extraction and secondary removal of the iris cyst by keratome-scissors incision, the eye remained comfortable with unconnected vision of finger-counting at three feet.
Keywords: steel; cataract; cyst; extraction; eye; foreign body; glaucoma; incision; iris; iris atrophy; lens; male

An analysis of 100 consecutive operations on the knee and a report on a xanthoma of the knee-joint - Marsden, C.M. (Journal of the Royal Army Medical Corps, 1947)
Of 100 consecutive operations on the knee 90 were for meniscal lesions, 69 of them affecting the medial cartilage. Five normal menisci were removed and in three of these cases relief was obtained. In the other two the lateral menisci were found to be torn and were removed afterwards. One case had both menisci torn and both were removed; another had 'discoid' medial cartilages removed from both knees at one sitting. An arthrography was used once and enabled a diagnosis of a bucket-handle tear of the lateral meniscus to be made. Five cysts of the menisci, one medial and four lateral, were removed. Once a pedunculated xanthoma was removed from the intercondyloid notch. This was examined and stated to be a benign histiocytoma. A Michel clip was removed from the knee joint in one case whose primary operation had been performed in another hospital. It is interesting that this author too uses clips, and now they are counted in the same way as abdominal swabs.
Keywords: furosemide; arthrography; cartilage; clip; cyst; diagnosis; foreign body; histiocytoma; hospital; knee; knee meniscus; knee meniscus rupture; lacrimal fluid; sitting; xanthoma

Perforation of the esophagus not caused by instrumentation. Review of eight cases - Engler, C.W. (Annals of Otology, Rhinology and Laryngology, 1946)
Report on eight cases of perforation of the oesophagus. Contrary to the opinion regarding carcinoma as the most frequent cause (Holinger, McGibbon and Mather) six of these cases were due to foreign bodies, one to a caustic burn and one to syphilis, the last-named being an exceptional case. In two cases of injury due to foreign bodies (pieces of bone) conservative treatment without chemotherapeutical agents was successful, although there was roentgenographic and endoscopic proof of perforation. The author further agrees with Holinger that the mediastinum must be opened by operation and drained if there are signs of progressive infection. A rise in the leucocytic count of the blood to 18,000 or more is regarded as particularly valuable in providing an indication for this treatment, a view which is supported by the cases described. The perforation of the oesophagus caused by caustic burning and by syphilis led to the formation of broncho-oesophageal fistulae. Both these patients died, one through subsequent suicide and one from bilateral bronchopneumonia, whilst a third succumbed to a fulminating sepsis (Holinger's classification) in spite of posterior and anterior mediastinotomy. The latter case gives rise to the question whether external removal of the foreign body with simultaneous drainage of the mediastinum should not be employed. Perforation of the pleura and formation of empyema can necessitate major surgical procedures and cause illness over a period of years. The diagnostic importance of the displacement of the oesophagus and widening of the mediastinal shadow seen in the roentgenogram are mentioned.
Keywords: caustic agent; blood; bone; bronchopneumonia; carcinoma; caustic burn; classification; conservative treatment; diagnosis; empyema; esophagus; esophagus fistula; esophagus perforation; foreign body; general aspects of disease; infection; injury; devices; mediastinum; patient; perforation; pleura; sepsis; suicide; surgical technique; syphilis; X ray picture

Lesions found in traumatic chest - Hodson, C. (British Journal of Radiology, 1945)
This paper deals with the author's war-time experience of traumatic lesions of the chest, with particular reference to missile tracts and extra-pleural haematomata. He emphasizes that in the majority of cases in which these lesions occur they are ill-defined radiologically and difficult to visualize on the film, as both missile tracts and extra-pleural haematomata are frequently obscured by concomitant pleural effusion or pulmonary collapse. Missile tracts are divided into 'solid' and 'air-containing', and clinical descriptions of both types are given accompanied by illustrative examples from a series of X-ray films. The percentage incidence of these lesions has not yet been worked out accurately, but a rough count of 500 cases of penetrating wounds of the chest shows radiologically recognizable lesions as follows: solid tracts 10 per cent, air-containing tracts 2 per cent. The lipiodol investigation of these tracts follows the same general lines as for sinuses and fistulae elsewhere in the body, but the value of screen examination of the lipiodol-filled tract is emphasized, with careful observation during the act of coughing in order to demonstrate any possible connection with a bronchus. Extra-pleural haematomata derive their importance from the fact that if adequately demonstrated radiologically, treatment can usually be effected without involving what may well be a normal pleural cavity. Thus when, as is often the case, they contain bone fragments, metallic foreign bodies, or are infected, all necessary surgical treatment can be carried out without opening the pleura, a performance that calls for careful radiological localisation of the lesion as an essential preliminary. The author in his series estimates the percentage incidence of extra-pleural haematomata at 1 per cent.
Keywords: iodinated poppyseed oil; bone; bronchus; coughing; examination; fistula; foreign body; injury; atelectasis; neuropathic joint disease; penetrating trauma; pleura; pleura cavity; pleura effusion; solid; surgery; thorax; war; X ray film